African Ancestry Individuals with Higher Educational Attainment Are Resilient to Alzheimer's Disease Measured by pTau181. - Rajabli, Farid; Seixas, Azizi A; Akgun, Bilcag; Adams, Larry D; Inciute, Jovita; Hamilton, Kara L; Whithead, Patrice G; Konidari, Ioanna; Gu, Tianjie; Arvizu, Jamie; Golightly, Charles G; Starks, Takiyah D; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive and functional abilities in individuals with Alzheimer's disease (AD) pathology (ADP) are highly variable. Factors contributing to this variability are not well understood. Previous research indicates that higher educational attainment (EA) correlates with reduced cognitive impairments among those with ADP. While cognitive and functional impairments are correlated, they are distinguishable in their manifestations. OBJECTIVE: To investigate whether levels of education are associated with functional impairments among those with ADP. METHODS: This research involved 410 African American (AA) individuals (Institutional Review Boards 20070307, 01/27/2023) to ascertain whether EA correlates with functional resilience and if this effect varies between APOE ɛ4 carriers and non-carriers. Utilizing EA as a cognitive reserve proxy, CDR-FUNC as a functional difficulties measure, and blood pTau181 as an ADP proxy, the non-parametric Mann-Whitney U test assessed the relationship between EA and CDR-FUNC in individuals with advanced pTau181 levels. RESULTS: The results showed that EA correlated with functional difficulties in AA individuals with high levels of pTau181, such that individuals with high EA are more likely to have better functional ability compared to those with lower EA (W = 730.5, p = 0.0007). Additionally, we found that the effect of high EA on functional resilience was stronger in ɛ4 non-carriers compared to ɛ4 carriers (W = 555.5, p = 0.022). CONCLUSION: This study extends the role of cognitive reserve and EA to functional performance showing that cognitive reserve influences the association between ADP burden and functional difficulties. Interestingly, this protective effect seems less pronounced in carriers of the strong genetic risk allele ɛ4.
Keywords: Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Educational Status; Humans; Resilience, Psychological

Alzheimer's Disease and Cognitive Decline in Patients with Cardiovascular Diseases Along the Heart-Brain Axis. - Trieu, Calvin; Van Harten, Argonde C; Leeuwis, Anna E; Exalto, Lieza G; Hooghiemstra, Astrid M; Verberk, Inge M W; Allaart, Cor P; Brunner-La Rocca, Hans-Peter; Kappelle, L Jaap; van Oostenbrugge, Robert J; Biessels, Geert-Jan; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2024)
BACKGROUND: We hypothesize that Alzheimer's disease (AD)-related pathology may accelerate cognitive decline in patients with cardiovascular diseases. OBJECTIVE: To investigate the association between blood-based biomarkers of AD, astrocyte activation, and neurodegeneration and cognitive decline. METHODS: From the multi-center Heart-Brain study, we included 412 patients with heart failure, carotid occlusive disease or vascular cognitive impairment (age:68.6±9.0) and 128 reference participants (65.7±7.5). Baseline amyloid-β42/40 (Aβ42/40), phosphorylated-tau181 (pTau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) were determined using SiMoA (Quanterix). Memory, attention, language, and executive functioning were evaluated (follow-up:2.1±0.3 years). We applied linear mixed models with terms for biomarker, time and biomarker*time interactions, adjusted for age, sex, education, and site, to assess associations between biomarkers and cognitive decline. RESULTS: Among patients, Aβ42/40 was not associated with cognitive performance at baseline. However, lower Aβ42/40 was associated with steeper decline in global cognition (β±SE:0.04±0.02). Higher pTau181 was associated with worse baseline performance on global cognition (-0.14±0.04) and memory (-0.31±0.09) and with steeper decline in global cognition (-0.07±0.02), memory (-0.09±0.04), attention (-0.05±0.02), and language (-0.10±0.03). Higher GFAP was associated with worse baseline performance on global cognition (-0.22±0.05), memory (-0.43±0.10), attention (-0.14±0.06), language (-0.15±0.05), and executive functioning (-0.15±0.05) and steeper decline in global cognition (-0.05±0.01). Higher NfL was associated with worse baseline performance on global cognition (-0.16±0.04), memory (-0.28±0.09), attention (-0.20±0.06), and executive functioning (-0.10±0.04), but was not associated with performance over time. In reference participants, no associations were found. CONCLUSIONS: Our findings suggest that blood-based biomarkers of AD-related pathology predict cognitive decline in patients with cardiovascular diseases.

Comprehensive Analysis of Metabolites in Postmortem Brains of Patients with Alzheimer's Disease. - Kurano, Makoto; Saito, Yuko; Yatomi, Yutaka (J Alzheimers Dis, 2024)
BACKGROUND: Disturbed metabolism has been proposed as being involved in the pathogenesis of Alzheimer's disease (AD), and more evidence from human AD brains is required. OBJECTIVE: In this study, we attempted to identify or confirm modulations in the levels of metabolites associated with AD in postmortem AD brains. METHODS: We performed metabolomics analyses using a gas chromatography mass spectrometry system in postmortem brains of patients with confirmed AD, patients with CERAD score B, and control subjects. RESULTS: Impaired phosphorylation of glucose and elevation of several tricarboxylic acid (TCA) metabolites, except citrate, were observed and the degree of impaired phosphorylation and elevation in the levels of the TCA cycle metabolites were negatively and positively correlated, respectively, with the clinical phenotypes of AD. The levels of uronic acid pathway metabolites were modulated in AD and correlated positively with the amyloid-β content. The associations of nucleic acid synthesis and amino acid metabolites with AD depended on the kinds of metabolites; in particular, the contents of ribose 5-phosphate, serine and glycine were negatively correlated, while those of ureidosuccinic acid and indole-3-acetic acid were positively modulated in AD. Comprehensive statistical analyses suggested that alterations in the inositol pathway were most closely associated with AD. CONCLUSIONS: The present study revealed many novel associations between metabolites and AD, suggesting that some of these might serve as novel potential therapeutic targets for AD.

Herpes Simplex Viral Infection Doubles the Risk of Dementia in a Contemporary Cohort of Older Adults: A Prospective Study. - Vestin, Erika; Boström, Gustaf; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo; Weidung, Bodil (J Alzheimers Dis, 2024)
BACKGROUND: Evidence indicates that herpes simplex virus (HSV) participates in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: We investigated AD and dementia risks according to the presence of herpesvirus antibodies in relation to anti-herpesvirus treatment and potential APOE ɛ4 carriership interaction. METHODS: This study was conducted with 1002 dementia-free 70-year-olds living in Sweden in 2001-2005 who were followed for 15 years. Serum samples were analyzed to detect anti-HSV and anti-HSV-1 immunoglobulin (Ig) G, anti-cytomegalovirus (CMV) IgG, anti-HSV IgM, and anti-HSV and anti-CMV IgG levels. Diagnoses and drug prescriptions were collected from medical records. Cox proportional-hazards regression models were applied. RESULTS: Cumulative AD and all-cause dementia incidences were 4% and 7%, respectively. Eighty-two percent of participants were anti-HSV IgG carriers, of whom 6% received anti-herpesvirus treatment. Anti-HSV IgG was associated with a more than doubled dementia risk (fully adjusted hazard ratio = 2.26, p = 0.031). No significant association was found with AD, but the hazard ratio was of the same magnitude as for dementia. Anti-HSV IgM and anti-CMV IgG prevalence, anti-herpesvirus treatment, and anti-HSV and -CMV IgG levels were not associated with AD or dementia, nor were interactions between anti-HSV IgG and APOE ɛ4 or anti-CMV IgG. Similar results were obtained for HSV-1. CONCLUSIONS: HSV (but not CMV) infection may be indicative of doubled dementia risk. The low AD incidence in this cohort may have impaired the statistical power to detect associations with AD.

Mendelian Randomization of Blood Metabolites Suggests Circulating Glutamine Protects Against Late-Onset Alzheimer's Disease. - Ramadan, Ferris A; Arani, Gayatri; Jafri, Ayan; Thompson, Tingting; Bland, Victoria L; Renquist, Benjamin; Raichlen, David A; Alexander, Gene E; Klimentidis, Yann C (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) represents a growing health burden. Previous studies suggest that blood metabolite levels influence risk of LOAD. OBJECTIVE: We used a genetics-based study design which may overcome limitations of other epidemiological studies to assess the influence of metabolite levels on LOAD risk. METHODS: We applied Mendelian randomization (MR) to evaluate bi-directional causal effects using summary statistics from the largest genome-wide association studies (GWAS) of 249 blood metabolites (n = 115,082) and GWAS of LOAD (ncase = 21,982, ncontrol = 41,944). RESULTS: MR analysis of metabolites as exposures revealed a negative association of genetically-predicted glutamine levels with LOAD (Odds Ratio (OR) = 0.83, 95% CI = 0.73, 0.92) that was consistent in multiple sensitivity analyses. We also identified a positive association of genetically-predicted free cholesterol levels in small LDL (OR = 1.79, 95% CI = 1.36, 2.22) on LOAD. Using genetically-predicted LOAD as the exposure, we identified associations with phospholipids to total lipids ratio in large LDL (OR = 0.96, 95% CI = 0.94, 0.98), but not with glutamine, suggesting that the relationship between glutamine and LOAD is unidirectional. CONCLUSIONS: Our findings support previous evidence that higher circulating levels of glutamine may be a target for protection against LOAD.

Visual Functions Are Associated with Biomarker Changes in Alzheimer's Disease. - Memon, Ashar; Moore, Jasmine A; Kang, Chris; Ismail, Zahinoor; Forkert, Nils D (J Alzheimers Dis, 2024)
BACKGROUND: While various biomarkers of Alzheimer's disease (AD) have been associated with general cognitive function, their association to visual-perceptive function across the AD spectrum warrant more attention due to its significant impact on quality of life. Thus, this study explores how AD biomarkers are associated with decline in this cognitive domain. OBJECTIVE: To explore associations between various fluid and imaging biomarkers and visual-based cognitive assessments in participants across the AD spectrum. METHODS: Data from participants (N = 1,460) in the Alzheimer's Disease Neuroimaging Initiative were analyzed, including fluid and imaging biomarkers. Along with the Mini-Mental State Examination (MMSE), three specific visual-based cognitive tests were investigated: Trail Making Test (TMT) A and TMT B, and the Boston Naming Test (BNT). Locally estimated scatterplot smoothing curves and Pearson correlation coefficients were used to examine associations. RESULTS: MMSE showed the strongest correlations with most biomarkers, followed by TMT-B. The p-tau181/Aβ1-42 ratio, along with the volume of the hippocampus and entorhinal cortex, had the strongest associations among the biomarkers. CONCLUSIONS: Several biomarkers are associated with visual processing across the disease spectrum, emphasizing their potential in assessing disease severity and contributing to progression models of visual function and cognition.

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Alzheimer's Disease: A Systems View Provides a Unifying Explanation of Its Development. - Grobler, Corlia; van Tongeren, Marvi; Gettemans, Jan; Kell, Douglas B; Pretorius, Etheresia (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a debilitating neurodegenerative disorder affecting 50 million people globally. It is characterized by the presence of extracellular senile plaques and intracellular neurofibrillary tangles, consisting of amyloid-β and hyperphosphorylated tau proteins, respectively. Despite global research efforts, there is currently no cure available, due in part to an incomplete understanding of the disease pathogenesis. Numerous possible mechanisms, or hypotheses, explaining the origins of sporadic or late-onset AD have been proposed, including the amyloid-β, inflammatory, vascular, and infectious hypotheses. However, despite ample evidence, the failure of multiple trial drugs at the clinical stage illuminates the possible pitfalls of these hypotheses. Systems biology is a strategy which aims to elucidate the interactions between parts of a whole. Using this approach, the current paper shows how the four previously mentioned hypotheses of AD pathogenesis can be intricately connected. This approach allows for seemingly contradictory evidence to be unified in a system-focused explanation of sporadic AD development. Within this view, it is seen that infectious agents, such as P. gingivalis, may play a central role. The data presented here shows that when present, P. gingivalis or its virulence factors, such as gingipains, may induce or exacerbate pathologies underlying sporadic AD. This evidence supports the view that infectious agents, and specifically P. gingivalis, may be suitable treatment targets in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Plaque, Amyloid; tau Proteins

Alzheimer's Disease Pathology Outside of the Cerebrum Is Related to a Higher Odds of Dementia. - Buchman, Aron S; Leurgans, Sue E; Kim, Namhee; Agrawal, Sonal; Oveisgharan, Shahram; Zammit, Andrea R; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2023)
BACKGROUND: Assessments of Alzheimer's disease pathology do not routinely include lower brainstem, olfactory bulb, and spinal cord. OBJECTIVE: Test if amyloid-β (Aβ) and paired helical filament (PHF) tau-tangles outside the cerebrum are associated with the odds of dementia. METHODS: Autopsies were obtained in decedents with cognitive testing (n = 300). Aβ plaques and PHF tau-tangles were assessed in 24 sites: cerebrum (n = 14), brainstem (n = 5), olfactory bulb, and four spinal cord levels. Since spinal Aβ were absent in the first 165 cases, it was not assessed in the remaining cases. RESULTS: Age at death was 91 years old. About 90% had Aβ in cerebrum and of these, half had Aβ in the brainstem. Of the latter, 85% showed Aβ in the olfactory bulb. All but one participant had tau-tangles in the cerebrum and 86% had brainstem tau-tangles. Of the latter, 80% had tau-tangles in olfactory bulb and 36% tau-tangles in one or more spinal cord levels. About 90% of adults with tau-tangles also had Aβ in one or more regions. In a logistic model controlling for demographics, Aβ and tau-tangles within the cerebrum, the presence of Aβ in olfactory bulb [OR, 1.74(1.00, 3.05)]; tau-tangles in brainstem [OR, 4.00(1.1.57,10.21)]; and spinal cord [OR, 1.87 (1.21,3.11)] were independently associated with higher odds of dementia. CONCLUSION: Regional differences in Aβ and tau-tangle accumulation extend beyond cerebrum to spinal cord and their presence outside the cerebrum are associated with a higher odds of dementia. Further studies are needed to clarify the extent, burden, and consequences of AD pathology outside of cerebrum.

The Anti-Amyloid Monoclonal Antibody Lecanemab: 16 Cautionary Notes. - Kepp, Kasper P; Sensi, Stefano L; Johnsen, Kasper B; Barrio, Jorge R; Høilund-Carlsen, Poul F; Neve, Rachael L; Alavi, Abass; Herrup, Karl; Perry, George; Robakis, Nikolaos K; Vissel, Bryce; Espay, Alberto J (J Alzheimers Dis, 2023)
After the CLARITY-AD clinical trial results of lecanemab were interpreted as positive, and supporting the amyloid hypothesis, the drug received accelerated Food and Drug Administration approval. However, we argue that benefits of lecanemab treatment are uncertain and may yield net harm for some patients, and that the data do not support the amyloid hypothesis. We note potential biases from inclusion, unblinding, dropouts, and other issues. Given substantial adverse effects and subgroup heterogeneity, we conclude that lecanemab's efficacy is not clinically meaningful, consistent with numerous analyses suggesting that amyloid-β and its derivatives are not the main causative agents of Alzheimer's disease dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Antibodies, Monoclonal; Humans; United States

Association of Age-Related Spontaneous Internal Jugular Vein Reflux with Cognitive Impairment and Incident Dementia. - Adachi, Utako; Toi, Sono; Hosoya, Megumi; Hoshino, Takao; Seki, Misa; Yoshizawa, Hiroshi; Tsutsumi, Yukiko; Maruyama, Kenji; Kitagawa, Kazuo (J Alzheimers Dis, 2023)
BACKGROUND: It remains unclear whether changes in the venous circulation contribute to cognitive decline. OBJECTIVE: This study aimed to clarify whether the spontaneous jugular vein reflux (JVR) is associated with cognitive impairment and incident dementia. METHODS: Patients with any evidence of cerebral vessel disease on magnetic resonance imaging (MRI) were consecutively enrolled between October 2015 to July 2019. We employed carotid duplex sonography to measure the internal jugular vein (IJV). The subjects were classified into two groups based on the degree of JVR on either side: none, mild (JVR(-) group) and moderate, severe (JVR (+) group) JVR. They underwent both the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment-Japanese (MoCA-J) global tests. Their cognitive status was prospectively assessed until March 2023. RESULTS: 302 patients with an MMSE score ≥24 underwent duplex sonography of the IJV. Among them, 91 had spontaneous JVR on either side. Both MMSE and MoCA-J were significantly lower in patients with JVR (+) group than in the JVR (-) group. After the adjustment for risk factors and MRI findings, intergroup differences in MoCA-J remained significant. Among the cognitive subdomains, median executive function and memory scores were significantly lower in the JVR (+) group than in the JVR (-) group. During the median 5.2-year follow-up, 11 patients with incident dementia were diagnosed. Patients with severe JVR were significantly more likely to be diagnosed with dementia (log-rank test, p = 0.031). CONCLUSIONS: Spontaneous IJV reflux especially severe JVR, was associated with global cognitive function, and potentially with incident dementia.

Association of Sarcopenia and Its Defining Components with the Degree of Cognitive Impairment in a Memory Clinic Population. - Larsson, LE; Wang, Rui; Cederholm, Tommy; Wiggenraad, Fleur; Rydén, Marie; Hagman, Göran; Hellénius, Mai-Lis; Kivipelto, Miia; Thunborg, Charlotta (J Alzheimers Dis, 2023)
BACKGROUND: Sarcopenia and cognitive impairment are two leading causes of disabilities. OBJECTIVE: The objective was to examine the prevalence of sarcopenia and investigate the association between sarcopenia diagnostic components (muscle strength, muscle mass, and physical performance) and cognitive impairment in memory clinic patients. METHODS: 368 patients were included (age 59.0±7.25 years, women: 58.7%), displaying three clinical phenotypes of cognitive impairments, i.e., subjective cognitive impairment (SCI, 57%), mild cognitive impairment (MCI, 26%), and Alzheimer's disease (AD, 17%). Sarcopenia was defined according to diagnostic algorithm recommended by the European Working Group on Sarcopenia in Older People. Components of sarcopenia were grip strength, bioelectrical impedance analysis, and gait speed. They were further aggregated into a score (0-3 points) by counting the numbers of limited components. Multi-nominal logistic regression was applied. RESULTS: Probable sarcopenia (i.e., reduced grip strength) was observed in 9.6% of the patients, and 3.5% were diagnosed with sarcopenia. Patients with faster gait speed showed less likelihood of MCI (odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.06-0.90) and AD (OR: 0.12, 95% CI: 0.03-0.60). One or more limited sarcopenia components was associated with worse cognitive function. After adjusting for potential confounders, the association remained significant only for AD (OR 4.29, 95% CI 1.45-11.92). CONCLUSION: The results indicate a connection between the sarcopenia components and cognitive impairments. Limitations in the sarcopenia measures, especially slow walking speed, were related to poorer cognitive outcomes. More investigationsare required to further verify the causal relationship between sarcopenia and cognitive outcomes.

Associations Between Ambient Air Pollution and Cognitive Abilities from Midlife to Early Old Age: Modification by APOE Genotype. - Franz, Carol E; Gustavson, Daniel E; Elman, Jeremy A; Fennema-Notestine, Christine; Hagler, Donald J; Baraff, Aaron; Tu, Xin M; Wu, Tsung-Chin; De Anda, Jaden; Beck, Asad; Kaufman, Joel D; Whitsel, Nathan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) measures of ambient air pollution are associated with accelerated age-related cognitive impairment, and Alzheimer's disease and related dementias (ADRD). OBJECTIVE: We examined associations between air pollution, four cognitive factors, and the moderating role of apolipoprotein E (APOE) genotype in the understudied period of midlife. METHODS: Participants were ∼1,100 men in the Vietnam Era Twin Study of Aging. Baseline cognitive assessments were from 2003 to 2007. Measures included past (1993-1999) and recent (3 years prior to baseline assessment) PM2.5 and NO2 exposure, in-person assessment of episodic memory, executive function, verbal fluency, and processing speed, and APOE genotype. Average baseline age was 56 years with a 12-year follow-up. Analyses adjusted for health and lifestyle covariates. RESULTS: Performance in all cognitive domains declined from age 56 to 68. Higher PM2.5 exposures were associated with worse general verbal fluency. We found significant exposure-by-APOE genotype interactions for specific cognitive domains: PM2.5 with executive function and NO2 with episodic memory. Higher PM2.5 exposure was related to worse executive function in APOE ɛ4 carriers, but not in non-carriers. There were no associations with processing speed. CONCLUSION: These results indicate negative effects of ambient air pollution exposure on fluency alongside intriguing differential modifications of cognitive performance by APOE genotype. APOE ɛ4 carriers appeared more sensitive to environmental differences. The process by which air pollution and its interaction with genetic risk for ADRD affects risk for later life cognitive decline or progression to dementia may begin in midlife.

Associations Between Local Area Deprivation and Physical Activity Participation in People with Cognitive Impairment in the North East of England. - Mc Ardle, Ríona; Hamilton, Calum; Del Din, Silvia; Kingston, Andrew; Robinson, Louise; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2023)
BACKGROUND: Promoting physical activity, such as habitual walking behaviors, in people with cognitive impairment may support their ability to remain independent with a good quality of life for longer. However, people with cognitive impairment participate in less physical activity compared to cognitively unimpaired older adults. The local area in which people live may significantly impact abilities to participate in physical activity. For example, people who live in more deprived areas may have less safe and walkable routes. OBJECTIVE: To examine this further, this study aimed to explore associations between local area deprivation and physical activity in people with cognitive impairment and cognitively unimpaired older adults (controls). METHODS: 87 participants with cognitive impairment (mild cognitive impairment or dementia) and 27 older adult controls from the North East of England were included in this analysis. Participants wore a tri-axial wearable accelerometer (AX3, Axivity) on their lower backs continuously for seven days. The primary physical activity outcome was daily step count. Individuals' neighborhoods were linked to UK government area deprivation statistics. Hierarchical Bayesian models assessed the association between local area deprivation and daily step count in people with cognitive impairment and controls. RESULTS: Key findings indicated that there was no association between local area deprivation and daily step count in people with cognitive impairment, but higher deprivation was associated with lower daily steps for controls. CONCLUSION: These findings suggest that cognitive impairment may be associated with lower participation in physical activity which supersedes the influence of local area deprivation observed in normal aging.

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

BACE2: A Promising Neuroprotective Candidate for Alzheimer's Disease. - Yeap, Yee Jie; Kandiah, Nagaendran; Nizetic, Dean; Lim, Kah-Leong (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is the most common cause of dementia that affects millions of predominantly elderly individuals worldwide. Despite intensive research over several decades, controversies still surround the etiology of AD and the disease remains incurable. Meanwhile, new molecular players of the central amyloid cascade hypothesis have emerged and among these is a protease known as β-site APP cleavage enzyme 2 (BACE2). Unlike BACE1, BACE2 cleaves the amyloid-β protein precursor within the Aβ domain that accordingly prevents the generation of Aβ42 peptides, the aggregation of which is commonly regarded as the toxic entity that drives neurodegeneration in AD. Given this non-amyloidogenic role of BACE2, it is attractive to position BACE2 as a therapeutic target for AD. Indeed, several groups including ours have demonstrated a neuroprotective role for BACE2 in AD. In this review, we discuss emerging evidence supporting the ability of BACE2 in mitigating AD-associated pathology in various experimental systems including human pluripotent stem cell-derived cerebral organoid disease models. Alongside this, we also provide an update on the identification of single nucleotide polymorphisms occurring in the BACE2 gene that are linked to increased risk and earlier disease onset in the general population. In particular, we highlight a recently identified point mutation on BACE2 that apparently leads to sporadic early-onset AD. We believe that a better understanding of the role of BACE2 in AD would provide new insights for the development of viable therapeutic strategies for individuals with dementia.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Humans

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Characterizing Limbic-Predominant Age-Related TDP-43 Encephalopathy Without Alzheimer's Disease and Lewy Body Dementia in the Oldest Old: A Case Series. - Leiby, Anne-Marie C; Scambray, Kiana A; Nguyen, Hannah L; Basith, Farheen; Fakhraee, Shahrzad; Melikyan, Zarui A; Bukhari, Syed A; Montine, Thomas J; Corrada, Maria M; Kawas, Claudia H; Sajjadi, S Ahmad (J Alzheimers Dis, 2023)
BACKGROUND: Limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC) is a clinicopathological construct proposed to facilitate studying TDP-43 pathology in older individuals. OBJECTIVE: Our aim was to describe clinical and cognitive characteristics of LATE-NC without Alzheimer's disease neuropathologic change (ADNC) and Lewy body (LB) and to compare this with ADNC and primary age related tauopathy (PART). METHODS: In 364 autopsies of the oldest old of The 90+ Study, we identified those with LATE-NC without ADNC and LB. Control groups were participants with ADNC and PART. RESULTS: Of 31% of participants who had LATE-NC, only 5 (1.4%) had LATE-NC without ADNC and LB, all of whom had tau. These participants had a gradual and progressive cognitive decline. Four (80%) had dementia at death, a rate that was higher than ADNC (50%) and PART (21.7%). Mean duration of cognitive impairment was twice as long in LATE-NC without ADNC and LB (6.2 years) compared to ADNC (2.9 years) and PART (3 years). LATE-NC without ADNC and LB group had a higher prevalence of syncope, depression, and extrapyramidal signs than the ADNC and PART groups. CONCLUSIONS: Despite the high prevalence of LATE-NC, LATE-NC without ADNC and LB was rare in this large oldest-old cohort, highlighting the very high prevalence of multiple pathologic changes in the oldest old. Slowly progressive cognitive decline, ubiquitous memory impairment, history of syncope and depression, and extrapyramidal signs were prominent features among our LATE-NC without ADNC and LB group.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; DNA-Binding Proteins; Humans; Lewy Body Disease; Syncope; Tauopathies; TDP-43 Proteinopathies

Circulating Omega-3 and Omega-6 Fatty Acids, Cognitive Decline, and Dementia in Older Adults. - de Oliveira Otto, Marcia C; Wu, Jason H Y; Thacker, Evan L; Lai, Heidi Tsz Mung; Lemaitre, Rozenn N; Padhye, Nikhil; Song, Xiaoling; King, Irena B; Lopez, Oscar; Siscovick, David S; Mozaffarian, Dariush (J Alzheimers Dis, 2023)
BACKGROUND: Comprising nearly 35% of brain lipids, polyunsaturated fatty acids (PUFA) are essential for optimal brain function. However, the role of PUFA on cognitive health outcomes later in life is largely unknown. OBJECTIVE: We investigated prospective associations of plasma phospholipid omega-3 (ALA [18 : 3], EPA [20 : 5], DPA [22 : 5], DHA [22 : 6]) and omega-6 (LA [18 : 2], AA [20 : 4]) PUFA with cognitive decline, risk of cognitive impairment and dementia among adults aged≥65 years in the Cardiovascular Health Study. METHODS: Circulating fatty acid concentrations were measured serially at baseline (1992/1993), 6 years, and 13 years later. Cognitive decline and impairment were assessed using the 100-point Modified Mini-Mental State Examination (3MSE) up to 7 times. Clinical dementia was identified using adjudicated neuropsychological tests, and ICD-9 codes. RESULTS: Among 3,564 older adults free of stroke and dementia at baseline, cognitive function declined annually by approximately -0.5 3MSE points; 507 participants developed cognitive impairment and 499 dementia over up to 23 years of follow-up. In multivariable models, higher circulating arachidonic acid (AA) concentrations were associated with slower cognitive decline and lower dementia risk, with associations growing stronger with greater length of follow-up (hazard ratio [HR,95% CI] of dementia per interquintile range, 0.74 [0.56-0.97] at 5 years, and 0.53 [0.37-0.77] at 15 years). Circulating docosapentaenoic (DPA) concentrations were associated with slower cognitive decline and lower risk of cognitive impairment (extreme-quintile HR, 0.72 [95% CI: 0.55, 0.95]). Findings were generally null or inconsistent for other omega-3 or omega-6 PUFA. CONCLUSION: Circulating AA and DPA, but not other PUFA, are associated with slower rate of cognitive decline and lower risk of dementia or cognitive impairment later in life.
Keywords: Aged; Arachidonic Acid; Cognitive Dysfunction; Dementia; Fatty Acids; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Humans

Cognition and Cognitive Changes in a Low-Income Sub-Saharan African Aging Population. - Kohler, Iliana V; Kämpfen, Fabrice; Bandawe, Chiwoza; Kohler, Hans-Peter (J Alzheimers Dis, 2023)
BACKGROUND: Cognition and its age-related changes remain vastly understudied in low-income countries (LICs), despite evidence suggesting that cognitive decline among aging low-income populations is a rapidly increasing disease burden often occurring at younger ages as compared to high-income countries (HICs). OBJECTIVE: We examine patterns of cognition among men and women, 45 + years old, living in rural Malawi. We analyze how key socioeconomic characteristics predict levels of cognition and its changes as individuals get older. METHODS: Utilizing the Mature Adults Cohort of the Malawi Longitudinal Study of Families and Health (MLSFH-MAC) collected during 2012-2017, we estimate standard regression models to analyze predictors of the age- and sex-specific levels and longitudinal changes in cognition. Cognition is assessed with a screening instrument that is adapted to this low-literacy context and measures different domains such as language, attention, or executive functioning. RESULTS: Women have lower levels of cognition than men, a pattern in stark contrast to findings in HICs. Schooling and socioeconomic status increase the probability of having consistently high performance during the cognitive assessment. Cognitive decline accelerates with age and is detectable already at mid-adult ages (45-55 years). Despite lower levels of cognitive function observed among women, the pace of decline with age is similar for both genders. CONCLUSION: Women are particularly affected by poor cognition in this context. The study emphasizes the importance of prioritizing cognitive health and research on cognition among older individuals in sub-Saharan Africa LICs, to which relatively little health care resources continue to be allocated.

The Complexity of Nutritional Problems in Persons with Dementia: Expanding a Theoretical Model. - van Buuren, Cornelia Pieternella; van der Steen, Jenny Theodora; Olthof-Nefkens, Maria; Bakker, Christian; Koopmans, Raymond Theodorus Catherina Maria; Perry, Marieke; Kalf, Johanna Gezina (J Alzheimers Dis, 2023)
BACKGROUND: Persons with dementia are at risk of developing nutritional problems. Theoretical models on nutritional problems have been developed, but have not been evaluated with healthcare professionals. OBJECTIVE: This study aimed to explore the comprehensiveness and applicability of a theoretical model of nutritional problems in persons with dementia for daily nursing home practice. METHODS: A qualitative design employing a combined deductive and inductive approach was used. Healthcare professionals were eligible to participate if they 1) had expert knowledge of and experience with nutritional problems related to dementia, and 2) worked in a nursing home affiliated with an academic network covering the east and south of the Netherlands. Three focus group interviews with 20 healthcare professionals from seven professions were held. We conducted thematic analysis and we compared themes with existing theoretical models from the literature. RESULTS: We identified six themes, four of which corresponded with the existing models (observing and analysing nutritional problems; consequences of nutritional problems; functioning of the person with dementia; environmental factors). Interprofessional collaboration and ethical factors were identified as new themes. The analyses indicated interactions within each theme, between themes, and a bidirectional connection between themes. CONCLUSIONS: This study demonstrated the relevance of interprofessional collaboration and ethical considerations in nutritional problems related to dementia. It uncovered complex bidirectional relations within and between factors regarding nutritional problems. All aspects should be taken into account to minimize the consequences of nutritional problems for persons with dementia.
Keywords: Attitude of Health Personnel; Dementia; Focus Groups; Health Personnel; Humans; Nursing Homes

Costs During the Last Five Years of Life for Patients with Clinical and Pathological Confirmed Diagnosis of Lewy Body Dementia and Alzheimer's Disease. - Zhu, Carolyn W; Gu, Yian; Kociolek, Anton J; Fernandez, Kayri K; Cosentino, Stephanie; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: Little is known regarding healthcare expenditures for patients with dementia with Lewy bodies (DLB) during the end of life. OBJECTIVE: This study estimated Medicare expenditures during the last 5 years of life in a decedent sample of patients who were clinically diagnosed with Alzheimer's disease (AD) or DLB and had autopsy confirmed diagnosis. METHODS: The study included 58 participants clinically diagnosed with mild dementia at study entry (AD: n = 44, DLB: n = 14) and also had autopsy-confirmed diagnoses of pure AD (n = 32), mixed AD+Lewy body (LB) (n = 5), or pure LB (n = 11). Total Medicare expenditures were compared by clinical and pathology confirmed diagnosis, adjusting for sex, age at death, and patient's cognition, function, comorbidities, and psychiatric and extrapyramidal symptoms. RESULTS: When pathology diagnoses were not considered, predicted annualized total Medicare expenditures during the last 5 years of life were similar between clinically diagnosed AD ($7,465±1,098) and DLB ($7,783±1,803). When clinical diagnoses were not considered, predicted expenditures were substantially higher in patients with pathology confirmed mixed AD+LB ($12,005±2,455) than either pure AD ($6,173±941) or pure LB ($4,629±1,968) cases. Considering clinical and pathology diagnosis together, expenditures for patients with clinical DLB and pathology mixed AD+LB ($23,592±3,679) dwarfed other groups. CONCLUSION: Medicare expenditures during the last 5 years of life were substantially higher in patients with mixed AD+LB pathology compared to those with pure-AD and pure-DLB pathologies, particularly in those clinically diagnosed with DLB. Results highlight the importance of having both clinical and pathology diagnoses in examining healthcare costs.

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Detecting Anosognosia from the Prodromal Stage of Alzheimer's Disease. - Guieysse, Thomas; Lamothe, Roxane; Houot, Marion; Razafimahatratra, Solofo; Medani, Takfarinas; Lejeune, François-Xavier; Dreyfus, Gérard; Klarsfeld, André; Pantazis, Dimitrios; Koechlin, Etienne; Andrade, Katia (J Alzheimers Dis, 2023)
BACKGROUND: Though not originally developed for this purpose, the Healthy Aging Brain Care Monitor (HABC-M) seems a valuable instrument for assessing anosognosia in Alzheimer's disease (AD). OBJECTIVES: Our study aimed at 1) investigating the validity of the HABC-M (31 items), and its cognitive, psychological, and functional subscales, in discriminating AD patients from controls; 2) exploring whether the HABC-M discrepancy scores between the self-reports of patients/controls in these different domains and the respective ratings provided by their caregivers/informants correlate with an online measure of self-awareness; 3) determining whether the caregiver burden level, also derived from the HABC-M, could add additional support for detecting anosognosia. METHODS: The HABC-M was administered to 30 AD patients and 30 healthy controls, and to their caregivers/informants. A measure of online awareness was established from subjects' estimation of their performances in a computerized experiment. RESULTS: The HABC-M discrepancy scores distinguished AD patients from controls. The cognitive subscale discriminated the two groups from the prodromal AD stage, with an AUC of 0.88 [95% CI: 0.78;0.97]. Adding the caregiver burden level raised it to 0.94 [0.86;0.99]. Significant correlations between the HABC-M and online discrepancy scores were observed in the patients group, providing convergent validity of these methods. CONCLUSIONS: The cognitive HABC-M (six items) can detect anosognosia across the AD spectrum. The caregiver burden (four items) may corroborate the suspicion of anosognosia. The short-hybrid scale, built from these 10 items instead of the usual 31, showed the highest sensitivity for detecting anosognosia from the prodromal AD stage, which may further help with timely diagnosis.
Keywords: Agnosia; Alzheimer Disease; Brain; Caregivers; Humans; Neuropsychological Tests; Prodromal Symptoms

Diagnostic Performance of Cerebrospinal Fluid Neurofilament Light Chain and Soluble Amyloid-β Protein Precursor β in the Subcortical Small Vessel Type of Dementia. - Axelsson Andrén, Elin; Kettunen, Petronella; Bjerke, Maria; Rolstad, Sindre; Zetterberg, Henrik; Blennow, Kaj; Wallin, Anders; Svensson, Johan (J Alzheimers Dis, 2023)
BACKGROUND: The subcortical small vessel type of dementia (SSVD) is a common subtype of vascular dementia, but there is a lack of disease-specific cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: We investigated whether CSF concentrations of neurofilament light chain (NFL), soluble amyloid-β protein precursor α (sAβPPα), sAβPPβ, and CSF/serum albumin ratio could separate SSVD from healthy controls, Alzheimer's disease (AD), and mixed dementia (combined AD and SSVD). METHODS: This was a mono-center study of patients with SSVD (n = 38), AD (n = 121), mixed dementia (n = 62), and controls (n = 96). The CSF biomarkers were measured using immunoassays, and their independent contribution to the separation between groups were evaluated using the Wald test. Then, the area under the receiver operating characteristics curve (AUROC) and 95% confidence intervals (CIs) were calculated. RESULTS: Elevated neurofilament light chain (NFL) and decreased sAβPPβ independently separated SSVD from controls, and sAβPPβ also distinguished SSVD from AD and mixed dementia. The combination of NFL and sAβPPβ discriminated SSVD from controls with high accuracy (AUROC 0.903, 95% CI: 0.834-0.972). Additionally, sAβPPβ combined with the core AD biomarkers (amyloid-β42, total tau, and phosphorylated tau181) had a high ability to separate SSVD from AD (AUROC 0.886, 95% CI: 0.830-0.942) and mixed dementia (AUROC 0.903, 95% CI: 0.838-0.968). CONCLUSIONS: The high accuracy of NFL and sAβPPβ to separate SSVD from controls supports that SSVD is a specific diagnostic entity. Moreover, SSVD was distinguished from AD and mixed dementia using sAβPPβ in combination with the core AD biomarkers.

Early Life Stress Enhances Cognitive Decline and Alters Synapse Function and Interneuron Numbers in Young Male APP/PS1 Mice. - Brosens, Niek; Samouil, Dimitris; Stolker, Sabine; Katsika, Efthymia Vasilina; Weggen, Sascha; Lucassen, Paul J; Krugers, Harm J (J Alzheimers Dis, 2023)
BACKGROUND: Exposure to stress early in life increases the susceptibility to Alzheimer's disease (AD) pathology in aged AD mouse models. So far, the underlying mechanisms have remained elusive. OBJECTIVE: To investigate 1) effects of early life stress (ELS) on early functional signs that precede the advanced neuropathological changes, and 2) correlate synaptosomal protein content with cognition to identify neural correlates of AD. METHODS: APPswe/PS1dE9 mice and littermates were subjected to ELS by housing dams and pups with limited bedding and nesting material from postnatal days 2-9. At 3 months of age, an age where no cognitive loss or amyloid-β (Aβ) pathology is typically reported in this model, we assessed hippocampal Aβ pathology, synaptic strength and synapse composition and interneuron populations. Moreover, cognitive flexibility was assessed and correlated with synaptosomal protein content. RESULTS: While ELS did not affect Aβ pathology, it increased synaptic strength and decreased the number of calretinin+ interneurons in the hippocampal dentate gyrus. Both genotype and condition further affected the level of postsynaptic glutamatergic protein content. Finally, APP/PS1 mice were significantly impaired in cognitive flexibility at 3 months of age, and ELS exacerbated this impairment, but only at relatively high learning criteria. CONCLUSIONS: ELS reduced cognitive flexibility in young APP/PS1 mice and altered markers for synapse and network function. These findings at an early disease stage provide novel insights in AD etiology and in how ELS could increase AD susceptibility.
Keywords: Adverse Childhood Experiences; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognitive Dysfunction; Disease Models, Animal; Interneurons; Male; Mice; Mice, Transgenic; Plaque, Amyloid; Presenilin-1; Synapses

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Etiology and Clinical Significance of Network Hyperexcitability in Alzheimer's Disease: Unanswered Questions and Next Steps. - Samudra, Niyatee; Ranasinghe, Kamalini; Kirsch, Heidi; Rankin, Katherine; Miller, Bruce (J Alzheimers Dis, 2023)
Cortical network hyperexcitability related to synaptic dysfunction in Alzheimer's disease (AD) is a potential target for therapeutic intervention. In recent years, there has been increased interest in the prevalence of silent seizures and interictal epileptiform discharges (IEDs, or seizure tendency), with both entities collectively termed "subclinical epileptiform activity" (SEA), on neurophysiologic studies in AD patients. SEA has been demonstrated to be common in AD, with prevalence estimates ranging between 22-54%. Converging lines of basic and clinical evidence imply that modifying a hyperexcitable state results in an improvement in cognition. In particular, though these results require further confirmation, post-hoc findings from a recent phase II clinical trial suggest a therapeutic effect with levetiracetam administration in patients with AD and IEDs. Here, we review key unanswered questions as well as potential clinical trial avenues. Specifically, we discuss postulated mechanisms and treatment of hyperexcitability in patients with AD, which are of interest in designing future disease-modifying therapies. Criteria to prompt screening and optimal screening methodology for hyperexcitability have yet to be defined, as does timing and personalization of therapeutic intervention.
Keywords: Alzheimer Disease; Causality; Clinical Relevance; Electroencephalography; Humans; Levetiracetam; Seizures

Exploring Reasons for Differential Vulnerability and Alzheimer's Disease Risk in Racial and Ethnic Minorities. - Daniel, E Valerie; Kleiman, Michael J; Galvin, James E (J Alzheimers Dis, 2023)
BACKGROUND: African American and Hispanic older adults are reported to have up to a 2-fold higher risk of Alzheimer's disease and related disorders (ADRD), but the reasons for this increased vulnerability have not been fully explored. The Vulnerability Index (VI) was designed to identify individuals who are at risk of developing cognitive impairment in the future, capturing 12 sociodemographic variables and modifiable medical comorbidities associated with higher ADRD risk. However, a prior limitation of the VI was that the original study cohort had limited diversity. We examined the association of the VI within and between non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment and different socioeconomic strata enrolled in a community-based dementia screening study. OBJECTIVE: To explore reasons for reported higher ADRD vulnerability in African Americans and Hispanics. METHODS: In a cross-sectional study of 300 non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment, we studied the association between cognitive status, the VI, and socioeconomic status (SES). RESULTS: When considering race/ethnicity, the presence of more vascular comorbidities drove greater vulnerability. When considering SES, vascular comorbidities played a less prominent role suggesting resources and access to care drives risk. The VI had differential effects on cognitive performance with the greatest effect in the earlier stages of impairment. CONCLUSION: Findings from this study provide a deeper understanding of the differential risk of ADRD in multicultural older adults captured by the VI and how barriers to healthcare access may increase vulnerability in racial/ethnic minorities.
Keywords: Aged; Alzheimer Disease; Cross-Sectional Studies; Ethnic and Racial Minorities; Ethnicity; Humans; White People

Extracellular Tau Oligomers Damage the Axon Initial Segment. - Best, Merci N; Lim, Yunu; Ferenc, Nina N; Kim, Nayoung; Min, Lia; Wang, Dora Bigler; Sharifi, Kamyar; Wasserman, Anna E; McTavish, Sloane A; Siller, Karsten H; Jones, Marieke K; Jenkins, Paul M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: In Alzheimer's disease (AD) brain, neuronal polarity and synaptic connectivity are compromised. A key structure for regulating polarity and functions of neurons is the axon initial segment (AIS), which segregates somatodendritic from axonal proteins and initiates action potentials. Toxic tau species, including extracellular oligomers (xcTauOs), spread tau pathology from neuron to neuron by a prion-like process, but few other cell biological effects of xcTauOs have been described. OBJECTIVE: Test the hypothesis that AIS structure is sensitive to xcTauOs. METHODS: Cultured wild type (WT) and tau knockout (KO) mouse cortical neurons were exposed to xcTauOs, and quantitative western blotting and immunofluorescence microscopy with anti-TRIM46 monitored effects on the AIS. The same methods were used to compare TRIM46 and two other resident AIS proteins in human hippocampal tissue obtained from AD and age-matched non-AD donors. RESULTS: Without affecting total TRIM46 levels, xcTauOs reduce the concentration of TRIM46 within the AIS and cause AIS shortening in cultured WT, but not TKO neurons. Lentiviral-driven tau expression in tau KO neurons rescues AIS length sensitivity to xcTauOs. In human AD hippocampus, the overall protein levels of multiple resident AIS proteins are unchanged compared to non-AD brain, but TRIM46 concentration within the AIS and AIS length are reduced in neurons containing neurofibrillary tangles. CONCLUSION: xcTauOs cause partial AIS damage in cultured neurons by a mechanism dependent on intracellular tau, thereby raising the possibility that the observed AIS reduction in AD neurons in vivo is caused by xcTauOs working in concert with endogenous neuronal tau.

The Impact of Routine Vaccinations on Alzheimer's Disease Risk in Persons 65 Years and Older: A Claims-Based Cohort Study using Propensity Score Matching. - Harris, Kristofer; Ling, Yaobin; Bukhbinder, Avram S; Chen, Luyao; Phelps, Kamal N; Cruz, Gabriela; Thomas, Jenna; Kim, Yejin; Jiang, Xiaoqian; Schulz, Paul E (J Alzheimers Dis, 2023)
BACKGROUND: Accumulating evidence suggests that adult vaccinations can reduce the risk of developing Alzheimer's disease (AD) and Alzheimer's disease related dementias. OBJECTIVE: To compare the risk for developing AD between adults with and without prior vaccination against tetanus and diphtheria, with or without pertussis (Tdap/Td); herpes zoster (HZ); or pneumococcus. METHODS: A retrospective cohort study was performed using Optum's de-identified Clinformatics® Data Mart Database. Included patients were free of dementia during a 2-year look-back period and were≥65 years old by the start of the 8-year follow-up period. We compared two similar cohorts identified using propensity score matching (PSM), one vaccinated and another unvaccinated, with Tdap/Td, HZ, or pneumococcal vaccines. We calculated the relative risk (RR) and absolute risk reduction (ARR) for developing AD. RESULTS: For the Tdap/Td vaccine, 7.2% (n = 8,370) vaccinated patients and 10.2% (n = 11,857) unvaccinated patients developed AD during follow-up; the RR was 0.70 (95% CI, 0.68-0.72) and ARR was 0.03 (95% CI, 0.02-0.03). For the HZ vaccine, 8.1% (n = 16,106) vaccinated patients and 10.7% (n = 21,273) unvaccinated patients developed AD during follow-up; the RR was 0.75 (95% CI, 0.73-0.76) and ARR was 0.02 (95% CI, 0.02-0.02). For the pneumococcal vaccine, 7.92% (n = 20,583) vaccinated patients and 10.9% (n = 28,558) unvaccinated patients developed AD during follow-up; the RR was 0.73 (95% CI, 0.71-0.74) and ARR was 0.02 (95% CI, 0.02-0.03). CONCLUSION: Several vaccinations, including Tdap/Td, HZ, and pneumococcal, are associated with a reduced risk for developing AD.

Impact of Yoga Versus Memory Enhancement Training on Hippocampal Connectivity in Older Women at Risk for Alzheimer's Disease. - Kilpatrick, Lisa A; Siddarth, Prabha; Krause-Sorio, Beatrix; Milillo, Michaela M; Aguilar-Faustino, Yesenia; Ercoli, Linda; Narr, Katherine L; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2023)
BACKGROUND: Yoga may be an ideal early intervention for those with modifiable risk factors for Alzheimer's disease (AD) development. OBJECTIVE: To examine the effects of Kundalini yoga (KY) training versus memory enhancement training (MET) on the resting-state connectivity of hippocampal subregions in women with subjective memory decline and cardiovascular risk factors for AD. METHODS: Participants comprised women with subjective memory decline and cardiovascular risk factors who participated in a parent randomized controlled trial (NCT03503669) of 12-weeks of KY versus MET and completed pre- and post-intervention resting-state magnetic resonance imaging scans (yoga: n = 11, age = 61.45±6.58 years; MET: n = 11, age = 64.55±6.41 years). Group differences in parcellated (Cole-anticevic atlas) hippocampal connectivity changes (post- minus pre-intervention) were evaluated by partial least squares analysis, controlling for age. Correlations between hippocampal connectivity and perceived stress and frequency of forgetting (assessed by questionnaires) were also evaluated. RESULTS: A left anterior hippocampal subregion assigned to the default mode network (DMN) in the Cole-anticevic atlas showed greater increases in connectivity with largely ventral visual stream regions with KY than with MET (p < 0.001), which showed associations with lower stress (p < 0.05). Several posterior hippocampal subregions assigned to sensory-based networks in the Cole-anticevic atlas showed greater increases in connectivity with regions largely in the DMN and frontoparietal network with MET than with KY (p < 0.001), which showed associations with lower frequency of forgetting (p < 0.05). CONCLUSION: KY training may better target stress-related hippocampal connectivity, whereas MET may better target hippocampal sensory-integration supporting better memory reliability, in women with subjective memory decline and cardiovascular risk factors.

Insights into the Pathophysiology of Alzheimer's Disease and Potential Therapeutic Targets: A Current Perspective. - Rajah Kumaran, Kesevan; Yunusa, Suleiman; Perimal, Enoch; Wahab, Habibah; Müller, Christian P; Hassan, Zurina (J Alzheimers Dis, 2023)
The aging population increases steadily because of a healthy lifestyle and medical advancements in healthcare. However, Alzheimer's disease (AD) is becoming more common and problematic among older adults. AD-related cases show an increasing trend annually, and the younger age population may also be at risk of developing this disorder. AD constitutes a primary form of dementia, an irreversible and progressive brain disorder that steadily damages cognitive functions and the ability to perform daily tasks. Later in life, AD leads to death as a result of the degeneration of specific brain areas. Currently, the cause of AD is poorly understood, and there is no safe and effective therapeutic agent to cure or slow down its progression. The condition is entirely preventable, and no study has yet demonstrated encouraging findings in terms of treatment. Identifying this disease's pathophysiology can help researchers develop safe and efficient therapeutic strategies to treat this ailment. This review outlines and discusses the pathophysiology that resulted in the development of AD including amyloid-β plaques, tau neurofibrillary tangles, neuroinflammation, oxidative stress, cholinergic dysfunction, glutamate excitotoxicity, and changes in neurotrophins level may sound better based on the literature search from Scopus, PubMed, ScienceDirect, and Google Scholar. Potential therapeutic strategies are discussed to provide more insights into AD mechanisms by developing some possible pharmacological agents for its treatment.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Oxidative Stress; Plaque, Amyloid; tau Proteins

Intracellular Amyloid-β in the Normal Rat Brain and Human Subjects and Its relevance for Alzheimer's Disease. - Kobro-Flatmoen, Asgeir; Hormann, Thea Meier; Gouras, Gunnar (J Alzheimers Dis, 2023)
BACKGROUND: Amyloid-β (Aβ) is a normal product of neuronal activity, including that of the aggregation-prone Aβ42 variant that is thought to cause Alzheimer's disease (AD). Much knowledge about AD comes from studies of transgenic rodents expressing mutated human amyloid-β protein precursor (AβPP) to increase Aβ production or the Aβ42/40 ratio. Yet, little is known about the normal expression of Aβ42 in rodent brains. OBJECTIVE: To characterize the brain-wide expression of Aβ42 throughout the life span of outbred Wistar rats, and to relate these findings to brains of human subjects without neurological disease. METHODS: Aβ42 immunolabeling of 12 Wistar rat brains (3-18 months of age) and brain sections from six human subjects aged 20-88 years. RESULTS: In healthy Wistar rats, we find intracellular Aβ42 (iAβ42) in neurons throughout the brain at all ages, but levels vary greatly between brain regions. The highest levels are in neurons of entorhinal cortex layer II, alongside hippocampal neurons at the CA1/subiculum border. Concerning entorhinal cortex layer II, we find similarly high levels of iAβ42 in the human subjects. CONCLUSION: Expression of iAβ42 in healthy Wistar rats predominates in the same structures where iAβ accumulates and Aβ plaques initially form in the much used, Wistar based McGill-R-Thy1-APP rat model for AD. The difference between wild-type Wistar rats and these AD model rats, with respect to Aβ42, is therefore quantitative rather that qualitative. This, taken together with our human results, indicate that the McGill rat model in fact models the underlying wild-type neuronal population-specific vulnerability to Aβ42 accumulation.

Linking Air Pollution Exposure to Blood-Based Metabolic Features in a Community-Based Aging Cohort with and without Dementia. - Kalia, Vrinda; Kulick, Erin R; Vardarajan, Badri; Gu, Yian; Manly, Jennifer J; Elkind, Mitchell S V; Kaufman, Joel D; Jones, Dean P; Baccarelli, Andrea A; Mayeux, Richard; Kioumourtzoglou, Marianthi-Anna; Miller, Gary W (J Alzheimers Dis, 2023)
BACKGROUND: Long-term exposure to air pollution has been associated with changes in levels of metabolites measured in the peripheral blood. However, most research has been conducted in ethnically homogenous, young or middle-aged populations. OBJECTIVE: To study the relationship between the plasma metabolome and long-term exposure to three air pollutants: particulate matter (PM) less than 2.5μm in aerodynamic diameter (PM2.5), PM less than 10μm in aerodynamic diameter (PM10), and nitrogen dioxide (NO2) in an ethnically diverse, older population. METHODS: Plasma metabolomic profiles of 107 participants of the Washington Heights and Inwood Community Aging Project in New York City, collected from 1995-2015, including non-Hispanic white, Caribbean Hispanic, and non-Hispanic Black older adults were used. We estimated the association between each metabolic feature and predicted annual mean exposure to the air pollutants using three approaches: 1) A metabolome wide association study framework; 2) Feature selection using elastic net regression; and 3) A multivariate approach using partial-least squares discriminant analysis. RESULTS: 79 features associated with exposure to PM2.5 but none associated with PM10 or NO2. PM2.5 exposure was associated with altered amino acid metabolism, energy production, and oxidative stress response, pathways also associated with Alzheimer's disease. Three metabolites were associated with PM2.5 exposure through all three approaches: cysteinylglycine disulfide, a diglyceride, and a dicarboxylic acid. The relationship between several features and PM2.5 exposure was modified by diet and metabolic diseases. CONCLUSIONS: These relationships uncover the mechanisms through which PM2.5 exposure can lead to altered metabolic outcomes in an older population.
Keywords: Aged; Aging; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Humans; Nitrogen Dioxide; Particulate Matter

Lithium Provides Broad Therapeutic Benefits in an Alzheimer's Disease Mouse Model. - Wiseman, Alyssa L; Briggs, Clark A; Peritt, Ariel; Kapecki, Nicolas; Peterson, Daniel A; Shim, Seong S; Stutzmann, Grace E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a progressive loss of cognitive function. Currently, no effective treatment regimen is available. Lithium, a mood stabilizer for bipolar disorder, exerts broad neuroprotective and neurotrophic actions and improves cognitive function. OBJECTIVE: The study investigated if lithium stabilizes Ca2+ signaling abnormalities in hippocampal neurons and subsequently normalize downstream effects on AD neuropathology and synaptic plasticity in young AD mice. METHODS: Four-month-old 3xTg-AD mice were treated with a LiCl diet chow for 30 days. At the end of the lithium treatment, a combination of two-photon Ca2+ imaging, electrophysiology, and immunohistochemistry assays were used to assess the effects of the LiCl treatment on inositol trisphosphate receptor (IP3R)-dependent endoplasmic reticulum (ER) Ca2+ and voltage-gated Ca2+ channel (VGCC)-mediated Ca2+ signaling in CA1 neurons, neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels and synaptic plasticity in the hippocampus and overlying cortex from 3xTg-ADmice. RESULTS: Thirty-day LiCl treatment reduced aberrant IP3R-dependent ER Ca2+ and VGCC-mediated Ca2+ signaling in CA1 pyramidal neurons from 3xTg-AD mice and restored neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels to control levels in the hippocampal subfields and overlying cortex. The LiCl treatment enhanced post-tetanic potentiation (PTP), a form of short-term plasticity in the hippocampus. CONCLUSION: The study found that lithium exerts therapeutic effects across several AD-associated early neuronal signaling abnormalities including aberrant Ca2+ signaling, nNOS, and p-tau formation and enhances short-term synaptic plasticity. Lithium could serve as an effective treatment or co-therapeutic for AD.
Keywords: Alzheimer Disease; Animals; Calcium; Disease Models, Animal; Hippocampus; Lithium; Mice; Mice, Transgenic; Nitric Oxide Synthase Type I; tau Proteins

Longitudinal Effects of Herpesviruses on Multiple Cognitive Outcomes in Healthy Elderly Adults. - Weidung, Bodil; Josefsson, Maria; Lyttkens, Peter; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo (J Alzheimers Dis, 2023)
BACKGROUND: Herpesviruses have been proposed to be involved in Alzheimer's disease development as potentially modifiable pathology triggers. OBJECTIVE: To investigate associations of serum antibodies for herpes simplex virus (HSV)-1 and cytomegalovirus (CMV) and anti-herpesvirus treatment with cognitive outcomes in relation to interactions with APOE ɛ4. METHODS: The study included 849 participants in the population-based Prospective Investigation of the Vasculature in Uppsala Seniors study. Cognitive performance at the ages of 75 and 80 years was assessed using the Mini-Mental State Examination (MMSE), trail-making test (TMT) A and B, and 7-minute screening test (7MS). RESULTS: Anti- HSV-1 IgG positivity was associated cross-sectionally with worse performance on the MMSE, TMT-A, TMT-B, 7MS, enhanced free recall, and verbal fluency tests (p = 0.016, p = 0.016, p <  0.001, p = 0.001, p = 0.033, and p <  0.001, respectively), but not orientation or clock drawing. Cognitive scores did not decline over time and longitudinal changes did not differ according to HSV-1 positivity. Anti- CMV IgG positivity was not associated cross-sectionally with cognition, but TMT-B scores declined more in anti- CMV IgG carriers. Anti- HSV-1 IgG interacted with APOE ɛ4 in association with worse TMT-A and better enhanced cued recall. Anti- HSV IgM interacted with APOE ɛ4 and anti-herpesvirus treatment in association with worse TMT-A and clock drawing, respectively. CONCLUSION: These findings indicate that HSV-1 is linked to poorer cognition in cognitively healthy elderly adults, including impairments in executive function, memory, and expressive language. Cognitive performance did not decline over time, nor was longitudinal decline associated with HSV-1.

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Microglial Imaging in Alzheimer's Disease and Its Relationship to Brain Amyloid: A Human 18F-GE180 PET Study. - Yang, Zhengshi; Banks, Sarah J; Ritter, Aaron R; Cummings, Jeffrey L; Sreenivasan, Karthik; Kinney, Jefferson W; Caldwell, Jessica K; Wong, Christina G; Miller, Justin B; Cordes, Dietmar (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence suggests a potential causal role of neuroinflammation in Alzheimer's disease (AD). Using positron emission tomography (PET) to image overexpressed 18 kDA translocator protein (TSPO) by activated microglia has gained increasing interest. The uptake of 18F-GE180 TSPO PET was observed to co-localize with inflammatory markers and have a two-stage association with amyloid PET in mice. Very few studies evaluated the diagnostic power of 18F-GE180 PET in AD population and its interpretation in human remains controversial about whether it is a marker of microglial activation or merely reflects disrupted blood-brain barrier integrity in humans. OBJECTIVE: The goal of this study was to study human GE180 from the perspective of the previous animal observations. METHODS: With data from twenty-four participants having 18F-GE180 and 18F-AV45 PET scans, we evaluated the group differences of 18F-GE180 uptake between participants with and without cognitive impairment. An association analysis of 18F-GE180 and 18F-AV45 was then conducted to test if the relationship in humans is consistent with the two-stage association in AD mouse model. RESULTS: Elevated 18F-GE180 was observed in participants with cognitive impairment compared to those with normal cognition. No regions showed reduced 18F-GE180 uptake. Consistent with mouse model, a two-stage association between 18F-GE180 and 18F-AV45 was observed. CONCLUSIONS: 18F-GE180 PET imaging showed promising utility in detecting pathological alterations in a symptomatic AD population. Consistent two-stage association between 18F-GE180 and amyloid PET in human and mouse suggested that 18F-GE180 uptake in human might be considerably influenced by microglial activation.

Midlife Neuropsychological Profiles and Associated Vascular Risk: The Bogalusa Heart Study. - De Anda-Duran, Ileana; Kolachalama, Vijaya B; Carmichael, Owen T; Hwang, Phillip H; Fernandez, Camilo; Au, Rhoda; Bazzano, Lydia A; Libon, David J (J Alzheimers Dis, 2023)
BACKGROUND: Individuals with Alzheimer's disease (AD) often present with coexisting vascular pathology that is expressed to different degrees and can lead to clinical heterogeneity. OBJECTIVE: To examine the utility of unsupervised statistical clustering approaches in identifying neuropsychological (NP) test performance subtypes that closely correlate with carotid intima-media thickness (cIMT) in midlife. METHODS: A hierarchical agglomerative and k-means clustering analysis based on NP scores (standardized for age, sex, and race) was conducted among 1,203 participants (age 48±5.3 years) from the Bogalusa Heart Study. Regression models assessed the association between cIMT ≥50th percentile and NP profiles, and global cognitive score (GCS) tertiles for sensitivity analysis. RESULTS: Three NP profiles were identified: Mixed-low performance [16%, n = 192], scores ≥1 SD below the mean on immediate, delayed free recall, recognition verbal memory, and information processing; Average [59%, n = 704]; and Optimal [26%, n = 307] NP performance. Participants with greater cIMT were more likely to have a Mixed-low profile [OR = 3.10, 95% CI (2.13, 4.53), p < 0.001] compared to Optimal. After adjusting for education and cardiovascular (CV) risks, results remained. The association with GCS tertiles was more attenuated [lowest (34%, n = 407) versus highest (33%, n = 403) tertile: adjusted OR = 1.66, 95% CI (1.07, 2.60), p = 0.024]. CONCLUSION: As early as midlife, individuals with higher subclinical atherosclerosis were more likely to be in the Mixed-low profile, underscoring the potential malignancy of CV risk as related to NP test performance, suggesting that classification approaches may aid in identifying those at risk for AD/vascular dementia spectrum illness.

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mortality Risks and Causes of Death by Dementia Types in a Japanese Cohort with Dementia: NCGG-STORIES. - Ono, Rei; Sakurai, Takashi; Sugimoto, Taiki; Uchida, Kazuaki; Nakagawa, Takeshi; Noguchi, Taiji; Komatsu, Ayane; Arai, Hidenori; Saito, Tami (J Alzheimers Dis, 2023)
BACKGROUND: Prognosis-related information regarding dementia needs to be updated, as changes in medical and long-term care environments for patients with dementia in recent decades may be improving the prognosis of the disease. OBJECTIVE: We aimed to investigate the mortality, cause of death, and prognostic factors by types of dementia in a Japanese clinic-based cohort. METHODS: The National Center for Geriatrics and Gerontology-Life Stories of People with Dementia consists of clinical records and prognostic data of patients who visited the Memory Clinic in Japan. Patients who attended the clinic between July 2010 and September 2018, or their close relatives, were asked about death information via a postal survey. A cohort of 3,229 patients (mean age, 76.9; female, 1,953) was classified into six groups: normal cognition (NC), mild cognitive impairment (MCI), Alzheimer's disease (AD), vascular dementia, dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration. A Cox proportional hazards model was employed to compare the mortality of each type of dementia, MCI, and NC. RESULTS: Patients with all types of dementia and MCI had higher mortality rates than those with NC (hazard risks: 2.61-5.20). The most common cause of death was pneumonia, followed by cancer. In the MCI, AD, and DLB groups, older age, male sex, and low cognitive function were common prognostic factors but not presence of apolipoprotein E ɛ4 allele. CONCLUSION: Our findings suggest important differences in the mortality risk and cause of death among patients with dementia, which will be useful in advanced care planning and policymaking.
Keywords: Aged; Alzheimer Disease; Cause of Death; Cognitive Dysfunction; Dementia; East Asian People; Female; Humans; Lewy Body Disease; Male

Neuropathologic Changes of Alzheimer's Disease and Related Dementias: Relevance to Future Prevention. - White, Lon R; Corrada, Maria M; Kawas, Claudia H; Cholerton, Brenna A; Edland, Steve E; Flanagan, Margaret E; Montine, Thomas J (J Alzheimers Dis, 2023)
BACKGROUND: Decedents with late-life dementia are often found at autopsy to have vascular pathology, cortical Lewy bodies, hippocampal sclerosis, and/or TDP-43 encephalopathy alone or with concurrent Alzheimer's disease (AD) lesions. Nonetheless, it is commonly believed that AD neuropathologic changes (NC) are the dominant or exclusive drivers of late-life dementia. OBJECTIVE: Assess associations of end-of-life cognitive impairment with any one or any combination of five distinct NC. Assess impairment prevalence among subjects having natural resistance to each type of NC. METHODS: Brains from 1,040 autopsied participants of the Honolulu-Asia Study, the Nun Study, and the 90 + Study were examined for NC of AD, Lewy body dementia, microvascular brain injury, hippocampal sclerosis, and limbic predominate TDP-43 encephalopathy. Associations with impairment were assessed for each NC and for NC polymorbidity (variable combinations of 2-5 concurrent NC). RESULTS: Among 387 autopsied decedents with severe cognitive impairment, 20.4% had only AD lesions (ADNC), 25.3% had ADNC plus 1 other NC, 11.1% had ADNC plus 2 or more other NC, 28.7% had no ADNC but 1-4 other NC, and 14.5% had no/negligible NC. Combinations of any two, three, or four NC were highly frequent among the impaired. Natural resistance to ADNC or any other single NC had a modest impact on overall cohort impairment levels. CONCLUSION: Polymorbidity involving 1-5 types of concurrent NC is a dominant neuropathologic feature of AD and related dementias. This represents a daunting challenge to future prevention and could explain failures of prior preventive intervention trials and of efforts to identify risk factors.

Neuroprotective Effect of Phloretin in Rotenone-Induced Mice Model of Parkinson's Disease: Modulating mTOR-NRF2-p62 Mediated Autophagy-Oxidative Stress Crosstalk. - Shirgadwar, Shubhendu M; Kumar, Rahul; Preeti, Kumari; Khatri, Dharmendra Kumar; Singh, Shashi Bala (J Alzheimers Dis, 2023)
BACKGROUND: Parkinson's disease (PD) is an age-related progressive multifactorial, neurodegenerative disease. The autophagy and Keap1-Nrf2 axis system are both implicated in the oxidative-stress response, metabolic stress, and innate immunity, and their dysregulation is associated with pathogenic processes in PD. Phloretin (PLT) is a phenolic compound reported possessing anti-inflammatory and antioxidant activities. OBJECTIVE: To evaluate the neuroprotective potential of PLT in PD via modulating the autophagy-antioxidant axisMethods:The neuroprotective effect of PLT was evaluated in vitro using rotenone (ROT) exposed SH-SY5Y cell line and in vivo using ROT administered C57BL/6 mice. Mice were administered with PLT (50 and 100 mg/kg, p.o.) concomitantly with ROT (1 mg/kg, i.p) for 3 weeks. Locomotive activity and anxiety behaviors were assessed using rotarod and open field tests respectively. Further apoptosis (Cytochrome-C, Bax), α-Synuclein (α-SYN), tyrosine hydroxylase (TH), antioxidant proteins (nuclear factor erythroid 2-related factor 2 (NRF2), heme oxygenase-1 (HO-1) and autophagic (mTOR, Atg5,7, p62, Beclin,LC3B-I/II) protein activity were evaluated both in in vitro and in vivo. RESULTS: PLT improved locomotive activity and anxiety-like behavior in mice. Further PLT diminished apoptotic cell death, α-SYN expression and improved the expression of TH, antioxidant, and autophagic regulating protein. CONCLUSION: Taken together, present data deciphers that the PLT effectively improves motor and non-motor symptoms via modulating the mTOR/NRF2/p62 pathway-mediated feedback loop. Hence, PLT could emerge as a prospective disease-modifying drug for PD management.
Keywords: Animals; Antioxidants; Autophagy; Humans; Kelch-Like ECH-Associated Protein 1; Mice; Mice, Inbred C57BL; Neuroblastoma; Neurodegenerative Diseases; Neuroprotective Agents; NF-E2-Related Factor 2; Oxidative Stress; Parkinson Disease; Phloretin; Prospective Studies; Rotenone; TOR Serine-Threonine Kinases

Noninvasive Gamma Sensory Stimulation May Reduce White Matter and Myelin Loss in Alzheimer's Disease. - Da, Xiao; Hempel, Evan; Ou, Yangming; Rowe, Olivia Elizabeth; Malchano, Zach; Hajós, Mihály; Kern, Ralph; Megerian, Jonathan Thomas; Cimenser, Aylin (J Alzheimers Dis, 2023)
BACKGROUND: Patients with Alzheimer's disease (AD) demonstrate progressive white matter atrophy and myelin loss. Restoring myelin content or preventing demyelination has been suggested as a therapeutic approach for AD. OBJECTIVE: Herein, we investigate the effects of non-invasive, combined visual and auditory gamma-sensory stimulation on white matter atrophy and myelin content loss in patients with AD. METHODS: In this study, we used the magnetic resonance imaging (MRI) data from the OVERTURE study (NCT03556280), a randomized, controlled, clinical trial in which active treatment participants received daily, non-invasive, combined visual and auditory, 40 Hz stimulation for six months. A subset of OVERTURE participants who meet the inclusion criteria for detailed white matter (N = 38) and myelin content (N = 36) assessments are included in the analysis. White matter volume assessments were performed using T1-weighted MRI, and myelin content assessments were performed using T1-weighted/T2-weighted MRI. Treatment effects on white matter atrophy and myelin content loss were assessed. RESULTS: Combined visual and auditory gamma-sensory stimulation treatment is associated with reduced total and regional white matter atrophy and myelin content loss in active treatment participants compared to sham treatment participants. Across white matter structures evaluated, the most significant changes were observed in the entorhinal region. CONCLUSIONS: The study results suggest that combined visual and auditory gamma-sensory stimulation may modulate neuronal network function in AD in part by reducing white matter atrophy and myelin content loss. Furthermore, the entorhinal region MRI outcomes may have significant implications for early disease intervention, considering the crucial afferent connections to the hippocampus and entorhinal cortex.

Odor Discrimination as a Marker of Early Alzheimer's Disease. - Audronyte, Egle; Pakulaite-Kazliene, Gyte; Sutnikiene, Vaiva; Kaubrys, Gintaras (J Alzheimers Dis, 2023)
BACKGROUND: Olfactory dysfunction is an early symptom of Alzheimer's disease (AD). However, olfactory tests are rarely performed in clinical practice because their diagnostic efficacy in detecting early AD is unclear. OBJECTIVE: To investigate odor discrimination in patients with early AD and the efficacy of olfactory discrimination tests in differentiating these patients from subjects with normal cognition (CN). METHODS: Thirty patients each with mild dementia due to AD (MD-AD) and mild cognitive impairment due to AD (MCI-AD) and 30 older subjects with CN were enrolled. All participants underwent cognitive examinations (CDR, MMSE, ADAS-Cog 13, and verbal fluency) and odor discrimination tests (Sniffin' Sticks test, Burghart®, Germany). RESULTS: The MD-AD group achieved significantly worse scores on the olfactory discrimination test than the MCI-AD group, and the MCI-AD group achieved significantly worse results than the CN group (p < 0.05). A cut-off score of≤10 had a diagnostic accuracy of 94.44% (95% CI, 87.51-98.17%) in differentiating patients with MCI-AD/MD-AD from subjects with CN and of 91.67% (95% CI, 81.61-97.24%) in differentiating those with MCI-AD from subjects with CN. Our multinomial logistic regression model with demographic data and ADAS-Cog 13 scores as predictor variables correctly classified 82.2% of the cases (CN, 93.3%; MC-AD, 70%; MD-AD, 83.3%); on adding the olfactory discrimination score to the model, the percentage increased to 92.2% (CN, 96.7%; MCI-AD, 86.7%; MD-AD, 93.3%). CONCLUSION: Odor discrimination is impaired in cases of early AD and continues to deteriorate as the disease progresses. The olfactory discrimination test showed good diagnostic efficacy in detecting early AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neuropsychological Tests; Odorants; Olfaction Disorders; Smell

Pathogenomic Signature and Aberrant Neurogenic Events in Experimental Cerebral Ischemic Stroke: A Neurotranscriptomic-Based Implication for Dementia. - Roshan, Syed Aasish; Elangovan, Gayathri; Gunaseelan, Dharani; Jayachandran, Swaminathan K; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
BACKGROUND: Cerebral ischemic stroke is caused due to neurovascular damage or thrombosis, leading to neuronal dysfunction, neuroinflammation, neurodegeneration, and regenerative failure responsible for neurological deficits and dementia. The valid therapeutic targets against cerebral stroke remain obscure. Thus, insight into neuropathomechanisms resulting from the aberrant expression of genes appears to be crucial. OBJECTIVE: In this study, we have elucidated how neurogenesis-related genes are altered in experimental stroke brains from the available transcriptome profiles in correlation with transcriptome profiles of human postmortem stroke brain tissues. METHODS: The transcriptome datasets available on the middle cerebral artery occlusion (MCAo) rat brains were obtained from the Gene Expression Omnibus, National Center for Biotechnology Information. Of the available datasets, 97 samples were subjected to the meta-analysis using the network analyst tool followed by Cytoscape-based enrichment mapping analysis. The key differentially expressed genes (DEGs) were validated and compared with transcriptome profiling of human stroke brains. RESULTS: Results revealed 939 genes are differently expressed in the brains of the MCAo rat model of stroke, in which 30 genes are key markers of neural stem cells, and regulators of neurogenic processes. Its convergence with DEGs from human stroke brains has revealed common targets. CONCLUSION: This study has established a panel of highly important DEGs to signify the potential therapeutic targets for neuroregenerative strategy against pathogenic events associated with cerebral stroke. The outcome of the findings can be translated to mitigate neuroregeneration failure seen in various neurological and metabolic disease manifestations with neurocognitive impairments.
Keywords: Animals; Brain; Dementia; Humans; Infarction, Middle Cerebral Artery; Ischemic Stroke; Neurogenesis; Rats; Stroke

Pathological and Therapeutic Advances in Parkinson's Disease: Mitochondria in the Interplay. - Naren, Padmashri; Cholkar, Anjali; Kamble, Suchita; Khan, Sabiya Samim; Srivastava, Saurabh; Madan, Jitender; Mehra, Neelesh; Tiwari, Vinod; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative illness majorly affecting the population between the ages of 55 to 65 years. Progressive dopaminergic neuronal loss and the collective assemblage of misfolded alpha-synuclein in the substantia nigra, remain notable neuro-pathological hallmarks of the disease. Multitudes of mechanistic pathways have been proposed in attempts to unravel the pathogenesis of PD but still, it remains elusive. The convergence of PD pathology is found in organelle dysfunction where mitochondria remain a major contributor. Mitochondrial processes like bioenergetics, mitochondrial dynamics, and mitophagy are under strict regulation by the mitochondrial genome and nuclear genome. These processes aggravate neurodegenerative activities upon alteration through neuroinflammation, oxidative damage, apoptosis, and proteostatic stress. Therefore, the mitochondria have grabbed a central position in the patho-mechanistic exploration of neurodegenerative diseases like PD. The management of PD remains a challenge to physicians to date, due to the variable therapeutic response of patients and the limitation of conventional chemical agents which only offer symptomatic relief with minimal to no disease-modifying effect. This review describes the patho-mechanistic pathways involved in PD not only limited to protein dyshomeostasis and oxidative stress, but explicit attention has been drawn to exploring mechanisms like organelle dysfunction, primarily mitochondria and mitochondrial genome influence, while delineating the newer exploratory targets such as GBA1, GLP, LRRK2, and miRNAs and therapeutic agents targeting them.
Keywords: Aged; alpha-Synuclein; Humans; Mitochondria; Oxidative Stress; Parkinson Disease

Patterns of Aging Changes in Bodyweight May Predict Alzheimer's Disease. - Ukraintseva, Svetlana; Duan, Hongzhe; Holmes, Rachel; Bagley, Olivia; Wu, Deqing; Yashkin, Arseniy; Kulminski, Alexander; Akushevich, Igor; Whitson, Heather; Stallard, Eric; Yashin, Anatoliy; Arbeev, Konstantin (J Alzheimers Dis, 2023)
Relationships between patterns of aging-changes in bodyweight and AD are not fully understood. We compared mean age-trajectories of weight between those who did and did not develop late-onset-AD, and evaluated impact of age at maximum weight (AgeMax), and slope of decline in weight, on AD risk. Women with late-onset-AD had lower weight three or more decades before AD onset, and ∼10 years younger AgeMax, compared to AD-free women. APOE4 carriers had younger AgeMax and steeper slope. Older AgeMax and flatter slope predicted lower AD risk. Premature decline in weight could be a sign of accelerated physical aging contributing to AD.

The PI3K/AKT Signaling Pathway and Caspase-3 in Alzheimer's Disease: Which One Is the Beginner? - Khezri, Mohammad Rafi; Ghasemnejad-Berenji, Morteza; Moloodsouri, Donya (J Alzheimers Dis, 2023)
One of the main players in apoptosis during Alzheimer's disease progression are different members of caspase family of proteases. The most well-known member of this family is caspase-3, in which alterations of its levels have been detected in samples from Alzheimer's disease patients. There are numerous intracellular factors involved in regulation of cellular apoptosis through regulation of caspase-3 activity, the most important of which is the PI3K/AKT signaling pathway. This commentary tries to highlight the probable relations between PI3K/AKT signaling pathway and caspase-3 in Alzheimer's disease.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Humans; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Signal Transduction

Plasma ApoE4 Levels Are Lower than ApoE2 and ApoE3 Levels, and Not Associated with Plasma Aβ 40/42 Ratio as a Biomarker of Amyloid-β Amyloidosis in Alzheimer's Disease. - Nakamura, Takumi; Kawarabayashi, Takeshi; Ueda, Tetsuya; Shimomura, Sachiko; Hoshino, Masaki; Itoh, Ken; Ihara, Kazushige; Nakaji, Shigeyuki; Takatama, Masamitsu; Ikeda, Yoshio; Shoji, Mikio (J Alzheimers Dis, 2023)
BACKGROUND: APOE4 is the strongest risk factor for Alzheimer's disease (AD). However, limited information is currently available on APOE4 and the pathological role of plasma apolipoprotein E (ApoE) 4 remains unclear. OBJECTIVE: The aims of the present study were to measure plasma levels of total ApoE (tE), ApoE2, ApoE3, and ApoE4 using mass spectrometry and elucidate the relationships between plasma ApoE and blood test items. METHODS: We herein examined plasma levels of tE, ApoE2, ApoE3, and ApoE4 in 498 subjects using liquid chromatograph-mass spectrometry (LC-MS/MS). RESULTS: Among 498 subjects, mean age was 60 years and 309 were female. tE levels were distributed as ApoE2/E3 = ApoE2/E4 >ApoE3/E3 = ApoE3/E4 >ApoE4/E4. In the heterozygous group, ApoE isoform levels were distributed as ApoE2 >ApoE3 >ApoE4. ApoE levels were not associated with aging, the plasma amyloid-β (Aβ) 40/42 ratio, or the clinical diagnosis of AD. Total cholesterol levels correlated with the level of each ApoE isoform. ApoE2 levels were associated with renal function, ApoE3 levels with low-density lipoprotein cholesterol and liver function, and ApoE4 levels with triglycerides, high-density lipoprotein cholesterol, body weight, erythropoiesis, and insulin metabolism. CONCLUSION: The present results suggest the potential of LC-MS/MS for the phenotyping and quantitation of plasma ApoE. Plasma ApoE levels are regulated in the order of ApoE2 >ApoE3 >ApoE4 and are associated with lipids and multiple metabolic pathways, but not directly with aging or AD biomarkers. The present results provide insights into the multiple pathways by which peripheral ApoE4 influences the progression of AD and atherosclerosis.

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Plasma Soluble ST2 Levels Are Higher in Neurodegenerative Disorders and Associated with Poorer Cognition. - Tan, Yi Jayne; Siow, Isabel; Saffari, Seyed Ehsan; Ting, Simon K S; Li, Zeng; Kandiah, Nagaendran; Tan, Louis C S; Tan, Eng King; Ng, Adeline S L (J Alzheimers Dis, 2023)
BACKGROUND: Suppressor of tumorgenicity 2 (ST2) is highly expressed in brain tissue and is a receptor for interleukin 33 (IL-33). ST2 exists in two forms, a transmembrane receptor (ST2L) and a soluble decoy receptor (sST2). IL-33 binds to ST2L, triggering downstream signaling pathways involved in amyloid plaque clearance. Conversely, sST2 binds competitively to IL-33, attenuating its neuroprotective effects. High sST2 levels have been reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD), suggesting that the IL-33/ST2 signaling pathway may be implicated in neurodegenerative diseases. OBJECTIVE: To investigate plasma sST2 levels in controls and patients with MCI, AD, frontotemporal dementia (FTD), and Parkinson's disease (PD). METHODS: Plasma sST2 levels were measured using ELISA in 397 subjects (91 HC, 46 MCI, 38 AD, 28 FTD, and 194 PD). Cerebrospinal fluid (CSF) levels of sST2 were measured in 22 subjects. Relationship between sST2 and clinical outcomes were analyzed. RESULTS: Plasma sST2 levels were increased across all disease groups compared to controls, with highest levels seen in FTD followed by AD and PD. Dementia patients with higher sST2 had lower cross-sectional cognitive scores in Frontal Assessment Battery and Digit Span Backward. At baseline, PD-MCI patients had higher sST2, associated with worse attention. In the longitudinal PD cohort, higher sST2 significantly associated with decline in global cognition and visuospatial domains. Plasma sST2 levels correlated with CSF sST2 levels. CONCLUSION: Plasma sST2 is raised across neurodegenerative diseases and is associated with poorer cognition. Higher baseline sST2 is a potential biomarker of disease severity in neurodegeneration.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cross-Sectional Studies; Frontotemporal Dementia; Humans; Interleukin-1 Receptor-Like 1 Protein; Interleukin-33; Parkinson Disease

Post-Translational Chemical Modifications of Amyloid-β Peptides by 4-Hydroxy-2-Nonenal. - Kikuchi, Hiroyuki; Takahashi, Miki; Komatsu, Hiroaki; Axelsen, Paul H (J Alzheimers Dis, 2023)
BACKGROUND: The extraction and quantification of amyloid-β (Aβ) peptides in brain tissue commonly uses formic acid (FA) to disaggregate Aβ fibrils. However, it is not clear whether FA can disaggregate post-translationally modified Aβ peptides, or whether it induces artifact by covalent modification during disaggregation. Of particular interest are Aβ peptides that have been covalently modified by 4-hydroxy-2-nonenal (HNE), an oxidative lipid degradation product produced in the vicinity of amyloid plaques that dramatically accelerates the aggregation of Aβ peptides. OBJECTIVE: Test the ability of FA to disaggregate Aβ peptides modified by HNE and to induce covalent artifacts. METHODS: Quantitative liquid-chromatography-tandem-mass spectrometry of monomeric Aβ peptides and identify covalently modified forms. RESULTS: FA disaggregated ordinary Aβ fibrils but also induced the time-dependent formylation of at least 2 residue side chains in Aβ peptides, as well as oxidation of its methionine side chain. FA was unable to disaggregate Aβ peptides that had been covalently modified by HNE. CONCLUSION: The inability of FA to disaggregate Aβ peptides modified by HNE prevents FA-based approaches from quantifying a pool of HNE-modified Aβ peptides in brain tissue that may have pathological significance.

Posttraumatic Stress and Traumatic Brain Injury: Cognition, Behavior, and Neuroimaging Markers in Vietnam Veterans. - Marcolini, Sofia; Rojczyk, Philine; Seitz-Holland, Johanna; Koerte, Inga K; Alosco, Michael L; Bouix, Sylvain (J Alzheimers Dis, 2023)
BACKGROUND: Posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) are common in Veterans and linked to behavioral disturbances, increased risk of cognitive decline, and Alzheimer's disease. OBJECTIVE: We studied the synergistic effects of PTSD and TBI on behavioral, cognitive, and neuroimaging measures in Vietnam war Veterans. METHODS: Data were acquired at baseline and after about one-year from male Veterans categorized into: PTSD, TBI, PTSD+TBI, and Veteran controls without PTSD or TBI. We applied manual tractography to examine white matter microstructure of three fiber tracts: uncinate fasciculus (N = 91), cingulum (N = 87), and inferior longitudinal fasciculus (N = 95). ANCOVAs were used to compare Veterans' baseline behavioral and cognitive functioning (N = 285), white matter microstructure, amyloid-β (N = 230), and tau PET (N = 120). Additional ANCOVAs examined scores' differences from baseline to follow-up. RESULTS: Veterans with PTSD and PTSD+TBI, but not Veterans with TBI only, exhibited poorer behavioral and cognitive functioning at baseline than controls. The groups did not differ in baseline white matter, amyloid-β, or tau, nor in behavioral and cognitive functioning, and tau accumulation change. Progression of white matter abnormalities of the uncinate fasciculus in Veterans with PTSD compared to controls was observed; analyses in TBI and PTSD+TBI were not run due to insufficient sample size. CONCLUSIONS: PTSD and PTSD+TBI negatively affect behavioral and cognitive functioning, while TBI does not contribute independently. Whether progressive decline in uncinate fasciculus microstructure in Veterans with PTSD might account for cognitive decline should be further studied. Findings did not support an association between PTSD, TBI, and Alzheimer's disease pathology based on amyloid and tau PET.

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Progression from Prodromal Alzheimer's Disease to Mild Alzheimer's Disease Dementia in the Verubecestat APECS Study: Adjudicating Diagnostic Transitions. - Voss, Tiffini; Kost, James; Mercer, Swati Pal; Furtek, Christine; Randolph, Christopher; Lines, Christopher; Egan, Michael F; Cummings, Jeffrey L (J Alzheimers Dis, 2023)
BACKGROUND: Delay of progression from prodromal Alzheimer's disease (AD) to dementia is an important outcome in AD trials. Centralized adjudication is intended to improve the consistency of dementia diagnosis but has not been scrutinized. OBJECTIVE: To evaluate centralized adjudication for determining progression to dementia compared with Site Investigator opinion or change in Clinical Dementia Rating (CDR). METHODS: We used data from the 2-year APECS trial of verubecestat versus placebo in 1,451 prodromal AD participants. Cases were triggered for central adjudication if: 1) the Site Investigator judged the participant had progressed to dementia, or 2) the participant's CDR sum-of-boxes score increased ≥2 points from baseline. Post-hoc analyses were performed on pooled treatment-group data to compare methods of assessing progression. RESULTS: 581/1,451 (40% ) participants had changes triggering adjudication and most (83% ) were confirmed as progression to dementia. Only 66% of those who met CDR criteria (regardless of whether they also met Site Investigator criteria) were adjudicated to have progressed to dementia and just 15% of those who met only CDR criteria were adjudicated to have progressed, representing 5% of progressors. In contrast, 99% of those who met Site Investigator criteria (regardless of whether they also met CDR criteria) were adjudicated to have progressed, and the same was true for those who met only Site Investigator criteria. CONCLUSION: A positive Site Investigator opinion is an excellent predictor for a positive adjudication decision regarding onset of dementia. Conversely, sole use of CDR sum-of-boxes change ≥2 is inadequate. The benefit of centralized adjudication appears doubtful.

Psychopharmacological Medication Use in Frontotemporal Dementia at the Time of Diagnosis: Comparison with Alzheimer's Disease. - Katisko, Kasper; Krüger, Johanna; Soppela, Helmi; Hartikainen, Päivi; Haapasalo, Annakaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2023)
BACKGROUND: Due to the significant presence of neuropsychiatric symptoms in patients with frontotemporal dementia (FTD) spectrum disorders, psychiatric misdiagnoses, diagnostic delay, and use of psychiatric treatments are common prior to the FTD diagnosis. Furthermore, treatment of diagnosed FTD patients mainly relies on off-label psychopharmacological approaches. Currently, limited real-world data are available regarding the actual use of psychopharmacological medications in FTD. OBJECTIVE: To evaluate psychopharmacological medication use at the time of FTD diagnosis. METHODS: Psychopharmacological medication use was evaluated in a Finnish FTD cohort containing 222 FTD patients, including the major clinical disease phenotypes (behavioral, language, and motor variants) and genetic patients carrying the C9orf72 repeat expansion. A cohort of 214 Alzheimer's disease (AD) patients was used as a neurodegenerative disease reference group. RESULTS: Active use of psychopharmacological medications at the time of diagnosis was significantly more common in FTD compared to AD, especially in the case of antidepressants (26.1% versus 15.0%, OR = 2.01, p = 0.008), antipsychotics (23.9% versus 9.3%, OR = 3.15, p < 0.001), and mood-stabilizers (6.3% versus 1.9%, OR = 2.93, p = 0.085; not statistically significant), whereas the use of cholinesterase inhibitors or memantine was nearly nonexistent in FTD patients. Female gender and behavioral variant of FTD phenotype alongside with depressive and psychotic symptoms were the most prominent factors associating with the use of these medications among the FTD spectrum patients. CONCLUSION: Use of off-label psychopharmacological medication and polypharmacy is substantially common at the time of FTD diagnosis. This likely reflects the challenges in using symptom-driven treatment approaches, especially prior to the eventual diagnosis.
Keywords: Alzheimer Disease; Delayed Diagnosis; Female; Frontotemporal Dementia; Humans; Memantine; Neurodegenerative Diseases

Racial/Ethnic Disparities in Misidentification of Dementia in Medicare Claims: Results from the Washington Heights-Inwood Columbia Aging Project. - Zhu, Carolyn W; Gu, Yian; Cosentino, Stephanie; Kociolek, Anton J; Hernandez, Michelle; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: Misidentification of dementia in Medicare claims is quite common. OBJECTIVE: We examined potential race/ethnic disparities in misidentification of dementia in Medicare claims in a diverse cohort of older adults who underwent careful clinical assessment. METHODS: Participants were enrolled the Washington Heights-Inwood Columbia Aging Project (WHICAP), a multiethnic, population-based, prospective study of cognitive aging in which dementia status was assessed using a rigorous clinical protocol. ICD-9-CM and ICD-10-CM diagnosis codes in all available Medicare claims (1999-2019) were compared to clinical dementia diagnosis and categorized into three mutually exclusive groups: 1) congruent-, 2) over-, and 3) under- identification during the study period. Multinomial logistic regression model was used to examine the relationship between race (White, African American/Black, other) and ethnicity (Hispanic/Latinx, non-Hispanic/Latinx) and congruency of dementia identification after controlling for clinical (cognition, function, comorbidities) and demographic characteristics (age, sex, education), and inpatient and outpatient utilization. RESULTS: Across all person-years, 88.4% had congruent identification of dementia compared to clinical diagnosis, in 4.1% of the times participants were over-identified with dementia, and 7.5% of the times the participants were under-identified. Rates of misidentification was higher in minority participants than in White, non-Hispanic participants. Multivariable estimation results showed that the probability of over-identification with dementia was 2.2% higher for African American/Black than White (p = 0.05) and 2.7% higher for Hispanic participants than non-Hispanics (p = 0.03) participants. Differences in under-identification by race/ethnicity were not statistically significant. CONCLUSIONS: African American/Black and Hispanic participants were more likely over-identified with dementia in Medicare claims.

Resveratrol Mediated Regulation of Hippocampal Neuroregenerative Plasticity via SIRT1 Pathway in Synergy with Wnt Signaling: Neurotherapeutic Implications to Mitigate Memory Loss in Alzheimer's Disease. - Surya, Kumar; Manickam, Nivethitha; Jayachandran, Kesavan Swaminathan; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a major form of dementia. Abnormal amyloidogenic event-mediated degeneration of cholinergic neurons in the cognitive centers of the brain has been attributed to neuropathological sequelae and behavioral deficits in AD. Besides, impaired adult neurogenesis in the hippocampus has experimentally been realized as an underlying cause of dementia regardless of neurodegeneration. Therefore, nourishing the neurogenic process in the hippocampus has been considered an effective therapeutic strategy to mitigate memory loss. In the physiological state, the Wnt pathway has been identified as a potent mitogenic generator in the hippocampal stem cell niche. However, downstream components of Wnt signaling have been noticed to be downregulated in AD brains. Resveratrol (RSV) is a potent Sirtuin1 (SIRT1) enhancer that facilitates neuroprotection and promotes neurogenesis in the hippocampus of the adult brain. While SIRT1 is an important positive regulator of Wnt signaling, ample reports indicate that RSV treatment strongly mediates the fate determination of stem cells through Wnt signaling. However, the possible therapeutic roles of RSV-mediated SIRT1 enhancement on the regulation of hippocampal neurogenesis and reversal of memory loss through the Wnt signaling pathway have not been addressed yet. Taken together, this review describes RSV-mediated effects on the regulation of hippocampal neurogenesis via the activation of SIRT1 in synergy with the Wnt signaling. Further, the article emphasizes a hypothesis that RSV treatment can provoke the activation of quiescent neural stem cells and prime their neurogenic capacity in the hippocampus via Wnt signaling in AD.
Keywords: Alzheimer Disease; Amnesia; Hippocampus; Humans; Neurogenesis; Resveratrol; Sirtuin 1; Wnt Signaling Pathway

Retinal Functional and Structural Neural Indices: Potential Biomarkers for the Monitoring of Cerebral Neurodegeneration: The Maastricht Study. - van der Heide, Frank C T; Mokhtar, Sara; Khanna, Anjani; Said, Mozhda; Henry, Ronald M A; Kroon, Abraham A; Dagnelie, Pieter C; Eussen, Simone J P M; Berendschot, Tos T J M; Schouten, Jan S A G; Schram, Miranda T; van der Kallen, Carla J H; et al. (J Alzheimers Dis, 2023)
BACKGROUND: If retinal indices of neurodegeneration are to be biomarkers for the monitoring of cerebral neurodegeneration, it is important to establish whether potentially modifiable risk factors for dementia are associated with retinal neurodegenerative changes. OBJECTIVE: To study associations of dementia risk factors with retinal sensitivity, an index of retinal neural function, and retinal nerve fiber layer (RNFL) thickness, an index of retinal neural structure. METHODS: We used cross-sectional data from The Maastricht Study (up to 5,666 participants, 50.5% men, mean age 59.7), and investigated associations with regression analyses (adjusted for potential confounders). RESULTS: Most risk factors under study (i.e., hyperglycemia, unhealthy diet, lower cardiorespiratory fitness, smoking, alcohol consumption, and hypertension) were significantly associated with lower retinal sensitivity and lower RNFL thickness. CONCLUSION: Findings of this population-based study support the concept that retinal neural indices may be biomarkers for the monitoring of therapeutic strategies that aim to prevent early-stage cerebral neurodegeneration and, ultimately, dementia.

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Serotonin Degeneration and Amyloid-β Deposition in Mild Cognitive Impairment: Relationship to Cognitive Deficits. - Smith, Gwenn S; Kuwabara, Hiroto; Yan, Haijuan; Nassery, Najlla; Yoon, Mark; Kamath, Vidya; Kraut, Michael; Gould, Neda F; Savonenko, Alena; Coughlin, Jennifer M; Lodge, Martin; Pomper, Martin G; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neuropathological and neuroimaging studies have demonstrated degeneration of the serotonin system in Alzheimer's disease (AD). Neuroimaging studies have extended these observations to the preclinical stages of AD, mild cognitive impairment (MCI). Serotonin degeneration has been observed also in transgenic amyloid mouse models, prior to widespread cortical distribution of amyloid-β (Aβ). OBJECTIVE: The present study evaluated the regional distribution of the serotonin transporter (5-HTT) and of Aβ in individuals with MCI and healthy older controls, as well as the contribution of 5-HTT and Aβ to cognitive deficits. METHODS: Forty-nine MCI participants and 45 healthy older controls underwent positron emission tomography (PET) imaging of 5-HTT and Aβ, structural magnetic resonance imaging and neuropsychological assessments. RESULTS: Lower cortical, striatal, and limbic 5-HTT and higher cortical Aβ was observed in MCIs relative to healthy controls. Lower 5-HTT, mainly in limbic regions, was correlated with greater deficits in auditory-verbal and visual-spatial memory and semantic, not phonemic fluency. Higher cortical A β was associated with greater deficits in auditory-verbal and visual-spatial memory and in semantic, not phonemic fluency. When modeling the association between cognition, gray matter volumes and Aβ, inclusion of 5-HTT in limbic and in select cortical regions significantly improved model fit for auditory-verbal and visual-spatial memory and semantic, but not phonemic fluency. CONCLUSIONS: These results support the role of serotonin degeneration in the memory and semantic fluency deficits observed in MCI.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognition; Cognition Disorders; Cognitive Dysfunction; Humans; Mice; Positron-Emission Tomography; Serotonin

Superior Global Cognition in Oldest-Old Is Associated with Resistance to Neurodegenerative Pathologies: Results from The 90+ Study. - Biswas, Roshni; Kawas, Claudia; Montine, Thomas J; Bukhari, Syed A; Jiang, Luohua; Corrada, Maria M (J Alzheimers Dis, 2023)
BACKGROUND: Some oldest-old individuals can maintain superior cognition despite advanced age. Little is known about the neuropathological changes in the brains of oldest-old superior cognitive performers. OBJECTIVE: Our objective was to examine the associations between Alzheimer's disease (AD) and non-AD neuropathologic features in relation to superior cognitive performance in oldest-old individuals. METHODS: We analyzed brain autopsy data from 102 participants with normal cognition from The 90+ Study. Superior global cognitive performers (SGCP) were defined as having Mini-Mental State Examination (MMSE) score ≥28 in the last visit 12 to 2 months before death. To examine the associations between individual and multiple comorbid neuropathologic features with SGCP status we used multiple logistic regression models adjusting for age, sex, and education. RESULTS: Alzheimer's disease neuropathological change (ADNC) and low levels of vascular pathologic change were not associated with superior cognition. In contrast, participants with limbic (OR = 8.37; 95% CI: 1.48-47.44) and neocortical (OR = 10.80;95% CI: 1.03-113.82) Lewy body disease (LBD), or with hippocampal sclerosis (HS) (OR = 5.28; 95% CI: 1.10-25.47) were more likely to be non-SGCP. High total burden of multiple comorbid neuropathologic features was associated with a lower likelihood of being SGCP. CONCLUSION: Oldest-old superior cognitive performers were resilient to ADNC and low levels of vascular pathologic change and were resistant to non-AD neurodegenerative changes and multiple comorbid neuropathologic features. Understanding the factors underlying the ability of superior cognitive performers to resist these changes might provide useful insights on maintenance of superior cognition despite advanced age.

TDP-43 Pathology in the Setting of Intermediate and High Alzheimer's Disease Neuropathologic Changes: A Preliminary Evaluation Across Ethnoracial Groups. - Huie, Emily Z; Escudero, Anthony; Saito, Naomi; Harvey, Danielle; Nguyen, My-Le; Lucot, Katherine L; LaGrande, Jayne; Mungas, Dan; DeCarli, Charles; Lamar, Melissa; Schneider, Julie A; Kapasi, Alifiya; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Transactive Response DNA Binding Protein 43 kDa (TDP-43) pathology is frequently found in cases with Alzheimer's disease (AD). TDP-43 pathology is associated with hippocampal atrophy and greater AD severity denoted by cognition and clinical representation. Current TDP-43 pathology studies are predominantly based on non-Hispanic White cohorts. OBJECTIVE: We sought to evaluate the presence of TDP-43 pathology across ethnoracial groups utilizing the National Alzheimer's Coordinating Center; a database containing data from over 29 institutions across the United States. Cases (N = 1,135: Hispanics/Latinos = 29, African Americans/Black Americans = 51, Asians/Asian Americans = 10, American Indians/Alaskan Natives = 2, non-Hispanic White = 1,043) with intermediate/high AD having data on TDP-43 pathology in the amygdala, hippocampus, entorhinal cortex, and neocortex. METHODS: TDP-43 pathology frequency in each neuroanatomic region among ethnoracial groups were compared using generalized linear mixed effects models with center as a random effect adjusting for age at death, education, and gender. RESULTS: Although groups were imbalanced, there was no significant difference across ethnoracial groups based on TDP-43 pathology (p = 0.84). With respect to neuroanatomical regions evaluated, there were no significant differences across ethnoracial groups (p-values > 0.06). There were also no significant differences for age at death and gender ratios across ethnoracial groups based on TDP-43 pathology. Although not statistically significant, TDP-43 pathology was present less often in Hispanic/Latinos (34%) when compared to non-Hispanic Whites (46%). CONCLUSION: While this is a preliminary evaluation, it highlights the need for diverse cohorts and on TDP-43 pathology research across ethnoracial groups. This is the first study to our knowledge having a focus on the neuroanatomical distribution of TDP-43 deposits in Hispanic/Latino decedents with AD.

Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Understanding the Involvement of microRNAs in Mitochondrial Dysfunction and Their Role as Potential Biomarkers and Therapeutic Targets in Parkinson's Disease. - Tryphena, Kamatham Pushpa; Anuradha, Urati; Kumar, Rohith; Rajan, Shruti; Srivastava, Saurabh; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease, affecting the elderly worldwide and causing significant movement impairments. The goal of PD treatment is to restore dopamine levels in the striatum and regulate movement symptoms. The lack of specific biomarkers for early diagnosis, as well as medication aimed at addressing the pathogenic mechanisms to decelerate the progression of dopaminergic neurodegeneration, are key roadblocks in the management of PD. Various pathogenic processes have been identified to be involved in the progression of PD, with mitochondrial dysfunction being a major contributor to the disease's pathogenesis. The regulation of mitochondrial functions is influenced by a variety of factors, including epigenetics. microRNAs (miRNAs) are epigenetic modulators involved in the regulation of gene expression and regulate a variety of proteins that essential for proper mitochondrial functioning. They are found to be dysregulated in PD, as evidenced by biological samples from PD patients and in vitro and in vivo research. In this article, we attempt to provide an overview of several miRNAs linked to mitochondrial dysfunction and their potential as diagnostic biomarkers and therapeutic targets in PD.
Keywords: Aged; Biomarkers; Humans; MicroRNAs; Mitochondria; Neurodegenerative Diseases; Parkinson Disease

Untangling the Role of TREM2 in Conjugation with Microglia in Neuronal Dysfunction: A Hypothesis on a Novel Pathway in the Pathophysiology of Alzheimer's Disease. - Basha, Sk Chand; Ramaiah, Mekala Janaki; Kosagisharaf, Jagannatha Rao (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving heterogenous pathophysiological characteristics, which has become a challenge to therapeutics. The major pathophysiology of AD comprises amyloid-β (Aβ), tau, oxidative stress, and apoptosis. Recent studies indicate the significance of Triggering receptor expressed on myeloid cells 2 (TREM2) and its mutant variants in AD. TREM2 are the transmembrane receptors of microglial cells that performs a broad range of physiological cell processes. Phagocytosis of Aβ is one of the physiological roles of TREM2, which plays a pivotal role in AD progression. R47H, a mutant variant of TREM2, increases the risk of AD by impairing TREM2-Aβ binding. Inconclusive evidence regarding the TREM2 signaling cascade mechanism of Aβ phagocytosis motivates the current review to propose a new hypothesis. The review systematically assesses the cross talk between TREM2 and other AD pathological domains and the influence of TREM2 on amyloid and tau seeding. Disease associated microglia (DAM), a novel state of microglia with unique transcriptional and functional signatures reported in neurodegenerative conditions, also depend on the TREM2 pathway for its differentiation. DAM is suggested to have a neuroprotective role. We hypothesize that TREM2, along with its signaling adaptors and endogenous proteins, play a key role in ameliorating Aβ clearance. We indicate that TREM2 has the potential to ameliorate the Aβ burden, though with differential clearance ability and may act as a potential therapeutic target.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Membrane Glycoproteins; Microglia; Neurons; Receptors, Immunologic

Urinary Amino Acid-Conjugated Acrolein and Taurine as New Biomarkers for Detection of Dementia. - Yoshida, Madoka; Uemura, Takeshi; Mizoi, Mutsumi; Waragai, Masaaki; Sakamoto, Akihiko; Terui, Yusuke; Kashiwagi, Keiko; Igarashi, Kazuei (J Alzheimers Dis, 2023)
BACKGROUND: Dementia, including Alzheimer's disease (AD), is one of the serious diseases at advanced age, and its early detection is important for maintaining quality of life (QOL). OBJECTIVE: In this study, we sought novel biomarkers for dementia in urine. METHODS: Samples of urine were collected from 57 control subjects without dementia, 62 mild cognitive impairment (MCI) patients, and 42 AD patients. Mini-Mental State Examination (MMSE) was evaluated when subjects were examined by medical doctors. Urinary amino acid (lysine)-conjugated acrolein (AC-Acro) was measured using N ɛ -(3-formyl-3, 4-dehydropiperidine) lysine (FDP-Lys) ELISA kit, and taurine content was measured using a taurine assay kit. Values were normalized by creatinine content which was measured with the colorimetric assay kit. RESULTS: We found that urinary amino acid (lysine)-conjugated acrolein (AC-Acro) and taurine negatively correlated with MMSE score and are significantly lower in dementia patients compared to the normal subjects. When AC-Acro and taurine were evaluated together with age using an artificial neural network model, median relative risk values for subjects with AD, subjects with mild cognitive impairment, and control subjects were 0.96, 0.53, and 0.06, respectively. CONCLUSION: Since urine is relatively easy to collect, our findings provide a novel biomarker for dementia without invasiveness.

Vacuolar Protein-Sorting Proteins Are Reduced Even Before Cognitive Decline in a Mouse Model of Alzheimer's Disease. - Shinagawa, Hijiri; Ohuchi, Kazuki; Goto, Yuya; Hashimoto, Kohei; Kijima, Hideki; Maekawa, Shogo; Kurita, Hisaka; Inden, Masatoshi (J Alzheimers Dis, 2023)
Currently, interventions from the preclinical stage are considered necessary for the treatment of Alzheimer's disease (AD). Previous studies have reported that vacuolar protein-sorting protein (VPS), a retromer construct, is involved in the pathogenic mechanisms of AD and Parkinson's disease. This study evaluated VPS26, VPS29, and VPS35 before and after the onset of cognitive decline in an App knock-in mouse model of AD that more closely resembles the human pathology than previous AD models. The results showed that the expression of VPS26 and VPS35 decreased before the onset of cognitive decline, suggesting the possibility of anti-amyloid-β disease-modifying treatment targeting these proteins.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Humans; Mice; Protein Transport; Vesicular Transport Proteins

Validation of a Multivariate Prediction Model of the Clinical Progression of Alzheimer's Disease in a Community-Dwelling Multiethnic Cohort. - Stallard, Eric; Kociolek, Anton; Jin, Zhezhen; Ryu, Hyunnam; Lee, Seonjoo; Cosentino, Stephanie; Zhu, Carolyn; Gu, Yian; Fernandez, Kayri; Hernandez, Michelle; Kinosian, Bruce; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: The major aims of the three Predictors Studies have been to further our understanding of Alzheimer's disease (AD) progression sufficiently to predict the length of time from disease onset to major disease outcomes in individual patients with AD. OBJECTIVES: To validate a longitudinal Grade of Membership (L-GoM) prediction algorithm developed using clinic-based, mainly white patients from the Predictors 2 Study in a statistically representative community-based sample of Hispanic (N = 211) and non-Hispanic (N = 62) older adults (with 60 males and 213 females) from the Predictors 3 Study and extend the algorithm to mild cognitive impairment (MCI). METHODS: The L-GoM model was applied to data collected at the initial Predictors 3 visit for 150 subjects with AD and 123 with MCI. Participants were followed annually for up to seven years. Observed rates of survival and need for full-time care (FTC) were compared to those predicted by the algorithm. RESULTS: Initial MCI/AD severity in Predictors 3 was substantially higher than among clinic-based AD patients enrolled at the specialized Alzheimer's centers in Predictors 2. The observed survival and need for FTC followed the L-GoM model trajectories in individuals with MCI or AD, except for N = 32 subjects who were initially diagnosed with AD but reverted to a non-AD diagnosis on follow-up. CONCLUSION: These findings indicate that the L-GoM model is applicable to community-dwelling, multiethnic older adults with AD. They extend the use of the model to the prediction of outcomes for MCI. They also justify release of our L-GoM calculator at this time.

Alteration of Gut Microbiota in Alzheimer's Disease and Their Relation to the Cognitive Impairment. - Khedr, Eman M; Omeran, Nehad; Karam-Allah Ramadan, Haidi; Ahmed, Gellan K; Abdelwarith, Ahmed M (J Alzheimers Dis, 2022)
BACKGROUND: Dysbiosis of gut microbiota has been reported to be enrolled in the pathogenesis of Alzheimer's disease (AD). However, there is a lack of relevant studies on this topic in Egyptian patients with AD. OBJECTIVE: To investigate different species of gut microbiota in Egyptian patients with AD and correlate microbiota bacterial abundance with clinical data. METHODS: The study included 25 patients with AD and 25 healthy volunteers as age and sex-matched controls. Clinical data was taken for each patient, including medical history and examination; Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were assessed for each participant. Bacterial DNA was extracted from stool, and abundance quantified via qPCR using 16S rRNA group-specific primers. RESULTS: Akkermansia, Enterobacteria, Bacteroidetes, Bacillus cereus, Prevotella, and Clostridium cluster IV were more abundant in the AD group than in the control group, although there was significantly less abundance of Bifidobacterium spp., Firmicutes, and Actinobacteria in patients with AD than in controls, whereas no such significance was found for lactic acid bacteria between both groups. Lactic acid bacteria and Prevotella abundance was negatively correlated with cognitive impairment (p = 0.03 with MMSE, and p = 0.03 with MoCA). Prevotella abundance was positively correlated with age of onset and duration of illness and negatively correlated with smoking and coronary heart disease (p = 0.007, p = 0.03, p = 0.035, and p = 0.047, respectively). CONCLUSION: The current work highlighted a significant relationship between AD and gut microbiota dysbiosis. A higher abundance of Prevotella species and lactic acid bacteria was correlated with cognition.
Keywords: Alzheimer Disease; Bacteria; Cognitive Dysfunction; Dysbiosis; Gastrointestinal Microbiome; Humans; RNA, Ribosomal, 16S

Alzheimer's Disease Diagnostics Using miRNA Biomarkers and Machine Learning. - Xu, Amy; Kouznetsova, Valentina L; Tsigelny, Igor F (J Alzheimers Dis, 2022)
BACKGROUND: The current standard for Alzheimer's disease (AD) diagnosis is often imprecise, as with memory tests, and invasive or expensive, as with brain scans. However, the dysregulation patterns of miRNA in blood hold potential as useful biomarkers for the non-invasive diagnosis and even treatment of AD. OBJECTIVE: The goal of this research is to elucidate new miRNA biomarkers and create a machine-learning (ML) model for the diagnosis of AD. METHODS: We utilized pathways and target gene networks related to confirmed miRNA biomarkers in AD diagnosis and created multiple models to use for diagnostics based on the significant differences among miRNA expression between blood profiles (serum and plasma). RESULTS: The best performing serum-based ML model, trained on filtered disease-specific miRNA datasets, was able to identify miRNA biomarkers with 92.0% accuracy and the best performing plasma-based ML model, trained on filtered disease-specific miRNA datasets, was able to identify miRNA biomarkers with 90.9% accuracy. Through analysis of AD implicated miRNA, thousands of descriptors reliant on target gene and pathways were created which can then be used to identify novel biomarkers and strengthen disease diagnosis. CONCLUSION: Development of a ML model including miRNA and their genomic and pathway descriptors made it possible to achieve considerable accuracy for the prediction of AD.

Alzheimer's Disease: Key Insights from Two Decades of Clinical Trial Failures. - Kim, C Kwon; Lee, Yin Rui; Ong, Lynnett; Gold, Michael; Kalali, Amir; Sarkar, Joydeep (J Alzheimers Dis, 2022)
Given the acknowledged lack of success in Alzheimer's disease (AD) drug development over the past two decades, the objective of this review was to derive key insights from the myriad failures to inform future drug development. A systematic and exhaustive review was performed on all failed AD compounds for dementia (interventional phase II and III clinical trials from ClinicalTrials.gov) from 2004 to the present. Starting with the initial ∼2,700 AD clinical trials, ∼550 trials met our initial criteria, from which 98 unique phase II and III compounds with various mechanisms of action met our criteria of a failed compound. The two recent reported phase III successes of aducanumab and oligomannate are very encouraging; however, we are awaiting real-world validation of their effectiveness. These two successes against the 98 failures gives a 2.0% phase II and III success rate since 2003, when the previous novel compound was approved. Potential contributing methodological factors for the clinical trial failures were categorized into 1) insufficient evidence to initiate the pivotal trials, and 2) pivotal trial design shortcomings. Our evaluation found that rational drug development principles were not always followed for AD therapeutics development, and the question remains whether some of the failed compounds may have shown efficacy if the principles were better adhered to. Several recommendations are made for future AD therapeutic development. The whole database of the 98 failed compounds is presented in the Supplementary Material.
Keywords: Alzheimer Disease; Humans

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Association Between Plasma Biomarkers of Amyloid, Tau, and Neurodegeneration with Cerebral Microbleeds. - McCarter, Stuart J; Lesnick, Timothy G; Lowe, Val J; Rabinstein, Alejandro A; Przybelski, Scott A; Algeciras-Schimnich, Alicia; Ramanan, Vijay K; Jack, Clifford R; Petersen, Ronald C; Knopman, David S; Boeve, Bradley F; Kantarci, Kejal; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral microbleeds (CMBs) are a common vascular pathology associated with future intracerebral hemorrhage. Plasma biomarkers of amyloid, tau, and neurodegeneration may provide a screening avenue to identify those with CMBs, but evidence is conflicting. OBJECTIVE: To determine the association between plasma biomarkers (Aβ40, Aβ42, t-tau, p-tau181, p-tau217, neurofilament light chain (NfL)) and CMBs in a population-based study of aging and whether these biomarkers predict higher signal on Aβ-PET imaging in patients with multiple CMBs. METHODS: 712 participants from the Mayo Clinic Study of Aging with T2 * GRE MRI and plasma biomarkers were included. Biomarkers were analyzed utilizing Simoa (Aβ40, Aβ42, t-tau, NfL) or Meso Scale Discovery (p-tau181, p-tau217) platforms. Cross-sectional associations between CMBs, plasma biomarkers and Aβ-PET were evaluated using hurdle models and multivariable regression models. RESULTS: Among the 188 (26%) individuals with≥1 CMB, a lower plasma Aβ42/Aβ40 ratio was associated with more CMBs after adjusting for covariables (IRR 568.5 95% CI 2.8-116,127). No other biomarkers were associated with risk or number CMBs. In 81 individuals with≥2 CMBs, higher plasma t-tau, p-tau181, and p-tau217 all were associated with higher Aβ-PET signal, with plasma p-tau217 having the strongest predictive value (r2 0.603, AIC -53.0). CONCLUSION: Lower plasma Aβ42/Aβ40 ratio and higher plasma p-tau217 were associated with brain amyloidosis in individuals with CMBs from the general population. Our results suggest that in individuals with multiple CMBs and/or lobar intracranial hemorrhage that a lower plasma Aβ42/Aβ40 ratio or elevated p-tau217 may indicate underlying cerebral amyloid angiopathy.

Association of Alzheimer's Disease with COVID-19 Susceptibility and Severe Complications: A Nationwide Cohort Study. - Chung, Seok Jong; Chang, Yoonkyung; Jeon, Jimin; Shin, Jae Il; Song, Tae-Jin; Kim, Jinkwon (J Alzheimers Dis, 2022)
BACKGROUND: Identification of patients at high susceptibility and high risk of developing serious complications related to coronavirus disease 2019 (COVID-19) infection is clinically important in the face of the COVID-19 pandemic. OBJECTIVE: To investigate whether patients with Alzheimer's disease (AD) are more susceptible to COVID-19 infection and whether they have a higher risk of developing serious complications. METHODS: We retrospectively reviewed the Korean nationwide population-based COVID-19 dataset for participants who underwent real-time reverse transcription polymerase chain reaction assays for COVID-19 between January 1 and June 4, 2020. A 1 : 3 ratio propensity score matching and binary logistic regression analysis were performed to investigate the association between AD and the susceptibility or severe complications (i.e., mechanical ventilation, intensive care unit admission, or death) of COVID-19. RESULTS: Among 195,643 study participants, 5,725 participants had AD and 7,334 participants were diagnosed with COVID-19. The prevalence of participants testing positive for COVID-19 did not differ according to the presence of AD (p = 0.234). Meanwhile, AD was associated with an increased risk of severe COVID-19 complications (OR 2.25 [95% CI 1.54-3.28]). Secondary outcome analyses showed that AD patients had an increased risk for mortality (OR 3.09 [95% CI 2.00-4.78]) but were less likely to receive mechanical ventilation (OR 0.42 [95% CI 0.20-0.87]). CONCLUSION: AD was not associated with increased susceptibility to COVID-19 infection, but was associated with severe COVID-19 complications, especially with mortality. Early diagnosis and active intervention are necessary for patients with AD suspected COVID-19 infection.
Keywords: Alzheimer Disease; Cohort Studies; COVID-19; Humans; Pandemics; Retrospective Studies; SARS-CoV-2

Association of Aspirin Use with Reduced Risk of Developing Alzheimer's Disease in Elderly Ischemic Stroke Patients: A Retrospective Cohort Study. - Gorenflo, Maria P; Davis, Pamela B; Kendall, Ellen K; Olaker, Veronica R; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
BACKGROUND: Currently there are no effective therapies to prevent or halt the development of Alzheimer's disease (AD). Multiple risk factors are involved in AD, including ischemic stroke (IS). Aspirin is often prescribed following IS to prevent blood clot formation. Observational studies have shown inconsistent findings with respect to the relationship between aspirin use and the risk of AD. OBJECTIVE: To investigate the relationship between aspirin therapy after IS and the new diagnosis of AD in elderly patients. METHODS: This retrospective cohort study leveraged a large database that contains over 90 million electronic health records to compare the hazard rates of AD after IS in elderly patients prescribed aspirin versus those not prescribed aspirin after propensity-score matching for relevant confounders. RESULTS: At 1, 3, and 5 years after first IS, elderly patients prescribed aspirin were less likely to develop AD than those not prescribed aspirin: Hazard Ratio = 0.78 [0.65,0.94], 0.8 1 [0.70,0.94], and 0.76 [0.70,0.92]. CONCLUSION: Our findings suggest that aspirin use may prevent AD in patients with IS, a subpopulation at high risk of developing the disease.

Association of Carotid Intima Media Thickening with Future Brain Region Specific Amyloid-β Burden. - Baradaran, Hediyeh; Peloso, Gina M; Polak, Joseph F; Killiany, Ronald J; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa; Romero, Jose R; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Carotid atherosclerosis is associated with cognitive impairment and dementia, though there is limited evidence of a direct link between carotid disease and amyloid-β (Aβ) burden. OBJECTIVE: We studied the association of baseline and progressive carotid intima media thickness (CIMT) with Aβ on 11C-Pittsburgh Compound B (PiB) to determine if those with carotid atherosclerosis would have higher Aβ burden. METHODS: We studied 47 participants from the Framingham Offspring cohort with carotid ultrasounds measuring CIMT at their 6th clinic examination (aged 49.5±5.7 years) and an average of 9.6 years later, and PiB imaging measuring Aβ on average 22.1 years post baseline. We used multivariate linear regression analyses to relate baseline, follow-up, mean, and progression of internal carotid artery (ICA) and common carotid artery (CCA) CIMT to Aβ in brain regions associated with Alzheimer's disease (AD) and related dementias (ADRD), adjusting for age, sex, and other vascular risk factors. RESULTS: Participants with higher mean ICA IMT had more Aβ in the precuneus (beta±standard error [β±SE]: 0.466±0.171 mm, p = 0.01) and the frontal, lateral, and retrosplenial regions (β±SE: 0.392±0.164 mm, p = 0.022) after adjusting for age, sex, vascular risk factors, and medication use. We did not find an association between any CCA IMT measures and Aβ or progression of ICA or CCA IMT and Aβ. CONCLUSION: Carotid atherosclerosis, as measured by ICA IMT, is associated with increased Aβ burden later in life. These findings support a link between vascular disease and AD/ADRD pathophysiology.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

Associations Between Brainstem Volume and Alzheimer's Disease Pathology in Middle-Aged Individuals of the Framingham Heart Study. - Jacobs, Heidi I L; O'Donnell, Adrienne; Satizabal, Claudia L; Lois, Cristina; Kojis, Daniel; Hanseeuw, Bernard J; Thibault, Emma; Sanchez, Justin S; Buckley, Rachel F; Yang, Qiong; DeCarli, Charles; Killiany, Ron; et al. (J Alzheimers Dis, 2022)
The brainstem is among the first regions to accumulate Alzheimer's disease (AD)-related hyperphosphorylated tau pathology during aging. We aimed to examine associations between brainstem volume and neocortical amyloid-β or tau pathology in 271 middle-aged clinically normal individuals of the Framingham Heart Study who underwent MRI and PET imaging. Lower volume of the medulla, pons, or midbrain was associated with greater neocortical amyloid burden. No associations were detected between brainstem volumes and tau deposition. Our results support the hypothesis that lower brainstem volumes are associated with initial AD-related processes and may signal preclinical AD pathology.

Associations Between Intrathecal Levels of Vitamin D, Cytokines, and Core Biomarkers of Alzheimer's Disease: A Cross-Sectional Study. - Soares, Jelena Zugic; Valeur, Jørgen; Šaltytė Benth, Jūratė; Knapskog, Anne-Brita; Selbæk, Geir; Bogdanovic, Nenad; Pettersen, Renate (J Alzheimers Dis, 2022)
BACKGROUND: Several studies have examined association between vitamin D levels in serum and cognition, but little is known of vitamin D levels in cerebrospinal fluid (CSF) and association with Alzheimer's disease (AD). OBJECTIVE: In this cross-sectional, explorative study we investigated possible associations of vitamin D in CSF with biomarkers for AD, amyloid-β, tau protein/phosphorylated tau protein in CSF, and with the cytokines IL-6, IL-8, and TNF-α in CSF in patients with cognitive impairment and cognitively healthy controls. METHODS: We included 100 outpatients ≥65 years referred for assessment of cognitive impairment and 76 age- and sex-matched cognitively healthy controls. Levels of 25-hydroxyvitamin D (25(OH)D), amyloid-β, tau protein and phosphorylated tau protein, as well as IL-6, IL-8, and TNF-α, were analyzed in CSF in both groups. RESULTS: Higher levels of 25(OH)D in CSF in all groups together were associated with lower levels of tau protein (p = 0.01) and phosphorylated tau protein (p = 0.005). We found no association between 25(OH)D levels in CSF and pathological levels of amyloid-β in CSF nor levels of IL-6 or TNF-α in CSF. Higher levels of 25(OH)D in CSF were associated with higher levels of IL-8 in CSF (p = 0.002). However, vitamin D explained only 6% of variance in IL-8. There was no significant difference between the patient groups and the control group regarding the association between 25(OH)D in CSF and any of the three cytokines in CSF. CONCLUSION: Participants with higher CSF levels of 25(OH)D exhibited reduced CSF levels of tau protein and phosphorylated tau protein.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Automated Early Detection of Alzheimer's Disease by Capturing Impairments in Multiple Cognitive Domains with Multiple Drawing Tasks. - Kobayashi, Masatomo; Yamada, Yasunori; Shinkawa, Kaoru; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2022)
BACKGROUND: Automatic analysis of the drawing process using a digital tablet and pen has been applied to successfully detect Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, most studies focused on analyzing individual drawing tasks separately, and the question of how a combination of drawing tasks could improve the detection performance thus remains unexplored. OBJECTIVE: We aimed to investigate whether analysis of the drawing process in multiple drawing tasks could capture different, complementary aspects of cognitive impairments, with a view toward combining multiple tasks to effectively improve the detection capability. METHODS: We collected drawing data from 144 community-dwelling older adults (27 AD, 65 MCI, and 52 cognitively normal, or CN) who performed five drawing tasks. We then extracted motion- and pause-related drawing features for each task and investigated the statistical associations of the features with the participants' diagnostic statuses and cognitive measures. RESULTS: The drawing features showed gradual changes from CN to MCI and then to AD, and the changes in the features for each task were statistically associated with cognitive impairments in different domains. For classification into the three diagnostic categories, a machine learning model using the features from all five tasks achieved a classification accuracy of 75.2%, an improvement by 7.8% over that of the best single-task model. CONCLUSION: Our results demonstrate that a common set of drawing features from multiple drawing tasks can capture different, complementary aspects of cognitive impairments, which may lead to a scalable way to improve the automated detection of AD and MCI.

B Vitamin Supplementation Slows Cognitive Decline in Mild Cognitive Impairment Patients with Frontal Lobe Atrophy. - Gong, Xianmin; Shi, Lin; Wu, Yuanyuan; Luo, Yishan; Kwok, Timothy (J Alzheimers Dis, 2022)
BACKGROUND: The effects of B vitamins on mild cognitive impairment (MCI) patients' cognition have been mixed, suggesting the existence of moderating factors. OBJECTIVE: A post hoc analysis of a negative B vitamin trial was performed to examine the potential modulating effect of regional brain atrophy on the cognitive response to B vitamins in MCI patients. METHODS: In the 24-month randomized trial, 279 MCI outpatients took 500μ#x03BC;g methylcobalamin and 400μ#x03BC;g folic acid once per day or placebo tablets once per day. Sixty-four aspirin users were excluded from analysis as aspirin use has been found to have significant negative interaction effects. Subjects were followed up at months 12 and 24. The primary cognitive outcome was clinical dementia rating scale sum of boxes (CDR_SOB). In a subgroup of 83 subjects, MRI brain scans were performed at baseline to estimate regional brain atrophy ratios. RESULTS: Among the trial subjects who had MRI data, B vitamin supplementation had no significant effect on CDR_SOB, despite having significant homocysteine lowering effects. The atrophy ratio of the left frontal lobe significantly moderated the effect of B vitamin supplementation on CDR_SOB, after adjusting for confounders, in that B vitamin supplementation was associated with lower CDR_SOB scores (i.e., better cognitive function) at the 24th month among those patients with above median atrophy ratios, but not among those with lower atrophy ratios, in the left frontal lobe. CONCLUSION: B vitamins may be more effective in slowing down cognitive decline in MCI patients with atrophy in the left frontal lobe.

Better Subjective Sleep Quality Partly Explains the Association Between Self-Reported Physical Activity and Better Cognitive Function. - Cheval, Boris; Maltagliati, Silvio; Sieber, Stefan; Cullati, Stéphane; Zou, Liye; Ihle, Andreas; Kramer, Arthur F; Yu, Qian; Sander, David; Boisgontier, Matthieu P (J Alzheimers Dis, 2022)
BACKGROUND: Physical activity has been associated with better cognitive function and better sleep quality. Yet, whether the beneficial effect of physical activity on cognitive function can be explained by an indirect pathway involving better sleep quality is unclear. OBJECTIVE: To investigate whether sleep quality mediates the association between physical activity and cognitive function in adults 50 years of age or older. METHODS: 86,541 community-dwelling European adults were included in the study. Physical activity and sleep quality were self-reported. Indicators of cognitive function (immediate recall, delayed recall, verbal fluency) were assessed using objective tests. All measures were collected six times between 2004 and 2017. The mediation was tested using multilevel mediation analyses. RESULTS: Results showed that self-reported physical activity was associated with better self-reported sleep quality, which was associated with better performance in all three indicators of cognitive function, demonstrating an indirect effect of physical activity on cognitive function through sleep quality. The mediating effect of sleep quality accounted for 0.41%, 1.46%, and 8.88% of the total association of physical activity with verbal fluency, immediate recall, and delayed recall, respectively. CONCLUSION: These findings suggest that self-reported sleep quality partly mediates the association between self-reported physical activity and cognitive function. These results need to be confirmed by device-based data of physical activity and sleep quality.
Keywords: Cognition; Exercise; Humans; Self Report; Sleep; Sleep Quality

Blood Tests for Alzheimer's Disease: Increasing Efforts to Expand and Diversify Research Participation Is Critical for Widespread Validation and Acceptance. - Karikari, Thomas K (J Alzheimers Dis, 2022)
The recent academic and commercial development, and regulatory approvals, of blood-based Alzheimer's disease (AD) biomarkers are breakthrough developments of immense potential. However, clinical validation studies and therapeutic trial applications are limited almost exclusively to non-Hispanic White cohorts often including highly-educated, high-earning participants. This commentary argues that the true benefits of blood tests for AD will be realized by active inclusion of diverse groups including minoritized populations, people of socioeconomic status different from those included in existing cohorts, and residents of low- and middle-income countries. The article discusses key factors that are critical for a successful implementation of diversity programs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Hematologic Tests; Humans; tau Proteins

Burden of Insomnia and Sleep Disturbances and the Impact of Sleep Treatments in Patients with Probable or Possible Alzheimer's Disease: A Structured Literature Review. - Benca, Ruth; Herring, W Joseph; Khandker, Rezaul; Qureshi, Zaina P (J Alzheimers Dis, 2022)
BACKGROUND: Sleep disturbances are frequent in Alzheimer's disease (AD). OBJECTIVE: To summarize the impact of sleep disturbances on AD patients and their caregivers and the effects of currently available sleep therapies. METHODS: Published studies (January 1985-March 2020) assessing the burden associated with insomnia/sleep disturbances in the AD population and insomnia treatment effects were identified by searching PubMed, Embase, and Cochrane Library and screened against inclusion criteria. RESULTS: 58 studies assessing patient and caregiver burden, institutionalization, and insomnia treatments in AD patients with sleep disturbances were identified. Sleep disturbances were associated with worse cognition, functional ability, and behavioral and neuropsychological functioning. Health status and quality of life of both patients and caregivers were reduced in the presence of sleep disturbances. Sleep disturbances were also associated with institutionalization. Although significant associations between sleep problems and clinical outcomes were apparent, there was generally no control for other influencing factors (e.g., cognitive status). Bright light and behavioral therapies as well as drugs showed some promise in AD patients, but studies were primarily small and limited data were available, particularly in regard to the effect on associated clinical burden. CONCLUSION: Sleep disturbances are a significant problem for AD patients and caregivers, associated with behavioral and psychological problems and cognitive decline. However, they remain poorly characterized and under-researched. As the global population is aging and AD is on thes rise, data from larger, prospective trials are required to fully understand the clinical correlates of sleep disturbances and the impact insomnia treatments can have.
Keywords: Alzheimer Disease; Caregivers; Humans; Prospective Studies; Quality of Life; Sleep; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders

Cancer and Vascular Comorbidity Effects on Dementia Risk and Neuropathology in the Oldest-Old. - Lachner, Christian; Day, Gregory S; Camsari, Gamze Balci; Kouri, Naomi; Ertekin-Taner, Nilufer; Boeve, Bradley F; Labuzan, Sydney A; Lucas, John A; Thompson, E Aubrey; Siddiqui, Habeeba; Crook, Julia E; Cabrera-Rodriguez, Janisse N; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Dementia, vascular disease, and cancer increase with age, enabling complex comorbid interactions. Understanding vascular and cancer contributions to dementia risk and neuropathology in oldest-old may improve risk modification and outcomes. OBJECTIVE: Investigate vascular and cancer contributions to dementia and neuropathology in oldest-old. METHODS: Longitudinal clinicopathologic study of prospectively followed Mayo Clinic participants dying≥95 years-old who underwent autopsy. Participants were stratified by dementia status and compared according to demographics, vascular risk factors, cancer, and neuropathology. RESULTS: Participants (n = 161; 83% female; 99% non-Hispanic whites)≥95 years (95-106 years-old) with/without dementia did not differ based on demographics. APOE ɛ2 frequency was higher in no dementia (20/72 [28%]) versus dementia (11/88 [12%]; p = 0.03), but APOE ɛ4 frequency did not differ. Coronary artery disease was more frequent in no dementia (31/72 [43%]) versus dementia (23/89 [26%]; p = 0.03) associated with 56% lower dementia odds (odds ratio [OR] = 0.44 [confidence interval (CI) = 0.19-0.98]; p = 0.04) and fewer neuritic/diffuse plaques. Diabetes had an 8-fold increase in dementia odds (OR = 8.42 [CI = 1.39-163]; p = 0.02). Diabetes associated with higher cerebrovascular disease (Dickson score; p = 0.05). Cancer associated with 63% lower dementia odds (OR = 0.37 [CI = 0.17-0.78]; p <  0.01) and lower Braak stage (p = 0.01). CONCLUSION: Cancer exposure in the oldest-old was associated with lower odds of dementia and tangle pathology, whereas history of coronary artery disease was associated with lower odds of dementia and amyloid-β plaque pathology. History of diabetes mellitus was associated with increased odds of dementia and cerebrovascular disease pathology. Cancer-related mechanisms and vascular risk factor reduction strategies may alter dementia risk and neuropathology in oldest-old.

Cerebrospinal Fluid Sphingomyelins in Alzheimer's Disease, Neurodegeneration, and Neuroinflammation. - Morrow, Autumn; Panyard, Daniel J; Deming, Yuetiva K; Jonaitis, Erin; Dong, Ruocheng; Vasiljevic, Eva; Betthauser, Tobey J; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Bayfield, Anna; Van Hulle, Carol A; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Sphingomyelin (SM) levels have been associated with Alzheimer's disease (AD), but the association direction has been inconsistent and research on cerebrospinal fluid (CSF) SMs has been limited by sample size, breadth of SMs examined, and diversity of biomarkers available. OBJECTIVE: Here, we seek to build on our understanding of the role of SM metabolites in AD by studying a broad range of CSF SMs and biomarkers of AD, neurodegeneration, and neuroinflammation. METHODS: Leveraging two longitudinal AD cohorts with metabolome-wide CSF metabolomics data (n = 502), we analyzed the relationship between the levels of 12 CSF SMs, and AD diagnosis and biomarkers of pathology, neurodegeneration, and neuroinflammation using logistic, linear, and linear mixed effects models. RESULTS: No SMs were significantly associated with AD diagnosis, mild cognitive impairment, or amyloid biomarkers. Phosphorylated tau, neurofilament light, α-synuclein, neurogranin, soluble triggering receptor expressed on myeloid cells 2, and chitinase-3-like-protein 1 were each significantly, positively associated with at least 5 of the SMs. CONCLUSION: The associations between SMs and biomarkers of neurodegeneration and neuroinflammation, but not biomarkers of amyloid or diagnosis of AD, point to SMs as potential biomarkers for neurodegeneration and neuroinflammation that may not be AD-specific.

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

Digital Technologies to Prevent Social Isolation and Loneliness in Dementia: A Systematic Review. - Rai, Harleen Kaur; Kernaghan, David; Schoonmade, Linda; Egan, Kieren J; Pot, Anne Margriet (J Alzheimers Dis, 2022)
BACKGROUND: Dementia poses significant and sustained challenges to global society. Diagnosis can lead to increased feelings of loneliness and social isolation. People with dementia living alone are particularly at risk. Considering the growing number of technologies proposed to aid people with dementia address social isolation and loneliness, we reviewed the existing literature. OBJECTIVE: To collate and summarize current evidence for digital technologies to prevent social isolation and loneliness for people with dementia. METHODS: Following the PRISMA guidelines, we systematically searched five databases to identify studies of digital technologies designed to support or prevent social isolation or loneliness for people with dementia. Pre-specified outcomes included social isolation, loneliness, and quality of life. We used deductive thematic analysis to synthesize the major themes emerging from the studies. RESULTS: Ten studies met our inclusion criteria where all studies reported improvements in quality of life and seven reported benefits regarding social inclusion or a reduction in loneliness. Technologies were varied across purpose, delivery format, theoretical models, and levels of personalization. Two studies clearly described the involvement of people with dementia in the study design and five technologies were available outside the research context. CONCLUSION: There is limited- but increasing- evidence that technologies hold potential to improve quality of life and reduce isolation/loneliness for people with dementia. Results presented are largely based in small-scale research studies. Involvement of people with dementia was limited and few research concepts are reaching implementation. Closer collaboration with people with dementia to provide affordable, inclusive, and person-centered solutions is urgently required.
Keywords: Dementia; Digital Technology; Humans; Loneliness; Quality of Life; Social Isolation

Does Loss of Integrity of the Cingulum Bundle Link Amyloid-β Accumulation and Neurodegeneration in Alzheimer's Disease? - Vlegels, Naomi; Ossenkoppele, Rik; van der Flier, Wiesje M; Koek, Huiberdina L; Reijmer, Yael D; Wisse, Laura Em; Biessels, Geert Jan (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease is characterized by the accumulation of amyloid-β (Aβ) into plaques, aggregation of tau into neurofibrillary tangles, and neurodegenerative processes including atrophy. However, there is a poorly understood spatial discordance between initial Aβ deposition and local neurodegeneration. OBJECTIVE: Here, we test the hypothesis that the cingulum bundle links Aβ deposition in the cingulate cortex to medial temporal lobe (MTL) atrophy. METHODS: 21 participants with mild cognitive impairment (MCI) from the UMC Utrecht memory clinic (UMCU, discovery sample) and 37 participants with MCI from Alzheimer's Disease Neuroimaging Initiative (ADNI, replication sample) with available Aβ-PET scan, T1-weighted and diffusion-weighted MRI were included. Aβ load of the cingulate cortex was measured by the standardized uptake value ratio (SUVR), white matter integrity of the cingulum bundle was assessed by mean diffusivity and atrophy of the MTL by normalized MTL volume. Relationships were tested with linear mixed models, to accommodate multiple measures for each participant. RESULTS: We found at most a weak association between cingulate Aβ and MTL volume (added R2 <0.06), primarily for the posterior hippocampus. In neither sample, white matter integrity of the cingulum bundle was associated with cingulate Aβ or MTL volume (added R2 <0.01). Various sensitivity analyses (Aβ-positive individuals only, posterior cingulate SUVR, MTL sub region volume) provided similar results. CONCLUSION: These findings, consistent in two independent cohorts, do not support our hypothesis that loss of white matter integrity of the cingulum is a connecting factor between cingulate gyrus Aβ deposition and MTL atrophy.

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

Expression Changes in Mitochondrial Genes Affecting Mitochondrial Morphology, Transmembrane Potential, Fragmentation, Amyloidosis, and Neuronal Cell Death Found in Brains of Alzheimer's Disease Patients. - Castora, Frank J; Kerns, Kimberly A; Pflanzer, Haley K; Hitefield, Naomi L; Gershon, Blake; Shugoll, Jason; Shelton, Morgan; Coleman, Randolph A (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a neurological disease that has both a genetic and non-genetic origin. Mitochondrial dysfunction is a critical component in the pathogenesis of AD as deficits in oxidative capacity and energy production have been reported. OBJECTIVE: Nuclear-encoded mitochondrial genes were studied in order to understand the effects of mitochondrial expression changes on mitochondrial function in AD brains. These expression data were to be incorporated into a testable mathematical model for AD used to further assess the genes of interest as therapeutic targets for AD. METHODS: RT2-PCR arrays were used to assess expression of 84 genes involved in mitochondrial biogenesis in AD brains. A subset of mitochondrial genes of interest was identified after extensive Ingenuity Pathway Analysis (IPA) (Qiagen). Further filtering of this subset of genes of interest was achieved by individual qPCR analyses. Expression values from this group of genes were included in a mathematical model being developed to identify potential therapeutic targets. RESULTS: Nine genes involved in trafficking proteins to mitochondria, morphology of mitochondria, maintenance of mitochondrial transmembrane potential, fragmentation of mitochondria and mitochondrial dysfunction, amyloidosis, and neuronal cell death were identified as significant to the changes seen. These genes include TP53, SOD2, CDKN2A, MFN2, DNM1L, OPA1, FIS1, BNIP3, and GAPDH. CONCLUSION: Altered mitochondrial gene expression indicates that a subset of nuclear-encoded mitochondrial genes compromise multiple aspects of mitochondrial function in AD brains. A new mathematical modeling system may provide further insights into potential therapeutic targets.

Frontal Atrophy and Executive Dysfunction Relate to Complex Numbers Impairment in Progressive Supranuclear Palsy. - Howard, Erica; Ballinger, Samantha; Kinney, Nikolas G; Balgenorth, Yvonne; Ehrhardt, Annabess; Phillips, Jeffrey S; Irwin, David J; Grossman, Murray; Cousins, Katheryn A Q (J Alzheimers Dis, 2022)
BACKGROUND: Previous research finds a range of numbers impairments in Parkinsonian syndromes (PS), but has largely focused on how visuospatial impairments impact deficits in basic numerical processes (e.g., magnitude judgments, chunking). Differentiation between these basic functions and more complex numerical processes often utilized in everyday tasks may help elucidate neurocognitive and neuroanatomic bases of numbers deficits in PS. OBJECTIVE: To test neurocognitive and neuroanatomic correlates of complex numerical processing in PS, we assessed number abilities, neuropsychological performance, and cortical thickness in progressive supranuclear palsy (PSP) and Lewy body spectrum disorders (LBSD). METHODS: Fifty-six patients (LBSD = 35; PSP = 21) completed a Numbers Battery, including basic and complex numerical tasks. The Mini-Mental State Exam (MMSE), letter fluency (LF), and Judgment of Line Orientation (JOLO) assessed global, executive, and visuospatial functioning respectively. Mann-Whitney U tests compared neuropsychological testing and rank-transformed analysis of covariance (ANCOVA) compared numbers performance between groups while adjusting for demographic variables. Spearman's and partial correlations related numbers performance to neuropsychological tasks. Neuroimaging assessed cortical thickness in disease groups and demographically-matched healthy controls. RESULTS: PSP had worse complex numbers performance than LBSD (F = 6.06, p = 0.02) but similar basic numbers performance (F = 0.38, p >  0.1), covarying for MMSE and sex. Across syndromes, impaired complex numbers performance was linked to poor LF (rho = 0.34, p = 0.01) but not JOLO (rho = 0.23, p >  0.05). Imaging revealed significant frontal atrophy in PSP compared to controls, which was associated with worse LF and complex numbers performance. CONCLUSION: PSP demonstrated selective impairments in complex numbers processing compared to LBSD. This complex numerical deficit may relate to executive dysfunction and frontal atrophy.

Informal Caregivers' Attitude Toward Dementia: The Impact of Dementia Knowledge, Confidence in Dementia Care, and the Behavioral and Psychological Symptoms of the Person with Dementia. A Cross-Sectional Study. - Teichmann, Birgit; Gkioka, Mara; Kruse, Andreas; Tsolaki, Magda (J Alzheimers Dis, 2022)
BACKGROUND: Dementia is rapidly increasing worldwide due to demographic aging. More than two-thirds of patients are cared by family members. The quality of care depends on the caregivers' attitude toward dementia influencing patient care decisions. OBJECTIVE: The aim of this study is to examine the factors that influence the caregivers' attitude and whether there is an association between participation in a psycho-educational program and attitude. METHODS: We performed a cross-sectional study using a structured closed-ended questionnaire to retrieve socio-demographic information from caregivers and the persons with dementia (N = 86). The study included validated scales such as the Dementia Attitude Scale, the Dementia Knowledge Assessment Tool 2, the Positive Aspects of Caregiving, the Zarit Burden Interview, the Confidence in Dementia Scale, and Spielberger's State-Trait Anxiety Inventory, as well as a neuropsychological battery to assess the condition of people with dementia. RESULTS: Our final model explains 55.6% of the total variance and shows a significant correlation of five factors with attitude toward dementia: confidence, behavioral and psychological symptoms of dementia, anxiety as a trait, positive aspects of caregiving, and dementia knowledge. The caregivers who participated in a psycho-educational program showed a significantly more positive attitude toward dementia, better dementia knowledge, higher confidence in dementia care, and lower anxiety as a state. CONCLUSION: The strong correlation of attitude and knowledge, as well as confidence in dementia care, supports the tripartite model of attitude, which hypothesizes the interrelation of affect, cognition, and behavior.
Keywords: Attitude; Caregivers; Cross-Sectional Studies; Dementia; Humans; Surveys and Questionnaires

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

Isolated Amyloid-β Pathology Is Associated with Preserved Cortical Plasticity in APOE4 Alzheimer's Disease Patients. - Assogna, Martina; Motta, Caterina; Bonní, Sonia; Borghi, Ilaria; Casula, Elias P; Martorana, Alessandro; Koch, Giacomo (J Alzheimers Dis, 2022)
BACKGROUND: Long-term potentiation (LTP) like-cortical plasticity impairment and cholinergic neurotransmission deficits have been widely demonstrated in Alzheimer's disease (AD) patients. OBJECTIVE: In this study we aim to investigate the neurophysiological features underlying cognitive decline in AD patients according to the National Institute on Aging-Alzheimer's Association (NIA-AA) classification and APOE genotype. METHODS: 65 newly diagnosed AD patients were enrolled. APOE genotype and lumbar puncture for the analysis of cerebrospinal fluid biomarkers were performed for diagnostic purposes. Patients were subdivided upon NIA-AA criteria, according to the presence of biomarkers of Aβ amyloid deposition (A) and fibrillar tau (T), in four groups: A+/T-E4 (n = 9), A+/T-E3 (n = 18), A+/T+ E4 (n = 21), and A+/T+ E3 (n = 17). We applied intermittent theta burst stimulation over the primary motor cortex to assess LTP-like cortical plasticity and short latency afferent inhibition (SAI) protocol to investigate central cholinergic activity. Patients were followed over 24 months. Cognitive decline was evaluated considering changes in Mini-Mental State Examination scores respect to the baseline. RESULTS: A+/T-E4 patients showed preserved LTP-like cortical plasticity as compared to A+/T-E3 and to A+/T+ patients independently from genotype (p <  0.001). In addition, A+/T-E4 patients showed a slower cognitive decline with respect to A+/T+ E4 (-0.5±2.12 versus -6.05±4.95; post-hoc p = 0.004) and to A+/T+ E3 patients (-4.12±4.14; post-hoc p = 0.028). No differences were found for SAI protocol (p >  0.05). CONCLUSION: Our results suggest that APOE4 in patients with isolated amyloid pathology could exert positive effects on LTP-like cortical plasticity with a consequent slower cognitive decline.

Late-Onset Alcohol Abuse as a Presenting Symptom of Neurodegenerative Diseases. - de Paula França Resende, Elisa; Ketelle, Robin; Karydas, Anna; Allen, Isabel; Grinberg, Lea T; Spina, Salvatore; Seeley, William W; Perry, David C; Miller, Bruce; Naasan, Georges (J Alzheimers Dis, 2022)
BACKGROUND: The association between lifetime alcohol abuse and a higher risk to develop dementia is well known. However, it is unknown whether older adults who begin abusing alcohol late in life have an underlying neurodegenerative disease. OBJECTIVE: Identify the frequency of lifelong alcohol abuse (L-AA), late-onset alcohol abuse (LO-AA), and alcohol abuse as a first symptom of dementia (AA-FS) in patients with neurodegenerative diseases. METHODS: Cross-sectional retrospective study of patients evaluated at an academic referral center with a clinical diagnosis of behavioral variant frontotemporal dementia (bvFTD), Alzheimer-type dementia (AD), and semantic variant primary progressive aphasia (svPPA) (n = 1,518). The presence of alcohol abuse was screened with the National Alzheimer's Coordinating Center questionnaire. L-AA was defined as onset <  40 years, LO-AA as onset ≥40 years, and AA-FS was defined when the abuse started within the first three years from symptom onset. RESULTS: The frequency of LO-AA was 2.2% (n = 33/1,518). LO-AA was significantly more frequent in patients with bvFTD than AD (7.5%, n = 13/173 versus 1.3%, n = 16/1,254, CI:1.0;11.4%), but not svPPA (4.4%, n = 4/91, CI: -4.4;10.7%). Similarly, AA-FS was more frequent in bvFTD patients than AD (5.7%, n = 10/173 versus 0.7%, n = 9/1,254, CI:0.5% ;9.5%), but not svPPA (2.2%, n = 2/91, CI:-2.4;9.1%). CONCLUSION: LO-AA can be a presenting symptom of dementia, especially bvFTD. Alcohol abuse onset later in life should prompt a clinical investigation into the possibility of an underlying neurodegenerative process because delay in diagnosis and treatment may increase patient and caregiver burden. The results need to be interpreted with caution due to the limitations of the study.

Lipid Peroxidation as a Marker of Apathy and Executive Dysfunction in Patients at Risk for Vascular Cognitive Impairment. - Bawa, Kritleen K; Ba, Joycelyn; Kiss, Alex; Wang, RuoDing; Feng, Vivian; Swardfager, Walter; Andreazza, Ana; Gallagher, Damien; Marotta, Giovanni; Herrmann, Nathan; Lanctôt, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: The co-occurrence of apathy and executive dysfunction, a correlate of vascular cognitive impairment (VCI), is highly prevalent, yet facilitating factors are largely unknown. OBJECTIVE: This study investigates the relationship between lipid peroxidation, apathy, and executive dysfunction in patients at risk for VCI. METHODS: In participants with coronary artery disease, who are at a high risk of VCI, apathy (Apathy Evaluation Scale), and executive function (composite z-score based on age and education population norms from trails making test B, animal naming, and phonemic fluency tests) were assessed. Serum concentrations of an early (lipid hydroperoxide (LPH)) and late (8-isoprostane (8-ISO)) lipid peroxidation marker, were measured and the 8-ISO/LPH ratio was calculated. RESULTS: Participants (n = 206, age±SD = 63.0±7.5, 80% men, total years of education = 15.9±3.4, AES score = 28.3±8.8, executive function = 0±1) demonstrated significantly different 8-ISO/LPH ratios between groups (F(3, 202) = 10.915, p <  0.001) with increasing levels in the following order: no apathy or executive dysfunction, only executive dysfunction (executive function composite score≤-1), only apathy (AES≥28), and both apathy and executive dysfunction. A model adjusting for demographics showed that lipid peroxidation was associated with both apathy (B(SE) = 4.63 (0.954), t = 4.852, p <  0.001) and executive function (B(SE) = -0.19 (0.079), t = -2.377, p = 0.018). However, when controlling for both demographics and vascular risk factors, lipid peroxidation was associated with only apathy (B(SE) = 3.11 (0.987), t = 3.149, p = 0.002). CONCLUSION: The results highlight a potentially important involvement of lipid peroxidation in the co-occurrence of apathy and executive dysfunction in those at risk for VCI.

Lipid Rafts Act as a Common Platform for Amyloid-β Oligomer-Induced Alzheimer's Disease Pathology. - Kawarabayashi, Takeshi; Nakamura, Takumi; Sato, Kaoru; Seino, Yusuke; Ichii, Sadanobu; Nakahata, Naoko; Takatama, Masamitsu; Westaway, David; George-Hyslop, Peter St; Shoji, Mikio (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) oligomers induce the overproduction of phosphorylated tau and neurodegeneration. These cascades gradually cause cognitive impairment in Alzheimer's disease (AD). While each pathological event in AD has been studied in detail separately, the spatial and temporal relationships between pathological events in AD remain unclear. OBJECTIVE: We demonstrated that lipid rafts function as a common platform for the pathological cascades of AD. METHODS: Cellular and synaptosomal lipid rafts were prepared from the brains of Aβ amyloid model mice (Tg2576 mice) and double transgenic mice (Tg2576 x TgTauP301L mice) and longitudinally analyzed. RESULTS: Aβ dimers, the cellular prion protein (PrPc), and Aβ dimer/PrPc complexes were detected in the lipid rafts. The levels of Fyn, the phosphorylated NR2B subunit of the N-methyl-D-aspartate receptor, glycogen synthase kinase 3β, total tau, phosphorylated tau, and tau oligomers increased with Aβ dimer accumulation in both the cellular and synaptosomal lipid rafts. Increases in the levels of these molecules were first seen at 6 months of age and corresponded with the early stages of Aβ accumulation in the amyloid model mice. CONCLUSION: Lipid rafts act as a common platform for the progression of AD pathology. The findings of this study suggest a novel therapeutic approach to AD, involving the modification of lipid raft components and the inhibition of their roles in the sequential pathological events of AD.

Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.

Mild Traumatic Brain Injury is Related to Elevated Cerebrospinal Fluid Tau in Alzheimer's Disease Dementia. - LoBue, Christian; Kelley, Brendan J; Hart, John; Helphrey, Jessica; Schaffert, Jeff; Cullum, C Munro; Peters, Matthew E; Douglas, Peter M (J Alzheimers Dis, 2022)
Few studies have examined an association between mild traumatic brain injury (mTBI) and Alzheimer's disease (AD). For this reason, we compared an AD dementia group with an mTBI history (n = 10) to a matched AD control group (n = 20) on measures of cognitive function, cerebral glucose metabolism, and markers of amyloid and tau deposition. Only a trend and medium-to-large effect size for higher phosphorylated and total tau was identified for the mTBI group. A history of mTBI may be associated with greater tau in AD, indicating a potential pathway for increasing risk for AD, though further evaluation with larger samples is needed.

Monitoring Alzheimer's Disease Progression in Mild Cognitive Impairment Stage Using Machine Learning-Based FDG-PET Classification Methods. - Beheshti, Iman; Geddert, Natasha; Perron, Jarrad; Gupta, Vinay; Albensi, Benedict C; Ko, Ji Hyun (J Alzheimers Dis, 2022)
BACKGROUND: We previously introduced a machine learning-based Alzheimer's Disease Designation (MAD) framework for identifying AD-related metabolic patterns among neurodegenerative subjects. OBJECTIVE: We sought to assess the efficiency of our MAD framework for tracing the longitudinal brain metabolic changes in the prodromal stage of AD. METHODS: MAD produces subject scores using five different machine-learning algorithms, which include a general linear model (GLM), two different approaches of scaled subprofile modeling, and two different approaches of a support vector machine. We used our pre-trained MAD framework, which was trained based on metabolic brain features of 94 patients with AD and 111 age-matched cognitively healthy (CH) individuals. The MAD framework was applied on longitudinal independent test sets including 54 CHs, 51 stable mild cognitive impairment (sMCI), and 39 prodromal AD (pAD) patients at the time of the clinical diagnosis of AD, and two years prior. RESULTS: The GLM showed excellent performance with area under curve (AUC) of 0.96 in distinguishing sMCI from pAD patients at two years prior to the time of the clinical diagnosis of AD while other methods showed moderate performance (AUC: 0.7-0.8). Significant annual increment of MAD scores were identified using all five algorithms in pAD especially when it got closer to the time of diagnosis (p <  0.001), but not in sMCI. The increased MAD scores were also significantly associated with cognitive decline measured by Mini-Mental State Examination in pAD (q <  0.01). CONCLUSION: These results suggest that MAD may be a relevant tool for monitoring disease progression in the prodromal stage of AD.

Novel Invisible Spectral Flicker Induces 40 Hz Neural Entrainment with Similar Spatial Distribution as 40 Hz Stroboscopic Light. - Agger, Mikkel Pejstrup; Carstensen, Marcus Schultz; Henney, Mark Alexander; Hansen, Luna Skytte; Baandrup, Anders Ohlhues; Nguyen, Mai; Petersen, Paul Michael; Madsen, Kristoffer Hougaard; Kjær, Troels Wesenberg (J Alzheimers Dis, 2022)
BACKGROUND: Exposure to 40 Hz stroboscopic light, for one hour a day, has previously been published as a potential treatment option for Alzheimer's disease in animal models. However, exposure for an hour a day to 40 Hz stroboscopic light can be strenuous and examining other types of 40 Hz inducing stimuli is paramount if chronic treatment is wanted. OBJECTIVE: A core assumption behind ensuring a therapeutic outcome is that the visual stimuli can induce 40 Hz gamma entrainment. Here, we examine whether a specific visual stimulus, 40 Hz invisible spectral flicker (ISF), can induce gamma entrainment and how it differs from both continuous light (CON) and 40 Hz stroboscopic light (STROBE). METHODS: The study included non-simultaneous EEG-fMRI neuroimaging of 13 young healthy volunteers during light exposure. Each light condition (i.e., CON, ISF, or STROBE) was active for 30 seconds followed immediately by the next. RESULTS: Entrainment of 40 Hz neural activity were significantly higher signal-to-noise ratio during exposure to ISF (mean: 3.03, 95% CI 2.07 to 3.99) and STROBE (mean: 12.04, 95% CI 10.18 to 13.87) compared to CON. Additionally STROBE had a higher entrainment than ISF (mean: 9.01, 95% CI 7.16 to 12.14). CONCLUSION: This study presents a novel method of 40 Hz entrainment using ISF. This enables the possibility of future randomized placebo-controlled clinical trials with acceptable double blinding due to the essentially imperceivable flicker, which is expected to substantially reduce discomfort compared to interventions with stroboscopic flicker.

Olfactory Bulb Integrity in Frontotemporal Dementia and Alzheimer's Disease. - Carnemolla, Sarah; Kumfor, Fiona; Liang, Cheng Tao; Foxe, David; Ahmed, Rebekah; Piguet, Olivier (J Alzheimers Dis, 2022)
BACKGROUND: Olfactory dysfunction is highly prevalent in dementia syndromes, including Alzheimer's disease (AD) and frontotemporal dementia (FTD). The structural integrity of the olfactory bulb (OB) is thought to play a critical role in odor detection and identification, but no MRI study has measured OB volume in FTD, or measured OB volume longitudinally in AD. OBJECTIVE: To measure OB volume in FTD and AD patients longitudinally using MRI. METHODS: This study measured OB volumes using MRI in patients diagnosed with behavioral-variant FTD (n = 55), semantic dementia (n = 34), progressive non-fluent aphasia (n = 30), AD (n = 50), and healthy age-matched controls (n = 55) at their first visit to a dementia research clinic ('baseline'). Imaging data in patients 12-months later were analyzed where available (n = 84) for longitudinal assessment. Volumes of subcortical and cortical olfactory regions ('olfactory network') were obtained via surface-based morphometry. RESULTS: Results revealed that in AD and FTD at baseline, OB volumes were similar to controls, whereas volumes of olfactory network regions were significantly reduced in all patient groups except in progressive non-fluent aphasia. Longitudinal data revealed that OB volume became significantly reduced (10-25% volume reduction) in all dementia groups with disease progression. CONCLUSION: Olfactory dysfunction is common in patients diagnosed with AD or FTD, but our results indicate that there is no detectable volume loss to the OBs upon first presentation to the clinic. Our findings indicate that the OBs become detectably atrophied later in the disease process. OB atrophy indicates the potential usefulness for OBs to be targeted in interventions to improve olfactory function.

Passive Immunotherapy Targeting Tau Oligomeric Strains Reverses Tauopathy Phenotypes in Aged Human-Tau Mice in a Mouse Model-Specific Manner. - Bittar, Alice; Al-Lahham, Rabab; Bhatt, Nemil; Moore, Kenya; Montalbano, Mauro; Jerez, Cynthia; Fung, Leiana; McAllen, Salome; Ellsworth, Anna; Kayed, Rakez (J Alzheimers Dis, 2022)
BACKGROUND: Tau oligomers are one of the most toxic species, displaying prion-like strains which have different conformations resulting in different tauopathies. Passive immunotherapy targeting different tau species is a promising therapeutic approach. Age is one of the greatest risk factors; however, most immunotherapy studies are done in young to middle-aged mice tauopathy models, which is not representative of the many clinical trials done with older humans with established tauopathies. OBJECTIVE: We utilized two different clones of tau oligomer monoclonal antibodies (TOMAs) in aged Htau and JNPL3 mouse models to investigate the potential of passive immunotherapy. METHODS: Aged mice received a single intravenous injection of 120 μg/animal of either TOMA1, TOMA3 clones or a non-specific IgG. Their cognitive functions were assessed one-week post-injection using Y-maze and novel object recognition tests. Brain tissues were analyzed using biochemical and immunological assays. RESULTS: TOMA 1 and 3 rescues cognitive phenotypes in aged animals in a mouse model-specific manner, indicative by a reduction in tau oligomers levels. The TOMAs were shown to have strong reactivity with different tau oligomeric species in the different mouse models in vitro and ex vivo. CONCLUSION: This is the first study testing tau passive immunotherapy in aged animals and supports our previous reports on of the role of oligomeric tau in disease progression further validating the potential of TOMAs to rescue the late-stage disease pathology and phenotype. Moreover, this study suggests that multiple tau oligomeric strains exist in aged animals; therefore, it is of great importance to further characterize these strains.

Plasma Myeloperoxidase as a Potential Biomarker of Patient Response to Anti-Dementia Treatment in Alzheimer's Disease. - Wright, Joy R; Deen, Quazi Fahm E; Stevenson, Anna; Telford-Cooke, Leolie; Parker, Craig; Martin-Ruiz, Carmen; Steinert, Joern R; Kalaria, Raj N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2022)
BACKGROUND: Myeloperoxidase (MPO), a neutrophil-derived pro-inflammatory protein, co-localizes with amyloid-β (Aβ) plaques in Alzheimer's disease (AD). Anti-dementia treatment may facilitate efflux of Aβ and associated plaque proteins from the brain to the peripheral circulation, therefore providing potential biomarkers for the monitoring of donor response to drug treatment. OBJECTIVE: We investigated the diagnostic utility of MPO as a biomarker of AD, and how anti-dementia treatment alters plasma MPO concentration. METHODS: Thirty-two AD patients were recruited, and plasma collected pre-drug administration (baseline), and 1- and 6-months post-treatment. All patients received cholinesterase inhibitors (ChEIs). At baseline and 6 months, patients underwent neuropsychological assessment. Forty-nine elderly healthy individuals with normal cognitive status served as controls. Plasma MPO concentration was measured by ELISA. RESULTS: AD drug naïve patients had similar plasma MPO concentration to their control counterparts (p >  0.05). Baseline MPO levels positively correlated with Neuropsychiatric Inventory score (r = 0.5080; p = 0.011) and carer distress (r = 0.5022; p = 0.012). Following 1-month ChEI treatment, 84.4% of AD patients exhibited increased plasma MPO levels (p <  0.001), which decreased at 6 months (p <  0.001). MPO concentration at 1 month was greatest in AD patients whose memory deteriorated during the study period (p = 0.028), and for AD patients with deterioration in Cornell assessment score (p = 0.044). CONCLUSION: Whereas baseline MPO levels did not differentiate between healthy and AD populations, baseline MPO positively correlated with initial Neuropsychiatric Inventory evaluation. Post-treatment, transient MPO upregulation in ChEI-treated patients may reflect worse therapeutic outcome. Further studies are required to assess the potential of plasma MPO as an AD therapeutic biomarker.

Polygenic Scores of Alzheimer's Disease Risk Genes Add Only Modestly to APOE in Explaining Variation in Amyloid PET Burden. - Ramanan, Vijay K; Heckman, Michael G; Przybelski, Scott A; Lesnick, Timothy G; Lowe, Val J; Graff-Radford, Jonathan; Mielke, M; Jack, Clifford R; Knopman, David S; Petersen, Ronald C; Ross, Owen A; Vemuri, Prashanthi (J Alzheimers Dis, 2022)
BACKGROUND: Brain accumulation of amyloid-β is a hallmark event in Alzheimer's disease (AD) whose underlying mechanisms are incompletely understood. Case-control genome-wide association studies have implicated numerous genetic variants in risk of clinically diagnosed AD dementia. OBJECTIVE: To test for associations between case-control AD risk variants and amyloid PET burden in older adults, and to assess whether a polygenic measure encompassing these factors would account for a large proportion of the unexplained variance in amyloid PET levels in the wider population. METHODS: We analyzed data from the Mayo Clinic Study of Aging (MCSA) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Global cortical amyloid PET burden was the primary outcome. The 38 gene variants from Wightman et al. (2021) were analyzed as predictors, with PRSice-2 used to assess the collective phenotypic variance explained. RESULTS: Known AD risk variants in APOE, PICALM, CR1, and CLU were associated with amyloid PET levels. In aggregate, the AD risk variants were strongly associated with amyloid PET levels in the MCSA (p = 1.51×10-50) and ADNI (p = 3.21×10-64). However, in both cohorts the non-APOE variants uniquely contributed only modestly (MCSA = 2.1%, ADNI = 4.4%) to explaining variation in amyloid PET levels. CONCLUSION: Additional case-control AD risk variants added only modestly to APOE in accounting for individual variation in amyloid PET burden, results which were consistent across independent cohorts with distinct recruitment strategies and subject characteristics. Our findings suggest that advancing precision medicine for dementia may require integration of strategies complementing case-control approaches, including biomarker-specific genetic associations, gene-by-environment interactions, and markers of disease progression and heterogeneity.

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Potential Involvement of Varicella Zoster Virus in Alzheimer's Disease via Reactivation of Quiescent Herpes Simplex Virus Type 1. - Cairns, Dana M; Itzhaki, Ruth F; Kaplan, David L (J Alzheimers Dis, 2022)
BACKGROUND: Varicella zoster virus (VZV) has been implicated in Alzheimer's disease (AD), and vaccination against shingles, caused by VZV, has been found to decrease the risk of AD/dementia. VZV might reside latently in brain, and on reactivation might cause direct damage leading to AD, as proposed for herpes simplex virus type 1 (HSV-1), a virus strongly implicated in AD. Alternatively, shingles could induce neuroinflammation and thence, reactivation of HSV-1 in brain. OBJECTIVE: To investigate these possibilities by comparing the effects of VZV and HSV-1 infection of cultured cells, and the action of VZV infection on cells quiescently infected with HSV-1. METHODS: We infected human-induced neural stem cell (hiNSC) cultures with HSV-1 and/or VZV and sought the presence of AD-related phenotypes such as amyloid-β (Aβ) and P-tau accumulation, gliosis, and neuroinflammation. RESULTS: Cells infected with VZV did not show the main AD characteristics, Aβ and P-tau accumulation, which HSV-1 does cause, but did show gliosis and increased levels of pro-inflammatory cytokines, suggesting that VZV's action relating to AD/dementia is indirect. Strikingly, we found that VZV infection of cells quiescently infected with HSV-1 causes reactivation of HSV-1 and consequent AD-like changes, including Aβ and P-tau accumulation. CONCLUSION: Our results are consistent with the suggestion that shingles causes reactivation of HSV1 in brain and with the protective effects against AD of various vaccines, as well as the decrease in herpes labialis reported after certain types of vaccination. They support an indirect role for VZV in AD/dementia via reactivation of HSV-1 in brain.

Potential Mechanisms Underlying Resistance to Dementia in Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Kok, Frédérique K; van Leerdam, Suzanne L; de Lange, Elizabeth C M (J Alzheimers Dis, 2022)
Alzheimer's disease (AD) is the most common form of dementia and typically characterized by the accumulation of amyloid-β plaques and tau tangles. Intriguingly, there also exists a group of elderly which do not develop dementia during their life, despite the AD neuropathology, the so-called non-demented individuals with AD neuropathology (NDAN). In this review, we provide extensive background on AD pathology and normal aging and discuss potential mechanisms that enable these NDAN individuals to remain cognitively intact. Studies presented in this review show that NDAN subjects are generally higher educated and have a larger cognitive reserve. Furthermore, enhanced neural hypertrophy could compensate for hippocampal and cingulate neural atrophy in NDAN individuals. On a cellular level, these individuals show increased levels of neural stem cells and 'von Economo neurons'. Furthermore, in NDAN brains, binding of Aβ oligomers to synapses is prevented, resulting in decreased glial activation and reduced neuroinflammation. Overall, the evidence stated here strengthens the idea that some individuals are more resistant to AD pathology, or at least show an elongation of the asymptomatic state of the disease compared to others. Insights into the mechanisms underlying this resistance could provide new insight in understanding normal aging and AD itself. Further research should focus on factors and mechanisms that govern the NDAN cognitive resilience in order to find clues on novel biomarkers, targets, and better treatments of AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Hippocampus; Humans; Plaque, Amyloid; Synapses

Pre-Diagnostic Symptoms of Young-Onset Dementia in the General Practice up to Five Years Before Diagnosis. - Hendriks, Stevie; Peetoom, Kirsten; Tange, Huibert; van Bokhoven, Marloes A; van der Flier, Wiesje M; Bakker, Christian; Papma, Janne M; Koopmans, Raymond; Verhey, Frans; Köhler, Sebastian; de Vugt, Marjolein (J Alzheimers Dis, 2022)
BACKGROUND: Young-onset dementia (YOD) has many underlying etiologies, leading to a large heterogeneity in first symptoms. This makes it difficult for general practitioners (GPs) to recognize YOD. OBJECTIVE: Identify early symptoms that are more common in the pre-diagnostic phase of YOD. METHODS: We performed a case-control study nested in a primary-care registry on 89 cases and 162 matched controls, where we compared symptoms of people with YOD up to 5 years before diagnosis to their matched control group without YOD. The variables included in this study were International Classification of Primary Care codes and symptoms extracted from written GP notes and categorized in groups. We used Generalized Equation Estimation to analyze symptom's time-trajectories and logistic regression and ROC-curves to analyze differences in number of symptom categories reported. RESULTS: Cognitive symptoms were more common in people with YOD 5 years before diagnosis, affective symptoms 4 years before diagnosis, social symptoms 3 years, behavioral symptoms 2 years, and daily functioning disturbances 1 year before diagnosis. The ROC-curve suggested that reporting two or more symptom categories at the GP gave the best trade-off between sensitivity (85%) and specificity (77% ), for the highest percentage of correctly diagnosed persons. CONCLUSION: This study showed people with YOD present differently than people without YOD. However, it may still be difficult for GPs to use these symptom categories to distinguish people with YOD, since the symptoms also occur in people with other diseases. A combination of reported symptom categories increases the probability of an underlying cause of YOD.

Prevalence of Depressive Symptoms in a Memory Clinic Cohort: A Retrospective Study. - Loreto, Flavia; Fitzgerald, Anna; Golemme, Mara; Gunning, Stephen; Win, Zarni; Patel, Neva; Carswell, Christopher; Perry, Richard; Kennedy, Angus; Edison, Paul; Malhotra, Paresh (J Alzheimers Dis, 2022)
BACKGROUND: Depression has been suggested to be a cause of reversible cognitive impairment but also a risk factor for neurodegenerative disease. Studies suggest that depression prevalence may be high in early onset dementia, particularly Alzheimer's disease, but this has not been systematically assessed in a biomarker-validated clinical dementia cohort to date. OBJECTIVE: To examine the prevalence, features, and association with amyloid pathology of lifetime depressive symptoms in a memory clinic cohort meeting appropriate use criteria for amyloid PET imaging. METHODS: We included 300 patients from a single-center memory clinic cohort that received diagnostic biomarker evaluation with amyloid PET imaging according to appropriate use criteria. History of lifetime depressive symptoms was retrospectively assessed through structured review of clinical correspondence. RESULTS: One hundred forty-two (47%) patients had a history of significant depressive symptoms ('D+'). Of these, 89% had ongoing symptoms and 60% were on antidepressants at the time of presentation to our Clinic. Depressive symptoms were equally highly prevalent in the amyloid-positive and the heterogeneous group of amyloid-negative patients. CONCLUSION: Approximately half of patients who meet appropriate use criteria for amyloid PET had a history of depressive symptoms. We suggest that depression is an important feature of both neurodegenerative and non-neurodegenerative cognitive impairment and may contribute to the diagnostic uncertainty behind referral to amyloid PET.

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among US Adults. - Fowler, Mackenzie E; Wright, Nicole C; Triebel, Kristen; Rocque, Gabrielle B; Irvin, Ryan; Kennedy, Richard E (J Alzheimers Dis, 2022)
BACKGROUND: Cancer-related cognitive impairment (CRCI), a frequent effect of cancer and its treatments, shares common cognitive symptoms with dementia syndromes. Cross-sectional studies demonstrate an inverse relationship between cancer and dementia. However, the longitudinal relationship between dementia decline and cancer has not been investigated. OBJECTIVE: To evaluate the association between cancer and longitudinal progression of dementia. METHODS: We extracted electronic health record data from July 2003 to February 2020 from a single academic medical center. We identified dementia and cancer history prior to dementia using ICD-9/10 codes. We measured cognitive decline with the Alabama Brief Cognitive Screener (ABCs). We used adjusted linear mixed models to estimate baseline cognition and rate of progression by cancer history, including differences by race. RESULTS: The study included 3,809 participants with dementia, of which 672 (17.6%) had cancer history. Those with cancer history had higher baseline cognition (β: 0.62, 95% CI: -0.02-1.25), but similar rate of decline. Non-Hispanic Blacks had lower cognitive scores at baseline and throughout follow-up regardless of cancer status compared to non-Hispanic Whites and other races/ethnicities with and without cancer history. CONCLUSION: In this longitudinal retrospective study, participants with cancer history demonstrate better cognition at dementia diagnosis and no difference in cognitive decline than those without cancer history. Smoking and comorbidities attenuate this association and results indicate non-Hispanic Blacks have worse cognitive outcomes in dementia regardless of cancer history than other race/ethnicity groups. Further exploration of the role of smoking, comorbidities, and race/ethnicity on cancer and dementia-related cognitive decline is needed.

Relationships Between the Deposition of Amyloid-β and Tau Protein and Glymphatic System Activity in Alzheimer's Disease: Diffusion Tensor Image Study. - Ota, Miho; Sato, Noriko; Nakaya, Moto; Shigemoto, Yoko; Kimura, Yukio; Chiba, Emiko; Yokoi, Yuma; Tsukamoto, Tadashi; Matsuda, Hiroshi (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) and tau protein accumulation in the brain is thought to be one of the causes of Alzheimer's disease (AD). Recent study found that the glymphatic system was waste drainage system in the brain and promoting the elimination of Aβ and tau protein. OBJECTIVE: Objective: We evaluated the relationships between the glymphatic system activity and Aβ and tau protein deposition. METHODS: Subjects were 21 patients with AD and 36 healthy subjects who underwent diffusion tensor imaging (DTI) scan and the positron emission tomography using with the Aβ tracer: 11C-PiB and the tau/inflammatory tracer: 18F-THK5351. We computed diffusion tensor image analysis along the perivascular space (DTI-ALPS) index as the proxy of glymphatic system activity and estimated the relationships between the DTI-ALPS index and Aβ and tau protein/inflammatory deposition. RESULTS: We found significant negative correlations between DTI-ALPS index and the standard uptake value ratio (SUVR) of 11C-PiB in the bilateral temporal and left parietal cortices and left posterior cingulate gyrus in all subjects. Further, we detected significant negative correlations between DTI-ALPS index and the SUVR of 18F-THK5351 in the bilateral temporal cortices and right parietal cortex in all participants, too. CONCLUSION: Our data suggested that DTI-ALPS index was a good biomarker for the evaluation of Aβ and tau deposition and neuroinflammation, and this marker might be effective to estimate the glymphatic system activity.

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

The Role of Amyloid, Tau, and APOE Genotype on the Relationship Between Informant-Reported Sleep Disturbance and Alzheimer's Disease Risks. - Kim, Hyun; Levine, Alina; Cohen, Daniel; Gehrman, Philip; Zhu, Xi; Devanand, Davangere P; Lee, Seonjoo; Goldberg, Terry E (J Alzheimers Dis, 2022)
BACKGROUND: The association between sleep and Alzheimer's disease (AD) biomarkers are well-established, but little is known about how they interact to change the course of AD. OBJECTIVE: To determine the potential interaction between sleep disturbance and Aβ, tau, and APOE4 on brain atrophy and cognitive decline. METHODS: Sample included 351 participants (mean age 72.01 ± 6.67, 50.4%female) who were followed for approximately 5 years as part of the Alzheimer's Disease Neuroimaging Initiative. Informant-reported sleep disturbance (IRSD) was measured using the Neuropsychiatric Inventory (NPI). Changes in magnetic resonance imaging (MRI)-measured AD signature brain regions and cognitive performance and IRSD's interaction with cerebrospinal fluid amyloid-β (Aβ42) and p-Tau depositions and APOE4 status were examined using the linear mixed models. RESULTS: Baseline IRSD was not significantly associated with the rate of atrophy after adjusting for covariates (age, sex, education, total NPI severity score, and sleep medications). However, there was a significant interaction between IRSD and AD biomarkers on faster atrophy rates in multiple brain regions, including the cortical and middle temporal volumes. Post-hoc analyses indicated that Aβ and p-Tau/Aβ predicted a faster decline in these regions/domains in IRSD, compared with biomarker-negative individuals with IRSD (ps≤0.001). There was a significant IRSD*APOE4 interaction for brain atrophy rate (ps≤0.02) but not for cognition. CONCLUSION: IRSD may increase the future risk of AD by contributing to faster brain atrophy and cognitive decline when combined with the presence of AD biomarkers and APOE4. Early intervention for sleep disturbance could help reduce the risk of developing AD.

Serum Levels of α-Klotho Are Correlated with Cerebrospinal Fluid Levels and Predict Measures of Cognitive Function. - Kundu, Payel; Zimmerman, Benjamin; Quinn, Joseph F; Kaye, Jeffrey; Mattek, Nora; Westaway, Shawn K; Raber, Jacob (J Alzheimers Dis, 2022)
BACKGROUND: α-klotho might play a role in neurodegenerative diseases. OBJECTIVE: To determine levels of α-klotho and apoE in serum and cerebrospinal fluid (CSF) samples and their relationship with the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). METHODS: All subjects were between age 39 to 83+ (n = 94). CDR and MMSE were administered to all participants. CSF was collected in the early afternoon by lumbar puncture. RESULTS: Serum and CSF levels of α-klotho are positively correlated and both predict scores on the MMSE and CDR, regardless of sex or apoE4 status. CONCLUSION: Our results demonstrate that α-klotho may be an important biomarker of cognitive health and neurodegeneration, and that relatively non-invasive sampling of α-klotho from serum is likely highly reflective of CSF levels.

Sex-Specific Patterns of Body Mass Index Relationship with White Matter Connectivity. - Rahmani, Farzaneh; Wang, Qing; McKay, Nicole S; Keefe, Sarah; Hantler, Nancy; Hornbeck, Russ; Wang, Yong; Hassenstab, Jason; Schindler, Suzanne; Xiong, Chengjie; Morris, John C; Benzinger, Tammie L S; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Obesity is an increasingly recognized modifiable risk factor for Alzheimer's disease (AD). Increased body mass index (BMI) is related to distinct changes in white matter (WM) fiber density and connectivity. OBJECTIVE: We investigated whether sex differentially affects the relationship between BMI and WM structural connectivity. METHODS: A cross-sectional sample of 231 cognitively normal participants were enrolled from the Knight Alzheimer Disease Research Center. Connectome analyses were done with diffusion data reconstructed using q-space diffeomorphic reconstruction to obtain the spin distribution function and tracts were selected using a deterministic fiber tracking algorithm. RESULTS: We identified an inverse relationship between higher BMI and lower connectivity in the associational fibers of the temporal lobe in overweight and obese men. Normal to overweight women showed a significant positive association between BMI and connectivity in a wide array of WM fibers, an association that reversed in obese and morbidly obese women. Interaction analyses revealed that with increasing BMI, women showed higher WM connectivity in the bilateral frontoparietal and parahippocampal parts of the cingulum, while men showed lower connectivity in right sided corticostriatal and corticopontine tracts. Subgroup analyses demonstrated comparable results in participants with and without positron emission tomography or cerebrospinal fluid evidence of brain amyloidosis, indicating that the relationship between BMI and structural connectivity in men and women is independent of AD biomarker status. CONCLUSION: BMI influences structural connectivity of WM differently in men and women across BMI categories and this relationship does not vary as a function of preclinical AD.

Shortening of Saccades as a Possible Easy-to-Use Biomarker to Detect Risk of Alzheimer's Disease. - Hannonen, Sanna; Andberg, Sami; Kärkkäinen, Virve; Rusanen, Minna; Lehtola, Juha-Matti; Saari, Toni; Korhonen, Ville; Hokkanen, Laura; Hallikainen, Merja; Hänninen, Tuomo; Leinonen, Ville; Kaarniranta, Kai; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Wide-ranging functional defects in eye movements have been reported in Alzheimer's disease (AD) dementia. The detection of abnormal eye movements and reading problems may identify persons at risk of AD when clear clinical symptoms are lacking. OBJECTIVE: To examine whether computer-based eye-tracking (ET) analysis of King-Devick (KD) test results differentiates cognitively healthy persons from persons with minor problems in cognitive testing or diagnosed mild AD. METHODS: We recruited 78 participants (57 non-demented, 21 with mild AD) who underwent neurological examination, the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological test battery (CERAD-NB), and a Clinical Dementia Rating (CDR) interview. The non-demented participants were further divided into control (normal CERAD subtests, mean MMSE = 28) and objective mild cognitive impairment (MCI; decline in at least one CERAD memory score, mean MMSE = 27) groups. The KD reading test was performed using computer-based ET. The total time used for the reading test, errors made, fixation and saccade durations, and saccade amplitudes were analyzed. RESULTS: We found significant differences between the control, objective MCI, and AD groups in regard to the mean saccade amplitude (3.58, 3.33, and 3.21 ms, respectively, p < 0.03) and duration (27.1, 25.3, and 24.8 ms, respectively, p < 0.05). The KD error scores in the AD group differed significantly (p < 0.01) from the other groups. CONCLUSION: Computed ET analysis of the KD test may help detect persons with objective MCI early when clear clinical symptoms are lacking. The portable device for ET is easy to use in primary health care memory clinics.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Humans; Neuropsychological Tests; Saccades

Small RNA Sequencing in the Tg4-42 Mouse Model Suggests the Involvement of snoRNAs in the Etiology of Alzheimer's Disease. - Lio, Chit Tong; Kacprowski, Tim; Klaedtke, Maik; Jensen, Lars R; Bouter, Yvonne; Bayer, Thomas A; Kuss, Andreas W (J Alzheimers Dis, 2022)
BACKGROUND: The Tg4-42 mouse model for sporadic Alzheimer's disease (AD) has unique features, as the neuronal expression of wild type N-truncated Aβ4-42 induces an AD-typical neurological phenotype in the absence of plaques. It is one of the few models developing neuron death in the CA1 region of the hippocampus. As such, it could serve as a powerful tool for preclinical drug testing and identification of the underlying molecular pathways that drive the pathology of AD. OBJECTIVE: The aim of this study was to use a differential co-expression analysis approach for analyzing a small RNA sequencing dataset from a well-established murine model in order to identify potentially new players in the etiology of AD. METHODS: To investigate small nucleolar RNAs in the hippocampus of Tg4-42 mice, we used RNA-Seq data from this particular tissue and, instead of analyzing the data at single gene level, employed differential co-expression analysis, which takes the comparison to gene pair level and thus affords a new angle to the interpretation of these data. RESULTS: We identified two clusters of differentially correlated small RNAs, including Snord55, Snord57, Snord49a, Snord12, Snord38a, Snord99, Snord87, Mir1981, Mir106b, Mir30d, Mir598, and Mir99b. Interestingly, some of them have been reported to be functionally relevant in AD pathogenesis, as AD biomarkers, regulating tau phosphorylation, TGF-β receptor function or Aβ metabolism. CONCLUSION: The majority of snoRNAs for which our results suggest a potential role in the etiology of AD were so far not conspicuously implicated in the context of AD pathogenesis and could thus point towards interesting new avenues of research in this field.

Systemic Injection of Aged Blood Plasma in Adult C57BL/6 Mice Induces Neurophysiological Impairments in the Hippocampal CA1. - Huffels, Christiaan F M; van Dijk, Roland E; Karst, Henk; Meye, Frank J; Hol, Elly M; Middeldorp, Jinte (J Alzheimers Dis, 2022)
BACKGROUND: Aging is characterized by systemic alterations and forms an important risk factor for Alzheimer's disease. Recently, it has been indicated that blood-borne factors present in the systemic milieu contribute to the aging process. Exposing young mice to aged blood plasma results in impaired neurogenesis and synaptic plasticity in the dentate gyrus, as well as impaired cognition. Vice versa, treating aged mice with young blood plasma rescues impairments associated with aging. OBJECTIVE: Whether blood-borne factors are sufficient to drive impairments outside the dentate gyrus, how they impact neurophysiology, and how the functional outcome compares to impairments found in mouse models for AD is still unclear. METHODS: Here, we treated adult mice with blood plasma from aged mice and assessed neurophysiological parameters in the hippocampal CA1. RESULTS: Mice treated with aged blood plasma show significantly impaired levels of long-term potentiation (LTP), similar to those present in APP/PS1 mice. These impaired levels of LTP in plasma-treated mice are associated with alterations in basic properties of glutamatergic transmission and the enhanced activity of voltage-gated Ca2 + channels. CONCLUSION: Together, the data presented in this study show that blood-borne factors are sufficient to drive neurophysiological impairments in the hippocampal CA1.

Undiagnosed Dementia Is Associated with Poor Physical Function in Older Adults. - McGrath, Ryan; Robinson-Lane, Sheria G; Klawitter, Lukus; Rhee, Yeong; Hamm, Jeremy M; McCourt, Mark E; Parker, Kelly; Hackney, Kyle J (J Alzheimers Dis, 2022)
BACKGROUND: Older adults with a cognitive impairment, including those not yet diagnosed, may have deficits in their physical function. OBJECTIVE: We sought to determine the associations of cognitive impairment consistent with dementia (CICD) diagnosis status on handgrip strength, gait speed, and functional disability in older adults. METHODS: The analytical sample included 8,383 adults aged ≥65-years without history of stroke, cancers, neurological conditions, or brain damage who participated in at least one-wave of the 2010-2016 waves of the Health and Retirement Study. A handgrip dynamometer measured handgrip strength. Men with handgrip strength RESULTS: Persons with undiagnosed CICD had 1.37 (95% confidence interval (CI): 1.04-1.80) greater odds for weakness and 2.02 (CI: 1.39-2.94) greater odds for slow gait speed. Older adults with diagnosed CICD had 2.29 (CI: 1.32-3.97) greater odds for slowness and 1.85 (CI: 1.19-2.90) greater odds for functional disability. CONCLUSION: Screening for CICD could be recommended when defects in physical function are observed in older adults.

Visually Identified Tau 18F-MK6240 PET Patterns in Symptomatic Alzheimer's Disease. - Krishnadas, Natasha; Huang, Kun; Schultz, Stephanie A; Doré, Vincent; Bourgeat, Pierrick; Goh, Anita M Y; Lamb, Fiona; Bozinovski, Svetlana; Burnham, Samantha C; Robertson, Joanne S; Laws, Simon M; Maruff, Paul; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease, heterogeneity has been observed in the postmortem distribution of tau neurofibrillary tangles. Visualizing the topography of tau in vivo may facilitate clinical trials and clinical practice. OBJECTIVE: This study aimed to investigate whether tau distribution patterns that are limited to mesial temporal lobe (MTL)/limbic regions, and those that spare MTL regions, can be visually identified using 18F-MK6240, and whether these patterns are associated with different demographic and cognitive profiles. METHODS: Tau 18F-MK6240 PET images of 151 amyloid-β positive participants with mild cognitive impairment (MCI) and dementia were visually rated as: tau negative, limbic predominant (LP), MTL-sparing, and Typical by two readers. Groups were evaluated for differences in age, APOE ɛ4 carriage, hippocampal volumes, and cognition (MMSE, composite memory and non-memory scores). Voxel-wise contrasts were also performed. RESULTS: Visual rating resulted in 59.6% classified as Typical, 17.9% as MTL-sparing, 9.9% LP, and 12.6% as tau negative. Intra-rater and inter-rater reliability was strong (Cohen's kappa values of 0.89 and 0.86 respectively). Tracer retention in a "hook"-like distribution on sagittal sequences was observed in the LP and Typical groups. The visually classified MTL-sparing group had lower APOE ɛ4 carriage and relatively preserved hippocampal volumes. Higher MTL tau was associated with greater amnestic cognitive impairment. High cortical tau was associated with greater impairments on non-memory domains of cognition, and individuals with high cortical tau were more likely to have dementia than MCI. CONCLUSION: Tau distribution patterns can be visually identified using 18F-MK6240 PET and are associated with differences in APOE ɛ4 carriage, hippocampal volumes, and cognition.

Weight Loss and Alzheimer's Disease in Down Syndrome. - Fleming, Victoria; Helsel, Brian C; Ptomey, Lauren T; Rosas, H Diana; Handen, Benjamin; Laymon, Charles; Christian, Bradley T; Head, Elizabeth; Mapstone, Mark; Lai, Florence; Krinsky-McHale, Sharon; Zaman, Shahid; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Virtually all adults with Down syndrome (DS) develop Alzheimer's disease (AD) pathology, but research gaps remain in understanding early signs of AD in DS. OBJECTIVE: The goal of the present study was to determine if unintentional weight loss is part of AD in DS. The specific aims were to: 1) examine relation between chronological age, weight, AD pathology, and AD-related cognitive decline were assessed in a large cohort of adults with DS, and 2) determine if baseline PET amyloid-β (Aβ) and tau PET status (-versus+) and/or decline in memory and mental status were associated with weight loss prior to AD progression. METHODS: Analyses included 261 adults with DS. PET data were acquired using [11C] PiB for Aβ and [18F] AV-1451 for tau. Body mass index (BMI) was calculated from weight and height. Direct measures assessed dementia and memory. Clinical AD status was determined using a case consensus process. Percent weight decline across 16-20 months was assessed in a subset of participants (n = 77). RESULTS: Polynomial regressions indicated an 0.23 kg/m2 decrease in BMI per year beginning at age 36.5 years, which occurs alongside the period during which Aβ and tau increase and memory and mental status decline. At a within-person level, elevated Aβ, decline in memory and mental status were associated with higher percent weight loss across 16-20 months. CONCLUSION: Unintentional weight loss occurs alongside Aβ deposition and prior to onset of AD dementia, and thus may be a useful sign of AD in DS.

Yoga Prevents Gray Matter Atrophy in Women at Risk for Alzheimer's Disease: A Randomized Controlled Trial. - Krause-Sorio, Beatrix; Siddarth, Prabha; Kilpatrick, Lisa; Milillo, Michaela M; Aguilar-Faustino, Yesenia; Ercoli, Linda; Narr, Katherine L; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2022)
BACKGROUND: Female sex, subjective cognitive decline (SCD), and cardiovascular risk factors (CVRFs) are known risk factors for developing Alzheimer's disease (AD). We previously demonstrated that yoga improved depression, resilience, memory and executive functions, increased hippocampal choline concentrations, and modulated brain connectivity in older adults with mild cognitive impairment. OBJECTIVE: In this study (NCT03503669), we investigated brain gray matter volume (GMV) changes in older women with SCD and CVRFs following three months of yoga compared to memory enhancement training (MET). METHODS: Eleven women (mean age = 61.45, SD = 6.58) with CVRF and SCD completed twelve weeks of Kundalini Yoga and Kirtan Kriya (KY + KK) while eleven women (mean age = 64.55, SD = 6.41) underwent MET. Anxiety, resilience, stress, and depression were assessed at baseline and 12 weeks, as were T1-weighted MRI scans (Siemens 3T Prisma scanner). We used Freesurfer 6.0 and tested group differences in GMV change, applying Monte-Carlo simulations with alpha = 0.05. Region-of-interest analysis was performed for hippocampus and amygdala. RESULTS: Compared to KY + KK, MET showed reductions in GMV in left prefrontal, pre- and post-central, supramarginal, superior temporal and pericalcarine cortices, right paracentral, postcentral, superior and inferior parietal cortices, the banks of the superior temporal sulcus, and the pars opercularis. Right hippocampal volume increased after yoga but did not survive corrections. CONCLUSION: Yoga training may offer neuroprotective effects compared to MET in preventing neurodegenerative changes and cognitive decline, even over short time intervals. Future analyses will address changes in functional connectivity in both groups.

α-Lipoic Acid Has the Potential to Normalize Copper Metabolism, Which Is Dysregulated in Alzheimer's Disease. - Metsla, Kristel; Kirss, Sigrid; Laks, Katrina; Sildnik, Gertrud; Palgi, Mari; Palumaa, Teele; Tõugu, Vello; Palumaa, Peep (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is an age-dependent progressive neurodegenerative disorder and the most common cause of dementia. The treatment and prevention of AD present immense yet unmet needs. One of the hallmarks of AD is the formation of extracellular amyloid plaques in the brain, composed of amyloid-β (Aβ) peptides. Besides major amyloid-targeting approach there is the necessity to focus also on alternative therapeutic strategies. One factor contributing to the development of AD is dysregulated copper metabolism, reflected in the intracellular copper deficit and excess of extracellular copper. OBJECTIVE: In the current study, we follow the widely accepted hypothesis that the normalization of copper metabolism leads to the prevention or slowing of the disease and search for new copper-regulating ligands. METHODS: We used cell culture, ICP MS, and Drosophila melanogaster models of AD. RESULTS: We demonstrate that the natural intracellular copper chelator, α-lipoic acid (LA) translocates copper from extracellular to intracellular space in an SH-SY5Y-based neuronal cell model and is thus suitable to alleviate the intracellular copper deficit characteristic of AD neurons. Furthermore, we show that supplementation with LA protects the Drosophila melanogaster models of AD from developing AD phenotype by improving locomotor activity of fruit fly with overexpression of human Aβ with Iowa mutation in the fly brain. In addition, LA slightly weakens copper-induced smooth eye phenotype when amyloid-β protein precursor (AβPP) and beta-site AβPP cleaving enzyme 1 (BACE1) are overexpressed in eye photoreceptor cells. CONCLUSION: Collectively, these results provide evidence that LA has the potential to normalize copper metabolism in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Brain; Cell Line; Copper; Disease Models, Animal; Drosophila melanogaster; Humans; Neurons; Thioctic Acid

Alzheimer's Disease-Related Neuropathology Among Patients with Medication Treated Type 2 Diabetes in a Community-Based Autopsy Cohort. - Barthold, Douglas; Gibbons, Laura E; Marcum, Zachary A; Gray, Shelly L; Dirk Keene, C; Grabowski, Thomas J; Postupna, Nadia; Larson, Eric B; Crane, Paul K (J Alzheimers Dis, 2021)
BACKGROUND: Diabetes is a risk factor for Alzheimer's disease and related dementias (ADRD). Epidemiologic evidence shows an association between diabetes medications and ADRD risk; cell and mouse models show diabetes medication association with AD-related neuropathologic change (ADNC). OBJECTIVE: This hypothesis-generating analysis aimed to describe autopsy-measured ADNC for individuals who used diabetes medications. METHODS: Descriptive analysis of ADNC for Adult Changes in Thought (ACT) Study autopsy cohort who used diabetes medications, including sulfonylureas, insulin, and biguanides; total N = 118. ADNC included amyloid plaque distribution (Thal phasing), neurofibrillary tangle (NFT) distribution (Braak stage), and cortical neuritic plaque density (CERAD score). We also examined quantitative measures of ADNC using the means of standardized Histelide measures of cortical PHF-tau and Aβ 1-42. Adjusted analyses control for age at death, sex, education, APOE genotype, and diabetes complication severity index. RESULTS: Adjusted analyses showed no significant association between any drug class and traditional neuropathologic measures compared to nonusers of that class. In adjusted Histelide analyses, any insulin use was associated with lower mean levels of Aβ 1-42 (-0.57 (CI: -1.12, -0.02)) compared to nonusers. Five years of sulfonylureas and of biguanides use was associated with lower levels of Aβ 1-42 compared to nonusers (-0.15 (CI: -0.28, -0.02), -0.31 (CI: -0.54, -0.07), respectively). CONCLUSION: Some evidence exists that diabetes medications are associated with lower levels of Aβ 1-42, but not traditional measures of neuropathology. Future studies are needed in larger samples to build understanding of the mechanisms between diabetes, its medications, and ADRD, and to potentially repurpose existing medications for prevention or delay of ADRD.

Anti-Aβ Antibody Aducanumab Regulates the Proteome of Senile Plaques and Closely Surrounding Tissue in a Transgenic Mouse Model of Alzheimer's Disease. - Bastrup, Joakim; Hansen, Kathrine H; Poulsen, Thomas B G; Kastaniegaard, Kenneth; Asuni, Ayodeji A; Christensen, Søren; Belling, Dorthe; Helboe, Lone; Stensballe, Allan; Volbracht, Christiane (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by accumulation of amyloid-β (Aβ) species and deposition of senile plaques (SPs). Clinical trials with the anti-Aβ antibody aducanumab have been completed recently. OBJECTIVE: To characterize the proteomic profile of SPs and surrounding tissue in a mouse model of AD in 10-month-old tgAPPPS1-21 mice after chronic treatment with aducanumab for four months with weekly dosing (10 mg/kg). METHODS: After observing significant reduction of SP numbers in hippocampi of aducanumab-treated mice, we applied a localized proteomic analysis by combining laser microdissection and liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the remaining SPs in hippocampi. We microdissected three subregions, containing SPs, SP penumbra level 1, and an additional penumbra level 2 to follow the proteomic profile as gradient. RESULTS: In the aducanumab-treated mice, we identified 17 significantly regulated proteins that were associated with 1) mitochondria and metabolism (ACAT2, ATP5J, ETFA, EXOG, HK1, NDUFA4, NDUFS7, PLCB1, PPP2R4), 2) cytoskeleton and axons (ADD1, CAPZB, DPYSL3, MAG), 3) stress response (HIST1H1C/HIST1H1D, HSPA12A), and 4) AβPP trafficking/processing (CD81, GDI2). These pathways and some of the identified proteins are implicated in AD pathogenesis. Proteins associated with mitochondria and metabolism were mainly upregulated while proteins associated with AβPP trafficking/processing and stress response pathways were mainly downregulated, suggesting that aducanumab could lead to a beneficial proteomic profile around SPs in tgAPPPS1-21 mice. CONCLUSION: We identified novel proteomic patterns of SPs and surrounding tissue indicating that chronic treatment with aducanumab could inhibit Aβ toxicity and increase phagocytosis and cell viability.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Antibodies, Monoclonal, Humanized; Brain; Chromatography, Liquid; Cytoskeletal Proteins; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Mitochondrial Proteins; Plaque, Amyloid; Presenilin-1; Protein Transport; Proteome; Proteomics; Stress, Physiological; Tandem Mass Spectrometry

Apolipoprotein E ɛ4 (APOE ɛ4) Allele is Associated with Long Sleep Duration Among Elderly with Cognitive Impairment. - Basta, Maria; Zaganas, Ioannis; Simos, Panagiotis; Koutentaki, Eirini; Dimovasili, Christina; Mathioudakis, Lambros; Bourbouli, Mara; Panagiotakis, Symeon; Kapetanaki, Stefania; Vgontzas, Alexandros (J Alzheimers Dis, 2021)
BACKGROUND: Apolipoprotein E gene (APOE) ɛ4 allele increases the risk for Alzheimer's disease (AD). Furthermore, among patients with cognitive impairment, longer sleep duration is associated with worse cognitive performance. To date, literature examining the associations between APOE ɛ4 allele and objective sleep duration is limited. OBJECTIVE: Our aim was to assess the association between APOE ɛ4 and objective sleep duration, among patients with mild cognitive impairment (MCI) and AD. A sub-sample of 89 patients with AD (n = 49) and MCI (n = 40) were recruited from a large, population-based cohort of 3,140 elders (>60 years) residing on Crete, Greece. METHODS: All participants underwent medical history/physical examination, extensive neuropsychiatric and neuropsychological evaluation, 3-day 24 h actigraphy and APOE ɛ4 allele genotyping. Comparisons of sleep duration variables between APOE ɛ4 allele carriers and non-carriers were assessed using ANCOVA, controlling for confounders. RESULTS: The sample included 18 APOE ɛ4 carriers and 71 non-carriers, aged 78.6±6.6 and 78.2±6.5 years, respectively. Comparisons between the APOE ɛ4 carriers and non-carriers revealed no significant differences in terms of demographic and clinical variables. In terms of objective sleep duration across the two groups, APOE ɛ4 carriers compared to non-carriers had significantly longer nighttime Total Sleep Time (nTST) (7.7±1.4 versus 7.2±1.3  h, respectively, p = 0.011), as well as 24 h TST (8.5±1.6 versus 7.8±1.5  h, respectively, p = 0.012). CONCLUSION: Among patients with MCI and AD, APOE ɛ4 carriers have longer objective nighttime and 24 h sleep duration compared to non-carriers. These findings further support that objective long sleep duration is a genetically-driven pre-clinical marker associated with worse prognosis in elderly with cognitive impairment.

Assessing the Progression of Alzheimer's Disease in Real-World Settings in Three European Countries. - Lladó, Albert; Froelich, Lutz; Khandker, Rezaul K; Roset, Montserrat; Black, Christopher M; Lara, Nuria; Chekani, Farid; Ambegaonkar, Baishali M (J Alzheimers Dis, 2021)
BACKGROUND: There exists considerable variation in disease progression rates among patients with Alzheimer's disease (AD). OBJECTIVE: The primary objective of this observational study is to assess the progression of AD by characterizing cognitive, functional, and behavioral changes during the follow-up period between 6 and 24 months. METHODS: A longitudinal prospective study with community-dwelling patients with an established clinical diagnosis of AD of mild to moderate severity was conducted in Germany, Spain and the UK. A sample of 616 patients from 69 sites was included. RESULTS: Patients had a mean of 1.9 years (SD = 1.9) since AD diagnosis at study inclusion. Cognitive symptoms were reported to have first occurred a mean of 1.1 years (SD = 1.7) prior to AD diagnosis and 1.4 (SD = 1.8) years prior to AD treatment. Patients initially diagnosed with mild and moderate AD spent a median (95%CI) of 3.7 (2.8; 4.4) and 11.1 (6.1, 'not reached') years until progression to moderate and severe AD, respectively, according to the Mini-Mental State Examination (MMSE) scores. A mixed model developed for cognitive, functional, and neuropsychiatric scores, obtained from study patients at baseline and during follow-up period, showed progressive deterioration of AD patients over time. CONCLUSION: The study showed a deterioration of cognitive, functional, and neuropsychiatric functions during the follow-up period. Cognitive deterioration was slightly faster in patients with moderate AD compared to mild AD. The duration of moderate AD can be overestimated due to the use of retrospective data, lack of availability of MMSE scores in clinical charts and exclusion of patients at time of institutionalization.
Keywords: Alzheimer Disease; Cholinesterase Inhibitors; Cognition Disorders; Disease Progression; Europe; Germany; Humans; Institutionalization; Neuropsychological Tests; Spain

Association of Amyloid-β Pathology with Decision Making and Scam Susceptibility. - Kapasi, Alifiya; Yu, Lei; Stewart, Christopher; Schneider, Julie A; Bennett, David A; Boyle, Patricia A (J Alzheimers Dis, 2021)
BACKGROUND: Recent findings suggest that poor decision making and increased scam susceptibility are harbingers of Alzheimer's disease (AD) dementia and may be among the earliest behavioral manifestations of pathologic cognitive aging. However, the degree to which poor decision making and scam susceptibility reflect accumulating Alzheimer's disease (AD) pathology remains unclear. OBJECTIVE: To investigate the associations of AD pathology with decision making and scam susceptibility in older adults without dementia. METHODS: Data came from 198 deceased participants without clinical dementia (mean age at death = 90 years; 69%women) from two ongoing studies of aging. All underwent annual clinical evaluations, completed assessments of healthcare and financial decision making and scam susceptibility, and brain donation. Neuropathologic evaluations quantified pathologic hallmarks of AD, amyloid-β and tau-tangles, Lewy body pathology, and TDP-43 proteinopathy. RESULTS: In linear regression models adjusted for demographics, amyloid-β pathology was associated with lower decision making (estimate = -0.35; SE = 0.16, p = 0.03), particularly healthcare decision making (estimate = -0.20; SE = 0.09, p = 0.03), as well as greater scam susceptibility (estimate = 0.12; SE = 0.04, p = 0.003); tau-tangle pathology was not related. Further, TDP-43 pathology was associated with greater scam susceptibility (estimate = 0.10; SE = 0.04; p = 0.02). CONCLUSION: Accumulating AD pathology, particularly amyloid-β, is associated with poor decision making and increased scam susceptibility among older persons without overt cognitive impairment. These findings provide compelling evidence that decision making and scam susceptibility are sensitive to the earliest pathological changes of AD.

The Association of Essential Metals with APOE Genotype in Alzheimer's Disease. - Babić Leko, Mirjana; Jurasović, Jasna; Nikolac Perković, Matea; Španić, Ena; Sekovanić, Ankica; Orct, Tatjana; Lukinović Škudar, Vesna; Bačić Baronica, Koraljka; Kiđemet-Piskač, Spomenka; Vogrinc, Željka; Pivac, Nela; Borovečki, Fran; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The major confirmed genetic risk factor for late-onset, sporadic Alzheimer's disease (AD) is variant ɛ4 of apolipoprotein E gene (APOE). It is proposed that ApoE, a protein involved in transport of cholesterol to neurons can cause neurodegeneration in AD through interaction with metals. Previous studies mostly associated copper, iron, zinc, and calcium with ApoE4-mediated toxicity. OBJECTIVE: To test the association of essential metals with APOE genotype. METHODS: We compared plasma and cerebrospinal fluid (CSF) levels of copper, zinc, iron, sodium, magnesium, calcium, cobalt, molybdenum, manganese, boron, and chromium, and CSF ferritin levels among AD, mild cognitive impairment (MCI) patients, and healthy controls (HC) with different APOE genotype. RESULTS: Sodium, copper, and magnesium levels were increased in carriers of ɛ4 allele. Additionally, the increase in sodium, calcium and cobalt plasma levels was observed in carriers of ɛ4/ɛx genotype. The decrease in boron plasma levels was observed in carriers of ɛ4 allele and ɛ4/ɛ4 genotype. Additionally, CSF zinc levels as well as plasma sodium levels were increased in AD patients compared to HC. CONCLUSION: These results indicate that the molecular underpinnings of association of essential metals and metalloids with APOE should be further tested and clarified in vivo and in vitro.

Association of Malnutrition with Functional and Cognitive Trajectories in People Living with Dementia: A Five-Year Follow-Up Study. - Borda, Miguel Germán; Ayala Copete, Ana María; Tovar-Rios, Diego Alejandro; Jaramillo-Jimenez, Alberto; Giil, Lasse Melvær; Soennesyn, Hogne; Gómez-Arteaga, Camilo; Venegas-Sanabria, Luis Carlos; Kristiansen, Ida; Chavarro-Carvajal, Diego Andrés; Caicedo, Sandra; Cano-Gutierrez, Carlos Alberto; et al. (J Alzheimers Dis, 2021)
BACKGROUND: In dementia, functional status depends on multiple factors in addition to cognition. Nutritional status is a potentially modifiable factor related to homeostasis and proper functioning of body systems and may contribute to cognitive and functional decline. OBJECTIVE: This paper aims to analyze the association of malnutrition with the course of cognitive and functional decline in people living with dementia. METHODS: This is an analysis of a longitudinal cohort study, the Dementia Study of Western Norway. Data of 202 patients diagnosed with mild dementia were analyzed; Alzheimer's disease (AD) (n = 103), Lewy body dementia (LBD) (n = 74), and other dementias (OD) (n = 25). Cognition was assessed with the Mini-Mental State Examination and functional decline through the activities of daily living included in the Rapid Disability Rating Scale. The Global Leadership Initiative on Malnutrition Index was used to determine nutritional status. Associations of nutritional status with cognitive and functional decline were evaluated through adjusted linear mixed models. RESULTS: At baseline, the prevalence of general malnutrition was 28.7%; 17.32% were classified as moderate malnutrition and 11.38% as severe malnutrition (there were no significant differences between AD and LBD). Malnutrition at diagnosis and over follow-up was a significant predictor of functional-decline, but not of cognitive decline. CONCLUSION: According to our results malnutrition was associated with faster functional loss but, not cognitive decline in older adults with dementia. A more comprehensive dementia approach including nutritional assessments could improve prognosis.

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

Association of White Matter Hyperintensity Progression with Cognitive Decline in Patients with Amnestic Mild Cognitive Impairment. - Hirao, Kentaro; Yamashita, Fumio; Tsugawa, Akito; Haime, Rieko; Fukasawa, Raita; Sato, Tomohiko; Kanetaka, Hidekazu; Umahara, Takahiko; Sakurai, Hirofumi; Hanyu, Haruo; Shimizu, Soichiro (J Alzheimers Dis, 2021)
BACKGROUND: White matter hyperintensities (WMH) on MRI have been reported to increase the risk of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD). However, effects of the progression of WMH on the cognition of patients with MCI remains unclear to date. OBJECTIVE: To investigate the association between WMH progression and cognitive decline in amnestic MCI patients. METHODS: Thirty-eight subjects with amnestic MCI were analyzed prospectively every year for 2 years. Fourteen MCI subjects dropped out on the final visit, and therefore 24 subjects with MCI were analyzed for the entire duration. The volumes of periventricular hyperintensities (PVH) and deep WMH (DWMH) were measured on T2 FLAIR using the 3D-slicer. The associations between PVH/DWMH progression and cognitive decline were investigated. RESULTS: An increase in DWMH volume significantly correlated with changes in Mini-Mental State Examination and category verbal fluency scores, whereas an increase in PVH volume did not correlate with changes in any item. CONCLUSION: DWMH progression was closely associated with a decline in frontal lobe function and semantic memory, suggesting that WMH progression might affect some AD pathophysiologies in amnestic MCI patients.

Blood-Based ATN Biomarkers of Alzheimer's Disease: A Meta-Analysis. - Koychev, Ivan; Jansen, Katrin; Dette, Alina; Shi, Liu; Holling, Heinz (J Alzheimers Dis, 2021)
BACKGROUND: The Amyloid Tau Neurodegeneration (ATN) framework was proposed to define the biological state underpinning Alzheimer's disease (AD). Blood-based biomarkers offer a scalable alternative to the costly and invasive currently available biomarkers. OBJECTIVE: In this meta-analysis we sought to assess the diagnostic performance of plasma amyloid (Aβ40, Aβ42, Aβ42/40 ratio), tangle (p-tau181), and neurodegeneration (total tau [t-tau], neurofilament light [NfL]) biomarkers. METHODS: Electronic databases were screened for studies reporting biomarker concentrations for AD and control cohorts. Biomarker performance was examined by random-effect meta-analyses based on the ratio between biomarker concentrations in patients and controls. RESULTS: 83 studies published between 1996 and 2020 were included in the analyses. Aβ42/40 ratio as well as Aβ42 discriminated AD patients from controls when using novel platforms such as immunomagnetic reduction (IMR). We found significant differences in ptau-181 concentration for studies based on single molecule array (Simoa), but not for studies based on IMR or ELISA. T-tau was significantly different between AD patients and control in IMR and Simoa but not in ELISA-based studies. In contrast, NfL differentiated between groups across platforms. Exosome studies showed strong separation between patients and controls for Aβ42, t-tau, and p-tau181. CONCLUSION: Currently available assays for sampling plasma ATN biomarkers appear to differentiate between AD patients and controls. Novel assay methodologies have given the field a significant boost for testing these biomarkers, such as IMR for Aβ, Simoa for p-tau181. Enriching samples through extracellular vesicles shows promise but requires further validation.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurodegenerative Diseases; Neurofibrillary Tangles; Neurofilament Proteins; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins

Body Mass Index and Mild Cognitive Impairment Among Middle-Aged and Older Adults from Low- and Middle-Income Countries. - Smith, Lee; Shin, Jae Il; Oh, Hans; Carmichael, Christina; Jacob, Louis; Stefanac, Sinisa; Lindsay, Rosie K; Soysal, Pinar; Veronese, Nicola; Tully, Mark A; Butler, Laurie; Barnett, Yvonne; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The effect of weight modification on future dementia risk is currently a subject of debate and may be modified by age. OBJECTIVE: The aim of the present study was to investigate the association between body mass index (BMI) status with mild cognitive impairment (MCI) (a preclinical stage of dementia) in middle-aged and older adults residing in six low- and middle-income countries using nationally representative data. METHODS: Cross-sectional data from the Study on Global Ageing and Adult Health (SAGE) were analyzed. MCI was defined using the National Institute on Aging-Alzheimer's Association criteria. BMI (kg/m2) was based on measured weight and height and categorized as: underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9), and obese (≥30.0). Multivariable logistic regression analysis and meta-analysis were conducted to assess associations. RESULTS: Data on 32,715 individuals aged ≥50 years with preservation in functional abilities were analyzed [mean (SD) age 62.1 (15.6) years; 51.7% females]. Among those aged 50-64 years, compared to normal weight, underweight (OR = 1.44; 95% CI = 1.14-1.81), overweight (OR = 1.17; 95% CI = 1.002-1.37), and obesity (OR = 1.46; 95% CI = 1.09-1.94) were all significantly associated with higher odds for MCI. In those aged ≥65 years, underweight (OR = 0.71; 95% CI = 0.54-0.95) and overweight (OR = 0.72; 95% CI = 0.55-0.94) were associated with significantly lower odds for MCI, while obesity was not significantly associated with MCI. CONCLUSION: The results of the study suggest that the association between BMI and MCI is likely moderated by age. Future longitudinal studies are required to confirm or refute the present findings before recommendations for policy and practice can be made.

Borrelia burgdorferi Co-Localizing with Amyloid Markers in Alzheimer's Disease Brain Tissues. - Senejani, Alireza G; Maghsoudlou, Jasmin; El-Zohiry, Dina; Gaur, Gauri; Wawrzeniak, Keith; Caravaglia, Cristina; Khatri, Vishwa A; MacDonald, Alan; Sapi, Eva (J Alzheimers Dis, 2021)
BACKGROUND: Infections by bacterial or viral agents have been hypothesized to influence the etiology of neurodegenerative diseases. OBJECTIVE: This study examined the potential presence of Borrelia burgdorferi spirochete, the causative agent of Lyme disease, in brain autopsy tissue of patients diagnosed with either Alzheimer's (AD) or Parkinson's diseases. METHODS: Brain tissue sections from patients with age-matched controls were evaluated for antigen and DNA presence of B. burgdorferi using various methods. Positive Borrelia structures were evaluated for co-localization with biofilm and AD markers such as amyloid and phospho-tau (p-Tau) using immunohistochemical methods. RESULTS: The results showed the presence of B. burgdorferi antigen and DNA in patients with AD pathology and among those, one of them was previously diagnosed with Lyme disease. Interestingly, a significant number of Borrelia-positive aggregates with a known biofilm marker, alginate, were found along with the spirochetal structures. Our immunohistochemical data also showed that Borrelia-positive aggregates co-localized with amyloid and anti-phospho-tau markers. To further prove the potential relationship of B. burgdorferi and amyloids, we infected two mammalian cell lines with B. burgdorferi which resulted in a significant increase in the expression of amyloid-β and p-Tau proteins in both cells lines post-infection. CONCLUSION: These results indicate that B. burgdorferi can be found in AD brain tissues, not just in spirochete but a known antibiotics resistant biofilm form, and its co-localized amyloid markers. In summary, this study provides evidence for a likely association between B. burgdorferi infections and biofilm formation, AD pathology, and chronic neurodegenerative diseases.

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

Central Obesity, Cardiometabolic Risk, and Cognitive Change in the Study of Latinos: Investigation of Neurocognitive Aging. - Stickel, Ariana M; Tarraf, Wassim; Gonzalez, Kevin A; Isasi, Carmen R; Kaplan, Robert; Gallo, Linda C; Zeng, Donglin; Cai, Jianwen; Pirzada, Amber; Daviglus, Martha L; Goodman, Zachary T; Schneiderman, Neil; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The relationships between obesity and cognitive decline in aging are mixed and understudied among Hispanics/Latinos. OBJECTIVE: To understand associations between central obesity, cognitive aging, and the role of concomitant cardiometabolic abnormalities among Hispanics/Latinos. METHODS: Participants included 6,377 diverse Hispanics/Latinos enrolled in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and SOL-Investigation for Neurocognitive Aging (SOL-INCA). Participants were 45 years and older at the first cognitive testing session (Visit 1). Cognitive outcomes (z-score units) included global composite and domain specific (learning, memory, executive functioning, processing speed) measures at a second visit (SOL-INCA, on average, 7 years later), and 7-year change. We used survey linear regression to examine associations between central obesity (waist circumference≥88 cm and≥102 cm for women and men, respectively) and cognition. We also tested whether the relationships between obesity and cognition differed by cardiometabolic status (indication of/treatment for 2 + of the following: high triglycerides, hypertension, hyperglycemia, low high-density lipoprotein cholesterol). RESULTS: Central obesity was largely unassociated with cognitive outcomes, adjusting for covariates. However, among individuals with central obesity, cardiometabolic abnormality was linked to poorer cognitive function at SOL-INCA (ΔGlobalCognition =-0.165, p < 0.001) and to more pronounced cognitive declines over the average 7 years (ΔGlobalCognition = -0.109, p < 0.05); this was consistent across cognitive domains. CONCLUSION: Central obesity alone was not associated with cognitive function. However, presence of both central obesity and cardiometabolic abnormalities was robustly predictive of cognition and 7-year cognitive declines, suggesting that in combination these factors may alter the cognitive trajectories of middle-aged and older Hispanics/Latinos.

Cerebrospinal Fluid Amyloid-β Oligomer Levels in Patients with Idiopathic Normal Pressure Hydrocephalus. - Kawamura, Kaito; Miyajima, Masakazu; Nakajima, Madoka; Kanai, Mitsuyasu; Motoi, Yumiko; Nojiri, Shuko; Akiba, Chihiro; Ogino, Ikuko; Xu, Hanbing; Kamohara, Chihiro; Yamada, Shinya; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The amyloid-β oligomers, consisting of 10-20 monomers (AβO10-20), have strong neurotoxicity and are associated with cognitive impairment in Alzheimer's disease (AD). However, their role in patients with idiopathic normal pressure hydrocephalus (iNPH) is poorly understood. OBJECTIVE: We hypothesized that cerebrospinal fluid (CSF) AβO10-20 accumulates in patients with iNPH, and its clearance after CSF shunting contributes to neurological improvement. We measured CSF AβO10-20 levels before and after CSF shunting in iNPH patients evaluating their diagnostic and prognostic role. METHODS: We evaluated two iNPH cohorts: "evaluation" (cohort-1) with 32 patients and "validation" (cohort-2) with 13 patients. Comparison cohorts included: 27 neurologically healthy controls (HCs), and 16 AD, 15 Parkinson's disease (PD), and 14 progressive supranuclear palsy (PSP) patients. We assessed for all cohorts CSF AβO10-20 levels and their comprehensive clinical data. iNPH cohort-1 pre-shunting data were compared with those of comparison cohorts, using cohort-2 for validation. Next, we compared cohort-1's clinical and CSF data: 1) before and after CSF shunting, and 2) increased versus decreased AβO10-20 levels at baseline, 1 and 3 years after shunting. RESULTS: Cohort-1 had higher CSF AβO10-20 levels than the HCs, PD, and PSP cohorts. This result was validated with data from cohort-2. CSF AβO10-20 levels differentiated cohort-1 from the PD and PSP groups, with an area under receiver operating characteristic curve of 0.94. AβO10-20 levels in cohort-1 decreased after CSF shunting. Patients with AβO10-20 decrease showed better cognitive outcome than those without. CONCLUSION: AβO10-20 accumulates in patients with iNPH and is eliminated by CSF shunting. AβO10-20 can be an applicable diagnostic and prognostic biomarker.

Cerebrospinal Fluid Sulfatide Levels Lack Diagnostic Utility in the Subcortical Small Vessel Type of Dementia. - Svensson, Johan; Blomqvist, Maria; Kettunen, Petronella; Eckerström, Carl; Henricsson, Marcus; Jonsson, Michael; Bjerke, Maria; Månsson, Jan-Eric; Wallin, Anders (J Alzheimers Dis, 2021)
BACKGROUND: Sulfatides (STs) in cerebrospinal fluid (CSF), as well as magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMHs), may reflect demyelination. Here, we investigated the diagnostic utility of CSF ST levels in the subcortical small vessel type of dementia (SSVD), which is characterized by the presence of brain WMHs. OBJECTIVE: To study the diagnostic utility of CSF ST levels in SSVD. METHODS: This was a mono-center, cross-sectional study of SSVD (n = 16), Alzheimer's disease (n = 40), mixed dementia (n = 27), and healthy controls (n = 33). Totally, 20 ST species were measured in CSF by liquid chromatography-mass spectrometry (LC-MS/MS). RESULTS: CSF total ST levels, as well as CSF levels of hydroxylated and nonhydroxylated ST species, did not differ across the study groups. In contrast, CSF neurofilament light chain (NFL) levels separated the patient groups from the controls. CSF total ST level correlated with CSF/serum albumin ratio in the total study population (r = 0.64, p <  0.001) and in all individual study groups. Furthermore, CSF total ST level correlated positively with MRI-estimated WMH volume in the total study population (r = 0.30, p <  0.05), but it did not correlate with CSF NFL level. CONCLUSION: Although there was some relation between CSF total ST level and WMH volume, CSF ST levels were unaltered in all dementia groups compared to the controls. This suggests that CSF total ST level is a poor biomarker of demyelination in SSVD. Further studies are needed to investigate the mechanisms underlying the marked correlation between CSF total ST level and CSF/serum albumin ratio.

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Combining Multimodal Behavioral Data of Gait, Speech, and Drawing for Classification of Alzheimer's Disease and Mild Cognitive Impairment. - Yamada, Yasunori; Shinkawa, Kaoru; Kobayashi, Masatomo; Caggiano, Vittorio; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2021)
BACKGROUND: Gait, speech, and drawing behaviors have been shown to be sensitive to the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, previous studies focused on only analyzing individual behavioral modalities, although these studies suggested that each of these modalities may capture different profiles of cognitive impairments associated with AD. OBJECTIVE: We aimed to investigate if combining behavioral data of gait, speech, and drawing can improve classification performance compared with the use of individual modality and if each of these behavioral data can be associated with different cognitive and clinical measures for the diagnosis of AD and MCI. METHODS: Behavioral data of gait, speech, and drawing were acquired from 118 AD, MCI, and cognitively normal (CN) participants. RESULTS: Combining all three behavioral modalities achieved 93.0% accuracy for classifying AD, MCI, and CN, and only 81.9% when using the best individual behavioral modality. Each of these behavioral modalities was statistically significantly associated with different cognitive and clinical measures for diagnosing AD and MCI. CONCLUSION: Our findings indicate that these behaviors provide different and complementary information about cognitive impairments such that classification of AD and MCI is superior to using either in isolation.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Gait; Humans; Male; Neuropsychological Tests; Speech

Copper Imbalance in Alzheimer's Disease and Its Link with the Amyloid Hypothesis: Towards a Combined Clinical, Chemical, and Genetic Etiology. - Squitti, Rosanna; Faller, Peter; Hureau, Christelle; Granzotto, Alberto; White, Anthony R; Kepp, Kasper P (J Alzheimers Dis, 2021)
The cause of Alzheimer's disease (AD) is incompletely defined. To date, no mono-causal treatment has so far reached its primary clinical endpoints, probably due to the complexity and diverse neuropathology contributing to the neurodegenerative process. In the present paper, we describe the plausible etiological role of copper (Cu) imbalance in the disease. Cu imbalance is strongly associated with neurodegeneration in dementia, but a complete biochemical etiology consistent with the clinical, chemical, and genetic data is required to support a causative association, rather than just correlation with disease. We hypothesize that a Cu imbalance in the aging human brain evolves as a gradual shift from bound metal ion pools, associated with both loss of energy production and antioxidant function, to pools of loosely bound metal ions, involved in gain-of-function oxidative stress, a shift that may be aggravated by chemical aging. We explain how this may cause mitochondrial deficits, energy depletion of high-energy demanding neurons, and aggravated protein misfolding/oligomerization to produce different clinical consequences shaped by the severity of risk factors, additional comorbidities, and combinations with other types of pathology. Cu imbalance should be viewed and integrated with concomitant genetic risk factors, aging, metabolic abnormalities, energetic deficits, neuroinflammation, and the relation to tau, prion proteins, α-synuclein, TAR DNA binding protein-43 (TDP-43) as well as systemic comorbidity. Specifically, the Amyloid Hypothesis is strongly intertwined with Cu imbalance because amyloid-β protein precursor (AβPP)/Aβ are probable Cu/Zn binding proteins with a potential role as natural Cu/Zn buffering proteins (loss of function), and via the plausible pathogenic role of Cu-Aβ.

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

COVID-19 Crisis Effects on Caregiver Distress in Neurocognitive Disorder. - Alexopoulos, Panagiotis; Soldatos, Rigas; Kontogianni, Evangelia; Frouda, Maria; Loanna Aligianni, Souzana; Skondra, Maria; Passa, Maria; Konstantopoulou, Georgia; Stamouli, Evangelia; Katirtzoglou, Evgenia; Politis, Anastasios; Economou, Polychronis; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The outbreak of the COVID-19 pandemic seems to have mental health implications for both people with neurocognitive disorder and their caregivers. OBJECTIVE: The study aimed to shed light on relations between caregiver mental reaction to the pandemic and caregiver distress related to neuropsychiatric symptoms, memory impairment progression, and functional impairment of people with neurocognitive disorder during the period of confinement in Greece. METHODS: The study included caregivers of patients with mild (N = 13) and major (N = 54) neurocognitive disorder. The caregiver-based telephone interview was based on items of the neuropsychiatric inventory questionnaire, the AD8 Dementia Screening Instrument, and the Bristol Activities of Daily Living Scale. Regarding the mental impact of the COVID-19 crisis on caregivers, four single questions referring to their worries in the last seven days were posed, in addition to the scales Generalized Anxiety Disorder 7-Item (GAD-7) and the 22-item Impact of Event Scale-revised (IES-R). A stepwise linear regression model was employed for studying the relationship between caregiver distress and demographic and clinical data and caregiver mental reaction to COVID-19 pandemic outbreak. RESULTS: Caregiver distress severity during the confinement period was influenced not only by memory deficits (p = 0.009) and neuropsychiatric symptoms (p < 0.001) of patients, but also by caregiver hyperarousal (p = 0.003) and avoidance symptoms (p = 0.033) and worries directly linked to the COVID-19 crisis (p = 0.022). CONCLUSION: These observations provide further evidence for the urgent need for support of caregivers of patients with neurocognitive disorder during the COVID-19 pandemic.
Keywords: Aged; Aged, 80 and over; Caregivers; COVID-19; Female; Greece; Humans; Male; Middle Aged; Neurocognitive Disorders; Quarantine

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Droplet Degeneration of Hippocampal and Cortical Neurons Signifies the Beginning of Neuritic Plaque Formation. - Streit, Wolfgang J; Rotter, Jonas; Winter, Karsten; Müller, Wolf; Khoshbouei, Habibeh; Bechmann, Ingo (J Alzheimers Dis, 2021)
BACKGROUND: Neuritic plaques contain neural and microglial elements, and amyloid-β protein (Aβ), but their pathogenesis remains unknown. OBJECTIVE: Elucidate neuritic plaque pathogenesis. METHODS: Histochemical visualization of hyperphosphorylated-tau positive (p-tau+) structures, microglia, Aβ, and iron. RESULTS: Disintegration of large projection neurons in human hippocampus and neocortex presents as droplet degeneration: pretangle neurons break up into spheres of numerous p-tau+ droplets of various sizes, which marks the beginning of neuritic plaques. These droplet spheres develop in the absence of colocalized Aβ deposits but once formed become encased in diffuse Aβ with great specificity. In contrast, neurofibrillary tangles often do not colocalize with Aβ. Double-labelling for p-tau and microglia showed a lack of microglial activation or phagocytosis of p-tau+ degeneration droplets but revealed massive upregulation of ferritin in microglia suggesting presence of high levels of free iron. Perl's Prussian blue produced positive staining of microglia, droplet spheres, and Aβ plaque cores supporting the suggestion that droplet degeneration of pretangle neurons in the hippocampus and cortex represents ferroptosis, which is accompanied by the release of neuronal iron extracellularly. CONCLUSION: Age-related iron accumulation and ferroptosis in the CNS likely trigger at least two endogenous mechanisms of neuroprotective iron sequestration and chelation, microglial ferritin expression and Aβ deposition, respectively, both contributing to the formation of neuritic plaques. Since neurofibrillary tangles and Aβ deposits colocalize infrequently, tangle formation likely does not involve release of neuronal iron extracellularly. In human brain, targeted deposition of Aβ occurs specifically in response to ongoing ferroptotic droplet degeneration thereby producing neuritic plaques.

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Effects of High Definition-Transcranial Direct Current Stimulation on Local GABA and Glutamate Levels Among Older Adults with and without Mild Cognitive Impairment: An Exploratory Study. - Lengu, Ketrin; Ryan, Shannon; Peltier, Scott J; Tyszkowski, Troy; Kairys, Anson; Giordani, Bruno; Hampstead, Benjamin M (J Alzheimers Dis, 2021)
BACKGROUND: Prior research, primarily with young adults, suggests transcranial direct current stimulation (tDCS) effects are driven by the primary excitatory and/or inhibitory neurotransmitters, glutamate, and gamma-aminobutyric acid (GABA), respectively. OBJECTIVE: We examined the neurometabolic mechanisms of tDCS in older adults with and without mild cognitive impairment (MCI). METHODS: We used data from a double-blind, cross-over, randomized controlled trial (NCT01958437) in 32 older adults to evaluate high definition (HD)-tDCS-induced changes in glutamate and GABA via magnetic resonance spectroscopy (MRS). Participants underwent MRS following two counterbalanced HD-tDCS sessions (one active, one sham) that targeted the right superior parietal cortex (center anode at P2) and delivered 2mA for 20 minutes. RESULTS: Relative to sham, and when co-varying for MRS voxel overlap and right superior parietal volume, active HD-tDCS significantly increased GABA and decreased the ratio of glutamate to GABA. No changes were observed in a left prefrontal control MRS voxel. Although we did not find a significant correlation between strength of delivered current (measured via MRI-based computational modeling) and neurometabolite change, there was a robust positive relationship between the volume of right superior parietal cortex and neurometabolite change. CONCLUSION: Our preliminary findings of increased GABA and reduced glutamate/GABA ratio raise the possibility that (HD-)tDCS effects differ by age. Moreover, age- and disease-related regional brain volume loss may be especially important to consider when planning future studies. Replication would emphasize the importance of developing population-specific tDCS parameters that consider structural and physiologic changes associated with "normal" and pathological aging.

Enhancing the Sensitivity of Memory Tests: Reference Data for the Free and Cued Selective Reminding Test and the Logical Memory Task from Cognitively Healthy Subjects with Normal Alzheimer's Disease Cerebrospinal Fluid Biomarker Levels. - Brugulat-Serrat, Anna; Cañas, Alba; Canals, Lidia; Marne, Paula; Gramunt, Nina; Milà-Alomà, Marta; Suárez-Calvet, Marc; Arenaza-Urquijo, Eider M; Grau-Rivera, Oriol; González-de-Echávarri, José María; Minguillon, Carolina; Fauria, Karine; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive performance of a given individual should be interpreted in the context of reference standards obtained in cognitively healthy populations. Recent evidence has shown that removing asymptomatic individuals with biomarker evidence of Alzheimer's disease (AD) pathology from normative samples increases the sensitivity of norms to detect memory impairments. These kind of norms may be useful for defining subtle cognitive decline, the transitional cognitive decline between normal cognition and mild cognitive impairment. OBJECTIVE: The present study aims to provide norms for the Free and Cued Selective Reminding Test (FCSRT) and the Logical Memory subtest of the Wechsler Memory Scale-IV in a sample of individuals aged 50-70 years with normal levels of amyloid (A) and tau (T) cerebrospinal fluid (CSF) biomarkers. METHODS: The sample was composed of 248 individuals from the ALFA+ study with negative amyloid-β and tau CSF biomarker levels. Regression-based norms were developed, including adjustments for age, education, and sex when applicable. RESULTS: We found that education was associated with the performance in all the variables of both tests while age had a marginal effect only in the delayed free recall of the FCSRT. Sex was also related to the performance in the FCSRT, with women outperforming men. Equations to calculate z-scores and normative percentile tables were created. As compared with previously published norms the reference data presented were more sensitive but less specific, as expected. CONCLUSION: The use of the norms provided in this work, in combination with the already published conventional norms, may contribute to detecting subtle memory impairment.

Five-Year Change in Body Mass Index Predicts Conversion to Mild Cognitive Impairment or Dementia Only in APOE ɛ4 Allele Carriers. - Kadey, Kylie R; Woodard, John L; Moll, Allison C; Nielson, Kristy A; Smith, J Carson; Durgerian, Sally; Rao, Stephen M (J Alzheimers Dis, 2021)
BACKGROUND: Body mass index (BMI) has been identified as an important modifiable lifestyle risk factor for dementia, but less is known about how BMI might interact with Apolipoprotein E ɛ4 (APOE ɛ4) carrier status to predict conversion to mild cognitive impairment (MCI) and dementia. OBJECTIVE: The aim of this study was to investigate the interaction between APOE ɛ4 status and baseline (bBMI) and five-year BMI change (ΔBMI) on conversion to MCI or dementia in initially cognitively healthy older adults. METHODS: The associations between bBMI, ΔBMI, APOE ɛ4 status, and conversion to MCI or dementia were investigated among 1,289 cognitively healthy elders from the National Alzheimer's Coordinating Center (NACC) database. RESULTS: After five years, significantly more carriers (30.6%) converted to MCI or dementia than noncarriers (17.6%), p <  0.001, OR = 2.06. Neither bBMI (OR = 0.99, 95%CI = 0.96-1.02) nor the bBMI by APOE interaction (OR = 1.02, 95%CI = 0.96-1.08) predicted conversion. Although ΔBMI also did not significantly predict conversion (OR = 0.90, 95%CI = 0.78-1.04), the interaction between ΔBMI and carrier status was significant (OR = 0.72, 95%CI = 0.53-0.98). For carriers only, each one-unit decline in BMI over five years was associated with a 27%increase in the odds of conversion (OR = 0.73, 95%CI = 0.57-0.94). CONCLUSION: A decline in BMI over five years, but not bBMI, was strongly associated with conversion to MCI or dementia only for APOE ɛ4 carriers. Interventions and behaviors aimed at maintaining body mass may be important for long term cognitive health in older adults at genetic risk for AD.

Hemochromatosis Mutations, Brain Iron Imaging, and Dementia in the UK Biobank Cohort. - Atkins, Janice L; Pilling, Luke C; Heales, Christine J; Savage, Sharon; Kuo, Chia-Ling; Kuchel, George A; Steffens, David C; Melzer, David (J Alzheimers Dis, 2021)
BACKGROUND: Brain iron deposition occurs in dementia. In European ancestry populations, the HFE p.C282Y variant can cause iron overload and hemochromatosis, mostly in homozygous males. OBJECTIVE: To estimated p.C282Y associations with brain MRI features plus incident dementia diagnoses during follow-up in a large community cohort. METHODS: UK Biobank participants with follow-up hospitalization records (mean 10.5 years). MRI in 206 p.C282Y homozygotes versus 23,349 without variants, including T2 * measures (lower values indicating more iron). RESULTS: European ancestry participants included 2,890 p.C282Y homozygotes. Male p.C282Y homozygotes had lower T2 * measures in areas including the putamen, thalamus, and hippocampus, compared to no HFE mutations. Incident dementia was more common in p.C282Y homozygous men (Hazard Ratio HR = 1.83; 95% CI 1.23 to 2.72, p = 0.003), as was delirium. There were no associations in homozygote women or in heterozygotes. CONCLUSION: Studies are needed of whether early iron reduction prevents or slows related brain pathologies in male HFE p.C282Y homozygotes.

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

Impact of 40 Hz Transcranial Alternating Current Stimulation on Cerebral Tau Burden in Patients with Alzheimer's Disease: A Case Series. - Dhaynaut, Maeva; Sprugnoli, Giulia; Cappon, Davide; Macone, Joanna; Sanchez, Justin S; Normandin, Marc; Guehl, Nicolas; Koch, Giacomo; Paciorek, Rachel; Connor, Ann; Press, Daniel; Johnson, Keith; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by diffuse amyloid-β (Aβ) and phosphorylated Tau (p-Tau) aggregates as well as neuroinflammation. Exogenously-induced 40 Hz gamma oscillations have been showing to reduce Aβ and p-Tau deposition presumably via microglia activation in AD mouse models. OBJECTIVE: We aimed to translate preclinical data on gamma-induction in AD patients by means of transcranial alternating current stimulation (tACS). METHODS: Four participants with mild-to-moderate AD received 1 h of daily 40 Hz (gamma) tACS for 4 weeks (Monday to Friday) targeting the bitemporal lobes (20 h treatment duration). Participant underwent Aβ, p-Tau, and microglia PET imaging with [11C]-PiB, [18F]-FTP, and [11C]-PBR28 respectively, before and after the intervention along with electrophysiological assessment. RESULTS: No adverse events were reported, and an increase in gamma spectral power on EEG was observed after the treatment. [18F]-FTP PET revealed a significant decrease over 2% of p-Tau burden in 3/4 patients following the tACS treatment, primarily involving the temporal lobe regions targeted by tACS and especially mesial regions (e.g., entorhinal cortex). The amount of intracerebral Aβ as measured by [11C]-PiB was not significantly influenced by tACS, whereas 1/4 reported a significant decrease of microglia activation as measured by [11C]-PBR28. CONCLUSION: tACS seems to represent a safe and feasible option for gamma induction in AD patients, with preliminary evidence of a possible effect on protein clearance partially mimicking what is observed in animal models. Longer interventions and placebo control conditions are needed to fully evaluate the potential for tACS to slow disease progression.

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Internal Jugular Vein Velocity and Spontaneous Echo Contrast Correlate with Alzheimer's Disease and Cognitive Function. - Matsuzono, Kosuke; Suzuki, Masayuki; Miura, Kumiko; Ozawa, Tadashi; Mashiko, Takafumi; Koide, Reiji; Tanaka, Ryota; Fujimoto, Shigeru (J Alzheimers Dis, 2021)
BACKGROUND: Many issues persist in the today's Alzheimer's disease (AD) screening and the breakthrough method is desired. OBJECTIVE: We aim to validate the association between venous reflux and AD, and to develop a new method for AD screening. METHODS: We examined spontaneous echo contrast, area, diameter, retrograde velocity, and anterograde velocity of the bilateral cervical internal jugular vein (IJV) using carotid ultrasonography. RESULTS: A total of 112 patients participated in this study, with 26 diagnosed as AD. The proportion of both or either IJV spontaneous echo contrast (+) occupied 25 of total 26 AD patients, which showed 96.2%of sensitivity and 98.5%negative predictive value. The IJV velocities also showed significant correlation with AD diagnosis, although the IJV area or diameter did not. CONCLUSION: Our results indicate that the validation of the spontaneous echo contrast or velocities of the IJV are convenient AD diagnosis screening methods and that the venous reflux disturbance correlates with AD development.

Longitudinally Increasing Elevated Asymmetric Flortaucipir Binding in a Cognitively Unimpaired Amyloid-Negative Older Individual. - Schwarz, Christopher G; Knopman, David S; Ramanan, Vijay K; Lowe, Val J; Wiste, Heather J; Cogswell, Petrice M; Utianski, Rene L; Senjem, Matthew L; Gunter, Jeffrey R; Vemuri, Prashanthi; Petersen, Ronald C; Jack, Clifford R (J Alzheimers Dis, 2021)
We present the case of a cognitively unimpaired 77-year-old man with elevated, asymmetric, and longitudinally increasing Flortaucipir tau PET despite normal (visually negative) amyloid PET. His atypical tau PET signal persisted and globally increased in a follow-up scan five years later. Across eight years of observations, temporoparietal atrophy was observed consistent with tau PET patterns, but he retained the cognitively unimpaired classification. Altogether, his atypical tau PET signal is not explained by any known risk factors or alternative pathologies, and other imaging findings were not remarkable. He remains enrolled for further observation.

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Near-Infrared Optical Spectroscopy In Vivo Distinguishes Subjects with Alzheimer's Disease from Age-Matched Controls. - Greco, Frank A; McKee, Ann C; Kowall, Neil W; Hanlon, Eugene B (J Alzheimers Dis, 2021)
BACKGROUND: Medical imaging methods such as PET and MRI aid clinical assessment of Alzheimer's disease (AD). Less expensive, less technically demanding, and more widely deployable technologies are needed to expand objective screening for diagnosis, treatment, and research. We previously reported brain tissue near-infrared optical spectroscopy (NIR) in vitro indicating the potential to meet this need. OBJECTIVE: To determine whether completely non-invasive, clinical, NIR in vivo can distinguish AD patients from age-matched controls and to show the potential of NIR as a clinical screen and monitor of therapeutic efficacy. METHODS: NIR spectra were acquired in vivo. Three groups were studied: autopsy-confirmed AD, control and mild cognitive impairment (MCI). A feature selection approach using the first derivative of the intensity normalized spectra was used to discover spectral regions that best distinguished "AD-alone" (i.e., without other significant neuropathology) from controls. The approach was then applied to other autopsy-confirmed AD cases and to clinically diagnosed MCI cases. RESULTS: Two regions about 860 and 895 nm completely separate AD patients from controls and differentiate MCI subjects according to the degree of impairment. The 895 nm feature is more important in separating MCI subjects from controls (ratio-of-weights: 1.3); the 860 nm feature is more important for distinguishing MCI from AD (ratio-of-weights: 8.2). CONCLUSION: These results form a proof of the concept that near-infrared spectroscopy can detect and classify diseased and normal human brain in vivo. A clinical trial is needed to determine whether the two features can track disease progression and monitor potential therapeutic interventions.

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Syrjanen, Jeremy A; Bezold, Jelena; Trautwein, Sandra; Barisch-Fritz, Bettina; Boes, Klaus; Woll, Alexander; Forzani, Erica; Kremers, Walter K; Machulda, Mary M; Mielke, Michelle M; Knopman, David S; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. OBJECTIVE: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. METHODS: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (ages 50-65) and late-life (last year) PA was assessed using a questionnaire. Neuropsychological testing was done every 15 months (mean follow-up 5.8 years). We ran linear mixed-effect models to examine whether mid- or late-life PA at three intensities (mild, moderate, vigorous) was associated with cognitive z-scores. RESULTS: Light intensity midlife PA was associated with less decline in memory function compared to the no-PA reference group (time x light PA; estimate [standard error] 0.047 [0.016], p = 0.004). Vigorous late-life PA was associated with less decline in language (0.033 [0.015], p = 0.030), attention (0.032 [0.017], p = 0.050), and global cognition (0.039 [0.016], p = 0.012). Females who were physically inactive in midlife experienced more pronounced cognitive decline than females physically active in midlife and males regardless of PA (p-values for time interaction terms with midlife PA levels and sex were all p <  0.05 for global cognition). APOE ɛ4 carriership did not moderate the association between PA and cognition. CONCLUSION: Engaging in PA, particularly of vigorous intensity in late-life, was associated with less pronounced decline in global and domain-specific cognition. This association may differ by sex.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells. - Huang, Wanyi; Zeng, Fan; Gu, Yebo; Jiang, Muzhou; Zhang, Xinwen; Yan, Xu; Kadowaki, Tomoko; Mizutani, Shinsuke; Kashiwazaki, Haruhiko; Ni, Junjun; Wu, Zhou (J Alzheimers Dis, 2021)
BACKGROUND: Studies have reported that synaptic failure occurs before the Alzheimer's disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. OBJECTIVE: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. METHODS: The responses of leptomeningeal cells and cortical neurons to systemic P. gingivalis infection were examined in 15-month-old mice. The mechanism of IL-1β production by P. gingivalis infected leptomeningeal cells was examined, and primary cortical neurons were treated with P. gingivalis infected leptomeningeal cells condition medium (Pg LCM). RESULTS: Systemic P. gingivalis infection increased the expression of IL-1β in leptomeninges and reduced the synaptophysin (SYP) expression in leptomeninges proximity cortex in mice. Leptomeningeal cells phagocytosed P. gingivalis resulting in lysosomal rupture and Cathepsin B (CatB) leakage. Leaked CatB mediated NLRP3 inflammasome activation inducing IL-1β secretion in leptomeningeal cells. Pg LCM decreased the expression of synaptic molecules, including SYP, which was inhibited by an IL-1 receptor antagonist pre-treatment. CONCLUSION: These observations demonstrate that P. gingivalis infection is involved in synaptic failure by inducing CatB/NLRP3 inflammasome-mediated IL-1β production in leptomeningeal cells. The periodontal bacteria-induced synaptic damage may accelerate the onset and cognitive decline of AD.

Porphyromonas gingivalis (W83) Infection Induces Alzheimer's Disease-Like Pathophysiology in Obese and Diabetic Mice. - Bahar, Bojlul; Kanagasingam, Shalini; Tambuwala, Murtaza M; Aljabali, Alaa A A; Dillon, Stephanie A; Doaei, Saeid; Welbury, Richard; Chukkapalli, Sasanka S; Singhrao, Sim K (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease(s) and metabolic illnesses negatively impact the quality of life and, eventually mental health. OBJECTIVE: This study investigated the effect of Porphyromonas gingivalis (W83) oral infection on the development of Alzheimer's disease (AD) pathophysiology in a wild-type obese, diabetic (db/db) mouse model. METHODS: The db/db mice were either orally infected with P. gingivalis and Fusobacterium nucleatum or sham infected for 16 weeks. The presence of amyloid-β (Aβ) and neurofibrillary tangles (NFTs) were assessed using a silver impregnation technique and subsequently by immunohistochemistry for tau and neuroinflammation. The mRNA abundance of a panel of 184 genes was performed using quantitative real-time PCR, and the differentially expressed genes were analyzed by Ingenuity Pathway Analysis. RESULTS: While no Aβ plaques and NFTs were evident by silver impregnation, immunohistochemistry (glial cell markers) of the P. gingivalis-infected mice tissue sections exhibited neuroinflammation in the form of reactive microglia and astrocytes. Anti-tau immunopositivity, in addition to cells, was prominent in thickened axons of hippocampal CA neurons. The mRNA abundance of crucial genes in the insulin signaling pathway (INSR, IGF1, IRS, IDE, PIK3R, SGK1, GYS, GSK3B, AKT1) were upregulated, potentially exacerbating insulin resistance in the brain by P. gingivalis oral infection. Increased mRNA abundance of several kinases, membrane receptors, transcription factors, and pro-inflammatory mediators indicated hyperactivation of intracellular cascades with potential for tau phosphorylation and Aβ release in the same infection group. CONCLUSION: P. gingivalis W83 infection of db/db mice provides a disease co-morbidity model with the potential to reproduce AD pathophysiology with induced periodontal disease.

Primary Prevention of Dementia: An Ethical Review. - Horstkötter, Dorothee; Deckers, Kay; Köhler, Sebastian (J Alzheimers Dis, 2021)
Dementia poses important medical and societal challenges, and of all health risks people face in life, dementia is one of the most feared. Recent research indicates that up to about 40% of all cases of dementia might be preventable. A series of environmental, social, and medical risk-factors have been identified that should be targeted from midlife onwards when people are still cognitively healthy. At first glance, this seems not merely advisable, but even imperative. However, these new developments trigger a series of new ethical questions and concerns which have hardly been addressed to date. Pro-active ethical reflection, however, is crucial to ensure that the interests and well-being of those affected, ultimately all of us, are adequately respected. This is the goal of the current contribution. Against the background of a concrete case in primary dementia prevention, it provides a systematic overview of the current ethical literature and sketches an ethical research agenda. First, possible benefits of increased well-being must be balanced with the burdens of being engaged in particularly long-term interventions for which it is unclear whether they will ever pay out on a personal level. Second, while knowledge about one's options to maintain brain health might empower people, it might also undermine autonomy, put high social pressure on people, medicalize healthy adults, and stigmatize those who still develop dementia. Third, while synergistic effects might occur, the ideals of dementia prevention might also conflict with other health and non-health related values people hold in life.
Keywords: Dementia; Ethical Review; Humans; Life Style; Primary Prevention

Promoting Successful Cognitive Aging: A Ten-Year Update. - Krivanek, Taylor J; Gale, Seth A; McFeeley, Brittany M; Nicastri, Casey M; Daffner, Kirk R (J Alzheimers Dis, 2021)
A decade has passed since we published a comprehensive review in this journal addressing the topic of promoting successful cognitive aging, making this a good time to take stock of the field. Because there have been limited large-scale, randomized controlled trials, especially following individuals from middle age to late life, some experts have questioned whether recommendations can be legitimately offered about reducing the risk of cognitive decline and dementia. Despite uncertainties, clinicians often need to at least make provisional recommendations to patients based on the highest quality data available. Converging lines of evidence from epidemiological/cohort studies, animal/basic science studies, human proof-of-concept studies, and human intervention studies can provide guidance, highlighting strategies for enhancing cognitive reserve and preventing loss of cognitive capacity. Many of the suggestions made in 2010 have been supported by additional research. Importantly, there is a growing consensus among major health organizations about recommendations to mitigate cognitive decline and promote healthy cognitive aging. Regular physical activity and treatment of cardiovascular risk factors have been supported by all of these organizations. Most organizations have also embraced cognitively stimulating activities, a heart-healthy diet, smoking cessation, and countering metabolic syndrome. Other behaviors like regular social engagement, limiting alcohol use, stress management, getting adequate sleep, avoiding anticholinergic medications, addressing sensory deficits, and protecting the brain against physical and toxic damage also have been endorsed, although less consistently. In this update, we review the evidence for each of these recommendations and offer practical advice about behavior-change techniques to help patients adopt brain-healthy behaviors.
Keywords: Cognition; Cognitive Aging; Diet, Healthy; Exercise; Healthy Aging; Healthy Lifestyle; Humans

Proton Stimulation Targeting Plaque Magnetite Reduces Amyloid-β Plaque and Iron Redox Toxicity and Improves Memory in an Alzheimer's Disease Mouse Model. - Seo, Seung-Jun; Chang, Won-Seok; Jeon, Jae-Geun; Choi, Younshick; Kim, EunHo; Kim, Jong-Ki (J Alzheimers Dis, 2021)
BACKGROUND: The coexistence of magnetite within protein aggregates in the brain is a typical pathologic feature of Alzheimer's disease (AD), and the formation of amyloid-β (Aβ) plaques induces critical impairment of cognitive function. OBJECTIVE: This study aimed to investigate the therapeutic effect of proton stimulation (PS) targeting plaque magnetite in the transgenic AD mouse brain. METHODS: A proton transmission beam was applied to the whole mouse brain at a single entrance dose of 2 or 4 Gy to test the effect of disruption of magnetite-containing Aβ plaques by electron emission from magnetite. The reduction in Aβ plaque burden and the cognitive function of the PS-treated mouse group were assayed by histochemical analysis and memory tests, respectively. Aβ-magnetite and Aβ fibrils were treated with PS to investigate the breakdown of the amyloid protein matrix. RESULTS: Single PS induced a 48-87%reduction in both the amyloid plaque burden and ferrous-containing magnetite level in the early-onset AD mouse brain while saving normal tissue. The overall Aβ plaque burden (68-82%) and (94-97%) hippocampal magnetite levels were reduced in late onset AD mice that showed improvements in cognitive function after PS compared with untreated AD mice (p <  0.001). Analysis of amyloid fibrils after exposure to a single 2 or 4 Gy proton transmission beam demonstrated that the protein matrix was broken down only in magnetite-associated Aβ fibrils. CONCLUSION: Single PS targeting plaque magnetite effectively decreases the amyloid plaque burden and the ferrous-containing magnetite level, and this effect is useful for memory recovery.

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Quantifying and Examining Reserve in Symptomatic Former National Football League Players. - Foley, Éimear M; Tripodis, Yorghos; Yhang, Eukyung; Koerte, Inga K; Martin, Brett M; Palmisano, Joseph; Makris, Nikos; Schultz, Vivian; Lepage, Chris; Muehlmann, Marc; Wróbel, Paweł P; Guenette, Jeffrey P; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Repetitive head impacts (RHI) from contact sports have been associated with cognitive and neuropsychiatric disorders. However, not all individuals exposed to RHI develop such disorders. This may be explained by the reserve hypothesis. It remains unclear if the reserve hypothesis accounts for the heterogenous symptom presentation in RHI-exposed individuals. Moreover, optimal measurement of reserve in this population is unclear and likely unique from non-athlete populations. OBJECTIVE: We examined the association between metrics of reserve and cognitive and neuropsychiatric functioning in 89 symptomatic former National Football League players. METHODS: Individual-level proxies (e.g., education) defined reserve. We additionally quantified reserve as remaining residual variance in 1) episodic memory and 2) executive functioning performance, after accounting for demographics and brain pathology. Associations between reserve metrics and cognitive and neuropsychiatric functioning were examined. RESULTS: Higher reading ability was associated with better attention/information processing (β=0.25; 95% CI, 0.05-0.46), episodic memory (β=0.27; 95% CI, 0.06-0.48), semantic and phonemic fluency (β=0.24; 95% CI, 0.02-0.46; β=0.38; 95% CI, 0.17-0.59), and behavioral regulation (β=-0.26; 95% CI, -0.48, -0.03) performance. There were no effects for other individual-level proxies. Residual episodic memory variance was associated with better attention/information processing (β=0.45; 95% CI, 0.25, 0.65), executive functioning (β=0.36; 95% CI, 0.15, 0.57), and semantic fluency (β=0.38; 95% CI, 0.17, 0.59) performance. Residual executive functioning variance was associated with better attention/information processing (β=0.44; 95% CI, 0.24, 0.64) and episodic memory (β=0.37; 95% CI, 0.16, 0.58) performance. CONCLUSION: Traditional reserve proxies (e.g., years of education, occupational attainment) have limitations and may be unsuitable for use in elite athlete samples. Alternative approaches of reserve quantification may prove more suitable for this population.

The Relationship Between Cardiovascular Health and Rate of Cognitive Decline in Young-Old and Old-Old Adults: A Population-Based Study. - Speh, Andreja; Wang, Rui; Winblad, Bengt; Kramberger, Milica G; Bäckman, Lars; Qiu, Chengxuan; Laukka, Erika J (J Alzheimers Dis, 2021)
BACKGROUND: Modifiable vascular risk factors have been associated with late-life cognitive impairment. The Life Simple 7 (LS7) score comprises seven cardiovascular health metrics: smoking, diet, physical activity, body mass index, plasma glucose, total serum cholesterol, and blood pressure. OBJECTIVE: To investigate the association between individual and composite LS7 metrics and rate of cognitive decline, and potential differences in these associations between young-old and old-old individuals. METHODS: This cohort study included 1,950 participants aged≥60 years (M = 70.7 years) from the Swedish National Study on Aging and Care-Kungsholmen (SNAC-K), who underwent repeated neuropsychological testing (episodic and semantic memory, verbal fluency, processing speed, global cognition) across 12 years. The LS7 score was assessed at baseline and categorized as poor, intermediate, or optimal. Level and change in cognitive performance as a function LS7 categories were estimated using linear mixed-effects models. RESULTS: Having an optimal LS7 total score was associated with better performance (expressed in standard deviation units) at baseline for perceptual speed (β= 0.21, 95%CI 0.12-0.29), verbal fluency (β= 0.08, 0.00-0.16), and global cognition (β= 0.06, 0.00-0.12) compared to the poor group. Age-stratified analyses revealed associations for cognitive level and change only in the young-old (<  78 years) group. For the specific metrics, diverging patterns were observed for young-old and old-old individuals. CONCLUSION: Meeting the LS7 criteria for ideal cardiovascular health in younger old age is associated with slower rate of cognitive decline. However, the LS7 criteria may have a different meaning for cognitive function in very old adults.

Relationships Between Cognition and Neuropathological Tau in Alzheimer's Disease Assessed by 18F Flortaucipir PET. - Devous, Michael D; Fleisher, Adam S; Pontecorvo, Michael J; Lu, Ming; Siderowf, Andrew; Navitsky, Michael; Kennedy, Ian; Southekal, Sudeepti; Harris, Thomas S; Mintun, Mark A (J Alzheimers Dis, 2021)
BACKGROUND: Tau neurofibrillary tangle burden increases with Alzheimer's disease (AD) stage and correlates with degree of cognitive impairment. Tau PET imaging could facilitate understanding the relationship between tau pathology and cognitive impairment. OBJECTIVE: Evaluate the relationship between 18F flortaucipir uptake patterns and cognition across multiple cognitive domains. METHODS: We acquired flortaucipir PET scans in 84 amyloid-positive control, mild cognitive impairment (MCI), and AD subjects. Flortaucipir standardized uptake value ratio (SUVr) values were obtained from a neocortical volume of interest (VOI), a precuneus VOI, and VOIs defined by the correlation between flortaucipir SUVr images and domain-specific cognitive tests. Cognitive assessments included Mini-Mental State Exam (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-cog), and a neuropsychological test battery (i.e., Wechsler Memory Scale-Revised Logical Memory (WMS-R), Trail Making Test, Boston Naming Test, Digit Symbol Substitution Test, Animal List Generation, WMS-R Digit Span, American National Adult Reading Test, Clock Drawing Test, Judgment of Line Orientation, and WMS-R Logical Memory II (Delayed Recall)) and the Functional Activities Questionnaire (FAQ). Correlation analyses compared regional and voxel-wise VOIs to cognitive scores. RESULTS: Subjects included 5 controls, 47 MCI, and 32 AD subjects. Significant correlations were seen between both flortaucipir and florbetapir SUVrs and MMSE, ADAS-Cog, and FAQ. Cognitive impairment was associated with increased flortaucipir uptake in regionally specific patterns consistent with the neuroanatomy underlying specific cognitive tests. CONCLUSION: Flortaucipir SUVr values demonstrated significant inverse correlations with cognitive scores in domain-specific patterns. Findings support the hypothesis that PET imaging of neuropathologic tau deposits may reflect underlying neurodegeneration in AD.

Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.

The Role of Microglia in Sporadic Alzheimer's Disease. - Streit, Wolfgang J; Khoshbouei, Habibeh; Bechmann, Ingo (J Alzheimers Dis, 2021)
Microglia constitute the brain's immune system and their involvement in Alzheimer's disease has been discussed. Commonly, and in line with the amyloid/neuroinflammation cascade hypothesis, microglia have been portrayed as potentially dangerous immune effector cells thought to be overactivated by amyloid and producing neurotoxic inflammatory mediators that lead to neurofibrillary degeneration. We disagree with this theory and offer as an alternative the microglial dysfunction theory stating that microglia become impaired in their normally neuroprotective roles because of aging, i.e., they become senescent and aging neurons degenerate because they lack the needed microglial support for their survival. Thus, while the amyloid cascade theory relies primarily on genetic data, the dysfunction theory incorporates aging as a critical etiological factor. Aging is the greatest risk factor for the sporadic (late-onset) and most common form of Alzheimer's disease, where fully penetrant genetic mutations are absent. In this review, we lay out and discuss the human evidence that supports senescent microglial dysfunction and conflicts with the amyloid/neuroinflammation idea.
Keywords: Aging; Alzheimer Disease; Humans; Microglia

Selective Impairment of Long-Range Default Mode Network Functional Connectivity as a Biomarker for Preclinical Alzheimer's Disease in People with Down Syndrome. - DiProspero, Natalie D; Keator, David B; Phelan, Michael; van Erp, Theo G M; Doran, Eric; Powell, David K; Van Pelt, Kathryn L; Schmitt, Frederick A; Head, Elizabeth; Lott, Ira T; Yassa, Michael A (J Alzheimers Dis, 2021)
BACKGROUND: Down syndrome (DS) is associated with increased risk for Alzheimer's disease (AD). In neurotypical individuals, clinical AD is preceded by reduced resting state functional connectivity in the default mode network (DMN), but it is unknown whether changes in DMN connectivity predict clinical onset of AD in DS. OBJECTIVE: Does lower DMN functional connectivity predict clinical onset of AD and cognitive decline in people with DS? METHODS: Resting state functional MRI (rsfMRI), longitudinal neuropsychological, and clinical assessment data were collected on 15 nondemented people with DS (mean age = 51.66 years, SD = 5.34 years, range = 42-59 years) over four years, during which 4 transitioned to dementia. Amyloid-β (Aβ) PET data were acquired on 13 of the 15 participants. Resting state fMRI, neuropsychological, and clinical assessment data were also acquired on an independent, slightly younger unimpaired sample of 14 nondemented people with DS (mean age = 44.63 years, SD = 7.99 years, range = 38-61 years). RESULTS: Lower functional connectivity between long-range but not short-range DMN regions predicts AD diagnosis and cognitive decline in people with DS. Aβ accumulation in the inferior parietal cortex is associated with lower regional DMN functional connectivity. CONCLUSION: Reduction of long-range DMN connectivity is a potential biomarker for AD in people with DS that precedes and predicts clinical conversion.

Site-Specific Cerebrospinal Fluid Tau Hyperphosphorylation in Response to Alzheimer's Disease Brain Pathology: Not All Tau Phospho-Sites are Hyperphosphorylated. - Barthélemy, Nicolas R; Toth, Balazs; Manser, Paul T; Sanabria-Bohórquez, Sandra; Teng, Edmond; Keeley, Michael; Bateman, Randall J; Weimer, Robby M; Wildsmith, Kristin R (J Alzheimers Dis, 2021)
BACKGROUND: Understanding patterns of association between CSF phosphorylated tau (p-tau) species and clinical disease severity will aid Alzheimer's disease (AD) diagnosis and treatment. OBJECTIVE: To evaluate changes in tau phosphorylation ratios to brain imaging (amyloid PET, [18F]GTP1 PET, and MRI) and cognition across clinical stages of AD in two different cohorts. METHODS: A mass spectrometry (MS)-based method was used to evaluate the relationship between p-tau/tau phosphorylation ratios on 11 sites in CSF and AD pathology measured by tau PET ([18F]GTP1) and amyloid PET ([18F]florbetapir or [18F]florbetaben). Cohort A included cognitively normal-amyloid negative (n = 6) and positive (n = 5) individuals, and amyloid positive prodromal (n = 13), mild (n = 12), and moderate AD patients (n = 10); and Cohort B included amyloid positive prodromal (n = 24) and mild (n = 40) AD patients. RESULTS: In this cross-sectional analysis, we identified clusters of phosphosites with different profiles of phosphorylation ratios across stages of disease. Eight of 11 investigated sites were hyperphosphorylated and associated with the SUVR measures from [18F]GTP1 and amyloid PET. Novel sites 111, 153, and 208 may be relevant biomarkers for AD diagnosis to complement tau hyperphosphorylation measures on previously established sites 181, 205, 217, and 231. Hypophosphorylation was detected on residues 175, 199, and 202, and was inversely associated with [18F]GTP1 and amyloid PET. CONCLUSION: Hyperphosphorylated and hypophosphorylated forms of tau are associated with AD pathologies, and due to their different site-specific profiles, they may be used in combination to assist with staging of disease.

Social Robot Interventions for People with Dementia: A Systematic Review on Effects and Quality of Reporting. - Hirt, Julian; Ballhausen, Nicola; Hering, Alexandra; Kliegel, Matthias; Beer, Thomas; Meyer, Gabriele (J Alzheimers Dis, 2021)
BACKGROUND: Using non-pharmacological interventions is a current approach in dementia care to manage responsive behaviors, to maintain functional capacity, and to reduce emotional stress. Novel technologies such as social robot interventions might be useful to engage people with dementia in activities and interactions as well as to improve their cognitive, emotional, and physical status. OBJECTIVE: Assessing the effects and the quality of reporting of social robot interventions for people with dementia. METHODS: In our systematic review, we included quasi-experimental and experimental studies published in English, French, or German, irrespective of publication year. Searching CINAHL, Cochrane Library, MEDLINE, PsycINFO, and Web of Science Core Collection was supplemented by citation tracking and free web searching. To assess the methodological quality of included studies, we used tools provided by the Joanna Briggs Institute. To assess the reporting of the interventions, we applied CReDECI 2 and TIDieR. RESULTS: We identified sixteen studies published between 2012 and 2018, including two to 415 participants with mostly non-defined type of dementia. Eight studies had an experimental design. The predominant robot types were pet robots (i.e., PARO). Most studies addressed behavioral, emotion-related, and functional outcomes with beneficial, non-beneficial, and mixed results. Predominantly, cognitive outcomes were not improved. Overall, studies were of moderate methodological quality. CONCLUSION: Heterogeneous populations, intervention characteristics, and measured outcomes make it difficult to generalize the results with regard to clinical practice. The impact of social robot interventions on behavioral, emotion-related, and functional outcomes should therefore be assessed considering the severity of dementia and intervention characteristics.
Keywords: Dementia; Humans; Research; Robotics; Social Behavior

Spiritual Fitness: A New Dimension in Alzheimer's Disease Prevention. - Khalsa, Dharma Singh; Newberg, Andrew B (J Alzheimers Dis, 2021)
BACKGROUND: Religious and spiritual interventions may have an effect on Alzheimer's disease prevention. Kirtan Kriya meditation has been shown to mitigate the deleterious effects of chronic stress on cognition, reverse memory loss, and create psychological and spiritual wellbeing, which may reduce multiple drivers of Alzheimer's disease risk. OBJECTIVE: To detail a new concept in medicine called Spiritual Fitness, a merging of stress reduction, basic wellbeing, and psycho/spiritual wellbeing to prevent Alzheimer's disease. METHODS: The literature on the topics mentioned above is described, including an in-depth discussion on why and how each are critical to advancing the future of Alzheimer's disease prevention. The many negative effects of chronic stress, and the benefits of Kirtan Kriya, are reviewed. The four pillars of basic wellbeing, six practical aspects of psychological wellbeing, and the four new non-sectarian features of spiritual fitness are then disclosed. Moreover, instructions on practicing Kirtan Kriya are offered in the Supplementary Material. CONCLUSION: Religious and spiritual practices, including Kirtan Kriya, are crucial components in the development of enhanced cognition and well-being, which may help prevent and, in some cases, reverse cognitive decline. The key point of this review is that making a commitment to live a brain longevity lifestyle including spiritual fitness is a critically important way for aging Alzheimer's disease free. We hope that this article will inspire scientists, clinicians, and patients to embrace this new concept of spiritual fitness and make it a part of every multidomain program for the prevention of cognitive disability.
Keywords: Alzheimer Disease; Humans; Life Style; Love; Meditation; Spirituality

Stages of Objective Memory Impairment Predict Alzheimer's Disease Neuropathology: Comparison with the Clinical Dementia Rating Scale-Sum of Boxes. - Grober, Ellen; Qi, Qi; Kuo, Lynn; Hassenstab, Jason; Perrin, Richard J; Lipton, Richard B (J Alzheimers Dis, 2021)
BACKGROUND: The ultimate validation of a clinical marker for Alzheimer's disease (AD) is its association with AD neuropathology. OBJECTIVE: To examine how well the Stages of Objective Memory Impairment (SOMI) system predicts intermediate/high AD neuropathologic change and extent of neurofibrillary tangle (NFT) pathology defined by Braak stage, in comparison to the Clinical Dementia Rating (CDR) Scale sum of boxes (CDR-SB). METHODS: 251 well-characterized participants from the Knight ADRC clinicopathologic series were classified into SOMI stage at their last assessment prior to death using the free recall and total recall scores from the picture version of the Free and Cued Selective Reminding Test with Immediate Recall (pFCSRT + IR). Logistic regression models assessed the predictive validity of SOMI and CDR-SB for intermediate/high AD neuropathologic change. Receiver operating characteristics (ROC) analysis evaluated the discriminative validity of SOMI and CDR-SB for AD pathology. Ordinal logistic regression was used to predict Braak stage using SOMI and CDR-SB in separate and joint models. RESULTS: The diagnostic accuracy of SOMI for AD diagnosis was similar to that of the CDR-SB (AUC: 85%versus 83%). In separate models, both SOMI and CDR-SB predicted Braak stage. In a joint model SOMI remained a significant predictor of Braak stage but CDR-SB did not. CONCLUSION: SOMI provides a neuropathologically validated staging system for episodic memory impairment in the AD continuum and should be useful in predicting tau positivity based on its association with Braak stage.

Synaptic Molecular and Neurophysiological Markers Are Independent Predictors of Progression in Alzheimer's Disease. - Smailovic, Una; Kåreholt, Ingemar; Koenig, Thomas; Ashton, Nicholas J; Winblad, Bengt; Höglund, Kina; Nilsson, Per; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (J Alzheimers Dis, 2021)
BACKGROUND: Cerebrospinal fluid (CSF) neurogranin and quantitative electroencephalography (qEEG) are potential molecular and functional markers of synaptic pathology in Alzheimer's disease (AD). Synaptic markers have emerged as candidate prognostic indicators of AD since synaptic degeneration was shown to be an early event and the best correlate of cognitive deficits in patients along the disease continuum. OBJECTIVE: The present study investigated the association between CSF neurogranin and qEEG measures as well as their potential to predict clinical deterioration in mild cognitive impairment (MCI) patients. METHODS: Patients diagnosed with MCI (n = 99) underwent CSF conventional AD biomarkers and neurogranin analysis and resting-state EEG recordings. The study population was further stratified into stable (n = 41) and progressive MCI (n = 31), based on the progression to AD dementia during two years follow-up. qEEG analysis included computation of global field power and global field synchronization in four conventional frequency bands. RESULTS: CSF neurogranin levels were associated with theta power and synchronization in the progressive MCI group. CSF neurogranin and qEEG measures were significant predictors of progression to AD dementia, independent of baseline amyloid status in MCI patients. A combination of CSF neurogranin with global EEG power in theta and global EEG synchronization in beta band exhibited the highest classification accuracy as compared to either of these markers alone. CONCLUSION: qEEG and CSF neurogranin are independent predictors of progression to AD dementia in MCI patients. Molecular and neurophysiological synaptic markers may have additive value in a multimodal diagnostic and prognostic approach to dementia.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

TREM2 Deficiency Disrupts Network Oscillations Leading to Epileptic Activity and Aggravates Amyloid-β-Related Hippocampal Pathophysiology in Mice. - Stoiljkovic, Milan; Gutierrez, Karel Otero; Kelley, Craig; Horvath, Tamas L; Hajós, Mihály (J Alzheimers Dis, 2021)
BACKGROUND: Genetic mutations in triggering receptor expressed on myeloid cells-2 (TREM2) have been strongly associated with increased risk of developing Alzheimer's disease (AD) and other progressive dementias. In the brain, TREM2 protein is specifically expressed on microglia suggesting their active involvement in driving disease pathology. Using various transgenic AD models to interfere with microglial function through TREM2, several recent studies provided important data indicating a causal link between TREM2 and underlying amyloid-β (Aβ) and tau pathology. However, mechanisms by which TREM2 contributes to increased predisposition to clinical AD and influences its progression still remain largely unknown. OBJECTIVE: Our aim was to elucidate the potential contribution of TREM2 on specific oscillatory dynamic changes associated with AD pathophysiology. METHODS: Spontaneous and brainstem nucleus pontis oralis stimulation-induced hippocampal oscillation paradigm was used to investigate the impact of TREM2 haploinsufficiency TREM2(Het) or total deficiency TREM2(Hom) on hippocampal network function in wild-type and Aβ overproducing Tg2576 mice under urethane anesthesia. RESULTS: Partial (TREM2(Het)) or total (TREM2(Hom)) deletion of TREM2 led to increased incidence of spontaneous epileptiform seizures in both wild-type and Tg2576 mice. Importantly, deficiency of TREM2 in Tg2576 mice significantly diminished power of theta oscillation in the hippocampus elicited by brainstem-stimulation compared to wild-type mice. However, it did not affect hippocampal theta-phase gamma-amplitude coupling significantly, since over a 60%reduction was found in coupling in Tg2576 mice regardless of TREM2 function. CONCLUSION: Our findings indicate a role for TREM2-dependent microglial function in the hippocampal neuronal excitability in both wild type and Aβ overproducing mice, whereas deficiency in TREM2 function exacerbates disruptive effects of Aβ on hippocampal network oscillations.

Upregulation of Local Hepcidin Contributes to Iron Accumulation in Alzheimer's Disease Brains. - Chaudhary, Suman; Ashok, Ajay; McDonald, Dallas; Wise, Aaron S; Kritikos, Alexander E; Rana, Neil A; Harding, Clifford V; Singh, Neena (J Alzheimers Dis, 2021)
BACKGROUND: Accumulation of iron is a consistent feature of Alzheimer's disease (AD) brains. The underlying cause, however, remains debatable. OBJECTIVE: To explore whether local hepcidin synthesized by brain cells contributes to iron accumulation in AD brains. METHODS: Brain tissue from the cingulate cortex of 33 cases of AD pre-assigned to Braak stage I-VI, 6 cases of non-dementia, and 15 cases of non-AD dementia were analyzed for transcriptional upregulation of hepcidin by RT-qPCR and RT-PCR. Change in the expression of ferritin, ferroportin (Fpn), microglial activation marker Iba1, IL-6, and TGFβ2 was determined by western blotting. Total tissue iron was determined by colorimetry. RESULTS: Significant transcriptional upregulation of hepcidin was observed in Braak stage III-VI relative to Braak stage I and II, non-AD dementia, and non-dementia samples. Ferritin was increased in Braak stage V, and a significant increase in tissue iron was evident in Braak stage III-VI. The expression of Iba1 and IL-6 was also increased in Braak stage III-VI relative to Braak stage I and II and non-AD dementia samples. Amyloid-β plaques were absent in most Braak stage I and II samples, and present in Braak stage III-VI samples with few exceptions. CONCLUSION: These observations suggest that upregulation of brain hepcidin is mediated by IL-6, a known transcriptional activator of hepcidin. The consequent downregulation of Fpn on neuronal and other cells results in accumulation of iron in AD brains. The increase in hepcidin is disease-specific, and increases with disease progression, implicating AD-specific pathology in the accumulation of iron.

White Matter Connectivity in Incident Mild Cognitive Impairment: A Diffusion Spectrum Imaging Study of World Trade Center Responders at Midlife. - Huang, Chuan; Kritikos, Minos; Clouston, Sean A P; Deri, Yael; Serrano-Sosa, Mario; Bangiyev, Lev; Santiago-Michels, Stephanie; Gandy, Sam; Sano, Mary; Bromet, Evelyn J; Luft, Benjamin J (J Alzheimers Dis, 2021)
BACKGROUND: Individuals who participated in response efforts at the World Trade Center (WTC) following 9/11/2001 are experiencing elevated incidence of mild cognitive impairment (MCI) at midlife. OBJECTIVE: We hypothesized that white matter connectivity measured using diffusion spectrum imaging (DSI) would be restructured in WTC responders with MCI versus cognitively unimpaired responders. METHODS: Twenty responders (mean age 56; 10 MCI/10 unimpaired) recruited from an epidemiological study were characterized using NIA-AA criteria alongside controls matched on demographics (age/sex/occupation/race/education). Axial DSI was acquired on a 3T Siemen's Biograph mMR scanner (12-channel head coil) using a multi-band diffusion sequence. Connectometry examined whole-brain tract-level differences in white matter integrity. Fractional anisotropy (FA), mean diffusivity (MD), and quantified anisotropy were extracted for region of interest (ROI) analyses using the Desikan-Killiany atlas. RESULTS: Connectometry identified both increased and decreased connectivity within regions of the brains of responders with MCI identified in the corticothalamic pathway and cortico-striatal pathway that survived adjustment for multiple comparisons. MCI was also associated with higher FA values in five ROIs including in the rostral anterior cingulate; lower MD values in four ROIs including the left rostral anterior cingulate; and higher MD values in the right inferior circular insula. Analyses by cognitive domain revealed nominal associations in domains of response speed, verbal learning, verbal retention, and visuospatial learning. CONCLUSIONS: WTC responders with MCI at midlife showed early signs of neurodegeneration characterized by both increased and decreased white matter diffusivity in regions commonly affected by early-onset Alzheimer's disease.
Keywords: Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Emergency Responders; Female; Humans; Incidence; Male; Middle Aged; September 11 Terrorist Attacks; White Matter

Aggregates of RNA Binding Proteins and ER Chaperones Linked to Exosomes in Granulovacuolar Degeneration of the Alzheimer's Disease Brain. - Yamoah, Alfred; Tripathi, Priyanka; Sechi, Antonio; Köhler, Christoph; Guo, Haihong; Chandrasekar, Akila; Nolte, Kay Wilhelm; Wruck, Christoph Jan; Katona, Istvan; Anink, Jasper; Troost, Dirk; Aronica, Eleonora; et al. (J Alzheimers Dis, 2020)
Granulovacuolar degeneration (GVD) occurs in Alzheimer's disease (AD) brain due to compromised autophagy. Endoplasmic reticulum (ER) function and RNA binding protein (RBP) homeostasis regulate autophagy. We observed that the ER chaperones GRP78/BiP, Sigma receptor 1 (SigR1), and VAPB were elevated in many AD patients' subicular neurons. However, those neurons which were affected by GVD showed lower chaperone levels, and there was only minor co-localization of chaperones with GVD bodies (GVBs), suggesting that neurons lacking sufficient chaperone-mediated proteostasis enter the GVD pathway. Consistent with this notion, granular, incipient pTau aggregates in human AD and pR5 tau transgenic mouse neurons were regularly co-localized with increased chaperone immunoreactivity, whereas neurons with mature neurofibrillary tangles lacked both the chaperone buildup and significant GVD. On the other hand, APP/PS1 (APPswe/PSEN1dE9) transgenic mouse hippocampal neurons that are devoid of pTau accumulation displayed only few GVBs-like vesicles, which were still accompanied by prominent chaperone buildup. Identifying a potential trigger for GVD, we found cytoplasmic accumulations of RBPs including Matrin 3 and FUS as well as stress granules in GVBs of AD patient and pR5 mouse neurons. Interestingly, we observed that GVBs containing aggregated pTau and pTDP-43 were consistently co-localized with the exosomal marker Flotillin 1 in both AD and pR5 mice. In contrast, intraneuronal 82E1-immunoreactive amyloid-β in human AD and APP/PS1 mice only rarely co-localized with Flotillin 1-positive exosomal vesicles. We conclude that altered chaperone-mediated ER protein homeostasis and impaired autophagy manifesting in GVD are linked to both pTau and RBP accumulation and that some GVBs might be targeted to exocytosis.

Is Alzheimer's Disease a Liver Disease of the Brain? - Bassendine, Margaret F; Taylor-Robinson, Simon D; Fertleman, Michael; Khan, Michael; Neely, Dermot (J Alzheimers Dis, 2020)
Clinical specialization is not only a force for progress, but it has also led to the fragmentation of medical knowledge. The focus of research in the field of Alzheimer's disease (AD) is neurobiology, while hepatologists focus on liver diseases and lipid specialists on atherosclerosis. This article on AD focuses on the role of the liver and lipid homeostasis in the development of AD. Amyloid-β (Aβ) deposits accumulate as plaques in the brain of an AD patient long before cognitive decline is evident. Aβ generation is a normal physiological process; the steady-state level of Aβ in the brain is determined by balance between Aβ production and its clearance. We present evidence suggesting that the liver is the origin of brain Aβ deposits and that it is involved in peripheral clearance of circulating Aβ in the blood. Hence the liver could be targeted to decrease Aβ production or increase peripheral clearance.

Association of Low Systolic Blood Pressure with Postmortem Amyloid-β and Tau. - Oveisgharan, Shahram; Capuano, Ana W; Kapasi, Alifiya; Buchman, Aron S; Schneider, Julie A; Bennett, David A; Arvanitakis, Zoe (J Alzheimers Dis, 2020)
BACKGROUND: Vascular mechanisms may contribute to the accumulation of AD pathology. OBJECTIVE: We examined whether the burden of vascular risk factors proximate to death is associated with amyloid-β and tau levels or modified their known association. METHODS: We examined the brains of 1, 585 participants from two longitudinal community-based studies of older adults. Amyloid-β and tau were quantified by postmortem examination. The burden of vascular risk factors was summarized by calculating the Framingham general cardiovascular risk score (FRS) proximate to death. Using linear regressions, we examined the association of the FRS with the amyloid-β and tau levels and examined if the FRS modified the association of the amyloid-β with tau. RESULTS: On average, participants were nearly 90 years old and two-thirds were women. The FRS was not associated with amyloid-β (Spearman r  = -0.00, p  = 0.918) or tau (r = 0.01, p = 0.701). However, the FRS as a whole (estimate = -0.022, SE = 0.008, p = 0.009), and specifically the systolic blood pressure (SBP) component (estimate = -0.033, SE = 0.012, p = 0.009), modified the association of the amyloid-β with tau. Further analysis showed that the association between amyloid-β and tau was stronger at lower levels of SBP. CONCLUSION: Late-life vascular risk scores were not related to postmortem levels of amyloid-β or tau. However, lower levels of vascular risk scores and SBP were associated with a stronger association between amyloid-β and tau. These data suggest that vascular risk factors may modify the relation of AD pathology markers to one another.

Association of Peripheral Insulin Resistance and Other Markers of Type 2 Diabetes Mellitus with Brain Amyloid Deposition in Healthy Individuals at Risk of Dementia. - Pekkala, Timo; Hall, Anette; Mangialasche, Francesca; Kemppainen, Nina; Mecocci, Patrizia; Ngandu, Tiia; Rinne, Juha O; Soininen, Hilkka; Tuomilehto, Jaakko; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2020)
We explored the association of type 2 diabetes related blood markers with brain amyloid accumulation on PiB-PET scans in 41 participants from the FINGER PET sub-study. We built logistic regression models for brain amyloid status with12 plasma markers of glucose and lipid metabolism, controlled for diabetes and APOEɛ4 carrier status. Lower levels of insulin, insulin resistance index (HOMA-IR), C-peptide, and plasminogen activator (PAI-1) were associated with amyloid positive status, although the results were not significant after adjusting for multiple testing. None of the models found evidence for associations between amyloid status and fasting glucose or HbA1c.

The Association of Post-Stroke Cognitive Impairment and Gut Microbiota and its Corresponding Metabolites. - Liu, Yongqiang; Kong, Cheng; Gong, Li; Zhang, Xiaohui; Zhu, Yuefei; Wang, Haichao; Qu, Xiao; Gao, Renyuan; Yin, Fang; Liu, Xueyuan; Qin, Huanlong (J Alzheimers Dis, 2020)
BACKGROUND: Post-stroke cognitive impairment (PSCI) is an important factor causing disabilities after acute ischemic stroke (AIS). Emerging evidence suggested that gut microbiota play an important role in cognitive impairment. OBJECTIVE: This study aimed to explore the association between PSCI and gut microbiota. METHOD: 65 patients with newly diagnostic AIS finished the fecal collection on admission and cognitive assessment 3 months later in the clinic. Fecal samples were subjected to 16SrRNA gene sequencing and gas chromatography-mass spectrometry analysis. Additionally, we enrolled new 18 AIS patients, whose treatment was supplemented by probiotics, to assess the potential of microbial treatment in PSCI. RESULTS: PSCI patients were characterized by the significantly decreased alpha-diversity, disturbed microbial composition, and corresponding metabolites compared with non-PSCI patients. Increased Fusobacterium and deficiency of microbial metabolized short-chain fatty acids (SCFAs) were significantly associated with PSCI. A model based on gut microbiota and SCFAs could predict 3 months or longer PSCI early and accurately after stroke onset. While traditional probiotic administration had little effect on PSCI, it could ameliorate patients' mood, including depression and anxiety in the 3 months after stroke. CONCLUSION: Our study revealed the association between PSCI and gut microbiota and its corresponding metabolites for the first time, suggesting the potential for applying microbiota and its corresponding metabolites to early clinical diagnosis and treatment of PSCI.

Awareness of the COVID-19 Outbreak and Resultant Depressive Tendencies in Patients with Severe Alzheimer's Disease. - Tsugawa, Akito; Sakurai, Shu; Inagawa, Yuta; Hirose, Daisuke; Kaneko, Yoshitsugu; Ogawa, Yusuke; Serisawa, Shuntaro; Takenoshita, Naoto; Sakurai, Hirofumi; Kanetaka, Hidekazu; Hirao, Kentaro; Shimizu, Soichiro (J Alzheimers Dis, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has substantially affected patients with dementia and their caregivers. However, we found not all Alzheimer's disease (AD) patients were afraid of COVID-19 infection. Therefore, we investigated the association between rate of awareness of COVID-19 and depressive tendency in AD. 126 consecutive outpatients with AD were enrolled in this study from May 25, on the day when the declaration of emergency was lifted in Japan, through June 30, 2020. In addition to routine psychological tests, the participants were asked the following two questions: "Do you know COVID-19?" and "Why are you wearing a face mask?". Moderate to severe AD patients were found to have a low COVID-19 recognition rate and did not fully understand why they were wearing face masks. In addition, because they did not understand the seriousness of the COVID-19 outbreak, their Geriatric Depression Scale scores were also substantially lower. These results may appear to simply indicate that people with severe dementia are unaware of current events. However, these results provide insights into how to care for patients with dementia and how to allocate the time and support of our limited staff during the COVID-19 outbreak.
Keywords: Aged; Alzheimer Disease; Awareness; Betacoronavirus; Caregivers; Communicable Disease Control; Coronavirus Infections; COVID-19; Female; Humans; Japan; Male; Mental Competency; Pandemics; Patient Care; Pneumonia, Viral; Psychosocial Support Systems; SARS-CoV-2; Severity of Illness Index

Brain Volume Predicts Behavioral and Psychological Symptoms in Alzheimer's Disease. - Boublay, Nawele; Bouet, Romain; Dorey, Jean-Michel; Padovan, Catherine; Makaroff, Zaza; Federico, Denis; Gallice, Isabelle; Barrellon, Marie-Odile; Robert, Philippe; Moreaud, Olivier; Rouch, Isabelle; Krolak-Salmon, Pierre (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are frequent and troublesome for patients and caregivers. Considering possible preventive approaches, a better understanding of underlying neural correlates of BPSD is crucial. OBJECTIVE: The aim is to assess whether brain regional volume predicts behavioral changes in mild AD. METHODS: This work took part from the PACO study, a multicenter and prospective study that included 252 patients with mild AD from 2009 to 2014. Fifty-three patients were retained. Forty healthy matched control subjects from the ADNI cohort were included as controls. Voxel-based morphometry analysis was conducted to assess regional brain volume using baseline MRI scans as a predictor of future behavioral changes over a period of 18 months. Behavior was assessed at baseline and longitudinally at 6-month intervals using the shortened form of the Neuropsychiatric Inventory (NPI). RESULTS: The volume of 23 brain structures in frontal, temporal, parietal, occipital, subcortical regions and cerebellum predicted the evolution of NPI scores. Frontal volume was the most powerful predictor with frontal gyri, anterior cingulate cortex, and orbital gyri being particularly involved. CONCLUSION: To our knowledge, this is the first study assessing regional brain volumes as predictors of behavioral changes considered at earlier stages of AD. Up to 23 brain structures were associated with an increased risk of developing BPSD. Frontal lobe volume was the strongest predictor of future evolution of NPI. The involvement of multiple structures in the prediction of behavior suggests a role of the main large-scale networks involved in cognition.

Cerebrospinal Fluid Metals and the Association with Cerebral Small Vessel Disease. - Shams, Mana; Martola, Juha; Charidimou, Andreas; Granberg, Tobias; Ferreira, Daniel; Westman, Eric; Wintermark, Max; Iv, Michael; Larvie, Mykol; Kristoffersen Wiberg, Maria; Kaijser, Magnus; Forsgard, Niklas; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Brain metal homeostasis is essential for brain health, and deregulation can result in oxidative stress on the brain parenchyma. OBJECTIVE: Our objective in this study was to focus on two hemorrhagic MRI manifestations of small vessel disease [cerebral microbleeds (CMBs) and cortical superficial siderosis (cSS)] and associations with cerebrospinal fluid (CSF) iron levels. In addition, we aimed to analyze CSF biomarkers for dementia and associations with CSF metal levels. METHODS: This is a cross-sectional study of 196 patients who underwent memory clinic investigation, including brain MRI. CSF was collected and analyzed for metals, amyloid-β (Aβ) 42, total tau (T-tau), and phosphorylated tau (P-tau), and CSF/serum albumin ratios. Statistical analyses were performed using generalized linear models. RESULTS: No significant difference was found between CSF metal levels across diagnostic groups. Higher iron and copper levels were associated with higher CSF levels of Aβ42, T-tau, P-tau, and CSF/serum albumin ratios (p < 0.05). Zinc was associated with higher CSF/serum albumin ratios. There was no significant association between CMBs or cSS and CSF iron levels. An increase in CSF iron with the number of CMBs was seen in APOEɛ4 carriers. CONCLUSION: CSF iron levels are elevated with cerebral microbleeds in APOEɛ4 carriers, with no other association seen with hemorrhagic markers of small vessel disease. The association of elevated CSF iron and copper with tau could represent findings of increased neurodegeneration in these patients.

Concentration-Dependent Activity of Hydromethylthionine on Clinical Decline and Brain Atrophy in a Randomized Controlled Trial in Behavioral Variant Frontotemporal Dementia. - Shiells, Helen; Schelter, Bjoern O; Bentham, Peter; Baddeley, Thomas C; Rubino, Christopher M; Ganesan, Harish; Hammel, Jeffrey; Vuksanovic, Vesna; Staff, Roger T; Murray, Alison D; Bracoud, Luc; Wischik, Damon J; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Hydromethylthionine is a potent inhibitor of pathological aggregation of tau and TDP-43 proteins. OBJECTIVE: To compare hydromethylthionine treatment effects at two doses and to determine how drug exposure is related to treatment response in bvFTD. METHODS: We undertook a 52-week Phase III study in 220 bvFTD patients randomized to compare hydromethylthionine at 200 mg/day and 8 mg/day (intended as a control). The principal outcomes were change on the Addenbrookes Cognitive Examination - Revised (ACE-R), the Functional Activities Questionnaire (FAQ), and whole brain volume. Secondary outcomes included Modified Clinical Global Impression of Change (Modified-CGIC). A population pharmacokinetic exposure-response analysis was undertaken in 175 of the patients with available blood samples and outcome data using a discriminatory plasma assay for the parent drug. RESULTS: There were no significant differences between the two doses as randomized. There were steep concentration-response relationships for plasma levels in the range 0.3-0.6 ng/ml at the 8 mg/day dose on clinical and MRI outcomes. There were significant exposure-dependent differences at 8 mg/day for FAQ, Modified-CGIC, and whole brain atrophy comparing patients with plasma levels greater than 0.346 ng/ml with having minimal drug exposure. The exposure-response is biphasic with worse outcomes at the high concentrations produced by 200 mg/day. CONCLUSIONS: Hydromethylthionine has a similar concentration-response profile for effects on clinical decline and brain atrophy at the 8 mg/day dose in bvFTD as recently reported in AD. Treatment responses in bvFTD are predicted to be maximal at doses in the range 20-60 mg/day. A confirmatory placebo-controlled trial is now planned.

Costs and Resource Use Associated with Community-Dwelling Patients with Alzheimer's Disease in Japan: Baseline Results from the Prospective Observational GERAS-J Study. - Nakanishi, Miharu; Igarashi, Ataru; Ueda, Kaname; Brnabic, Alan J M; Treuer, Tamas; Sato, Masayo; Kahle-Wrobleski, Kristin; Meguro, Kenichi; Yamada, Masahito; Mimura, Masaru; Arai, Heii (J Alzheimers Dis, 2020)
BACKGROUND: As the Japanese population ages, caring for people with Alzheimer's disease (AD) dementia is becoming a major socioeconomic issue. OBJECTIVE: To determine the contribution of patient and caregiver costs to total societal costs associated with AD dementia. METHODS: Baseline data was used from the longitudinal, observational GERAS-J study. Using the Mini-Mental State Examination (MMSE) score, patients routinely visiting memory clinics were stratified into three groups based on AD severity. Health care resource utilizationwas recorded using the Resource Utilization in Dementia questionnaire. Total monthly societal costs were estimated using Japan-specific unit costs of services and products (patient direct health care use, patient social care use, and informal caregiving time). Uncertainty around mean costs was estimated using bootstrapping methods. RESULTS: Overall, 553 community-dwelling patients withADdementia (28.3% mild[MMSE21-26], 37.8% moderate[MMSE 15-20], and 34.0% moderately severe/severe [MMSE < 14]) and their caregivers were enrolled. Patient characteristics were: mean age 80.3 years, 72.7% female, and 13.6% living alone. Caregiver characteristics were: mean age 62.1 years, 70.7% female, 78.8% living with patient, 49.0% child of patient, and 39.2% sole caregiver. Total monthly societal costs of AD dementia (Japanese yen) were: 158,454 (mild), 211,301 (moderate), and 294,224 (moderately severe/severe). Informal caregiving costs comprised over 50% of total costs. CONCLUSION: Baseline results of GERAS-J showed that total monthly societal costs associated with AD dementia increased with AD severity. Caregiver-related costs were the largest cost component. Interventions are needed to decrease informal costs and decrease caregiver burden.

Costs of Early Stage Alzheimer's Disease in the United States: Cross-Sectional Analysis of a Prospective Cohort Study (GERAS-US)1. - Robinson, Rebecca L; Rentz, Dorene M; Andrews, Jeffrey Scott; Zagar, Anthony; Kim, Yongin; Bruemmer, Valerie; Schwartz, Ronald L; Ye, Wenyu; Fillit, Howard M (J Alzheimers Dis, 2020)
BACKGROUND: Costs associated with early stages of Alzheimer's disease (AD; mild cognitive impairment [MCI] and mild dementia [MILD]) are understudied. OBJECTIVE: To compare costs associated with MCI and MILD due to AD in the United States. METHODS: Data included baseline patient/study partner medical history, healthcare resource utilization, and outcome assessments as part of a prospective cohort study. Direct, indirect, and total societal costs were derived by applying standardized unit costs to resources for the 1-month pre-baseline period (USD2017). Costs/month for MCI and MILD cohorts were compared using analysis of variance models. To strengthen the confidence of diagnosis, amyloid-β (Aβ) tests were included and analyses were replicated stratifying within each cohort by amyloid status [+ /-]. RESULTS: Patients (N = 1327) with MILD versus MCI had higher total societal costs/month ($4243 versus $2816; p < 0.001). These costs were not significantly different within each severity cohort by amyloid status. The largest fraction of overall costs were informal caregiver costs (45.1%) for the MILD cohort, whereas direct medical patient costs were the largest for the MCI cohort (39.0%). Correspondingly, caregiver time spent on basic activities of daily living (ADLs), instrumental ADLs, and supervision time was twice as high for MILD versus MCI (all p < 0.001). CONCLUSION: Early AD poses a financial burden, and despite higher functioning among those with MCI, caregivers were significantly impacted. The major cost driver was the patient's clinical cognitive-functional status and not amyloid status. Differences were primarily due to rising need for caregiver support.

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Dementia in the COVID-19 Period. - Korczyn, Amos D (J Alzheimers Dis, 2020)
Keywords: Betacoronavirus; Coronavirus; Coronavirus Infections; COVID-19; Dementia; Humans; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2; Telemedicine

Development and Validation of a High Sensitivity Assay for Measuring p217 + tau in Cerebrospinal Fluid. - Triana-Baltzer, Gallen; Van Kolen, Kristof; Theunis, Clara; Moughadam, Setareh; Slemmon, Randy; Mercken, Marc; Galpern, Wendy; Sun, Hong; Kolb, Hartmuth (J Alzheimers Dis, 2020)
BACKGROUND: Early and accurate detection and staging is critical to managing Alzheimer's disease (AD) and supporting clinical trials. Cerebrospinal fluid (CSF) biomarkers for amyloid-β peptides, tau species, and various neurodegenerative and inflammatory analytes are leading the way in this regard, yet there is room for improved sensitivity and specificity. In particular tau is known to be present in many different fragments, conformations, and post-translationally modified forms. While the exact tau species that might best reflect AD pathology is unknown, a growing body of evidence suggests that forms with high levels of phosphorylation in the mid-region may be especially enriched in AD. OBJECTIVE: Develop an assay for measuring p217tau in CSF. METHODS: Here we describe the development and validation of a novel sELISA for measuring CSF tau species containing phosphorylation at threonines 212 & 217, aka p217 + tau, using the PT3 antibody. RESULTS: While the analyte is present at extremely low levels the assay is sufficiently sensitive and specific to quantitate p217 + tau with excellent precision, accuracy, and dilution linearity, allowing good differentiation between diagnostic subgroups. The p217 + tau measurements appear to track AD pathology better than the commonly used p181tau epitope, suggesting superior diagnostic and staging performance. Finally, the assay can also be configured to differentiate antibody-bound versus antibody-free tau, and therefore can be used to measure target engagement by p217 + tau-targeting immunotherapeutics. CONCLUSION: The assay for measuring p217 + tau described here is highly sensitive, accurate, precise, dilution linear, and shows good potential for identifying and staging AD.

Development of Classification Models for the Prediction of Alzheimer's Disease Utilizing Circulating Sex Hormone Ratios. - Hayashi, Kentaro; Gonzales, Tina K; Kapoor, Amita; Ziegler, Toni E; Meethal, Sivan Vadakkadath; Atwood, Craig S (J Alzheimers Dis, 2020)
BACKGROUND: While sex hormones are essential for normal cognitive health, those individuals with greater endocrine dyscrasia around menopause and with andropause are more likely to develop cognitive loss and Alzheimer's disease (AD). OBJECTIVE: To assess whether circulating sex hormones may provide an etiologically significant, surrogate biomarker, for cognitive decline. METHODS: Plasma (n = 152) and serum (n = 107) samples from age- and gender-matched AD and control subjects from the Wisconsin Alzheimer's Disease Research Center (ADRC) were analyzed for11 steroids and follicle-stimulating hormone. Logistic regression (LR), correlation analyses, and recursive partitioning (RP) were used to examine the interactions of hormones and hormone ratios and their association with AD. Models generated were then tested on an additional 43 ADRC samples. RESULTS: The wide variation and substantial overlap in the concentrations of all circulating sex steroids across control and AD groups precluded their use for predicting AD. Classification tree analyses (RP) revealed interactions among single hormones and hormone ratios that associated with AD status, the most predictive including only the hormone ratios identified by LR. The strongest associations were observed between cortisol, cortisone, and androstenedione with AD, with contributions from progesterone and 17β-estradiol. Utilizing this model, we correctly predicted 81% of AD test cases and 64% of control test cases. CONCLUSION: We have developed a diagnostic model for AD, the Wisconsin Hormone Algorithm Test for Cognition (WHAT-Cog), that utilizes classification tree analyses of hormone ratios. Further refinement of this technology could provide a quick and cheap diagnostic method for screening those with AD.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Effect of Mentally Challenging Occupations on Incident Dementia Differs Between African Americans and Non-Hispanic Whites. - Hyun, Jinshil; Hall, Charles B; Sliwinski, Martin J; Katz, Mindy J; Wang, Cuiling; Ezzati, Ali; Lipton, Richard B (J Alzheimers Dis, 2020)
BACKGROUND: Engaging in mentally challenging activities may protect against dementia in late life. However, little is known whether the association between mentally challenging activities and dementia risk varies with race/ethnicity. OBJECTIVE: The current study investigates whether having jobs with higher mental stimulation is differentially associated with a decreased risk of dementia between African Americans (AAs) and non-Hispanic Whites (nHWs). METHODS: The sample consisted of 1,079 individuals (66% nHWs, 28% AAs; age = 78.6±5.3) from the longitudinal Einstein Aging Study. Occupation information of each participant was collected retrospectively at baseline and was linked to the substantive complexity of work score from the Dictionary of Occupational Titles. Cox proportional hazards models were used to evaluate the associations of occupational complexity with risk of dementia. RESULTS: Individuals whose jobs had moderate-to-high levels of complexity, compared to those with the lowest complexity, were at modestly decreased risk for incident dementia. When stratified by race, moderate-to-high levels of occupational complexity were significantly associated with lower risk of developing dementia for AAs (HR = 0.35). When risk of dementia was evaluated based on the combinations of race×occupational complexity, AAs with lowest occupational complexity showed the highest risk of developing dementia, while other combinations exhibited lower risk of developing dementia (HRs = 0.36 0.43). CONCLUSION: Our results suggest that moderate-to-high levels of complexity at work are associated with a decreased risk of incident dementia in AAs. Understanding the differential effects of mentally challenging occupations across race/ethnicity may suggest important intervention strategies that could mitigate racial disparities in dementia rates.

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Effects of Probiotic Supplementation on Short Chain Fatty Acids in the AppNL-G-F Mouse Model of Alzheimer's Disease. - Kaur, Harpreet; Golovko, Svetlana; Golovko, Mikhail Y; Singh, Surjeet; Darland, Diane C; Combs, Colin K (J Alzheimers Dis, 2020)
BACKGROUND: The intestinal microbiota and its metabolites, particularly short-chain fatty acids (SCFAs), have been implicated in immune function, host metabolism, and even behavior. OBJECTIVE: This study was performed to investigate whether probiotic administration influences levels of intestinal microbiota and their metabolites in a fashion that may attenuate brain changes in a mouse model of Alzheimer's disease (AD). METHODS: C57BL/6 wild-type (WT) mice were compared to AppNL-G-Fmice. The animals were treated with either vehicle or probiotic (VSL#3) for 8 weeks. Fecal microbiome analysis along with Aβ, GFAP, Iba-1, c-Fos, and Ki-67 immunohistochemistry was done. SCFAs were analyzed in serum and brains using UPLC-MS/MS. RESULTS: Probiotic (VSL#3) supplementation for 2 months resulted in altered microbiota in both WT and AppNL-G-Fmice. An increase in serum SCFAs acetate, butyrate, and lactate were found in both genotypes following VSL#3 treatment. Propionate and isobutyrate were only increased in AppNL-G-Fmice. Surprisingly, VSL#3 only increased lactate and acetate in brains of AppNL-G-Fmice. No significant differences were observed between vehicle and VSL#3 fed AppNL-G-Fhippocampal immunore activities of Aβ, GFAP, Iba-1, and Ki-67. However, hippocampal c-Fos staining increased in VSL#3 fed AppNL-G-Fmice. CONCLUSION: These data demonstrate intestinal dysbiosis in the AppNL-G-Fmouse model of AD. Probiotic VSL#3 feeding altered both serum and brain levels of lactate and acetate in AppNL-G-Fmice correlating with increased expression of the neuronal activity marker, c-Fos.

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Exploration of Plasma Lipids in Mild Cognitive Impairment due to Alzheimer's Disease. - Bergland, Anne Katrine; Proitsi, Petroula; Kirsebom, Bjørn-Eivind; Soennesyn, Hogne; Hye, Abdul; Larsen, Alf Inge; Xu, Jin; Legido-Quigley, Cristina; Rajendran, Lawrence; Fladby, Tormod; Aarsland, Dag (J Alzheimers Dis, 2020)
BACKGROUND: Lipids have important structural roles in cell membranes and changes to these membrane lipids may influence β- and γ-secretase activities and thus contribute to Alzheimer's disease (AD) pathology. OBJECTIVE: To explore baseline plasma lipid profiling in participants with mild cognitive impairment (MCI) with and without AD pathology. METHODS: We analyzed 261 plasma lipid profiles using reversed phase chromatography mass spectrometry in cerebrospinal fluid amyloid positive (Aβ+) or negative (Aβ-) participants with MCI as compared to controls. Additionally, we analyzed the potential associations of plasma lipid profiles with performance on neuropsychological tests at baseline and after two years. RESULTS: Sphingomyelin (SM) concentrations, particularly, SM(d43:2), were lower in MCI Aβ+ individuals compared to controls. Further, SM(d43:2) was also nominally reduced in MCI Aβ+ individuals compared to MCI Aβ-. No plasma lipids were associated with performance on neuropsychological tests at baseline or between the two time points after correction for multiple testing. CONCLUSION: Reduced plasma concentrations of SM were associated with AD.

Falls Associate with Neurodegenerative Changes in ATN Framework of Alzheimer's Disease. - Keleman, Audrey; Wisch, Julie K; Bollinger, Rebecca M; Grant, Elizabeth A; Benzinger, Tammie L; Morris, John C; Ances, Beau M; Stark, Susan L (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral markers for Alzheimer's disease (AD) are not included within the widely used amyloid-tau-neurodegeneration framework. OBJECTIVE: To determine when falls occur among cognitively normal (CN) individuals with and without preclinical AD. METHODS: This cross-sectional study recorded falls among CN participants (n = 83) over a 1-year period. Tailored calendar journals recorded falls. Biomarkers including amyloid positron emission tomography (PET) and structural and functional magnetic resonance imaging were acquired within 2 years of fall evaluations. CN participants were dichotomized by amyloid PET (using standard cutoffs). Differences in amyloid accumulation, global resting state functional connectivity (rs-fc) intra-network signature, and hippocampal volume were compared between individuals who did and did not fall using Wilcoxon rank sum tests. Among preclinical AD participants (amyloid-positive), the partial correlation between amyloid accumulation and global rs-fc intra-network signature was compared for those who did and did not fall. RESULTS: Participants who fell had smaller hippocampal volumes (p = 0.04). Among preclinical AD participants, those who fell had a negative correlation between amyloid uptake and global rs-fc intra-network signature (R = -0.75, p = 0.012). A trend level positive correlation was observed between amyloid uptake and global rs-fc intra-network signature (R = 0.70, p = 0.081) for preclinical AD participants who did not fall. CONCLUSION: Falls in CN older adults correlate with neurodegeneration biomarkers. Participants without falls had lower amyloid deposition and preserved global rs-fc intra-network signature. Falls most strongly correlated with presence of amyloid and loss of brain connectivity and occurred in later stages of preclinical AD.

Feasibility and Efficacy of Intra-Arterial Administration of Embryonic Stem Cell Derived-Mesenchymal Stem Cells in Animal Model of Alzheimer's Disease. - Kim, Dong Yeol; Choi, Sung Hyun; Lee, Jee Sun; Kim, Hyoung Jun; Kim, Ha Na; Lee, Ji Eun; Shin, Jin Young; Lee, Phil Hyu (J Alzheimers Dis, 2020)
Mesenchymal stem cells (MSCs) promote functional recoveries in pathological experimental models of the central nervous system and are currently being tested in clinical trials for neurological disorders. However, no studies have examined the various roles of embryonic stem cell derived (ES)-MSCs in eliciting therapeutic effects for Alzheimer's disease (AD). In the present study, we investigated the neuroprotective effect of ES-MSCs in cellular and animal models of AD, as well as the safety of the intra-arterial administration of ES-MSCs in an AD animal model. ES-MSCs displayed higher cell viability than that of bone marrow (BM)-MSCs in amyloid-β (Aβ)-induced cellular models. Moreover, the efficacy of autophagy induction in ES-MSCs was comparable to that of BM-MSCs; however, intracellular Aβ levels were more significantly reduced in ES-MSCs than in BM-MSCs. In a rat model of AD, ES-MSCs significantly inhibited Aβ-induced cell death in the hippocampus and promoted autophagolysosomal clearance of Aβ, which was concomitantly followed by decreased levels of Aβ in the hippocampus. Furthermore, ES-MSC treatment in Aβ-treated rats featured a higher memory performance than that of rats injected solely with Aβ. Finally, intra-arterial administration of an appropriate cell density of ES-MSCs was safe and free from in situ occlusion or cerebral ischemia. These data support the therapeutic potential of ES-MSCs and clinical applications of the intra-arterial route of ES-MSC administration in AD.

Functional Integrity of Synapses in the Central Nervous System of Cognitively Intact Individuals with High Alzheimer's Disease Neuropathology is Associated with Absence of Synaptic Tau Oligomers. - Singh, Ayush; Allen, Dyron; Fracassi, Anna; Tumurbaatar, Batbayar; Natarajan, Chandramouli; Scaduto, Pietro; Woltjer, Randy; Kayed, Rakez; Limon, Agenor; Krishnan, Balaji; Taglialatela, Giulio (J Alzheimers Dis, 2020)
BACKGROUND: Certain individuals, here referred to as Non-Demented with Alzheimer Neuropathology (NDAN), do not show overt neurodegeneration (N - ) and remain cognitively intact despite the presence of plaques (A+) and tangles (T+) that would normally be consistent with fully symptomatic Alzheimer's disease (AD). OBJECTIVE: The existence of NDAN (A + T +N - ) subjects suggests that the human brain utilizes intrinsic mechanisms that can naturally evade cognitive decline normally associated with the symptomatic stages of AD (A + T +N +). Deciphering the underlying mechanisms would prove relevant to develop complementing therapeutics to prevent progression of AD-related cognitive decline. METHODS: Previously, we have reported that NDAN present with preserved neurogenesis and synaptic integrity paralleled by absence of amyloid oligomers at synapses. Using postmortem brain samples from age-matched control subjects, demented AD patients and NDAN individuals, we performed immunofluorescence, western blots, micro transplantation of synaptic membranes in Xenopus oocytes followed by twin electrode voltage clamp electrophysiology and fluorescence assisted single synaptosome-long term potentiation studies. RESULTS: We report decreased tau oligomers at synapses in the brains of NDAN subjects. Furthermore, using novel approaches we report, for the first time, that such absence of tau oligomers at synapses is associated with synaptic functional integrity in NDAN subjects as compared to demented AD patients. CONCLUSION: Overall, these results give further credence to tau oligomers as primary actors of synaptic destruction underscoring cognitive demise in AD and support their targeting as a viable therapeutic strategy for AD and related tauopathies.

Gamma Entrainment in a Large Retrospective Cohort: Implications for Photic Stimulation Therapy for Alzheimer's Disease. - Zibrandtsen, Ivan C; Agger, Mikkel; Kjaer, Troels W (J Alzheimers Dis, 2020)
BACKGROUND: Studies on mice models of Alzheimer's disease (AD) have suggested potential therapeutic benefits of intermittent photic stimulation at 40 Hz. OBJECTIVE: We examined the physiological response of 40 Hz intermittent photic stimulation (IPS) on routine EEG in a large retrospective cohort to investigate the effects of age on induced gamma oscillations by intermittent photic stimulation. Since most AD patients are elderly, it is important for future research to know if age affects photic stimulation. METHODS: Retrospective data from 1,464 subjects aged 0- 91. We performed frequency analysis and automatic peak detection and used regression analysis to investigate the effects of age and sex on peak frequencies and amplitude changes. To investigate the spread of the induced gamma oscillations, we assessed averaged topographies of 40 Hz band power. RESULTS: There was a statistically significant but very minor effect of age on amplitude change (- 0.002 normalized power per year, p < 0.0001) but not for sex (p = 0.728). Detection probability of induced peaks was significantly predicted by both age (OR = 0.988, CI 95 % [0.984, 0.993], p < 0.00001) and sex (OR = 0.625, CI 95 % [0.496, 0.787>], p < 0.0001). The induced 40 Hz gamma entrainment is spatially confined to the occipital area. CONCLUSION: There is a significant effect of age on induced gamma activity, but advanced age does not fundamentally change the behavior of the response in either magnitude or spatial distribution. This fact is important regarding future research into the possible therapeutic effects of photic stimulation in patients with AD.

Gene Ontology Curation of Neuroinflammation Biology Improves the Interpretation of Alzheimer's Disease Gene Expression Data. - Kramarz, Barbara; Huntley, Rachael P; Rodríguez-López, Milagros; Roncaglia, Paola; Saverimuttu, Shirin C C; Parkinson, Helen; Bandopadhyay, Rina; Martin, Maria-Jesus; Orchard, Sandra; Hooper, Nigel M; Brough, David; Lovering, Ruth C (J Alzheimers Dis, 2020)
BACKGROUND: Gene Ontology (GO) is a major bioinformatic resource used for analysis of large biomedical datasets, for example from genome-wide association studies, applied universally across biological fields, including Alzheimer's disease (AD) research. OBJECTIVE: We aim to demonstrate the applicability of GO for interpretation of AD datasets to improve the understanding of the underlying molecular disease mechanisms, including the involvement of inflammatory pathways and dysregulated microRNAs (miRs). METHODS: We have undertaken a systematic full article GO annotation approach focused on microglial proteins implicated in AD and the miRs regulating their expression. PANTHER was used for enrichment analysis of previously published AD data. Cytoscape was used for visualizing and analyzing miR-target interactions captured from published experimental evidence. RESULTS: We contributed 3,084 new annotations for 494 entities, i.e., on average six new annotations per entity. This included a total of 1,352 annotations for 40 prioritized microglial proteins implicated in AD and 66 miRs regulating their expression, yielding an average of twelve annotations per prioritized entity. The updated GO resource was then used to re-analyze previously published data. The re-analysis showed novel processes associated with AD-related genes, not identified in the original study, such as 'gliogenesis', 'regulation of neuron projection development', or 'response to cytokine', demonstrating enhanced applicability of GO for neuroscience research. CONCLUSIONS: This study highlights ongoing development of the neurobiological aspects of GO and demonstrates the value of biocuration activities in the area, thus helping to delineate the molecular bases of AD to aid the development of diagnostic tools and treatments.

The Impact of Amyloid-β or Tau on Cognitive Change in the Presence of Severe Cerebrovascular Disease. - Jang, Hyemin; Kim, Hee Jin; Sim Choe, Yeong; Kim, Soo-Jong; Park, Seongbeom; Kim, Yeshin; Woon Kim, Ko; Hyoung Lyoo, Chul; Cho, Hanna; Hoon Ryu, Young; Choi, Jae Yong; DeCarli, Charles; et al. (J Alzheimers Dis, 2020)
BACKGROUND: As Alzheimer's disease (AD) and cerebral small vessel disease (CSVD) commonly coexist, the interaction between two has been of the considerable interest. OBJECTIVE: We determined whether the association of Aβ and tau with cognitive decline differs by the presence of significant CSVD. METHODS: We included 60 subcortical vascular cognitive impairment (SVCI) from Samsung Medical Center and 82 Alzheimer's disease-related cognitive impairment (ADCI) from ADNI, who underwent Aβ (florbetaben or florbetapir) and tau (flortaucipir, FTP) PET imaging. They were retrospectively assessed for 5.0±3.9 and 5.6±1.9 years with Clinical Dementia Rating-sum of boxes (CDR-SB)/Mini-Mental State Examination (MMSE). Mixed effects models were used to investigate the interaction between Aβ/tau and group on CDR-SB/MMSE changes. RESULTS: The frequency of Aβ positivity (45% versus 54.9%, p = 0.556) and mean global FTP SUVR (1.17±0.21 versus 1.16±0.17, p = 0.702) were not different between the two groups. We found a significant interaction effect of Aβ positivity and SVCI group on CDR-SB increase/MMSE decrease (p = 0.013/p <  0.001) change, and a significant interaction effect of global FTP uptake and SVCI group on CDR-SB increase/MMSE decrease (p <  0.001 and p = 0.030) change. Finally, the interaction effects of regional tau and group were prominent in the Braak III/IV (p = 0.001) and V/VI (p = 0.003) not in Braak I/II region (p = 0.398). CONCLUSION: The association between Aβ/tau and cognitive decline is stronger in SVCI than in ADCI. Therefore, our findings suggested that Aβ positivity or tau burden (particularly in the Braak III/IV or V/VI regions) and CSVD might synergistically affect cognitive decline.

Impact of APOE and BDNF Val66Met Gene Polymorphisms on Cognitive Functions in Patients with Amnestic Mild Cognitive Impairment. - Cechova, Katerina; Andel, Ross; Angelucci, Francesco; Chmatalova, Zuzana; Marková, Hana; Laczó, Jan; Vyhnálek, Martin; Matoska, Vaclav; Kaplan, Vojtech; Nedelska, Zuzana; Ward, David D; Hort, Jakub (J Alzheimers Dis, 2020)
Apolipoprotein (APOE) ɛ4 is a well-known risk factor for late-onset Alzheimer's disease (AD), but other AD-related gene polymorphisms might also be important, such as the polymorphism within the brain-derived neurotrophic factor (BDNF) gene. Carriage of BDNF Val66Met has been associated with faster cognitive decline and greater hippocampal atrophy in cognitively normal elderly. Thus, we examined the effects of the concurrent presence of APOE and BDNF polymorphisms on cognitive functions and brain morphometry in amnestic mild cognitive impairment (aMCI) patients. 107 aMCI patients (mean age = 72.2) were recruited from the Czech Brain Aging Study and, based on APOE and BDNF genes polymorphisms, were divided into four groups: ɛ4-BDNFVal/Val (n = 37), ɛ4-BDNFMet (n = 19), ɛ4+BDNFVal/Val (n = 35), and ɛ4+BDNFMet (n = 16). All patients underwent clinical examination, magnetic resonance imaging, and complex neuropsychological battery. The combination of APOEɛ4+ and BDNF Met was associated with significantly worse memory performance in immediate and delayed recall compared to other polymorphism groups. We did not observe increased atrophy in areas related to memory function in the ɛ4+BDNFMet group. Our findings suggest that carriage of ɛ4+BDNFMet is associated with more pronounced memory dysfunction, a typical feature of early AD, but not with structural brain changes in aMCI patients. These findings suggest that in APOEɛ4/BDNF Met carriers, synaptic dysfunction affecting memory may precede pronounced structural changes.

In Vivo Validation of a Small Molecule Inhibitor of Tau Self-Association in htau Mice. - Davidowitz, Eliot J; Krishnamurthy, Pavan K; Lopez, Patricia; Jimenez, Heidy; Adrien, Leslie; Davies, Peter; Moe, James G (J Alzheimers Dis, 2020)
Tau oligomers have been shown to transmit tau pathology from diseased neurons to healthy neurons through seeding, tau misfolding, and aggregation that is thought to play an influential role in the progression of Alzheimer's disease (AD) and related tauopathies. To develop a small molecule therapeutic for AD and related tauopathies, we have developed in vitro and cellular assays to select molecules inhibiting the first step in tau aggregation, the self-association of tau into oligomers. In vivo validation studies of an optimized lead compound were independently performed in the htau mouse model of tauopathy that expresses the human isoforms of tau without inherited tauopathy mutations that are irrelevant to AD. Treated mice did not show any adverse events related to the compound. The lead compound significantly reduced the level of self-associated tau and total and phosphorylated insoluble tau aggregates. The dose response was linear with respect to levels of compound in the brain. A confirmatory study was performed with male htau mice that gave consistent results. The results validated our screening approach by showing that targeting tau self-association can inhibit the entire tau aggregation pathway by using the selected and optimized lead compound whose activity translated from in vitro and cellular assays to an in vivo model of tau aggregation.

Individual Differences in the Effects of Physical Activity on Cognitive Function in People with Mild to Moderate Dementia. - Uijen, Iris L; Aaronson, Justine A; Karssemeijer, Esther G A; Olde Rikkert, Marcel G M; Kessels, Roy P C (J Alzheimers Dis, 2020)
The aim of this study was to investigate whether the effect of physical activity on cognitive function in persons with dementia is moderated by patient characteristics as Apolipoprotein E and dementia type. We included 101 individuals with dementia and calculated the reliable change index to determine the change in global cognition, executive function, episodic memory, working memory, and processing speed before and after a 12-week exercise training. We found a higher treatment-related benefit in episodic memory in persons with non-Alzheimer's disease compared to persons with Alzheimer's disease, and in executive function in individuals with better baseline cognitive function.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Loss of Functional Dentition is Associated with Cognitive Impairment. - Han, Ji Hyun; Lee, Hyo-Jung; Han, Ji Won; Suh, Seung Wan; Lee, Ju Ri; Byun, Seonjeong; Kim, Keun Suh; Kim, Sung Yeol; Lee, Jung-Tae; Yoo, Eunha; Chang, Na-Hee; Kim, Tae Hui; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Although tooth loss is known to increase the risk of cognitive impairment and dementia, few studies have investigated the association between functional teeth including rehabilitated lost teeth and cognitive functionObjective:We investigated the associations of the numbers of functional teeth and functional occlusal units with cognitive impairment and cognitive function in late life. METHODS: The current study was conducted as a part of the Korean Longitudinal Study on Cognitive Aging and Dementia (KLOSCAD), a community-based elderly cohort study. We analyzed 411 participants who have agreed with the additional dental exam. Geriatric psychiatrists and neuropsychologists administered the Consortium to Establish a Registry for Alzheimer's disease Assessment Packet Clinical and Neuropsychological Assessment Battery to all participants, and dentists examined their dental status. RESULTS: Higher number of functional teeth (OR = 0.955, 95% CI = 0.914-0.997, p = 0.037) and higher number of functional occlusal units (OR = 0.900, 95% CI = 0.813-0.996, p = 0.042) were associated with lower odds of cognitive impairment. When we analyzed these relationships separated by the location of teeth, only the numbers of functional teeth (OR = 0.566, 95% CI = 0.373-0.857, p = 0.007) and functional occlusal units (OR = 0.399, 95% CI = 0.213-0.748, p = 0.004) in the premolar area were associated with lower odds of cognitive impairment. CONCLUSION: Loss of functional teeth and functional occlusal units (especially in the premolar region) were associated with increased cognitive impairment.

Metabolic Profiles Help Discriminate Mild Cognitive Impairment from Dementia Stage in Alzheimer's Disease. - Jääskeläinen, Olli; Hall, Anette; Tiainen, Mika; van Gils, Mark; Lötjönen, Jyrki; Kangas, Antti J; Helisalmi, Seppo; Pikkarainen, Maria; Hallikainen, Merja; Koivisto, Anne; Hartikainen, Päivi; Hiltunen, Mikko; et al. (J Alzheimers Dis, 2020)
Accurate differentiation between neurodegenerative diseases is developing quickly and has reached an effective level in disease recognition. However, there has been less focus on effectively distinguishing the prodromal state from later dementia stages due to a lack of suitable biomarkers. We utilized the Disease State Index (DSI) machine learning classifier to see how well quantified metabolomics data compares to clinically used cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD). The metabolic profiles were quantified for 498 serum and CSF samples using proton nuclear magnetic resonance spectroscopy. The patient cohorts in this study were dementia (with a clinical AD diagnosis) (N = 359), mild cognitive impairment (MCI) (N = 96), and control patients with subjective memory complaints (N = 43). DSI classification was conducted for MCI (N = 51) and dementia (N = 214) patients with low CSF amyloid-β levels indicating AD pathology and controls without such amyloid pathology (N = 36). We saw that the conventional CSF markers of AD were better at classifying controls from both dementia and MCI patients. However, quantified metabolic subclasses were more effective in classifying MCI from dementia. Our results show the consistent effectiveness of traditional CSF biomarkers in AD diagnostics. However, these markers are relatively ineffective in differentiating between MCI and the dementia stage, where the quantified metabolomics data provided significant benefit.

Mitochondrial DNA Manipulations Affect Tau Oligomerization. - Weidling, Ian W; Wilkins, Heather M; Koppel, Scott J; Hutfles, Lewis; Wang, Xiaowan; Kalani, Anuradha; Menta, Blaise W; Ryan, Benjamin; Perez-Ortiz, Judit; Gamblin, T Chris; Swerdlow, Russell H (J Alzheimers Dis, 2020)
BACKGROUND: Mitochondrial dysfunction and tau aggregation occur in Alzheimer's disease (AD), and exposing cells or rodents to mitochondrial toxins alters their tau. OBJECTIVE: To further explore how mitochondria influence tau, we measured tau oligomer levels in human neuronal SH-SY5Y cells with different mitochondrial DNA (mtDNA) manipulations. METHODS: Specifically, we analyzed cells undergoing ethidium bromide-induced acute mtDNA depletion, ρ0 cells with chronic mtDNA depletion, and cytoplasmic hybrid (cybrid) cell lines containing mtDNA from AD subjects. RESULTS: We found cytochrome oxidase activity was particularly sensitive to acute mtDNA depletion, evidence of metabolic re-programming in the ρ0 cells, and a relatively reduced mtDNA content in cybrids generated through AD subject mitochondrial transfer. In each case tau oligomer levels increased, and acutely depleted and AD cybrid cells also showed a monomer to oligomer shift. CONCLUSION: We conclude a cell's mtDNA affects tau oligomerization. Overlapping tau changes across three mtDNA-manipulated models establishes the reproducibility of the phenomenon, and its presence in AD cybrids supports its AD-relevance.

Neuropathologic Correlates of White Matter Hyperintensities in a Community-Based Cohort of Older Adults. - Arfanakis, Konstantinos; Evia, Arnold M; Leurgans, Sue E; Cardoso, Luis F C; Kulkarni, Arman; Alqam, Nabil; Lopes, Lucas F; Vieira, Diego; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2020)
BACKGROUND: The association of white matter hyperintensities (WMH) with age-related vascular and neurodegenerative pathologies remains incompletely understood. OBJECTIVE: The objective of this work was to elucidate the neuropathologic correlates of WMH in a large community-based cohort of older adults. METHODS: Cerebral hemispheres from 603 community-based older adults were imaged with MRI ex vivo. All participants underwent annual clinical evaluation, cognitive assessment, and neuropathologic examination. WMH burden was assessed using a modified Fazekas rating scale. Multiple ordinal logistic regression was used to test the association of WMH burden with an array of age-related neuropathologies, adjusting for demographics. Mixed effects models of cognition controlling for neuropathologies and demographics were used to determine whether WMH burden contributes to cognitive decline beyond measured pathologies. RESULTS: WMH burden in the whole group was associated with both vascular and Alzheimer's disease (AD) pathologies: arteriolosclerosis (p < 10-4), gross (p < 10-4), and microscopic infarcts (p = 0.04), and amyloid-β plaques (p = 0.028). In non-demented participants (mild or no cognitive impairment) (N = 332), WMH burden was related to gross infarcts (p = 10-4) and arteriolosclerosis (p < 10-4), but not to AD pathology. Similarly, in those with no cognitive impairment (N = 178), WMH burden was related to gross infarcts (p = 8×10-4) and arteriolosclerosis (p = 0.014). WMH burden was associated with faster decline in perceptual speed in both the whole (p = 0.038) and non-demented (p = 0.006) groups. CONCLUSION: WMH burden has independent associations with vascular pathologies in older adults regardless of clinical status, and with AD pathology later in the progression of AD. Moreover, WMH burden may reflect additional tissue injury not captured with traditional neuropathologic indices.

A New Serum Biomarker Set to Detect Mild Cognitive Impairment and Alzheimer's Disease by Peptidome Technology. - Abe, Koji; Shang, Jingwei; Shi, Xiaowen; Yamashita, Toru; Hishikawa, Nozomi; Takemoto, Mami; Morihara, Ryuta; Nakano, Yumiko; Ohta, Yasuyuki; Deguchi, Kentaro; Ikeda, Masaki; Ikeda, Yoshio; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Because dementia is an emerging problem in the world, biochemical markers of cerebrospinal fluid (CSF) and radio-isotopic analyses are helpful for diagnosing Alzheimer's disease (AD). Although blood sample is more feasible and plausible than CSF or radiological biomarkers for screening potential AD, measurements of serum amyloid- β (Aβ), plasma tau, and serum antibodies for Aβ1 - 42 are not yet well established. OBJECTIVE: We aimed to identify a new serum biomarker to detect mild cognitive impairment (MCI) and AD in comparison to cognitively healthy control by a new peptidome technology. METHODS: With only 1.5μl of serum, we examined a new target plate "BLOTCHIP®" plus a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) to discriminate control (n = 100), MCI (n = 60), and AD (n = 99). In some subjects, cognitive Mini-Mental State Examination (MMSE) were compared to positron emission tomography (PET) with Pittsburgh compound B (PiB) and the serum probability of dementia (SPD). The mother proteins of candidate serum peptides were examined in autopsied AD brains. RESULTS: Apart from Aβ or tau, the present study discovered a new diagnostic 4-peptides-set biomarker for discriminating control, MCI, and AD with 87% of sensitivity and 65% of specificity between control and AD (***p < 0.001). MMSE score was well correlated to brain Aβ deposition and to SPD of AD. The mother proteins of the four peptides were upregulated for coagulation, complement, and plasticity (three proteins), and was downregulated for anti-inflammation (one protein) in AD brains. CONCLUSION: The present serum biomarker set provides a new, rapid, non-invasive, highly quantitative and low-cost clinical application for dementia screening, and also suggests an alternative pathomechanism of AD for neuroinflammation and neurovascular unit damage.

Oxidized Products of Omega-6 and Omega-3 Long Chain Fatty Acids Are Associated with Increased White Matter Hyperintensity and Poorer Executive Function Performance in a Cohort of Cognitively Normal Hypertensive Older Adults. - Shinto, Lynne; Lahna, David; Murchison, Charles F; Dodge, Hiroko; Hagen, Kirsten; David, Jason; Kaye, Jeffrey; Quinn, Joseph F; Wall, Rachel; Silbert, Lisa C (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease is a common cause of dementia in older adults, and potentially preventable with early intervention. Oxylipins are produced from the oxidation of long-chain polyunsaturated fatty acids (PUFA) possessing potent vascular effects. Oxylipins generated from the cytochrome P450 pathway are enzymatically converted to diols by soluble epoxide hydrolase (sEH); sEH products have been associated with small vessel ischemic disease. Little is known about oxylipins' impact on markers of dementia risk. OBJECTIVE: An exploratory examination of the association between omega-6 and omega-3 derived oxylipins, brain MRI, and cognition. METHODS: Thirty-seven non-demented participants with controlled hypertension (mean age 65.6 years) were enrolled in a dementia prevention study investigating fish oil and lipoic acid on preserving cognitive function. Baseline associations between plasma oxylipins, white matter hyperintensity (WMH), and Trails-B were examined using linear regression. P450-derived diol/epoxide ratio was an indirect measure of sEH activity. RESULTS: Omega-6 derived 9-HODE was associated with increased WMH (p = 0.017) and reduced grey matter volume (p = 0.02). Omega-6 P450-derived diol/epoxide ratio 9,10-DiHOME/9,10-EpOME was associated with increased WMH (p = 0.035) and poorer performance on Trails-B (p = 0.05); ratio14,15-DHET/14,15-EET was associated with increased WMH (p = 0.045). Omega-3 P450-derived diol/epoxide ratio 19,20-DiHDPE/19,20-EpDPE was associated with increased WMH (p = 0.04) and poorer performance on Trails-B (p = 0.04). Arachidonic acid was associated with better performance on Trails-B (p = 0.012); Omega-3 derived 16,17-EpDPE was associated with decreased WMH (p = 0.005). CONCLUSIONS: With the exception of arachidonic acid, it was specific oxylipin products, not their parent PUFAs, that were associated with unfavorable and favorable MRI and cognitive markers of dementia risk.

Is the p3 Peptide (Aβ17-40, Aβ17-42) Relevant to the Pathology of Alzheimer's Disease?1. - Kuhn, Ariel J; Raskatov, Jevgenij (J Alzheimers Dis, 2020)
Despite the vast heterogeneity of amyloid plaques isolated from the brains of those with Alzheimer's Disease (AD), the basis of the Amyloid Cascade Hypothesis targets a single peptide, the amyloid-β (Aβ) peptide. The countless therapeutic efforts targeting the production and aggregation of this specific peptide have been met with disappointment, leaving many to question the role of Aβ in AD. An alternative cleavage product of the Amyloid-β protein precursor, called the p3 peptide, which has also been isolated from the brains of AD patients, has been largely absent from most Aβ-related studies. Typically referred to as non-amyloidogenic and even suggested as neuroprotective, the p3 peptide has garnered little attention aside from some conflicting findings on cytotoxicity and potential self-assembly to form higher order aggregates. Herein, we report an extensive analysis of the findings surrounding p3 and offer some evidence as to why it may not be as innocuous as previously suggested.

Partial Inhibition of Mitochondrial Complex I Reduces Tau Pathology and Improves Energy Homeostasis and Synaptic Function in 3xTg-AD Mice. - Stojakovic, Andrea; Chang, Su-Youne; Nesbitt, Jarred; Pichurin, Nicholas P; Ostroot, Mark A; Aikawa, Tomonori; Kanekiyo, Takahisa; Trushina, Eugenia (J Alzheimers Dis, 2020)
BACKGROUND: Accumulation of hyperphosphorylated tau (pTau) protein is associated with synaptic dysfunction in Alzheimer's disease (AD). We previously demonstrated that neuroprotection in familial mouse models of AD could be achieved by targeting mitochondria complex I (MCI) and activating the adaptive stress response. Efficacy of this strategy on pTau-related pathology remained unknown. OBJECTIVE: To investigate the effect of specific MCI inhibitor tricyclic pyrone compound CP2 on levels of human pTau, memory function, long term potentiation (LTP), and energy homeostasis in 18-month-old 3xTg-AD mice and explore the potential mechanisms. METHODS: CP2 was administered to male and female 3xTg-AD mice from 3.5-18 months of age. Cognitive function was assessed using the Morris water maze. Glucose metabolism was measured in periphery using a glucose tolerance test and in the brain using fluorodeoxyglucose F18 positron-emission tomography (FDG-PET). LTP was evaluated using electrophysiology in the hippocampus. The expression of key proteins associated with neuroprotective mechanisms were assessed by western blotting. RESULTS: Chronic CP2 treatment restored synaptic activity in female 3xTg-AD mice; cognitive function, levels of synaptic proteins, glucose metabolism, and energy homeostasis were improved in male and female 3xTg-AD mice. Significant reduction of human pTau in the brain was associated with increased activity of protein phosphatase of type 2A (PP2A), and reduced activity of cyclin-dependent kinase 5 (CDK5) and glycogen synthase kinase 3β (GSK3β). CONCLUSION: CP2 treatment protected against synaptic dysfunction and memory impairment in symptomatic 3xTg-AD mice, and reduced levels of human pTau, indicating that targeting mitochondria with small molecule specific MCI inhibitors represents a promising strategy for treating AD.

Potential for Digital Monitoring to Enhance Wellbeing at Home for People with Mild Dementia and Their Family Carers. - Fowler-Davis, Sally; Barnett, Deborah; Kelley, John; Curtis, David (J Alzheimers Dis, 2020)
Digital technologies have the potential to assist people with dementia to monitor day to day activities and mitigate the risks of living independently. This purposive pilot study surveyed participants for frailty, wellbeing, and perceived carer burden using the 3Rings™ digital plug. 30 paired participants used the digital device for four months. People with dementia reported a decline in wellbeing and increased frailty. Family carers reported a decline in wellbeing but 18 reported a reduction in burden. The use of digital monitoring by family carers demonstrated a reduction in their perceived burden and the device was acceptable to people with mild dementia living alone.

Quantitative Mass Spectrometric Assay of Whole and CNBr-Cleaved Amyloid-β Peptides in Human Brain. - Furman, Ran; Ng, Sharon C W; Komatsu, Hiroaki; Axelsen, Paul H (J Alzheimers Dis, 2020)
Various amyloid-β (Aβ) peptides accumulate in brain in Alzheimer's disease, and the amounts of specific peptide variants may have pathological significance. The quantitative determination of these variants is challenging because losses inevitably occur during tissue processing and analysis. This report describes the use of stable-isotope-labeled Aβ peptides as internal standards for quantitative mass spectrometric assays, and the use of cyanogen bromide (CNBr) to remove C-terminal residues beyond Met35. The removal of residues beyond Met35 reduces losses due to aggregation, and facilitates the detection of post-translationally modified Aβ peptides. Results from 8 human brain samples suggest that the tissue concentrations of the 42-residue Aβ peptide tend to be similar in different patients. Concentrations of the 40-residue Aβ peptide are more variable, and may be greater or lesser than the 42-residue peptide. The concentration of the CNBr cleavage product closely matches the sum of the 40-residue and 42-residue peptide concentrations, indicating that these two Aβ peptides account for most of the C-terminal variants in these patients. CNBr treatment facilitated the detection of post-translational modifications such as pyroglutamyl and hexose-modified Aβ peptides.

Revised Framingham Stroke Risk Profile: Association with Cognitive Status and MRI-Derived Volumetric Measures. - Pelcher, Isabelle; Puzo, Christian; Tripodis, Yorghos; Aparicio, Hugo J; Steinberg, Eric G; Phelps, Alyssa; Martin, Brett; Palmisano, Joseph N; Vassey, Elizabeth; Lindbergh, Cutter; McKee, Ann C; Stein, Thor D; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The Framingham Stroke Risk Profile (FSRP) was created in 1991 to estimate 10-year risk of stroke. It was revised in 2017 (rFSRP) to reflect the modern data on vascular risk factors and stroke risk. OBJECTIVE: This study examined the association between the rFSRP and cognitive and brain aging outcomes among participants from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS). METHODS: Cross-sectional rFSRP was computed at baseline for 19,309 participants (mean age = 72.84, SD = 8.48) from the NACC-UDS [9,697 (50.2%) normal cognition, 4,705 (24.4%) MCI, 4,907 (25.4%) dementia]. Multivariable linear, logistic, or ordinal regressions examined the association between the rFSRP and diagnostic status, neuropsychological test performance, CDR® Sum of Boxes, as well as total brain volume (TBV), hippocampal volume (HCV), and log-transformed white matter hyperintensities (WMH) for an MRI subset (n = 1,196). Models controlled for age, sex, education, racial identity, APOEɛ4 status, and estimated intracranial volume for MRI models. RESULTS: The mean rFSRP probability was 10.42% (min = 0.50%, max = 95.71%). Higher rFSRP scores corresponded to greater CDR Sum of Boxes (β= 0.02, p = 0.028) and worse performance on: Trail Making Test A (β= 0.05, p <  0.001) and B (β= 0.057, p <  0.001), and Digit Symbol (β= -0.058, p <  0.001). Higher rFSRP scores were associated with increased odds for a greater volume of log-transformed WMH (OR = 1.02 per quartile, p = 0.015). No associations were observed for diagnosis, episodic memory or language test scores, HCV, or TBV. CONCLUSION: These results support the rFSRP as a useful metric to facilitate clinical research on the associations between cerebrovascular disease and cognitive and brain aging.

Specific Neuropsychiatric Symptoms Are Associated with Faster Progression in Alzheimer's Disease: Results of the Prospective Dementia Registry (PRODEM-Austria). - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Dal-Bianco, Peter; Ransmayr, Gerhard; Benke, Thomas; Mosbacher, Jochen; Höller, Yvonne; Schmidt, Reinhold (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms (NPS) occur frequently in the course of Alzheimer's disease (AD) and are suspected to be associated with a faster dementia progression. Numerous reports have defined specific subsyndromes, summarized in clusters of items of the Neuropsychiatric Inventory (NPI). OBJECTIVE: This study investigated the influence of specific NPI subsyndromes and clinical patient characteristics on dementia progression. METHODS: Data of the prospective registry on dementia in Austria (PRODEM) were retrospectively analyzed. Cognitive functioning was determined at baseline and 2 yearly follow-up visits using the Mini-Mental State Examination (MMSE) and the Consortium to Establish a Registry for Alzheimer's dementia neuropsychological test battery (CERAD). To assess NPS, the NPI was used: NPI items were classified in three subsyndromes (psychotic cluster, behavioral cluster, emotional cluster). RESULTS: Out of the 662 included patients (mean age 76.4±8.4 years), 43% completed follow-up visits for two years. Significant correlation between higher scores in all three subsyndromes and worse cognitive performance were found for MMSE score, naming, and verbal fluency. Results of linear mixed model analysis revealed lower age and higher scores in the psychotic cluster as significant predictors of changes in MMSE with time. CONCLUSION: In this study, we report the influence of psychotic subsyndromes and lower age on faster MMSE decline in early AD. These results emphasize the importance of not only assessing but also differentiating neuropsychiatric symptoms in subsyndromes in the early stages of AD as a possible predictor of disease progression.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Supplementation with Matured Hop Bitter Acids Improves Cognitive Performance and Mood State in Healthy Older Adults with Subjective Cognitive Decline. - Fukuda, Takafumi; Ohnuma, Tohru; Obara, Kuniaki; Kondo, Sumio; Arai, Heii; Ano, Yasuhisa (J Alzheimers Dis, 2020)
BACKGROUND: Prevention of age-related cognitive decline and depression is becoming urgent because of rapid growing aging populations. Effects of vagal nerve activation on brain function by food ingredients are inadequately investigated; matured hop bitter acid (MHBA) administration reportedly improves cognitive function and depression via vagal nerve activation in model mice. OBJECTIVE: We investigated the effects of MHBA supplementation on cognitive function and mood state in healthy older adults with perceived subjective cognitive decline. METHODS: Using a randomized double-blind placebo-controlled trial design, 100 subjects (aged 45-69 years) were randomly assigned into placebo (n = 50) and MHBA (n = 50) groups, and received placebo or MHBA capsules daily for 12 weeks. RESULTS: Symbol Digit Modalities Test (SDMT) score assessing divided attention at week 12 was significantly higher (p = 0.045) and β-endorphin at week 12 was significantly lower (p = 0.043) in the subjects receiving MHBA. Transthyretin in serum, a putative mild cognitive impairment marker, was significantly higher at week 12 in the MHBA group than in the placebo group (p = 0.048). Subgroup analysis classified by the subjective cognitive decline questionnaire revealed that in addition to improved SDMT scores, memory retrieval assessed using the standard verbal paired-associate learning tests and the Ray Verbal Learning Test at week 12 had significantly improved in the subgroup with perceived subjective cognitive decline and without requirement for medical assistance in the MHBA group compared with that in the placebo group. CONCLUSION: This study suggested that MHBA intake improves cognitive function, attention, and mood state in older adults.

Synaptic Vesicle Protein 2B Negatively Regulates the Amyloidogenic Processing of AβPP as a Novel Interaction Partner of BACE1. - Miyamoto, Masakazu; Kuzuya, Akira; Noda, Yasuha; Ueda, Sakiho; Asada-Utsugi, Megumi; Ito, Shinji; Fukusumi, Yoshiyasu; Kawachi, Hiroshi; Takahashi, Ryosuke; Kinoshita, Ayae (J Alzheimers Dis, 2020)
BACKGROUND: Given that amyloid-β (Aβ) peptide is produced and released at synapses, synaptic Aβ is one of the promising therapeutic targets to prevent synaptic dysfunction in Alzheimer's disease (AD). Although Aβ production begins with the cleavage of the amyloid-β protein precursor (AβPP) by β-site AβPP cleaving enzyme 1 (BACE1), the mechanism on how BACE1 is involved in AβPP processing at synapses remains unclear. OBJECTIVE: This study aimed to identify novel BACE1 interacting proteins regulating Aβ production at the synapse. METHODS: BACE1 interacting proteins were pulled down using a mass spectrometry-based proteomics of wild-type (WT) rat brain synaptoneurosome lysates utilizing anti-BACE1 antibody. Then, a novel BACE1 interactor was identified and characterized using experimental systems that utilized transfected cells and knockout (KO) mice. RESULTS: Synaptic vesicle protein 2B (SV2B) was identified as a novel presynaptic interaction partner of BACE1. In HEK293 cells, co-overexpression of SV2B with BACE1 significantly reduced the sAβPPβ and Aβ levels released in the media; thus, SV2B overexpression negatively affected the AβPP cleavage by BACE1. Compared with those of WT mice, the hippocampal lysates of SV2B knockout mice had significantly elevated Aβ levels, whereas the β-secretase activity and the AβPP and BACE1 protein levels remained unchanged. Finally, a fractionation assay revealed that BACE1 was mislocalized in SV2B KO mice; hence, SV2B may be involved in BACE1 trafficking downregulating the amyloidogenic pathway of AβPP. CONCLUSION: SV2B has a novel role of negatively regulating the amyloidogenic processing of AβPP at the presynapses.

Utility of MemTrax and Machine Learning Modeling in Classification of Mild Cognitive Impairment. - Bergeron, Michael F; Landset, Sara; Zhou, Xianbo; Ding, Tao; Khoshgoftaar, Taghi M; Zhao, Feng; Du, Bo; Chen, Xinjie; Wang, Xuan; Zhong, Lianmei; Liu, Xiaolei; Ashford, J Wesson (J Alzheimers Dis, 2020)
BACKGROUND: The widespread incidence and prevalence of Alzheimer's disease and mild cognitive impairment (MCI) has prompted an urgent call for research to validate early detection cognitive screening and assessment. OBJECTIVE: Our primary research aim was to determine if selected MemTrax performance metrics and relevant demographics and health profile characteristics can be effectively utilized in predictive models developed with machine learning to classify cognitive health (normal versus MCI), as would be indicated by the Montreal Cognitive Assessment (MoCA). METHODS: We conducted a cross-sectional study on 259 neurology, memory clinic, and internal medicine adult patients recruited from two hospitals in China. Each patient was given the Chinese-language MoCA and self-administered the continuous recognition MemTrax online episodic memory test on the same day. Predictive classification models were built using machine learning with 10-fold cross validation, and model performance was measured using Area Under the Receiver Operating Characteristic Curve (AUC). Models were built using two MemTrax performance metrics (percent correct, response time), along with the eight common demographic and personal history features. RESULTS: Comparing the learners across selected combinations of MoCA scores and thresholds, Naïve Bayes was generally the top-performing learner with an overall classification performance of 0.9093. Further, among the top three learners, MemTrax-based classification performance overall was superior using just the top-ranked four features (0.9119) compared to using all 10 common features (0.8999). CONCLUSION: MemTrax performance can be effectively utilized in a machine learning classification predictive model screening application for detecting early stage cognitive impairment.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Waist Circumference and Domain-Specific Cognitive Function Among Non-Demented Japanese Older Adults Stratified by Sex: Results from the Takashima Cognition Study. - Waki, Takashi; Tanaka-Mizuno, Sachiko; Takashima, Naoyuki; Takechi, Hajime; Hayakawa, Takehito; Miura, Katsuyuki; Ueshima, Hirotsugu; Kita, Yoshikuni; Dodge, Hiroko H (J Alzheimers Dis, 2020)
BACKGROUND: While being obese in mid-life is associated with an increased risk of dementia and cognitive decline in late-life, being obese in late-life is shown to be associated with a lower risk of these outcomes in some studies. This phenomenon is known as the "obesity paradox", but the underlying reasons and potential sex difference have not been well understood. OBJECTIVE: To investigate the association between cognition and waist circumference (WC), an alternative measure of body fat which can be measured easier than body mass index (BMI), among older adults in each generation of late-life for men and women separately. METHODS: Three hundred thirty-five participants were used in the current study who were identified by random sampling of residents aged 65-74, 75-84, and 85 + years in Takashima County, Shiga Prefecture, Japan during 2005-2006. Associations between WC and domain-specific cognitive functions measured by 12 neuropsychological tests were examined using multivariable linear regression models with covariates: age, education, and hypertension. RESULTS: Larger WC was associated with better attention/working memory among 65-74-year old women and with better learning/acquisition among 65-74-year-old men, while larger WC was associated with worse learning/acquisition, memory, attention/working memory, and language/fluency among 75-84-year old men. CONCLUSION: We found age and sex differences in the association between WC and domain-specific cognitive functions. Among older old men (age 75-84) larger WC had negative effects on various domains including memory, attention, language, and executive functions, while we did not find any negative effects of larger WC on cognition among women in any age groups.

18F-FDG Is a Superior Indicator of Cognitive Performance Compared to 18F-Florbetapir in Alzheimer's Disease and Mild Cognitive Impairment Evaluation: A Global Quantitative Analysis. - Khosravi, Mohsen; Peter, Jonah; Wintering, Nancy A; Serruya, Mijail; Shamchi, Sara Pourhassan; Werner, Thomas J; Alavi, Abass; Newberg, Andrew B (J Alzheimers Dis, 2019)
BACKGROUND: 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and 18F-florbetapir PET are approved neuroimaging biomarkers for the Alzheimer's disease (AD) and mild cognitive impairment (MCI). OBJECTIVES: This study aims to compare the efficacy of 18F-FDG and 18F-florbetapir PET at evaluating the cognitive performance of patients with AD, MCI, and normal controls (NCs). METHODS: 63 subjects (36 male/27 female, mean age = 68.3) including 19 AD, 23 MCI, and 21 NCs underwent 18F-FDG and 18F-florbetapir PET imaging. A global quantification approach was applied on supra-tentorial, frontal, parieto-occipital, temporal, and cerebellar brain regions by calculating the global SUVmean ratios (GSUVr) as the weighted average of all regional SUVmean. 18F-FDG and 18F-florbetapir GSUVr of each region were subsequently correlated with the Mini-Mental Status Examination (MMSE). RESULTS: Subjects were studied in five categories as NC, MCI patients, AD patients, MCI and AD patients grouped together (MCI/AD), and a group including all the subjects (NC/MCI/AD). Both 18F-FDG and 18F-florbetapir could successfully detect subjects with dementia (p <  0.001). Studied in all regions and groups, the correlation analysis of 18F-FDG GSUVr with MMSE scores was significant in more regions and groups compared to that of 18F-florbetapir. We also demonstrated that the correlation of 18F-FDG GSUVr with MMSE is stronger than that of 18F-florbetapir in the supra-tentorial and temporal regions. CONCLUSIONS: This study reveals how 18F-FDG-PET global quantification is a superior indicator of cognitive performance in AD and MCI patients compared to 18F-florbetapir PET. Accordingly, we still recommend 18F-FDG-PET over amyloid imaging in the evaluation for AD and MCI.

Anemia in Association with Cognitive Impairment: A Systematic Review and Meta-Analysis. - Kim, Hong-Bae; Park, Byoungjin; Shim, Jae-Yong (J Alzheimers Dis, 2019)
BACKGROUND: Prevalence of both anemia and cognitive impairment tends to increase with age. Individual studies have recently shown that anemia could be associated with cognitive impairment. OBJECTIVE: To investigate the association between anemia and cognitive impairment including dementia. METHODS: Two of the authors systematically searched PubMed, EMBASE, and the Cochrane library to retrieve observational studies reporting a relationship between anemia and cognitive impairment from 1964 to July 10, 2019. Case-control and cohort studies were included, and odds ratios (ORs) or relative risks (RRs) with 95% confidence intervals (CIs) for the risk of cognitive impairment were calculated using a random-effects model. RESULTS: In total, 16 observational studies including eight case-control studies and eight cohort studies were included in the final analysis. Anemia was significantly linked to cognitive impairment (OR or RR 1.51; 95% CI: 1.32-1.73) in a random-effects meta-analysis, albeit with medium heterogeneity (I2 = 47.8%). Meta-estimates of dementia from prospective population-based cohort studies were similar (RR 1.46; 95% CI: 1.22-1.76) without substantial heterogeneity (I2 = 23.2%). CONCLUSION: Our meta-analysis indicates that anemia is associated with cognitive impairment. Further prospective research is warranted to determine the cause-effect relationship of anemia with cognitive impairment and whether treatment of anemia might reduce the risk of dementia.

Antiepileptic Drug Use Is Associated with an Increased Risk of Pneumonia Among Community-Dwelling Persons with Alzheimer's Disease-Matched Cohort Study. - Taipale, Heidi; Lampela, Pasi; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Hartikainen, Sirpa; Tolppanen, Anna-Maija (J Alzheimers Dis, 2019)
BACKGROUND: Antiepileptic drugs (AEDs) have sedative properties which may lead to an increased risk of pneumonia. OBJECTIVES: To investigate whether incident AED use is associated with an increased risk of pneumonia among community-dwelling persons with Alzheimer's disease (AD). In addition, we determined the risk according to duration of AED use and specific AEDs. METHODS: Persons with AD were identified from the MEDALZ dataset which includes all community-dwelling persons who received a clinically verified diagnosis of AD during 2005-2011 in Finland (N=70,718). New AED users were identified with one-year washout period. A matched cohort (1 : 1, N=5,769, matching criteria age, gender, and time since AD diagnoses) of nonusers was formed. Data from nationwide registers included dispensed medications which were modelled with PRE2DUP method, hospitalizations, and causes of death. The association between AED use and hospital admission or death due to pneumonia was analyzed with Cox proportional hazard models. RESULTS: AED use was associated with an increased risk of pneumonia (adjusted HR 1.92, 95% CI 1.63-2.26; incidence rate per 100 person-years 12.58, 95% CI 12.49-12.66 during AED use and 6.41, 95% CI 6.37-6.45 during nonuse). The highest risk was observed during the first month of use (aHR 3.59, 95% CI 2.29-5.61) and the risk remained elevated until two years of use. Of specific drug substances, phenytoin, carbamazepine, valproic acid, and pregabalin were associated with an increased risk. CONCLUSION: Antiepileptic drug use may increase the risk of pneumonia which is concerning as persons with AD have elevated risk of pneumonia.

APOE ɛ4 Carriers Show Delayed Recovery of Verbal Memory and Smaller Entorhinal Volume in the First Year After Ischemic Stroke. - Werden, Emilio; Khlif, Mohamed Salah; Bird, Laura J; Cumming, Toby; Bradshaw, Jennifer; Khan, Wasim; Pase, Matthew; Restrepo, Carolina; Veldsman, Michele; Egorova, Natalia; Patel, Sheila K; Gottlieb, Elie; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The apolipoprotein E (APOE) gene ɛ4 allele is a risk factor for Alzheimer's disease and cardiovascular disease. However, its relationship with cognition and brain volume after stroke is not clear. OBJECTIVE: We compared cognition and medial temporal lobe volumes in APOEɛ4 carriers and non-carriers in the first year after ischemic stroke. METHODS: We sampled 20 APOEɛ4 carriers and 20 non-carriers from a larger cohort of 135 ischemic stroke participants in the longitudinal CANVAS study. Participants were matched on a range of demographic and stroke characteristics. We used linear mixed-effect models to compare cognitive domain z-scores (attention, processing speed, executive function, verbal and visual memory, language, visuospatial function) and regional medial temporal lobe volumes (hippocampal, entorhinal cortex) between groups at each time-point (three, 12-months post-stroke), and within groups across time-points. APOE gene single nucleotide polymorphisms (SNPs; rs7412, rs429358) were genotyped on venous blood. RESULTS: APOEɛ4 carriers and non-carriers did not differ on any demographic, clinical, or stroke variable. Carriers performed worse than non-carriers in verbal memory at three months post-stroke (p = 0.046), but were better in executive function at 12 months (p = 0.035). Carriers demonstrated a significant improvement in verbal memory (p = 0.012) and executive function (p = 0.015) between time-points. Non-carriers demonstrated a significant improvement in visual memory (p = 0.0005). Carriers had smaller bilateral entorhinal cortex volumes (p <  0.05), and larger-right-sided and contralesional hippocampal volumes, at both time-points (p <  0.05). CONCLUSION: APOE ɛ4 is associated with delayed recovery of verbal memory function and reduced entorhinal cortex volumes in the first year after ischemic stroke.

The Association between Mushroom Consumption and Mild Cognitive Impairment: A Community-Based Cross-Sectional Study in Singapore. - Feng, Lei; Cheah, Irwin Kee-Mun; Ng, Maisie Mei-Xi; Li, Jialiang; Chan, Sue Mei; Lim, Su Lin; Mahendran, Rathi; Kua, Ee-Heok; Halliwell, Barry (J Alzheimers Dis, 2019)
We examined the cross-sectional association between mushroom intake and mild cognitive impairment (MCI) using data from 663 participants aged 60 and above from the Diet and Healthy Aging (DaHA) study in Singapore. Compared with participants who consumed mushrooms less than once per week, participants who consumed mushrooms >2 portions per week had reduced odds of having MCI (odds ratio = 0.43, 95% CI 0.23-0.78, p = 0.006) and this association was independent of age, gender, education, cigarette smoking, alcohol consumption, hypertension, diabetes, heart disease, stroke, physical activities, and social activities. Our cross-sectional data support the potential role of mushrooms and their bioactive compounds in delaying neurodegeneration.

CD14 and Toll-Like Receptor 4 Promote Fibrillar Aβ42 Uptake by Microglia Through A Clathrin-Mediated Pathway. - Fujikura, Mai; Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Manabe, Tatsuo; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2019)
We previously demonstrated that microglia play an essential role in clearance of amyloid-β (Aβ) in Alzheimer's disease (AD)-like pathology. Our prior work also showed that several receptors expressed on microglia participated in Aβ phagocytosis. However, clathrin-mediated endocytosis (CME), which is associated with production and release of Aβ in neurons, has received much less attention in the context of microglial Aβ uptake. To elucidate the detailed mechanisms of microglial Aβ uptake pathways, we focused on CD14 and Toll-like receptor 4 (TLR4), which have been shown to mediate fibrillar Aβ1 - 42 (fAβ42) phagocytosis in microglia. CD14 has also been known to control lipopolysaccharide-induced internalization of TLR4 in a clathrin-dependent manner. However, it remains unclear whether CD14 and TLR4 engage in CME in microglial fAβ42 uptake, including whether CD14 interacts with TLR4 in the process. In the present study, we found that CD14-positive microglia increased in an age-dependent manner in the cortex of AD model mice. Immunostaining showed that CD14 interacted with TLR4 to internalize fAβ42 in the mouse microglial cell line MG6. Knock-down of CD14 and TLR4 in MG6 cells significantly reduced intracellular fAβ42, showing their involvement in fAβ42 uptake. We also found that clathrin participated in fAβ42 uptake by MG6 cells. Furthermore, CD14 and TLR4 mediated fAβ42 uptake via clathrin-dependent mechanisms. These results indicate that CD14 and TLR4 participate not only in phagocytosis but also in clathrin-dependent fAβ42 internalization in microglia. These findings provide novel molecular understanding of microglial fAβ42 uptake, which could be of therapeutic relevance for AD.

Cerebral Microbleeds Are Associated with Cerebral Hypoperfusion in Patients with Alzheimer's Disease. - Hatada, Yutaka; Hashimoto, Mamoru; Shiraishi, Shinya; Ishikawa, Tomohisa; Fukuhara, Ryuji; Yuki, Seiji; Tanaka, Hibiki; Miyagawa, Yusuke; Kitajima, Mika; Uetani, Hiroyuki; Tsunoda, Naoko; Koyama, Asuka; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Although cerebral microbleeds (CMBs) are commonly observed in patients with Alzheimer's disease (AD), their clinical relevance for AD remains unclear. OBJECTIVE: We investigated the significance of CMBs in AD by examining the relationship between CMBs and cerebral blood flow (CBF) in patients with AD. METHODS: Thirty-four patients (aged 77.9±7.6 years; 17 men) with probable AD and multiple (≥8) CMBs were selected from 394 consecutive patients. For each lobe of the brain, the correlation between the number of CMBs observed on susceptibility-weighted images and the decrease in CBF observed on single-photon emission computed tomography was assessed. RESULTS: The number of microbleeds was significantly correlated with the severity of decrease in the occipital lobe (Spearman's r = 0.531, p <  0.001) and temporal lobe (r = 0.437, p <  0.001) but not in the frontal lobe (r = 0.201, p = 0.101) and parietal lobe (r = 0.178, p = 0.146). These results were unchanged in the partial correlational analysis after controlling the effect of other small vessel disease such as lacunars and white matter hyperintensities. CONCLUSION: Multiple CMBs are associated with cerebral hypoperfusion in AD. The effects of CMBs on CBF differed according to brain location, possibly reflecting different distributions of the underlying cerebral amyloid angiopathy and AD-related histopathology, such as neurofibrillary tangles.

The Clinical Phenotype of Vascular Cognitive Impairment in Patients with Type 2 Diabetes Mellitus. - Groeneveld, Onno N; Moneti, Costanza; Heinen, Rutger; de Bresser, Jeroen; Kuijf, Hugo J; Exalto, Lieza G; Boomsma, Jooske M F; Kappelle, L Jaap; Barkhof, Frederik; Prins, Niels D; Scheltens, Philip; van der Flier, Wiesje M; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes mellitus (T2DM) increases the risk of vascular cognitive impairment (VCI). It is unknown which type of vascular lesions and co-morbid etiologies, in particular Alzheimer's disease pathology, are associated with T2DM in patients with VCI, and how this relates to cognition and prognosis. OBJECTIVE: To compare brain MRI and cerebrospinal fluid (CSF) markers, cognition, and prognosis in patients with possible VCI with and without T2DM. METHODS: We included 851 memory clinic patients with vascular brain injury on MRI (i.e., possible VCI) from a prospective cohort study (T2DM: n = 147, 68.4±7.9 years, 63% men; no T2DM: n = 704, 67.6±8.5 years, 52% men). At baseline, we assessed between-group differences in brain MRI abnormalities, CSF markers of Alzheimer's disease, and cognitive profile. After two years follow-up, we compared occurrence of cognitive decline, stroke, and death. RESULTS: The distribution of clinical diagnoses did not differ between patients with and without T2DM. T2DM patients had more pronounced brain atrophy (total and white matter volume), and more lacunar infarcts, whereas microbleeds were less common (all p <  0.05). CSF amyloid-β levels were similar between the groups. T2DM patients performed worse on working memory (effect size: - 0.17, p = 0.03) than those without, whereas performance on other domains was similar. During follow-up, risk of further cognitive decline was not increased in T2DM.∥Conclusion: In patients with possible VCI, presence of T2DM is related to more pronounced brain atrophy and a higher burden of lacunar infarcts, but T2DM does not have a major impact on cognitive profile or prognosis.∥.

A Comparison of Partial Volume Correction Techniques for Measuring Change in Serial Amyloid PET SUVR. - Schwarz, Christopher G; Gunter, Jeffrey L; Lowe, Val J; Weigand, Stephen; Vemuri, Prashanthi; Senjem, Matthew L; Petersen, Ronald C; Knopman, David S; Jack, Clifford R (J Alzheimers Dis, 2019)
Longitudinal PET studies in aging and Alzheimer's disease populations rely on accurate and precise measurements of change over time from serial PET scans. Various methods for partial volume correction (PVC) are commonly applied to such studies, but existing comparisons and validations of these PVC methods have focused on cross-sectional measurements. Rate of change measurements inherently have smaller magnitudes than cross-sectional measurements, so levels of noise amplification due to PVC must be smaller, and it is necessary to re-evaluate methods in this context. Here we compare the relative precision in longitudinal measurements from serial amyloid PET scans when using geometric transfer matrix (GTM) PVC versus the traditional two-compartment (Meltzer-style), three-compartment (Müller-Gärtner-style), and no-PVC approaches. We used two independent implementations of standardized uptake value ratio (SUVR) measurement and PVC (one in-house pipeline based on SPM12 and ANTs, and one using FreeSurfer 6.0). For each approach, we also tested longitudinal-specific variants. Overall, we found that measurements using GTM PVC had significantly worse relative precision (unexplained within-subject variability ≈4-8%) than those using two-compartment, three-compartment, or no PVC (≈2-4%). Longitudinally-stabilized approaches did not improve these properties. This data suggests that GTM PVC methods may be less suitable than traditional approaches when measuring within-person change over time in longitudinal amyloid PET.

Developing Effective Alzheimer's Disease Therapies: Clinical Experience and Future Directions. - Elmaleh, David R; Farlow, Martin R; Conti, Peter S; Tompkins, Ronald G; Kundakovic, Ljiljana; Tanzi, Rudolph E (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) clinical trials, focused on disease modifying drugs and conducted in patients with mild to moderate AD, as well as prodromal (early) AD, have failed to reach efficacy endpoints in improving cognitive function in most cases to date or have been terminated due to adverse events. Drugs that have reached clinical stage were reviewed using web resources (such as clinicaltrials.gov, alzforum.org, company press releases, and peer reviewed literature) to identify late stage (Phase II and Phase III) efficacy clinical trials and summarize reasons for their failure. For each drug, only the latest clinical trials and ongoing trials that aimed at improving cognitive function were included in the analysis. Here we highlight the potential reasons that have hindered clinical success, including clinical trial design and choice of outcome measures, heterogeneity of patient populations, difficulties in diagnosing and staging the disease, drug design, mechanism of action, and toxicity related to the long-term use. We review and suggest approaches for AD clinical trial design aimed at improving our ability to identify novel therapies for this devastating disease.

Evaluation of Associations of Alzheimer's Disease Risk Variants that Are Highly Expressed in Microglia with Neuropathological Outcome Measures. - Sakae, Nobutaka; Heckman, Michael G; Vargas, Emily R; Carrasquillo, Minerva M; Murray, Melissa E; Kasanuki, Koji; Ertekin-Taner, Nilufer; Younkin, Steven G; Dickson, Dennis W (J Alzheimers Dis, 2019)
A number of Alzheimer's disease (AD) susceptibility loci are expressed abundantly in microglia. We examined associations between AD risk variants in genes that are highly expressed in microglia and neuropathological outcomes, including cerebral amyloid angiopathy (CAA) and microglial activation, in 93 AD patients. We observed significant associations of CAA pathology with APOEɛ4 and PTK2B rs28834970. Nominally significant associations with measures of microglial activation in white matter were observed for variants in PTK2B, PICALM, and CR1. Our findings suggest that several AD risk variants may also function as disease modifiers through amyloid-β metabolism and white matter microglial activity.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

A Fragment of S38AA is a Novel Plasma Biomarker of Alzheimer's Disease. - Hashimoto, Masakazu; Yamazaki, Akira; Ohno, Atsushi; Kimura, Toru; Winblad, Bengt; Tjernberg, Lars O (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease without a cure. The pathological process starts decades before clinical onset, and thus clinical trials of drugs aimed at treating AD should start at a presymptomatic stage. Therefore, it is critical to diagnose AD at an early stage. Tau, phosphorylated tau, and amyloid-β peptide (Aβ) in cerebrospinal fluid (CSF), and positron emission tomography (PET) imaging of Aβ or tau accumulation are supportive biomarkers for AD diagnosis, but there is no reliable presymptomatic diagnostic marker. Since CSF sampling is invasive, and PET imaging is expensive and available only at specialized centers, a reliable blood biomarker has long been sought for. Here we describe a novel extramembrane fragment from solute carrier family 38 member 10 (SLC38A10, S38AA) that we found to be decreased in pyramidal neurons in AD cases by proteomics and immunohistochemical analysis. We detected a S38AA fragment in CSF and found the levels to correlate with severity of AD and APOE genotype. Importantly, the plasma levels of the fragment also showed a significant correlation with Mini-Mental State Examination scores in AD. Moreover, plasma from other neurodegenerative disease was analyzed and the fragment was found to be increased specifically in AD. Interestingly, the fragment is detected in mouse, rat, and monkey, and increases in amyloid precursor protein transgenic mice as the AD-like pathology progresses. We propose that the S38AA fragment in plasma could be a novel quantitative diagnostic marker for AD and potentially a marker of disease progression in AD.

Gender and Educational Differences in the Association between Lifestyle and Cognitive Decline over 10 Years: The Doetinchem Cohort Study. - Deckers, Kay; Nooyens, Astrid; van Boxtel, Martin; Verhey, Frans; Verschuren, Monique; Köhler, Sebastian (J Alzheimers Dis, 2019)
BACKGROUND: Several modifiable risk factors for cognitive decline have been identified, but whether differences by gender and educational level exist is unclear. OBJECTIVE: The present study aims to clarify this by prospectively investigating the relationship between health and lifestyle factors and cognitive functioning in different subgroups defined by gender and educational level. METHODS: 2,347 cognitive healthy individuals (mean age = 54.8, SD = 6.8, range: 41-71; 51.8% female; 26.2% low education) from the Doetinchem Cohort Study were examined for cognitive function at baseline, and at 5- and 10-year follow-up. Health- and lifestyle factors were captured by a poly-environmental risk score labelled 'LIfestyle for BRAin Health' (LIBRA). This score consists of 12 modifiable risk and protective factors for cognitive decline and dementia, with higher scores indicating greater risk (range: -2.7 to +12.7). Heterogeneity in associations between LIBRA and decline in verbal memory, cognitive flexibility, and mental speed between males and females and individuals with different levels of education were assessed in linear mixed models. RESULTS: Overall, higher LIBRA scores predicted faster decline in verbal memory, cognitive flexibility, and mental speed over 10 years. Higher LIBRA scores were further associated with increased risk for incident cognitive impairment (one-point increase in LIBRA: HR = 1.09, 1.04-1.14, p = 0.001). In general, these effects were similar across gender and educational level. CONCLUSION: A composite risk score comprising unhealthy lifestyle and relatively poor health in midlife is significantly associated with a worse course of cognition 10 years later. These associations were for the most part unrelated to gender or educational differences.

Glial Fibrillary Acidic Protein in Serum is Increased in Alzheimer's Disease and Correlates with Cognitive Impairment. - Oeckl, Patrick; Halbgebauer, Steffen; Anderl-Straub, Sarah; Steinacker, Petra; Huss, André M; Neugebauer, Hermann; von Arnim, Christine A F; Diehl-Schmid, Janine; Grimmer, Timo; Kornhuber, Johannes; Lewczuk, Piotr; Danek, Adrian; et al. (J Alzheimers Dis, 2019)
Reliable blood biomarkers for Alzheimer's disease (AD) are missing. We measured astroglial GFAP in patients with AD (n = 28), frontotemporal dementia (bvFTD, n = 35), Parkinson's disease (n = 11), Lewy body dementias (n = 19), and controls (n = 34). Serum GFAP was increased in AD (p < 0.001) and DLB/PDD (p < 0.01), and cerebrospinal fluid GFAP was increased in all neurodegenerative diseases (p < 0.001). Serum GFAP correlated with the Mini-Mental State Examination score (r= -0.42, p < 0.001) and might be a follow-up marker in clinical trials. Sensitivity and specificity of serum GFAP for AD versus bvFTD was 89% and 79% and might be the first blood biomarker in the differential diagnosis of AD and bvFTD.

Identifying Unmet Needs of Family Dementia Caregivers: Results of the Baseline Assessment of a Cluster-Randomized Controlled Intervention Trial. - Zwingmann, Ina; Michalowsky, Bernhard; Esser, Alexander; Kaczynski, Anika; Monsees, Jessica; Keller, Armin; Hertel, Johannes; Wucherer, Diana; Thyrian, Jochen René; Eichler, Tilly; Kilimann, Ingo; Teipel, Stefan; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Caregivers providing informal care for people with dementia (PwD) often report unmet needs, burden, and health impairments. Optimal support for family dementia caregivers will likely benefit from better understanding and assessment of the prevalence and types of caregivers' unmet needs and associated socio-demographic and clinical characteristics. OBJECTIVE: The present study investigates 1) the number and types of caregivers' unmet needs, 2) socio-demographic and clinical characteristics of both PwD and caregivers, and 3) caregivers' burden and health-related outcomes that are related to caregivers' unmet needs. METHODS: The present analyses are based on cross-sectional data of n = 226 dyads of caregivers and their community-dwelling PwD participating in a comprehensive standardized, computer-based caregivers' needs assessment within a general practitioner (GP)-based, cluster-randomized intervention trial. RESULTS: A total of n = 505 unmet needs were identified for n = 171 caregivers from the intervention group at baseline. Only 24.3% caregivers reported no unmet need (n = 55), whereas 75.7% caregivers had at least one unmet need (n = 171). Caregivers had on average 2.19 unmet needs (mean = 2.19, SD = 2.15). Specifically, 53.1% of caregivers had one up to three unmet needs (n = 120), 18.6% (n = 42) had three up to six unmet needs, and 4.0% (n = 9) had more than six unmet needs. DISCUSSION: Our results underline the importance of a comprehensive needs assessment for family dementia caregivers to develop and implement concepts that can provide family dementia caregivers with optimal support.

Improved Differential Diagnosis of Alzheimer's Disease by Integrating ELISA and Mass Spectrometry-Based Cerebrospinal Fluid Biomarkers. - Khoonsari, Payam Emami; Shevchenko, Ganna; Herman, Stephanie; Remnestål, Julia; Giedraitis, Vilmantas; Brundin, RoseMarie; Degerman Gunnarsson, Malin; Kilander, Lena; Zetterberg, Henrik; Nilsson, Peter; Lannfelt, Lars; Ingelsson, Martin; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Alzheimer's disease (AD) is diagnosed based on a clinical evaluation as well as analyses of classical biomarkers: Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in cerebrospinal fluid (CSF). Although the sensitivities and specificities of the classical biomarkers are fairly good for detection of AD, there is still a need to develop novel biochemical markers for early detection of AD. OBJECTIVE: We explored if integration of novel proteins with classical biomarkers in CSF can better discriminate AD from non-AD subjects. METHODS: We applied ELISA, mass spectrometry, and multivariate modeling to investigate classical biomarkers and the CSF proteome in subjects (n = 206) with 76 AD patients, 74 mild cognitive impairment (MCI) patients, 11 frontotemporal dementia (FTD) patients, and 45 non-dementia controls. The MCI patients were followed for 4-9 years and 21 of these converted to AD, whereas 53 remained stable. RESULTS: By combining classical CSF biomarkers with twelve novel markers, the area of the ROC curves (AUROCS) of distinguishing AD and MCI/AD converters from non-AD were 93% and 96%, respectively. The FTDs and non-dementia controls were identified versus all other groups with AUROCS of 96% and 87%, respectively. CONCLUSIONS: Integration of new and classical CSF biomarkers in a model-based approach can improve the identification of AD, FTD, and non-dementia control subjects.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Influx of Tau and Amyloid-β Proteins into the Blood During Hemodialysis as a Therapeutic Extracorporeal Blood Amyloid-β Removal System for Alzheimer's Disease. - Kitaguchi, Nobuya; Tatebe, Harutsugu; Sakai, Kazuyoshi; Kawaguchi, Kazunori; Matsunaga, Shinji; Kitajima, Tomoko; Tomizawa, Hiroshi; Kato, Masao; Sugiyama, Satoshi; Suzuki, Nobuo; Mizuno, Masao; Takechi, Hajime; et al. (J Alzheimers Dis, 2019)
The accumulation of amyloid-β protein (Aβ) and tau in the brain is a major pathological change related to Alzheimer's disease. We have continued to develop Extracorporeal Blood Aβ Removal Systems (E-BARS) as a method for enhancing Aβ clearance from the brain. Our previous report revealed that dialyzers effectively remove blood Aβ and evoke large Aβ influxes into the blood, resulting in a decrease in brain Aβ accumulation after initiating hemodialysis, and that patients who underwent hemodialysis had lower brain Aβ accumulation than those who did not. Here, plasma total tau concentrations from 30 patients undergoing hemodialysis were measured using an ultrasensitive immunoassay and compared to those from 11 age-matched controls. Plasma total tau concentrations were higher in patients with renal failure regardless of whether they underwent hemodialysis, suggesting the involvement of the kidneys in tau degradation and excretion. Hemodialyzers effectively removed blood Aβ but not extracorporeal blood tau. The influx of tau into the blood was observed at around the 1 h period during hemodialysis sessions. However, the influx amount of tau was far smaller than that of Aβ. Furthermore, histopathological analysis revealed similar, not significantly less, cerebral cortex phosphorylated tau accumulation between the 17 patients who underwent hemodialysis and the 16 age-matched subjects who did not, although both groups showed sparse accumulation. These findings suggest that hemodialysis may induce both tau and Aβ migration into the blood. However, as a therapeutic strategy for Alzheimer's disease, it may only be effective for removing Aβ from the brain.

Long-Term Trazodone Use and Cognition: A Potential Therapeutic Role for Slow-Wave Sleep Enhancers. - La, Alice L; Walsh, Christine M; Neylan, Thomas C; Vossel, Keith A; Yaffe, Kristine; Krystal, Andrew D; Miller, Bruce L; Karageorgiou, Elissaios (J Alzheimers Dis, 2019)
BACKGROUND: Recent studies reveal an association between slow-wave sleep (SWS), amyloid-β aggregation, and cognition. OBJECTIVE: This retrospective study examines whether long-term use of trazodone, an SWS enhancer, is associated with delayed cognitive decline. METHODS: We identified 25 regular trazodone users (mean age 75.4±7.5; 9 women, 16 men) who carried a diagnosis of Alzheimer's dementia, mild cognitive impairment, or normal cognition, and 25 propensity-matched trazodone non-users (mean age 74.5±8.0; 13 women, 12 men), accounting for age, sex, education, type of sleep deficit (hypersomnia, insomnia, parasomnia), diagnosis, and baseline Mini-Mental State Examination (MMSE). Longitudinal group differences in cognitive testing were evaluated through repeated measures tests over an average inter-evaluation interval of four years. RESULTS: Trazodone non-users had 2.6-fold faster decline MMSE (primary outcome) compared to trazodone users, 0.27 (95% confidence interval [CI]: 0.07-0.48) versus 0.70 (95% CI: 0.50-0.90) points per year (p = 0.023). The observed effects were especially associated with subjective improvement of sleep complaints in post-hoc analyses (p = 0.0006). Secondary outcomes of other cognitive and functional scores had variable worsening in non-users and varied in significance when accounting for co-administered medications and multiple comparisons. Trazodone effects on MMSE remained significant within participants with AD-predicted pathology, with 2.4-fold faster decline in non-users (p = 0.038). CONCLUSIONS: These results suggest an association between trazodone use and delayed cognitive decline, adding support for a potentially attractive and cost-effective intervention in dementia. Whether the observed relationship of trazodone to cognitive function is causal or an indirect marker of other effects, such as treated sleep disruption, and if such effects are mediated through SWS enhancement requires confirmation through prospective studies.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

The MemTrax Test Compared to the Montreal Cognitive Assessment Estimation of Mild Cognitive Impairment. - van der Hoek, Marjanne D; Nieuwenhuizen, Arie; Keijer, Jaap; Ashford, J Wesson (J Alzheimers Dis, 2019)
Cognitive impairment is a leading cause of dysfunction in the elderly. When mild cognitive impairment (MCI) occurs in elderly, it is frequently a prodromal condition to dementia. The Montreal Cognitive Assessment (MoCA) is a commonly used tool to screen for MCI. However, this test requires a face-to-face administration and is composed of an assortment of questions whose responses are added together by the rater to provide a score whose precise meaning has been controversial. This study was designed to evaluate the performance of a computerized memory test (MemTrax), which is an adaptation of a continuous recognition task, with respect to the MoCA. Two outcome measures are generated from the MemTrax test: MemTraxspeed and MemTraxcorrect. Subjects were administered the MoCA and the MemTrax test. Based on the results of the MoCA, subjects were divided in two groups of cognitive status: normal cognition (n = 45) and MCI (n = 37). Mean MemTrax scores were significantly lower in the MCI than in the normal cognition group. All MemTrax outcome variables were positively associated with the MoCA. Two methods, computing the average MTX score and linear regression were used to estimate the cutoff values of the MemTrax test to detect MCI. These methods showed that for the outcome MemTraxspeed a score below the range of 0.87 - 91 s-1 is an indication of MCI, and for the outcome MemTraxcorrect a score below the range of 85 - 90% is an indication for MCI.

Midlife Insulin Resistance as a Predictor for Late-Life Cognitive Function and Cerebrovascular Lesions. - Toppala, Sini; Ekblad, Laura L; Lötjönen, Jyrki; Helin, Semi; Hurme, Saija; Johansson, Jarkko; Jula, Antti; Karrasch, Mira; Koikkalainen, Juha; Laine, Hanna; Parkkola, Riitta; Viitanen, Matti; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes (T2DM) increases the risk for Alzheimer's disease (AD) but not for AD neuropathology. The association between T2DM and AD is assumed to be mediated through vascular mechanisms. However, insulin resistance (IR), the hallmark of T2DM, has been shown to associate with AD neuropathology and cognitive decline. OBJECTIVE: To evaluate if midlife IR predicts late-life cognitive performance and cerebrovascular lesions (white matter hyperintensities and total vascular burden), and whether cerebrovascular lesions and brain amyloid load are associated with cognitive functioning. METHODS: This exposure-to-control follow-up study examined 60 volunteers without dementia (mean age 70.9 years) with neurocognitive testing, brain 3T-MRI and amyloid-PET imaging. The volunteers were recruited from the Finnish Health 2000 survey (n = 6062) to attend follow-up examinations in 2014-2016 according to their insulin sensitivity in 2000 and their APOE genotype. The exposure group (n = 30) had IR in 2000 and the 30 controls had normal insulin sensitivity. There were 15 APOEɛ4 carriers per group. Statistical analyses were performed with multivariable linear models. RESULTS: At follow-up the IR+group performed worse on executive functions (p = 0.02) and processing speed (p = 0.007) than the IR- group. The groups did not differ in cerebrovascular lesions. No associations were found between cerebrovascular lesions and neurocognitive test scores. Brain amyloid deposition associated with slower processing speed. CONCLUSION: Midlife IR predicted poorer executive functions and slower processing speed, but not cerebrovascular lesions. Brain amyloid deposition was associated with slower processing speed. The association between midlife IR and late-life cognition might not be mediated through cerebrovascular lesions measured here.

Mild Cognitive Impairment and Dementia Involving Multiple Cognitive Domains in Mexican Urbanites. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Kulesza, Randy J; Torres-Jardón, Ricardo; Hernández-Luna, Jacqueline; Ávila-Cervantes, Rodrigo; Macías-Escobedo, Edgar; González-González, Oscar; González-Maciel, Angelica; García-Hernández, Kevin; Hernández-Castillo, Ariatna; Villarreal-Ríos, Rodolfo (J Alzheimers Dis, 2019)
Exposures to fine particulate matter PM2.5 and ozone O3 are associated with Alzheimer's disease (AD) risk. Mexico City residents have lifetime exposures to PM2.5 and O3 above annual USEPA standards and their brains contain high redox, combustion, and friction-derived magnetite nanoparticles. AD pathological changes with subcortical pre-tangle stages in infancy and cortical tau pre-tangles, NFT Stages I-II, and amyloid phases 1-2 are identified by the 2nd decade. Given their AD continuum, a reliable identification of cognitive impairment is of utmost importance. The Montreal Cognitive Assessment (MoCA) was administered to 517 urbanites, age 21.60±5.88 years, with 13.69±1.28 formal education years, in Mexican PM2.5 polluted cities. MoCA score was 23.92±2.82, and 24.7% and 30.3% scored ≤24 and ≤22, respectively (MCI≤24, AD≤22). Cognitive deficits progressively targeted Visuospatial, Executive, Language, and Memory domains, body mass index (BMI) impacting total scores negatively (p = 0.0008), aging driving down Executive, Visuospatial, and Language index scores (p <  0.0001, 0.0037, and 0.0045), and males performing better in Executive tasks. Average age for AD MoCA scores was 22.38±7.7 years. Residency in polluted cities is associated with progression of multi-domain cognitive impairment affecting 55% of Mexican seemingly healthy youth. Normal BMI ought to be a neuroprotection goal. MoCA provides guidance for further mandatory neuropsychological testing in young populations. Identifying and lowering key neurotoxicants impacting neural risk trajectories in the developing brain and monitoring cognitive performance would greatly facilitate multidisciplinary early diagnosis and prevention of AD in high risk young populations. Cognitive deficits hinder development of those representing the force moving the country in future years.

O-GlcNAcylation of Amyloid-β Protein Precursor by Insulin Signaling Reduces Amyloid-β Production. - Kwon, Oh Hoon; Cho, Yoon Young; Kim, Tae-Wan; Chung, Sungkwon (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is caused by the accumulation of neurotoxic amyloid-β (Aβ) peptides. Aβ is derived from amyloid-β protein precursor (AβPP). In the non-amyloidogenic pathway, AβPP is cleaved by α-secretase and γ-secretase at the plasma membrane, excluding Aβ production. Alternatively, AβPP in the plasma membrane is internalized via endocytosis, and delivered to early endosomes and lysosomes, where it is cleaved by β-secretase and γ-secretase. Recent studies have shown that insulin in the periphery crosses the blood-brain barrier, and plays important roles in the brain. Furthermore, impaired insulin signaling has been linked to the progression of AD, and intranasal insulin administration improves memory impairments and cognition. However, the underlying molecular mechanisms of insulin treatment remain largely unknown. To investigate the effects of insulin on AβPP processing, we tested the effects of insulin on neuroblastoma SH-SY5Y cells overexpressing AβPP, and cultured rat cortical neurons. We found that insulin increased the level of cell surface AβPP, decreasing the endocytosis rate of AβPP. Insulin reduced Aβ generation through upregulation of AβPP O-GlcNAcylation via Akt insulin signaling. Our present data suggest that insulin affects Aβ production by regulating AβPP processing through AβPP O-GlcNAcylation. These results provide mechanistic insight into the beneficial effects of insulin, and a possible link between insulin deficient diabetes and cerebral amyloidosis in the pathogenesis of AD.

Ovariectomy Influences Cognition and Markers of Alzheimer's Disease. - Agca, Cansu; Klakotskaia, Diana; Stopa, Edward G; Schachtman, Todd R; Agca, Yuksel (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is one of the most devastating and costly diseases, and prevalence of AD increases with age. Furthermore, females are twice as likely to suffer from AD compared to males. The cessation of reproductive steroid hormone production during menopause is hypothesized to cause this difference. Two rodent AD models, APP21 and APP+PS1, and wild type (WT) rats underwent an ovariectomy or sham surgery. Changes in learning and memory, brain histology, amyloid-β (Aβ) deposition, levels of mRNAs involved in Aβ production and clearance, and synaptic and cognitive function were determined. Barnes maze results showed that regardless of ovariectomy status, APP+PS1 rats learned slower and had poor memory retention. Ovariectomy caused learning impairment only in the APP21 rats. High levels of Aβ42 and very low levels of Aβ40 were observed in the brain cortices of APP+PS1 rats indicating limited endogenous PS1. The APP+PS1 rats had 43-fold greater formic acid soluble Aβ42 than Aβ40 at 17 months. Furthermore, levels of formic acid soluble Aβ42 increased 57-fold in ovariectomized APP+PS1 rats between 12 and 17 months of age. The mRNA encoding Grin1 significantly decreased due to ovariectomy whereas levels of Bace1, Chat, and Prkcb all decreased with age. The expression levels of mRNAs involved in Aβ degradation and AβPP cleavage (Neprilysin, Ide, Adam9, and Psenen) were found to be highly correlated with each other as well as hippocampal Aβ deposition. Taken together, these results indicate that both ovariectomy and genotype influence AD markers in a complex manner.

Porphyromonas gingivalis Infection Induces Amyloid-β Accumulation in Monocytes/Macrophages. - Nie, Ran; Wu, Zhou; Ni, Junjun; Zeng, Fan; Yu, Weixian; Zhang, Yufeng; Kadowaki, Tomoko; Kashiwazaki, Haruhiko; Teeling, Jessica L; Zhou, Yanmin (J Alzheimers Dis, 2019)
Abnormal accumulation of amyloid-β (Aβ) in the brain is the most significant pathological hallmark of Alzheimer's disease (AD). We have found that chronic systemic exposure to lipopolysaccharide of Porphyromonas gingivalis (P. gingivalis) induces the accumulation of Aβ in the brain of middle-aged mice. On the other hand, recent research has shown that circulating Aβ is transferred into the brain; however, the involvement of chronic systemic P. gingivalis infection in the peripheral Aβ metabolism is unknown. We hypothesized that chronic P. gingivalis infection expands Aβ pools in peripheral inflammatory tissues and thereby contributes to the accumulation of Aβ in the brain of patients with periodontitis. We showed that the increased expression of IL-1β, AβPP770, CatB, Aβ1-42, and Aβ3-42 was mainly co-localized with macrophages in the liver of P. gingivalis infected mice. Blocking CatB and NF-κB significantly inhibited the P. gingivalis-induced expression of IL-1β, AβPP770, Aβ1-42, and Aβ3-42 in RAW264.7 cells. Aβ3-42, but not Aβ1-42, induced the significant death of macrophages, and the reduction of phagocytic abilities induced by Aβ3-42 tended to be higher than that induced by Aβ1-42. Additionally, the expression of AβPP770, CatB, Aβ1-42, and Aβ3-42 was determined in the macrophages of gingival tissues from periodontitis patients. These findings indicate that chronic systemic P. gingivalis infection induces the Aβ accumulation in inflammatory monocytes/macrophages via the activation of CatB/NF-κB signaling, thus suggesting monocytes/macrophages serve as a circulating pool of Aβ in patients with periodontitis. Taken together, CatB may be a novel therapeutic target for preventing the periodontitis-related AD initiation and pathological progression.

The Prevalence and Subtypes of Young Onset Dementia in Central Norway: A Population-Based Study. - Kvello-Alme, Marte; Bråthen, Geir; White, Linda R; Sando, Sigrid Botne (J Alzheimers Dis, 2019)
BACKGROUND: Young onset dementia poses several challenges for the individual, health care, and society that are not normally relevant for late onset dementia, but is little researched. OBJECTIVE: To determine the prevalence and subtypes of young onset dementia in a defined catchment area in central Norway. METHODS: The main sources of patient identification were the databases at the Department of Neurology, University Hospital of Trondheim (St. Olav's Hospital), and Department of Psychiatry, Levanger Hospital. Both departments are the main sites for referral of young onset dementia (onset before age 65 years) in the county, covering approximately 90% of the catchment area of the study. Other sources included key persons in the communities, collaborating hospital departments examining dementia, and review of hospital records of all three hospitals in the area. Included patients met the DSM-IV criteria for dementia. The prevalence of dementias was calculated by sex and age. RESULTS: All patients identified with dementia and onset before 65 years on census date were included in the study (n = 390). Patients younger than 65 on census date were included in the calculation of prevalence, giving a result of 76.3 per 100 000 persons at risk in the age category of 30-65 years, and 163.1 per 100,000 for the category 45-64 years. Etiology was heterogeneous, but the main subtype of dementia was Alzheimer's disease. CONCLUSIONS: Young onset dementia affects a significant number of people in central Norway. Prevalence figures are higher than previously reported from England and Japan, but are similar to a more recent study from Australia.

Quantification of Tau Protein Lysine Methylation in Aging and Alzheimer's Disease. - Huseby, Carol J; Hoffman, Claire N; Cooper, Grace L; Cocuron, Jean-Christophe; Alonso, Ana P; Thomas, Stefani N; Yang, Austin J; Kuret, Jeff (J Alzheimers Dis, 2019)
Tau is a microtubule-associated protein that normally interacts in monomeric form with the neuronal cytoskeleton. In Alzheimer's disease, however, it aggregates to form the structural component of neurofibrillary lesions. The transformation is controlled in part by age- and disease-associated post-translational modifications. Recently we reported that tau isolated from cognitively normal human brain was methylated on lysine residues, and that high-stoichiometry methylation depressed tau aggregation propensity in vitro. However, whether methylation stoichiometry reached levels needed to influence aggregation propensity in human brain was unknown. Here we address this problem using liquid chromatography-tandem mass spectrometry approaches and human-derived tau samples. Results revealed that lysine methylation was present in soluble tau isolated from cognitively normal elderly cases at multiple sites that only partially overlapped with the distributions reported for cognitively normal middle aged and AD cohorts, and that the quality of methylation shifted from predominantly dimethyl-lysine to monomethyl-lysine with aging and disease. However, bulk mol methylation/mol tau stoichiometries never exceeded 1 mol methyl group/mol tau protein. We conclude that lysine methylation is a physiological post-translational modification of tau protein that changes qualitatively with aging and disease, and that pharmacological elevation of tau methylation may provide a means for protecting against pathological tau aggregation.

Self and Informant Memory Reports in FINGER: Associations with Two-Year Cognitive Change. - Vaskivuo, Laura; Hokkanen, Laura; Hänninen, Tuomo; Antikainen, Riitta; Bäckman, Lars; Laatikainen, Tiina; Paajanen, Teemu; Stigsdotter-Neely, Anna; Strandberg, Timo; Tuomilehto, Jaakko; Soininen, Hilkka; Kivipelto, Miia; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Subjective memory complaints (SMCs) may be the first sign of cognitive decline in aging. OBJECTIVE: To examine whether SMCs reported by oneself and informant predict cognitive change over 2 years among at-risk elderly people, and to determine the relationship of different types of SMCs (prospective and retrospective memory complaints) and change in cognitive function. METHODS: This investigation is part of the FINGER project, which is a multicenter randomized controlled trial aiming at preventing cognitive decline in cognitively healthy older adults with increased risk of dementia. A subsample of 303 control-group participants (aged 60-80 years) and their informants (n = 261) rated the frequency of SMCs, using the Prospective and Retrospective Memory Questionnaire (PRMQ). Cognitive performance was measured at baseline and at 1- and 2-year follow-up visits using a neuropsychological test battery. RESULTS: Participants who reported more SMCs improved less in global cognition, executive function, and memory during the subsequent 2 years in the fully-adjusted analyses. Self-reported retrospective memory problems predicted less improvement in all cognitive domains, whereas prospective memory problems did not. Informant-reported memory problems were not linked to subsequent change in cognition. CONCLUSION: Our results indicate that self-reported SMCs, measured with PRMQ, predict future cognitive change in several cognitive domains. By contrast, reports by informants were not linked to changes in cognition. Among cognitively healthy at-risk elderly individuals, the persons themselves observe more easily problems relevant for their future cognitive trajectories than their informants.

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling. - Chen, Ci-Di; Zeldich, Ella; Khodr, Christina; Camara, Kaddy; Tung, Tze Yu; Lauder, Emma C; Mullen, Patrick; Polanco, Taryn J; Liu, Yen-Yu; Zeldich, Dean; Xia, Weiming; Van Nostrand, William E; et al. (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a compound library for inhibitors of AβPP dimerization, and identified a compound that reduces Aβ levels. In the present study, we have identified an analog, compound Y10, which also reduced Aβ. Initial kinase profiling assays identified the receptor tyrosine kinase cKit as a putative Y10 target. To elucidate the precise mechanism involved, AβPP phosphorylation was examined by IP-western blotting. We found that Y10 inhibits cKit phosphorylation and increases AβPP phosphorylation mainly on tyrosine residue Y743, according to AβPP751 numbering. A known cKit inhibitor and siRNA specific to cKit were also found to increase AβPP phosphorylation and lower Aβ levels. We also investigated a cKit downstream signaling molecule, the Shp2 phosphatase, and found that known Shp2 inhibitors and siRNA specific to Shp2 also increase AβPP phosphorylation, suggesting that the cKit signaling pathway is also involved in AβPP phosphorylation and Aβ production. We further found that inhibitors of both cKit and Shp2 enhance AβPP surface localization. Thus, regulation of AβPP phosphorylation by small molecules should be considered as a novel therapeutic intervention for AD.

Stem Cell-Derived Neurons as Cellular Models of Sporadic Alzheimer's Disease. - Foveau, Bénédicte; Correia, Ana Sofia; Hébert, Sébastien S; Rainone, Sara; Potvin, Olivier; Kergoat, Marie-Jeanne; Belleville, Sylvie; Duchesne, Simon; LeBlanc, Andréa C (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) occurs as either an autosomal dominant inherited disease or sporadically. While familial mutant genes can be expressed in cells or in animal models to assess dysregulated functions, sporadic AD cannot be replicated in models given our lack of understanding of causality. Furthermore, the study of sporadic forms of AD is difficult given the inaccessibility of brain tissues in living individuals and the manifestation of symptoms years after the onset of disease. Here, the objective was to assess if induced pluripotent stem cell-derived neurons from well-ascertained sporadic AD individuals could represent potential cellular models to determine the underlying molecular mechanisms of disease. We used cryopreserved peripheral blood mononuclear cells from three well-ascertained sporadic AD and three non-cognitively impaired (NCI) individuals of the CIMA-Q cohort to obtain iPSC-derived neurons. Microtubule associated protein 2 was decreased in AD neurons, whereas expression of AD-associated amyloid precursor protein, tau, and amyloid-β peptide was similar in AD and NCI individuals. RNA sequencing identified several upregulated and downregulated mRNAs in AD relative to NCI neurons. Of these, complement Factor H (CFH), signal regulatory protein beta1 (SIRPB1), and insulin like growth factor binding protein 5 (IGFBP5) were previously associated with AD. In addition, several transcription factors not previously associated with AD, but involved in neuronal proliferation and differentiation were differentially expressed. The results identify novel avenues for the study of the underlying causes of sporadic AD and support the establishment of additional lines to identify mechanisms of disease in sporadic AD individuals.

Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Transcriptome Changes in the Alzheimer's Disease Middle Temporal Gyrus: Importance of RNA Metabolism and Mitochondria-Associated Membrane Genes. - Piras, Ignazio S; Krate, Jonida; Delvaux, Elaine; Nolz, Jennifer; Mastroeni, Diego F; Persico, Antonio M; Jepsen, Wayne M; Beach, Thomas G; Huentelman, Matthew J; Coleman, Paul D (J Alzheimers Dis, 2019)
We used Illumina Human HT-12 v4 arrays to compare RNA expression of middle temporal gyrus (MTG; BA21) in Alzheimer's disease (AD = 97) and non-demented controls (ND = 98). A total of 938 transcripts were highly differentially expressed (adj p < 0.01; log2 FC ≥ |0.500|, with 411 overexpressed and 527 underexpressed in AD. Our results correlated with expression profiling in neurons from AD and ND obtained by laser capture microscopy in MTG from an independent dataset (log2 FC correlation: r = 0.504; p = 2.2e-16). Additionally, selected effects were validated by qPCR. ANOVA analysis yielded no difference between genders in response to AD, but some gender specific genes were detected (e.g., IL8 and AGRN in males, and HSPH1 and GRM1 in females). Several transcripts were associated with Braak staging (e.g., AEBP1 and DNALI1), antemortem MMSE (e.g., AEBP1 and GFAP), and tangle density (e.g., RNU1G2, and DNALI1). At the pathway level, we detected enrichment of synaptic vesicle processes and GABAergic transmission genes. Finally, applying the Weighted Correlation Network Analysis, we identified four expression modules enriched for neuronal and synaptic genes, mitochondria-associated membrane, chemical stimulus and olfactory receptor and non-coding RNA metabolism genes. Our results represent an extensive description of MTG mRNA profiling in a large sample of AD and ND. These data provide a list of genes associated with AD, and correlated to neurofibrillary tangles density. In addition, these data emphasize the importance of mitochondrial membranes and transcripts related to olfactory receptors in AD.

TSPO Ligands Boost Mitochondrial Function and Pregnenolone Synthesis. - Lejri, Imane; Grimm, Amandine; Hallé, François; Abarghaz, Mustapha; Klein, Christian; Maitre, Michel; Schmitt, Martine; Bourguignon, Jean-Jacques; Mensah-Nyagan, Ayikoe Guy; Bihel, Frederic; Eckert, Anne (J Alzheimers Dis, 2019)
Translocator protein 18 kDa (TSPO) is located in the mitochondrial outer membrane and plays an important role in steroidogenesis and cell survival. In the central nervous system (CNS), its expression is upregulated in neuropathologies such as Alzheimer's disease (AD). Previously, we demonstrated that two new TSPO ligands based on an imidazoquinazolinone termed 2a and 2b, stimulated pregnenolone synthesis and ATP production in vitro. In the present study, we compared their effects to those of TSPO ligands described in the literature (XBD173, SSR-180,575, and Ro5-4864) by profiling the mitochondrial bioenergetic phenotype before and after treatment and investigating the protective effects of these ligands after oxidative injury in a cellular model of AD overexpressing amyloid-β (Aβ). Of note, ATP levels increased with rising pregnenolone levels suggesting that the energetic performance of mitochondria is linked to an increased production of this neurosteroid via TSPO modulation. Our results further demonstrate that the TSPO ligands 2a and 2b exerted neuroprotective effects by improving mitochondrial respiration, reducing reactive oxygen species and thereby decreasing oxidative stress-induced cell death as well as lowering Aβ levels. The compounds 2a and 2b show similar or even better functional effects than those obtained with the reference TSPO ligands XBD173 and SSR-180.575. These findings indicate that the new TSPO ligands modulate mitochondrial bioenergetic phenotype and protect against oxidative injury probably through the de novo synthesis of neurosteroids, suggesting that these compounds could be potential new therapeutic tools for the treatment of neurodegenerative disease.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

A 10-Year Follow-Up of Adiposity and Dementia in Swedish Adults Aged 70 Years and Older. - Arnoldussen, Ilse A C; Sundh, Valter; Bäckman, Kristoffer; Kern, Silke; Östling, Svante; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Kiliaan, Amanda J; Gustafson, Deborah R (J Alzheimers Dis, 2018)
BACKGROUND: Adiposity measured in mid- or late-life and estimated using anthropometric measures such as body mass index (BMI) and waist-to-hip ratio (WHR), or metabolic markers such as blood leptin and adiponectin levels, is associated with late-onset dementia risk. However, during later life, this association may reverse and aging- and dementia-related processes may differentially affect adiposity measures. OBJECTIVE: We explored associations of concurrent BMI, WHR, and blood leptin and high molecular weight adiponectin levels with dementia occurrence. METHODS: 924 Swedish community-dwelling elderly without dementia, aged 70 years and older, systematically-sampled by birth day and birth year population-based in the Gothenburg city region of Sweden. The Gothenburg Birth Cohort Studies are designed for evaluating risk and protective factors for dementia. All dementias diagnosed after age 70 for 10 years were identified. Multivariable logistic regression models were used to predict dementia occurrence between 2000-2005, 2005-2010, and 2000-2010 after excluding prevalent baseline (year 2000) dementias. Baseline levels of BMI, WHR, leptin, and adiponectin were used. RESULTS: Within 5 years of baseline, low BMI (<20 kg/m2) was associated with higher odds of dementia compared to those in the healthy BMI category (≥ 20-24.9 kg/m2). Compared to the lowest quartile, leptin levels in the second quartile were associated with lower odds of dementia in women (p < 0.05). CONCLUSION: In late-life, anthropometric and metabolic adiposity measures appear to be differentially associated with dementia risk. While BMI and leptin levels are highly positively correlated, our results show that their association with dementia at age ≥70 years, is asynchronous. These data suggest that with aging, the complexity of the adiposity exposure may increase and suggests metabolic dysregulation. Additional studies are needed to better understand this complexity.

18F-FDG PET for Prediction of Conversion to Alzheimer's Disease Dementia in People with Mild Cognitive Impairment: An Updated Systematic Review of Test Accuracy. - Smailagic, Nadja; Lafortune, Louise; Kelly, Sarah; Hyde, Chris; Brayne, Carol (J Alzheimers Dis, 2018)
BACKGROUND: A previous Cochrane systematic review concluded there is insufficient evidence to support the routine use of 18F-FDG PET in clinical practice in people with mild cognitive impairment (MCI). OBJECTIVES: To update the evidence and reassess the accuracy of 18F-FDG-PET for detecting people with MCI at baseline who would clinically convert to Alzheimer's disease (AD) dementia at follow-up. METHODS: A systematic review including comprehensive search of electronic databases from January 2013 to July 2017, to update original searches (1999 to 2013). All key review steps, including quality assessment using QUADAS 2, were performed independently and blindly by two review authors. Meta-analysis could not be conducted due to heterogeneity across studies. RESULTS: When all included studies were examined across all semi-quantitative and quantitative metrics, exploratory analysis for conversion of MCI to AD dementia (n = 24) showed highly variable accuracy; half the studies failed to meet four or more of the seven sets of QUADAS 2 criteria. Variable accuracy for all metrics was also found across eleven newly included studies published in the last 5 years (range: sensitivity 56-100%, specificity 24-100%). The most consistently high sensitivity and specificity values (approximately ≥80%) were reported for the sc-SPM (single case statistical parametric mapping) metric in 6 out of 8 studies. CONCLUSION: Systematic and comprehensive assessment of studies of 18FDG-PET for prediction of conversion from MCI to AD dementia reveals many studies have methodological limitations according to Cochrane diagnostic test accuracy gold standards, and shows accuracy remains highly variable, including in the most recent studies. There is some evidence, however, of higher and more consistent accuracy in studies using computer aided metrics, such as sc-SPM, in specialized clinical settings. Robust, methodologically sound prospective longitudinal cohort studies with long (≥5 years) follow-up, larger consecutive samples, and defined baseline threshold(s) are needed to test these promising results. Further evidence of the clinical validity and utility of 18F-FDG PET in people with MCI is needed.

[18F]-Flutemetamol Uptake in Cortex and White Matter: Comparison with Cerebrospinal Fluid Biomarkers and [18F]-Fludeoxyglucose. - Kalheim, Lisa Flem; Fladby, Tormod; Coello, Christopher; Bjørnerud, Atle; Selnes, Per (J Alzheimers Dis, 2018)
Flutemetamol (18F-Flut) is an [18F]-labelled amyloid PET tracer with increasing availability. The main objectives of this study were to investigate 1) cerebrospinal fluid (CSF) Aβ 1-42 (Aβ42) concentrations associated with regional 18F-Flut uptake, 2) associations between cortical 18F-Flut and [18F]-fludeoxyglucose (18F-FDG)-PET, and 3) the potential use of 18F-Flut in WM pathology. Cognitively impaired, nondemented subjects were recruited (n = 44). CSF was drawn, and 18F-Flut-PET, 18F-FDG-PET, and MRI performed. Our main findings were: 1) Different Alzheimer's disease predilection areas showed increased 18F-Flut retention at different CSF Aβ42 concentrations (posterior regions were involved at higher concentrations). 2) There were strong negative correlations between regional cortical 18F-Flut and 18F-FDG uptake. 3) Increased 18F-Flut uptake were observed in multiple subcortical regions in amyloid positive subjects, including investigated reference regions. However, WM hyperintensity 18F-Flut standardized uptake value ratios (SUVr) were not significantly different, thus we cannot definitely conclude that the higher uptake in 18F-Flut(+) is due to amyloid deposition. In conclusion, our findings support clinical use of CSF Aβ42, putatively relate decreasing CSF Aβ42 concentrations to a sequence of regional amyloid deposition, and associate amyloid pathology to cortical hypometabolism. However, we cannot conclude that 18F-Flut-PET is a suitable marker for WM pathology due to high aberrant WM uptake.

ABCA7 Downregulation Modifies Cellular Cholesterol Homeostasis and Decreases Amyloid-β Peptide Efflux in an in vitro Model of the Blood-Brain Barrier. - Lamartinière, Yordenca; Boucau, Marie-Christine; Dehouck, Lucie; Krohn, Markus; Pahnke, Jens; Candela, Pietra; Gosselet, Fabien; Fenart, Laurence (J Alzheimers Dis, 2018)
The role of ABCA7 in brain homeostasis and Alzheimer's disease (AD) is currently under intense scrutiny, since it has been reported that polymorphisms in the Abca7 gene and a loss of function of the protein are closely linked to excessive accumulation of amyloid peptides and disturbed cholesterol homeostasis. The blood-brain barrier (BBB), which isolates the brain from the blood compartment, is involved in both of these processes. We therefore hypothesized that ABCA7 downregulation might affect cholesterol and amyloid exchanges at the BBB. Using siRNA and primary cultures of mouse endothelial cells purified from brain microvessels and seeded on Transwell ® inserts, we investigated the role of ABCA7 in cholesterol and amyloid exchanges across the BBB. Our results showed that a decrease in ABCA7 expression at the BBB provokes in vitro a reduction in ABCA1 expression and a decrease in APOE secretion. In vitro, these decreases reduce cholesterol exchange across the BBB, particularly for high-density lipoproteins and ApoA-I particles. When ABCA7 was absent, we observed a reduction in Aβ peptide basolateral-to-apical transport in the presence of ApoA-I, with non-significant changes in the expression levels of Rage, Lrp1, Abcb1, Abcc1, and Abcg2. Our study in murine BBB model highlighted a putative new role for ABCA7 in AD via the protein's involvement in cholesterol metabolism and amyloid clearance at the BBB.

Aberrant Cortical Event-Related Potentials During Associative Learning in Rat Models for Presymptomatic Stages of Alzheimer's Disease. - Nouriziabari, Bardia; Sarkar, Susmita; Tanninen, Stephanie E; Dayton, Robert D; Klein, Ronald L; Takehara-Nishiuchi, Kaori (J Alzheimers Dis, 2018)
Trace eyeblink conditioning is a hippocampus-dependent associative learning paradigm which is impaired in patients with Alzheimer's disease (AD) and animal AD models. Learning in this paradigm accompanies changes in oscillatory activity in forebrain regions, some of which are loci of pathogenic changes in prodromal AD stages. These observations motivated us to examine how cortical event-related potentials (ERPs) during this paradigm are affected by two features of the asymptomatic, AD-related brain abnormality, entorhinal tau accumulation and mild cholinergic deficit. Adult rats received viral overexpression of P301L mutant human tau in the entorhinal cortex, low-dose scopolamine treatment, or both. Electroencephalograms were recorded with epidural electrodes on the surface of the frontal, parietal, and temporal cortices during differential and reversal trace eyeblink conditioning. All rats developed conditioned responses to one of two stimuli (auditory or visual) paired with mild eyelid shock (CS+), but not to the other stimulus presented alone (CS-). They were also able to adjust the response when the stimulus contingency was reversed. With learning, the amplitude of several ERP components in the frontal and temporal cortices came to differentiate the CS+ from CS-. Scopolamine affected the learning-related change in temporal P2 and other learning-unrelated components in three regions. Entorhinal tau overexpression primary affected the amplitude of temporal visual ERPs and learning-unrelated frontal and temporal auditory ERP components. The double manipulation only affected two components of temporal auditory ERPs. Thus, cortical ERPs during differential associative learning are sensitive to asymptomatic brain abnormality associated with AD.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

Age-Dependent Changes to Sphingolipid Balance in the Human Hippocampus are Gender-Specific and May Sensitize to Neurodegeneration. - Couttas, Timothy A; Kain, Nupur; Tran, Collin; Chatterton, Zac; Kwok, John B; Don, Anthony S (J Alzheimers Dis, 2018)
The greatest risk factor for developing Alzheimer's disease (AD) is aging. The major genetic risk factor for AD is the ɛ4 allele of the APOE gene, encoding the brain's major lipid transport protein, apolipoprotein E (ApoE). The research community is yet to decipher why the ApoE4 variant pre-disposes to AD, and how aging causes the disease. Studies have shown deregulated levels of sphingolipids, including decreased levels of the neuroprotective signaling lipid sphingosine 1-phosphate (S1P), and increased ceramide content, in brain tissue and serum of people with pre-clinical or very early AD. In this study we investigated whether sphingolipid levels are affected as a function of age or APOE genotype, in the hippocampus of neurologically normal subjects over the age of 65. Lipids were quantified in 80 postmortem tissue samples using liquid chromatography tandem mass spectrometry (LC-MS/MS). Sphingolipid levels were not significantly affected by the presence of one ɛ4 or ɛ2 allele. However, ceramide, sphingomyelin, and sulfatide content was very significantly correlated with age in the hippocampus of males. On the other hand, S1P, normalized to its non-phosphorylated precursor sphingosine, was inversely correlated with age in females. Our results therefore establish gender-specific differences in sphingolipid metabolism in the aging human brain. Ceramide is a pro-apoptotic lipid, and heavily implicated as a driver of insulin resistance in metabolic tissues. S1P is a neuroprotective lipid that supports glutamatergic neurotransmission. Increasing ceramide and decreasing S1P levels may contribute significantly to a pro-neurodegenerative phenotype in the aging brain.

Age-Dependent Decrease of Mitochondrial Complex II Activity in a Familial Mouse Model for Alzheimer's Disease. - Emmerzaal, Tim L; Rodenburg, Richard J; Tanila, Heikki; Verweij, Vivienne; Kiliaan, Amanda J; Kozicz, Tamas (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a severe neurodegenerative disorder for which the exact etiology is largely unknown. An increasingly recognized and investigated notion is the pathogenic role of mitochondrial dysfunction in AD. We assessed mitochondrial oxidative-phosphorylation (OXPHOS) enzyme activities in the APPswe/PS1ΔE9 mouse model from 4.5 to 14 months of age. We show an age-dependent decrease in mitochondrial complex-II activity starting at 9 months in APP/PS1 mice. Other enzymes of the OXPHOS do not show any alterations. Since amyloid-β (Aβ) plaques are already present from 4 months of age, mitochondrial dysfunction likely occurs downstream of Aβ pathology in this mouse model.

Age-Related Changes in the Spatial Frequency Threshold of Male and Female 3xTg-AD Mice Using OptoMotry. - King, Jillian L; Wong, Aimée A; Brown, Richard E (J Alzheimers Dis, 2018)
Visual impairments and retinal abnormalities occur in patients with Alzheimer's disease (AD) and in mouse models of AD. It is important to know the visual ability of mouse models of AD to ensure that age-related cognitive deficits are not confounded by visual impairments. Using OptoMotry, the spatial frequency thresholds of male and female 3xTg-AD mice did not differ from their B6129SF2 wildtype controls between 1-18 months of age, but females had higher spatial frequency thresholds than males. However, the differences were quite small, and the visual ability of all mice was comparable to that of C57BL/6 mice.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Sex Characteristics; tau Proteins; Vision, Ocular

Aging-Related Calcium Dysregulation in Rat Entorhinal Neurons Homologous with the Human Entorhinal Neurons in which Alzheimer's Disease Neurofibrillary Tangles First Appear. - Gant, John C; Kadish, Inga; Chen, Kuey-Chu; Thibault, Olivier; Blalock, Eric M; Porter, Nada M; Landfield, Philip W (J Alzheimers Dis, 2018)
Aging is the leading risk factor for idiopathic Alzheimer's disease (AD), indicating that normal aging processes promote AD and likely are present in the neurons in which AD pathogenesis originates. In AD, neurofibrillary tangles (NFTs) appear first in entorhinal cortex, implying that aging processes in entorhinal neurons promote NFT pathogenesis. Using electrophysiology and immunohistochemistry, we find pronounced aging-related Ca2 + dysregulation in rat entorhinal neurons homologous with the human neurons in which NFTs originate. Considering that humans recapitulate many aspects of animal brain aging, these results support the hypothesis that aging-related Ca2 + dysregulation occurs in human entorhinal neurons and promotes NFT pathogenesis.

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alterations in the Plasma Levels of Specific Choline Phospholipids in Alzheimer's Disease Mimic Accelerated Aging. - Dorninger, Fabian; Moser, Ann B; Kou, Jianqiu; Wiesinger, Christoph; Forss-Petter, Sonja; Gleiss, Andreas; Hinterberger, Margareta; Jungwirth, Susanne; Fischer, Peter; Berger, Johannes (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disease and of continuously rising prevalence. The identification of easy-to-measure biomarkers capable to assist in the prediction and early diagnosis of AD is currently a main research goal. Lipid metabolites in peripheral blood of human patients have recently gained major attention in this respect. Here, we analyzed plasma of 174 participants (not demented at baseline; mean age: 75.70±0.44 years) of the Vienna Transdanube Aging (VITA) study, a longitudinal, population-based birth cohort study, at baseline and after 90 months or at diagnosis of probable AD. We determined the levels of specific choline phospholipids, some of which have been suggested as potential biomarkers for the prediction of AD. Our results show that during normal aging the levels of lysophosphatidylcholine, choline plasmalogen, and lyso-platelet activating factor increase significantly. Notably, we observed similar but more pronounced changes in the group that developed probable AD. Thus, our results imply that, in terms of choline-containing plasma phospholipids, the conversion to AD mimics an accelerated aging process. We conclude that age, even in the comparatively short time frame between 75 and 82.5 years, is a crucial factor in the quest for plasma lipid biomarkers for AD that must be carefully considered in future studies and trials.

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

The Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog): Modifications and Responsiveness in Pre-Dementia Populations. A Narrative Review. - Kueper, Jacqueline K; Speechley, Mark; Montero-Odasso, Manuel (J Alzheimers Dis, 2018)
The Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog) was developed in the 1980s to assess the level of cognitive dysfunction in Alzheimer's disease. Advancements in the research field have shifted focus toward pre-dementia populations, and use of the ADAS-Cog has extended into these pre-dementia studies despite concerns about its ability to detect important changes at these milder stages of disease progression. If the ADAS-Cog cannot detect important changes, our understanding of pre-dementia disease progression may be compromised and trials may incorrectly conclude that a novel treatment approach is not beneficial. The purpose of this review was to assess the performance of the ADAS-Cog in pre-dementia populations, and to review all modifications that have been made to the ADAS-Cog to improve its measurement performance in dementia or pre-dementia populations. The contents of this review are based on bibliographic searches of electronic databases to locate all studies using the ADAS-Cog in pre-dementia samples or subsamples, and to locate all modified versions. Citations from relevant articles were also consulted. Overall, our results suggest the original ADAS-Cog is not an optimal outcome measure for pre-dementia studies; however, given the prominence of the ADAS-Cog, care must be taken when considering the use of alternative outcome measures. Thirty-one modified versions of the ADAS-Cog were found. Modification approaches that appear most beneficial include altering scoring methodology or adding tests of memory, executive function, and/or daily functioning. Although modifications improve the performance of the ADAS-Cog, this is at the cost of introducing heterogeneity that may limit between-study comparison.

Alzheimer's Disease Can Be Spared by Nonsteroidal Anti-Inflammatory Drugs. - McGeer, Patrick L; Guo, Jian Ping; Lee, Moonhee; Kennedy, Krista; McGeer, Edith G (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by deposits of amyloid-β protein (Aβ) in brain which become foci of inflammation. Neurons are destroyed by this inflammatory process, leading to the cognitive deficits which define AD clinical onset. Epidemiological studies indicate that nonsteroidal anti-inflammatory drugs (NSAIDs) can ameliorate this destructive process if they are started well before clinical signs develop. Biomarker studies indicate that the disease process starts at least a decade before cognitive deficits appear. This pre-clinical onset explains the NSAID effect. It also opens a window of opportunity for preventive treatment that can be met with a simple diagnostic test. Salivary levels of Aβ42 may fulfill that need. They can be measured by a simple ELISA test we have developed using commercially available reagents. By this ELISA test, normal controls, who are not at risk for AD, have levels of Aβ42 close to 20 pg/ml. AD cases, as well as high level controls, secrete levels in the range of 40-85 pg/ml. Widespread application of this test to detect high level controls, followed by NSAID consumption, could substantially reduce the prevalence of AD.

Alzheimer's Disease: Recent Concepts on the Relation of Mitochondrial Disturbances, Excitotoxicity, Neuroinflammation, and Kynurenines. - Zádori, Dénes; Veres, Gábor; Szalárdy, Levente; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2018)
The pathomechanism of Alzheimer's disease (AD) certainly involves mitochondrial disturbances, glutamate excitotoxicity, and neuroinflammation. The three main aspects of mitochondrial dysfunction in AD, i.e., the defects in dynamics, altered bioenergetics, and the deficient transport, act synergistically. In addition, glutamatergic neurotransmission is affected in several ways. The balance between synaptic and extrasynaptic glutamatergic transmission is shifted toward the extrasynaptic site contributing to glutamate excitotoxicity, a phenomenon augmented by increased glutamate release and decreased glutamate uptake. Neuroinflammation in AD is predominantly linked to central players of the innate immune system, with central nervous system (CNS)-resident microglia, astroglia, and perivascular macrophages having been implicated at the cellular level. Several abnormalities have been described regarding the activation of certain steps of the kynurenine (KYN) pathway of tryptophan metabolism in AD. First of all, the activation of indolamine 2,3-dioxygenase, the first and rate-limiting step of the pathway, is well-demonstrated. 3-Hydroxy-L-KYN and its metabolite, 3-hydroxy-anthranilic acid have pro-oxidant, antioxidant, and potent immunomodulatory features, giving relevance to their alterations in AD. Another metabolite, quinolinic acid, has been demonstrated to be neurotoxic, promoting glutamate excitotoxicity, reactive oxygen species production, lipid peroxidation, and microglial neuroinflammation, and its abundant presence in AD pathologies has been demonstrated. Finally, the neuroprotective metabolite, kynurenic acid, has been associated with antagonistic effects at glutamate receptors, free radical scavenging, and immunomodulation, giving rise to potential therapeutic implications. This review presents the multiple connections of KYN pathway-related alterations to three main domains of AD pathomechanism, such as mitochondrial dysfunction, excitotoxicity, and neuroinflammation, implicating possible therapeutic options.
Keywords: Alzheimer Disease; Animals; Central Nervous System; Disease Models, Animal; Energy Metabolism; Glutamic Acid; Humans; Immunity, Innate; Inflammation; Kynurenine; Mitochondria; Quinolinic Acid; Reactive Oxygen Species; Receptors, Glutamate; Signal Transduction

Amyloid-Mediated Cholinergic Dysfunction in Motor Impairment Related to Alzheimer's Disease. - Schirinzi, Tommaso; Di Lorenzo, Francesco; Sancesario, Giulia Maria; Di Lazzaro, Giulia; Ponzo, Viviana; Pisani, Antonio; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro (J Alzheimers Dis, 2018)
BACKGROUND: Although motor disturbances parallel the course of dementia, worsening both quality of life and social costs, the pathogenesis remains still unclear. OBJECTIVE: Through the combination of cerebrospinal fluid (CSF) biomarkers assessment and transcranial magnetic stimulation (TMS) protocols, here we provided a cross-sectional study to understand pathogenic mechanisms of Alzheimer's disease (AD)-related early motor disturbances. METHODS: The motor phenotype, as defined with Unified Parkinson's Disease Rating Scale (UPDRS) part 2-3, Rating Scale for Gait Evaluation in Cognitive Deterioration (RSEGCD) and Tinetti scale, together with CSF profile of amyloid-β 42 (Aβ42), total-tau, and phosphorylated-tau were determined in 37 AD patients and compared to 18 patients with vascular dementia (VaD). A TMS protocol of short afferent inhibition (SAI) was further applied on a subset of AD patients. Clinical, biochemical, and neurophysiological data were then compared and correlated in order to find significant associations. RESULTS: AD patients exhibited subtle locomotor impairment and slight extrapyramidal signs. Main motor features (UPDRS part 3, RSGECD, and Tinetti scale scores) correlate with Aβ42 levels but not with t-tau and p-tau. AD patients also presented SAI impairment directly related to UPDRS part 3 score and Aβ42 levels. Motor disturbances of VaD group did not differ statistically from AD and did not correlate with CSF biomarkers. CONCLUSIONS: The association of motor disturbances with low Aβ42 CSF levels and individual SAI suggests that amyloid-mediated degeneration of cholinergic system may account for early AD-related motor impairment, providing interesting insights either for frailty stratification of patients or personalized therapies.

The Amyloid-β Oligomer Hypothesis: Beginning of the Third Decade. - Cline, Erika N; Bicca, Maíra Assunção; Viola, Kirsten L; Klein, William L (J Alzheimers Dis, 2018)
The amyloid-β oligomer (AβO) hypothesis was introduced in 1998. It proposed that the brain damage leading to Alzheimer's disease (AD) was instigated by soluble, ligand-like AβOs. This hypothesis was based on the discovery that fibril-free synthetic preparations of AβOs were potent CNS neurotoxins that rapidly inhibited long-term potentiation and, with time, caused selective nerve cell death (Lambert et al., 1998). The mechanism was attributed to disrupted signaling involving the tyrosine-protein kinase Fyn, mediated by an unknown toxin receptor. Over 4,000 articles concerning AβOs have been published since then, including more than 400 reviews. AβOs have been shown to accumulate in an AD-dependent manner in human and animal model brain tissue and, experimentally, to impair learning and memory and instigate major facets of AD neuropathology, including tau pathology, synapse deterioration and loss, inflammation, and oxidative damage. As reviewed by Hayden and Teplow in 2013, the AβO hypothesis "has all but supplanted the amyloid cascade." Despite the emerging understanding of the role played by AβOs in AD pathogenesis, AβOs have not yet received the clinical attention given to amyloid plaques, which have been at the core of major attempts at therapeutics and diagnostics but are no longer regarded as the most pathogenic form of Aβ. However, if the momentum of AβO research continues, particularly efforts to elucidate key aspects of structure, a clear path to a successful disease modifying therapy can be envisioned. Ensuring that lessons learned from recent, late-stage clinical failures are applied appropriately throughout therapeutic development will further enable the likelihood of a successful therapy in the near-term.

Antibodies to Multiple Receptors are Associated with Neuropsychiatric Symptoms and Mortality in Alzheimer's Disease: A Longitudinal Study. - Giil, Lasse M; Aarsland, Dag; Hellton, Kristoffer; Lund, Anders; Heidecke, Harald; Schulze-Forster, Kai; Riemekasten, Gabriela; Vik-Mo, Audun Osland; Kristoffersen, Einar K; Vedeler, Christian A; Nordrehaug, Jan Erik (J Alzheimers Dis, 2018)
BACKGROUND: Endogenous antibodies to signaling molecules and receptors (Abs) are associated with Alzheimer's disease (AD). OBJECTIVES: To investigate the association of 33 Abs to dopaminergic, serotoninergic, muscarinic, adrenergic, vascular, and immune receptors with cognitive, neuropsychiatric, and mortality outcomes. METHODS: Ninety-one patients with mild AD were followed annually for 5 years with the Mini-Mental State Examination (MMSE) and the Neuropsychiatric Inventory (NPI; composite outcomes: "psychosis" (item 1 + 2), "mood" (item 4 + 5 + 7), and "agitation" (item 3 + 8 + 9)). Abs were quantified in sera obtained at baseline by ELISA and reduced to principal components (PCs). Associations between Abs and outcomes were assessed by a mixed model (MMSE decline), zero-inflated fixed effects count models (composite NPI scores), and Cox regression (mortality). The resulting p-values were adjusted for multiple testing according to a false discovery rate of 0.05 (Benjamini-Hochberg). RESULTS: The measured levels of the 33 Abs formed four PCs. PC1 (dopaminergic and serotonergic Abs) was associated with increased mortality (Hazard ratio 2.57, p < 0.001), PC2 (serotonergic, immune, and vascular Abs) with decreased agitation symptoms (β - 0.19, p < 0.001), and PC3 (cholinergic receptor Abs) with increased mood symptoms (β 0.04, p = 0.002), over time. There were no associations between Abs and MMSE decline. CONCLUSION: The associations between Abs, mortality, and neuropsychiatric symptoms reported in this cohort are intriguing. They cannot, however, be generalized. Validation in independent sample sets is required.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

Aortic Stiffness is Associated with Increased Risk of Incident Dementia in Older Adults. - Cui, Chendi; Sekikawa, Akira; Kuller, Lewis H; Lopez, Oscar L; Newman, Anne B; Kuipers, Allison L; Mackey, Rachel H (J Alzheimers Dis, 2018)
Cardiovascular disease risk factors, including age, hypertension, and diabetes, contribute to aortic stiffness and subclinical cardiovascular and brain disease, increasing dementia risk. Aortic stiffness, measured by carotid-femoral pulse wave velocity (cfPWV), reduces the buffering of pulsatile blood flow, exposing cerebral small arteries to microvascular damage. High cfPWV is related to white matter hyperintensities and brain amyloid deposition, and to cognitive decline, but it is unclear whether cfPWV independently predicts incident dementia. Therefore, we tested the hypothesis that cfPWV predicts incident dementia in older adults, independent of potential confounders. The Cardiovascular Health Study Cognition Study followed 532 non-demented older adults with annual cognitive exams from 1998-99 through 2013. CfPWV was measured on 356 (mean age = 78, 59% women) between 1996-2000. Over 15 years, 212 (59.6%) developed dementia (median time from cfPWV measurement = 4 years). In age and sex-adjusted Cox models, cfPWV was significantly associated with increased risk of dementia, but systolic blood pressure, mean arterial pressure and pulse pressure were not. CfPWV (transformed as - 1/cfPWV) remained significantly associated with dementia risk when further adjusted for education, race, APOEɛ4, diabetes, body mass index, mean arterial pressure, and anti-hypertensive medication (hazard ratio = 1.60, 95% CI = 1.02, 2.51). Results were similar when further adjusted for baseline global cognition, subclinical brain measures, and coronary artery calcification. Finally, higher cfPWV was related to lower physical activity intensity and higher systolic blood pressure, heart rate, and waist circumference measured 5 years prior. An important unanswered question is whether interventions to slow arterial stiffening can reduce the risk of dementia.

An Aspartyl Cathepsin Targeted PET Agent: Application in an Alzheimer's Disease Mouse Model. - Snir, Jonatan A; Suchy, Mojmir; Bindseil, Geron A; Kovacs, Michael; Chronik, Blaine A; Hudson, Robert H E; Pasternak, Stephen H; Bartha, Robert (J Alzheimers Dis, 2018)
BACKGROUND: Early detection of Alzheimer's disease (AD) pathology is a serious challenge for both diagnosis and clinical trials. The aspartyl protease, Cathepsin D (CatD), is overexpressed in AD and could be a biomarker of disease. We have previously designed a unique contrast agent (CA) for dual-optical and magnetic resonance imaging of the activity of the CatD class of enzymes. OBJECTIVE: To compare the uptake and retention of a novel, more sensitive, and clinically-translatable 68Ga PET tracer targeting CatD activity in 5XFAD mice and non-Tg littermates. METHODS: The targeted CA consisted of an HIV-1 Tat cell penetrating peptide (CPP) conjugated to a specialized cleavage sequence targeting aspartyl cathepsins and a DOTA conjugate chelating 68Ga. PET images were acquired using a Siemens Inveon preclinical microPET in female Tg AD mice and non-Tg age matched female littermates (n = 5-8) following intravenous CA administration at 2, 6, and 9 months of age. Additionally, 18F fluorodeoxyglucose (FDG) PET imaging was performed at 10 months to measure glucose uptake. RESULTS: The Tg mice showed significantly higher relative uptake rate of the targeting CA in the forebrain relative to hindbrain at all ages compared to controls, consistent with histology. In contrast, no differences were seen in CA uptake in other organs. Additionally, the Tg mice did not show any differences in relative uptake of FDG at 10 months of age in the forebrain relative to the hindbrain compared to age matched non-Tg controls. CONCLUSIONS: Elevated aspartryl cathepsin activity was detected in vivo in the 5XFAD mouse model of AD using a novel targeted PET contrast agent.
Keywords: Alzheimer Disease; Animals; Brain; Cathepsin D; Contrast Media; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Glucose; Mice; Mice, Transgenic; Positron-Emission Tomography

Assessment of the Mid-Life Demographic and Lifestyle Risk Factors of Dementia Using Data from the Framingham Heart Study Offspring Cohort. - Li, Jinlei; Ogrodnik, Matthew; Kolachalama, Vijaya B; Lin, Honghuang; Au, Rhoda (J Alzheimers Dis, 2018)
BACKGROUND: Dementia is the leading cause of dependence and disability in the elderly population worldwide. However, currently there is no effective medication for dementia treatment. Therefore, identifying lifestyle-related risk factors including some that are modifiable may provide important strategies for reducing risk of dementia. OBJECTIVE: This study aims to highlight associations between easily obtainable lifestyle risk factors in mid-life and dementia in later adulthood. METHODS: Using data from the Framingham Heart Study Offspring cohort, we leveraged well-known classification models (decision tree classifier and random forests) to associate demographic and lifestyle behavioral data with dementia status. We then evaluated model performance by computing area under receiver operating characteristic (ROC) curve. RESULTS: As expected, age was strongly associated with dementia. The analysis also identified 'widowed' marital status, lower BMI, and less sleep at mid-life as risk factors of dementia. The areas under the ROC curves were 0.79 for the decision tree, and 0.89 for the random forest model. CONCLUSION: Demographic and lifestyle factors that are non-invasive and inexpensive to implement can be assessed in midlife and used to potentially modify the risk of dementia in late adulthood. Classification models can help identify associations between dementia and midlife lifestyle risk factors. These findings inform further research, in order to help public health officials develop targeted programs for dementia prevention.

The Association Between Body Mass Index, and Cognitive, Functional, and Behavioral Declines for Incident Dementia. - Michaud, Tzeyu L; Siahpush, Mohammad; Farazi, Paraskevi A; Kim, Jungyoon; Yu, Fang; Su, Dejun; Murman, Daniel L (J Alzheimers Dis, 2018)
BACKGROUND: Association between high adiposity and the clinical progression of dementia remains puzzling. OBJECTIVE: To separately examine the association between body mass index (BMI) and cognitive, functional, and behavioral declines before, at, and after diagnosis of dementia, and further stratified by age groups, and sex. METHODS: A total of 1,141 individuals with incident dementia were identified from the Uniform Data Set of the National Alzheimer's Coordinating Center. Cognitive function was evaluated by Mini-Mental State Exam, functional abilities were assessed using Functional Activities Questionnaire, and behavioral symptoms were captured by Neuropsychiatric Inventory Questionnaire at each follow-up visit. We used separate linear-mixed effects models to examine the association. RESULTS: Compared to moderate baseline BMI, high baseline BMI was associated with 0.30-point slower annual progression rates in functional decline. For individuals aged 76 and over, high baseline BMI was associated with 0.42-point faster progression rates in cognitive decline annually. A U-shaped association between baseline BMI and cognitive decline was observed among men. CONCLUSION: BMI levels before dementia diagnosis may facilitate the identification of different risk profiles for progression rates of cognitive and functional declines in individuals who developed dementia.

The Association Between Frontotemporal Lobar Degeneration and Bullous Pemphigoid. - Katisko, Kasper; Kokkonen, Nina; Krüger, Johanna; Hartikainen, Päivi; Koivisto, Anne M; Helisalmi, Seppo; Korhonen, Ville E; Kokki, Merja; Tuusa, Jussi; Herukka, Sanna-Kaisa; Solje, Eino; Haapasalo, Annakaisa; et al. (J Alzheimers Dis, 2018)
Recent studies have shown an epidemiological and immunological association between bullous pemphigoid (BP) and several neurological or psychiatric diseases. Here, our aim was for the first time to specify whether an association exists between BP and frontotemporal lobar degeneration (FTLD). Medical histories of FTLD patients (N = 196) were screened for clinical comorbidity, and BP180 and BP230 autoantibodies were analyzed in the sera of FTLD patients (N = 70, including 24 C9orf72 repeat expansion carriers) by BP180-NC16A-ELISA and BP230-ELISA. One FTLD patient (C9orf72 repeat expansion carrier) had a comorbid diagnosis of BP. Increased levels of serum BP180 autoantibodies (cutoff value >9 U/ml) were detected more often in FTLD patients (10.0%) than in controls (4.9%). Moreover, elevated levels of both BP180 and BP230 autoantibodies were found more often in C9orf72 repeat expansion-carrying FTLD than non-carrying patients or controls. However, none of these differences reached a statistical significance likely due to our limited cohort size. In conclusion, our findings suggest that subset of FTLD patients especially with the C9orf72 repeat expansion may have an immunological association with BP.

Association Between the Use of Antihyperglycemic Drugs and Dementia Risk: A Case-Control Study. - Bohlken, Jens; Jacob, Louis; Kostev, Karel (J Alzheimers Dis, 2018)
BACKGROUND: There is a conflicting literature on the association between the use of antihyperglycemic drugs and dementia risk. OBJECTIVE: The goal of this case-control study was to analyze the association between the use of antihyperglycemic drugs and dementia risk in patients followed in general practices in Germany. METHODS: This study included patients with type 2 diabetes mellitus who had received a first dementia diagnosis in 972 general practices in Germany between January 2013 and December 2017 (index date). Controls without dementia were matched (1:1) to cases by age, gender, index year, and physician. Two multivariate regression models were used to study the association between the use of antihyperglycemic drugs and dementia risk. Model 1 included all antihyperglycemic drugs prescribed to patients regardless of the prescription duration, whereas Model 2 only included the longest therapy prescribed to each patient. RESULTS: There were 8,276 diabetes patients with dementia and 8,276 diabetes patients without dementia included in this study. In Model 1, glitazones were associated with a decreased dementia risk (odds ratio [OR] = 0.80), whereas insulin was associated with an increased risk of developing the condition (OR = 1.34). In Model 2, metformin, prescribed as monotherapy (OR = 0.71) or as dual therapy with sulfonylureas (OR = 0.90), was associated with a decrease in the likelihood of subsequently being diagnosed with dementia. By contrast, the combination of basal insulin and bolus insulin (OR = 1.47) and premix insulin (OR = 1.33) were risk factors for dementia. CONCLUSION: Metformin and glitazones were negatively associated with dementia, while insulin was positively associated with dementia.

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

The Association of Mid- and Late-Life Systemic Inflammation with Brain Amyloid Deposition: The ARIC-PET Study. - Walker, Keenan A; Windham, B Gwen; Brown, Charles H; Knopman, David S; Jack, Clifford R; Mosley, Thomas H; Selvin, Elizabeth; Wong, Dean F; Hughes, Timothy M; Zhou, Yun; Gross, Alden L; Gottesman, Rebecca F (J Alzheimers Dis, 2018)
BACKGROUND: Although inflammation has been implicated in the pathogenesis of Alzheimer's disease, the effects of systemic inflammation on brain amyloid deposition remain unclear. OBJECTIVE: We examined the association of midlife and late-life systemic inflammation with late-life brain amyloid levels in a community sample of non-demented older adults from the Atherosclerosis Risk in Communities (ARIC) - PET Study. METHODS: 339 non-demented participants (age: 75 [SD 5]) were recruited from the ARIC Study to undergo florbetapir PET (amyloid) imaging. Blood levels of high sensitivity C-reactive protein (CRP), a marker of systemic inflammation, were measured 22 years (Visit 2), 16 years (Visit 4), and up to 2 years before PET imaging (Visit 5). Elevated brain amyloid deposition (standardized uptake value ratio >1.2) was the primary outcome. RESULTS: Our primary analyses found no association of midlife and late-life CRP with late-life brain amyloid levels. However, in secondary stratified analyses, we found that higher midlife (Visit 2) CRP was associated with elevated amyloid among males (OR 1.65, 95% CI: 1.13-2.42), and among white (OR 1.33, 95% CI: 1.02-1.75), but not African American, participants (p-interactions<0.05). Among male participants, those who maintained high CRP levels (≥3 mg/L) throughout mid- and late-life were most likely to have elevated brain amyloid (OR, 8.81; 95% CI: 1.23, 62.91). CONCLUSIONS: Although our primary analysis does not support an association between systemic inflammation and brain amyloid deposition, we found evidence for sex- and race-dependent associations. However, findings from subgroup analyses should be interpreted with caution.

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

Aβ42/Aβ40 and Aβ42/Aβ38 Ratios Are Associated with Measures of Gait Variability and Activities of Daily Living in Mild Alzheimer's Disease: A Pilot Study. - Koychev, Ivan; Galna, Brook; Zetterberg, Henrik; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil H; Rowe, James B; Thomas, Alan; Howard, Robert; Malhotra, Paresh; Ritchie, Craig; Lovestone, Simon; et al. (J Alzheimers Dis, 2018)
Gait disturbances are some of the earliest changes in dementia and their monitoring presents an opportunity for early diagnosis. The exact relationship between gait and well-established biomarkers of Alzheimer's disease (AD) remains to be clarified. In this study we compared gait-related measures with cerebrospinal fluid (CSF) markers of AD pathology. We recruited seventeen participants with mild AD in a multi-site study and performed gait assessment as well as lumbar punctures to obtain CSF. CSF Aβ42/Aβ40 and Aβ42/Aβ38 correlated positively with measures of variability (step time and step length) in the clinic-based assessments. This was driven by a negative relationship between gait variability and Aβ40 and Aβ38 but not Aβ42.The amyloid ratios and gait variability measures were also associated with more severe functional impairment. We interpret these data as an indication that increasing amyloid production (i.e., increasing Aβ40 and Aβ38) is associated with diminishing cognitive-motor control of gait. These preliminary results suggest that the two amyloid ratios may be a marker of the earliest disturbances in the interplay between cognitive and motor control which characterize dementia.

Biological Factors Contributing to the Response to Cognitive Training in Mild Cognitive Impairment. - Peter, Jessica; Schumacher, Lena V; Landerer, Verena; Abdulkadir, Ahmed; Kaller, Christoph P; Lahr, Jacob; Klöppel, Stefan (J Alzheimers Dis, 2018)
In mild cognitive impairment (MCI), small benefits from cognitive training were observed for memory functions but there appears to be great variability in the response to treatment. Our study aimed to improve the characterization and selection of those participants who will benefit from cognitive intervention. We evaluated the predictive value of disease-specific biological factors for the outcome after cognitive training in MCI (n = 25) and also considered motivation of the participants. We compared the results of the cognitive intervention group with two independent control groups of MCI patients (local memory clinic, n = 20; ADNI cohort, n = 302). The primary outcome measure was episodic memory as measured by verbal delayed recall of a 10-word list. Episodic memory remained stable after treatment and slightly increased 6 months after the intervention. In contrast, in MCI patients who did not receive an intervention, episodic memory significantly decreased during the same time interval. A larger left entorhinal cortex predicted more improvement in episodic memory after treatment and so did higher levels of motivation. Adding disease-specific biological factors significantly improved the prediction of training-related change compared to a model based simply on age and baseline performance. Bootstrapping with resampling (n = 1000) verified the stability of our finding. Cognitive training might be particularly helpful in individuals with a bigger left entorhinal cortex as individuals who did not benefit from intervention showed 17% less volume in this area. When extended to alternative treatment options, stratification based on disease-specific biological factors is a useful step towards individualized medicine.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Apolipoproteins E; Biological Factors; Cognitive Behavioral Therapy; Cognitive Dysfunction; Entorhinal Cortex; Female; Follow-Up Studies; Functional Laterality; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Reaction Time; Spatial Navigation; Treatment Outcome

Blood Inflammatory Mediators and Cognitive Decline in Alzheimer's Disease: A Two Years Longitudinal Study. - Julian, Adrien; Rioux-Bilan, Agnès; Ragot, Stéphanie; Krolak-Salmon, Pierre; Berrut, Gilles; Dantoine, Thierry; Hommet, Caroline; Hanon, Olivier; Page, Guylène; Paccalin, Marc (J Alzheimers Dis, 2018)
Peripheral inflammatory processes are involved in Alzheimer's disease (AD). We aimed to determine whether plasma inflammatory mediator levels at diagnosis are associated with cognitive decline through a 2-year follow-up in AD patients. Patients (n = 109, mean age 79.44 (6.82) years) were included at diagnosis with MMSE scores between 16 and 25, with C-reactive protein <10 mg/L, and without any acute or chronic inflammation status. Plasma IL-1β, IL-6, TNF-α, and CCL5 were measured using Luminex X-MAP technology at baseline, and after one year and two years of follow-up. The mean values of IL-1β, IL-6, TNF-α, and CCL5 at diagnosis were 0.3, 1.94, 6.57, and 69,615.81 pg/mL, respectively. Mean cognitive decline in MMSE was 3.35 points. No correlation between plasmatic value of IL-1β, IL-6, TNF-α, or CCL5 at diagnosis and cognitive decline during the two years of follow-up was found. Cognitive decline in AD does not appear to be predictable by the tested inflammatory mediators.

A Blood Test for Alzheimer's Disease: Progress, Challenges, and Recommendations. - Kiddle, Steven J; Voyle, Nicola; Dobson, Richard J B (J Alzheimers Dis, 2018)
Ever since the discovery of APOEɛ4 around 25 years ago, researchers have been excited about the potential of a blood test for Alzheimer's disease (AD). Since then researchers have looked for genetic, protein, metabolite, and/or gene expression markers of AD and related phenotypes. However, no blood test for AD is yet being used in the clinical setting. We first review the trends and challenges in AD blood biomarker research, before giving our personal recommendations to help researchers overcome these challenges. While some degree of consistency and replication has been seen across independent studies, several high-profile studies have seemingly failed to replicate. Partly due to academic incentives, there is a reluctance in the field to report predictive ability, to publish negative findings, and to independently replicate the work of others. If this can be addressed, then we will know sooner whether a blood test for AD or related phenotypes with clinical utility can be developed.

Bone-Marrow-Derived Microglia-Like Cells Ameliorate Brain Amyloid Pathology and Cognitive Impairment in a Mouse Model of Alzheimer's Disease. - Kawanishi, Shohei; Takata, Kazuyuki; Itezono, Shouma; Nagayama, Hiroko; Konoya, Sayaka; Chisaki, Yugo; Toda, Yuki; Nakata, Susumu; Yano, Yoshitaka; Kitamura, Yoshihisa; Ashihara, Eishi (J Alzheimers Dis, 2018)
Microglia, the primary immune cells in the brain, sense pathogens and tissue damage, stimulate cytokine production, and phagocytosis to maintain homeostasis. Accumulation of amyloid-β peptides (Aβ) in the brain triggers the onset of Alzheimer's disease (AD). Accordingly, promotion of Aβ clearance represents a promising strategy for AD therapy. We previously demonstrated that primary-cultured rat microglia phagocytose Aβ, and that transplantation of these cells ameliorates the Aβ burden in brains of Aβ-injected rats. In this study, we demonstrate that stimulation with colony-stimulating factor-1 efficiently differentiates mouse bone marrow cells into bone marrow-derived microglia-like (BMDML) cells that express markers for microglia, including the recently identified transmembrane protein 119. BMDML cells effectively phagocytose Aβ in vitro, with effects comparable to primary-cultured mouse microglia and greater than peritoneal macrophages. RT-qPCR analysis for cytokine mRNA levels revealed that BMDML cells polarize to a relatively anti-inflammatory state under non-stimulated and inflammatory conditions but exert a pro-inflammatory reaction after lipopolysaccharide treatment. Moreover, BMDML cells hippocampally injected into a mouse model of AD are morphologically similar to the ramified and amoeboid types of residential microglia. Comparisons with simulations assuming a uniform distribution of cells suggest that BMDML cells migrate directionally toward Aβ plaques. We also detected Aβ phagocytosis by BMDML cells, concomitant with a reduction in the number and area of Aβ plaques. Finally, we observed amelioration of cognitive impairment in a mouse model of AD after hippocampal injection of BMDML cells. Our results suggest that BMDML cells have potential as a cell-based disease-modifying therapy against AD.

Brain Amyloid Contribution to Cognitive Dysfunction in Early-Stage Parkinson's Disease: The PPMI Dataset. - Fiorenzato, Eleonora; Biundo, Roberta; Cecchin, Diego; Frigo, Anna Chiara; Kim, Jinhee; Weis, Luca; Strafella, Antonio P; Antonini, Angelo (J Alzheimers Dis, 2018)
BACKGROUND: The pathological processes underlying cognitive impairment in Parkinson's disease (PD) are heterogeneous and the contribution of cerebral amyloid deposits is poorly defined, particularly in the early stages of the disease. OBJECTIVE: To investigate regional [18F]florbetaben binding to amyloid-β (Aβ) and its contribution to cognitive dysfunction in early stage PD. METHODS: A multicenter cohort of 48 PD patients from the Parkinson's Progression Marker Initiative (PPMI) underwent [18F]florbetaben positron emission tomography (PET) scanning. Clinical features, including demographic characteristics, motor severity, cerebrospinal fluid (CSF), and cognitive testing were systematically assessed according to the PPMI study protocol. For the purpose of this study, we analyzed various neuropsychological tests assessing all cognitive functions. RESULTS: There were 10/48 (21%) amyloid positive PD patients (PDAβ+). Increased [18F]florbetaben uptake in widespread cortical and subcortical regions was associated with poorer performance on global cognition, as assessed by Montreal Cognitive Assessment (MoCA), and impaired performance on Symbol Digit Modality test (SDMT). Further, we found that PDAβ+ patients had higher CSF total-tau/Aβ1 - 42 (p = 0.001) and phosphorylated-tau/Aβ1 - 42 in (p = 0.002) compared to amyloid-negative PD. CONCLUSION: These findings suggest that multiple disease processes are associated with PD cognitive impairment and amyloid deposits may be observed already in early stages. However, prevalence of amyloid positivity is in the range of literature age-matched control population. Increased cortical and subcortical amyloid is associated with poor performance in attentive-executive domains while cognitive deficits at MoCA and SDMT may identify amyloid-related dysfunction in early PD.

Call for a Uniform Strategy of Collecting Alzheimer's Disease Costs: A Review and Meta-Analysis. - Maresova, Petra; Dolejš, Josef; Kuca, Kamil (J Alzheimers Dis, 2018)
BACKGROUND: There is now a general attempt in developed countries to implement strategic plans to fight against Alzheimer's disease and other dementia disorders. Among others, attention is paid to the issues of registers and calculations of economic burden. Currently available calculations of costs are difficult to compare. The problem is a different breakdown of cost categories and non-unified monitoring of cost types. OBJECTIVE: The aim of this paper is to note the problem of poor availability and inconsistencies in cost monitoring. Furthermore, the intersection of cost items that are comparable and consistently monitored in expert studies are specified. METHODS: The Web of Science, Elsevier Science Direct, PubMed, and Scopus databases are used in a systematic review. Two independent reviewers screened the identified records and selected relevant articles published in the period from 2010 to 2016. A meta-analysis of costs is performed in four categories related to patients suffering from Alzheimer's disease. RESULTS: The resulting estimation of total costs per patient per month through meta-analysis is € 3,896, with 95% CI [2078, 5713]. The highest costs arise from informal care following non-medical and medical care. CONCLUSION: The results confirm assumption that inconsistencies in cost monitoring of the treatment and care of people with dementia exists in Europe. Homogeneity could be assumed only in the medical costs of severe patients. Heterogeneity is assumed in non-medical costs, informal costs. Cost items should be defined and collected more precisely for future more precise monitoring of the economic burden.

Can a Novel High-Density EEG Approach Disentangle the Differences of Visual Event Related Potential (N170), Elicited by Negative Facial Stimuli, in People with Subjective Cognitive Impairment? - Lazarou, Ioulietta; Adam, Katerina; Georgiadis, Kostas; Tsolaki, Anthoula; Nikolopoulos, Spiros; Yiannis Kompatsiaris, Ioannis; Tsolaki, Magda (J Alzheimers Dis, 2018)
BACKGROUND: Studies on subjective cognitive impairment (SCI) and neural activation report controversial results. OBJECTIVE: To evaluate the ability to disentangle the differences of visual N170 ERP, generated by facial stimuli (Anger & Fear) as well as the cognitive deterioration of SCI, mild cognitive impairment (MCI), and Alzheimer's disease (AD) compared to healthy controls (HC). METHOD: 57 people took part in this study. Images corresponding to facial stimuli of "Anger" and "Fear" were presented to 12 HC, 14 SCI, 17 MCI and 14 AD participants. EEG data were recorded by using a HD-EEG HydroCel with 256 channels. RESULTS: Results showed that the amplitude of N170 can contribute in distinguishing the SCI group, since statistically significant differences were observed with the HC (p < 0.05) and the MCI group from HC (p < 0.001), as well as AD from HC (p = 0.05) during the processing of facial stimuli. Noticeable differences were also observed in the topographic distribution of the N170 amplitude, while localization analysis by using sLORETA images confirmed the activation of superior, middle-temporal, and frontal lobe brain regions. Finally, in the case of "Fear", SCI and HC demonstrated increased activation in the orbital and inferior frontal gyrus, respectively, MCI in the inferior temporal gyrus, and AD in the lingual gyrus. CONCLUSION: These preliminary findings suggest that the amplitude of N170 elicited after negative facial stimuli could be modulated by the decline related to pathological cognitive aging and can contribute in distinguishing HC from SCI, MCI, and AD.

Cardiorespiratory Fitness and Cognitive Function are Positively Related Among Participants with Mild and Subjective Cognitive Impairment. - Stuckenschneider, Tim; Askew, Christopher David; Rüdiger, Stefanie; Polidori, Maria Cristina; Abeln, Vera; Vogt, Tobias; Krome, Andreas; Olde Rikkert, Marcel; Lawlor, Brian; Schneider, Stefan (J Alzheimers Dis, 2018)
BACKGROUND: By 2030, about 74 million people will be diagnosed with dementia, and many more will experience subjective (SCI) or mild cognitive impairment (MCI). As physical inactivity has been identified to be a strong modifiable risk factor for dementia, exercise and physical activity (PA) may be important parameters to predict the progression from MCI to dementia, but might also represent disease trajectory modifying strategies for SCI and MCI. OBJECTIVE: A better understanding of the relationship between activity, fitness, and cognitive function across the spectrum of MCI and SCI would provide an insight into the potential utility of PA and fitness as early markers, and treatment targets to prevent cognitive decline. METHODS: 121 participants were stratified into three groups, late MCI (LMCI), early MCI (EMCI), and SCI based on the Montreal Cognitive Assessment (MoCA). Cognitive function assessments also included the Trail Making Test A+B, and a verbal fluency test. PA levels were evaluated with an interviewer-administered questionnaire (LAPAQ) and an activity monitor. An incremental exercise test was performed to estimate cardiorespiratory fitness and to determine exercise capacity relative to population normative data. RESULTS: ANCOVA revealed that LMCI subjects had the lowest PA levels (LAPAQ, p = 0.018; activity monitor, p = 0.041), and the lowest exercise capacity in relation to normative values (p = 0.041). Moreover, a modest correlation between MoCA and cardiorespiratory fitness (r = 0.25; p < 0.05) was found. CONCLUSION: These findings suggest that during the earliest stages of cognitive impairment PA and exercise capacity might present a marker for the risk of further cognitive decline. This finding warrants further investigation using longitudinal cohort studies.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Ceramide Accumulation Is Associated with Declining Verbal Memory in Coronary Artery Disease Patients: An Observational Study. - Chan, Parco; Saleem, Mahwesh; Herrmann, Nathan; Mielke, Michelle M; Haughey, Norman J; Oh, Paul I; Kiss, Alexander; Lanctôt, Krista L (J Alzheimers Dis, 2018)
BACKGROUND: Biomarkers in cognitively vulnerable populations, like those with coronary artery disease (CAD), may inform earlier intervention in vascular neurodegeneration. Circulating ceramide C18:0 (CerC18:0) is associated with changes in verbal memory in early neurodegeneration and CAD progression. OBJECTIVE: To investigate whether plasma CerC18:0 accumulation is associated with longitudinal declines in verbal memory performance in CAD. METHODS: In addition to total CerC18:0, we assessed its relative abundance to its precursors as ratios: CerC18:0 to monohexosylceramide C18:0 (MHxCer18:0), CerC18:0 to sphingomyelin C18:0 (SM18:0), and CerC18:0 to sphingosine-1-phosphate (S1P). Verbal memory was assessed using the California Verbal Learning Test 2nd Ed. Using mixed models in 60 CAD participants, we evaluated associations between baseline CerC18:0 ratios and changes in verbal memory performance, adjusting for age, body mass index, and education. Given that cognitive decline is more rapid following onset of deficits, these associations were compared between those with possible mild vascular neurocognitive disorder (MVND). RESULTS: Increased baseline CerC18:0 concentrations correlated with worse verbal memory performance over time (b[SE] = - 0.91[0.30], p = 0.003). Increased baseline CerC18:0/SM18:0 (b[SE] = - 1.11[`], p = 0.03) were associated with worse verbal memory performance over time. These associations were not mediated by whether or not patients had possible MVND at baseline. CONCLUSION: These findings support aberrant CerC18:0 metabolism as an early neurobiological change in vascular neurodegeneration. Future studies should measure enzymes responsible for conversion of sphingolipid precursors into CerC18:0 to assess enzymatic activity.

Cerebral Amyloid Angiopathy: Similarity in African-Americans and Caucasians with Alzheimer's Disease. - Kamara, Dennis M; Gangishetti, Umesh; Gearing, Marla; Willis-Parker, Monica; Zhao, Liping; Hu, William T; Walker, Lary C (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) of the Aβ type is variably present in the brains of patients with Alzheimer's disease (AD). CAA contributes to cognitive decline and increases the risk of lobar hemorrhage; because both AD-typical dementia and lobar hemorrhage are more common in African-Americans than in Caucasians, we postulated that African-Americans with AD might be particularly susceptible to CAA. To test this hypothesis, we analyzed CAA histopathologically in the large vessels and capillaries of autopsy-derived frontal, temporal, parietal, and occipital cortical samples from African-Americans (n = 18) and Caucasians (n = 19) with end-stage AD. In the combined cohort of 37 subjects, 22% of the subjects had severe CAA in large vessels, and 11% had severe CAA in capillaries. However, the prevalence and histopathologic characteristics of CAA were similar in the African-Americans and Caucasians. This conclusion was substantiated in an independent sample from the National Alzheimer's Coordinating Center database, in which the degree of CAA was comparable in 1,554 Caucasians and 68 African-Americans with end-stage AD. These findings support a growing consensus that the fundamental histopathologic features of AD are largely impartial to the race of the afflicted.

Cerebral White Matter Lesions have Low Impact on Cognitive Function in a Large Elderly Memory Clinic Population. - Claus, Jules J; Coenen, Mirthe; Staekenborg, Salka S; Schuur, Jacqueline; Tielkes, Caroline E M; Koster, Pieter; Scheltens, Philip (J Alzheimers Dis, 2018)
BACKGROUND: Evidence suggests that cerebral white matter lesions (WML) play a role in cognitive decline. OBJECTIVE: To assess the impact of cerebral WML on cognitive function relative to absence or presence of medial temporal atrophy (MTA) in a large single-center memory clinic population. METHODS: Patients included had subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492) and Alzheimer's disease (AD, n = 832). The relationships between visually rated WML (Fazekas scale, 0-3) on brain Computed Tomography and CAMCOG memory and non-memory function were investigated with regression analysis adjusted for age, gender and education in combined patient groups. We assessed possible interaction versus addition effects of these relationships with visually rated MTA (Scheltens scale). RESULTS: The highly statistical significant relationship between WML and memory function was no longer significant when MTA was taken into account. However, the strong significant relationship between WML and non-memory function remained significant after adjustment for MTA, but the explained variance attributed to WML was only 1.3%. There was no interaction between WML and MTA on CAMCOG test scores. In addition, shown by a 2×2 factorial model by presence versus absence of WML and MTA, WML affected non-memory function only in the presence of MTA. CONCLUSION: Our data suggest that presence of WML is associated with lower non-memory cognitive function but this effect is conditional on the presence of pre-existing MTA. The very small explained variance suggests little impact of WML to the clinical profile of a memory clinic patient.

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer's Disease Pathology and Neuronal Damage. - Bettcher, Brianne M; Johnson, Sterling C; Fitch, Ryan; Casaletto, Kaitlin B; Heffernan, Kate S; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M; Neuhaus, John; Bendlin, Barbara B; Kramer, Joel H (J Alzheimers Dis, 2018)
Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and cerebrospinal fluid (CSF) markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer's disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n = 173). CSF samples were analyzed for markers of AD pathology (Aβ42, phosphorylated tau [p-tau], sAβPPβ) or neuronal damage (total tau; neurofilament light chain) (n = 147). Separate linear models for each analyte were conducted with CSF and plasma levels entered simultaneously as predictors and markers of AD pathology or neuronal damage as outcome measures. Strong associations were noted between CSF and plasma MIP-1β levels, and modest associations were observed for remaining analytes. With respect to AD pathology, higher levels of plasma and CSF IL-8, CSF MIP-1β, and CSF IP-10 were associated with higher levels of p-tau. Higher levels of CSF IL-8 were associated with higher levels of CSF Aβ42. Higher CSF sAβPPβ levels were associated with higher plasma markers only (IL-8; MCP-1). In terms of neuronal injury, higher levels of plasma and CSF IL-8, CSF IP-10, and CSF MIP-1β were associated with higher levels of CSF total tau. Exploratory analyses indicated that CSF Aβ42 modifies the relationship between plasma inflammatory levels and CSF tau levels. Results suggest that both plasma and CSF inflammatory markers independently relay integral information about AD pathology and neuronal damage.

Cerebrospinal Fluid C-C Motif Chemokine Ligand 2 Correlates with Brain Atrophy and Cognitive Impairment in Alzheimer's Disease. - Kimura, Akio; Yoshikura, Nobuaki; Hayashi, Yuichi; Inuzuka, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: Chronic neuroinflammation has been implicated in Alzheimer's disease (AD) pathology. OBJECTIVE: To investigate the association between cytokine and anti-amyloid-β (Aβ) autoantibody levels and the degree of brain atrophy and cognitive impairment in AD patients. METHODS: Cerebrospinal fluid (CSF) levels of C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 8, C-X-C motif chemokine ligand 10, interleukin 6, and anti-Aβ autoantibody were evaluated in 69 AD patients. Serum levels of CCL2 and anti-Aβ autoantibody were also examined. The degree of brain atrophy was assessed using the voxel-based specific regional analysis system for AD, which targets the volumes of interest (VOI) in medial temporal structures. Cognitive function was evaluated by neuropsychological testing, including the Mini-Mental State Examination (MMSE) and Frontal Assessment Battery (FAB). RESULTS: CSF CCL2 levels correlated significantly with the severity (p = 0.023) and the extent (p = 0.022) of VOI atrophy, and with the extent of gray matter atrophy (p = 0.039) in AD patients. CSF anti-Aβ autoantibody levels were inversely correlated with the severity of VOI atrophy (p = 0.020), the extent of VOI atrophy (p = 0.015), and the ratio of VOI/GM atrophy (r = -0.358, p = 0.004). CSF CCL2 levels were also inversely correlated with MMSE (p = 0.0497) and FAB scores (p = 0.016). CONCLUSIONS: CSF CCL2 levels are associated with the degree of medial temporal lobe and gray matter atrophy, and cognitive decline in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Chemokine CCL2; Cognitive Dysfunction; Disease Progression; Female; Gray Matter; Humans; Linear Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; tau Proteins; Temporal Lobe

CFH and ARMS2 Polymorphisms Interact with Zinc Supplements in Cognitive Impairment in the Women's Health Initiative Hormone Trial. - Kustra, Rafal; Awh, Carl C; Rojas-Fernandez, Carlos; Zanke, Brent (J Alzheimers Dis, 2018)
BACKGROUND: An interaction between genetic variants in complement factor H (CFH) and age-related maculopathy susceptibility 2 (ARMS2) and high-dose zinc supplementation on progression to advanced age-related macular degeneration (AMD) exists. Because cognitive impairment (CI) is associated with AMD, we used data from the Women's Health Initiative (WHI) to search for a zinc/genetics interaction. OBJECTIVE: To study the interaction of chronic zinc supplementation with genetic variants in CFH and ARMS2 on the development of CI. BACKGROUND: Zinc dietary supplements, CFH and ARMS2 genotypes, and serial mental status was analyzed in participants with available genetic data (n = 7,483). Cognition was assessed using the Modified Mini-Mental State Examination. The development of CI over 5 years was analyzed by genotype and zinc intake using a repeated measures logistic regression model. RESULTS: Zinc supplementation of approximately 15 mg/day was associated with decreased development of CI in women with 1 or 2 CFH and no ARMS2 risk alleles (OR = 0.46: 1 CFH risk allele; 0.20: 2 CFH risk alleles; p = 0.002). CONCLUSION: Low-dose zinc (approximately 15 mg) is associated with reduced CI in women with 2 CFH and 0 ARMS2 AMD risk alleles. This interaction is opposite in direction to that observed in AMD, where patients with 2 CFH and 0 ARMS2 risk alleles had increased progression to neovascular AMD if treated with 80 mg/day of zinc. This may be due to a zinc dose-response or to a fundamental difference in the role of zinc in the progression of early CI versus advanced AMD.

Change of Amyloid-β 1-42 Toxic Conformer Ratio After Cerebrospinal Fluid Diversion Predicts Long-Term Cognitive Outcome in Patients with Idiopathic Normal Pressure Hydrocephalus. - Akiba, Chihiro; Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Motoi, Yumiko; Kawamura, Kaito; Adachi, Satoshi; Kondo, Akihide; Sugano, Hidenori; Tokuda, Takahiko; Irie, Kazuhiro; Arai, Hajime (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology in idiopathic normal pressure hydrocephalus (iNPH) contributes to poor shunt responses. Amyloid-β 1- 42 (Aβ42) toxic conformer was recently identified with features of rapid oligomerization, strong neurotoxicity and synaptotoxicity. OBJECTIVE: This observational study points to Aβ42 toxic conformer as a biomarker for AD pathology and for poor postoperative prognosis in patients with iNPH. METHODS: The first cohort consisted of patients with AD (n = 17) and iNPH (n = 17), and cognitively normal individuals (CN, n = 12). The second cohort, consisted of 51 patients with iNPH, was divided into two groups according to phosphorylated Tau (pTau) level (low- and high-pTau groups); the low-pTau group was further subdivided according to one-year postoperative change in Aβ42 toxic conformer ratio (%) [Aβ42 toxic conformer/Aβ42×100] (decreased- and increased-conformer subgroups). Enzyme-linked immunosorbent assay was used to measure pTau, Aβ42, and Aβ42 toxic conformer in cerebrospinal fluid. Outcomes were evaluated using neuropsychological tests one- and two-years postoperatively. RESULTS: In the first cohort, Aβ42 toxic conformer ratio in the iNPH group (10.8%) was significantly higher than that in the CN group (6.3%) and significantly lower than that in the AD group (17.2%). In the second cohort, the high-pTau group showed cognitive decline two-years postoperatively compared to baseline. However, the low-pTau group showed favorable outcomes one-year postoperatively; furthermore, the increased-conformer subgroup showed cognitive decline two-years postoperatively while the decreased-conformer subgroup maintained the improvement. CONCLUSIONS: Change in Aβ42 toxic conformer ratio predicts long-term cognitive outcome in iNPH, even in the low-pTau group.

Chronic Lithium Treatment Increases Telomere Length in Parietal Cortex and Hippocampus of Triple-Transgenic Alzheimer's Disease Mice. - Cardillo, Giancarlo de Mattos; De-Paula, Vanessa de Jesus Rodrigues; Ikenaga, Eliza Hiromi; Costa, Luciana Rodrigues; Catanozi, Sergio; Schaeffer, Evelin Lisete; Gattaz, Wagner Farid; Kerr, Daniel Shikanai; Forlenza, Orestes Vicente (J Alzheimers Dis, 2018)
Telomere length (TL) is a biomarker of cell aging, and its shortening has been linked to several age-related diseases. In Alzheimer's disease (AD), telomere shortening has been associated with neuroinflammation and oxidative stress. The majority of studies on TL in AD were based on leucocyte DNA, with little information about its status in the central nervous system. In addition to other neuroprotective effects, lithium has been implicated in the maintenance of TL. The present study aims to determine the effect of chronic lithium treatment on TL in different regions of the mouse brain, using a triple-transgenic mouse model (3xTg-AD). Eighteen transgenic and 22 wild-type (Wt) male mice were treated for eight months with chow containing 1.0 g (Li1) or 2.0 g (Li2) of lithium carbonate/kg, or standard chow (Li0). DNA was extracted from parietal cortex, hippocampus and olfactory epithelium and TL was quantified by real-time PCR. Chronic lithium treatment was associated with longer telomeres in the hippocampus (Li2, p = 0.0159) and in the parietal cortex (Li1, p = 0.0375) of 3xTg-AD compared to Wt. Our findings suggest that chronic lithium treatment does affect telomere maintenance, but the magnitude and nature of this effect depend on the working concentrations of lithium and characteristics of the tissue. This effect was observed when comparing 3xTg-AD with Wt mice, suggesting that the presence of AD pathology was required for the lithium modulation of TL.

Class-Specific Incidence of All-Cause Dementia and Alzheimer's Disease: A Latent Class Approach. - Zammit, Andrea R; Hall, Charles B; Katz, Mindy J; Muniz-Terrera, Graciela; Ezzati, Ali; Bennett, David A; Lipton, Richard B (J Alzheimers Dis, 2018)
Identifying preclinical Alzheimer's disease (AD) is an important step toward developing approaches to early treatment and dementia prevention. We applied latent class analysis (LCA) to 10 baseline neuropsychological assessments for 1,345 participants from Einstein Aging Study. Time-to-event models for all-cause dementia and AD were run examining events in 4-year intervals. Five classes were identified: Mixed-Domain Impairment (n = 107), Memory-Specific Impairment (n = 457), Average (n = 539), Frontal Impairment (n = 118), and Superior Cognition (n = 124). Compared to the Average class, the Mixed-Domain Impairment and Memory-Specific Impairment classes were at higher risk of incident all-cause dementia and AD in the first 4 years from baseline, while the Frontal Impairment class was associated with higher risk between 4 and 8 years of follow-up. LCA identified classes which differ in cross-sectional cognitive patterns and in risk of dementia over specific follow-up intervals.

Clinical Evaluation of Amyloid-Related Imaging Abnormalities in Bapineuzumab Phase III Studies. - Brashear, H Robert; Ketter, Nzeera; Bogert, Jennifer; Di, Jianing; Salloway, Stephen P; Sperling, Reisa (J Alzheimers Dis, 2018)
BACKGROUND: Amyloid-related imaging abnormalities with effusion or edema (ARIA-E) reported in patients with mild-to-moderate Alzheimer's disease in bapineuzumab phase III studies. OBJECTIVES: Assess symptoms, clinical severity, and ARIA-E outcomes, and to evaluate effects on cognition and function. METHODS: A centralized systematic sequential locked procedure and scoring system for assessment of magnetic resonance imaging scans in 1,331 APOE ɛ4 noncarriers and 1,121 carriers was conducted by experienced and trained pairs of neuroradiologists. RESULTS: Treatment-emergent ARIA-E occurred in 15.8% of bapineuzumab and 0.8% placebo-treated patients. In all treated APOE ɛ4 noncarriers, the percentage of patients with ARIA-E was 5.6%, 13.4%, and 19.9% in the 0.5, 1.0, and 2.0 mg/kg groups respectively, and the incidence of symptomatic ARIA-E was 1.5%, 1.5%, and 7.8%, respectively. In carriers, ARIA-E occurred in 21.2% in the 0.5 mg/kg group, and symptomatic ARIA-E occurred in 2.4%. The clinical severity of ARIA-E in those patients in whom it was detected during the study was mild in 57.1%, 61.3%, and 50.0% of cases in 0.5, 1.0, and 2.0 mg/kg noncarriers respectively, and in 73.8% of cases in 0.5 mg/kg carriers. Vascular risk factors did not appear to increase susceptibility to ARIA-E. Rate of decline in cognition and function measured by changes in ADAS-Cog/11 and DAD total scores did not meaningfully differ in patients with ARIA-E versus those without ARIA-E. Extent of cognitive decline was similar over all visit intervals. CONCLUSIONS: Overall, ARIA-E was mild and asymptomatic. ARIA-E did not demonstrate clinically meaningful acute or chronic impact on cognition or function.Registration: NCT00574132 (Bapineuzumab-301), NCT00575055 (Bapineuzumab-302).

A Clinicopathological Investigation of White Matter Hyperintensities and Alzheimer's Disease Neuropathology. - Alosco, Michael L; Sugarman, Michael A; Besser, Lilah M; Tripodis, Yorghos; Martin, Brett; Palmisano, Joseph N; Kowall, Neil W; Au, Rhoda; Mez, Jesse; DeCarli, Charles; Stein, Thor D; McKee, Ann C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMH) on magnetic resonance imaging (MRI) have been postulated to be a core feature of Alzheimer's disease. Clinicopathological studies are needed to elucidate and confirm this possibility. OBJECTIVE: This study examined: 1) the association between antemortem WMH and autopsy-confirmed Alzheimer's disease neuropathology (ADNP), 2) the relationship between WMH and dementia in participants with ADNP, and 3) the relationships among cerebrovascular disease, WMH, and ADNP. METHODS: The sample included 82 participants from the National Alzheimer's Coordinating Center's Data Sets who had quantitated volume of WMH from antemortem FLAIR MRI and available neuropathological data. The Clinical Dementia Rating (CDR) scale (from MRI visit) operationalized dementia status. ADNP+ was defined by moderate to frequent neuritic plaques and Braak stage III-VI at autopsy. Cerebrovascular disease neuropathology included infarcts or lacunes, microinfarcts, arteriolosclerosis, atherosclerosis, and cerebral amyloid angiopathy. RESULTS: 60/82 participants were ADNP+. Greater volume of WMH predicted increased odds for ADNP (p = 0.037). In ADNP+ participants, greater WMH corresponded with increased odds for dementia (CDR≥1; p = 0.038). WMH predicted cerebral amyloid angiopathy, microinfarcts, infarcts, and lacunes (ps < 0.04). ADNP+ participants were more likely to have moderate-severe arteriolosclerosis and cerebral amyloid angiopathy compared to ADNP-participants (ps < 0.04). CONCLUSIONS: This study found a direct association between total volume of WMH and increased odds for having ADNP. In patients with Alzheimer's disease, FLAIR MRI WMH may be able to provide key insight into disease severity and progression. The association between WMH and ADNP may be explained by underlying cerebrovascular disease.

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Cognitive Impairment is Associated with Mortality in Hemodialysis Patients. - Angermann, Susanne; Schier, Johannes; Baumann, Marcus; Steubl, Dominik; Hauser, Christine; Lorenz, Georg; Günthner, Roman; Braunisch, Matthias C; Kemmner, Stephan; Satanovskij, Robin; Haller, Bernhard; Heemann, Uwe; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The prevalence of cognitive impairment in hemodialysis patients is notably high. In previous studises performed in the general population, cognitive impairment has been associated with increased mortality. OBJECTIVE: We evaluated the relationship between global cognitive function tested by a short screening instrument and mortality in hemodialysis patients. METHODS: Cognitive testing was performed in 242 maintenance hemodialysis patients under standardized conditions at baseline using the Montreal Cognitive Assessment (MoCA).Cognitive impairment was defined as a MoCA test score ≤24 points, as published previously. All-cause mortality was monitored during a median follow-up of 3.54 years. Kaplan-Meier plot and Cox regression model adjusted for known risk factors for mortality in hemodialysis patients were used to examine a possible association between global cognitive function and all-cause mortality. RESULTS: A MoCA test score ≤24 points resulted in a significant almost 3-fold higher hazard for all-cause mortality (unadjusted hazard ratio [HR]: 2.812; 95% confidence interval [95% CI]: 1.683-4.698; p < 0.001). After adjustment, this association was attenuated but remained significant (adjusted HR: 1.749; 95% CI: 1.007-3.038; p = 0.047). CONCLUSION: Impairment of global cognitive function measured by a short screening instrument was identified for the first time as an independent predictor of all-cause mortality in hemodialysis patients. Thus, implementing the MoCA test in clinical routine could contribute to a better risk stratification of this patient population.

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Colocalization of Aluminum and Iron in Nuclei of Nerve Cells in Brains of Patients with Alzheimer's Disease. - Yumoto, Sakae; Kakimi, Shigeo; Ishikawa, Akira (J Alzheimers Dis, 2018)
Increasing evidence indicates that metal-induced oxidative stress plays a pivotal role in the pathogenesis of Alzheimer's disease (AD). Recently, the presence of 8-hydroxydeoxyguanosine, a biomarker of oxidative DNA damage, was demonstrated in nuclear DNA (nDNA) in the AD brain. Iron (Fe) is a pro-oxidant metal capable of generating hydroxyl radicals that can oxidize DNA, and aluminum (Al) has been reported to facilitate Fe-mediated oxidation. In the present study, we examined the elements contained in the nuclei of nerve cells in AD brains using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS). Our results demonstrated that Al and Fe were colocalized in the nuclei of nerve cells in the AD brain. Within the nuclei, the highest levels of both Al and Fe were measured in the nucleolus. The SEM-EDS analysis also revealed the colocalization of Al and Fe in the heterochromatin and euchromatin in neuronal nuclei in the AD brain. Notably, the levels of Al and Fe in the nucleus of nerve cells in the AD brain were markedly higher than those in age-matched control brains. We hypothesize that the colocalization of Al and Fe in the nucleus of nerve cells might induce oxidative damage to nDNA and concurrently inhibit the repair of oxidatively damaged nDNA. An imbalance caused by the increase in DNA damage and the decrease in DNA repair activities might lead to the accumulation of unrepaired damaged DNA, eventually causing neurodegeneration and the development of AD.

Combination Therapy of Serotonin Reuptake Inhibitors and Memantine for Obsessive- Compulsive Disorder: A Meta-Analysis of Double-Blind, Randomized, Placebo-Controlled Trials. - Kishi, Taro; Matsuda, Yuki; Iwata, Nakao (J Alzheimers Dis, 2018)
We performed a meta-analysis to determine whether combination therapy with serotonin reuptake inhibitors (SRIs) and memantine (MEM) was beneficial for the treatment of obsessive- compulsive disorder. This study included three double-blind, randomized, placebo-controlled trials. MEM+SRI was superior to placebo+SRI with regard to response rate [primary outcome, n = 97; risk ratio = 0.22; 95% confidence intervals (CI) = 0.12-0.42; p < 0.00001; I2 = 0%; number needed to treat = 2], the Yale- Brown Obsessive- Compulsive Scale total [standardized mean difference (SMD) = - 4.56; 95% CI = - 8.50, - 0.62; p = 0.02], obsession subscale (SMD = - 4.39; 95% CI = - 5.94, - 2.85; p < 0.00001), and compulsion subscale score (SMD = - 4.60; 95% CI = - 7.64, - 1.55; p = 0.003). No significant differences in any safety outcome were found between the groups.

Combining Cognitive, Genetic, and Structural Neuroimaging Markers to Identify Individuals with Increased Dementia Risk. - Payton, Nicola M; Kalpouzos, Grégoria; Rizzuto, Debora; Fratiglioni, Laura; Kivipelto, Miia; Bäckman, Lars; Laukka, Erika J (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive and biological markers have shown varying degrees of success in identifying persons who will develop dementia. OBJECTIVE: To evaluate different combinations of cognitive and biological markers and identify prediction models with the highest accuracy for identifying persons with increased dementia risk. METHODS: Neuropsychological assessment, genetic testing (apolipoprotein E -APOE), and structural magnetic resonance imaging (MRI) were performed for 418 older individuals without dementia (60-97 years) from a population-based study (SNAC-K). Participants were followed for six years. RESULTS: Cognitive, genetic, and MRI markers were systematically combined to create prediction models for dementia at six years. The most predictive individual markers were perceptual speed or carrying at least one APOEɛ4 allele (AUC = 0.875). The most predictive model (AUC = 0.924) included variables from all three modalities (category fluency, general knowledge, any ɛ4 allele, hippocampal volume, white matter-hyperintensity volume). CONCLUSION: This study shows that combining markers within and between modalities leads to increased predictivity for future dementia. However, minor increases in predictive value should be weighed against the cost of additional tests in larger-scale screening.

The Coming of Age of the Angiotensin Hypothesis in Alzheimer's Disease: Progress Toward Disease Prevention and Treatment? - Kehoe, Patrick Gavin (J Alzheimers Dis, 2018)
There is wide recognition of a complex association between midlife hypertension and cardiovascular disease and later development of Alzheimer's disease (AD) and cognitive impairment. While significant progress has been made in reducing rates of mortality and morbidity due to cardiovascular disease over the last thirty years, progress towards effective treatments for AD has been slower. Despite the known association between hypertension and dementia, research into each disease has largely been undertaken in parallel and independently. Yet over the last decade and a half, the emergence of converging findings from pre-clinical and clinical research has shown how the renin angiotensin system (RAS), which is very important in blood pressure regulation and cardiovascular disease, warrants careful consideration in the pathogenesis of AD. Numerous components of the RAS have now been found to be altered in AD such that the multifunctional and potent vasoconstrictor angiotensin II, and similarly acting angiotensin III, are greatly altered at the expense of other RAS signaling peptides considered to contribute to neuronal and cognitive function. Collectively these changes may contribute to many of the neuropathological hallmarks of AD, as well as observed progressive deficiencies in cognitive function, while also linking elements of a number of the proposed hypotheses for the cause of AD. This review discusses the emergence of the RAS and its likely importance in AD, not only because of the multiple facets of its involvement, but also perhaps fortuitously because of the ready availability of numerous RAS-acting drugs, that could be repurposed as interventions in AD.

Comparison of Different Hypotheses Regarding the Spread of Alzheimer's Disease Using Markov Random Fields and Multimodal Imaging. - Dyrba, Martin; Grothe, Michel J; Mohammadi, Abdolreza; Binder, Harald; Kirste, Thomas; Teipel, Stefan J (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by a cascade of pathological processes that can be assessed in vivo using different neuroimaging methods. Recent research suggests a systematic sequence of pathogenic events on a global biomarker level, but little is known about the associations and dependencies of distinct lesion patterns on a regional level. Markov random fields are a probabilistic graphical modeling approach that represent the interaction between individual random variables by an undirected graph. We propose the novel application of this approach to study the interregional associations and dependencies between multimodal imaging markers of AD pathology and to compare different hypotheses regarding the spread of the disease. We retrieved multimodal imaging data from 577 subjects enrolled in the Alzheimer's Disease Neuroimaging Initiative. Mean amyloid load (AV45-PET), glucose metabolism (FDG-PET), and gray matter volume (MRI) were calculated for the six principle nodes of the default mode network- a functional network of brain regions that appears to be preferentially targeted by AD. Multimodal Markov random field models were developed for three different hypotheses regarding the spread of the disease: the "intraregional evolution model", the "trans-neuronal spread" hypothesis, and the "wear-and-tear" hypothesis. The model likelihood to reflect the given data was evaluated using tenfold cross-validation with 1,000 repetitions. The most likely graph structure contained the posterior cingulate cortex as main hub region with edges to various other regions, in accordance with the "wear-and-tear" hypothesis of disease vulnerability. Probabilistic graphical models facilitate the analysis of interactions between several variables in a network model and therefore afford great potential to complement traditional multiple regression analyses in multimodal neuroimaging research.

Comprehensive Characterization of the Pyroglutamate Amyloid-β Induced Motor Neurodegenerative Phenotype of TBA2.1 Mice. - Dunkelmann, Tina; Schemmert, Sarah; Honold, Dominik; Teichmann, Kerstin; Butzküven, Elke; Demuth, Hans-Ulrich; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; Willbold, Dieter; Willuweit, Antje (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and is being intensively investigated using a broad variety of animal models. Many of these models express mutant versions of human amyloid-β protein precursor (AβPP) that are associated with amyloid-β protein (Aβ)-induced early onset familial AD. Most of these models, however, do not develop bold neurodegenerative pathology and the respective phenotypes. Nevertheless, this may well be essential for their suitability to identify therapeutically active compounds that have the potential for a curative or at least disease-modifying therapy in humans. In this study, the new transgenic mouse model TBA2.1 was explored in detail to increase knowledge about the neurodegenerative process induced by the presence of pyroglutamate modified human Aβ3-42 (pEAβ3-42). Analysis of the sensorimotor phenotype, motor coordination, Aβ pathology, neurodegeneration, and gliosis revealed formation and progression of severe pathology and phenotypes including massive neuronal loss in homozygous TBA2.1 mice within a few months. In contrast, the start of a slight phenotype was observed only after 21 months in heterozygous mice. These data highlight the role of pEAβ3-42 in the disease development and progression of AD. Based on the findings of this study, homozygous TBA2.1 mice can be utilized to gain deeper understanding in the underlying mechanisms of pEAβ3-42 and might be suitable as an animal model for treatment studies targeting toxic Aβ species, complementary to the well described transgenic AβPP mouse models.

Consent to Medical Procedures of Patients with Neurodegenerative Diseases: A Comparative Study of Legal Regulations in Selected European Countries and in the United States. - Guzik-Makaruk, Ewa M; Pływaczewski, Emil W; Mroczko, Piotr; Olesiuk-Okomska, Magda; Kulczyńska-Przybik, Agnieszka (J Alzheimers Dis, 2018)
According to the projections of the statistical office of the European Union, Eurostat, nearly one third of EU citizens will be at least 65 in 2060. The U.S. population age 65 and older continues to increase and is projected to nearly double from 48 million to 88 million by 2050. Elderly people are especially exposed to neurodegenerative diseases (NDs). The most common ND is Alzheimer's disease (AD), a chronic and progressive disorder with a variety of pathological changes within neuronal tissue, which begin even 10-15 years before the onset of cognitive impairment symptoms. AD is perceived as a disease continuum and considered to include three basic phases: preclinical (asymptomatic) stage, mild cognitive impairment (MCI), and dementia due to AD. A very important issue, from medical and legal perspectives, is the NDs patient's consent to medical procedures, including diagnostic procedures, such as lumber puncture. NDs patients are not always able to express their consent and do not always understand the information provided by a physician. This applies to a group of patients in the final stages of NDs. This paper presents legal regulations of selected European countries and signalizes the U.S. legal solutions on the issue of NDs patients' informed consent to medical procedures.

Constructing a Local Potential Participant Registry to Improve Alzheimer's Disease Clinical Research Recruitment. - Grill, Joshua D; Hoang, Dan; Gillen, Daniel L; Cox, Chelsea G; Gombosev, Adrijana; Klein, Kirsten; O'Leary, Steve; Witbracht, Megan; Pierce, Aimee (J Alzheimers Dis, 2018)
Potential participant registries are tools to address the challenge of slow recruitment to clinical research. In particular, registries may aid recruitment to secondary prevention clinical trials for Alzheimer's disease (AD), which enroll cognitively normal older individuals meeting specific genetic or biomarker criteria. Evidence of registry effectiveness is sparse, as is guidance on optimal designs or methods of conduct. We report our experiences of developing a novel local potential participant registry that implemented online enrollment and data collection. In the first year of operation, 957 individuals submitted email addresses to the registry, of whom 592 self-reported demographic, family history, and medical data. In addition, registrants provided information related to their interest and willingness to be contacted about studies. Local earned media and community education were the most effective methods of recruitment into the registry. Seventy-six (26%) of 298 registrants contacted about studies in the first year enrolled in those studies. One hundred twenty-nine registrants were invited to enroll in a preclinical AD trial, of whom 25 (18%) screened and 6 were randomized. These results indicate that registries can aid recruitment and provide needed guidance for investigators initiating new local registries.

The Conundrum of GSK3 Inhibitors: Is it the Dawn of a New Beginning? - Bhat, Ratan V; Andersson, Ulf; Andersson, Shalini; Knerr, Laurent; Bauer, Udo; Sundgren-Andersson, Anna K (J Alzheimers Dis, 2018)
Spanning over three decades of extensive drug discovery research, the efforts to develop a potent and selective GSK3 inhibitor as a therapeutic for the treatment of type 2 diabetes, Alzheimer's disease (AD), bipolar disorders and cancer have been futile. Since its initial discovery in 1980 and subsequent decades of research, one cannot underscore the importance of the target and the promise of a game changing disease modifier. Several pharmaceutical companies, biotech companies, and academic institutions raged in a quest to unravel the biology and discover potent and selective GSK3 inhibitors, some of which went through clinical trials. However, the conundrum of what happened to the fate of the AstraZeneca's GSK3 inhibitors and the undertaking to find a therapeutic that could control glycogen metabolism and aberrant tau hyperphosphorylation in the brain, and rescue synaptic dysfunction has largely been untold. AstraZeneca was in the forefront of GSK3 drug discovery research with six GSK3 drug candidates, one of which progressed up to Phase II clinical trials in the quest to untangle the tau hypothesis for AD. Analysis of key toxicity issues, serendipitous findings and efficacy, and biomarker considerations in relation to safety margins have limited the potential of small molecule therapeutics as a way forward. To guide future innovation of this important target, we reveal the roller coaster journey comprising of two decades of preclinical and clinical GSK3 drug discovery at AstraZeneca; the understanding of which could lead to improved GSK3 therapies for disease. These learnings in combination with advances in achieving kinase selectivity, different modes of action as well as the recent discovery of novel conjugated peptide technology targeting specific tissues have potentially provided a venue for scientific innovation and a new beginning for GSK3 drug discovery.

Correlates of Subjective Cognitive Decline in Lesbian, Gay, Bisexual, and Transgender Older Adults. - Flatt, Jason D; Johnson, Julene K; Karpiak, Stephen E; Seidel, Liz; Larson, Britta; Brennan-Ing, Mark (J Alzheimers Dis, 2018)
BACKGROUND: Little is known about subjective cognitive decline (SCD) in lesbian, gay, bisexual, and transgender (LGBT) older adults. OBJECTIVES: To examine SCD and its association with dementia risk factors, other physical and psychosocial health factors in LGBT older adults. METHODS: A cross-sectional study of SCD was conducted with LGBT older adults, aged 50 and older (n = 210). SCD was categorized based on endorsement of memory problems and one other cognitive domain. Hierarchical logistic regression examined the associations between demographic factors, dementia risk factors, other health and psychosocial factors, and SCD. RESULTS: Nearly 25% of LGBT older adults were classified as having SCD. LGBT older adults who were people of color (OR = 2.5; 95% CI = 1.1- 7.8), depressed (OR = 2.9; 95% CI = 1.3- 6.9), or reported having functional impairment (OR = 2.6; 95% CI = 1.1- 6.5) were significantly more likely to be classified as having SCD (Nagelkerke pseudo R2 = 0.27). CONCLUSION: Depression and functional impairment should be considered when screening LGBT older adults for cognitive impairment and dementia. Future research on the cognitive impairment and dementia risk in LGBT older adults is needed.

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Dementia Care Competence Among Care Professionals and Reduced Challenging Behavior of Home-Dwelling Persons with Dementia: A Pre- and Post-Intervention Data Analysis. - Nakanishi, Miharu; Hirooka, Kayo; Imai, Yasuaki; Inoue, Shintaro; Yukari, Yukio; Katayama, Chie; Miyamoto, Yuki; Shindo, Yumi; Ueno, Hideki; Toya, Junichiro; Takano, Yosuke; Nishida, Atsushi (J Alzheimers Dis, 2018)
BACKGROUND: We developed a psychosocial dementia care program to help care managers and professional caregivers manage challenging behavior in home-dwelling persons with dementia in Japan. The program consists of a web-based tool for ongoing monitoring and assessment for challenging behavior, and multi-agency discussion meetings. Results of a cluster-randomized controlled trial indicate a reduction in challenging behavior through this program. OBJECTIVES: The present study aimed to identify a key component of the developed program that is associated with a reduction in challenging behavior. METHODS: We used consecutive data of the intervention and examined the association between challenging behavior in home-dwelling persons with dementia, professionals' competence, and the frequency of revision of action plans. Challenging behavior was assessed using the total score of the Neuropsychiatric Inventory. A baseline and follow-up questionnaire was completed by care professionals using a Japanese version of the Sense of Competence in Dementia Care Staff scale. RESULTS: A total of 86 care professionals completed a 6-month intervention with 219 persons with dementia. The 86 care professionals significantly improved in their dementia care competence. Challenging behavior was significantly reduced among the 219 persons with dementia at follow-up regardless of the level of professionals' competence or the frequency of revision of action plans. Less pain was significantly related to the lower levels of challenging behavior. CONCLUSION: The ongoing multi-agency discussion meetings, with a focus on challenging behavior, may have been the key component in the psychosocial dementia care program. Pain management should be emphasized in action plans for challenging behavior.

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Diaphanous 1 (DIAPH1) is Highly Expressed in the Aged Human Medial Temporal Cortex and Upregulated in Myeloid Cells During Alzheimer's Disease. - Derk, Julia; Bermudez Hernandez, Keria; Rodriguez, Moises; He, Meilun; Koh, Hyunwook; Abedini, Andisheh; Li, Huilin; Fenyö, David; Schmidt, Ann Marie (J Alzheimers Dis, 2018)
BACKGROUND: The receptor for advanced glycation end products (RAGE) is linked to cellular stress and inflammation during Alzheimer's disease (AD). RAGE signals through Diaphanous-1 (DIAPH1); however, the expression of DIAPH1 in the healthy and AD human brain has yet to be methodically addressed. OBJECTIVE: To delineate the cell- and disease-state specific expression of DIAPH1 in the human medial temporal cortex during healthy aging and AD. METHODS: We used semi-quantitative immunohistochemistry in the human medial temporal cortex paired with widefield and confocal microscopy and automated analyses to determine colocalization and relative expression of DIAPH1 with key cell markers and molecules in the brains of subjects with AD versus age-matched controls. RESULTS: We report robust colocalization of DIAPH1 with myeloid cells and increased expression during AD, which strongly correlated to increased neutral lipids and morphology of inflamed myeloid cells. DIAPH1 moderately colocalized with markers of endothelial cells, astrocytes, neurons, and oligodendrocytes. DISCUSSION: Our findings localize DIAPH1 particularly to myeloid cells in the CNS, especially in AD in the locations of lipid droplet accumulation, thereby implicating RAGE-DIAPH1 signaling in dysregulated lipid metabolism and morphological changes of inflamed myeloid cells in this disorder.

Diazepam Toxicity Presenting as a Dementia Disorder. - Kurlawala, Zimple; Roberts, Jeffrey A; McMillan, Joseph D; Friedland, Robert P (J Alzheimers Dis, 2018)
The toxicity associated with long-standing benzodiazepine use in older persons is a critical issue. Several epidemiological reports have studied correlation between benzodiazepine use and risk of dementia development. In this manuscript, we used a case report to demonstrate how chronic diazepam use can cause cognitive deficits that resemble Alzheimer's disease and related conditions. Benzodiazepine use is common in the geriatric population and is often taken for long periods of time in improper doses. In combination with age-related cortical atrophy on the MRI, our patient risked being misdiagnosed with Alzheimer's disease or another dementing disorder if not for the systematic investigation to resolve his symptoms. With elimination of the offending dispensable drug (diazepam), the patient's cognition improved greatly.

Differences Between Women and Men in Incidence Rates of Dementia and Alzheimer's Disease. - Beam, Christopher R; Kaneshiro, Cody; Jang, Jung Yun; Reynolds, Chandra A; Pedersen, Nancy L; Gatz, Margaret (J Alzheimers Dis, 2018)
In the following brief report, we examined gender differences in incidence rates of any dementia, Alzheimer's disease (AD) alone, and non-Alzheimer's dementia alone in 16,926 women and men in the Swedish Twin Registry aged 65+. Dementia diagnoses were based on clinical workup and national health registry linkage. Incidence rates of any dementia and AD were greater in women than men, with any dementia rates diverging after age 85 and AD rates diverging around 80. This pattern is consistent with women's survival to older ages compared to men. These findings are similar to incidence rates reported in other Swedish samples.

Differences in Dementia Beliefs between Non-Demented Public Screeners and In-Home Screeners and Their Potential Impact on Future Dementia Screening Intention: The Nakajima Study. - Yuki-Nozaki, Sohshi; Noguchi-Shinohara, Moeko; Domoto, Chiaki; Ikeda, Yoshihisa; Samuraki, Miharu; Iwasa, Kazuo; Yokogawa, Masami; Asai, Kimiko; Komai, Kiyonobu; Nakamura, Hiroyuki; Yamada, Masahito (J Alzheimers Dis, 2018)
In many cohort studies of dementia, while differences in sociodemographic characters between responders and non-responders of dementia screening have been reported, differences in dementia beliefs have been relatively less known. The aims of this study were to clarify dementia beliefs and to explore potential impacts on an intention to attend a future dementia screening in public screeners and in-home screeners, respectively. We performed a cross-sectional population-based study using a question about an intention to attend a future dementia screening and a questionnaire on dementia beliefs. Subjects were all residents aged 65 years or older in the north area of Nakajima, Japan (n = 385). All subjects were asked to attend a public dementia screening first. An in-home dementia screening was subsequently conducted in subjects with non-responders to a public screening. The questionnaire consisted of four dementia beliefs: "perceived susceptibility," "perceived severity," "perceived barriers," and "perceived benefits." Public screeners significantly expressed an intention to attend a future dementia screening more than in-home screeners (p = 0.002). In in-home screeners, low "perceived severity" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 0.51 (0.32-0.80)]. In both public and in-home screeners, high "perceived benefits" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 2.13 (1.46-3.10); adjusted OR (95% CI) = 2.56 (1.22-5.35), respectively]. It is necessary to reduce "perceived severity" among in-home screeners to increase dementia screening participants.

Early Impairments of Hippocampal Neurogenesis in 5xFAD Mouse Model of Alzheimer's Disease Are Associated with Altered Expression of SOXB Transcription Factors. - Zaletel, Ivan; Schwirtlich, Marija; Perović, Milka; Jovanović, Mirna; Stevanović, Milena; Kanazir, Selma; Puškaš, Nela (J Alzheimers Dis, 2018)
Dysregulation of neurogenesis in the subgranular zone (SGZ) of the hippocampal dentate gyrus has been related to cognitive deficits and memory loss in neurodegenerative diseases, such as Alzheimer's disease (AD). Members of the B group of SOX transcription factors play critical roles in regulating neurogenesis in the embryonic and adult nervous system, including maintaining the multipotency, renewal, and cell fate decision of neural stem/progenitor cells. The aim of the present study was to evaluate the expression patterns of selected SOXB proteins in the SGZ, of 8-week-old male and female 5xFAD mice, which represent a transgenic model of AD with a severe and very early development of amyloid pathology. Immunohistochemical analysis showed a significant decrease in the number of cells expressing SOX1, SOX2, and SOX21 transcription factors within the SGZ of 5xFAD mice in comparison to their non-transgenic counterparts which coincidences with reduced number of doublecortin immunoreactive immature neurons found in Tg males. Despite observed changes in expressional pattern of examined SOXB proteins, the proliferative capacity evaluated by the number of Ki-67 immunoreactive cells remained unaffected in transgenic mice of both genders. Based on our results, we suggest that SOXB proteins might be considered as new biomarkers for the detection of early impairments in adult neurogenesis in different animal models or/and new targets in human regenerative medicine.

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Economic Burden, Mortality, and Institutionalization in Patients Newly Diagnosed with Alzheimer's Disease. - Black, Christopher M; Fillit, Howard; Xie, Lin; Hu, Xiaohan; Kariburyo, M Furaha; Ambegaonkar, Baishali M; Baser, Onur; Yuce, Huseyin; Khandker, Rezaul K (J Alzheimers Dis, 2018)
BACKGROUND: Current information is scarce regarding comorbid conditions, treatment, survival, institutionalization, and health care utilization for Alzheimer's disease (AD) patients. OBJECTIVES: Compare all-cause mortality, rate of institutionalization, and economic burden between treated and untreated newly-diagnosed AD patients. METHODS: Patients aged 65-100 years with ≥1 primary or ≥2 secondary AD diagnoses (ICD-9-CM:331.0] with continuous medical and pharmacy benefits for ≥12 months pre-index and ≥6 months post-index date (first AD diagnosis date) were identified from Medicare fee-for-service claims 01JAN2011-30JUN2014. Patients with AD treatment claims or AD/AD-related dementia diagnosis during the pre-index period were excluded. Patients were assigned to treated and untreated cohorts based on AD treatment received post-index date. Total 8,995 newly-diagnosed AD patients were identified; 4,037 (44.8%) were assigned to the treated cohort. Time-to-death and institutionalization were assessed using Cox regression. To compare health care costs and utilizations, 1 : 1 propensity score matching (PSM) was used. RESULTS: Untreated patients were older (83.85 versus 81.44 years; p < 0.0001), with more severe comorbidities (mean Charlson comorbidity index: 3.54 versus 3.22; p < 0.0001). After covariate adjustment, treated patients were less likely to die (hazard ratio[HR] = 0.69; p < 0.0001) and were associated with 20% lower risk of institutionalization (HR = 0.801; p = 0.0003). After PSM, treated AD patients were less likely to have hospice visits (3.25% versus 9.45%; p < 0.0001), and incurred lower annual all-cause costs ($25,828 versus $30,110; p = 0.0162). CONCLUSION: After controlling for comorbidities, treated AD patients have better survival, lower institutionalization, and sometimes fewer resource utilizations, suggesting that treatment and improved care management could be beneficial for newly-diagnosed AD patients from economic and clinical perspectives.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Comorbidity; Cost of Illness; Female; Humans; Institutionalization; Male; Neuropsychological Tests

Effect of Cilostazol on Incident Dementia in Elderly Men and Women with Ischemic Heart Disease. - Kim, Mi-Young; Noh, Yoojin; Son, Sang Joon; Shin, Sooyoung; Paik, Hee-Young; Lee, Sukhyang; Jung, Yi-Sook (J Alzheimers Dis, 2018)
BACKGROUND: Ischemic heart disease (IHD) is associated with cognitive decline and may contribute to an increased risk of dementia. OBJECTIVE: The goal of the present study was to investigate whether cilostazol use is associated with a lower risk of incident dementia in Asian patients with IHD, and whether these effects differed based on sex. METHODS: This retrospective cohort study was performed using the Korean National Insurance Claim Data of the Health Insurance Review and Assessment Service; the duration of the study was from January 1, 2007 to December 31, 2015. The study group comprised 66,225 patients with IHD, aged >65 years, who had received cilostazol. Age- and sex-matched IHD patients without cilostazol exposure were selected as the control group. The risk of dementia was compared between the cilostazol and control groups. RESULTS: Compared to the control group, total cilostazol users had a marginally significant lower risk of incident dementia. After stratification by sex, the reducing effect of cilostazol on incident dementia was significant in female participants, but not in male participants. Female patients who had cilostazol for over 2 years showed a clinically meaningful preventive effect (HR, 0.85; 95% CI, 0.82-0.88). CONCLUSIONS: This study suggested that cilostazol treatment may reduce the risk of incident dementia in Korean patients with IHD. Its beneficial effect was remarkably significant in female patients who received cilostazol for over a 2-year period.

Effect of Fluvoxamine on Amyloid-β Peptide Generation and Memory. - Kim, Woojin Scott; Fu, YuHong; Dobson-Stone, Carol; Hsiao, Jen-Hsiang T; Shang, Kani; Hallupp, Marianne; Schofield, Peter R; Garner, Brett; Karl, Tim; Kwok, John B J (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by abnormal amyloid-β (Aβ) peptide accumulation beginning decades before symptom onset. An effective prophylactic treatment aimed at arresting the amyloidogenic pathway would therefore need to be initiated prior to the occurrence of Aβ pathology. The SIGMAR1 gene encodes a molecular chaperone that modulates processing of the amyloid-β protein precursor (AβPP). Fluvoxamine is a selective serotonin reuptake inhibitor and a potent SIGMAR1 agonist. We therefore hypothesized that fluvoxamine treatment would reduce Aβ production and improve cognition. We firstly investigated the impact of SIGMAR1 on AβPP processing, and found that overexpression and knockdown of SIGMAR1 significantly affected γ-secretase activity in SK-N-MC neuronal cells. We then tested the impact of fluvoxamine on Aβ production in an amyloidogenic cell model, and found that fluvoxamine significantly reduced Aβ production by inhibiting γ-secretase activity. Finally, we assessed the efficacy of long-term treatment (i.e., ∼8 months) of 10 mg/kg/day fluvoxamine in the J20 amyloidogenic mouse model; the treatment was initiated prior to the occurrence of predicted Aβ pathology. Physical examination of the animals revealed no overt pathology or change in weight. We conducted a series of behavioral tests to assess learning and memory, and found that the fluvoxamine treatment significantly improved memory function as measured by novel object recognition task. Two other tests revealed no significant change in memory function. In conclusion, fluvoxamine has a clear impact on γ-secretase activity and AβPP processing to generate Aβ, and may have a protective effect on cognition in the J20 mice.

Effect of Physical Activity on the Progression of Alzheimer's Disease: The Clinical Research Center for Dementia of South Korea Study. - Minn, Yang-Ki; Choi, Seong Hye; Suh, Young Ju; Jeong, Jee Hyang; Kim, Eun-Joo; Kim, Jong Hun; Park, Kyung Won; Park, Moon Ho; Youn, Young Chul; Yoon, Bora; Choi, Seok-Jin; Oh, Youn Kyung; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a lack of research on the effects of physical activity (PA) on the progression of Alzheimer's disease (AD). OBJECTIVES: We investigated whether PA is associated with progression of dementia and mortality in AD. METHODS: In the present study, 934 patients with mild-to-moderate AD were included. PA was evaluated using a questionnaire written by the caregiver. The outcome measures were the Clinical Dementia Rating-Sum of Boxes (CDR-SB), Seoul-Instrumental Activities of Daily Living (S-IADL), Caregiver-Administered Neuropsychiatric Inventory (CGA-NPI), a global composite score of neuropsychological subtests, and mortality. They were evaluated annually and received a maximum of three follow-up examinations. RESULTS: Between-group differences compared with the no PA group in the change of CDR-SB scores were -0.431 (95% CI = -0.824∼-0.039; p = 0.031) for the moderate PA group (150-750 minutes per week of moderate intensity PA), and -1.148 (-1.656∼-0.639; p < 0.001) for the high PA group (>750 minutes per week). As PA increased, there was a significant trend to slow the rate of increase in the CDR-SB, S-IADL, and CGA-NPI scores. The patients with ≥150 minutes per week for each of non-recreational and recreational PAs had a lower risk of mortality compared to those with <150 minutes per week for each of the PAs (hazard ratio 0.22, 95% CI = 0.05∼0.88; p = 0.033). CONCLUSION: More PA is associated with slower progression of dementia severity, functional decline, and abnormal behavior, and with a lower risk of mortality in AD.

Effectiveness of a Personalized Brain-Computer Interface System for Cognitive Training in Healthy Elderly: A Randomized Controlled Trial. - Yeo, Si Ning; Lee, Tih Shih; Sng, Wei Theng; Heo, Min Quan; Bautista, Dianne; Cheung, Yin Bun; Zhang, Hai Hong; Wang, Chuanchu; Chin, Zheng Yang; Feng, Lei; Zhou, Juan; Chong, Mei Sian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive training has been demonstrated to improve cognitive performance in older adults. To date, no study has explored personalized training that targets the brain activity of each individual. OBJECTIVE: This is the first large-scale trial that examines the usefulness of personalized neurofeedback cognitive training. METHODS: We conducted a randomized-controlled trial with participants who were 60-80 years old, with Clinical Dementia Rating (CDR) score of 0-0.5, Mini-Mental State Examination (MMSE) score of 24 and above, and with no neuropsychiatric diagnosis. Participants were randomly assigned to the Intervention or Waitlist-Control group. The training system, BRAINMEM, has attention, working memory, and delayed recall game components. The intervention schedule comprised 24 sessions over eight weeks and three monthly booster sessions. The primary outcome was the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total score after the 24-session training. RESULTS: There were no significant between-subjects differences in overall cognitive performance post-intervention. However, a sex moderation effect (p = 0.014) was present. Men in the intervention group performed better than those in the waitlist group (mean difference, +4.03 (95% CI 0.1 to 8.0), p = 0.046. Among females, however, both waitlist-control and intervention participants improved from baseline, although the between-group difference in improvement did not reach significance. BRAINMEM also received positive appraisal and intervention adherence from the participants. CONCLUSION: A personalized neurofeedback intervention is potentially feasible for use in cognitive training for older males. The sex moderation effect warrants further investigation and highlights the importance of taking sex into account during cognitive training.

Effects of Meditation and Music-Listening on Blood Biomarkers of Cellular Aging and Alzheimer's Disease in Adults with Subjective Cognitive Decline: An Exploratory Randomized Clinical Trial. - Innes, Kim E; Selfe, Terry Kit; Brundage, Kathleen; Montgomery, Caitlin; Wen, Sijin; Kandati, Sahiti; Bowles, Hannah; Khalsa, Dharma Singh; Huysmans, Zenzi (J Alzheimers Dis, 2018)
BACKGROUND: Telomere length (TL), telomerase activity (TA), and plasma amyloid-β (Aβ) levels have emerged as possible predictors of cognitive decline and dementia. OBJECTIVE: To assess the: 1) effects of two 12-week relaxation programs on TL, TA, and Aβ levels in adults with subjective cognitive decline; and 2) relationship of biomarker changes to those in cognitive function, psychosocial status, and quality of life (QOL). METHODS: Participants were randomized to a 12-week Kirtan Kriya meditation (KK) or music listening (ML) program and asked to practice 12 minutes/day. Plasma Aβ(38/40/42) and peripheral blood mononuclear cell TL and TA were measured at baseline and 3 months. Cognition, stress, sleep, mood, and QOL were assessed at baseline, 3 months, and 6 months. RESULTS: Baseline blood samples were available for 53 participants (25 KK, 28 ML). The KK group showed significantly greater increases in Aβ40 than the ML group. TA rose in both groups, although increases were significant only among those with higher practice adherence and lower baseline TA. Changes in both TL and TA varied by their baseline values, with greater increases among participants with values ≤50th percentile (ps-interaction <0.006). Both groups improved in cognitive and psychosocial status (ps ≤0.05), with improvements in stress, mood, and QOL greater in the KK group. Rising Aβ levels were correlated with gains in cognitive function, mood, sleep, and QOL at both 3 and 6 months, associations that were particularly pronounced in the KK group. Increases in TL and TA were also correlated with improvements in certain cognitive and psychosocial measures. CONCLUSION: Practice of simple mind-body therapies may alter plasma Aβ levels, TL, and TA. Biomarker increases were associated with improvements in cognitive function, sleep, mood, and QOL, suggesting potential functional relationships.

Efficacy, Acceptability, and Safety of Intravenous Immunoglobulin Administration for Mild-To-Moderate Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Okuya, Makoto; Matsunaga, Shinji; Ikuta, Toshikazu; Kishi, Taro; Iwata, Nakao (J Alzheimers Dis, 2018)
A systematic review and meta-analysis of the efficacy/safety of intravenous immunoglobulin (IVIG) administration in mild-to-moderate Alzheimer's disease (AD) patients was performed. Six randomized double-blind, placebo-controlled trials (n = 801) were included in this study. No significant difference in cognitive function was observed between the groups. Moreover, IVIG was inferior to placebo in behavioral disturbances (mean difference = 2.19). Further, IVIG administration was associated with a higher incidence of rash than placebo. Our results do not support IVIG administration for mild-to-moderate AD, suggesting that IVIG is not effective to treat mild-to-moderate AD and that it deteriorates behavioral and psychological symptoms of dementia in mild-to-moderate AD.

The Ethyl Acetate Extract of Leaves of Ugni molinae Turcz. Improves Neuropathological Hallmarks of Alzheimer's Disease in Female APPswe/PS1dE9 Mice Fed with a High Fat Diet. - Jara-Moreno, Daniela; Castro-Torres, Rubn D; Ettcheto, Miren; Auladell, Carme; Kogan, Marcelo J; Folch, Jaume; Verdaguer, Ester; Cano, Amanda; Busquets, Oriol; Delporte, Carla; Camins, Antoni (J Alzheimers Dis, 2018)
The most common type of dementia is Alzheimer's disease (AD), a progressive neurodegenerative disease characterized by impairment in cognitive performance in aged individuals. Currently, there is no effective pharmacological treatment that cures the disease due to the lack of knowledge on the actual mechanisms involved in its pathogenesis. In the last decades, the amyloidogenic hypothesis has been the most studied theory trying to explain the origin of AD, yet it does not address all the concerns relating to its development. In the present study, a possible new preclinical treatment of AD was evaluated using the ethyl acetate extract (EAE) of leaves of Ugni molinae Turcz. (synonym Myrtus ugni Molina Family Myrtacea). The effects were assessed on female transgenic mice from a preclinical model of familial AD (APPswe/PS1dE9) combined with a high fat diet. This preclinical model was selected due to the already available experimental and observational data proving the relationship between obesity, gender, metabolic stress, and cognitive dysfunction; related to characteristics of sporadic AD. According to chemical analyses, EAE would contain polyphenols such as tannins, flavonoid derivatives, and phenolic acids, as well as pentacyclic triterpenoids that exhibit neuroprotective, anti-inflammatory, and antioxidant effects. In addition, the treatment evidenced its capacity to prevent deterioration of memory capacity and reduction of progression speed of AD neuropathology.

Evaluation of Matrix Metalloproteinase-2 (MMP-2) and -9 (MMP-9) and Their Tissue Inhibitors (TIMP-1 and TIMP-2) in Plasma from Patients with Neurodegenerative Dementia. - Tuna, Gamze; Yener, Görsev Gülmen; Oktay, Gülgün; İşlekel, Gül Hüray; Kİrkalİ, Fatoş Güldal (J Alzheimers Dis, 2018)
Matrix metalloproteinases (MMPs) are substantial regulators of learning and memory and might be involved in neurodegeneration. It is known that MMPs are involved in pathogenesis of Alzheimer's disease (AD) and are particularly involved in the amyloid-β processing pathway. However, information on circulating levels of these proteins and their tissue inhibitors (TIMPs) in AD and other neurodegenerative dementia (ND) diseases such as dementia with Lewy bodies (DLB) and frontotemporal dementia (FTD) is not clear. Therefore, this study was directed toward finding out how plasma levels of MMP-2, MMP-9, TIMP-1, and TIMP-2 vary in AD, DLB, and FTD; and investigating the correlation of the levels of MMPs and their inhibitors with clinical parameters of the patients. MMP-2, MMP-9, TIMP-1, and TIMP-2 levels were measured by enzyme linked immunosorbent assay (ELISA). Plasma MMP-2 levels were significantly lower in all the patient groups than in the age-matched healthy controls (HCs) (p < 0.05). MMP-9 levels were significantly lower in the FTD patients than in the HCs (p < 0.05). Also, TIMP-1 levels were lower in the AD and FTD patients than in the HCs (p < 0.05). TIMP-2 levels were similar in all the groups. These findings highlight the importance of circulating MMPs in ND and suggest that MMPs and their inhibitors might play a role in impaired amyloid-β peptide metabolism which is responsible for the genesis and progression of ND. Furthermore, measurement of MMP-2 and MMP-9 and their inhibitors may be of great importance for large scale basic research and clinical studies of ND.

Exploring the Profile of Incidental Memory in Patients with Amnestic Mild Cognitive Impairment and Mild Alzheimer's Disease. - Kontaxopoulou, Dionysia; Beratis, Ion N; Fragkiadaki, Stella; Pavlou, Dimosthenis; Andronas, Nikos; Yannis, George; Economou, Alexandra; Papanicolaou, Andrew C; Papageorgiou, Sokratis G (J Alzheimers Dis, 2018)
Incidental memory can be defined as the ability to acquire information unintentionally. The present study investigated incidental memory performance in amnestic mild cognitive impairment (aMCI) and mild Alzheimer's disease (AD) patients; additionally, hippocampal atrophy between groupswas examined. Twenty-nine aMCI patients (14 with hippocampal atrophy, measured by the Medial Temporal Lobe Atrophy scale), 15 mild AD patients, and 20 cognitively intact individuals underwent a detailed medical and neuropsychological assessment examining intentional memory, using the Hopkins Verbal Learning Test-Revised and the Brief Visuospatial Memory Test. Participants first took part in a driving simulator experiment, followed by an unexpected incidental memory questionnaire referring to elements related to the driving simulation. The mild AD group performed worse than the aMCI group and the control group both in incidental and intentional memory tasks, whereas the aMCI group differed significantly from the control group only in the intentional memory tasks. The incidental recognition memory task was the only measure that differed between aMCI patients with and without hippocampal atrophy. Moreover, incidental memory tasks were the only measures that correlated significantly with both left and right hippocampal atrophy. The current findings indicate that incidental memory testing may provide potentially useful information for detecting aMCI patients with greater hippocampal atrophy, who may be considered at higher risk of developing dementia due to AD.

Exposure to General Anesthesia and Risk of Dementia: A Nationwide Population-Based Cohort Study. - Kim, Clara Tammy; Myung, Woojae; Lewis, Matthew; Lee, Hyewon; Kim, Satbyul Estella; Lee, Kyungsang; Lee, Chunsoo; Choi, Junbae; Kim, Ho; Carroll, Bernard J; Kim, Doh Kwan (J Alzheimers Dis, 2018)
BACKGROUND: There is a growing concern that general anesthesia could increase the risk of dementia. However, the relationship between anesthesia and subsequent dementia is still undetermined. OBJECTIVE: To determine whether the risk of dementia increases after exposure to general anesthesia. METHODS: A population-based prospective cohort study analyzing the Korean National Health Insurance Service-National Sample Cohort database was conducted of all persons aged over 50 years (n = 219,423) from 1 January 2003 and 31 December 2013. RESULTS: 44,956 in the general anesthesia group and 174,469 in the control group were followed for 12 years. The risk of dementia associated with previous exposure to general anesthesia was increased after adjusting for all covariates such as gender, age, health care visit frequency, and co-morbidities (Hazard ratio = 1.285, 95% confidence interval = 1.262-1.384, time-varying Cox hazard model). In addition, the number of anesthetic agents administered, the number of exposures to general anesthesia, the cumulative exposure time, and the organ category involved in surgery were associated with risk of dementia. CONCLUSION: In light of the increasing societal burden of dementia, careful surveillance for dementia and prevention guidelines for patients after general anesthesia are needed.

Exposure to Strong Anticholinergic Medications and Dementia-Related Neuropathology in a Community-Based Autopsy Cohort. - Gray, Shelly L; Anderson, Melissa L; Hanlon, Joseph T; Dublin, Sascha; Walker, Rod L; Hubbard, Rebecca A; Yu, Onchee; Montine, Thomas J; Crane, Paul K; Sonnen, Josh A; Keene, C Dirk; Larson, Eric B (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic medication exposure has been associated with increased risk for dementia. No study has examined the association between anticholinergic medication use and neuropathologic lesions in a community-based sample. OBJECTIVE: To examine the relationship between anticholinergic exposure and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N = 420), we ascertained use of anticholinergic medications over a 10-year period from automated pharmacy data and calculated total standardized daily doses (TSDD). We used modified Poisson regression to calculate adjusted relative risks (RRs) and 95% confidence intervals (CIs) for the association between anticholinergic exposure and dementia-associated neuropathology. Inverse probability weighting was used to account for selection into the autopsy cohort. RESULTS: Heavy anticholinergic exposure (≥1,096 TSDD) was not associated with greater neuropathologic changes of Alzheimer's disease; the adjusted RRs for heavy use of anticholinergics (≥1,096 TSDD) compared to no use were 1.22 (95% CI 0.81-1.88) for neuritic plaque scores and 0.89 (0.47-1.66) for extent of neurofibrillary degeneration. Moderate (91-1,095 TSDD) and heavy use of anticholinergics was associated with a significantly lower cerebral microinfarct burden compared with no use with adjusted RRs of 0.44 (0.21-0.89) and 0.24 (0.09-0.62), respectively. Anticholinergic exposure was not associated with macroscopic infarcts or atherosclerosis. CONCLUSIONS: Use of anticholinergic medications is not associated with Alzheimer's disease-related neuropathologic changes but is associated with lower cerebral microinfarct burden. Further research into biological mechanisms underlying the anticholinergic-dementia link is warranteds.

Expression Profiling of Cytokine, Cholinergic Markers, and Amyloid-β Deposition in the APPSWE/PS1dE9 Mouse Model of Alzheimer's Disease Pathology. - Reale, Marcella; D'Angelo, Chiara; Costantini, Erica; Di Nicola, Marta; Yarla, Nagnedra Sastry; Kamal, Mohammad Amjad; Salvador, Nieves; Perry, George (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD), a neurodegenerative disease, is associated with dysfunction of the olfactory and the entorhinal cortex of the brain that control memory and cognitive functions and other daily activities. Pro-inflammatory cytokines, amyloid-β (Aβ), and the cholinergic system play vital roles in the pathophysiology of AD. However, the role of changes in cholinergic system components, Aβ accumulation, and cytokines in both the olfactory and entorhinal cortex is not known clearly. OBJECTIVE: The present study is aimed to evaluate the changes of cholinergic system components, Aβ accumulation, and cytokines in both the olfactory bulb (OB) and entorhinal cortex (EC) of young and aged APPSWE/PS1dE9 transgenic (Tg) mice. METHODS: We have explored the changes of cholinergic system components, Aβ accumulation, and expression profiling of cytokines in the OB and EC of aged APPswe transgenic mice and age-matched wild type mice using quantitative Real-Time PCR assays and immunohistochemistry techniques. RESULTS: In aged Tg mice, a significant increase of expression of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and chemokine MCP1 (p < 0.001, p < 0.001, and p = 0.001, respectively) and a significant reduction of nAChRα4 (p = 0.048) and AChE (p = 0.023) was observed when compared with age-matched wild type mice. Higher levels of AChE and BuChE are expressed in OB and EC of the APPSWE/PS1dE9 of Tg mice. Aβ accumulation was observed in OB and EC of the APPSWE/PS1dE9 of Tg mice. CONCLUSION: The study demonstrates the expression profiling of pro-inflammatory cytokines and cholinergic markers as well as Aβ accumulation in OB and EC of the APPSWE/PS1dE9 Tg mice. Moreover, the study also demonstrated that the APPSWE/PS1dE9 Tg mice can be useful as a mouse model to understand the role of pro-inflammatory cytokines and cholinergic markers in pathophysiology of AD.

Free Heme and Amyloid-β: A Fatal Liaison in Alzheimer's Disease. - Chiziane, Elisabeth; Telemann, Henriette; Krueger, Martin; Adler, Juliane; Arnhold, Jürgen; Alia, A; Flemmig, Jörg (J Alzheimers Dis, 2018)
While the etiology of Alzheimer's disease (AD) is still unknown, an increased formation of amyloid-β (Aβ) peptide and oxidative processes are major pathological mechanism of the disease. The interaction of Aβ with free heme leads to the formation of peroxidase-active Aβ-heme complexes. However, enzyme-kinetic data and systematic mutational studies are still missing. These aspects were addressed in this study to evaluate the role of Aβ-heme complexes in AD. The enzyme-kinetic measurements showed peroxidase-specific pH- and H2O2-dependencies. In addition, the enzymatic activity of Aβ-heme complexes constantly increased at higher peptide excess. Moreover, the role of the Aβ sequence for the named enzymatic activity was tested, depicting human-specific R5, Y10, and H13 as essential amino acids. Also by studying Y10 as an endogenous peroxidase substrate for Aβ-heme complexes, ratio-specific effects were observed, showing an optimal dityrosine formation at an about 40-fold peptide excess. As dityrosine formation promotes Aβ fibrillation while free heme disturbs protein aggregation, we also investigated the effect of Aβ-heme complex-derived peroxidase activity on the formation of Aβ fibrils. The fluorescence measurements showed a different fibrillation behavior at strong peroxidase activity, leading also to altered fibril morphologies. The latter was detected by electron microscopy. As illustrated by selected in vivo measurements on a mouse model of AD, the disease is also characterized by Aβ-derived microvessel destructions and hemolytic processes. Thus, thrombo-hemorrhagic events are discussed as a source for free heme in brain tissue. In summary, we suggest the formation and enzymatic activity of Aβ-heme complexes as pathological key features of AD.
Keywords: Alzheimer Disease; Amino Acid Sequence; Amyloid; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Heme; Humans; Hydrogen Peroxide; Mice; Mice, Transgenic; Oxidation-Reduction; Peptide Fragments; Peroxidases

A Free Radical-Generating System Regulates Amyloid Oligomers: Involvement of Cathepsin B. - Llorente, Patricia; Kristen, Henrike; Sastre, Isabel; Toledano-Zaragoza, Ana; Aldudo, Jesús; Recuero, María; Bullido, Maria J (J Alzheimers Dis, 2018)
Amyloid-β (Aβ), a major component of senile plaques, is generated via the proteolysis of amyloid-β protein precursor (AβPP). This cleavage also produces AβPP fragment-derived oligomers which can be highly neurotoxic. AβPP metabolism/processing is affected by many factors, one of which is oxidative stress (OS). Associated with aging, OS is an important risk factor for Alzheimer's disease. In addition, the protein degradation systems, especially those involving cathepsins, are impaired in aging brains. Moreover, cathepsin B (CTSB) is a cysteine protease with potentially specific roles in AβPP proteolysis (β-secretase activity) and Aβ clearance (Aβ degradative activity). The present work examines the effect of OS and the involvement of CTSB in amyloid oligomer formation. The xanthine/xanthine oxidase (X-XOD) free radical generating system induced the partial inhibition of CTSB activity, which was accompanied by an increase in large amyloid oligomers. These were located throughout the cytosol and in endo-lysosomal vesicles. Cells treated with the CTSB inhibitor CA-074Me also showed increased amyloid oligomer levels, whereas those subjected to OS in the presence of the inhibitor showed no such increase. However, CTSB inhibition clearly modulated the AβPP metabolism/processing induced by X-XOD, as revealed by the increase in intracellular AβPP and secreted α-secretase-cleaved soluble AβPP. The present results suggest that CTSB participates in the changes of amyloid oligomer induced by mild OS.

Gait in Mild Alzheimer's Disease: Feasibility of Multi-Center Measurement in the Clinic and Home with Body-Worn Sensors: A Pilot Study. - Mc Ardle, Ríona; Morris, Rosie; Hickey, Aodhán; Del Din, Silvia; Koychev, Ivan; Gunn, Roger N; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; et al. (J Alzheimers Dis, 2018)
Gait is emerging as a potential diagnostic tool for cognitive decline. The 'Deep and Frequent Phenotyping for Experimental Medicine in Dementia Study' (D&FP) is a multicenter feasibility study embedded in the United Kingdom Dementia Platform designed to determine participant acceptability and feasibility of extensive and repeated phenotyping to determine the optimal combination of biomarkers to detect disease progression and identify early risk of Alzheimer's disease (AD). Gait is included as a clinical biomarker. The tools to quantify gait in the clinic and home, and suitability for multi-center application have not been examined. Six centers from the National Institute for Health Research Translational Research Collaboration in Dementia initiative recruited 20 individuals with early onset AD. Participants wore a single wearable (tri-axial accelerometer) and completed both clinic-based and free-living gait assessment. A series of macro (behavioral) and micro (spatiotemporal) characteristics were derived from the resultant data using previously validated algorithms. Results indicate good participant acceptability, and potential for use of body-worn sensors in both the clinic and the home. Recommendations for future studies have been provided. Gait has been demonstrated to be a feasible and suitable measure, and future research should examine its suitability as a biomarker in AD.

Gene Transfer Induced Hypercholesterolemia in Amyloid Mice. - Grames, Mychal S; Dayton, Robert D; Lu, Xiaohong; Schilke, Robert M; Alexander, J Steven; Orr, A Wayne; Barmada, Sami J; Woolard, Matthew D; Klein, Ronald L (J Alzheimers Dis, 2018)
A risk factor for cardiovascular disease (CVD), mutant PCSK9, was expressed in APP/PS1 mice to study the CVD-Alzheimer's disease inter-relationship. Cholesterol levels were elevated by 5-6-fold from 3 to 13 weeks after PCSK9 gene transfer. We tested whether hypercholesterolemia would increase amyloid-β plaques at a relatively early stage of plaque deposition. Plaque burden was increased in the hippocampus of PCSK9 treated mice though the increase was modest compared to the large elevation in cholesterol. Elevating cholesterol via gene transfer could be valuable in a variety of disease models compared to making crosses with germ-line transgenic mouse models of CVD.

Generation of a New Tau Knockout (tauΔex1) Line Using CRISPR/Cas9 Genome Editing in Mice. - Tan, Daniel C S; Yao, Sherilyn; Ittner, Arne; Bertz, Josefine; Ke, Yazi D; Ittner, Lars M; Delerue, Fabien (J Alzheimers Dis, 2018)
Alzheimer's disease and other dementias present with tau pathology. Several mouse lines with knockout of the tau-encoding Mapt gene have been reported, yet findings often differed between lines and sites. Here, we report a new tau knockout strain (tauΔex1), generated by CRISPR/Cas9-mediated genome editing of intron -1/exon 1 of Mapt in C57Bl/6J mice. TauΔex1 mice had no overt phenotype, but, in line with previous models, they showed a significantly reduced susceptibility to excitotoxic seizures, with normal memory formation in young mice. This new in vivo resource will be made freely available to the research community.

Genetic Risk for Age-Related Cognitive Impairment Does Not Predict Cognitive Performance in Middle Age. - Korthauer, Laura E; Awe, Elizabeth; Frahmand, Marijam; Driscoll, Ira (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by memory loss and executive dysfunction, which correspond to structural changes to the medial temporal lobes (MTL) and prefrontal cortex (PFC), respectively. Given the overlap in cognitive deficits between healthy aging and the earliest stages of AD, early detection of AD remains a challenge. The goal of the present study was to study MTL- and PFC-dependent cognitive functioning in middle-aged individuals at genetic risk for AD or cognitive impairment who do not currently manifest any clinical symptoms. Participants (N = 150; aged 40-60 years) underwent genotyping of 47 single nucleotide polymorphisms (SNPs) in six genes previously associated with memory or executive functioning: APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT. They completed two MTL-dependent tasks, the virtual Morris Water Task (vMWT) and transverse patterning discriminations task (TPDT), and the PFC-dependent reversal learning task. Although age was associated with poorer performance on the vMWT and TPDT within this middle-aged sample, there were no genotype-associated differences in cognitive performance. Although the vMWT and TPDT may be sensitive to age-related changes in cognition, carriers of APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT risk alleles do not exhibit alteration in MTL- and PFC-dependent functioning in middle age compared to non-carriers.

Glia Maturation Factor and Mast Cell-Dependent Expression of Inflammatory Mediators and Proteinase Activated Receptor-2 in Neuroinflammation. - Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Ahmed, Mohammad Ejaz; Zaheer, Smita; Kumar, Keerthana Kuppamma; Yelam, Anudeep; Kaur, Harleen; Dubova, Iuliia; Raikwar, Sudhanshu P; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Parkinson's disease (PD) is characterized by the presence of inflammation-mediated dopaminergic neurodegeneration in the substantia nigra. Inflammatory mediators from activated microglia, astrocytes, neurons, T-cells and mast cells mediate neuroinflammation and neurodegeneration. Administration of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induces PD like motor deficits in rodents. 1-methyl-4-phenylpyridinium (MPP+), a toxic metabolite of MPTP activates glial cells, neurons and mast cells to release neuroinflammatory mediators. Glia maturation factor (GMF), mast cells and proteinase activated receptor-2 (PAR-2) are implicated in neuroinflammation. Alpha-synuclein which induces neurodegeneration increases PAR-2 expression in the brain. However, the exact mechanisms are not yet understood. In this study, we quantified inflammatory mediators in the brains of MPTP-administered wild type (Wt), GMF-knockout (GMF-KO), and mast cell knockout (MC-KO) mice. Additionally, we analyzed the effect of MPP+, GMF, and mast cell proteases on PAR-2 expression in astrocytes and neurons in vitro. Results show that the levels of interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and the chemokine (C-C motif) ligand 2 (CCL2) were lesser in the brains of GMF-KO mice and MC-KO mice when compared to Wt mice brain after MPTP administration. Incubation of astrocytes and neurons with MPP+, GMF, and mouse mast cell protease-6 (MMCP-6) and MMCP-7 increased the expression of PAR-2. Our studies show that the absence of mast cells and GMF reduce the expression of neuroinflammatory mediators in the brain. We conclude that GMF along with mast cell interactions with glial cells and neurons during neuroinflammation can be explored as a new therapeutic target for PD and other neuroinflammatory disorders.

Healthy versus Entorhinal Cortical Atrophy Identification in Asymptomatic APOE4 Carriers at Risk for Alzheimer's Disease. - Konishi, Kyoko; Joober, Ridha; Poirier, Judes; MacDonald, Kathleen; Chakravarty, Mallar; Patel, Raihaan; Breitner, John; Bohbot, Véronique D (J Alzheimers Dis, 2018)
Early detection of Alzheimer's disease (AD) has been challenging as current biomarkers are invasive and costly. Strong predictors of future AD diagnosis include lower volume of the hippocampus and entorhinal cortex, as well as the ɛ4 allele of the Apolipoprotein E gene (APOE) gene. Therefore, studying functions that are critically mediated by the hippocampus and entorhinal cortex, such as spatial memory, in APOE ɛ4 allele carriers, may be key to the identification of individuals at risk of AD, prior to the manifestation of cognitive impairments. Using a virtual navigation task developed in-house, specifically designed to assess spatial versus non-spatial strategies, the current study is the first to differentiate functional and structural differences within APOE ɛ4 allele carriers. APOE ɛ4 allele carriers that predominantly use non-spatial strategies have decreased fMRI activity in the hippocampus and increased atrophy in the hippocampus, entorhinal cortex, and fimbria compared to APOE ɛ4 allele carriers who use spatial strategies. In contrast, APOE ɛ4 allele carriers who use spatial strategies have grey matter levels comparable to non-APOE ɛ4 allele carriers. Furthermore, in a leave-one-out analysis, grey matter in the entorhinal cortex could predict navigational strategy with 92% accuracy.
Keywords: Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Atrophy; Case-Control Studies; Entorhinal Cortex; Female; Heterozygote; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors; Spatial Memory

Heparin Modulates the Kinetics of Zinc-Induced Aggregation of Amyloid-β Peptides. - Radko, Sergey P; Khmeleva, Svetlana A; Mantsyzov, Alexey B; Kiseleva, Yana Y; Mitkevich, Vladimir A; Kozin, Sergey A; Makarov, Alexander A (J Alzheimers Dis, 2018)
Zinc-induced aggregation of amyloid-β peptides (Aβ) is considered to contribute to the pathogenesis of Alzheimer's disease. While glycosaminoglycans (GAGs) that are commonly present in interneuronal space are known to enhance Aβ self-aggregation in vitro, the impact of GAGs on the formation of zinc-induced amorphous Aβ aggregates has not yet been thoroughly studied. Here, employing dynamic light scattering, bis-ANS fluorimetry, and sedimentation assays, we demonstrate that heparin serving as a representative GAG modulates the kinetics of zinc-induced Aβ42 aggregation in vitro by slowing the rate of aggregate formation and aggregate size growth. By using synthetic Aβ16 peptides to model the Aβ metal-binding domain (MBD), heparin was found to effectively interact with MBDs in complex with zinc ions. We suggest that heparin adsorbs to the surface of growing zinc-induced Aβ42 aggregates via electrostatic interactions, thus creating a steric hindrance that inhibits further inclusion of monomeric and/or oligomeric zinc-Aβ42 complexes. Furthermore, the adsorbed heparin can interfere with the zinc-bridging mechanism of Aβ42 aggregation, requiring the formation of two zinc-mediated interaction interfaces in the MBD. As revealed by computer simulations of the zinc-Aβ16 homodimer complexed with a heparin chain, heparin can interact with the MBD via polar contacts with residues Arg-5 and Tyr-10, resulting in a conformational rearrangement that hampers the formation of the second zinc-mediated interaction in the MBD interface. The findings of this study suggest that GAGs, which are common in the in vivo macromolecular environment, may have a substantial impact on the time course of zinc-induced Aβ aggregation.

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

High-Density Lipoprotein Subclasses and Mild Cognitive Impairment: Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia)1. - Ohtani, Ryo; Nirengi, Shinsuke; Nakamura, Michikazu; Murase, Nagako; Sainouchi, Makoto; Kuwata, Yasuhiro; Takata, Masaki; Masuda, Yuuichi; Kotani, Kazuhiko; Sakane, Naoki (J Alzheimers Dis, 2018)
BACKGROUND: High-density lipoprotein (HDL) containing apolipoprotein A-I is associated with the pathogenesis of Alzheimer's disease (AD). HDL particle size is modified in the presence of pathological conditions, while the significance of the HDL particle size remains controversial. OBJECTIVE: The aim of this study was to investigate the HDL lipoprotein subclasses in mild cognitive impairment (MCI) and AD. METHODS: This cross-sectional study included 20 AD patients, 17 MCI patients, and 17 age-matched controls without cognitive impairment, selected from the database of the Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia) registry. The diagnoses of AD and MCI were performed by expert neurologists according to the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition criteria. Serum HDL subclasses were measured by electrophoretic separation of lipoproteins using the Lipoprint System. The neutrophil-lymphocyte ratio (NLR), a marker of inflammation, was calculated by dividing the neutrophil count by the lymphocyte count. RESULTS: Small-sized HDL particle levels in the MCI group were significantly higher than in the control group, although there was no difference in serum HDL-cholesterol levels between MCI and control groups. NLR in the MCI group was higher than in the control group, but this difference was non-significant (p = 0.09). There was no difference in HDL subclasses or NLR between the AD and control groups. CONCLUSION: These findings suggest that HDL subclasses might be associated with the development of MCI.

Higher Blood Vitamin C Levels are Associated with Reduction of Apolipoprotein E E4-related Risks of Cognitive Decline in Women: The Nakajima Study. - Noguchi-Shinohara, Moeko; Abe, Chiemi; Yuki-Nozaki, Sohshi; Dohmoto, Chiaki; Mori, Ayaka; Hayashi, Koji; Shibata, Syutaro; Ikeda, Yoshihisa; Sakai, Kenji; Iwasa, Kazuo; Yokogawa, Masami; Ishimiya, Mai; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Antioxidants like vitamins C and E may minimize the risk for Alzheimer's disease. OBJECTIVE: We examined whether vitamins C and E modify the apolipoprotein E (APOE) E4-related risks for developing cognitive decline. METHODS: We conducted a population-based prospective study including Japanese residents aged 65 years from Nakajima, Japan. The participants received an evaluation of cognitive function and underwent blood tests including tests for vitamins C and E levels and APOE phenotypes. The APOE E4-by-gender-by-vitamin C or E interactions on developing cognitive decline were analyzed. RESULTS: Of 606 participants with normal cognitive function determined using a baseline survey (2007-2008), 349 completed the follow up survey between 2014 and 2016. In women with APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin C concentration tertile [multivariate OR 0.10 (95% CI 0.01-0.93)] compared with the lowest tertile. In men without APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin E concentration tertile [multivariate OR 0.19 (0.05-0.74)] as compared with the lowest tertile. CONCLUSION: Our results demonstrate significant beneficial effects of vitamins C and E in reducing the risk of cognitive decline in women with APOE E4 and men without APOE E4, respectively.

Hippocampal Sclerosis in the Oldest Old: A Finnish Population-Based Study. - Kero, Mia; Raunio, Anna; Polvikoski, Tuomo; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2018)
BACKGROUND: There are only few population-based studies that have systemically investigated the prevalence of hippocampal sclerosis (HS) in the very old. The frequency of unilateral versus bilateral HS has been rarely studied. OBJECTIVE: We investigated the prevalence and laterality of HS and its association with other neurodegenerative and vascular pathologies in a population-based sample of very elderly. Furthermore, the concomitant presence of immunoreactivity for TDP-43, p62, and HPtau was studied. METHODS: The population-based Vantaa 85+ study includes all inhabitants of the city of Vantaa, who were >85 years in 1991 (n = 601). Neuropathological assessment was possible in 302 subjects. Severity of neuronal loss of CA sectors and subiculum was determined bilaterally by HE- staining. Immunohistochemistry performed using antibodies for TDP-43, p62, and HPtau. RESULTS: Neuronal loss and pathological changes in the hippocampus sector CA1 and subiculum were observed in 47 of the 302 individuals (16%), and 51% of these changes were bilateral. HS without comorbid neurodegenerative pathology was found in 1/47 subjects with HS (2%). Dementia (p < 0.001) and TDP-43 immunopositivity of the granular cell layer of the dentate fascia (p < 0.001) were strongly associated with HS. The CERAD score, immunopositivity for HPtau and p62 in the granular cell layer of the fascia dentate were also associated. CONCLUSION: HS is prevalent (16%) in the oldest old population, but HS without any comorbid neurodegenerative pathology is rare. The high frequency of unilateral HS (49%) implied that bilateral sampling of hippocampi should be routine practice in neuropathological examination.

Hospitalization after Oral Antibiotic Initiation in Finnish Community Dwellers with and without Alzheimer's Disease: Retrospective Register-Based Cohort Study. - Järvinen, Heli; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Tolppanen, Anna-Maija; Hartikainen, Sirpa (J Alzheimers Dis, 2018)
BACKGROUND: Persons with Alzheimer's disease (AD) are frequently hospitalized from infection-related causes. There are no previous studies investigating hospitalization associated with antibiotic initiation in persons with AD. OBJECTIVE: To investigate the frequency and risk of hospitalization associated with oral antibiotic initiation among community dwellers with and without AD. METHODS: We performed a retrospective register-based study utilizing register-based Medication Use and Alzheimer's disease (MEDALZ) cohort. It includes all community dwellers diagnosed with AD during 2005-2011 in Finland and their matched comparison persons without AD. Antibiotic use was initiated by 34,785 persons with and 36,428 without AD. Drug use data were collected from Prescription Register and comorbidities from Special Reimbursement and Hospital Care Registers. Infection diagnoses were collected from the Hospital Care Register. Factors associated with hospitalization were estimated utilizing logistic regression models. RESULTS: Risk of hospitalization following antibiotic initiation was higher among antibiotic initiators with AD than without AD (adjusted odds ratio, aOR, 1.37, 95% Cl 1.28-1.46).Strongest association with hospitalization was found for oral glucocorticoid use, aOR 1.41 (1.25-1.59); epilepsy, aOR 1.33 (1.10-1.63); and active cancer, aOR 1.30 (1.14-1.49). Among initiators of cephalexin, pivmecillinam, amoxicillin/amoxicillin, and enzyme inhibitor and doxycycline, persons with AD were more frequently hospitalized than persons without AD. A quarter of hospitalized antibiotic initiators had infection diagnosis in their hospital care records. CONCLUSIONS: Persons with AD initiating an antibiotic had a higher risk for hospitalization than antibiotic initiators without AD. Further research is needed to determine whether infection-related hospitalization could be reduced.

Humanin Exerts Neuroprotection During Cardiac Ischemia-Reperfusion Injury. - Kumfu, Sirinart; Charununtakorn, Savitree T; Jaiwongkam, Thidarat; Chattipakorn, Nipon; Chattipakorn, Siriporn C (J Alzheimers Dis, 2018)
Cardiac ischemia-reperfusion (I/R) injury has been shown to impair brain function. Humanin analogue (HNG) given prior to cardiac ischemia has been shown to attenuate both heart and brain mitochondrial dysfunction caused by cardiac I/R injury. In a clinical setting, patients received medical treatment for acute myocardial infarction either during or after the onset of myocardial ischemia; thus, in this study, we tested the hypothesis that the administration of HNG during cardiac I/R injury has therapeutic potential for brain protection. Thirty-six male Wistar rats were divided into two groups: a cardiac I/R group (n = 30), and a sham group (n = 6). The I/R rats were then divided into five subgroups to receive: 1) vehicle; 2) HNG (84 μg/kg); 3) HNG (168 μg/kg); 4) HNG (252 μg/kg) intravenously administered during the cardiac-ischemia; and 5) HNG at 252 μg/kg given at the onset of reperfusion. At the end of treatment, brains were removed for determination of blood-brain barrier (BBB) breakdown, oxidative stress, brain mitochondrial function, brain mitochondrial dynamics, p-tau, amyloid-β (Aβ) and apoptosis. HNG at a dose of 168 and 252 μg/kg administered during ischemia, and 252 μg/kg given at the onset of reperfusion effectively attenuated the brain mitochondrial dysfunction, tau hyperphosphorylation and Aβ accumulation, and apoptosis, without reducing BBB breakdown, brain oxidative stress, or mitochondrial dynamic, caused by cardiac I/R injury. In conclusion, humanin exerted neuroprotection during induced cardiac I/R injury via improvement in brain mitochondrial function, and the reduction of Alzheimer's disease pathology and apoptosis.
Keywords: Animals; Apoptosis; Blood-Brain Barrier; Brain; Intracellular Signaling Peptides and Proteins; Male; Microscopy, Electron; Mitochondria; Myocardial Reperfusion Injury; Neurons; Neuroprotection; Neuroprotective Agents; Oxidative Stress; Rats; Rats, Wistar; Signal Transduction

Hypoxia-Induced Signaling Activation in Neurodegenerative Diseases: Targets for New Therapeutic Strategies. - Jha, Niraj Kumar; Jha, Saurabh Kumar; Sharma, Renu; Kumar, Dhiraj; Ambasta, Rashmi K; Kumar, Pravir (J Alzheimers Dis, 2018)
For the maintenance of cellular homeostasis and energy metabolism, an uninterrupted supply of oxygen (O2) is routinely required in the brain. However, under the impaired level of O2 (hypoxia) or reduced blood flow (ischemia), the tissues are not sufficiently oxygenated, which triggers disruption of cellular homeostasis in the brain. Hypoxia is known to have a notable effect on controlling the expression of proteins involved in a broad range of biological processes varying from energy metabolism, erythropoiesis, angiogenesis, neurogenesis to mitochondrial trafficking and autophagy, thus facilitating neuronal cells to endure in deprived O2. On the contrary, hypoxia to the brain is a major source of morbidity and mortality in humans culminating in cognitive impairment, gradual muscle weakness, loss of motor activity, speech deficit, and paralysis as well as other pathological consequences. Further, hypoxia resulting in reduced O2 deliveries to brain tissues is supposed to cause neurodegeneration in both in vivo and in vitro models. Similarly, chronic exposure to hypoxia has also been reportedly involved in defective vessel formation. Such vascular abnormalities lead to altered blood flow, reduced nutrient delivery, and entry of otherwise restricted infiltrates, thereby limiting O2 availability to the brain and causing neurological disabilities. Moreover, the precise mechanistic role played by hypoxia in mediating key processes of the brain and alternatively, in triggering pathological signals associated with neurodegeneration remains mysterious. Therefore, this review elucidates the intricate role played by hypoxia in modulating crucial processes of the brain and their severity in neuronal damage. Additionally, the involvement of numerous pharmacological approaches to compensate hypoxia-induced neuronal damage has also been addressed, which may be considered as a potential therapeutic approach in hypoxia-mediated neurodegeneration.

Imaging Biomarkers of Neurodegeneration in Alzheimer's Disease: Distinct Contributions of Cortical MRI Atrophy and FDG-PET Hypometabolism. - Benvenutto, Agnès; Giusiano, Bernard; Koric, Lejla; Gueriot, Claude; Didic, Mira; Felician, Olivier; Guye, Maxime; Guedj, Eric; Ceccaldi, Mathieu (J Alzheimers Dis, 2018)
BACKGROUND: Neurodegeneration biomarkers are routinely used in the diagnosis of Alzheimer's disease (AD). OBJECTIVE: To evaluate the respective contributions of two neuroimaging biomarkers, structural MRI and 18FDG-PET, in the assessment of neurodegeneration in AD dementia. METHODS: Patients with mild AD dementia diagnosed based on clinical and cerebrospinal fluid criteria and cognitively healthy subjects, from the Marseille cohort ADAge with cognitive, structural MRI and 18FDG-PET assessments, were included. Extent of atrophy on MRI and of hypometabolism on 18FDG-PET were individually evaluated in each patient using a voxel-based analysis on whole-brain approach and compared to healthy subjects. Patients were divided in distinct groups according to their atrophy extent on the one hand and to their hypometabolism extent on the other, then, to their imaging profile combining the extent of the two biomarkers. RESULTS: Fifty-two patients were included. The MMSE score was significantly lower in the "Extensive hypometabolism" group than in the "Limited hypometabolism" group (respectively 19.5/30 versus 23/30). A lower Innotest Amyloid Tau Index was associated with an extensive hypometabolism (p = 0.04). There were more patients with low educational level in the "Extensive atrophy" group, while a higher educational level was more found in the "Limited atrophy" group (p = 0.005). CONCLUSION: 18FDG-PET hypometabolism extent is associated with the pathological processes and clinical severity of AD, while MRI atrophy seems to be influenced by the cognitive reserve. In the context of mild AD dementia, these two biomarkers of neurodegeneration are thus not interchangeable and require to be considered in combination rather than in isolation.

The Impact of a Shared Decision-Making Training Program on Dementia Care Planning in Long-Term Care. - Mariani, Elena; Chattat, Rabih; Ottoboni, Giovanni; Koopmans, Raymond; Vernooij-Dassen, Myrra; Engels, Yvonne (J Alzheimers Dis, 2018)
BACKGROUND: Shared decision-making (SDM) can be a way for staff to adopt international recommendations advocating the involvement of nursing home residents and their family members in care planning and the development of personalized care plans. OBJECTIVE: The main aim was to analyze the effects of training nursing home staff in the implementation of SDM on agreement of residents' 'life-and-care plans' with the recommendations (primary outcome) and on family caregivers' quality of life and sense of competence, and staff's job satisfaction (secondary outcomes). METHODS: In the intervention condition, staff attended a training program on the use of SDM with residents and family caregivers in the care planning process. In the control condition, care planning as usual took place. For the primary outcome, in-depth qualitative and quantitative analyses of the care plans were performed. Multivariate Permutation Tests were applied to assess the impact on secondary outcomes. RESULTS: Forty-nine residents and family caregivers and 34 professionals were involved. Overall, many of the care plans developed during the intervention showed a high level of agreement with the care planning recommendations. Both Italian and Dutch care plans showed improvement in the number of clear problem statements (p < 0.001). In Italy, significant improvements (p < 0.05) were also found regarding specific care objectives, documentation of objectives met, and of residents and families' involvement. No impact was found on secondary outcomes. CONCLUSION: The involvement of residents and family caregivers in care planning contributed to an improvement of the residents' care plans, but it did not have an effect on family caregivers and staff outcomes.

Impact of a Virtual Dementia Experience on Medical and Pharmacy Students' Knowledge and Attitudes Toward People with Dementia: A Controlled Study. - Gilmartin-Thomas, Julia F-M; McNeil, John; Powell, Anne; Malone, Daniel T; Wolfe, Rory; Larson, Ian C; O'Reilly, Claire L; Kirkpatrick, Carl M; Kipen, Eva; Petrovich, Tanya; Bell, J Simon (J Alzheimers Dis, 2018)
BACKGROUND: Clinical practice guidelines for dementia highlight the importance of providing patient-centered care. This can be achieved by improving health professionals' attitudes and knowledge toward people with dementia. OBJECTIVE: Quantitatively evaluate the impact of a virtual dementia experience on medical and pharmacy students' knowledge and attitudes toward people with dementia. METHODS: A non-randomized controlled study from September-October 2016. The intervention group received a 1.5-hour multisensory, virtual simulation of light, sound, color, and visual content to experience the cognitive and perceptual difficulties faced by people with dementia. Controls participated in the standard curriculum only. All students were invited to complete the 20-item Dementia Attitudes Scale (DAS) pre- and post-intervention. RESULTS: A total of 278 students (n = 64 medical, n = 214 pharmacy) were analyzed (n = 80 intervention, n = 198 control). The majority of students were female (n = 184, 66.2%), with an average age of 22.5 years. The intervention improved the DAS total score and subdomains of comfort and knowledge (p < 0.001). CONCLUSION: The intervention had a positive impact on medical and pharmacy students' knowledge and attitudes toward people with dementia.
Keywords: Australia; Curriculum; Dementia; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Students, Medical; Students, Pharmacy; Virtual Reality; Young Adult

The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

The Impact of Hospitalization on Readmission, Institutionalization, and Mortality of People with Dementia: A Systematic Review and Meta-Analysis. - Lehmann, Jana; Michalowsky, Bernhard; Kaczynski, Anika; Thyrian, Jochen René; Schenk, Nele Sophie; Esser, Alexander; Zwingmann, Ina; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: People with dementia (PwD) are at a high risk of hospitalization. Hospitals are often not adequately equipped for PwD and discharges often come unexpected. Therefore, PwD are at a risk of adverse outcomes. However, information about those outcomes is rare but crucial for the development of preventive strategies. OBJECTIVES: To conduct a quantitative systematic review and meta-analyses on the impact of a hospitalization on readmission, institutionalization, and mortality in PwD. To identify factors associated with these outcomes. METHODS: PubMed, CENTRAL, and ScienceDirect were searched for studies including terms for dementia, hospital, readmission, institutionalization, and mortality. Relevant were assessed by a quality criteria sheet. Results were summarized in a table. Meta-analysis was conducted with Review Manager 5.3. RESULTS: The search yielded 1,108 studies; 20 fulfilled the inclusion criteria and 10 studies were eligible for meta-analyses. The incidence and relative risk (RR) of mortality (RR 1.74 CI95 % 1.50, 2.05) and institutionalization (RR: 2.16 CI95 % 1.31, 3.56) of PwD was significantly higher when compared to people without dementia. Results according to readmission rate were inconsistent. Factors significantly associated with the examined adverse outcomes were severity of dementia, number of medications, and deficits in daily living activities. CONCLUSION: Hospitalization of PwD lead to adverse outcomes. An improvement in the identification of and care for PwD in the acute setting as well as in after care in the community setting, especially in the interface between both settings, is required to prevent adverse outcomes in hospitalized PwD.

Impact of Mild Cognitive Impairment on Mortality and Cause of Death in the Elderly. - Bae, Jong Bin; Han, Ji Won; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Kim, Tae Hui; Ryu, Seung-Ho; Moon, Seok Woo; Park, Joon Hyuk; Youn, Jong Chul; Lee, Dong Young; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Mild cognitive impairment (MCI) is a cognitive state that lies on the continuum between normal aging and dementia, and the prevalence of MCI is higher than dementia. However, the risk for mortality of people with MCI has been far less studied than that of people with dementia, and the population attributable risk percent (PAR%) of death attributable to MCI has not been estimated yet. OBJECTIVE: To investigate the impact of MCI on mortality and the cause of death in the elderly, and to estimate the PAR% of deaths attributable to MCI. METHODS: Data came from 7,315 elderly subjects aged ≥60 years without dementia from two cohort studies with diagnostic assessments of MCI at baseline. Deaths among participants were confirmed through the nationwide mortality database of Statistics Korea. RESULTS: MCI increased the risk of mortality in a multivariate Cox proportional model adjusting for age, sex, education, smoking, alcohol drinking, chronic illness, depression, vascular components, and cohort (hazard ratio = 1.59, 95% confidence interval 1.30, 1.94). PAR% of death attributable to MCI was 10.7% for age 65-74 years, 16.0% for age 75-84 years, and 24.2% for age ≥85 years. In the elderly with MCI, mortality risks from cerebrovascular disease, respiratory disease, and external causes were higher than in the cognitively normal elderly. CONCLUSIONS: Our results suggest that the mortality risk of MCI in Asian countries may be comparable to that in Western countries, and MCI can contribute to the death of the elderly as much as dementia.

Impact of Osteoporosis on the Risk of Dementia in Almost 60,000 Patients Followed in General Practices in Germany. - Kostev, Karel; Hadji, Peyman; Jacob, Louis (J Alzheimers Dis, 2018)
BACKGROUND: There has been in recent decades a growing interest in the relationship between osteoporosis and cognitive decline. OBJECTIVE: The goal of this study was to analyze the impact of osteoporosis on the risk of dementia in patients followed for up to 20 years in general practices in Germany. METHODS: This study included patients who received an initial diagnosis of osteoporosis and were followed by 1,215 general practitioners in Germany between January 1993 and December 2012 (index date). Controls were matched (1:1) to osteoporosis patients using propensity scores based on age, gender, index year, comorbidities, and co-therapies. Kaplan-Meier curves were performed to study the development of dementia separately in men and women with or without osteoporosis within 20 years of the index date. Cox proportional regression models were used to estimate the relationship between osteoporosis and dementia in men and women. RESULTS: The present study included 29,983 cases and 29,983 controls. After 20 years of follow-up, 20.5% of women with osteoporosis and 16.4% of controls had been diagnosed with dementia (log-rank p-value <0.001). At the end of the follow-up period, dementia was found in 22.0% of men previously diagnosed with osteoporosis and 14.9% of men without this chronic condition (log-rank p-value <0.001). Osteoporosis was associated with a 1.2-fold increase in the risk of being diagnosed with dementia in women and a 1.3-fold increase in the risk of being diagnosed with dementia in men. CONCLUSIONS: There was a positive association between osteoporosis and dementia in patients followed in general practices in Germany.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

Impaired IL-17 Production in Gut-Residing Immune Cells of 5xFAD Mice with Alzheimer's Disease Pathology. - Saksida, Tamara; Koprivica, Ivan; Vujičić, Milica; Stošić-Grujičić, Stanislava; Perović, Milka; Kanazir, Selma; Stojanović, Ivana (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulation of amyloid-β plaques that further promotes microglia-mediated neuroinflammatory responses and inflammation in the brain. Emerging data are revealing the relation between gut-associated lymphoid tissue (GALT) cells and CNS, as effector cells primed in the gut might home to the brain. This study aimed to determine cell composition of GALT in 5xFAD mice, an established model for AD. Immune cells isolated from Peyer's patches (PP) and mesenteric lymph nodes (MLN) were stained with surface and intracellular markers for T helper (Th) subpopulations, B lymphocytes and macrophages and analyzed cytofluorimetrically, while cytokine expression and production were determined by qPCR and ELISA, respectively. Inflammation was detected in GALT of 5xFAD mice with established AD pathology. Although the production of IFN-γ, IL-4, and IL-10 was comparable between the strains, lower IL-17 production was observed in PP and MLN cells. This phenomenon could not be attributed to a lower abundance of Th17 cells, or cytokines that initiate their formation or propagation (TGF-β, IL-6, and IL-23). Also, reduced IL-17 production was not a consequence of altered Il-17 mRNA transcription or deficiency of Rorγt, a key transcription factor for IL-17. However, the expression of miR-155 (a non-coding micro RNA that promotes the development of Th17 cells), was significantly lower in MLN cells of 5xFAD mice. In contrast, mice without AD neuropathology did not have inflammation in GALT or altered Th17 numbers, nor decreased IL-17 production. In conclusion, the observed changes in GALT of 5xFAD mice mirror the disease progression and might reflect inadequate immune surveillance in the gut and lead to enhanced AD pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; B-Lymphocytes; Disease Models, Animal; Female; Interleukin-17; Lymph Nodes; Male; Mice; Mice, Transgenic; MicroRNAs; Peyer's Patches; Th17 Cells

Impaired Spike Timing Dependent Cortico-Cortical Plasticity in Alzheimer's Disease Patients. - Di Lorenzo, Francesco; Ponzo, Viviana; Motta, Caterina; Bonní, Sonia; Picazio, Silvia; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro; Koch, Giacomo (J Alzheimers Dis, 2018)
BACKGROUND: Mechanisms of cortical plasticity have been recently investigated in Alzheimer's disease (AD) patients with transcranial magnetic stimulation protocols showing a clear impairment of long-term potentiation (LTP) cortical-like plasticity mechanisms. OBJECTIVE: We aimed to investigate mechanisms of cortico-cortical spike-timing dependent plasticity (STDP) in AD patients investigating the connections between posterior parietal cortex (PPC) and primary motor cortex (M1). METHODS: We used a cortico-cortical paired associative stimulation (cc-PAS) protocol to repeatedly activate the connection between PPC and M1 of the left-dominant hemisphere in a sample of fifteen AD patients and ten age-matched healthy subjects. PPC transcranial magnetic stimulation preceded (ccPAS +5) or followed M1 stimulation (ccPAS - 5) by 5 ms. Motor-evoked potentials (MEPs) were collected to assess the time course of the after effects of cc-PAS protocol measuring MEP amplitude as index of cortico-cortical associative plasticity. RESULTS: In healthy subjects, ccPAS - 5 protocol induced the expected long-lasting increase of MEP amplitude compatible with LTP-like cortical plasticity while PAS +5 protocol induced the opposite effect. AD patients did not show any significant modification of the amplitude of MEP after both ccPAS protocols. CONCLUSIONS: Our study shows that in AD patients the time-locked activation of human cortico-cortical connections is not able to form STDP, reflecting an impairment of a multi-factor plasticity process.

In Vitro Potency and Preclinical Pharmacokinetic Comparison of All-D-Enantiomeric Peptides Developed for the Treatment of Alzheimer's Disease. - Schartmann, Elena; Schemmert, Sarah; Niemietz, Nicole; Honold, Dominik; Ziehm, Tamar; Tusche, Markus; Elfgen, Anne; Gering, Ian; Brener, Oleksandr; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; et al. (J Alzheimers Dis, 2018)
Diffusible amyloid-β (Aβ) oligomers are currently presumed to be the most cytotoxic Aβ assembly and held responsible to trigger the pathogenesis of Alzheimer's disease (AD). Thus, Aβ oligomers are a prominent target in AD drug development. Previously, we reported on our solely D-enantiomeric peptide D3 and its derivatives as AD drug candidates. Here, we compare one of the most promising D3 derivatives, ANK6, with its tandem version (tANK6), and its head-to-tail cyclized isoform (cANK6r). In vitro tests investigating the D-peptides' potencies to inhibit Aβ aggregation, eliminate Aβ oligomers, and reduce Aβ-induced cytotoxicity revealed that all three D-peptides efficiently target Aβ. Subsequent preclinical pharmacokinetic studies of the three all-D-peptides in wildtype mice showed promising blood-brain barrier permeability with cANK6r yielding the highest levels in brain. The peptides' potencies to lower Aβ toxicity and their remarkable brain/plasma ratios make them promising AD drug candidates.

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Risk of Dementia in Subjective Cognitive Decline if CT Brain Changes are Present. - Sacuiu, Simona; Eckerström, Marie; Johansson, Lena; Kern, Silke; Sigström, Robert; Xinxin, Guo; Östling, Svante; Skoog, Ingmar (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive decline (SCD) has low predictive value for incident dementia. OBJECTIVES: We examined whether CT detectable brain changes add predictive value to SCD in a population sample with high scores on the Mini-Mental State Examination. METHODS: Subjective reports of memory and executive function were gathered in a non-demented population sample ≥70 years (n = 921). CT-brain was performed at baseline (n = 626). Brain atrophy, infarcts, and white matter lesions (WMLs) were classified using visual ratings. Dementia incidence was evaluated periodically during 12 years. RESULTS: The prevalence of SCD was 32.5% among individuals without dementia. During follow-up, 151 individuals (16.4%) developed dementia. The risk of dementia was increased in SCD, and increased further with WMLs and cortical atrophy present. However, the positive predictive values for incident dementia were low, 25% in SCD and 41% in SCD with WMLs and cortical atrophy. CONCLUSION: Our observations add clinical value to the use of SCD and CT to select relevant populations for interventions against dementia, but more stringent screening methods are necessary to reach individuals at risk.

Increasing Diagnostic Accuracy of Mild Cognitive Impairment due to Alzheimer's Disease by User-Independent, Web-Based Whole-Brain Volumetry. - Hedderich, Dennis M; Spiro, Judith E; Goldhardt, Oliver; Kaesmacher, Johannes; Wiestler, Benedikt; Yakushev, Igor; Zimmer, Claus; Boeckh-Behrens, Tobias; Grimmer, Timo (J Alzheimers Dis, 2018)
BACKGROUND: Volumetric quantification of structural MRI has been shown to increase the diagnostic accuracy of patients with mild cognitive impairment (MCI); however, its implementation in clinical routine is usually technically difficult and time-consuming. OBJECTIVE: The purpose of this study was to investigate whether volumetric information obtained from the free and easy-to-use online tool volBrain can improve correct identification of MCI patients with Alzheimer's disease (AD) compared to visual reading. METHODS: The study cohort consisted of 27 patients with MCI due to AD (AD positive) as determined by biomarker information and 26 cognitively normal controls (CN). Three blinded readers, 2 radiologists and 1 clinical dementia expert, assessed the patients' MRI regarding brain atrophy and probability of underlying AD two times, without and with supporting volumetric information from volBrain. To assess diagnostic accuracy of volBrain measures alone, a simple sum score based on basic volumetric measures was developed and tested. RESULTS: Correct patient classification by readers 1, 2, and 3 without a volumetric report was 73.6%, 77.4%, and 83.0%. With a volumetric report, correct classification increased for the radiological readers to 77.4% and 81.1%, respectively and decreased to 77.4% for reader 3. Usage of the volumetric report alone yielded the highest diagnostic accuracy of 84.9%. Diagnostic confidence increased significantly for radiological readers. CONCLUSION: Volumetric information from volBrain increases the radiologist's diagnostic performance and confidence in identifying MCI patients with AD. We propose that such tools may be implemented in the routine diagnostic work-up of patients with suspected AD.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

Inflammatory Cytokine, IL-1β, Regulates Glial Glutamate Transporter via microRNA-181a in vitro. - Zumkehr, Joannee; Rodriguez-Ortiz, Carlos J; Medeiros, Rodrigo; Kitazawa, Masashi (J Alzheimers Dis, 2018)
Glutamate overload triggers synaptic and neuronal loss that potentially contributes to neurodegenerative diseases including Alzheimer's disease (AD). Glutamate clearance and regulation at synaptic clefts is primarily mediated by glial glutamate transporter 1 (GLT-1). We determined that inflammatory cytokines significantly upregulated GLT-1 through microRNA-181a-mediated post-transcriptional modifications. Unveiling the key underlying mechanisms modulating GLT-1 helps better understand its physiological and pathological interactions with cytokines. Primary murine astrocyte and neuron co-culture received 20 ng/mL IL-1β, TNF-α, or IL-6 for 48 h. Soluble proteins or total RNA were extracted after treatment for further analyses. Treatment with inflammatory cytokines, IL-1β and TNF-α, but not IL-6, significantly increased GLT-1 steady-state levels (p≤0.05) without affecting mRNA levels, suggesting the cytokine-induced GLT-1 was regulated through post-transcriptional modifications. Among the candidate microRNAs predicted to modulate GLT-1, only microRNA-181a was significantly decreased following the IL-1β treatment (p≤0.05). Co-treatment of microRNA-181a mimic in IL-1β-treated primary astrocytes and neurons effectively blocked the IL-1β-induced upregulation of GLT-1. Lastly, we attempted to determine the link between GLT-1 and microRNA-181a in human AD brains. A significant reduction of GLT-1 was found in AD hippocampus tissues, and the ratio of mature microRNA-181a over primary microRNA-181a had an increasing tendency in AD. MicroRNA-181a controls rapid modifications of GLT-1 levels in astrocytes. Cytokine-induced inhibition of microRNA-181a and subsequent upregulation of GLT-1 may have physiological implications in synaptic plasticity while aberrant maturation of microRNA-181a may be involved in pathological consequences in AD.

The Influence of Polypharmacy on the Initiation of Anti-Dementia Therapy in Germany. - Bohlken, Jens; Jacob, Louis; van den Bussche, Hendrik; Kostev, Karel (J Alzheimers Dis, 2018)
The goal of the present retrospective study was to focus on the potential influence of polypharmacy on the initiation of antidementia therapy in patients diagnosed with dementia in general practices in Germany. The current study sample included patients diagnosed with dementia in 1,217 general practices in Germany between 2014 and 2016 (index date). The primary outcome measure was the rate of prescription of anti-dementia drugs within one year following the index date. The explanatory variable was the number of different drugs prescribed at baseline per patient. Independent variables included age, sex, and type of dementia. Logistic regression analyses were conducted to study the impact of the number of different drugs prescribed at baseline per participant on the odds of receiving anti-dementia therapy (in all patients and in patients diagnosed with Alzheimer's disease). The study included 21,888 patients with all-cause dementia. Mean age was 80.2 years (SD = 7.3 years) and 61.4% of the study population were women. Individuals receiving six drugs or more at baseline were significantly less likely to be prescribed anti-dementia treatment when compared to those without any drug at baseline (6- 9 drugs: odds ratio [OR] = 0.75;≥10 drugs: OR = 0.58). In the subgroup of patients with Alzheimer's disease, the odds of being prescribed anti-dementia therapy were lower in individuals with four drugs or more, compared to patients who had not been prescribed any drugs at baseline (4- 5 drugs: OR = 0.60; 6- 9 drugs: OR = 0.49;≥10 drugs: OR = 0.36). There is a negative association between polypharmacy and antidementia therapy initiation in general practices in Germany.

Inhibition of Histone Acetylation by ANP32A Induces Memory Deficits. - Chai, Gao-Shang; Feng, Qiong; Ma, Rong-Hong; Qian, Xiao-Hang; Luo, Dan-Ju; Wang, Zhi-Hao; Hu, Yu; Sun, Dong-Sheng; Zhang, Jun-Fei; Li, Xiao; Li, Xiao-Guang; Ke, Dan; et al. (J Alzheimers Dis, 2018)
There is accumulating evidence that decreased histone acetylation is involved in normal aging and neurodegenerative diseases. Recently, we found that ANP32A, a key component of INHAT (inhibitor of acetyltransferases) that suppresses histone acetylation, increased in aged and cognitively impaired C57 mice and expressing wild-type human full length tau (htau) transgenic mice. Downregulating ANP32A restored cognitive function and synaptic plasticity through upregulation of the expressions of synaptic-related proteins via increasing histone acetylation. However, there is no direct evidence that ANP32A can induce neurodegeneration and memory deficits. In the present study, we overexpressed ANP32A in the hippocampal CA3 region of C57 mice and found that ANP32A overexpression induced cognitive abilities and synaptic plasticity deficits, with decreased synaptic-related protein expression and histone acetylation. Combined with our recent studies, our findings reveal that upregulated ANP32A induced-suppressing histone acetylation may underlie the cognitive decline in neurodegenerative disease, and suppression of ANP32A may represent a promising therapeutic approach for neurodegenerative diseases including Alzheimer's disease.

Leisure-Time Physical Activity and the Risk of Incident Dementia: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Feder, Nathanael T; Roberts, Rosebud O; Mielke, Michelle M; Christianson, Teresa J; Knopman, David S; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2018)
We conducted a prospective cohort study derived from the population-based Mayo Clinic Study of Aging. We investigated if leisure-time physical activity among individuals with mild cognitive impairment (MCI) was associated with a decreased risk of developing dementia. 280 persons aged≥70 years (median 81 years, 165 males) with MCI and available data from neurologic evaluation, neuropsychological testing, and questionnaire-based physical activity assessment, were followed for a median of 3 years to the outcomes of incident dementia or censoring variables. We conducted Cox proportional hazards regression analyses with age as a time scale and adjusted for sex, education, medical comorbidity, depression, and APOE ɛ4 status. Moderate intensity midlife physical activity among MCI participants was significantly associated with a decreased risk of incident dementia (HR = 0.64; 95% CI, 0.41-0.98). There was a non-significant trend for a decreased risk of dementia for light and vigorous intensity midlife physical activity, as well as light and moderate intensity late-life physical activity. In conclusion, we observed that physical activity may be associated with a reduced risk of dementia among individuals with MCI. Furthermore, intensity and timing of physical activity may be important factors when investigating this association.

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

Longitudinal Changes in Serum Glucose Levels are Associated with Metabolic Changes in Alzheimer's Disease Related Brain Regions. - Burns, Christine M; Kaszniak, Alfred W; Chen, Kewei; Lee, Wendy; Bandy, Daniel J; Caselli, Richard J; Reiman, Eric M (J Alzheimers Dis, 2018)
BACKGROUND: The association between longitudinal changes in serum glucose level and longitudinal changes in [18F] Fluorodeoxyglucose-PET (FDG PET) measurements of Alzheimer's disease (AD) risk are unknown. OBJECTIVE: To investigate whether variation in serum glucose levels across time are associated with changes in FDG PET measurements of cerebral metabolic rate for glucose (rCMRgl) in brain regions preferentially affected by Alzheimer's disease (AD). METHODS: Participants are a subset of a prospective cohort study investigating FDG PET, apolipoprotein E (APOE) ɛ4, and risk for AD which includes data from baseline, interim, and follow up visits over 4.4±1.0-years. An automated brain-mapping algorithm was utilized to characterize and compare associations between longitudinal changes in serum glucose levels and longitudinal changes in rCMRgl. RESULTS: This study included 80 adults aged 61.5±5 years, including 38 carriers and 42 non-carriers of the APOE ɛ4 allele. Longitudinal increases in serum glucose levels were associated with longitudinal CMRgl decline in the vicinity of parietotemporal, precuneus/posterior cingulate, and prefrontal brain regions preferentially affected by AD (p < 0.05, corrected for multiple comparisons). Findings remained significant when controlled for APOE ɛ4 status and baseline and advancing age. CONCLUSIONS: Additional studies are needed to clarify and confirm the relationship between longitudinal changes in peripheral glucose and FDG PET measurements of AD risk. Future findings will set the stage on the use of FDG PET in the evaluation of possible interventions that target risk factors for the development of AD.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Blood Glucose; Brain; Brain Mapping; Female; Fluorodeoxyglucose F18; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Positron-Emission Tomography; Prospective Studies; Radiopharmaceuticals

Long-Term Follow Up of Patients with Mild-to-Moderate Alzheimer's Disease Treated with Bapineuzumab in a Phase III, Open-Label, Extension Study. - Salloway, Stephen P; Sperling, Reisa; Fox, Nick C; Sabbagh, Marwan N; Honig, Lawrence S; Porsteinsson, Anton P; Rofael, Hany; Ketter, Nzeera; Wang, Daniel; Liu, Enchi; Carr, Stephen; Black, Ronald S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A 3-year extension of two Phase III parent studies of intravenous (IV) bapineuzumab in patients with mild-to-moderate Alzheimer's disease dementia (apolipoprotein (APOE) ɛ4 carriers and noncarriers) is summarized. OBJECTIVES: The primary and secondary objectives were to evaluate the long-term safety, tolerability, and maintenance of efficacy of bapineuzumab. METHODS: A multicenter study in patients who had participated in double-blind placebo-controlled parent studies. Patients enrolled in the extension study were assigned to receive IV infusions of bapineuzumab (0.5 or 1.0 mg/kg) every 13 weeks until termination but were blinded to whether they had received bapineuzumab or placebo in the parent studies. RESULTS: A total of 1,462 (688 were APOEɛ4 carriers and 774 were noncarriers) patients were enrolled. Extension-onset adverse events occurred in >81% of the patients in each dose group. Fall, urinary tract infection, agitation, and ARIA-E occurred in ≥10% of participants. The incidence proportion of ARIA-E was higher among carriers and noncarriers who received bapineuzumab for the first time in the extension study (11.8% and 5.4%, respectively) versus those who were previously exposed in the parent studies (5.1% and 1.3%, respectively). After 6 to 12 months exposure to bapineuzumab IV in the extension study, similar deterioration of cognition and function occurred with no significant differences between the dose groups. CONCLUSIONS: Infusion of bapineuzumab 0.5 or 1.0 mg/kg every 13 weeks for up to 3 years was generally well tolerated, with a safety and tolerability profile similar to that in previous studies.

Low Cerebrospinal Fluid Aβ42 and Aβ40 are Related to White Matter Lesions in Cognitively Normal Elderly. - Skoog, Ingmar; Kern, Silke; Zetterberg, Henrik; Östling, Svante; Börjesson-Hanson, Anne; Guo, Xinxin; Blennow, Kaj (J Alzheimers Dis, 2018)
BACKGROUND: Low cerebrospinal fluid (CSF) levels of Aβ42 may be the earliest manifestation of Alzheimer's disease (AD). Knowledge on how CSF Aβ interacts with different brain pathologies early in the disease process is limited. We examined how CSF Aβ markers relate to brain atrophy and white matter lesions (WMLs) in octogenarians with and without dementia to explore the earliest pathogenetic pathways of AD in the oldest old. OBJECTIVE: To study CSF amyloid biomarkers in relation to brain atrophy and WMLs in 85-year-olds with and without dementia. METHODS: 53 octogenarians took part in neuropsychiatric examinations and underwent both a lumbar puncture and a brain CT scan. CSF levels of Aβ42 and Aβ40 were examined in relation to cerebral atrophy and WMLs. Dementia was diagnosed. RESULTS: In 85-year-olds without dementia, lower levels of both CSF Aβ42 and CSF Aβ40 were associated with WMLs. CSF Aβ42 also correlated with measures of central atrophy, but not with cortical atrophy. In participants with dementia, lower CSF levels of Aβ42 were related to frontal, temporal, and parietal cortical atrophy but not to WMLs. CONCLUSIONS: Our findings may suggest that there is an interrelationship between Aβ and subcortical WMLs in older persons without dementia. After onset of dementia, low CSF Aβ42, probably representing amyloid deposition in plaques, is associated with cortical atrophy. WMLs may be an earlier manifestation of Aβ deposition than cortical degeneration.

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers. - Vassilaki, Maria; Aakre, Jeremiah A; Syrjanen, Jeremy A; Mielke, Michelle M; Geda, Yonas E; Kremers, Walter K; Machulda, Mary M; Alhurani, Rabe E; Staubo, Sara C; Knopman, David S; Petersen, Ronald C; Lowe, Val J; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is accumulating evidence suggesting that diet may play a role in preventing or delaying cognitive decline and dementia, but the underlying biological mechanisms are not well understood. OBJECTIVES: To examine the cross-sectional associations of the Mediterranean diet (MeDi) and its components with 11C-PiB-PET scan measures of amyloid-β (Aβ) deposition. METHODS: The study consisted of 278 Mayo Clinic Study of Aging participants 70+ years old, who were cognitively unimpaired (CU) at the time of completion of the Food Frequency Questionnaire (FFQ) and when they underwent PET imaging. Adherence to the MeDi was assessed by computing the MeDi score for each participant. All scans were performed after the FFQ completion; median [IQR] time between FFQ and Aβ PET was 3.5 (1.4) years. Z-scores were created for component, macro- and micronutrients measured. Linear and logistic regression models were adjusted for age, sex, education, apolipoprotein E (APOE) ɛ4 allele carrier status, time interval between the FFQ completion and PET scan, and total energy intake. RESULTS: Participants' median age at FFQ was 77.7 years (55.8% men; 26.6% with an APOE ɛ4 allele). Higher MeDi score (linear regression slope (beta):-0.035, p = 0.012; per standard deviation increase), vegetable intake (beta:-0.043, p = 0.002), intake of vitamin A (beta:-0.041, p = 0.003) or β-carotene (beta: -0.039, p = 0.005) from food sources and moderate alcohol consumption (beta: -0.074, p = 0.03) were associated with lower 11C-PiB standardized uptake value ratio. CONCLUSION: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.

Memory Binding Test Predicts Incident Dementia: Results from the Einstein Aging Study. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2018)
BACKGROUND: The Memory Binding Test (MBT) demonstrated good cross-sectional discriminative validity and predicted incident aMCI. OBJECTIVE: To assess whether the MBT predicts incident dementia better than a conventional list learning test in a longitudinal community-based study. METHODS: As a sub-study in the Einstein Aging Study, 309 participants age≥70 initially free of dementia were administered the MBT and followed annually for incident dementia for up to 13 years. Based on previous work, poor memory binding was defined using an optimal empirical cut-score of≤17 on the binding measure of the MBT, Total Items in the Paired condition (TIP). Cox proportional hazards models were used to assess predictive validity adjusting for covariates. We compared the predictive validity of MBT TIP to that of the free and cued selective reminding test free recall score (FCSRT-FR; cut-score:≤24) and the single list recall measure of the MBT, Cued Recalled from List 1 (CR-L1; cut-score:≤12). RESULTS: Thirty-five of 309 participants developed incident dementia. When assessing each test alone, the hazard ratio (HR) for dementia was significant for MBT TIP (HR = 8.58, 95% CI: (3.58, 20.58), p < 0.0001), FCSRT-FR (HR = 4.19, 95% CI: (1.94, 9.04), p = 0.0003) and MBT CR-L1 (HR = 2.91, 95% CI: (1.37, 6.18), p = 0.006). MBT TIP remained a significant predictor of dementia (p = 0.0002) when adjusting for FCSRT-FR or CR-L1. CONCLUSIONS: Older adults with poor memory binding as measured by the MBT TIP were at increased risk for incident dementia. This measure outperforms conventional episodic memory measures of free and cued recall, supporting the memory binding hypothesis.

Mental States in Moving Shapes: Distinct Cortical and Subcortical Contributions to Theory of Mind Impairments in Dementia. - Synn, Artemis; Mothakunnel, Annu; Kumfor, Fiona; Chen, Yu; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2018)
Impaired capacity for Theory of Mind (ToM) represents one of the hallmark features of the behavioral variant of frontotemporal dementia (bvFTD) and is suggested to underpin an array of socioemotional disturbances characteristic of this disorder. In contrast, while social processing typically remains intact in Alzheimer's disease (AD), the cognitive loading of socioemotional tasks may adversely impact mentalizing performance in AD. Here, we employed the Frith-Happé animations as a dynamic on-line assessment of mentalizing capacity with reduced incidental task demands in 18 bvFTD, 18 AD, and 25 age-matched Controls. Participants viewed silent animations in which geometric shapes interact in Random, Goal-Directed, and ToM conditions. An exclusive deficit in ToM classification was observed in bvFTD relative to Controls, while AD patients were impaired in the accurate classification of both Random and ToM trials. Correlation analyses revealed robust associations between ToM deficits and carer ratings of affective empathy disruption in bvFTD, and with episodic memory dysfunction in AD. Voxel-based morphometry analyses further identified dissociable neural correlates contingent on patient group. A distributed network of medial prefrontal, frontoinsular, striatal, lateral temporal, and parietal regions were implicated in the bvFTD group, whereas the right hippocampus correlated with task performance in AD. Notably, subregions of the cerebellum, including lobules I-IV and V, bilaterally were implicated in task performance irrespective of patient group. Our findings reveal new insights into the mechanisms potentially mediating ToM disruption in dementia syndromes, and suggest that the cerebellum may play a more prominent role in social cognition than previously appreciated.
Keywords: Aged; Alzheimer Disease; Brain; Case-Control Studies; Female; Frontotemporal Dementia; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Mentalization; Middle Aged; Neuropsychological Tests; Task Performance and Analysis; Theory of Mind

Midlife Physical Activity, Psychological Distress, and Dementia Risk: The HUNT Study. - Zotcheva, Ekaterina; Bergh, Sverre; Selbæk, Geir; Krokstad, Steinar; Håberg, Asta Kristine; Strand, Bjørn Heine; Ernstsen, Linda (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) is associated with a decreased dementia risk, whereas psychological distress (distress) is linked to an increased dementia risk. OBJECTIVE: We investigated independent and joint associations of midlife moderate-to-vigorous PA (MVPA) and distress with incident dementia. METHODS: Our study comprised 28,916 participants aged 30-60 years from the Nord-Trøndelag Health Study (HUNT1, 1984-1986). Data on MVPA and distress from HUNT1 was linked to the Health and Memory Study in Nord-Trøndelag for dementia case identification. Participants were followed from 1995 until 2011. We used adjusted Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (95% CI). RESULTS: In fully adjusted analyses, MVPA was associated with a reduced dementia risk (HR 0.81, 95% CI 0.62-1.06), compared to no MVPA. Distress was associated with an increased dementia risk (HR 1.30, 95% CI 0.99-1.70). Compared to distressed participants not taking part in MVPA, non-distressed no-MVPA participants had a reduced dementia risk (HR 0.72, 95% CI 0.54-0.96). The same applied to distressed MVPA participants (HR 0.50, 95% CI 0.22-1.14), and non-distressed MVPA participants (HR 0.63, 95% CI 0.44-0.90). Our results indicated an additive interaction between MVPA and distress on dementia risk. CONCLUSION: Our results suggest that midlife MVPA reduces risk of incident dementia among both distressed and non-distressed individuals.

Mitochondrial Dysfunction as a Predictor and Driver of Alzheimer's Disease-Like Pathology in OXYS Rats. - Tyumentsev, Mikhail A; Stefanova, Natalia A; Muraleva, Natalia A; Rumyantseva, Yulia V; Kiseleva, Elena; Vavilin, Valentin A; Kolosova, Nataliya G (J Alzheimers Dis, 2018)
Growing evidence suggests that mitochondrial dysfunction is an early event in sporadic Alzheimer's disease (AD), but the impact of mitochondrial dysfunction on the transition from healthy aging to AD remains elusive. Here we estimated the influence of mitochondrial dysfunction on the initiation of AD signs in OXYS rats, which simulate key characteristics of sporadic AD. We assessed the mitochondrial ultrastructure of pyramidal neurons of the hippocampus at the age preceding the development (age 20 days), during manifestation (4-5 months), and at the well-pronounced stages (18-24 months) of the AD-like pathology in OXYS rats. Ultrastructural alterations were collated with the amounts of proteins mediating mitochondrial dynamics [mitofusins (MFN1 and MFN2) and dynamin-1-like protein (DRP1)]; with activity of respiratory chain complexes I, IV, and V in the hippocampal mitochondria; with reactive oxygen species (ROS) production; and with expression of uncoupling protein 2 (UCP2) regulating ROS production. Already at the preclinical stage, OXYS rats showed some characteristic changes in hippocampal mitochondria, which increased in size with the manifestation and progression of AD-like pathology, including decreased activity of respiratory complexes against the background of greater fusion and formation of larger mitochondria. Signs of AD developed simultaneously with increasing dysfunction of mitochondria, with a dramatic decrease in their number, and with increased fission but without upregulation of ROS production (observed only in 20-day-old OXYS rats). Summarizing the data from our present and previous studies, we conclude that mitochondrial dysfunction appears to mediate or possibly even initiate pathological molecular cascades of AD-like pathology in OXYS rats and can be considered a predictor of the early development of the late-onset form of AD in humans.

Moringa Oleifera Alleviates Homocysteine-Induced Alzheimer's Disease-Like Pathology and Cognitive Impairments. - Mahaman, Yacoubou Abdoul Razak; Huang, Fang; Wu, Mengjuan; Wang, Yuman; Wei, Zhen; Bao, Jian; Salissou, Maibouge Tanko Mahamane; Ke, Dan; Wang, Qun; Liu, Rong; Wang, Jian-Zhi; Zhang, Bin; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is multifactorial with unclear etiopathology. Due to the complexity of AD, many attempted single therapy treatments, like Aβ immunization, have generally failed. Therefore, there is a need for drugs with multiple benefits. Naturally occurring phytochemicals with neuroprotective, anti-amyloidogenic, antioxidative, and anti-inflammatory properties could be a possible way out. In this study, the effect of Moringa oleifera (MO), a naturally occurring plant with high antioxidative, anti-inflammatory, and neuroprotective effects, was evaluated on hyperhomocysteinemia (HHcy) induced AD-like pathology in rats. Homocysteine (Hcy) injection for 14 days was used to induce AD-like pathology. Simultaneous MO extract gavage followed the injection as a preventive treatment or, after injection completion, MO gavage was performed for another 14 days as a curative treatment. MO was found to not only prevent but also rescue the oxidative stress and cognitive impairments induced by Hcy treatment. Moreover, MO recovered the decreased synaptic proteins PSD93, PSD95, Synapsin 1 and Synaptophysin, and improved neurodegeneration. Interestingly, MO decreased the Hyc-induced tau hyperphosphorylation at different sites including S-199, T-231, S-396, and S-404, and at the same time decreased Aβ production through downregulation of BACE1. These effects in HHcy rats were accompanied by a decrease in calpain activity under MO treatment, supporting that calpain activation might be involved in AD pathogenesis in HHcy rats. Taken together, our data, for the first time, provided evidence that MO alleviates tau hyperphosphorylation and Aβ pathology in a HHcy AD rat model. This and previous other studies support MO as a good candidate for, and could provide new insights into, the treatment of AD and other tauopathies.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

Multi-Modality Sparse Representation for Alzheimer's Disease Classification. - Kwak, Kichang; Yun, Hyuk Jin; Park, Gilsoon; Lee, Jong-Min (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) and mild cognitive impairment (MCI) are age-related neurodegenerative diseases characterized by progressive loss of memory and irreversible cognitive functions. The hippocampus, a brain area critical for learning and memory processes, is especially susceptible to damage at early stages of AD. OBJECTIVE: We aimed to develop prediction model using a multi-modality sparse representation approach. METHODS: We proposed a sparse representation approach to the hippocampus using structural T1-weighted magnetic resonance imaging (MRI) and 18-fluorodeoxyglucose-positron emission tomography (FDG-PET) to distinguish AD/MCI from healthy control subjects (HCs). We considered structural and function information for the hippocampus and applied a sparse patch-based approach to effectively reduce the dimensions of neuroimaging biomarkers. RESULTS: In experiments using Alzheimer's Disease Neuroimaging Initiative data, our proposed method demonstrated more reliable than previous classification studies. The effects of different parameters on segmentation accuracy were also evaluated. The mean classification accuracy obtained with our proposed method was 0.94 for AD/HCs, 0.82 for MCI/HCs, and 0.86 for AD/MCI. CONCLUSION: We extracted multi-modal features from automatically defined hippocampal regions of training subjects and found this method to be discriminative and robust for AD and MCI classification. The extraction of features in T1 and FDG-PET images is expected to improve classification performance due to the relationship between brain structure and function.

Multi-Parametric Classification of Vascular Cognitive Impairment and Dementia: The Impact of Diverse Cerebrovascular Injury Biomarkers. - Lang, Brittany; Kindy, Mark S; Kozel, F Andrew; Schultz, Susan K; Taheri, Saeid (J Alzheimers Dis, 2018)
Vascular cognitive impairment and dementia (VCID) is a diagnostic term applied to cognitively impaired individuals with heterogeneous cerebrovascular conditions affecting large and/or small vessels. Individual biomarkers have been identified as instrumental in relating VCID to specific underlying pathologies to better characterize this syndrome. Emerging research to refine panels of biomarkers will increase classification sensitivity and specificity. Refined VCID clustering based on the severity and pathology of vascular injury will permit the development of optimal prevention and treatment strategies. Here, we review recently reported data concerning the diversity of VCID-related pathology and attempts for VCID clustering based on biomarkers obtained from different sets of measurements. We discuss three major sets of biomarkers: 1) neuroimaging biomarkers, 2) neuropsychological performance measures, and 3) biochemical markers in current VCID clustering. Finally, we highlight the effect of blood-brain barrier health on cerebrovascular disease trajectory.

Nailfold Capillary Morphology in Alzheimer's Disease Dementia. - Cousins, Clara C; Alosco, Michael L; Cousins, Henry C; Chua, Alicia; Steinberg, Eric G; Chapman, Kimberly R; Bing-Canar, Hanaan; Tripodis, Yorghos; Knepper, Paul A; Stern, Robert A; Pasquale, Louis R (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrovascular disease (CVD) is highly comorbid with Alzheimer's disease (AD), yet its role is not entirely understood. Nailfold video capillaroscopy (NVC) is a noninvasive method of live imaging the capillaries near the fingernail's cuticle and may help to describe further vascular contributions to AD. OBJECTIVE: To examine finger nailfold capillary morphology using NVC in subjects with AD dementia, mild cognitive impairment (MCI), and normal cognition (NC). METHODS: We evaluated nailfold capillary hemorrhages, avascular zones ≥100 microns, and degree of tortuosity in 28 NC, 15 MCI, and 18 AD dementia subjects using NVC. Tortuosity was measured with a semi-quantitative rating scale. To assess the relation between nailfold capillary morphological features and diagnostic grouping, univariate and multivariable logistic regression models were fit to the data. RESULTS: 56% of subjects with AD dementia compared to 14% with NC and 13% with MCI displayed moderate to severe tortuosity. Greater severity of tortuosity was associated with 10.6-fold (95% confidence interval [CI]: 2.4, 46.2; p = 0.0018) and 7.4-fold (95% CI: 1.3, 41.3; p = 0.023) increased odds of AD dementia relative to NC and MCI, respectively, after adjusting for multiple covariates. CONCLUSION: Greater nailfold capillary tortuosity was found in participants with AD dementia compared to those with MCI or NC. These data provide preliminary evidence of a systemic microvasculopathy in AD that may be noninvasively and inexpensively evaluated through NVC.

The Need to Separate Chronic Traumatic Encephalopathy Neuropathology from Clinical Features. - Iverson, Grant L; Keene, C Dirk; Perry, George; Castellani, Rudolph J (J Alzheimers Dis, 2018)
There is tremendous recent interest in chronic traumatic encephalopathy (CTE) in former collision sport athletes, civilians, and military veterans. This critical review places important recent research results into a historical context. In 2015, preliminary consensus criteria were developed for defining the neuropathology of CTE, which substantially narrowed the pathology previously reported to be characteristic. There are no agreed upon clinical criteria for diagnosis, although sets of criteria have been proposed for research purposes. A prevailing theory is that CTE is an inexorably progressive neurodegenerative disease within the molecular classification of the tauopathies. However, historical and recent evidence suggests that CTE, as it is presented in the literature, might not be pathologically or clinically progressive in a substantial percentage of people. At present, it is not known whether the emergence, course, or severity of clinical symptoms can be predicted by specific combinations of neuropathologies, thresholds for accumulation of pathology, or regional distributions of pathologies. More research is needed to determine the extent to which the neuropathology ascribed to long-term effects of neurotrauma is static, progressive, or both. Disambiguating the pathology from the broad array of clinical features that have been reported in recent studies might facilitate and accelerate research- and improve understanding of CTE.
Keywords: Chronic Traumatic Encephalopathy; Cognition Disorders; Disease Progression; Gait Disorders, Neurologic; Humans; Neurodegenerative Diseases; Neuropathology; Tremor

Negative Prospective Memory in Alzheimer's Disease: "Do Not Perform That Action". - El Haj, Mohamad; Coello, Yann; Kapogiannis, Dimitrios; Gallouj, Karim; Antoine, Pascal (J Alzheimers Dis, 2018)
Relatively to "standard" prospective memory, i.e., remembering to perform a future action, little is known about negative prospective memory, i.e., remembering not to perform a future action. This study investigated the latter ability in Alzheimer's disease (AD). AD participants and healthy older adults were asked to click on the keyboard or not to click on it when a cue word was encountered. Results showed more omissions (i.e., forgetting to click the keyboard when the instruction was to do so) in AD participants than in healthy older adults, suggesting a prospective memory deficit. Interestingly, more commissions (i.e., clicking the keyboard when the instruction was not to do so) were also observed in AD participants than in healthy older adults. Similar levels of commissions and omissions were observed in AD participants and in healthy older adults. Also, commissions and omissions were correlated with performance on an inhibition assessment task. Our findings reveal that AD is characterized by not only difficulty in the retrieval of recent information, but also difficulty to inhibit no-longer appropriate stimulus-response associations previously learned, suggesting a specific deficit of negative prospective memory in AD.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Humans; Inhibition (Psychology); Male; Memory Disorders; Memory, Episodic; Mental Recall; Neuropsychological Tests

Neural Correlates of Sleep Disturbance in Alzheimer's Disease: Role of the Precuneus in Sleep Disturbance. - Matsuoka, Teruyuki; Imai, Ayu; Fujimoto, Hiroshi; Kato, Yuka; Shibata, Keisuke; Nakamura, Kaeko; Yokota, Hajime; Yamada, Kei; Narumoto, Jin (J Alzheimers Dis, 2018)
BACKGROUND: Sleep disturbance may affect the development of Alzheimer's disease (AD), but the neural correlates of sleep disturbance in AD have not been fully clarified. OBJECTIVE: To examine the factors associated with sleep disturbance in AD. METHODS: A retrospective study was performed in 63 patients with AD. None of the patients had been prescribed antidementia or psychoactive drugs, and all underwent brain magnetic resonance imaging (MRI) before medication. Sleep disturbance was defined as a score of at least 1 point on the sleep disturbance subscale of the Neuropsychiatric Inventory (NPI). Whole brain image analysis was performed using SPM8 and VBM8. A two-sample t-test was used to compare patients with AD with (n = 19) and without (n = 44) sleep disturbance, with age and gender included as covariates. The statistical thresholds were set to an uncorrected p-value of 0.001 at the voxel level and a corrected p-value of 0.05 at the cluster level. In addition, pineal gland volume (PGV) measured using MRI, and white matter hyperintensity (WMH) assessed with the modified Fazekas scale were compared between patients with AD with and without sleep disturbance using independent group t-tests. RESULTS: In whole brain analysis, the precuneus volume in patients with AD with sleep disturbance was significantly smaller than those without sleep disturbance. There were no significant differences in PGV and WMH between the two groups. CONCLUSION: Sleep disturbance in AD was associated with reduction of precuneus volume. This suggests that the precuneus might be an important region in sleep disturbance in AD.

Neuro-Immuno-Gene- and Genome-Editing-Therapy for Alzheimer's Disease: Are We There Yet? - Raikwar, Sudhanshu P; Thangavel, Ramasamy; Dubova, Iuliia; Ahmed, Mohammad Ejaz; Selvakumar, Pushpavathi Govindhasamy; Kempuraj, Duraisamy; Zaheer, Smita; Iyer, Shankar; Zaheer, Asgar (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a highly complex neurodegenerative disorder and the current treatment strategies are largely ineffective thereby leading to irreversible and progressive cognitive decline in AD patients. AD continues to defy successful treatment despite significant advancements in the field of molecular medicine. Repeatedly, early promising preclinical and clinical results have catapulted into devastating setbacks leading to multi-billion dollar losses not only to the top pharmaceutical companies but also to the AD patients and their families. Thus, it is very timely to review the progress in the emerging fields of gene therapy and stem cell-based precision medicine. Here, we have made sincere efforts to feature the ongoing progress especially in the field of AD gene therapy and stem cell-based regenerative medicine. Further, we also provide highlights in elucidating the molecular mechanisms underlying AD pathogenesis and describe novel AD therapeutic targets and strategies for the new drug discovery. We hope that the quantum leap in the scientific advancements and improved funding will bolster novel concepts that will propel the momentum toward a trajectory leading to a robust AD patient-specific next generation precision medicine with improved cognitive function and excellent life quality.

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer's Disease. - Ehrenberg, Alexander J; Suemoto, Claudia K; França Resende, Elisa de Paula; Petersen, Cathrine; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Ferretti-Rebustini, Renata Eloah de Lucena; You, Michelle; Oh, Jun; Nitrini, Ricardo; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al. (J Alzheimers Dis, 2018)
Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem interviews with reliable informants were used to collect information regarding neuropsychiatric and cognitive status. Of 1,092 cases collected, those with any non-Alzheimer pathology were excluded, bringing the cohort to 455 cases. Braak staging was used to evaluate neurofibrillary tangle burden, and the CERAD neuropathology score was used to evaluate amyloid-β burden. The 12-item neuropsychiatric inventory was used to evaluate neuropsychiatric symptoms and CDR-SOB score was used to evaluate dementia status. In Braak I/II, significantly increased odds were detected for agitation, anxiety, appetite changes, depression, and sleep disturbances, compared to controls. Increased odds of agitation continue into Braak III/IV. Braak V/VI is associated with higher odds for delusions. No increased odds for neuropsychiatric symptoms were found to correlate with amyloid-β pathology. Increased odds of neuropsychiatric symptoms are associated with early neurofibrillary tangle pathology, suggesting that subcortical neurofibrillary tangle accumulation with minimal cortical pathology is sufficient to impact quality of life and that neuropsychiatric symptoms are a manifestation of AD biological processes.

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Neurotoxic Effects of Aβ6-42 Peptides Mimicking Putative Products Formed by the Angiotensin Converting Enzyme. - Medvedev, Alexei E; Radko, Sergey P; Yurinskaya, Marina M; Vinokurov, Maxim G; Buneeva, Olga A; Kopylov, Arthur T; Kozin, Sergey A; Mitkevich, Vladimir A; Makarov, Alexander A (J Alzheimers Dis, 2018)
Angiotensin converting enzyme (ACE) is involved in proteolytic processing of the amyloid-β(Aβ) peptide implicated in the development of Alzheimer's disease (AD) and known products of ACE-based processing of Aβ42 are characterized by reduced aggregability and cytotoxicity. Recently it has been demonstrated that ACE can act as an arginine specific endopeptidase cleaving the N-terminal pentapeptide (Aβ1-5) from synthetic Aβ peptide analogues. In the context of proteolytic processing of full length Aβ42, this suggests possible formation of Aβ6-42 species. The aim of this study was to test a hypothesis that some N-terminally truncated Aβ peptide(s) could retain aggregability and neurotoxic properties typical for Aβ42. We have investigated aggregability of two amyloid-β peptides, Aβ6-42 and isoD7-Aβ6-42, mimicking potential proteolytic products of Aβ42 and isoD7-Aβ42, and evaluated their effects on the repertoire of brain Aβ binding proteins, and cytotoxicity towards neuroblastoma SH-SY5Y cells. Aggregability of isoD7-Aβ6-42 and Aβ6-42 was higher than that of full-length peptides Aβ42 and isoD7-Aβ42, while the repertoire of mouse brain Aβ binding proteins dramatically decreased. Aβ6-42 and isoD7-Aβ6-42 exhibited higher neurotoxicity towards SH-SY5Y cells than Aβ42 and isoD7-Aβ42, respectively. They effectively stimulated production of ROS and NO, and also TNFα secretion by cells. Thus, our results suggest that ACE-dependent processing of full-length Aβs could result in formation of more pathogenic peptides.

A New Perspective in Utilizing MMP-9 as a Therapeutic Target for Alzheimer's Disease and Type 2 Diabetes Mellitus. - Kaminari, Archontia; Tsilibary, Effie C; Tzinia, Athina (J Alzheimers Dis, 2018)
Matrix metalloprotease 9 (MMP-9) is a 92 kDa type IV collagenase and a member of the family of endopeptidases. MMP-9 is involved in the degradation of extracellular matrix components, tissue remodeling, cellular receptor stripping, and processing of various signaling molecules. In the CNS, the effects of MMP-9 are quite complex, since it exerts beneficial effects including neurogenesis, angiogenesis, myelogenesis, axonal growth, and inhibition of apoptosis, or destructive effects including apoptosis, blood-brain barrier disorder, and demyelination. Likewise, in the periphery, physiological events, as the involvement of MMP-9 in angiogenesis, for instance in wound healing, can be turned into pathological, such as in tumor metastasis, depending on the state of the organism. Alzheimer's disease is a neurodegenerative disorder, characterized by amyloid accumulation and deposition in the brain. Amyloidogenesis, however, also occurs in diseases of the periphery, such as type II diabetes mellitus, where an analogous type of amyloid, is deposited in the pancreas. Interestingly, both diseases exhibit similar pathology and disease progression, with insulin resistance being a major common denominator. Hence, combinatorial strategies searching new or existing molecules to apply for therapeutic use for both diseases are gaining momentum. MMP-9 is extensively studied due to its association with a variety of physiological and pathological processes. Consequently, meticulous design could render MMP-9 into a potential therapeutic target for Alzheimer's disease and type 2 diabetes mellitus; two seemingly unrelated diseases.

A Nomogram for Predicting Amyloid PET Positivity in Amnestic Mild Cognitive Impairment. - Kim, Si Eun; Woo, Sookyoung; Kim, Seon Woo; Chin, Juhee; Kim, Hee Jin; Lee, Byung In; Park, Jinse; Park, Kyung Won; Kang, Do-Young; Noh, Young; Ye, Byoung Seok; Yoo, Han Soo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most clinical trials focus on amyloid-β positive (Aβ+) amnestic mild cognitive impairment (aMCI), but screening failures are high because only a half of patients with aMCI are positive on Aβ PET. Therefore, it becomes necessary for clinicians to predict which patients will have Aβ biomarker. OBJECTIVE: We aimed to compare clinical factors, neuropsychological (NP) profiles, and apolipoprotein E (APOE) genotype between Aβ+ aMCI and Aβ-aMCI and to develop a clinically useful prediction model of Aβ positivity on PET (PET-Aβ+) in aMCI using a nomogram. METHODS: We recruited 523 aMCI patients who underwent Aβ PET imaging in a nation-wide multicenter cohort. The results of NP measures were divided into following subgroups: 1) Stage (Early and Late-stage), 2) Modality (Visual, Verbal, and Both), 3) Recognition failure, and 4) Multiplicity (Single and Multiple). A nomogram for PET-Aβ+ in aMCI patients was constructed using a logistic regression model. RESULTS: PET-Aβ+ had significant associations with NP profiles for several items, including high Clinical Dementia Rating Scale Sum of Boxes score (OR 1.47, p = 0.013) and impaired memory modality (impaired both visual and verbal memories compared with visual only, OR 3.25, p = 0.001). Also, presence of APOEɛ4 (OR 4.14, p < 0.001) was associated with PET-Aβ+. These predictors were applied to develop the nomogram, which showed good prediction performance (C-statistics = 0.79). Its prediction performances were 0.77/0.74 in internal/external validation. CONCLUSIONS: The nomogram consisting of NP profiles, especially memory domain, and APOEɛ4 genotype may provide a useful predictive model of PET-Aβ+ in patients with aMCI.

Non-Ashkenazi Jewish Origin is Associated with Early Onset Alzheimer's Disease. - Keret, Ophir; Shochat, Tzippy; Steiner, Israel; Glik, Amir (J Alzheimers Dis, 2018)
Early-onset Alzheimer's disease (EOAD) accounts for 1-5% of Alzheimer's disease cases and is associated with specific ethnicities. It has been our impression that non-Ashkenazi Jews have a higher rate of EOAD and we therefore explored this hypothesis. We performed a retrospective case control study of EOAD cases referred to our cognitive neurology clinic between January 1999 and December 2016. Patients (n = 129) were compared to age- and geographically-matched controls generated from the Second Israeli National Health Survey (n = 1,811). Data on country of origin, education, dementia family history, depression, and vascular risk factors were compared between the groups. The association of non-Ashkenazi Jewish heritage and country of origin with EOAD was calculated using a logistic multivariate regression model. The EOAD group's mean age was 59.6±4.1 years, with a female predominance (64.3%). The EOAD group had a higher percentage of individuals of non-Ashkenazi Jewish origin (64.3% versus 51.4%, p = 0.003) and of Yemenite descent in particular (16.28% versus 6.24%, p < 0.001). On multiple logistic regression analysis, Yemenite Jewish origin was an independently associated with EOAD (OR 2.54, 95% CI 1.4-4.8). There were no significant differences in parameters between non-Ashkenazi and Ashkenazi Jews. Only 4.6% of EOAD cases had a positive EOAD family history. In conclusion, EOAD is over-represented among non-Ashkenazi Jews. Yemenite origin is independently associated with EOAD and the majority of patients with EOAD have no family history of Alzheimer's disease. Further evaluation with genetic studies is warranted.

Novel Lipidized Analog of Prolactin-Releasing Peptide Improves Memory Impairment and Attenuates Hyperphosphorylation of Tau Protein in a Mouse Model of Tauopathy. - Popelová, Andrea; Pražienková, Veronika; Neprašová, Barbora; Kasperová, Barbora Judita; Hrubá, Lucie; Holubová, Martina; Zemenová, Jana; Blum, David; Železná, Blanka; Galas, Marie-Christine; Kuneš, Jaroslav; Maletínská, Lenka (J Alzheimers Dis, 2018)
Obesity and type 2 diabetes mellitus (T2DM) were characterized as risk factors for Alzheimer's disease (AD) development. Subsequently, T2DM drugs, such as liraglutide, were proven to be neuroprotective compounds attenuating levels of amyloid deposits, and tau hyperphosphorylation, both hallmarks of AD. The central anorexigenic effects of liraglutide inspired us to examine the potential neuroprotective effects of palm11-PrRP31, a strong anorexigenic analog with glucose-lowering properties, in THY-Tau22 mice overexpressing mutated human tau, a model of AD-like tau pathology. Seven-month-old THY-Tau22 mice were subcutaneously infused with palm11-PrRP31 for 2 months. Spatial memory was tested before and after the treatment, using a Y-maze. At the end of the treatment, mice were sacrificed by decapitation and hippocampi were dissected and analyzed by immunoblotting with specific antibodies. Treatment with palm11-PrRP31 resulted in significantly improved spatial memory. In the hippocampi of palm11-PrRP31-treated THY-Tau22 mice, tau protein phosphorylation was attenuated at Thr231, Ser396, and Ser404, the epitopes linked to AD progression. The mechanism of this attenuation remains unclear, since the activation of those kinases most implicated in tau hyperphosphorylation, such as GSK-3β, JNK, or MAPK/ERK1/2, remained unchanged by palm11-PrRP31 treatment. Furthermore, we observed a significant increase in the amount of postsynaptic density protein PSD95, and a non-significant increase of synaptophysin, both markers of increased synaptic plasticity, which could also result in improved spatial memory of THY-Tau22 mice treated with palm11-PrRP31. Palm11-PrRP31 seems to be a potential tool for the attenuation of neurodegenerative disorders in the brain. However, the exact mechanism of its action must be elucidated.

Observational Study of Clinical and Functional Progression Based on Initial Brain MRI Characteristics in Patients with Alzheimer's Disease. - Choi, Hojin; Yang, YoungSoon; Han, Hyun Jeong; Jeong, Jee Hyang; Park, Mee Young; Kim, Yong Bum; Jo, Kwang Deog; Choi, Jin-Yong; Kang, Kyung-Hun; Kang, Heeyoung; Kwon, Do-Young; Yoo, Bong-Goo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) is a useful tool to predict the diagnosis and progression of Alzheimer's disease (AD), especially for primary physicians. However, the correlation between baseline MRI findings and AD progression has not been fully established. OBJECTIVE: To investigate the correlation between hippocampal atrophy (HA) and white matter hyperintensities (WMH) on initial brain MRI images and the degree of cognitive decline and functional changes over 1 year. METHODS: In this prospective, 12-month observational study, dementia outpatients were recruited from 29 centers across South Korea. Baseline assessments of HA and WMH on baseline brain MRI were derived as well as cognitive function, dementia severity, activities of daily living, and acetylcholinesterase inhibitor (AChEI) use. Follow-up assessments were conducted at 6 and 12 months. RESULTS: Among 899 enrolled dementia patients, 748 were diagnosed with AD of whom 654 (87%) were taking AChEIs. Baseline WMH showed significant correlations with age, current alcohol consumption, and Clinical Dementia Rating score; baseline HA was correlated with age, family history, physical exercise, and the results of cognitive assessments. Among the AChEI group, changes in the Korean version of the Instrumental Activities of Daily Living (K-IADL) were correlated with the severity of HA on baseline brain MRI, but not with the baseline severity of WMH. In the no AChEI group, changes in K-IADL were correlated with the severity of WMH and HA at baseline. CONCLUSION: Baseline MRI findings could be a useful tool for predicting future clinical outcomes by primary physicians, especially in relation to patients' functional status.

Odor Identification Ability Predicts PET Amyloid Status and Memory Decline in Older Adults. - Kreisl, William Charles; Jin, Peng; Lee, Seonjoo; Dayan, Ezra R; Vallabhajosula, Shankar; Pelton, Gregory; Luchsinger, Jose A; Pradhaban, Gnanavalli; Devanand, D P (J Alzheimers Dis, 2018)
BACKGROUND: Odor identification deficits occur in Alzheimer's disease (AD), as measured by the 40-item University of Pennsylvania Smell Identification Test (UPSIT). OBJECTIVE: To determine if UPSIT scores predict amyloid-β (Aβ) status, determined by 11C-Pittsburgh Compound B PET. We also compared UPSIT scores to Aβ status in predicting future memory decline. METHODS: Subjects were recruited into a longitudinal clinical prediction study. We analyzed data from those who had UPSIT, cognitive testing, PIB PET, and at least 12 months' clinical follow-up. Forty-six amnestic mild cognitive impairment patients and 25 cognitively normal controls were included. Amyloid-positivity was defined as composite PIB standardized uptake value ratio >1.5. Logistic regression and Receiver Operating Characteristic Curve analyses tested the predictive utility of impaired olfaction (defined as UPSIT score <35) and amyloid-positivity for memory decline. RESULTS: High UPSIT scores predicted absence of amyloidosis on PET, with negative predictive value of 100%. Positive predictive value of low UPSIT scores on positive Aβ status was only 41%. Both low UPSIT score (OR = 4.301, 95% CI = 1.248, 14.821, p = 0.021) and positive PET scan (OR = 20.898, 95% CI = 2.222, 196.581, p = 0.008) predicted memory decline. CONCLUSION: Individuals with high UPSIT scores are less likely to have cerebral amyloidosis or experience memory decline. Therefore, UPSIT has potential as a screening tool to determine utility of Aβ PET in clinical practice or enrollment in clinical trials. Low UPSIT score is a non-specific marker of neurodegeneration that could indicate further workup in patients with memory complaints.

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Parietal Involvement in the Semantic Variant of Primary Progressive Aphasia with Alzheimer's Disease Cerebrospinal Fluid Profile. - Bera, Géraldine; Migliaccio, Raffaella; Michelin, Thibaut; Lamari, Foudil; Ferrieux, Sophie; Nogues, Marie; Bertin, Hugo; Habert, Marie Odile; Dubois, Bruno; Teichmann, Marc; Kas, Aurélie (J Alzheimers Dis, 2018)
Semantic variant of primary progressive aphasia (svPPA) is typically associated with non-Alzheimer's disease (AD) pathology. However, some anatomopathological studies have found AD lesions in those patients. We compared brain perfusion SPECT of 18 svPPA patients with cerebrospinal fluid (CSF) biomarkers indicative of non-AD pathology (svPPA-nonAD) and three svPPA patients with CSF biomarkers indicative of underlying AD (svPPA-AD). All svPPA patients had severe left temporopolar hypoperfusion. SvPPA-nonAD had additional anterior cingulate and mediofrontal hypoperfusion, whereas svPPA-AD had greater left parietal and posterior cingulate involvement. Parietal damage in svPPA constitutes a biomarker for underlying Alzheimer pathology thus refining the classification of this PPA variant.

Parkinsonism is a Phenotypical Signature of Amyloidopathy in Patients with Gait Disorders. - Allali, Gilles; Kern, Ilse; Laidet, Magali; Armand, Stéphane; Assal, Frèdèric (J Alzheimers Dis, 2018)
BACKGROUND: Central neurological gait abnormalities (CNGA) are frequently associated with parkinsonism in older adults. However, the neuropathological substrates and the clinical impact of parkinsonism have been not described in CNGA. OBJECTIVE: This cross-sectional study aims to compare the CSF total tau, Aβ1-42, and phosphorylated tau levels in non-Parkinson's disease (PD) patients with CNGA with and without parkinsonism and to study the clinical impact of parkinsonism on gait and cognition. METHODS: CSF biomarkers were measured by ELISA in 49 non-PD patients with CNGA (77.7±6.6 years; 32.7% women). Gait was quantified with an optoelectronic system and cognition with a comprehensive neuropsychological assessment. Parkinsonism was defined by presence of bradykinesia and at least one of the following signs among muscular rigidity, rest tremor, or postural instability. RESULTS: Parkinsonism was identified in 14 CNGA patients (28.6% ). CSF Aβ1-42 level was decreased in CNGA patients with parkinsonism (β: - 189.4; 95% CI [- 352.3; - 26.6]; p = 0.024) even after adjusting for age, gender, comorbidities, and total white matter burden; while CSF total tau and phosphorylated tau levels were similar between CNGA patients with and without parkinsonism. CNGA patients with parkinsonism presented decreased attentional and executive performances but similar gait parameters than those without parkinsonism. CONCLUSION: Parkinsonism represents a phenotype related with amyloidopathy-decreased CSF Aβ1-42 level-in non-PD patients with CNGA. This phenotype is clinically associated with impaired cognition, but similar quantitative gait parameters in comparison to CNGA patients without parkinsonism.

Patient Characteristics and Outcomes Associated with Receiving an Earlier Versus Later Diagnosis of Probable Alzheimer's Disease. - Kirson, Noam Y; Scott Andrews, J; Desai, Urvi; King, Sarah B; Schonfeld, Sophie; Birnbaum, Howard G; Ball, Daniel E; Kahle-Wrobleski, Kristin (J Alzheimers Dis, 2018)
BACKGROUND: Effectiveness of Alzheimer's disease (AD) treatments may depend critically on the timeliness of intervention. OBJECTIVE: To compare characteristics and outcomes of patients diagnosed with probable AD (prAD) based on time elapsed from first onset of cognitive decline. METHODS: Patients with ≥1 prAD diagnosis and ≥1 follow-up visit were selected from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS; 9/2005-6/2015) and stratified based on the time between the perceived onset of cognitive decline at baseline and first prAD diagnosis (i.e., earlier versus later diagnosis). Characteristics at baseline and prAD diagnosis, clinically meaningful progression, and medication use following prAD diagnosis were compared. RESULTS: Median time from perceived onset of cognitive decline to prAD diagnosis was 4.5 years (earlier diagnosis: ≤3.46; later diagnosis: >5.71). Earlier-diagnosed patients (n = 1,476) were younger at baseline (74.3 versus 76.3 years) and had better cognitive and functional scores than later-diagnosed patients (n = 1,474). At first prAD diagnosis, earlier-diagnosed patients had lower mean global Clinical Dementia Rating (CDR) score (0.8 versus 1.1), higher mean Mini-Mental State Examination (MMSE) (22.6 versus 20.0), and lower mean Functional Activities Questionnaire (11.6 versus 17.3). Earlier- and later-diagnosed patients experienced similar time to a decrease of ≥3 points in MMSE (median 23.2 versus 23.1 months, p = 0.83), but earlier-diagnosed patients had longer time to a CDR score of ≥2 points, and longer times to initiation of AD medication and antipsychotic agents (all p < 0.01). CONCLUSION: Earlier prAD diagnosis in NACC data is associated with higher cognitive function and lower functional impairment at diagnosis.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Cohort Studies; Datasets as Topic; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors

Patients with Dementia in Primary Care: Who Is Referred to a Neurologist/Psychiatrist and What Patient-Oriented Factors Are Associated with the Visit? - Strohmaier, Urs; Keller, Felix; Kilimann, Ingo; Michalowsky, Bernhard; Wucherer, Diana; Zwingmann, Ina; Teipel, Stefan; Hoffmann, Wolfgang; Thyrian, Jochen René (J Alzheimers Dis, 2018)
BACKGROUND: The current guidelines imply that basic medical diagnostics for dementia should be provided by general practitioners in cooperation with other specialists such as neurologists and psychiatrists. OBJECTIVES: The aims of this paper were to 1) compare the dementia patients of general practice residents whose care is co-managed by neurology/psychiatry residents with those whose care is not; 2) identify the patient variables associated with the utilization of neurological and psychiatric specialists; and 3) describe the frequency of imaging used for dementia patients in primary care. METHODS: The analyses utilized data from 485 individuals who screened positive for dementia in primary care (PWD). Clinical variables and the utilization of specialists were assessed via medical records and face-to-face interviews. The factors associated with the utilization of specialists were assessed using multivariate linear regression and included age, sex, relationship status, cognitive impairment, depression, activities of daily living, and formal diagnosis of dementia. RESULTS: Our results show that 89 out of 485 study participants (18.4%) were referred to specialists 12 months prior to assessment. Of these 89 individuals, 14.6% (n = 13) did not receive imaging diagnostics, while 39.3% (n = 35) received brain imaging by CT scan and 46.1% (n = 41) by MRI. PWD referred to specialists differed from those not referred, in age, relationship status, and the presence of a formal diagnosis. Our multivariate analysis revealed that younger age (OR = 0.95; 95% -confidence interval 0.90-0.99; p = 0.04) and higher functional impairment (OR = 1.15; 95% -confidence interval 1.02-1.30; p = 0.02) were associated with a visit to a specialist. DISCUSSION: Only 1 out of every 4 to 5 individuals who have screened positive for dementia have visited a specialist in psychiatry or neurology. While in general, women utilized specialists less often than men, younger and more functionally impaired patients were more likely to be sent to a specialist by their treating general practitioner. Almost 90% of the patients sent to a specialist received cranial neuroimaging, suggesting high adherence to diagnostic guidelines in specialized care.

Patterns of Physical Activity and Sedentary Behavior for Older Adults with Alzheimer's Disease, Mild Cognitive Impairment, and Cognitively Normal in Hong Kong. - Lu, Zhihui; Harris, Tamara B; Shiroma, Eric J; Leung, Jason; Kwok, Timothy (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia, and mild cognitive impairment (MCI) is a transitional phase between healthy cognition and dementia. Physical activity (PA) has protective effects on cognitive decline. However, few studies have examined how PA and sedentary behavior is structured throughout the day in older adults across varied cognitive status in Hong Kong. OBJECTIVE: This study aimed to compare patterns of PA and sedentary behavior among individuals with AD, MCI, or normal cognition living in Hong Kong. METHODS: Participants in the MrOs and MsOs Hong Kong cohort study and the Hong Kong AD biomarker study (n = 810) wore a wrist-worn accelerometer for 7 days in free-living environment. Patterns of PA in wake time and in-bed time, and detailed analysis of sedentary bouts were compared between groups using analysis of covariance adjusting for covariates. RESULTS: Participants with MCI and low MoCA only did not differ from their cognitively normal peers in PA and sedentary behavior. Nevertheless, when comparing to the others, participants with AD exhibited significantly lower average daily counts per minute during the day (p < 0.05), and tended to start their activity later in the morning. AD participants spent a larger proportion of time in sedentary behavior (p < 0.05) and had more sedentary bouts≥30 minutes (p < 0.05). CONCLUSIONS: The pattern of PA and sedentary behavior was different between individuals with AD and the others. Cognitive status may alter the purpose and type of PA intervention for AD individuals.

Personality Modulates the Efficacy of Art Intervention on Chronic Pain in a Population of Patients with Alzheimer's Disease. - Rouch, Isabelle; Pongan, Elodie; Leveque, Yohana; Tillmann, Barbara; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Krolak-Salmon, Pierre; Laurent, Bernard; Dorey, Jean-Michel (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mainly occurs in elderly individuals. Comorbidities and chronic pain are frequent in this population. Previous studies revealed that personality modulates both chronic pain (CP) andADoccurrence and evolution. Moreover, as pain treatments can induce side-effects, non-drugs treatments, such as art interventions, are interesting alternative therapies for decreasing CP in these patients. OBJECTIVE: Our aim was to assess the potential role of personality traits on art intervention efficacy for reducing CP in a population of patients with mild AD. METHODS: Design: multicenter randomized controlled trial. Fifty mild AD patients underwent a 12-week art intervention including singing and painting groups. Personality was assessed with the Big Five Inventory before the sessions. CP was measured with Numeric Rating Scale (NRS) [Usual pain (NRS-U) and most Intense pain (NRS-I)], Simple Visual Scale [Usual pain (SVS-U) and most Intense pain (SVS-I)] and Brief Pain Inventory (BPI) before and after the sessions. The influence of personality traits on CP evolution before and after art intervention was assessed with multiple linear regression models. RESULTS: A positive association was observed between neuroticism and the evolution of three CP measures including NRS-U (B = 0.34, p = 0.01), SVS-U (B = 0.20, p = 0.04), and BPI-U (B = 0.46, p = 0.02) evolution. No significant relationship was observed between neuroticism and NRS-I, SVS-I and BPI-R evolution. CONCLUSIONS: Our findings suggest that neuroticism can decrease the efficacy of group art intervention on pain in patients with mild AD. Individual therapies could be more appropriate for these patients. These results emphasize the interest of taking into account patients' personality before proposing them to participate to a group therapy.

Physical Fitness and Aortic Stiffness Explain the Reduced Cognitive Performance Associated with Increasing Age in Older People. - Kennedy, Greg; Meyer, Denny; Hardman, Roy J; Macpherson, Helen; Scholey, Andrew B; Pipingas, Andrew (J Alzheimers Dis, 2018)
BACKGROUND: Greater physical fitness is associated with reduced rates of cognitive decline in older people; however, the mechanisms by which this occurs are still unclear. One potential mechanism is aortic stiffness, with increased stiffness resulting in higher pulsatile pressures reaching the brain and possibly causing progressive micro-damage. There is limited evidence that those who regularly exercise may have lower aortic stiffness. OBJECTIVE: To investigate whether greater fitness and lower aortic stiffness predict better cognitive performance in older people and, if so, whether aortic stiffness mediates the relationship between fitness and cognition. METHODS: Residents of independent living facilities, aged 60-90, participated in the study (N = 102). Primary measures included a computerized cognitive assessment battery, pulse wave velocity analysis to measure aortic stiffness, and the Six-Minute Walk test to assess fitness. Based on hierarchical regression analyses, structural equation modelling was used to test the mediation hypothesis. RESULTS: Both fitness and aortic stiffness independently predicted Spatial Working Memory (SWM) performance, however no mediating relationship was found. Additionally, the derived structural equation model shows that, in conjunction with BMI and sex, fitness and aortic stiffness explain 33% of the overall variation in SWM, with age no longer directly predicting any variation. CONCLUSIONS: Greater fitness and lower aortic stiffness both independently predict better SWM in older people. The strong effect of age on cognitive performance is totally mediated by fitness and aortic stiffness. This suggests that addressing both physical fitness and aortic stiffness may be important to reduce the rate of age associated cognitive decline.

Phytochemicals from Achillea fragrantissima are Modulators of AβPP Metabolism. - Bartolotti, Nancy; Disouky, Ahmed; Kalinski, Arthur; Elmann, Anat; Lazarov, Orly (J Alzheimers Dis, 2018)
Plant derivatives offer a novel and natural source of therapeutics. The desert plant Achillea fragrantissima (Forssk) Sch. Bip (Af) is characterized by protective antioxidative and anti-inflammatory properties. Here, we examined the effect of two Af-derived phytochemicals on learning and memory, amyloid-β protein precursor (AβPP) metabolism, and tau phosphorylation in the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mouse model. We observed that mice that were injected with the phytochemicals showed a trend of improvement, albeit statistically insignificant, in the Novel Object Recognition task. However, we did not observe improvement in contextual fear conditioning, suggesting that the benefits of treatment may be either indirect or task-specific. In addition, we observed an increase in the full-length form of AβPP in the brains of mice treated with Af-derived phytochemicals. Interestingly, both in vivo and in vitro, there was no change in levels of soluble Aβ, oligomeric Aβ, or the carboxyl terminus fragments of AβPP (APP-CTFs), suggesting that the increase in full length AβPP does not exacerbate AβPP pathology, but may stabilize the full-length form of the molecule. Together, our data suggest that phytochemicals present in Af may have a modest positive impact on the progression of Alzheimer's disease.

Platelets: Peripheral Biomarkers of Dementia? - Akingbade, Oluwatomi E S; Gibson, Claire; Kalaria, Raj N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2018)
Dementia continues to be the most burdening neurocognitive disorder, having a negative impact on the lives of millions. The search for biomarkers to improve the clinical diagnosis of dementia is ongoing, with the focus on effective use of readily accessible peripheral markers. In this review, we concentrate on platelets as biomarkers of dementia and analyze their potential as easily-accessible clinical biomarkers for various subtypes of dementia. Current platelet protein biomarkers that have been investigated for their clinical utility in the diagnosis of dementia, in particular Alzheimer's disease, include amyloid-β protein precursor (AβPP), the AβPP secretases (BACE1 and ADAM10), α-synuclein, tau protein, serotonin, cholesterol, phospholipases, clusterin, IgG, surface receptors, MAO-B, and coated platelets. Few of them, i.e., platelet tau, AβPP (particularly with regards to coated platelets) and secreted ADAM10 and BACE1 show the most promise to be taken forward into clinical setting to diagnose dementia. Aside from protein biomarkers, changes in factors such as mean platelet volume have the potential to play a very specific role in both the dementia diagnosis and prognosis. This review raises a number of research questions for consideration before application of the above biomarkers to routine clinical setting. It is without doubt that there is a need for more clarification on the effects of dementia on platelet morphology and protein content before these changes can be clinically applied as dementia biomarkers and explored further in differentiating distinct dementia subtypes.

Polypharmacy and Potentially Inappropriate Medication in People with Dementia: A Nationwide Study. - Kristensen, Rachel Underlien; Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Wimberley, Theresa; Waldemar, Gunhild (J Alzheimers Dis, 2018)
BACKGROUND: Polypharmacy (use of ≥5 different medications) and potentially inappropriate medication (PIM) are well-known risk factors for numerous negative health outcomes. However, the use of polypharmacy and PIM in people with dementia is not well-described. OBJECTIVE: To examine the prevalence of polypharmacy and PIM in older people with and without dementia in a nationwide population. METHODS: Cross-sectional study of the Danish population aged ≥65 in 2014 (n = 1,032,120) based on register data, including information on diagnoses and dispensed prescriptions. Polypharmacy and PIM use among people with (n = 35,476) and without dementia (n = 994,231) were compared, stratified by living situation and adjusted for age, sex, and comorbidity. The red-yellow-green list from the Danish Institute for Rational Pharmacotherapy and the German PRISCUS list were used to define PIM. RESULTS: People with dementia were more frequently exposed to polypharmacy (dementia: 62.6% versus no-dementia: 35.1%, p < 0.001) and likewise PIM (red-yellow-green: 45.0% versus 29.7%, p < 0.001; PRISCUS: 24.4% versus 13.2%, p < 0.001). After adjustments for age, sex, and comorbidity, the likelihood of polypharmacy and PIM was higher for community-dwelling people with dementia than without dementia (odds ratio (OR); [95% confidence interval (CI)] polypharmacy: 1.50 [1.45-1.55]; red-yellow-green: 1.27 [1.23-1.31]; PRISCUS: 1.25 [1.20-1.30]). In contrast, dementia slightly decreased the odds of polypharmacy and PIM in nursing home residents. CONCLUSION: Use of polypharmacy and PIM were widespread in the older population and more so in people with dementia. This could have negative implications for patient-safety and demonstrates the need for interventions to improve drug therapy in people with dementia.

Possible Role of Chitin-Like Proteins in the Etiology of Alzheimer's Disease. - Lomiguen, Christine; Vidal, Luis; Kozlowski, Piotr; Prancan, Arthur; Stern, Robert (J Alzheimers Dis, 2018)
Chitin is a β-linked straight chain carbohydrate matrix monopolymer prominent in invertebrates, from fungi to arthropods. Surprisingly, chitin is now documented in vertebrates, including humans, a component of vertebrate physiology that has been neglected until now. Chitin levels are elevated in Alzheimer's disease (AD) patients, not only in the central nervous system but also in the cerebrospinal fluid and plasma. Elevated levels of chitin lectin have been reported in patients with AD. Chitinase activity varies widely in the human population. Chitin levels can increase in individuals with intrinsically low chitinase activity. Elevated amounts of chitin can reflect accumulation of the small chitin fragments that remain wherever rapid hyaluronan synthesis occurs. Another source of chitin may be from remote fungal infections. Chitin can be toxic for neurons, and its accumulation may lead to the development of AD. We present new suggestions for animal models and treatment modalities that could prove useful in future research endeavors. An unexpected connection with Gaucher's disease patients and their heterozygote relatives is also identified. These chitin-related mechanisms are novel approaches to AD whose etiology until now has defied explication.

Postmortem T2*- Weighted MRI Imaging of Cortical Iron Reflects Severity of Alzheimer's Disease. - Bulk, Marjolein; Kenkhuis, Boyd; Graaf, Linda M van der; Goeman, Jelle J; Natté, Remco; Weerd, Louise van der (J Alzheimers Dis, 2018)
The value of iron-based MRI changes for the diagnosis and staging of Alzheimer's disease (AD) depends on an association between cortical iron accumulation and AD pathology. Therefore, this study determined the cortical distribution pattern of MRI contrast changes in cortical regions selected based on the known distribution pattern of tau pathology and investigated whether MRI contrast changes reflect the underlying AD pathology in the different lobes. T2*-weighted MRI was performed on postmortem cortical tissue of controls, late-onset AD (LOAD), and early-onset AD (EOAD) followed by histology and correlation analyses. Combining ex vivo high-resolution MRI and histopathology revealed that: 1) LOAD and EOAD have a different distribution pattern of AD pathological hallmarks and MRI contrast changes over the cortex, with EOAD showing more severe MRI changes; 2) per lobe, severity of AD pathological hallmarks correlates with iron accumulation, and hence with MRI. Therefore, iron-sensitive MRI sequences allow detection of the cortical distribution pattern of AD pathology ex vivo.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

Prediction and Early Detection of Alzheimer's Dementia: Professional Disclosure Practices and Ethical Attitudes. - Schweda, Mark; Kögel, Anna; Bartels, Claudia; Wiltfang, Jens; Schneider, Anja; Schicktanz, Silke (J Alzheimers Dis, 2018)
BACKGROUND: Biomarker-supported testing for preclinical and prodromal Alzheimer's disease (AD) finds its way into clinical practice. Professional attitudes and practices regarding disclosure and ethical issues are controversial in many countries. OBJECTIVES: Against this background, the objective was to survey the actual practice and the attitudes of physicians in German hospitals and memory clinics in order to explore possible practical insecurities and ethical concerns. METHODS: A detailed survey with 37 items was conducted among medical professionals at German hospitals and memory clinics (n = 108). Analyses were performed using SPSS 21.0 (IBM). Findings were based on frequency and percentage distribution. RESULTS: Nearly half of the respondents stated that persons with mild cognitive impairment and pathological cerebrospinal fluid biomarkers were informed they had or would soon develop AD. While 81% acknowledged a 'right not to know', 75% said that results were always communicated. A majority agreed there was a benefit of prediction or later life planning [end-of-life, financial, family, housing (73-75%)] but also expected high psychological stress (82%) and self-stigmatization (70%) for those tested. CONCLUSIONS: There is considerable heterogeneity and insecurity regarding prediction and early detection in the context of AD in Germany. Information of professionals and standardization of professional testing and disclosure practices are needed.

Preoperative Phosphorylated Tau Concentration in the Cerebrospinal Fluid Can Predict Cognitive Function Three Years after Shunt Surgery in Patients with Idiopathic Normal Pressure Hydrocephalus. - Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Kawamura, Kaito; Kamohara, Chihiro; Fusegi, Keiko; Harada, Yoshinao; Hara, Takeshi; Sugano, Hidenori; Tange, Yuichi; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is commonly treated by cerebrospinal fluid (CSF) shunting. However, the long-term efficacy of shunt intervention in the presence of comorbid Alzheimer's disease (AD) pathology is debated. OBJECTIVE: To identify AD-associated CSF biomarkers predictive of shunting surgery outcomes in patients with iNPH. METHODS: Preoperative levels of total and phosphorylated Tau (p-Tau) were measured in 40 patients with iNPH divided into low (<30 pg/mL) and high (≥30 pg/mL) p-Tau groups and followed up for three years after lumboperitoneal shunting. The modified Rankin Scale (mRS), Mini-Mental State Examination (MMSE), Frontal Assessment Battery, and iNPH Grading Scale scores were compared between the age-adjusted low (n = 24; mean age 75.7 years [SD 5.3]) and high (n = 11; mean age 76.0 years [SD 5.6]) p-Tau groups. RESULTS: Cognitive function improved early in the low p-Tau group and was maintained thereafter (p = 0.005). In contrast, the high p-Tau group showed a gradual decline to baseline levels by the third postoperative year (p = 0.040). Although the p-Tau concentration did not correlate with the preoperative MMSE score, a negative correlation appeared and strengthened during follow-up (R2 = 0.352, p < 0.001). Furthermore, the low p-Tau group showed rapid and sustained mRS grade improvement, whereas mRS performance gradually declined in the high p-Tau group. CONCLUSIONS: Preoperative CSF p-Tau concentration predicted some aspects of cognitive function after shunt intervention in patients with iNPH. The therapeutic effects of shunt treatment were shorter-lasting in patients with coexisting AD pathology.

Prevalence and Determinants of Agonistic Autoantibodies Against α1-Adrenergic Receptors in Patients Screened Positive for Dementia: Results from the Population-Based DelpHi-Study. - Thyrian, Jochen René; Hertel, Johannes; Schulze, Lara N; Dörr, Marcus; Prüss, Harald; Hempel, Petra; Bimmler, Marion; Kunze, Rudolf; Grabe, Hans Jörgen; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to assess promising biomarkers for diagnosis and treatment response in real-life settings. Despite the important role of vascular risk factors, cardiovascular biomarkers have played a minor role in dementia research. Agonistic autoantibodies (agAAB) directed against G-protein-coupled receptors (GPCR) are discussed as modulators of pathology and clinical manifestation. OBJECTIVE: 1) Describe prevalence of agAAB directed against GPCR, especially agABB against α1-adrenergic receptors (α1-AR-agAAB) and agABB directed against β2-adrenergic receptors (β2-AR-agAAB) and 2) identify factors associated with agAAB in people with dementia during routine care. METHODS: Blood samples and data from 95 subjects who screened positive for dementia from a primary care cohort, analyzed using an enzyme-linked immunosorbent assay (ELISA) for detecting agAAB. Sociodemographic and clinical data were assessed, and medical records checked. RESULTS: In 40 (42%) samples, agAAB was detected, with n = 29 (31%) representing α1-AR-agAAB and n = 21 (22%) β2-AR-agAAB. There was no association between the presence of any antibody and a formal diagnosis of dementia. However, patients with coronary heart disease were more likely (OR = 4.23) to have α1-AR-agAAB than those without coronary heart disease. There were no associations between agAAB and age, sex, education, or cognitive impairment. DISCUSSION: For the first time, we show that autoantibodies have a significant prevalence in people with dementia in a routine care setting. Previous findings were restricted to highly selective samples. We replicated the association between α1-AR-agAAB in patients with coronary heart diseases but were not able to find other factors associated with the presence of agAAB.

Prevalence, Semiology, and Risk Factors of Epilepsy in Alzheimer's Disease: An Ambulatory EEG Study. - Horváth, András; Szűcs, Anna; Hidasi, Zoltán; Csukly, Gábor; Barcs, Gábor; Kamondi, Anita (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the primary cause of cognitive decline. A growing body of evidence suggests that AD patients have a higher risk to develop epileptic seizures; however, results are contradictory due to different methodological approaches of previous studies. OBJECTIVE: We aimed to identify the prevalence, semiology, and risk factors of epilepsy in AD using long-term EEG. METHODS: We selected forty-two AD patients and examined them using 24-hour ambulatory EEG. Neurological and epileptological data were collected with retro- and prospective methods. We analyzed the semiology of the identified seizures and the possible risk factors using logistic regression analysis. RESULTS: We identified seizures confirmed by EEG in 24%. The majority of the seizures were aware focal (72%) without any motor activity (55%). We found epileptiform discharges without seizures in 28%. Patients with seizures and only with epileptic EEG activity showed similar clinical and demographical features. Higher education (OR:1.8) and lower Addenbrooke Examination Score (OR: 0.9) were identified as risk factors of epilepsy. Increase of 0.1 point in the Verbal-Language/Orientation-Memory ratio (VLOM) was associated with higher epilepsy risk as well (OR:2.9). CONCLUSION: Epilepsy is a frequent comorbidity of AD. Since most of the seizures are aware non-motor focal seizures, sensitive EEG techniques are required for precise diagnosis of epilepsy. Long-term ambulatory EEG is a safe and well-tolerated option. Epileptiform EEG in AD signals the presence of concomitant epilepsy. Clinicians have to pay attention to comorbid epilepsy in dementia patients with high education, with high VLOM ratio and severe stage.

The Price of Stress: High Bedtime Salivary Cortisol Levels Are Associated with Brain Atrophy and Cognitive Decline in Stroke Survivors. Results from the TABASCO Prospective Cohort Study. - Tene, Oren; Hallevi, Hen; Korczyn, Amos D; Shopin, Ludmila; Molad, Jeremy; Kirschbaum, Clemens; Bornstein, Natan M; Shenhar-Tsarfaty, Shani; Kliper, Efrat; Auriel, Eitan; Usher, Sali; Stalder, Tobias; et al. (J Alzheimers Dis, 2018)
BACKGROUND AND OBJECTIVE: Previous studies suggest that excessive cortisol levels after stroke are associated with cognitive dysfunction. However, limited data exist regarding associations between post-stroke cortisol levels, brain abnormalities, genetic factors, and cognitive outcome. We sought to study these issues in a longitudinal stroke survivors cohort. METHODS: Data from 182 cognitively intact ischemic stroke patients from the TABASCO study were available. Saliva cortisol levels (bedtime and post-awakening) and cognitive assessments were obtained on admission, and 6, 12, and 24 months thereafter. During hospitalization, patients underwent 3T MRI scans and APOE genotyping. RESULTS: Higher bedtime cortisol levels immediately post-stroke were associated with larger neurological deficits (p < 0.001), brain atrophy (p = 0.025), worse white matter integrity (p = 0.003), and worse cognitive results up to 24 months post-stroke. These findings remained significant when adjusted for age, gender, education, smoking, stroke severity, apolipoprotein E4 (ApoE4) status, and body mass index. ApoE4 negatively modified the relation between cortisol and memory. As a group, participants who presented with high admission bedtime cortisol levels continued to present relatively elevated bedtime levels across all examined time-points, and this group had inferior memory and executive functioning scores compared to the lower cortisol group 24 months post-stroke (p = 0.05, p = 0.035, respectively). Post-awakening cortisol levels were not associated with neuroimaging findings or cognitive scores. CONCLUSIONS: High bedtime salivary cortisol levels post-stroke may provide information about dysregulation of diurnal HPA-axis activity under acute challenge conditions, and predict worse cognitive outcome. ApoE4 genotype might modify this association. These findings call for specific stress management interventions in stroke survivors.

Prodromal Alzheimer's Disease Demonstrates Increased Errors at a Simple and Automated Anti-Saccade Task. - Holden, John G; Cosnard, Alexandre; Laurens, Brice; Asselineau, Julien; Biotti, Damien; Cubizolle, Stéphanie; Dupouy, Sandrine; Formaglio, Maıté; Koric, Lejla; Seassau, Magali; Tilikete, Caroline; Vighetto, Alain; et al. (J Alzheimers Dis, 2018)
Saccade alterations are potential early signs of Alzheimer's disease. However, uncertainty persists in how early and reliably automated saccade recording systems detect impairments. This multicenter pathophysiological case-control transversal study explored saccade execution in carefully diagnosed amnestic mild cognitive impairment patients fulfilling research criteria for prodromal Alzheimer's disease (n = 29), as compared to both aged-matched mild Alzheimer's disease patients (n = 23) and controls (n = 27). Auto-coded saccades from horizontal (gap) vertical (step) stimulus elicited pro-saccades, and anti-saccade (gap) tasks were compared across the 3 groups. Mild cognitive impairment patients committed significantly more anti-saccade errors compared to controls (46.9 versus 24.3%, p < 0.001). Conventional analyses of the auto-coded stimulus elicited saccades parameters did not distinguish the amnestic mild cognitive impairment from controls or the mild Alzheimer's disease group. However, an offline analysis of manually coded saccade latencies, using resampling statistics did reveal subtle differences among the groups. Analysis of the manually coded data revealed that the mild Alzheimer's disease group had a reliably larger self-corrected error-rate than in amnestic mild cognitive impairment and controls (p = 0.003). Analysis of the manually coded saccade latencies, using more sensitive lognormal bootstrap analysis revealed a continuum, from amnestic mild cognitive impairment to mild Alzheimer's disease, of an increased severity of impaired inhibition of stimulus elicited saccades and correct voluntary saccade initiation. Anti-saccade error rates and psychometric measures of executive and several other cognitive functions were moderately and negatively correlated. Overall, inhibitory impairments in stimulus elicited saccades, characteristic of Alzheimer's disease, may be detected early in presumed prodromal patients using a simple, automated anti-saccade task.

Progression of Alzheimer's Disease: A Longitudinal Study in Norwegian Memory Clinics. - Eldholm, Rannveig Sakshaug; Barca, Maria Lage; Persson, Karin; Knapskog, Anne-Brita; Kersten, Hege; Engedal, Knut; Selbæk, Geir; Brækhus, Anne; Skovlund, Eva; Saltvedt, Ingvild (J Alzheimers Dis, 2018)
BACKGROUND: The course of Alzheimer's disease (AD) varies considerably between individuals. There is limited evidence on factors important for disease progression. OBJECTIVE: The primary aim was to study the progression of AD, as measured by the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB). Secondary aims were to investigate whether baseline characteristics are important for differences in progression, and to examine the correlation between progression assessed using three different instruments: CDR-SB (0-18), the cognitive test Mini-Mental State Examination (MMSE, 0-30), and the functional measure Instrumental Activities of Daily Living (IADL, 0-1). METHODS: The Progression of AD and Resource use (PADR) study is a longitudinal observational study in three Norwegian memory clinics. RESULTS: In total, 282 AD patients (mean age 73.3 years, 54% female) were followed for mean 24 (16-37) months. The mean annual increase in CDR-SB was 1.6 (SD 1.8), the mean decrease in MMSE score 1.9 (SD 2.6), and the mean decrease in IADL score 0.13 (SD 0.14). Of the 282 patients, 132 (46.8%) progressed slowly, with less than 1 point yearly increase in CDR-SB. Cognitive test results at baseline predicted progression rate, and together with age, ApoE, history of hypertension, and drug use could explain 17% of the variance in progression rate. The strongest correlation of change was found between CDR-SB and IADL scores, the weakest between MMSE and IADL scores. CONCLUSION: Progression rate varied considerably among AD patients; about half of the patients progressed slowly. Cognitive test results at baseline were predictors of progression rate.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Disease Progression; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory; Neuropsychological Tests; Norway

The Progression of Dementia and Cognitive Decline in a Dutch 2-Year Cohort Study of People with Young-Onset Dementia. - Gerritsen, Adrie A J; Bakker, Christian; Verhey, Frans R J; Bor, Hans; Pijnenburg, Yolande A L; de Vugt, Marjolein E; Koopmans, Raymond T C M (J Alzheimers Dis, 2018)
BACKGROUND: The progression of dementia in people with young-onset dementia (YOD) is relatively unknown. OBJECTIVE: To investigate the progression of dementia and cognitive decline in the three most common subtypes in YOD and to explore which factors are associated with this course. METHODS: The course of dementia was examined in 198 people with YOD. The primary outcomes were cognitive function, as assessed by the Mini-Mental State Examination (MMSE) and dementia severity, as assessed by the Global Deterioration Scale (GDS). Mixed-model analyses were used to explore factors associated with the course of dementia of the diagnostic sub-types. RESULTS: The mean overall two-year progression of dementia severity was 0.9 GDS points, this was a statistically significant change (p = 0.012) and was not significant different for the three dementia subtypes. The mean overall two-year decline in cognitive function was 1.6 points on the MMSE. The differences in cognitive decline were statistically significant (p = 0.046) among the three diagnosis groups, AD participants showed the greatest decline, of 2.3 points. In addition to lower education (p = 0.010), higher scores on the Neuropsychiatric Inventory (NPI) sub-syndromes psychosis (p < 0.001) and hyperactivity (p = 0.002) were associated with higher rates of cognitive decline. In contrast, higher scores on the NPI affect cluster were associated with lower levels of cognitive decline (p < 0.001). CONCLUSION: Different YOD subtypes show different rates of decline in cognitive functioning, and this decline seems less progressive compared to those observed in studies in late-onset AD. Further research is needed to evaluate whether managing neuropsychiatric symptoms can positively influence the decline of cognitive function.

The Progression of Neuropsychiatric Symptoms in Alzheimer's Disease During a Five-Year Follow-Up: Kuopio ALSOVA Study. - Hallikainen, Ilona; Hongisto, Kristiina; Välimäki, Tarja; Hänninen, Tuomo; Martikainen, Janne; Koivisto, Anne M (J Alzheimers Dis, 2018)
BACKGROUND: An improved understanding of the role of neuropsychiatric symptoms (NPS) in the course of Alzheimer's disease (AD) has recently emerged. NPS lead to hospitalization and caregiver stress, but are more variable during the course of the disease than other symptoms. Knowledge about the role of specific NPS in disease progression and prognosis is especially limited. OBJECTIVES: To examine the relationship between specific NPS and AD severity during a 5-year follow-up period, and to determine which baseline NPS predict AD progression. METHODS: 236 persons with very mild (CDR 0.5) or mild (CDR 1) AD at baseline and their caregivers were followed up for five years as part of the ALSOVA study. The Neuropsychiatric Inventory was used to assess NPS, and AD severity progression was measured with the Clinical Dementia Rating Sum of Boxes. Data was analyzed with Generalized Estimated Equations and Linear Mixed Models. RESULTS: The baseline NPS that best predicted AD progression were delusions, agitation, and aberrant motor behavior, while AD severity during follow-up was associated with hallucinations, delusions, agitation, apathy, aberrant motor behavior, and sleep and appetite disturbances. CONCLUSIONS: Persons with mild AD presenting delusions, agitation, and aberrant motor behavior at the time of diagnosis could have a more rapidly progressing disease, and some NPS are associated with AD severity. These results highlight the importance of evaluating NPS at the time of AD diagnosis, and the need to offer additional support to persons presenting delusions, agitation and aberrant motor behavior, and their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety; Caregivers; Delusions; Disease Progression; Female; Finland; Hallucinations; Humans; Linear Models; Male; Motor Activity; Multivariate Analysis; Neuropsychological Tests; Severity of Illness Index

Prominent Non-Memory Deficits in Alzheimer's Disease Are Associated with Faster Disease Progression. - Scheltens, Nienke M E; Tijms, Betty M; Heymans, Martijn W; Rabinovici, Gil D; Cohn-Sheehy, Brendan I; Miller, Bruce L; Kramer, Joel H; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Scheltens, Philip; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a heterogeneous disorder. OBJECTIVE: To investigate whether cognitive AD subtypes are associated with different rates of disease progression. METHODS: We included 1,066 probable AD patients from the Amsterdam Dementia Cohort (n = 290), Alzheimer's Disease Neuroimaging Initiative (n = 268), Dementia Competence Network (n = 226), and University of California, San Francisco (n = 282) with available follow-up data. Patients were previously clustered into two subtypes based on their neuropsychological test results: one with most prominent memory impairment (n = 663) and one with most prominent non-memory impairment (n = 403). We examined associations between cognitive subtype and disease progression, as measured with repeated Mini-Mental State Examination (MMSE) and Clinical Dementia Rating scale sum of boxes (CDR sob), using linear mixed models. Furthermore, we investigated mortality risk associated with subtypes using Cox proportional hazard analyses. RESULTS: Patients were 71±9 years old; 541 (51%) were female. At baseline, pooled non-memory patients had worse MMSE scores (23.1±0.1) and slightly worse CDR sob (4.4±0.1) than memory patients (MMSE 24.0±0.1; p < 0.001; CDR sob 4.1±0.1; p < 0.001). During follow-up, pooled non-memory patients showed steeper annual decline in MMSE (-2.8±0.1) and steeper annual increase in CDR sob (1.8±0.1) than memory patients (MMSE - 1.9±0.1; pinteraction<0.001; CDR sob 1.3±0.1; pinteraction<0.001). Furthermore, the non-memory subtype was associated with an increased risk of mortality compared with the memory subtype at trend level (HR = 1.36, CI = 1.00-1.85, p = 0.05). CONCLUSIONS: AD patients with most prominently non-memory impairment show faster disease progression and higher risk of mortality than patients with most prominently memory impairment.

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantifying the Diagnostic Pathway for Patients with Cognitive Impairment: Real-World Data from Seven European and North American Countries. - Ritchie, Craig W; Black, Christopher M; Khandker, Rezaul K; Wood, Robert; Jones, Eddie; Hu, Xiaohan; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
To ensure that patients with dementia and their caregivers receive appropriate treatment and support, early diagnosis is essential but remains challenging. Real-world data from a multi-national, cross-sectional survey of physicians and their patients were analyzed to quantify the diagnostic pathway for dementia, including a focus on severity of patients' cognitive impairment (CI) at the time of symptom onset, referral and subsequent diagnosis. Data were collected for 7,620 patients with CI. Most patients saw a healthcare professional within 1 year of first symptoms and received a diagnosis within 3-7 months of initial consultation. However, only 20% of patients received a diagnosis before their disease progressed beyond the prodromal stage and 23.5% already had moderate CI at diagnosis. These findings show that the goal of identifying and diagnosing CI at the earliest stages of disease is, for many patients, not achieved. Efforts toward public awareness and proactive, earlier detection and intervention, must be maintained-indeed where possible invigorated.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative PET and Histology of Brain Biopsy Reveal Lack of Selective Pittsburgh Compound-B Binding to Intracerebral Amyloidoma. - Groot, Colin; Tolboom, Nelleke; Ikonomovic, Milos D; Lammertsma, Adriaan A; Boon, Baayla D C; Barkhof, Frederik; Scheltens, Philip; Klunk, William E; Rozemuller, Annemieke J M; Ossenkoppele, Rik; van Berckel, Bart N M (J Alzheimers Dis, 2018)
This single case study examines selective Pittsburgh compound-B (PiB) binding to an intracerebral light-chain amyloidoma using a 90-minute dynamic [11C]PiB-PET scan and brain biopsy tissue. Parametric non-displaceable binding potential (BPND) images showed low specific binding in the amyloidoma (BPND = 0.23), while relative tracer delivery was adequate (R1 = 0.44). Histology of the tissue revealed strong coloring with Congo-red, thioflavin-S, and X-34, indicating presence of amyloid. However, immunological staining with 6F/3D revealed absence of amyloid-β and histofluorescence of 6-CN-PiB, a highly fluorescent derivative of PiB, was at background levels. Our results suggest that PiB does not detect the atypical amyloid pathology associated with an intracerebral light-chain amyloidoma. These findings are of interest to clinicians and researchers applying [11C]PiB-PET to detect atypical forms of amyloid pathology.

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Reaction of Amyloid-β Peptide Antibody with Different Infectious Agents Involved in Alzheimer's Disease. - Vojdani, Aristo; Vojdani, Elroy; Saidara, Evan; Kharrazian, Datis (J Alzheimers Dis, 2018)
As early as the 1980s, molecular virologist Ruth Itzhaki began to investigate if there was a causal connection between infections and neurodegenerative disorder. Although the theory has yet to be universally embraced, in 2016 Itzhaki and 33 other scientists from all over the world published a review article in this very journal presenting evidence for the causal role of pathogens in Alzheimer's disease (AD). Exactly how and in what way pathogens affect the induction of AD has yet to be determined, but one possible answer may involve the cross-reactivity of different pathogens with amyloid-β (Aβ). Aβ autoantibodies have been detected in the serum and cerebrospinal fluid of AD patients and in some healthy individuals. In the present study our major goal was to investigate whether antibodies made against Aβ would react both with other brain proteins as well as pathogens associated with AD as a result of molecular mimicry or the binding of bacterial toxins to Aβ42. Our study used a specific monoclonal antibody made against Aβ42, which not only reacted strongly with Aβ42, tau protein, and α-synuclein, but also had from weak to strong reactions with 25 different pathogens or their molecules, some of which have been associated with AD. The homology between peptide stretches of microbial origin and proteins involved in AD could be a mechanism by which antibodies to homologous peptides mount attacks against autoantigens in AD. We concluded that bacterial molecules bind to Aβ protein, forming small oligomers, then encasing pathogens and their molecules to form amyloid plaques, the tell-tale markers of AD. Conversely, these same Aβ peptides induce the production of antibodies to both Aβ42 and bacterial molecules, which may inhibit bacterial pathogenesis, but in the process may promote amyloid plaque formation.

Real-World, Multinational, Retrospective Observational Survey of the ADAS-Cog and Associations with Healthcare Resource Utilization in Patients with Alzheimer's Disease. - Ritchie, Craig W; Khandker, Rezaul K; Pike, James; Black, Christopher M; Jones, Eddie; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is one of the most costly conditions, both economically and regarding patient disability and dependency. The huge costs coupled with the predicted increase in prevalence worldwide are likely to challenge healthcare systems in the future. The classic version of the Alzheimer's Disease Assessment Scale-Cognition subscale (ADAS-Cog) is generally seen as the current gold standard primary outcome measure of cognitive symptom progression in dementia clinical trials. OBJECTIVE: This study evaluated the relationship between ADAS-Cog scores as a measure of clinical progression and the healthcare resource utilization (HCRU)-measured burden of cognitive impairment in patients with mild cognitive impairment, AD, or suspected AD in the real world. METHODS: A retrospective observational survey of physicians and their consulting patients with multiple ADAS-Cog scores. Regression models were constructed for HCRU variables (e.g., consultations, hospitalizations, caregiving requirements) with ADAS-Cog rate of change, baseline ADAS-Cog, and their interaction included as exposure variables. RESULTS: 651 patient records were completed by 154 physicians. Approximately 70% of patients had mild to moderate dementia. In 56.7% of patients, clinical progression was maintained/stable from baseline. Mean change in ADAS-Cog (adjusted to 12 months) was 2.8 points and change scores increased with increasing dementia severity. Most HCRU variables increased significantly (p < 0.05; joint test) with increasing ADAS-Cog scores (indexing clinical deterioration). CONCLUSION: The results suggest that further understanding the relationship between HCRU and ADAS-Cog changes in real-world clinical practice could potentially provide a baseline upon which the success of disease-modifying, as well as newer symptomatic, dementia therapies can be judged.

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

Relationship Between Body Mass Index, ApoE4 Status, and PET-Based Amyloid and Neurodegeneration Markers in Amyloid-Positive Subjects with Normal Cognition or Mild Cognitive Impairment. - Blautzik, Janusch; Kotz, Sebastian; Brendel, Matthias; Sauerbeck, Julia; Vettermann, Franziska; Winter, Yaroslav; Bartenstein, Peter; Ishii, Kazunari; Rominger, Axel (J Alzheimers Dis, 2018)
Body weight loss in late-life is known to occur at a very early stage of Alzheimer's disease (AD). Apolipoprotein E4 (ApoE4) represents a major genetic risk factor for AD and is linked to an increased cortical amyloid-β (Aβ) accumulation. Since the relationship between body weight, ApoE4, and AD pathology is poorly investigated, we aimed to evaluate whether ApoE4 allelic status modifies the association of body mass index (BMI) with markers of AD pathology. A total of 368 Aβ-positive cognitively healthy or mild cognitive impaired subjects had undergone [18F]-AV45-PET, [18F]-FDG-PET, and T1w-MRI examinations. Composite cortical [18F]-AV45 uptake and [18F]-FDG uptake in posterior cingulate cortex were calculated as surrogates of cortical Aβ load and glucose metabolism, respectively. Multiple linear regressions were performed to assess the relationships between these PET biomarkers with BMI, present cognitive performance, and cognitive changes over time. Multivariate analysis of covariance was conducted to test for statistical differences between ApoE4/BMI categories on the PET markers and cognitive scores. In carriers of the ApoE4 allele only, BMI was inversely associated with cortical amlyoid load (β= -0.193, p < 0.005) and recent cognitive decline (β= -0.209, p < 0.05), and positively associated with cortical glucose metabolism in an AD-vulnerable region (β= 0.145, p < 0.05). ApoE4/BMI category analyses demonstrated lower Aβ load, higher posterior cingulate glucose metabolism, improved cognitive performance, and lower progression of cognitive decline in obese ApoE4 carriers. The effect of ApoE4 in promoting the accumulation of cortical amyoid, which may itself be a driver for weight loss, may be moderated by altering leptin signaling in the hypothalamus.

Relationship of Area of Soft Drusen in Retina with Cerebral Amyloid-β Accumulation and Blood Amyloid-β Level in the Elderly. - Shoda, Chiho; Kitagawa, Yorihisa; Shimada, Hiroyuki; Yuzawa, Mitsuko; Tateno, Amane; Okubo, Yoshiro (J Alzheimers Dis, 2018)
BACKGROUND: Histopathological studies have confirmed that soft drusen contains amyloid-β (Aβ). OBJECTIVE: To examine the relationship between the area of soft drusen in the macular area and cerebral Aβ accumulation or plasma Aβ level in elderly persons without dementia. METHODS: Fourteen consecutive patients (18 eyes) aged ≥50 years with macular soft drusen were studied prospectively. From color fundus photographs, the area of soft drusen (pixel) within a 6,000 μm diameter with the macula as center was measured. Standard uptake value ratio (SUVR) was obtained from positron emission tomography using florbetapir, which indicates the ratio of cerebral cortical-to-cerebellar Aβ accumulation. Ratio of plasma Aβ1-42 to Aβ1-40 level was calculated. RESULTS: Mean age was 73.3±7.6 years. The soft drusen area was 4.32±2.42 mm2. The SUVR was 1.08±0.15. Plasma Aβ1-42/Aβ1-40 ratio was 0.17±0.08. When SUVR ≥1.10 was defined as positive and <1.10 as negative, the soft drusen area in SUVR-positive patients (6.19±1.14 mm2) was significantly (p = 0.0043) larger than that in SUVR-negative patients (3.13±2.27 mm2). Multivariate regression analysis showed that SUVR positivity correlated with soft drusen area (p = 0.0484) and with Voxel-based Specific Regional Analysis System for Alzheimer's Disease score (p = 0.0360). However, there was no correlation with gender (p = 0.1921), age (p = 0.2361), Alzheimer's Disease Assessment Scale score (p = 0.6310), Mini-Mental State Examination score (p = 0.4246), or plasma Aβ1-42/Aβ1-40 ratio (p = 0.8398). CONCLUSION: Among elderly persons without dementia, the area of soft drusen was larger in those with more extensive cerebral Aβ accumulation. The area of soft drusen may be a biomarker of cerebral Aβ accumulation.

Relationships between Cognition and Activities of Daily Living in Alzheimer's Disease During a 5-Year Follow-Up: ALSOVA Study. - Saari, Toni; Hallikainen, Ilona; Hänninen, Tuomo; Räty, Hannu; Koivisto, Anne (J Alzheimers Dis, 2018)
BACKGROUND: Impaired cognition and activities of daily living (ADL) are core symptoms of Alzheimer's disease (AD), but their relationship is unclear. OBJECTIVES: To explore relationships between cognitive domains and functional ability during 5-year follow-up in persons with AD. METHODS: We analyzed ALSOVA study data from 236 individuals with very mild or mild AD at baseline. The CERAD Neuropsychological Battery (CERAD-NB) was used as a cognitive measure and Alzheimer's Disease Cooperative Study ADL (ADCS-ADL) as a functional measure, analyzing the IADL and BADL sub-scores separately. Annual regression models and linear mixed-effect models (LMMs) covering a 5-year follow-up period were used. RESULTS: Annually, the CERAD-NB total and especially Verbal Fluency, Clock Drawing, and Constructional Praxis were associated with the total ADCS-ADL and IADL scores increasingly yet modestly, and to a lesser extent the BADL score. In the LMMs, the same measures and MMSE were associated with ADL. CONCLUSION: Measures of executive function and visuoconstructive skills appear to be associated with caregiver-interview based ADL measure during the progression of AD.

Relevance of Coded Prodromal Mild Cognitive Impairment in the Routine Treatment of Patients with Dementia in Germany. - Bohlken, Jens; Kostev, Karel (J Alzheimers Dis, 2018)
Little is known about the impact of prior mild cognitive impairment (MCI, ICD-10: F06.7) diagnosis on the time to dementia diagnosis, anti-dementia drug therapy, and treatment persistence in patients with dementia (PWD). Patients with dementia diagnoses who started anti-dementia therapy between January 2010 and December 2016 were selected from 203 neurological/psychiatric practices in the Disease Analyzer databank (IQVIA). Patients with a history of MCI were compared to non-MCI controls in terms of demographic characteristics, anti-dementia therapy, and the rate of persistence with anti-dementia drugs. For persistence analyses, a 1:1 matching procedure was used based on age, gender, type of residence, and depression and dementia diagnosis. Persistence was represented using Kaplan-Meier curves. A Cox regression analysis was used to determine the influence of MCI diagnosis on persistence with anti-dementia drugs. 339 PWD with MCI diagnoses and 339 controls were available for analysis. PWD with MCI were younger (78.9 versus 80.4 years), less likely to live in a nursing home (8.5% versus 22.5%), more frequently received donepezil (40.1% versus 33.7%), and more likely to exhibit comorbid depression (29.6% versus 16.9%). There was no association between the risk of treatment discontinuation and prior MCI diagnosis. After 24 months, 40% versus 41.1% of patients had discontinued treatment. The prior MCI diagnosis presumably led to an earlier diagnosis of dementia and earlier anti-dementia treatment. Treatment continuity did not differ, which would suggest that it does not depend on prior MCI diagnosis but on the behavior of patients and their caregiving relatives.

The Relevance of Iron in the Pathogenesis of Multiple System Atrophy: A Viewpoint. - Kaindlstorfer, Christine; Jellinger, Kurt A; Eschlböck, Sabine; Stefanova, Nadia; Weiss, Günter; Wenning, Gregor K (J Alzheimers Dis, 2018)
Iron is essential for cellular development and maintenance of multiple physiological processes in the central nervous system. The disturbance of its homeostasis leads to abnormal iron deposition in the brain and causes neurotoxicity via generation of free radicals and oxidative stress. Iron toxicity has been established in the pathogenesis of Parkinson's disease; however, its contribution to multiple system atrophy (MSA) remains elusive. MSA is characterized by cytoplasmic inclusions of misfolded α-synuclein (α-SYN) in oligodendrocytes referred to as glial cytoplasmic inclusions (GCIs). Remarkably, the oligodendrocytes possess high amounts of iron, which together with GCI pathology make a contribution toward MSA pathogenesis likely. Consistent with this observation, the GCI density is associated with neurodegeneration in central autonomic networks as well as olivopontocerebellar and striatonigral pathways. Iron converts native α-SYN into a β-sheet conformation and promotes its aggregation either directly or via increasing levels of oxidative stress. Interestingly, α-SYN possesses ferrireductase activity and α-SYN expression underlies iron mediated translational control via RNA stem loop structures. Despite a correlation between progressive putaminal atrophy and iron accumulation as well as clinical decline, it remains unclear whether pathologic iron accumulation in MSA is a secondary event in the cascade of neuronal degeneration rather than a primary cause. This review summarizes the current knowledge of iron in MSA and gives evidence for perturbed iron homeostasis as a potential pathogenic factor in MSA-associated neurodegeneration.
Keywords: alpha-Synuclein; Brain; Humans; Inclusion Bodies; Iron; Magnetic Resonance Imaging; Multiple System Atrophy; Oligodendroglia; Parkinsonian Disorders

Reproducibility of Alzheimer's Disease Cerebrospinal Fluid-Biomarker Measurements under Clinical Routine Conditions. - Vogelgsang, Jonathan; Wedekind, Dirk; Bouter, Caroline; Klafki, Hans-W; Wiltfang, Jens (J Alzheimers Dis, 2018)
Analysis of cerebrospinal fluid (CSF) is one of the key tools for the state-of-the-art differential diagnosis of dementias. Dementia due to Alzheimer's disease (AD) is characterized by elevated CSF levels of total Tau (tTau) and phospho-181-Tau (pTau) and low CSF amyloid-β42 (Aβ42). Discrepancies in the laboratory analysis of human materials are well known and much effort has been put into harmonization procedures. In this study, we measured CSF biomarkers of more than 100 patients obtained under clinical routine conditions in two different clinical laboratories. The CSF biomarker levels obtained from the two different sites were significantly correlated: R2 = 0.7129 (tTau, p < 0.001), 0.7914 (pTau, p < 0.001), 0.5078 (Aβ42, p < 0.001), 0.5739 (Aβ40, p < 0.001), and 0.4308 (Aβ42/40, p < 0.001). However, the diagnostic classifications of the Aβ42, tTau, and pTau levels of identical subjects into normal versus pathological range made by the two different sites showed substantial discrepancies (31.5%, 29.6%, and 25.0% discordant cases, respectively). Applying Aβ42/40, instead of CSF Aβ42 alone, lead to a reduction of the discordant cases to 16.8%. Our findings suggest that CSF Aβ42/40 can outperform Aβ42 as a biomarker for AD neuropathology, not only under well-controlled study conditions but also in real life clinical routine. Thus, we recommend the inclusion of Aβ42/40 as a CSF biomarker in the diagnostic procedure.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk Factors Associated with Cortical Thickness and White Matter Hyperintensities in Dementia Free Okinawan Elderly. - Silbert, Lisa C; Lahna, David; Promjunyakul, Nutta-On; Boespflug, Erin; Ohya, Yusuke; Higashiuesato, Yasushi; Nishihira, Junko; Katsumata, Yuriko; Tokashiki, Takashi; Dodge, Hiroko H (J Alzheimers Dis, 2018)
BACKGROUND: Cortical gray matter (GM) and white matter (WM) deterioration are signals of neurodegeneration and increased dementia risk; however, their specific etiologies in dementia-free aging is unclear. OBJECTIVE: The objective of this study was to examine potentially modifiable risk factors of GM and WM degeneration in a well-characterized cohort of dementia-free elderly. METHODS: 96 Okinawan elderly participants (age 83.6) from the Keys to Optimal Cognitive Aging Project (KOCOA) underwent MRI and cognitive evaluation. Serum markers of inflammation (interleukin-6 (IL-6), high sensitivity C-reactive protein), cerebrovascular disease (systolic blood pressure (SBP) 140+, hemoglobin A1C (HgbA1C), total cholesterol), and essential minerals (copper (Cu), magnesium, and calcium) were examined in relation to mean cortical thickness (MCT) and white matter hyperintensities (WMH), adjusting for age and gender. Voxel-based morphometry (VBM) analyses identified relationships between regional GM density and the above markers. RESULTS: Decreased MCT was associated with SBP 140 + (p = 0.029) and increased serum IL-6 (p = 0.036), HgbA1C (p = 0.002), and Cu (p = 0.025). In VBM analyses, increased IL-6, HgbA1C, and Cu were associated with decreased GM density in temporal lobe regions. HgbA1C (p = 0.004) was associated with greater WMH volume. CONCLUSIONS: Peripheral markers of Cu, CVD risk, and inflammation are associated with MRI-markers of decreased brain health in dementia-free Okinawan elderly, with regional cortical thinning in areas involved in early accumulation of Alzheimer's disease pathology. Results identify potentially modifiable biomarkers as targets in the prevention of dementia in older individuals.

Role of ASK1/p38 Cascade in a Mouse Model of Alzheimer's Disease and Brain Aging. - Hasegawa, Yu; Toyama, Kensuke; Uekawa, Ken; Ichijo, Hidenori; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2018)
To examine the role of ASK1 in Alzheimer's disease (AD), we generated 5XFAD mice deficient in ASK1 and investigated the characteristics of old 5XFAD and wild-type mice with ASK1 deficiency. ASK1 deficiency improved cognitive function in 24-month-old 5XFAD mice, which was associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade seems to play some role in the pathogenesis of AD in mice. In 24-month-old wild-type mice, ASK1 deficiency increased cerebral vasoreactivity to acetazolamide and significantly reduced brain soluble Aβ, which were also associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade may contribute to brain aging of wild-type mice. Collectively, our present results provided the evidence suggesting the involvement of ASK1/p38 cascade in AD and brain aging.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Avoidance Learning; Disease Models, Animal; Gene Expression Regulation; MAP Kinase Kinase Kinase 5; MAP Kinase Signaling System; Mice; Mice, Inbred C57BL; Mice, Transgenic; Presenilin-1; Reaction Time

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Separating Symptomatic Alzheimer's Disease from Depression based on Structural MRI. - Klöppel, Stefan; Kotschi, Maria; Peter, Jessica; Egger, Karl; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex; Heimbach, Bernhard; Normann, Claus; Vach, Werner; Urbach, Horst; Abdulkadir, Ahmed (J Alzheimers Dis, 2018)
Older patients with depression or Alzheimer's disease (AD) at the stage of early dementia or mild cognitive impairment may present with objective cognitive impairment, although the pathology and thus therapy and prognosis differ substantially. In this study, we assessed the potential of an automated algorithm to categorize a test set of 65 T1-weighted structural magnetic resonance images (MRI). A convenience sample of elderly individuals fulfilling clinical criteria of either AD (n = 28) or moderate and severe depression (n = 37) was recruited from different settings to assess the potential of the pattern recognition method to assist in the differential diagnosis of AD versus depression. We found that our algorithm learned discriminative patterns in the subject's grey matter distribution reflected by an area under the receiver operator characteristics curve of up to 0.83 (confidence interval ranged from 0.67 to 0.92) and a balanced accuracy of 0.79 for the separation of depression from AD, evaluated by leave-one-out cross validation. The algorithm also identified consistent structural differences in a clinically more relevant scenario where the data used during training were independent from the data used for evaluation and, critically, which included five possible diagnoses (specifically AD, frontotemporal dementia, Lewy body dementia, depression, and healthy aging). While the output was insufficiently accurate to use it directly as a means for classification when multiple classes are possible, the continuous output computed by the machine learning algorithm differed between the two groups that were investigated. The automated analysis thus could complement, but not replace clinical assessments.

Serotonin Selective Reuptake Inhibitor Treatment Improves Cognition and Grey Matter Atrophy but not Amyloid Burden During Two-Year Follow-Up in Mild Cognitive Impairment and Alzheimer's Disease Patients with Depressive Symptoms. - Brendel, Matthias; Sauerbeck, Julia; Greven, Sonja; Kotz, Sebastian; Scheiwein, Franziska; Blautzik, Janusch; Delker, Andreas; Pogarell, Oliver; Ishii, Kazunari; Bartenstein, Peter; Rominger, Axel (J Alzheimers Dis, 2018)
Late-life depression, even when of subsyndromal severity, has shown strong associations with mild cognitive impairment (MCI) and Alzheimer's disease (AD). Preclinical studies have suggested that serotonin selective reuptake inhibitors (SSRIs) can attenuate amyloidogenesis. Therefore, we aimed to investigate the effect of SSRI medication on amyloidosis and grey matter volume in subsyndromal depressed subjects with MCI and AD during an interval of two years. 256 cognitively affected subjects (225 MCI/ 31 AD) undergoing [18F]-AV45-PET and MRI at baseline and 2-year follow-up were selected from the ADNI database. Subjects with a positive depression item (DEP(+); n = 73) in the Neuropsychiatric Inventory Questionnaire were subdivided to those receiving SSRI medication (SSRI(+); n = 24) and those without SSRI treatment (SSRI(-); n = 49). Longitudinal cognition (Δ-ADAS), amyloid deposition rate (standardized uptake value, using white matter as reference region (SUVRWM), and changes in grey matter volume were compared using common covariates. Analyses were performed separately in all subjects and in the subgroup of amyloid-positive subjects. Cognitive performance in DEP(+)/SSRI(+) subjects (Δ-ADAS: -5.0%) showed less deterioration with 2-year follow-up when compared to DEP(+)/SSRI(-) subjects (Δ-ADAS: +18.6%, p < 0.05), independent of amyloid SUVRWM at baseline. With SSRI treatment, the progression of grey matter atrophy was reduced (-0.9% versus -2.7%, p < 0.05), notably in fronto-temporal cortex. A slight trend towards lower amyloid deposition rate was observed in DEP(+)/SSRI(+) subjects versus DEP(+)/SSRI(-). Despite the lack of effect to amyloid PET, SSRI medication distinctly rescued the declining cognitive performance in cognitively affected patients with depressive symptoms, and likewise attenuated grey matter atrophy.

Sex-Dependent Differences in Spontaneous Autoimmunity in Adult 3xTg-AD Mice. - Kapadia, Minesh; Mian, M Firoz; Michalski, Bernadeta; Azam, Amber B; Ma, Donglai; Salwierz, Patrick; Christopher, Adam; Rosa, Elyse; Zovkic, Iva B; Forsythe, Paul; Fahnestock, Margaret; Sakic, Boris (J Alzheimers Dis, 2018)
The triple-transgenic (3xTg-AD) mouse strain is a valuable model of Alzheimer's disease (AD) because it develops both amyloid-β (Aβ) and tau brain pathology. However, 1-year-old 3xTg-AD males no longer show plaques and tangles, yet early in life they exhibit diverse signs of systemic autoimmunity. The current study aimed to address whether females, which exhibit more severe plaque/tangle pathology at 1 year of age, show similar autoimmune phenomena and if so, whether these immunological changes coincide with prodromal markers of AD pathology, markers of learning and memory formation, and epigenetic markers of neurodegenerative disease. Six-month-old 3xTg-AD and wild-type mice of both sexes were examined for T-cell phenotype (CD3+, CD8+, and CD4+ populations), serological measures (autoantibodies, hematocrit), soluble tau/phospho-tau and Aβ levels, brain-derived neurotrophic factor (BDNF) expression, and expression of histone H2A variants. Although no significant group differences were seen in tau/phospho-tau levels, 3xTg-AD mice had lower brain mass and showed increased levels of soluble Aβ and downregulation of BDNF expression in the cortex. Splenomegaly, depleted CD+ T-splenocytes, increased autoantibody levels and low hematocrit were more pronounced in 3xTg-AD males than in females. Diseased mice also failed to exhibit sex-specific changes in histone H2A variant expression shown by wild-type mice, implicating altered nucleosome composition in these immune differences. Our study reveals that the current 3xTg-AD model is characterized by systemic autoimmunity that is worse in males, as well as transcriptional changes in epigenetic factors of unknown origin. Given the previously observed lack of plaque/tangle pathology in 1-year-old males, an early, sex-dependent autoimmune mechanism that interferes with the formation and/or deposition of aggregated protein species is hypothesized. These results suggest that more attention should be given to studying sex-dependent differences in the immunological profiles of human patients.

Sex-Related Reserve Hypothesis in Alzheimer's Disease: Changes in Cortical Thickness with a Five-Year Longitudinal Follow-Up. - Lee, Juyoun; Cho, Hanna; Jeon, Seun; Kim, Hee Jin; Kim, Yeo Jin; Lee, Jeongmin; Kim, Sung Tae; Lee, Jong-Min; Chin, Juhee; Lockhart, Samuel N; Lee, Ae Young; Na, Duk L; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Sex effects on the progression of Alzheimer's disease (AD) have received less attention than other demographic factors, including onset age and education. OBJECTIVE: The aim of this study was to investigate whether sex affected cortical thinning in the disease progression of AD. METHODS: We prospectively recruited 36 patients with early-stage AD and 14 people with normal cognition. All subjects were assessed with magnetic resonance imaging at baseline, Year 1, Year 3, and Year 5. We performed cortical thickness analyses using surface-based morphometry on magnetic resonance imaging. RESULTS: Women with AD showed more rapid cortical thinning in the left dorsolateral frontal cortex, left superior temporal gyrus, bilateral temporo-parietal association cortices, bilateral anterior cingulate gyri, bilateral medial frontal cortices, and bilateral occipital cortices over 5 years than men with AD, even though there was no difference in cortical thickness at baseline. In contrast, there were no regions of significantly more rapid atrophy in men with AD. CONCLUSIONS: Our findings suggest that women deteriorate faster than men in the progression of AD.

Simultaneous Aerobic Exercise and Memory Training Program in Older Adults with Subjective Memory Impairments. - McEwen, Sarah C; Siddarth, Prabha; Abedelsater, Berna; Kim, Yena; Mui, Wenli; Wu, Pauline; Emerson, Natacha D; Lee, Jacob; Greenberg, Shayna; Shelton, Tiffany; Kaiser, Scott; Small, Gary W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several modifiable lifestyle factors have been shown to have potential beneficial effects in slowing cognitive decline. Two such factors that may affect cognitive performance and slow the progression of memory loss into dementia in older adults are cognitive training and physical activity. There are currently no effective treatments for dementia; therefore, preventative strategies to delay or prevent the onset of dementia are of critical importance. OBJECTIVE: The aim of this study was to determine the relative effectiveness of simultaneous performance of memory training and aerobic exercise to a sequential performance intervention on memory functioning in older adults. METHODS: 55 older adults (aged 60- 75) with subjective memory impairments (non-demented and non-MCI) completed the intervention that consisted of 90-minute small group classes held twice weekly. Participants were randomized to either 4-weeks of supervised strategy-based memory training done simultaneously while stationary cycling (SIM) or sequentially after the stationary cycling (SEQ). Standardized neurocognitive measures of memory, executive functioning, speed of processing, attention, and cognitive flexibility were assessed at baseline and post-intervention. RESULTS: The SIM group, but not the SEQ group, had a significant improvement on composite memory following the intervention (t(51) = 2.7, p = 0.01, effect size (ES) = 0.42) and transfer to non-trained reasoning abilities (t(51) = 6.0, ES = 0.49) and complex attention (t(51) = 3.1, p = 0.003, ES = 0.70). Conversely, the SEQ group, but not the SIM, showed significant improvement in executive functioning (t(51) = 5.0, p = 0.0001, ES = 0.96). CONCLUSION: These findings indicate that a 4-week simultaneous memory training and aerobic exercise program is sufficient to improve memory, attention, and reasoning abilities in older adults.
Keywords: Aged; Attention; California; Cognition; Executive Function; Exercise; Female; Humans; Learning; Male; Memory; Memory Disorders; Middle Aged; Treatment Outcome

Sleep and EEG Power Spectral Analysis in Three Transgenic Mouse Models of Alzheimer's Disease: APP/PS1, 3xTgAD, and Tg2576. - Kent, Brianne A; Strittmatter, Stephen M; Nygaard, Haakon B (J Alzheimers Dis, 2018)
BACKGROUND: Sleep disturbances have long been associated with Alzheimer's disease (AD), and there is a growing interest in how these disturbances might impact AD pathophysiology. Despite this growing interest, surprisingly little is known about how sleep architecture and the broader neuronal network are affected in widely used transgenic mouse models of AD. OBJECTIVE: We analyzed sleep and electroencephalography (EEG) power in three transgenic mouse models of AD, using identical and commercially available hardware and analytical software. The goal was to assess the suitability of these mouse lines to model sleep and the broader neuronal network dysfunction measured by EEG in AD. METHODS: Tg2576, APP/PS1, and 3xTgAD transgenic AD mice were studied using in vivo EEG recordings for sleep/wake time and power spectral analysis. RESULTS: Both the APP/PS1 model at 8- 10 months and the Tg2576 model at 12 months of age exhibited stage-dependent decreases in theta and delta power, and shifts in the power spectra toward higher frequencies. Stage-dependent power spectral analyses showed no changes in the 3xTgAD model at 18 months of age. The percentage of time spent awake, in non-rapid eye movement sleep (NREM), or in rapid-eye-movement sleep (REM) was not different between genotypes in any of the transgenic lines. CONCLUSION: Our findings are consistent with data from several other transgenic AD models as well as certain studies in patients with mild cognitive impairment. Further studies will be needed to better understand the correlation between EEG spectra and AD pathophysiology, both in AD models and the human condition.

A Small Molecule Inhibitor of Plasminogen Activator Inhibitor-1 Reduces Brain Amyloid-β Load and Improves Memory in an Animal Model of Alzheimer's Disease. - Akhter, Hasina; Huang, Wen-Tan; van Groen, Thomas; Kuo, Hui-Chien; Miyata, Toshio; Liu, Rui-Ming (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a major cause of dementia in the elderly with no effective treatment. Accumulation of amyloid-β peptide (Aβ) in the brain is a pathological hallmark of AD and is believed to be a central disease-causing and disease-promoting event. In a previous study, we showed that deletion of plasminogen activator inhibitor 1 (PAI-1), a primary inhibitor of tissue type and urokinase type plasminogen activators (tPA and uPA), significantly reduced brain Aβ load in APP/PS1 mice, an animal model of familial AD. In this study, we further show that oral administration of TM5275, a small molecule inhibitor of PAI-1, for a period of 6 weeks, inhibits the activity of PAI-1 and increases the activities of tPA and uPA as well as plasmin, which is associated with a reduction of Aβ load in the hippocampus and cortex and improvement of learning/memory function in APP/PS1 mice. Protein abundance of low density lipoprotein related protein-1 (LRP-1), a multi ligand endocytotic receptor involved in transporting Aβ out of the brain, as well as plasma Aβ42 are increased, whereas the expression and processing of full-length amyloid-β protein precursor is not affected by TM5275 treatment in APP/PS1 mice. In vitro studies further show that PAI-1 increases, whereas TM5275 reduces, Aβ40 level in the culture medium of SHSY5Y-APP neuroblastoma cells. Collectively, our data suggest that TM5275 improves memory function of APP/PS1 mice, probably by reducing brain Aβ accumulation through increasing plasmin-mediated degradation and LRP-1-mediated efflux of Aβ in the brain.

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Stabilized Low-n Amyloid-β Oligomers Induce Robust Novel Object Recognition Deficits Associated with Inflammatory, Synaptic, and GABAergic Dysfunction in the Rat. - Watremez, William; Jackson, Joshua; Almari, Bushra; McLean, Samantha L; Grayson, Ben; Neill, Joanna C; Fischer, Nicolas; Allouche, Ahmad; Koziel, Violette; Pillot, Thierry; Harte, Michael K (J Alzheimers Dis, 2018)
BACKGROUND: With current treatments for Alzheimer's disease (AD) only providing temporary symptomatic benefits, disease modifying drugs are urgently required. This approach relies on improved understanding of the early pathophysiology of AD. A new hypothesis has emerged, in which early memory loss is considered a synapse failure caused by soluble amyloid-β oligomers (Aβo). These small soluble Aβo, which precede the formation of larger fibrillar assemblies, may be the main cause of early AD pathologies. OBJECTIVE: The aim of the current study was to investigate the effect of acute administration of stabilized low-n amyloid-β1-42 oligomers (Aβo1-42) on cognitive, inflammatory, synaptic, and neuronal markers in the rat. METHODS: Female and male Lister Hooded rats received acute intracerebroventricular (ICV) administration of either vehicle or 5 nmol of Aβo1-42 (10μL). Cognition was assessed in the novel object recognition (NOR) paradigm at different time points. Levels of inflammatory (IL-1β, IL-6, TNF-α), synaptic (PSD-95, SNAP-25), and neuronal (n-acetylaspartate, parvalbumin-positive cells) markers were investigated in different brain regions (prefrontal and frontal cortex, striatum, dorsal and ventral hippocampus). RESULTS: Acute ICV administration of Aβo1-42 induced robust and enduring NOR deficits. These deficits were reversed by acute administration of donepezil and rolipram but not risperidone. Postmortem analysis revealed an increase in inflammatory markers, a decrease in synaptic markers and parvalbumin containing interneurons in the frontal cortex, with no evidence of widespread neuronal loss. CONCLUSION: Taken together the results suggest that acute administration of soluble low-n Aβo may be a useful model to study the early mechanisms involved in AD and provide us with a platform for testing novel therapeutic approaches that target the early underlying synaptic pathology.

Statins and Brain Health: Alzheimer's Disease and Cerebrovascular Disease Biomarkers in Older Adults. - Ramanan, Vijay K; Przybelski, Scott A; Graff-Radford, Jonathan; Castillo, Anna M; Lowe, Val J; Mielke, Michelle M; Roberts, Rosebud O; Reid, Robert I; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Vemuri, Prashanthi (J Alzheimers Dis, 2018)
BACKGROUND: Statins have been proposed to reduce the risk of Alzheimer's disease (AD). OBJECTIVE: Assess whether long-term statin use was associated with neuroimaging biomarkers of aging and dementia. METHODS: Methods: We analyzed neuroimaging biomarkers in 1,160 individuals aged 65+ from the Mayo Clinic Study of Aging, a population-based prospective longitudinal study of cognitive aging. RESULTS: Statin-treated (5+ years of therapy) individuals had greater burden of mid-and late-life cardiovascular disease (p < 0.001) than statin-untreated (≤3 months) individuals. Lower fractional anisotropy in the genu of the corpus callosum, an early marker of cerebrovascular disease, was associated with long-term statin exposure (p < 0.035). No significant associations were identified between long-term statin exposure and cerebral amyloid or tau burden, AD pattern neurodegeneration, or white matter hyperintensity burden. CONCLUSIONS: Long-term statin therapy was not associated with differences in AD biomarkers. Individuals with long-term statin exposure had worse white matter integrity in the genu of the corpus callosum, consistent with the coexistence of higher cerebrovascular risk factor burden in this group.

A Study of a Supplement Containing Huperzine A and Curcumin in Dementia Patients and Individuals with Mild Cognitive Impairment. - Tabira, Takeshi; Kawamura, Nobutoshi (J Alzheimers Dis, 2018)
Extracts from Huperzia serrata (HS) function as a cholinesterase inhibitor and a glutamic acid receptor antagonist. We tested a supplement containing HS extracts, curcumin, and others in dementia patients and individuals with mild cognitive impairment (MCI) in an open label study. Most patients with Alzheimer's disease, dementia with Lewy bodies, and MCI individuals exhibited improvements in cognitive functions, as assessed by the Alzheimer's Disease Assessment Scale-cognitive subscale Japanese version. The scores were significantly improved at 6-12 weeks compared with baseline scores (p = 0.007) and at 22-28 weeks (p = 0.004). Thus, this supplement may be administered to dementia patients as well as MCI individuals.

Subjective Cognitive Decline Prediction of Mortality: Results from the Einstein Aging Study. - Katz, Mindy J; Wang, Cuiling; Derby, Carol A; Lipton, Richard B; Zimmerman, Molly E; Sliwinski, Martin J; Rabin, Laura A (J Alzheimers Dis, 2018)
BACKGROUND: The relation of pre-dementia stages to mortality has not been fully explored. Previous work examining subjective cognitive decline (SCD) and mortality is limited and mixed regarding methods used and consistency of findings. OBJECTIVE: To examine SCD and mortality in a longitudinal, community-based cohort, using item response theory (IRT) methodology to form a composite SCD measure. Also, to assess whether this relationship was independent of clinical cognitive status. METHODS: The Einstein Aging Study is a diverse longitudinal cohort of adults aged ≥70. SCD items were extracted from baseline CERAD questionnaires and a composite score was formed using IRT methodology. A total of 1,741 participants with complete data were clinically diagnosed as cognitively normal, or as having amnestic mild cognitive impairment (aMCI), nonamnestic mild cognitive impairment (naMCI), or dementia. 645 deaths occurred over a period of 8,912 person-years of follow-up. Cox proportional hazard models predicted time to death adjusting for covariates. RESULTS: A one standard deviation unit increase in level of SCD was associated with >20% higher risk of mortality. However, when models were adjusted for clinical cognitive status, the association was no longer significant. Both dementia and aMCI predicted mortality. Furthermore, when analyses focused only on those without cognitive impairment, SCD level did not predict mortality. CONCLUSIONS: The association of SCD with mortality may be due to the association of SCD with clinical cognitive status. Thus, SCD may be used as a community-based screen to initially identify those with cognitive impairment who may be at greatest risk for death.

Subtle Cognitive Impairment and Alzheimer's Disease-Type Pathological Changes in Cerebrospinal Fluid are Common Among Neurologically Healthy Subjects. - Haapalinna, Fanni; Kokki, Merja; Jääskeläinen, Olli; Hallikainen, Merja; Helisalmi, Seppo; Koivisto, Anne; Kokki, Hannu; Paajanen, Teemu; Penttinen, Janne; Pikkarainen, Maria; Rautiainen, Minna; Soininen, Hilkka; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The neuropathology of Alzheimer's disease (AD) has previously been shown to be rather common among the elderly. OBJECTIVE: The aim of this study was to inspect the associations between cerebrospinal fluid (CSF) AD biomarker concentrations, age, the APOEɛ4 allele, cardiovascular diseases, diabetes, and cognitive performance in a cohort of a neurologically healthy population. METHODS: This study included 93 subjects (42 men, mean age 67 years) without previous neurological symptoms or subjective cognitive complaints. Their cognition was assessed, and CSF biomarkers and APOEɛ4 status were analyzed. RESULTS: Of the studied subjects, 8.6% (n = 8) had a pathological CSF AD biomarker profile. An increase in age correlated positively with CSF tau pathology and negatively with global cognitive performance. CONCLUSION: AD-type pathological changes in CSF and subtle cognitive impairment are common within a population with no previous memory complaints. Age was the main risk factor for the changes.

Subtypes Based on Neuropsychological Performance Predict Incident Dementia: Findings from the Rush Memory and Aging Project. - Zammit, Andrea R; Muniz-Terrera, Graciela; Katz, Mindy J; Hall, Charles B; Ezzati, Ali; Bennett, David A; Lipton, Richard B (J Alzheimers Dis, 2018)
BACKGROUND: In a previous report, we used latent class analysis (LCA) to identify natural subgroups of older adults in the Einstein Aging Study (EAS) based on neuropsychological performance. These subgroups differed in demographics, genetic profile, and prognosis. Herein, we assess the generalizability of these findings to an independent sample, the Rush Memory and Aging Project (MAP), which used an overlapping, but distinct neuropsychological battery. OBJECTIVE: Our aim was to identify the association of natural subgroups based on neuropsychological performance in the MAP cohort with incident dementia and compare them with the associations identified in the EAS. METHODS: MAP is a community-dwelling cohort of older adults living in the northeastern Illinois, Chicago. Latent class models were applied to baseline scores of 10 neuropsychological measures across 1,662 dementia-free MAP participants. Results were compared to prior findings from the EAS. RESULTS: LCA resulted in a 5-class model: Mixed-Domain Impairment (n = 71, 4.3%), Memory-specific-Impairment (n = 274, 16.5%), Average (n = 767, 46.1%), Frontal Impairment (n = 222, 13.4%), and a class of Superior Cognition (n = 328, 19.7%). Similar to the EAS, the Mixed-Domain Impairment, the Memory-Specific Impairment, and the Frontal Impairment classes had higher risk of incident Alzheimer's disease when compared to the Average class. By contrast, the Superior Cognition had a lower risk of Alzheimer's disease when compared to the Average class. CONCLUSIONS: Natural cognitive subgroups in MAP are similar to those identified in EAS. These similarities, despite study differences in geography, sampling strategy, and cognitive tests, suggest that LCA is capable of identifying classes that are not limited to a single sample or a set of cognitive tests.

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Targeted Assessment of Enlargement of the Perivascular Space in Alzheimer's Disease and Vascular Dementia Subtypes Implicates Astroglial Involvement Specific to Alzheimer's Disease. - Boespflug, Erin L; Simon, Matthew J; Leonard, Emmalyn; Grafe, Marjorie; Woltjer, Randall; Silbert, Lisa C; Kaye, Jeffrey A; Iliff, Jeffrey J (J Alzheimers Dis, 2018)
Waste clearance from the brain parenchyma occurs along perivascular pathways. Enlargement of the perivascular space (ePVS) is associated with pathologic features of Alzheimer's disease (AD), although the mechanisms and implications of this dilation are unclear. Fluid exchange along the cerebral vasculature is dependent on the perivascular astrocytic water channel aquaporin-4 (AQP4) and loss of perivascular AQP4 localization is found in AD. We directly measured ePVS in postmortem samples of pathologically characterized tissue from participants who were cognitively intact or had AD or mixed dementia (vascular lesions with AD). We found that both AD and mixed dementia groups had significantly increased ePVS compared to cognitively intact subjects. In addition, we found increased global AQP4 expression of the AD group over both control and mixed dementia groups and a qualitative reduction in perivascular localization of AQP4 in the AD group. Among these cases, increasing ePVS burden was associated with the presence of tau and amyloid-β pathology. These findings are consistent with the existing evidence of ePVS in AD and provide novel information regarding differences in AD and vascular dementia and the potential role of astroglial pathology in ePVS.

Tau Proteolysis in the Pathogenesis of Tauopathies: Neurotoxic Fragments and Novel Biomarkers. - Quinn, James P; Corbett, Nicola J; Kellett, Katherine A B; Hooper, Nigel M (J Alzheimers Dis, 2018)
With predictions showing that 131.5 million people worldwide will be living with dementia by 2050, an understanding of the molecular mechanisms underpinning disease is crucial in the hunt for novel therapeutics and for biomarkers to detect disease early and/or monitor disease progression. The metabolism of the microtubule-associated protein tau is altered in different dementias, the so-called tauopathies. Tau detaches from microtubules, aggregates into oligomers and neurofibrillary tangles, which can be secreted from neurons, and spreads through the brain during disease progression. Post-translational modifications exacerbate the production of both oligomeric and soluble forms of tau, with proteolysis by a range of different proteases being a crucial driver. However, the impact of tau proteolysis on disease progression has been overlooked until recently. Studies have highlighted that proteolytic fragments of tau can drive neurodegeneration in a fragment-dependent manner as a result of aggregation and/or transcellular propagation. Proteolytic fragments of tau have been found in the cerebrospinal fluid and plasma of patients with different tauopathies, providing an opportunity to develop these fragments as novel disease progression biomarkers. A range of therapeutic strategies have been proposed to halt the toxicity associated with proteolysis, including reducing protease expression and/or activity, selectively inhibiting protease-substrate interactions, and blocking the action of the resulting fragments. This review highlights the importance of tau proteolysis in the pathogenesis of tauopathies, identifies putative sites during tau fragment-mediated neurodegeneration that could be targeted therapeutically, and discusses the potential use of proteolytic fragments of tau as biomarkers for different tauopathies.

TDP-43 and Alzheimer's Disease Pathologic Subtype in Non-Amnestic Alzheimer's Disease Dementia. - Sahoo, Aradhana; Bejanin, Alexandre; Murray, Melissa E; Tosakulwong, Nirubol; Weigand, Stephen D; Serie, Amanda M; Senjem, Matthew L; Machulda, Mary M; Parisi, Joseph E; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: TDP-43 has been shown to be strongly associated with memory loss, smaller hippocampal volumes, and faster rates of hippocampal atrophy in Alzheimer's disease (AD) patients with an amnestic presentation. Whether TDP-43 has any clinical or anatomical associations in AD patients with non-amnestic phenotype is unknown. OBJECTIVE: To determine whether TDP-43 plays a significant role in the clinic-anatomic features of non-amnestic AD. METHODS: All cases with pathologically confirmed intermediate-high probability AD from 1996-2012 were identified and retrospectively sub-classified into amnestic versus non-amnestic dementia at the time of presentation. Neurofibrillary tangle counts were performed in those with a non-amnestic presentation using thioflavin-S microscopy in the hippocampus and three neocortical regions, and all cases were subtyped into hippocampal-sparing, limbic-predominant, and typical AD pathology. TDP-43 immunoreactivity was used to assess for the presence of TDP-43. Statistical analyses helped determine whether pathologic subtype or TDP-43 was more strongly associated with clinico-imaging features. RESULTS: Out of 172 pathologically confirmed AD cases, 36 (19%) were classified as non-amnestic. Twenty-five of these 36 (69%) had typical pathology, 0 limbic-predominant pathology, and 11 (31%) hippocampal-sparing pathology. Eleven (44%) of the 25 cases with typical pathology were TDP-43+. Of the 11 cases with hippocampal-sparing pathology, 4 (36%) were TDP-43+. There were no differences in demographic, clinical, or neuroimaging features in those with TDP-43 versus those without except for older age at onset (p = 0.02) and age at death (p = 0.02) in those with TDP-43. AD pathological subtype accounted for slightly more of the variances in the neocortex than TDP-43. CONCLUSION: In non-amnestic AD, we find little evidence that clinical or anatomical features of the disease are related to TDP-43.

Time Trends in the Prevalence of Neurocognitive Disorders and Cognitive Impairment in the United States: The Effects of Disease Severity and Improved Ascertainment. - Akushevich, Igor; Yashkin, Arseniy P; Kravchenko, Julia; Ukraintseva, Svetlana; Stallard, Eric; Yashin, Anatoliy I (J Alzheimers Dis, 2018)
BACKGROUND: Trends in the prevalence of cognitive impairment (CI) based on cognitive assessment instruments are often inconsistent with those of neurocognitive disorders (ND) based on Medicare claims records. OBJECTIVE: We hypothesized that improved ascertainment and resulting decrease in disease severity at the time of diagnosis are responsible for this phenomenon. METHODS: Using Medicare data linked to the Health and Retirement Study (1992-2012), we performed a joint analysis of trends in CI and ND to test our hypothesis. RESULTS: We identified two major contributors to the divergent directions in CI and ND trends: reductions in disease severity explained more than 60% of the differences between CI and ND prevalence over the study period; the remaining 40% was explained by a decrease in the fraction of undiagnosed individuals. DISCUSSION: Improvements in the diagnoses of ND diseases were a major contributor to reported trends in ND and CI. Recent forecasts of CI and ND trends in the U.S. may be overly pessimistic.

Total MRI Small Vessel Disease Burden Correlates with Cognitive Performance, Cortical Atrophy, and Network Measures in a Memory Clinic Population. - Banerjee, Gargi; Jang, Hyemin; Kim, Hee Jin; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Im, Kiho; Kwon, Hunki; Lee, Jong Min; Na, Duk L; Seo, Sang Won; Werring, David John (J Alzheimers Dis, 2018)
BACKGROUND: Recent evidence suggests that combining individual imaging markers of cerebral small vessel disease (SVD) may more accurately reflect its overall burden and better correlate with clinical measures. OBJECTIVE: We wished to establish the clinical relevance of the total SVD score in a memory clinic population by investigating the association with SVD score and cognitive performance, cortical atrophy, and structural network measures, after adjusting for amyloid-β burden. METHODS: We included 243 patients with amnestic mild cognitive impairment (MCI), Alzheimer's disease dementia, subcortical vascular MCI, or subcortical vascular dementia. All underwent MR and [11C] PiB-PET scanning and had standardized cognitive testing. Multiple linear regression was used to evaluate the relationships between SVD score and cognition, cortical thickness, and structural network measures. Path analyses were performed to evaluate whether network disruption mediates the effects of SVD score on cortical thickness and cognition. RESULTS: Total SVD score was associated with the performance of frontal (β - 4.31, SE 2.09, p = 0.040) and visuospatial (β - 0.95, SE 0.44, p = 0.032) tasks, and with reduced cortical thickness in widespread brain regions. Total SVD score was negatively correlated with nodal efficiency, as well as changes in brain network organization, with evidence of reduced integration and increasing segregation. Path analyses showed that the associations between SVD score and frontal and visuospatial scores were partially mediated by decreases in their corresponding nodal efficiency and cortical thickness. CONCLUSION: Total SVD burden has clinical relevance in a memory clinic population and correlates with cognition, and cortical atrophy, as well as structural network disruption.

Trajectories of Physiological Brain Aging and Related Factors in People Aged from 20 to over-80. - Lee, Jin San; Kim, Seonwoo; Yoo, Heejin; Park, Seongbeom; Jang, Young Kyoung; Kim, Hee Jin; Kim, Ko Woon; Kim, Yeshin; Jang, Hyemin; Park, Key-Chung; Yaffe, Kristine; Yang, Jin-Ju; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: In this study, we investigated a long-term trajectory of brain aging (from the 20 s to over-80) in cognitively normal (CN) individuals. We further determined whether differences in sex, education years, and apolipoprotein E ε 4 status affect age-related cortical thinning. METHODS: A total of 2,944 CN individuals who underwent high-resolution (3.0-Tesla) magnetic resonance imaging were included in this study. Cortical thickness was measured using a surface-based method. Multiple linear regression analyses were performed to evaluate age-related cortical thinning and related factors. RESULTS: Compared to those in their 20 s/30 s, participants in their 40 s showed thinning primarily in the medial and lateral frontal and inferior parietal regions, and cortical thinning occurred across most of the cortices with increasing age. Notably, the precuneus, inferior temporal and lateral occipital regions were relatively spared until later in life. Male and lower education years were associated with greater cortical thinning with distinct regional specificity. CONCLUSION: Our findings provide an important clue to understanding the mechanism of age-related cognitive decline and new strategies for preventing the acceleration of pathological brain aging.

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

Ubisol-Q10 (a Nanomicellar Water-Soluble Formulation of CoQ10) Treatment Inhibits Alzheimer-Type Behavioral and Pathological Symptoms in a Double Transgenic Mouse (TgAPEswe, PSEN1dE9) Model of Alzheimer's Disease. - Muthukumaran, Krithika; Kanwar, Annie; Vegh, Caleb; Marginean, Alexandra; Elliott, Austin; Guilbeault, Nicholas; Badour, Alexander; Sikorska, Marianna; Cohen, Jerome; Pandey, Siyaram (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. Previously, we have shown that a water-soluble formulation of Coenzyme Q10 (Ubisol-Q10), an integral part of the electron transport chain, stabilizes mitochondria and prevents neuronal cell death caused by neurotoxins or oxidative stress both in vitro and in vivo. In this study, we evaluated the neuroprotective effects of Ubisol-Q10 treatment in double transgenic AD mice. In the present study, we report that providing Ubisol-Q10 in drinking water (at a dose of ∼6 mg/kg/day) reduced circulating amyloid-β (Aβ) peptide, improved long term memory, preserved working spatial memory, and drastically inhibited Aβ plaque formation in 18-month-old transgenic mice compared to an untreated transgenic group. Thus Ubisol-Q10 supplementation has the potential to inhibit the progression of neurodegeneration, leading to a better quality of life for humans suffering with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Male; Maze Learning; Memory; Memory Disorders; Mice; Mice, Transgenic; Microglia; Mutation; Nerve Tissue Proteins; Peptide Fragments; Presenilin-1; Ubiquinone; Vitamins

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

Update on Vascular Cognitive Impairment Associated with Subcortical Small-Vessel Disease. - Wallin, Anders; Román, Gustavo C; Esiri, Margaret; Kettunen, Petronella; Svensson, Johan; Paraskevas, George P; Kapaki, Elisabeth (J Alzheimers Dis, 2018)
Subcortical small-vessel disease (SSVD) is a disorder well characterized from the clinical, imaging, and neuropathological viewpoints. SSVD is considered the most prevalent ischemic brain disorder, increasing in frequency with age. Vascular risk factors include hypertension, diabetes, hyperlipidemia, elevated homocysteine, and obstructive sleep apnea. Ischemic white matter lesions are the hallmark of SSVD; other pathological lesions include arteriolosclerosis, dilatation of perivascular spaces, venous collagenosis, cerebral amyloid angiopathy, microbleeds, microinfarcts, lacunes, and large infarcts. The pathogenesis of SSVD is incompletely understood but includes endothelial changes and blood-brain barrier alterations involving metalloproteinases, vascular endothelial growth factors, angiotensin II, mindin/spondin, and the mammalian target of rapamycin pathway. Metabolic and genetic conditions may also play a role but hitherto there are few conclusive studies. Clinical diagnosis of SSVD includes early executive dysfunction manifested by impaired capacity to use complex information, to formulate strategies, and to exercise self-control. In comparison with Alzheimer's disease (AD), patients with SSVD show less pronounced episodic memory deficits. Brain imaging has advanced substantially the diagnostic tools for SSVD. With the exception of cortical microinfarcts, all other lesions are well visualized with MRI. Diagnostic biomarkers that separate AD from SSVD include reduction of cerebrospinal fluid amyloid-β (Aβ)42 and of the ratio Aβ42/Aβ40 often with increased total tau levels. However, better markers of small-vessel function of intracerebral blood vessels are needed. The treatment of SSVD remains unsatisfactory other than control of vascular risk factors. There is an urgent need of finding targets to slow down and potentially halt the progression of this prevalent, but often unrecognized, disorder.
Keywords: Animals; Cerebrovascular Disorders; Dementia; Humans

Utility of Amyloid and FDG-PET in Clinical Practice: Differences Between Secondary and Tertiary Care Memory Units. - Lage, Carmen; Suarez, Andrea Gonzalez; Pozueta, Ana; Riancho, Javier; Kazimierczak, Martha; Bravo, María; Jimenez Bonilla, Julio; de Arcocha Torres, Marıa; Quirce, Remedios; Banzo, Ignacio; Vázquez-Higuera, José Luis; Rabinovici, Gil D; et al. (J Alzheimers Dis, 2018)
The clinical utility of amyloid positron emission tomography (PET) has not been fully established. Our aim was to evaluate the effect of amyloid imaging on clinical decision making in a secondary care unit and compare our results with a previous study in a tertiary center following the same methods. We reviewed retrospectively 151 cognitively impaired patients who underwent amyloid (Pittsburgh compound B [PiB]) PET and were evaluated clinically before and after the scan in a secondary care unit. One hundred and fifty concurrently underwent fluorodeoxyglucose (FDG)-PET. We assessed changes between the pre- and post-PET clinical diagnosis and Alzheimer's disease treatment plan. The association between PiB/FDG results and changes in management was evaluated using χ2 and multivariate logistic regression. Concordance between classification based on scan readings and baseline diagnosis was 66% for PiB and 47% for FDG. The primary diagnosis changed after PET in 17.2% of cases. When examined independently, discordant PiB and discordant FDG were both associated with diagnostic change (p < 0.0001). However, when examined together in a multivariate logistic regression, only discordant PiB remained significant (p = 0.0002). Changes in treatment were associated with concordant PiB (p = 0.009) while FDG had no effect on treatment decisions. Based on our regression model, patients with diagnostic dilemmas, a suspected non-amyloid syndrome, and Clinical Dementia Rating <1 were more likely to benefit from amyloid PET due to a higher likelihood of diagnostic change. We found that changes in diagnosis after PET in our secondary center almost doubled those of our previous analysis of a tertiary unit (9% versus 17.2%). Our results offer some clues about the rational use of amyloid PET in a secondary care memory unit stressing its utility in mild cognitive impairment patients.

Utility of the LIBRA Index in Relation to Cognitive Functioning in a Clinical Health Seeking Sample. - Pons, Anke; LaMonica, Haley M; Mowszowski, Loren; Köhler, Sebastian; Deckers, Kay; Naismith, Sharon L (J Alzheimers Dis, 2018)
BACKGROUND: Dementia prevalence is expected to increase substantially over the next few decades. Since there is currently no cure for dementia available, there is an urgent need for the early identification of individuals at high risk for dementia, so that primary and secondary prevention strategies can be implemented. Recently, the LIfestyle for BRAin health (LIBRA) index was developed as a new dementia risk algorithm. It specifically focuses on modifiable risk and protective factors that can be targeted in midlife. OBJECTIVE: The objective of this study was to evaluate the LIBRA index in relation to markers of cognitive functioning in a clinical, health-seeking sample of community-based older adults. METHODS: 484 participants (mean age 62.7 years) were recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney. Participants underwent comprehensive clinical and neuropsychological assessment and completed a self-report survey pack. Participants were rated via consensus as having either subjective cognitive complaints (SCC) or meeting criteria for mild cognitive impairment (MCI). The LIBRA score was calculated based on 11 available risk and protective factors. RESULTS: 65.4% of the sample met criteria for MCI. People with MCI showed a significantly higher LIBRA score compared to people with SCC. Furthermore, multiple cognitive domains, in particular executive functioning, were associated with a higher LIBRA score, with stronger correlations in people with MCI. CONCLUSION: The LIBRA index might be a useful tool to determine lifestyle-attributable risk of cognitive decline in an older health-seeking population, including people with MCI.

Vascular Effects on Depressive Symptoms in Cognitive Impairment. - Kim, Yeshin; Jang, Hyemin; Kim, Seung Joo; Cho, Soo Hyun; Kim, Si Eun; Kim, Sung Tae; Kim, Hee Jin; Moon, Seung Hwan; Ewers, Michael; Im, Kiho; Kwon, Hunki; Na, Duk L; et al. (J Alzheimers Dis, 2018)
Late life depression is related to pathologic burdens, such as cerebral small vascular disease (CSVD) and amyloid, which are associated with brain network changes and cortical thinning. To examine the associations of various CSVD imaging markers, amyloid, and network changes with depression in cognitively impaired patients, we prospectively recruited 228 cognitively impaired patients having various degrees of amyloid and CSVD who underwent diffuse tensor image and PiB PET. Greater CSVD burden was associated with greater Geriatric Depression Scale (GDS) (white matter hyperintensities, WMH: p = 0.025, lacunes: p < 0.001) but not with amyloid (p = 0.095), and cortical thinning (p = 0.630) was not associated with greater GDS. The changes in white matter networks were related to GDS with decreasing integration (global efficiency: p < 0.001) and increasing segregation (clustering coefficient: p = 0.009). The network changes mediated the relationships of WMH and lacunes with GDS. Our findings provide insight to better understand how CSVD burdens contribute to depression in cognitively impaired patients having varying degrees of amyloid and vascular burdens.

Voxel-Based Acetylcholinesterase PET Study in Early and Late Onset Alzheimer's Disease. - Hirano, Shigeki; Shinotoh, Hitoshi; Shimada, Hitoshi; Ota, Tsuneyoshi; Sato, Koichi; Tanaka, Noriko; Zhang, Ming-Rong; Higuchi, Makoto; Fukushi, Kiyoshi; Irie, Toshiaki; Kuwabara, Satoshi; Suhara, Tetsuya (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by chronic progressive cognitive decline and displays underlying brain cholinergic dysfunction, providing a rationale for treatment with cholinomimetic medication. The clinical presentations and courses of AD patients may differ by age of onset. OBJECTIVE: The objective of the present study was to illustrate the regional differences of brain acetylcholinesterase (AChE) activity as quantified by N-[11C]methylpiperidinyl-4-acetate ([11C]MP4A) and PET using parametric whole brain analysis and clarify those differences as a function of age. METHODS: 22 early onset AD (EOAD) with age at onset under 65, the remaining 26 as late onset AD (LOAD), and 16 healthy controls (HC) were enrolled. Voxel-based AChE activity estimation of [11C]MP4A PET images was conducted by arterial input and unconstrained nonlinear least-squares method with subsequent parametrical analyses. Statistical threshold was set as Family Wise Error corrected, p-value <0.05 on cluster-level and cluster extent over 30 voxels. RESULTS: Voxel-based group comparison showed that, compared to HC, both EOAD and LOAD showed cortical AChE decrement in parietal, temporal, and occipital cortices, with wider and stringent cortical involvement in the EOAD group, most prominently demonstrated in the temporal region. There was no significant correlation between age and regional cerebral AChE activity except for a small left superior temporal region in the AD group (Brodmann's area 22, Zmax = 5.13, 396 voxels), whereas no significant cluster was found in the HC counterpart. CONCLUSION: Difference in cortical cholinergic dysfunction between EOAD and LOAD may shed some light on the cholinomimetic drug efficacy in AD.

What Factors Predict Family Caregivers' Attendance at Dementia Cafés? - Jones, Susan May; Killett, Anne; Mioshi, Eneida (J Alzheimers Dis, 2018)
BACKGROUND: Dementia Cafés are community support groups which provide post-diagnostic support for families affected by dementia. However, little is known about the characteristics of caregivers who attend Cafés. OBJECTIVES: To describe the demographic and psychosocial characteristics of caregivers who attend Dementia Cafés, and to identify which of those factors may influence the likelihood of family caregivers attending Dementia Cafés. METHODS: A cross-sectional study on caregivers (n = 80; July 2016- July 2017). Resilience (Brief Resilient Coping Scale), Subjective Wellbeing (Personal Wellbeing Index), and Social Support (MOS-Social Support Survey) were measured. Café attendees and non-attendees were compared in regards to demographic characteristics (Chi-Square tests), resilience, subjective wellbeing and social support (independent t-tests). Bivariate and multivariate regression analyses were run to detect associations between predictor variables and café attendance. RESULTS: Caregivers who attended Cafés reported higher resilience (OR: 1.26; 95% CI 1.10-1.45; p = 0.001) and subjective wellbeing (OR: 1.63; 95% CI 1.24-2.142; p = 0.001); no significant difference in social support was detected. Female caregivers were more likely to attend a Café (OR: 3.23; 95% CI 1.14-9.10; p = 0.03). However, only higher subjective wellbeing (OR: 1.63; 95% CI 1.10-24.2; p = 0.02) and fewer years formal education (OR: 4.99; 95% CI 1.12-21.36; p = 0.03) predicted attendance at a café. CONCLUSION: Dementia Cafés may bring about benefits in resilience and subjective wellbeing, or may be best suited to those with higher resilience and wellbeing. Cafes are not being accessed by all caregiver groups. Alternative models of post-diagnostic support should be considered to increase equity of care.

Which Risk Factors Causally Influence Dementia? A Systematic Review of Mendelian Randomization Studies. - Kuźma, Elżbieta; Hannon, Eilis; Zhou, Ang; Lourida, Ilianna; Bethel, Alison; Levine, Deborah A; Lunnon, Katie; Thompson-Coon, Jo; Hyppönen, Elina; Llewellyn, David J (J Alzheimers Dis, 2018)
BACKGROUND: Numerous risk factors for dementia are well established, though the causal nature of these associations remains unclear. OBJECTIVE: To systematically review Mendelian randomization (MR) studies investigating causal relationships between risk factors and global cognitive function or dementia. METHODS: We searched five databases from inception to February 2017 and conducted citation searches including MR studies investigating the association between any risk factor and global cognitive function, all-cause dementia or dementia subtypes. Two reviewers independently assessed titles and abstracts, full-texts, and study quality. RESULTS: We included 18 MR studies investigating education, lifestyle factors, cardiovascular factors and related biomarkers, diabetes related and other endocrine factors, and telomere length. Studies were of predominantly good quality, however eight received low ratings for sample size and statistical power. The most convincing causal evidence was found for an association of shorter telomeres with increased risk of Alzheimer's disease (AD). Causal evidence was weaker for smoking quantity, vitamin D, homocysteine, systolic blood pressure, fasting glucose, insulin sensitivity, and high-density lipoprotein cholesterol. Well-replicated associations were not present for most exposures and we cannot fully discount survival and diagnostic bias, or the potential for pleiotropic effects. CONCLUSIONS: Genetic evidence supported a causal association between telomere length and AD, whereas limited evidence for other risk factors was largely inconclusive with tentative evidence for smoking quantity, vitamin D, homocysteine, and selected metabolic markers. The lack of stronger evidence for other risk factors may reflect insufficient statistical power. Larger well-designed MR studies would therefore help establish the causal status of these dementia risk factors.

White Matter and Cognition in Traumatic Brain Injury. - Filley, Christopher M; Kelly, James P (J Alzheimers Dis, 2018)
Traumatic brain injury (TBI) is a leading cause of disability and produces a wide range of cognitive, emotional, and physical consequences. The impact of TBI on cognition is among the most important questions in this field but remains incompletely understood. The immediate cognitive effects of concussion, while usually short-lived, may be profound and lasting in some individuals, and long-term sequelae of TBI may include dementia of several varieties including post-traumatic leukoencephalopathy, chronic traumatic encephalopathy, and Alzheimer's disease. Whereas the etiopathogenesis of cognitive dysfunction after TBI remains uncertain, a reasonable point to begin is a focus on the white matter of the brain, where the neuropathological lesion known as diffuse axonal injury (DAI) is routinely identified. White matter is not typically accorded the significance granted to cortical gray matter in discussions of cognitive dysfunction and dementia, but increasing evidence is accumulating to suggest that cognitive decline after TBI is a direct result of white matter injury, and that lesions in this brain component are crucial in the sequence of events leading ultimately to dementia of several types. In this review, we consider the topic of white matter and cognition in TBI, beginning with DAI and proceeding to the role of inflammation in the pathogenesis of cognitive dysfunction and dementia that can follow. A brief review of possible therapeutic options will also be offered, including the use of anti-inflammatory agents and the exploitation of white matter plasticity, to treat acute and post-acute injuries, and lower the incidence of dementia resulting from TBI.

White Matter Hyperintensities and Cognition in Mild Cognitive Impairment and Alzheimer's Disease: A Domain-Specific Meta-Analysis. - van den Berg, Esther; Geerlings, Mirjam I; Biessels, Geert Jan; Nederkoorn, Paul J; Kloppenborg, Raoul P (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMHs) are related to cognitive dysfunction in the general population. The clinical relevance of WMHs in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) is, however, unclear. OBJECTIVE: This meta-analysis aimed to quantify the association of WMHs and specific cognitive domains in patients with MCI or AD. METHODS: PubMed (January 1990-January 2017) was searched for studies that used MRI to quantify WMHs, and measured cognitive functioning (≥1 predefined cognitive domain with ≥1 test) in a well-defined population of persons diagnosed with MCI or AD. Fischer's Z was used as the common metric for effect size. Modifying effects of demographics, MMSE, and WMH location were examined. RESULTS: Twelve cross-sectional studies on AD (total n = 1,370, median age 75 years) and 10 studies on MCI (9 cross-sectional, 1 longitudinal; total n = 2,286, median age 73 years) were included. The association between WMHs and overall cognition was significantly stronger for MCI (-0.25, -0.36 to -0.14) than for AD (-0.11, -0.14 to -0.08; QM = 10.7, p < 0.05). For both groups, largest effect sizes were found in attention and executive functions (-0.26, -0.36 to -0.15) and processing speed (-0.21, -0.35 to -0.12). No significant modifying effects of age and gender were found. CONCLUSION: WMHs have a medium-sized association with different cognitive functions in patients with MCI and a small, but statistically significant, association with cognition in AD. These result underscore the role of co-occurring vascular brain damage in MCI and AD.

Zinc Exacerbates Tau Pathology in a Tau Mouse Model. - Craven, Kristen M; Kochen, William R; Hernandez, Carlos M; Flinn, Jane M (J Alzheimers Dis, 2018)
Hyperphosphorylated tau protein is a key pathology in Alzheimer's disease (AD), frontotemporal dementia, chronic traumatic encephalopathy, and Parkinson's disease. The essential trace element zinc exacerbates tauopathy in vitro as well as in a Drosophila model of AD. However, the interaction has never been assessed behaviorally or biochemically in mammals. Zinc supplementation is prevalent in society, finding use as a treatment for macular degeneration and cataracts, and is also taken as an immune system booster with high levels appearing in multivitamins marketed toward the elderly. Using a transgenic mouse model that contains the human gene for tau protein (P301L), we assessed the effects of excess chronic zinc supplementation on tau pathology. Behavioral tests included nest building, circadian rhythm, Morris Water Maze, fear conditioning, and open field. Biochemically, total tau and Ser396 phosphorylation were assessed using western blot. Number of tangles were assessed by Thioflavin-S and free zinc levels were assessed by Zinpyr-1. Tau mice demonstrated behavioral deficits compared to control mice. Zinc supplementation exacerbated tauopathic deficits in circadian rhythm, nesting behavior, and Morris Water Maze. Biochemically, zinc-supplemented tau mice showed increased phosphorylation at pSer396. Zinc supplementation in tau mice also increased tangle numbers in the hippocampus while decreasing free-zinc levels, demonstrating that tangles were sequestering zinc. These results show that zinc intensified the deficits in behavior and biochemistry caused by tau.

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

ABCA1 Deficiency Affects Basal Cognitive Deficits and Dendritic Density in Mice. - Fitz, Nicholas F; Carter, Alexis Y; Tapias, Victor; Castranio, Emilie L; Kodali, Ravindra; Lefterov, Iliya; Koldamova, Radosveta (J Alzheimers Dis, 2017)
ATP-binding cassette transporter A1 (ABCA1) mediates cholesterol efflux to lipid-free apolipoproteins and regulates the generation of high density lipoproteins. Previously, we have shown that lack of Abca1 significantly increases amyloid deposition and cognitive deficits in Alzheimer's disease model mice expressing human amyloid-β protein precursor (APP). The goal of this study was to determine if ABCA1 plays a role in memory deficits caused by amyloid-β (Aβ) oligomers and examine neurite architecture of pyramidal hippocampal neurons. Our results confirm previous findings that Abca1 deficiency significantly impairs spatial memory acquisition and retention in the Morris water maze and long-term memory in novel object recognition of APP transgenic mice at a stage of early amyloid pathology. Neither test demonstrated a significant difference between Abca1ko and wild-type (WT) mice. We also examined the effect of intra-hippocampal infused Aβ oligomers on cognitive performance of Abca1ko mice, compared to control infusion of scrambled Aβ peptide. Age-matched WT mice undergoing the same infusions were also used as controls. In this model system, we found a statistically significant difference between WT and Abca1ko mice infused with scrambled Aβ, suggesting that Abca1ko mice are vulnerable to the effect of mild stresses. Moreover, examination of neurite architecture in the hippocampi revealed a significant decrease in neurite length, number of neurite segments, and branches in Abca1ko mice when compared to WT mice. We conclude that mice lacking ABCA1 have basal cognitive deficits that prevent them from coping with additional stressors, which is in part due to impairment of neurite morphology in the hippocampus.

Abnormalities of Cerebral Deep Medullary Veins on 7 Tesla MRI in Amnestic Mild Cognitive Impairment and Early Alzheimer's Disease: A Pilot Study. - Bouvy, Willem H; Kuijf, Hugo J; Zwanenburg, Jaco J M; Koek, Huiberdina L; Kappelle, L Jaap; Luijten, Peter R; Ikram, M Kamran; Biessels, Geert Jan (J Alzheimers Dis, 2017)
Cerebral small vessel disease (SVD) contributes to cognitive impairment and dementia. SVD may affect veins, but veins are difficult to detect with 1.5 and 3T MRI. We compared deep medullary veins (DMVs) visualized on 7T-MRI between patients with early Alzheimer's disease (eAD; n = 17) or amnestic MCI (aMCI; n = 12) and controls (n = 40). The number and density of DMVs was similar in patients and controls, but tortuosity was higher in eAD (Cohen's d = 0.7, 95% CI: 0.1-1.2, p = 0.02) and aMCI (Cohen's d = 0.8, 95% CI: 0.2-1.5, p = 0.01), independent of brain atrophy. Venous changes provide a new perspective on vascular involvement in dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Brain; Cerebral Small Vessel Diseases; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male

Alcohol Intake and Cognitively Healthy Longevity in Community-Dwelling Adults: The Rancho Bernardo Study. - Richard, Erin L; Kritz-Silverstein, Donna; Laughlin, Gail A; Fung, Teresa T; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
To better understand the association of alcohol intake with cognitively healthy longevity (CHL), we explored the association between amount and frequency of alcohol intake and CHL among 1,344 older community-dwelling adults. Alcohol intake was assessed by questionnaire in 1984-1987. Cognitive function was assessed in approximate four-year intervals between 1988 and 2009. Multinomial logistic regression, adjusting for multiple lifestyle and health factors, was used to examine the association between alcohol consumption and CHL (living to age 85 without cognitive impairment), survival to age 85 with cognitive impairment (MMSE score >1.5 standard deviations below expectation for age, sex, and education), or death before age 85. Most participants (88%) reported some current alcohol intake; 49% reported a moderate amount of alcohol intake, and 48% reported drinking near-daily. Relative to nondrinkers, moderate and heavy drinkers (up to 3 drinks/day for women and for men 65 years and older, up to 4 drinks/day for men under 65 years) had significantly higher adjusted odds of survival to age 85 without cognitive impairment (p's < 0.05). Near-daily drinkers had 2-3 fold higher adjusted odds of CHL versus living to at least age 85 with cognitive impairment (odds ratio (OR) = 2.06; 95% confidence interval (CI): 1.21, 3.49) or death before 85 (OR = 3.24; 95% CI: 1.92, 5.46). Although excessive drinking has negative health consequences, these results suggest that regular, moderate drinking may play a role in cognitively healthy longevity.

Alzheimer's Disease: Characterization of the Brain Sites of the Initial Tau Cytoskeletal Pathology Will Improve the Success of Novel Immunological Anti-Tau Treatment Approaches. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Seidel, Kay; Bouzrou, Mohamed; Korf, Horst-Werner (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) represents the most frequent neurodegenerative disease of the human brain worldwide. Currently practiced treatment strategies for AD only include some less effective symptomatic therapeutic interventions, which unable to counteract the disease course of AD. New therapeutic attempts aimed to prevent, reduce, or remove the extracellular depositions of the amyloid-β protein did not elicit beneficial effects on cognitive deficits or functional decline of AD. In view of the failure of these amyloid-β-based therapeutic trials and the close correlation between the brain pathology of the cytoskeletal tau protein and clinical AD symptoms, therapeutic attention has since shifted to the tau cytoskeletal protein as a novel drug target. The abnormal hyperphosphorylation and intraneuronal aggregation of this protein are early events in the evolution of the AD-related neurofibrillary pathology, and the brain spread of the AD-related tau aggregation pathology may possibly follow a corruptive protein templating and seeding-like mechanism according to the prion hypothesis. Accordingly, immunotherapeutic targeting of the tau aggregation pathology during the very early pre-tangle phase is currently considered to represent an effective and promising therapeutic approach for AD. Recent studies have shown that the initial immunoreactive tau aggregation pathology already prevails in several subcortical regions in the absence of any cytoskeletal changes in the cerebral cortex. Thus, it may be hypothesized that the subcortical brain regions represent the "port of entry" for the pathogenetic agent from which the disease ascends anterogradely as an "interconnectivity pathology".
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Humans; Immunotherapy; tau Proteins

Alzheimer's Disease-Related Polymorphisms in Shunt-Responsive Idiopathic Normal Pressure Hydrocephalus. - Huovinen, Joel; Helisalmi, Seppo; Paananen, Jussi; Laiterä, Tiina; Kojoukhova, Maria; Sutela, Anna; Vanninen, Ritva; Laitinen, Marjo; Rauramaa, Tuomas; Koivisto, Anne M; Remes, Anne M; Soininen, Hilkka; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a late onset, surgically treated progressive brain disease caused by impaired cerebrospinal fluid dynamics and subsequent ventriculomegaly. Comorbid Alzheimer's disease (AD) seems to be frequent in iNPH. OBJECTIVE: We aim to evaluate the role of AD-related polymorphisms in iNPH. METHODS: Overall 188 shunt-operated iNPH patients and 688 controls without diagnosed neurodegenerative disease were included into analysis. Twenty-three single-nucleotide polymorphisms (SNPs FRMD4A [rs7081208_A, rs2446581_A, rs17314229_T], CR1, BIN, CD2AP, CLU, MS4A6A, MS4A4E, PICALM, ABCA7, CD33, INPP5D, HLA_DRB5, EPHA1, PTK2B, CELF1, SORL1, FERMT2, SLC24A, DSG2, CASS4, and NME8) adjusted to APOE were analyzed between groups by using binary logistic regression analysis. Neuroradiological characteristics and AD-related changes in the right frontal cortical brain biopsies were available for further analysis. RESULTS: Logistic regression analysis adjusted to age, gender, and other SNPs indicated allelic variation of NME8 between iNPH patients and non-demented controls (p = 0.014). The allelic variation of NME8 was not related to the neuropathological changes in the brain biopsies of iNPH patients. However, periventricular white matter changes (p = 0.017) were more frequent in the iNPH patients with the AA-genotype, an identified risk factor of AD. CONCLUSIONS: Our findings increase the evidence that iNPH is characterized by genetic and pathophysiological mechanisms independent from AD. Considering that NME8 plays a role in the ciliary function and displays SNP-related diversity in white matter changes, the mechanisms of NME8 in iNPH and other neurodegenerative processes are worth further study.

Amygdala α-Synuclein Pathology in the Population-Based Vantaa 85+ Study. - Raunio, Anna; Myllykangas, Liisa; Kero, Mia; Polvikoski, Tuomo; Paetau, Anders; Oinas, Minna (J Alzheimers Dis, 2017)
We investigated the frequency of Lewy-related pathology (LRP) in the amygdala among the population-based Vantaa 85+ study. Data of amygdala samples (N = 304) immunostained with two α-synuclein antibodies (clone 42 and clone 5G4) was compared with the previously analyzed LRP and AD pathologies from other brain regions. The amygdala LRP was present in one third (33%) of subjects. Only 5% of pure AD subjects, but 85% of pure DLB subjects had LRP in the amygdala. The amygdala LRP was associated with dementia; however, the association was dependent on LRP on other brain regions, and thus was not an independent risk factor. The amygdala-predominant category was a rare (4%) and heterogeneous group.

Amylin Enhances Amyloid-β Peptide Brain to Blood Efflux Across the Blood-Brain Barrier. - Mohamed, Loqman A; Zhu, Haihao; Mousa, Youssef M; Wang, Erming; Qiu, Wei Qiao; Kaddoumi, Amal (J Alzheimers Dis, 2017)
Findings from Alzheimer's disease (AD) mouse models showed that amylin treatment improved AD pathology and enhanced amyloid-β (Aβ) brain to blood clearance; however, the mechanism was not investigated. Using the Tg2576 AD mouse model, a single intraperitoneal injection of amylin significantly increased Aβ serum levels, and the effect was abolished by AC253, an amylin receptor antagonist, suggesting that amylin effect could be mediated by its receptor. Subsequent mechanistic studies showed amylin enhanced Aβ transport across a cell-based model of the blood-brain barrier (BBB), an effect that was abolished when the amylin receptor was inhibited by two amylin antagonists and by siRNA knockdown of amylin receptor Ramp3. To explain this finding, amylin effect on Aβ transport proteins expressed at the BBB was evaluated. Findings indicated that cells treated with amylin induced LRP1 expression, a major receptor involved in brain Aβ efflux, in plasma membrane fraction, suggesting intracellular translocation of LRP1 from the cytoplasmic pool. Increased LRP1 in membrane fraction could explain, at least in part, the enhanced uptake and transport of Aβ across the BBB. Collectively, our findings indicated that amylin induced Aβ brain to blood clearance through amylin receptor by inducing LRP1 subcellular translocation to the plasma membrane of the BBB endothelium.

Amylin Treatment Reduces Neuroinflammation and Ameliorates Abnormal Patterns of Gene Expression in the Cerebral Cortex of an Alzheimer's Disease Mouse Model. - Wang, Erming; Zhu, Haihao; Wang, Xiaofan; Gower, Adam; Wallack, Max; Blusztajn, Jan Krzysztof; Kowall, Neil; Qiu, Wei Qiao (J Alzheimers Dis, 2017)
Our recent study has demonstrated that peripheral amylin treatment reduces the amyloid pathology in the brain of Alzheimer's disease (AD) mouse models, and improves their learning and memory. We hypothesized that the beneficial effects of amylin for AD was beyond reducing the amyloids in the brain, and have now directly tested the actions of amylin on other aspects of AD pathogenesis, especially neuroinflammation. A 10-week course of peripheral amylin treatment significantly reduced levels of cerebral inflammation markers, Cd68 and Iba1, in amyloid precursor protein (APP) transgenic mice. Mechanistic studies indicated the protective effect of amylin required interaction with its cognate receptor because silencing the amylin receptor expression blocked the amylin effect on Cd68 in microglia. Using weighted gene co-expression network analysis, we discovered that amylin treatment influenced two gene modules linked with amyloid pathology: 1) a module related to proinflammation and transport/vesicle process that included a hub gene of Cd68, and 2) a module related to mitochondria function that included a hub gene of Atp5b. Amylin treatment restored the expression of most genes in the APP cortex toward levels observed in the wild-type (WT) cortex in these two modules including Cd68 and Atp5b. Using a human dataset, we found that the expression levels of Cd68 and Atp5b were significantly correlated with the neurofibrillary tangle burden in the AD brain and with their cognition. These data suggest that amylin acts on the pathological cascade in animal models of AD, and further supports the therapeutic potential of amylin-type peptides for AD.

Amyloid Burden in Obstructive Sleep Apnea. - Yun, Chang-Ho; Lee, Ho-Young; Lee, Seung Ku; Kim, Hyun; Seo, Hyung Suk; Bang, Seong Ae; Kim, Sang Eun; Greve, Douglas N; Au, Rhoda; Shin, Chol; Thomas, Robert J (J Alzheimers Dis, 2017)
To test the hypothesis that excessive amyloid deposition is a biological link between obstructive sleep apnea (OSA) and Alzheimer's disease, we determined whether OSA increases cerebral amyloid burden, relative to controls, using Pittsburgh Compound B (PiB) PET imaging. The subjects were adult participants (age 50-65 years) from the Korean Genome and Epidemiology Study. Polysomnography, brain MRI including 3D images, and a detailed neuro-cognitive function test battery were done in 2011-2012. Nineteen OSA subjects (Apnea-Hypopnea Index [AHI] ≥15/h, 21.2±5.1/h; age 58.5±4.1 years; 9 male) and 19 controls (AHI 1.8±1.3/h; age 58.5±4.2 years; 9 male) underwent 60-min dynamic 11C-PiB PET. All subjects were right-handed with normal cognitive function and brain MRI. Controls were matched by age, gender, education, and APOE genotype. A voxel-wise comparison of PiB-PET images between the two groups was performed after spatial and count normalization with cerebellar gray matter as a reference. Covariates included the status of sleep duration, hypertension, diabetes, body mass index, exercise, depressive mood, smoking, and alcohol drinking. Cortical thickness on 3D MRI was also measured and compared between the two groups. The OSA group showed a higher PiB deposition in the right posterior cingulate gyrus and right temporal cortex (corrected p < 0.05). There was no area of higher uptake in the control compared with OSA. Regional differences in cortical thickness were not significant. The study suggests that OSA accelerates amyloid deposition and may contribute to the development or progression of Alzheimer's disease.

Amyloid Plaques Show Binding Capacity of Exogenous Injected Amyloid-β. - Gureviciene, Irina; Gurevicius, Kestutis; Mugantseva, Ekaterina; Kislin, Mikhail; Khiroug, Leonard; Tanila, Heikki (J Alzheimers Dis, 2017)
Amyloid plaques, although inducing damage to the immediately surrounding neuropil, have been proposed to provide a relatively innocuous way to deposit toxic soluble amyloid-β (Aβ) species. Here we address this hypothesis by exploring spread and absorption of fluorescent Aβ to pre-existing amyloid plaques after local application in wild-type mice versus APP/PS1 transgenic mice with amyloid plaques. Local intracortical or intracerebroventricular injection of fluorescently-labeled Aβ in APP/PS1 mice with a high plaque density resulted in preferential accumulation of the peptide in amyloid plaques in both conventional postmortem histology and in live imaging using two-photon microscopy. These findings support the contention that amyloid plaques may act as buffers to protect neurons from the toxic effects of momentary high concentrations of soluble Aβ oligomers.

Amyloid-Related Imaging Abnormalities in an Aged Squirrel Monkey with Cerebral Amyloid Angiopathy. - Heuer, Eric; Jacobs, Jessica; Du, Rebecca; Wang, Silun; Keifer, Orion P; Cintron, Amarallys F; Dooyema, Jeromy; Meng, Yuguang; Zhang, Xiaodong; Walker, Lary C (J Alzheimers Dis, 2017)
Amyloid-related imaging abnormalities (ARIA) in magnetic resonance imaging scans have emerged as indicators of potentially serious side effects in clinical trials of therapeutics for Alzheimer's disease. These anomalies include an edematous type (ARIA-E) that appears as hyperintense (bright) regions by T2-weighted MRI, and a type characterized by the deposition of hemosiderin (ARIA-H) that elicits a hypointense signal, especially in T2* susceptibility weighted images. ARIA in general has been linked to the presence of amyloid-β (Aβ)-type cerebral amyloid angiopathy, an accumulation of misfolded Aβ protein in the vascular wall that impairs the integrity of brain blood vessels. However, the pathobiology of ARIA remains poorly understood, in part due to the absence of an animal model of the disorder that would enable a contemporaneous analysis of tissue integrity in the affected region. Here we describe both ARIA-E and ARIA-H in an aged squirrel monkey (Saimiri sciureus), a nonhuman primate model of naturally occurring cerebral amyloid angiopathy. Histopathologic examination of the anomalous region revealed reactive astrocytosis and microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition. The disruption of axons in particular suggests that ARIA-E could have functional consequences for affected regions. The squirrel monkey model can be useful for studying the pathogenesis and long-term effects of ARIA, and for testing the safety and efficacy of emerging therapies for Alzheimer's disease.

Analytical Strategy to Prioritize Alzheimer's Disease Candidate Genes in Gene Regulatory Networks Using Public Expression Data. - Kawalia, Shweta Bagewadi; Raschka, Tamara; Naz, Mufassra; de Matos Simoes, Ricardo; Senger, Philipp; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) progressively destroys cognitive abilities in the aging population with tremendous effects on memory. Despite recent progress in understanding the underlying mechanisms, high drug attrition rates have put a question mark behind our knowledge about its etiology. Re-evaluation of past studies could help us to elucidate molecular-level details of this disease. Several methods to infer such networks exist, but most of them do not elaborate on context specificity and completeness of the generated networks, missing out on lesser-known candidates. In this study, we present a novel strategy that corroborates common mechanistic patterns across large scale AD gene expression studies and further prioritizes potential biomarker candidates. To infer gene regulatory networks (GRNs), we applied an optimized version of the BC3Net algorithm, named BC3Net10, capable of deriving robust and coherent patterns. In principle, this approach initially leverages the power of literature knowledge to extract AD specific genes for generating viable networks. Our findings suggest that AD GRNs show significant enrichment for key signaling mechanisms involved in neurotransmission. Among the prioritized genes, well-known AD genes were prominent in synaptic transmission, implicated in cognitive deficits. Moreover, less intensive studied AD candidates (STX2, HLA-F, HLA-C, RAB11FIP4, ARAP3, AP2A2, ATP2B4, ITPR2, and ATP2A3) are also involved in neurotransmission, providing new insights into the underlying mechanism. To our knowledge, this is the first study to generate knowledge-instructed GRNs that demonstrates an effective way of combining literature-based knowledge and data-driven analysis to identify lesser known candidates embedded in stable and robust functional patterns across disparate datasets.

Angiotensin-III is Increased in Alzheimer's Disease in Association with Amyloid-β and Tau Pathology. - Kehoe, Patrick Gavin; Hibbs, Elliott; Palmer, Laura E; Miners, J Scott (J Alzheimers Dis, 2017)
Hyperactivity of the renin-angiotensin system (RAS) is associated with the pathogenesis of Alzheimer's disease (AD) believed to be mediated by angiotensin-II (Ang-II) activation of the angiotensin type 1 receptor (AT1R). We previously showed that angiotensin-converting enzyme-1 (ACE-1) activity, the rate-limiting enzyme in the production of Ang-II, is increased in human postmortem brain tissue in AD. Angiotensin-III (Ang-III) activates the AT1R and angiotensin type-2 receptor (AT2R), but its potential role in the pathophysiology of AD remains unexplored. We measured Ang-II and Ang-III levels by ELISA, and the levels and activities of aminopeptidase-A (AP-A) and aminopeptidase-N (AP-N) (responsible for the production and metabolism of Ang-III, respectively) in human postmortem brain tissue in the mid-frontal cortex (Brodmann area 9) in a cohort of AD (n = 90) and age-matched non-demented controls (n = 59), for which we had previous measurements of ACE-1 activity, Aβ level, and tau pathology (also in the mid-frontal cortex). We found that both Ang-II and Ang-III levels were significantly higher in AD compared to age-matched controls and that Ang-III, rather than Ang-II, was strongly associated with Aβ load and tau load. Levels of AP-A were significantly reduced in AD but AP-A enzyme activity was unchanged whereas AP-N activity was reduced in AD but AP-N protein level was unchanged. Together, these data indicate that the APA/Ang-III/APN/Ang-IV/AT4R pathway is dysregulated and that elevated Ang-III could contribute to the pathogenesis of AD.

Antibodies to Signaling Molecules and Receptors in Alzheimer's Disease are Associated with Psychomotor Slowing, Depression, and Poor Visuospatial Function. - Giil, Lasse M; Vedeler, Christian A; Kristoffersen, Einar K; Nordrehaug, Jan Erik; Heidecke, Harald; Dechend, Ralf; Schulze-Forster, Kai; Muller, Dominik N; von Goetze, Victoria S; Cabral-Marques, Otavio; Riemekasten, Gabriela; Vogelsang, Petra; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with several antibodies as well as signaling molecules and receptors. These may be detrimental in the presence of a disrupted blood-brain barrier (BBB). OBJECTIVE: To investigate whether the levels of antibodies toward 33 signaling molecules involved in neurotransmitter, vascular, and immune functions were associated with AD and, within the AD group; cognitive function and mood. METHODS: Antibodies in sera from patients with mild AD [(n = 91) defined as a Mini-Mental State Examination ≥ 20 or a Clinical Dementia Rating Scale≤1] and healthy controls (n = 102) were measured with enzyme-linked immunosorbent assays. Levels in AD and controls were compared by Mann-Whitney test. In the AD group, associations between antibodies and psychometric test scores were analyzed by robust regression. The false discovery threshold was set to 0.05. RESULTS: Antibodies to serotonin receptors [5-HT2AR (effect size (r) = 0.21, p = 0.004), 5-HT2CR (r = 0.25, p = 0.0005) and 5-HT7R (r = 0.21, p = 0.003)], vascular endothelial growth factor receptor 1 [VEGFR1 (r = 0.29, p < 0.001)] and immune-receptors (Stabilin-1 (r = 0.23, p = 0.001) and C5aR1 (r = 0.21, p = 0.004) were higher in AD. Psychomotor speed was associated with D1R-abs (β 0.49, p < 0.001), depression with ETAR-abs (β 0.31, p < 0.001), and visuospatial function with 5-HT1AR-abs (β 0.27, p = 0.004) despite similar antibody levels compared to controls. CONCLUSIONS: Antibody levels to VEGFR1, serotonergic receptors, and receptors in the immune system were increased in AD. Antibodies at similar levels as in controls were associated cognitive dysfunction and depression in AD.

Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.

Aortic Valve Calcification and the Risk of dementia: A Population-Based Study. - Wolters, Frank J; Bos, Daniel; Vernooij, Meike W; Franco, Oscar H; Hofman, Albert; Koudstaal, Peter J; van der Lugt, Aad; Ikram, M Arfan (J Alzheimers Dis, 2017)
The association of aortic valve calcification (AVC) with dementia remains unknown. In 2,428 non-demented participants from the population-based Rotterdam Study, we investigated the association of CT-assessed AVC with risk of dementia and cognitive decline. AVC was present in 33.1% of the population. During a median follow-up of 9.3 years, 160 participants developed dementia. We found no association between presence of AVC and risk of all-cause dementia [hazard ratio (HR): 0.89 (95% confidence interval (CI):0.63;1.26)]. Presence of AVC was not associated with cognitive decline on any of the cognitive tests, nor with a measure of global cognition.

Apolipoprotein A1 in Cerebrospinal Fluid and Plasma and Progression to Alzheimer's Disease in Non-Demented Elderly. - Slot, Rosalinde E R; Van Harten, Argonde C; Kester, Maartje I; Jongbloed, Wesley; Bouwman, Femke H; Teunissen, Charlotte E; Scheltens, Philip; Veerhuis, Robert; van der Flier, Wiesje M (J Alzheimers Dis, 2017)
BACKGROUND: HDL-cholesterol transporter Apolipoprotein A1 (ApoA1) holds neuroprotective properties, such as inhibition of amyloid-β aggregation. Low plasma ApoA1 concentrations are associated with Alzheimer's disease (AD). Little is known about ApoA1 levels in the pre-dementia stages of AD. OBJECTIVE: To investigate associations between cerebrospinal fluid (CSF) and plasma ApoA1 levels and clinical progression toward AD in non-demented elderly. METHODS: From the Amsterdam Dementia Cohort, we included 429 non-demented elderly with subjective cognitive decline (SCD; n = 206, 61±9 years, Mini-Mental State Exam (MMSE) 28±2) and mild cognitive impairment (MCI; n = 223, 67±8 years, MMSE 27±2), with a mean follow-up of 2.5±1.6 years. We used Cox proportional hazard models to investigate relations between CSF and plasma ApoA1 concentrations and clinical progression, defined as progression to MCI or AD for SCD, and progression to AD for MCI. Analyses were adjusted for age, gender, MMSE, and plasma cholesterol levels. Analyses were stratified for diagnosis and APOEɛ4 carriership. RESULTS: 117 patients (27%) showed clinical progression. One standard deviation increase of CSF ApoA1 was associated with a 30% increased risk of clinical progression (hazard ratio (HR) (95% CI)  = 1.3(1.0-1.6)). The effect appeared to be attributable to the APOEɛ4 carriers with SCD (HR 3.3(1.0-10.9)). Lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD (HR 5.0(1.3-18.9)). CONCLUSION: Higher CSF and lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD; suggesting that ApoA1 may be involved in the earliest stages of AD.

Apomorphine Therapy for Neuronal Insulin Resistance in a Mouse Model of Alzheimer's Disease. - Nakamura, Norimichi; Ohyagi, Yasumasa; Imamura, Tomohiro; Yanagihara, Yuki T; Iinuma, Kyoko M; Soejima, Naoko; Murai, Hiroyuki; Yamasaki, Ryo; Kira, Jun-Ichi (J Alzheimers Dis, 2017)
Apomorphine (APO) promotes intraneuronal amyloid-β (Aβ) degradation and improves memory function in an Alzheimer's disease (AD) model, 3xTg-AD mice. Since insulin resistance is increased in AD neurons, we investigated the effects of APO on brain insulin resistance in 3xTg-AD mice at early and late stages. After 1-month subcutaneous injection of Apokyn® to 3xTg-AD mice at 6 or 12 months of age, memory function was significantly improved in both age groups. Protein levels of insulin-degrading enzyme (IDE), which is linked to insulin signaling and degrades Aβ, significantly increased in the 3xTg-AD mice brain compared with non-transgenic mice, and were further increased by APO. Protein levels of two types of serine-phosphorylated insulin receptor substrate-1 (IRS-1), pS616 and pS636/639, significantly decreased following APO treatment in the 13-month-old 3xTg-AD mice brain, suggesting improved brain insulin resistance. Immunostaining of the IDE, pS616 and pS636/639 IRS-1 demonstrated similar changes due to APO treatment. Thus, brain insulin resistance is considered an important therapeutic target in AD, and APO may provide improved neuronal insulin resistance.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

Association between Anti-Dementia Treatment Persistence and Daily Dosage of the First Prescription: A Retrospective Analysis in Neuropsychiatric Practices in Germany. - Bohlken, Jens; Jacob, Louis; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: High adherence and persistence are important for the efficacy of anti-dementia treatments. OBJECTIVE: The goal of this study was to analyze the association between anti-dementia treatment persistence and daily dosage of the first prescription in patients treated in neuropsychiatric practices in Germany. METHODS: This study included patients aged 60 years or over who were diagnosed with Alzheimer's disease and received anti-dementia prescriptions (galantamine, donepezil, memantine, and rivastigmine) for the first time between 2005 and 2014. The main outcome measure was the treatment persistence rate within 12 months after the index date as a function of the first dose. Cox proportional hazards regression models were used to estimate the relation between persistence and daily dosages after adjusting for age, gender, and residence in nursing homes. RESULTS: In this study, 2,442, 5,669, 4,416, 642, and 2,334 patients received galantamine, donepezil, memantine, oral rivastigmine, and patch rivastigmine, respectively. After 12 months of follow-up, continuation rates were similar for individuals using different doses of galantamine, donepezil, oral rivastigmine, and patch rivastigmine, but were significantly different for those taking memantine. Patients using 20 mg of memantine were less likely to discontinue their treatment than patients using 10 mg (HR = 0.88, 95% CI: 0.80-0.96). There was no significant association between daily dosages and persistence for the other drugs (HRs ranging from 0.86 to 1.15). CONCLUSIONS: There was no significant association between treatment persistence and daily dosages in patients with Alzheimer's disease in Germany who were treated with galantamine, donepezil, or rivastigmine.

Association between Cholesterol Exposure and Neuropathological Findings: The ACT Study. - Bettcher, Brianne M; Ard, M Colin; Reed, Bruce R; Benitez, Andreana; Simmons, Amanda; Larson, Eric B; Sonnen, Josh A; Montine, Thomas J; Li, Ge; Keene, C Dirk; Crane, Paul K; Mungas, Dan (J Alzheimers Dis, 2017)
We characterized the relationship between late life cholesterol exposure and neuropathological outcomes in a community-based, older adult cohort. Adult Changes in Thought (ACT) is a cohort study that enrolls consenting, randomly selected, non-demented people aged ≥65 from a healthcare delivery system. We used late life HDL and total cholesterol lab values from Group Health computerized records, and calculated HDL and non-HDL levels. We evaluated neuropathological outcomes of Alzheimer's disease, cerebral amyloid angiopathy, vascular brain injury, and Lewy body disease. Using linear mixed models with age and antilipemic medication as predictors, we obtained predicted cholesterol values at age 70 and 10 years prior to death for individuals with available cholesterol data in 10-year exposure windows. We used logistic regression to determine whether predicted late life cholesterol levels were associated with neuropathological outcomes controlling for age at death, APOE genotype, sex, and their interactions with cholesterol levels. 525 decedents came to autopsy by 08/2014. Of these, plasma cholesterol concentration was available for 318 (age 70, model 1) and 396 (10 years prior to death, model 2) participants. We did not find associations between late life cholesterol and Alzheimer's disease neuropathological changes, and there were no associations between cholesterol levels and amyloid angiopathy or vascular brain injury. We observed an association between predicted non-HDL cholesterol at age 70 and Lewy body disease. Our study suggests an association between late life non-HDL cholesterol exposure and Lewy body disease. We did not observe associations between late life cholesterol levels and Braak stage or CERAD score.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Association between Mid-Regional Proadrenomedullin Levels and Progression of Deep White Matter Lesions in the Brain Accompanying Cognitive Decline. - Kuriyama, Nagato; Ihara, Masafumi; Mizuno, Toshiki; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Kondo, Masaki; Tokuda, Takahiko; Tamura, Aiko; Yamada, Kei; Akazawa, Kentaro; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Adrenomedullin (ADM) is a vasoreactive physiological peptide with anti-inflammatory effects and vasodilative and immunomodulatory actions that is widely distributed throughout the vascular system of the brain. OBJECTIVE: To investigate mid-regional proADM (MR-proADM), a stable fragment of the ADM precursor, and cerebral deep white matter lesions (DWMLs) in association with cognitive decline. METHODS: The study participants were 288 patients (194 men, 94 women) who gave consent to participate in a 5-year longitudinal survey on arteriosclerosis from 2008 to 2013. The Fazekas classification system (Grade [G] 0 [normal] to G3 [severe]) was used for the evaluation of DWMLs on brain magnetic resonance imaging (MRI). In addition, all participants were asked to undergo cognitive function tests regarding word/letter fluency, the results of which were assessed for correlations with MR-proADM levels. RESULTS: MR-proADM levels significantly increased with DWML grade progression. The odds ratio for high MR-proADM levels was 3.08 (95% confidence interval: 1.49-5.17) in the groups graded G3 on brain MRI, suggesting that a high level of MR-proADM is an independent risk factor for DWMLs. A significant inverse correlation was observed between MR-proADM levels and cognitive test scores. MR-proADM levels were significantly increased in the G3 group in 2013 compared with 2008. CONCLUSION: MR-proADM levels were significantly different between the DWML groups and inversely correlated with cognitive function test scores, suggesting that high MR-proADM levels and DWMLs are associated with cognitive decline. Therefore, the MR-proADM level may be an effective candidate as a potential diagnostic surrogate marker of cognitive decline.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Association of Central Arterial Stiffness and Pressure Pulsatility with Mild Cognitive Impairment and Dementia: The Atherosclerosis Risk in Communities Study-Neurocognitive Study (ARIC-NCS). - Meyer, Michelle L; Palta, Priya; Tanaka, Hirofumi; Deal, Jennifer A; Wright, Jacqueline; Knopman, David S; Griswold, Michael E; Mosley, Thomas H; Heiss, Gerardo (J Alzheimers Dis, 2017)
BACKGROUND: The association of central arterial stiffness and pressure pulsatility with mild cognitive impairment (MCI) and dementia is not well characterized in the population-based setting. OBJECTIVE: The aim of this study was to quantify the cross-sectional association of arterial stiffness and pressure pulsatility with MCI and dementia among 4,461 older white and black adults from the population-based Atherosclerosis Risk in Communities Study-Neurocognitive Study. METHODS: We used race-stratified multinomial logistic regression to evaluate associations of percentile cut points of carotid-femoral pulse wave velocity, central systolic blood pressure, central pulse pressure, and pulse pressure amplification with MCI and dementia versus no cognitive impairment. RESULTS: Among whites, those with carotid-femoral pulse wave velocity or central systolic blood pressure ≥75th percentile had a higher prevalence of MCI compared to participants <75th percentile (conditional odds ratio (OR); 95% confidence interval (CI): 1.27 (1.02, 1.56) and 1.28 (1.04, 1.57), respectively) and those with central pulse pressure ≥75th percentile had a higher prevalence of MCI (OR 1.27 (95% CI: 1.03, 1.58)) and dementia (OR 1.76 (95% CI: 1.06, 2.92) compared to participants <75th percentile. Also among whites, those with pulse pressure amplification ≤25th percentile had a higher prevalence of dementia compared to participants >25th percentile (OR 1.65; (95% CI: 1.01, 2.70). Weaker associations were seen among black participants. CONCLUSION: Higher arterial stiffness and pulsatility were associated with MCI and dementia in white participants. Longitudinal characterization of the observed associations is warranted to assess whether arterial stiffness and pressure pulsatility predict MCI and dementia among older adults.

Association of Gait Speed, Psychomotor Speed, and Dementia. - Kuate-Tegueu, Callixte; Avila-Funes, José-Alberto; Simo, Nadine; Le Goff, Mélanie; Amiéva, Hélène; Dartigues, Jean-François; Tabue-Teguo, Maturin (J Alzheimers Dis, 2017)
BACKGROUND: Gait speed (GS) and psychomotor speed (PS) could be considered as two different dimensions of age-related slowness and both measures are associated with higher risk of adverse health-related outcomes among elderly people. OBJECTIVE: To determine the association between GS, PS, and incident dementia among community-dwelling older adults. METHODS: Twelve-year longitudinal study of 1,265 participants in the Bordeaux Three-City Study, a French prospective cohort designed to determine the risk of dementia and cognitive impairment attributable to cardiovascular risk factors. Participants completed a battery of cognitive tests, including time to complete the Trail Making Test A, and a walking speed test. The incidence of dementia was determined over the 12-year follow-up period. Cox proportional hazards models with delayed entry were used to estimate the cumulative risk of dementia and were adjusted for sex, education, and ApoE4 genotype. RESULTS: Mean age of participants was 74.0 years (SD 4.8). Over the 12-year follow-up, 203 participants developed dementia. GS and PS were both independent predictors of incident all-cause dementia after 12 years of follow-up. For a one SD increase of either GS or PS, the hazard ratio (HR) for Alzheimer's disease was 1.2 (95% CI = 1.02-1.32) and 1.4 (95% CI = 1.2-1.61), respectively; whereas for incident vascular dementia, the HR was 1.3 (95% CI = 1.05-1.71) and 1.5 (95% CI = 1.16-2.08), respectively. No significant interaction between GS and PS was observed. CONCLUSIONS: In older French people aged 65+, our findings showed that both low GS and PS were independently associated with risk of incident Alzheimer's disease and vascular dementia.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Associations of CAIDE Dementia Risk Score with MRI, PIB-PET measures, and cognition. - Stephen, Ruth; Liu, Yawu; Ngandu, Tiia; Rinne, Juha O; Kemppainen, Nina; Parkkola, Riitta; Laatikainen, Tiina; Paajanen, Teemu; Hänninen, Tuomo; Strandberg, Timo; Antikainen, Riitta; Tuomilehto, Jaakko; et al. (J Alzheimers Dis, 2017)
BACKGROUND: CAIDE Dementia Risk Score is the first validated tool for estimating dementia risk based on a midlife risk profile. OBJECTIVES: This observational study investigated longitudinal associations of CAIDE Dementia Risk Score with brain MRI, amyloid burden evaluated with PIB-PET, and detailed cognition measures. METHODS: FINGER participants were at-risk elderly without dementia. CAIDE Risk Score was calculated using data from previous national surveys (mean age 52.4 years). In connection to baseline FINGER visit (on average 17.6 years later, mean age 70.1 years), 132 participants underwent MRI scans, and 48 underwent PIB-PET scans. All 1,260 participants were cognitively assessed (Neuropsychological Test Battery, NTB). Neuroimaging assessments included brain cortical thickness and volumes (Freesurfer 5.0.3), visually rated medial temporal atrophy (MTA), white matter lesions (WML), and amyloid accumulation. RESULTS: Higher CAIDE Dementia Risk Score was related to more pronounced deep WML (OR 1.22, 95% CI 1.05-1.43), lower total gray matter (β-coefficient -0.29, p = 0.001) and hippocampal volume (β-coefficient -0.28, p = 0.003), lower cortical thickness (β-coefficient -0.19, p = 0.042), and poorer cognition (β-coefficients -0.31 for total NTB score, -0.25 for executive functioning, -0.33 for processing speed, and -0.20 for memory, all p < 0.001). Higher CAIDE Dementia Risk Score including APOE genotype was additionally related to more pronounced MTA (OR 1.15, 95% CI 1.00-1.30). No associations were found with periventricular WML or amyloid accumulation. CONCLUSIONS: The CAIDE Dementia Risk Score was related to indicators of cerebrovascular changes and neurodegeneration on MRI, and cognition. The lack of association with brain amyloid accumulation needs to be verified in studies with larger sample sizes.

Atrial Fibrillation is Independently Associated with Cognitive Impairment after Ischemic Stroke. - Chander, Russell Jude; Lim, Levinia; Handa, Sagarika; Hiu, Shaun; Choong, Angeline; Lin, Xuling; Singh, Rajinder; Oh, Daniel; Kandiah, Nagaendran (J Alzheimers Dis, 2017)
BACKGROUND: While atrial fibrillation (AF) is an important risk factor for ischemic strokes and mild cognitive impairment (MCI) in Alzheimer's disease, the association between AF and post-stroke cognitive impairment (PSCI), and the factors mediating this association, is unclear. OBJECTIVE: To investigate the role of AF in PSCI, especially in relation to other markers of cerebrovascular disease. METHODS: 445 subjects with mild ischemic stroke without pre-stroke cognitive decline were assessed 3-6 months post-stroke for cognitive deficits. MRIs were reviewed by trained raters for acute infarct characteristics, global cortical atrophy, white matter hyperintensities, cerebral microbleeds, and intracranial stenosis. Logistic regression analysis was used to identify factors independently associated with PSCI. Subjects were also categorized according to paroxysmal (pAF) or persistent/chronic AF (p/cAF), and presence or absence of AF or large cortical infarcts (LCI) to study cognitive trends. RESULTS: 80 (18.0%) subjects had AF. 76.3% of AF subjects and 42.7% of subjects without AF had PSCI. The odds ratio (OR) of AF in developing PSCI was 2.31 (95% CI: 1.12-4.75; p = 0.035), after correcting for other risk factors. pAF subjects and AF subjects with LCIs had higher ORs for PSCI. AF subjects performed worse in neuropsychological tasks associated with global cognition, episodic memory, and executive function. CONCLUSION: AF is a significant risk factor for PSCI, even after correcting for AF-related infarcts. Other mechanisms, such as hypoperfusion, microhemorrhages, and neuroinflammation, may be at play. All stroke patients with AF, regardless of the type of infarction, should be closely monitored for PSCI.

AVN-492, A Novel Highly Selective 5-HT6R Antagonist: Preclinical Evaluation. - Ivachtchenko, Alexandre V; Okun, Ilya; Aladinskiy, Vladimir; Ivanenkov, Yan; Koryakova, Angela; Karapetyan, Ruben; Mitkin, Oleg; Salimov, Ramiz; Ivashchenko, Andrey (J Alzheimers Dis, 2017)
Discovery of 5-HT6 receptor subtype and its exclusive localization within the central nervous system led to extensive investigations of its role in Alzheimer's disease, schizophrenia, and obesity. In the present study, we present preclinical evaluation of a novel highly-potent and highly-selective 5-HT6R antagonist, AVN-492. The affinity of AVN-492 to bind to 5-HT6R (Ki = 91 pM) was more than three orders of magnitude higher than that to bind to the only other target, 5-HT2BR, (Ki = 170 nM). Thus, the compound displayed great 5-HT6R selectivity against all other serotonin receptor subtypes, and is extremely specific against any other receptors such as adrenergic, GABAergic, dopaminergic, histaminergic, etc. AVN-492 demonstrates good in vitro and in vivo ADME profile with high oral bioavailability and good brain permeability in rodents. In behavioral tests, AVN-492 shows anxiolytic effect in elevated plus-maze model, prevents an apomorphine-induced disruption of startle pre-pulse inhibition (the PPI model) and reverses a scopolamine- and MK-801-induced memory deficit in passive avoidance model. No anti-obesity effect of AVN-492 was found in a murine model. The data presented here strongly indicate that due to its high oral bioavailability, extremely high selectivity, and potency to block the 5-HT6 receptor, AVN-492 is a very promising tool for evaluating the role the 5-HT6 receptor might play in cognitive and neurodegenerative impairments. AVN-492 is an excellent drug candidate to be tested for treatment of such diseases, and is currently being tested in Phase I trials.

AZD3293: Pharmacokinetic and Pharmacodynamic Effects in Healthy Subjects and Patients with Alzheimer's Disease. - Cebers, Gvido; Alexander, Robert C; Haeberlein, Samantha Budd; Han, David; Goldwater, Ronald; Ereshefsky, Larry; Olsson, Tina; Ye, Naidong; Rosen, Laura; Russell, Muir; Maltby, Justine; Eketjäll, Susanna; et al. (J Alzheimers Dis, 2017)
AZD3293 (LY3314814) is a promising new potentially disease-modifying BACE1 (β-secretase) inhibitor in Phase III clinical development for the treatment of Alzheimer's disease. Reported here are the first two Phase I studies: (1) a single ascending dose study evaluating doses of 1-750 mg with a food-effect component (n = 72), and (2) a 2-week multiple ascending dose study evaluating doses of 15 or 50 mg once daily (QD) or 70 mg once weekly (QW) in elderly subjects (Part 1, n = 31), and 15, 50, or 150 mg QD in patients with mild to moderate Alzheimer's disease (Part 2, n = 16). AZD3293 was generally well tolerated up to the highest doses given. No notable food effects were observed. PK following multiple doses (Part 2) were tmax of 1 to 3 h and mean t1/2 of 16 to 21 h across the 15 to 150 mg dose range. For single doses of ≥5 mg, a ≥70% reduction was observed in mean plasma Aβ40 and Aβ42 concentrations, with prolonged suppression for up to 3 weeks at the highest dose level studied. Following multiple doses, robust reductions in plasma (≥64% at 15 mg and ≥78% at ≥50 mg) and cerebrospinal fluid (≥51% at 15 mg and ≥76% at ≥50 mg) Aβ peptides were seen, including prolonged suppression even with a QW dosing regimen. AZD3293 is the only BACE1 inhibitor for which prolonged suppression of plasma Aβ with a QW dosing schedule has been reported. Two Phase III studies of AZD3293 (AMARANTH, NCT02245737; and DAYBREAK-ALZ, NCT02783573) are now ongoing.

Baseline Telomere Length and Effects of a Multidomain Lifestyle Intervention on Cognition: The FINGER Randomized Controlled Trial. - Sindi, Shireen; Ngandu, Tiia; Hovatta, Iiris; Kåreholt, Ingemar; Antikainen, Riitta; Hänninen, Tuomo; Levälahti, Esko; Laatikainen, Tiina; Lindström, Jaana; Paajanen, Teemu; Peltonen, Markku; Khalsa, Dharma Singh; et al. (J Alzheimers Dis, 2017)
Leukocyte telomere length (LTL) is a biomarker of aging, and it is associated with lifestyle. It is currently unknown whether LTL is associated with the response to lifestyle interventions. The goal is to assess whether baseline LTL modified the cognitive benefits of a 2-year multidomain lifestyle intervention (exploratory analyses). The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a 2-year randomized controlled trial including 1,260 people at risk of cognitive decline, aged 60-77 years identified from the general population. Participants were randomly assigned to the lifestyle intervention (diet, exercise, cognitive training, and vascular risk management) and control (general health advice) groups. Primary outcome was change in cognition (comprehensive neuropsychological test battery). Secondary outcomes were changes in cognitive domains: memory, executive functioning, and processing speed. 775 participants (392 control, 383 intervention) had baseline LTL (peripheral blood DNA). Mixed effects regression models with maximum likelihood estimation were used to analyze change in cognition as a function of randomization group, time, baseline LTL, and their interaction. Intervention and control groups did not significantly differ at baseline. Shorter LTL was related to less healthy baseline lifestyle. Intervention benefits on executive functioning were more pronounced among those with shorter baseline LTL (p-value for interaction was 0.010 adjusted for age and sex, and 0.007 additionally adjusted for baseline lifestyle factors). The FINGER intervention cognitive benefits were more pronounced with shorter baseline LTL, particularly for executive functioning, indicating that the multidomain lifestyle intervention was especially beneficial among higher-risk individuals.

BDNF Responses in Healthy Older Persons to 35 Minutes of Physical Exercise, Cognitive Training, and Mindfulness: Associations with Working Memory Function. - Håkansson, Krister; Ledreux, Aurélie; Daffner, Kirk; Terjestam, Yvonne; Bergman, Patrick; Carlsson, Roger; Kivipelto, Miia; Winblad, Bengt; Granholm, Ann-Charlotte; Mohammed, Abdul Kadir H (J Alzheimers Dis, 2017)
Brain-derived neurotrophic factor (BDNF) has a central role in brain plasticity by mediating changes in cortical thickness and synaptic density in response to physical activity and environmental enrichment. Previous studies suggest that physical exercise can augment BDNF levels, both in serum and the brain, but no other study has examined how different types of activities compare with physical exercise in their ability to affect BDNF levels. By using a balanced cross over experimental design, we exposed nineteen healthy older adults to 35-minute sessions of physical exercise, cognitive training, and mindfulness practice, and compared the resulting changes in mature BDNF levels between the three activities. We show that a single bout of physical exercise has significantly larger impact on serum BDNF levels than either cognitive training or mindfulness practice in the same persons. This is the first study on immediate BDNF effects of physical activity in older healthy humans and also the first study to demonstrate an association between serum BDNF responsivity to acute physical exercise and working memory function. We conclude that the BDNF increase we found after physical exercise more probably has a peripheral than a central origin, but that the association between post-intervention BDNF levels and cognitive function could have implications for BDNF responsivity in serum as a potential marker of cognitive health.

Blood Pressure and Hispanic/Latino Cognitive Function: Hispanic Community Health Study/Study of Latinos Results. - Tarraf, Wassim; Rodríguez, Carlos J; Daviglus, Martha L; Lamar, Melissa; Schneiderman, Neil; Gallo, Linda; Talavera, Gregory A; Kaplan, Robert C; Fornage, Myriam; Conceicao, Alan; González, Hector M (J Alzheimers Dis, 2017)
BACKGROUND: Hispanics/Latinos are at increased risk for cardiovascular disease and cognitive decline and dementias. High blood pressure (BP) has been implicated in both stroke and dementias. Associations between BP and cognition among diverse Latinos are still unpublished. OBJECTIVE: We examined associations between cognition and four BP based measures among diverse Hispanics/Latinos. We hypothesized that higher BP, particularly systolic pressure, and increased arterial stiffness (i.e., pulse pressure), would be associated with lower cognitive function. METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; n = 9,019; ages 45-74 years) data to examine cognition in relation to BP measures. RESULTS: In age, sex, and education adjusted models, systolic, pulse, and mean arterial pressure were consistently negatively associated with executive function, psychomotor speed and sustained attention, verbal episodic learning and memory, speech fluency, and mental status measures. These associations were attenuated but remained statistically significant in fully adjusted models. CONCLUSION: Among middle-aged and older diverse Hispanics/Latinos, we found modest but consistent associations between indicators of arterial stiffness, and compromised blood flow and lower cognitive function. Clinical management and public health interventions to raise awareness and enhance BP management beginning in midlife could reduce disparities and improve population health by reducing cognitive decline burdens.

Body Mass Index, Height, and Socioeconomic Position in Adolescence, Their Trajectories into Adulthood, and Cognitive Function in Midlife. - Cohen-Manheim, Irit; Doniger, Glen M; Sinnreich, Ronit; Simon, Ely S; Murad, Havi; Pinchas-Mizrachi, Ronit; Kark, Jeremy D (J Alzheimers Dis, 2017)
BACKGROUND: Whether life course anthropometric indices relate to cognitive function in midlife remains insufficiently explored. Rarely was socioeconomic position (SEP) adequately accounted for. OBJECTIVE: To examine the association of the cumulative life course burden of high-ranked body mass index (BMI), its trajectory, and stature with cognitive function in midlife. METHODS: Weight and height were measured from age 17 across a 33-year follow-up. 507 individuals completed a NeuroTrax computerized cognitive assessment at ages 48-52. Life course SEP was assessed by multiple methods. Using mixed models we calculated the area under the curve (AUC), representing both the life-course burden of BMI (total AUC) and trends in BMI (incremental AUC) from age 17 to midlife. The associations of BMI and height with global cognition and its five component domains were assessed by multiple regression. RESULTS: Higher BMI in late adolescence and total AUC over the life course were associated with poorer global cognition (Standardized beta (Beta) = -0.111, p = 0.005 and Beta = -0.105, p = 0.018, respectively), adjusted for childhood and adulthood SEP, and demographic characteristics. The associations with higher adolescent and midlife BMI were both restricted to those with low childhood SEP (p < 0.05 for interaction). Short adolescent stature was related to poorer cognition (Beta = 0.084, p = 0.044), whereas late final growth in women was associated with better cognition (Beta = 0.213, p = 0.007). CONCLUSION: An adverse association of higher BMI with cognitive function began in adolescence and was restricted to low childhood SEP. Taller stature in both sexes and late growth in women were associated with better midlife cognitive performance.

Brain Biomarkers in Familial Alzheimer's Disease Mouse Models. - Kuttner-Hirshler, Yafit; Venkatasubramanian, Palamadai N; Apolinario, Joan; Bonds, Jacqueline; Wyrwicz, Alice M; Lazarov, Orly (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by progressive loss of memory and cognitive deterioration. It is thought that the onset of the disease takes place several decades before memory deficits are apparent. Reliable biomarkers for the diagnosis or prognostication of the disease are highly desirable. Neural stem cells (NSC) exist in the adult brain throughout life and give rise to neural progenitor cells (NPC), which differentiate into neurons or glia. The level of NPC proliferation and new neuron formation is significantly compromised in mouse models of familial Alzheimer's disease (FAD). These deficits are readily detected in young adults, at 2-3 months of age, preceding amyloid deposition and cognitive impairments, which may indicate that impaired neurogenesis can be an early biomarker for cognitive deficits in AD. Recent studies suggest that NSC can be detected in live rodents, noninvasively, using proton magnetic resonance spectroscopy (1H-MRS) signal at 1.28 ppm. Here we examined the use of 1H-MRS for determining the extent of neurogenesis in the brains of FAD mice. We observed that the reduction in neurogenesis in the FAD mice as observed by immunohistochemistry, was not manifested by a reduction in the 1.28 ppm signal, suggesting that this marker is either not specific for neurogenesis or not sensitive enough for the detection of alterations in hippocampal neurogenesis in the brains of FAD mice.

The Brain's Structural Connectome Mediates the Relationship between Regional Neuroimaging Biomarkers in Alzheimer's Disease. - Pandya, Sneha; Kuceyeski, Amy; Raj, Ashish (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), one of the most common causes of dementia in adults, is a progressive neurodegenerative disorder exhibiting well-defined neuropathological hallmarks. It is known that disease pathology involves misfolded amyloid-β (Aβ) and tau proteins, and exhibits a relatively stereotyped progression over decades. The relationship between AD neuropathological hallmarks (Aβ, hypometabolism, and tau proteins) and imaging biomarkers (MRI, AV-45/FDG-PET) is not fully understood. In addition, biomarker pathologies are oftentimes discordant, wherein it may show varying levels of abnormality across brain regions. Evidence based on recent elucidation of trans-neuronal "prion-like" transmission and other available data already suggests that disease spread follows the brain's fiber connectivity network. Thereby, the brain's connectome information can be used to predict the process of disease spread in AD. A recently established mathematical model of AD pathology spread using a connectome-based network diffusion model was successful in encapsulating neurodegenerative progression. Motivated by these network-based findings, the current study explores whether and how network connectivity mediates the interactions between various AD biomarkers. We hypothesized that the structural connectivity matrix will mediate the cross-sectional association between regional AD-associated hypometabolism and Aβ deposition. Given recent reports of inherent or lifetime activity of brain regions as strong predictors of Aβ deposition in patients, we also tested whether healthy metabolism exerts a network-mediated effect on Aβ deposition and hypometabolism in AD patients. We found that regional Aβ deposition is best predicted by a linear combination of both regional healthy local metabolism and connectome-mediated regional healthy metabolism.

Bryostatin Effects on Cognitive Function and PKCɛ in Alzheimer's Disease Phase IIa and Expanded Access Trials. - Nelson, Thomas J; Sun, Miao-Kun; Lim, Chol; Sen, Abhik; Khan, Tapan; Chirila, Florin V; Alkon, Daniel L (J Alzheimers Dis, 2017)
Bryostatin 1, a potent activator of protein kinase C epsilon (PKCɛ), has been shown to reverse synaptic loss and facilitate synaptic maturation in animal models of Alzheimer's disease (AD), Fragile X, stroke, and other neurological disorders. In a single-dose (25 μg/m2) randomized double-blind Phase IIa clinical trial, bryostatin levels reached a maximum at 1-2 h after the start of infusion. In close parallel with peak blood levels of bryostatin, an increase of PBMC PKCɛ was measured (p = 0.0185) within 1 h from the onset of infusion. Of 9 patients with a clinical diagnosis of AD, of which 6 received drug and 3 received vehicle within a double-blind protocol, bryostatin increased the Mini-Mental State Examination (MMSE) score by +1.83±0.70 unit at 3 h versus -1.00±1.53 unit for placebo. Bryostatin was well tolerated in these AD patients and no drug-related adverse events were reported. The 25 μg/m2 administered dose was based on prior clinical experience with three Expanded Access advanced AD patients treated with bryostatin, in which return of major functions such as swallowing, vocalization, and word recognition were noted. In one Expanded Access patient trial, elevated PKCɛ levels closely tracked cognitive benefits in the first 24 weeks as measured by MMSE and ADCS-ADL psychometrics. Pre-clinical mouse studies showed effective activation of PKCɛ and increased levels of BDNF and PSD-95. Together, these Phase IIa, Expanded Access, and pre-clinical results provide initial encouragement for bryostatin 1 as a potential treatment for AD.

Can Musical or Painting Interventions Improve Chronic Pain, Mood, Quality of Life, and Cognition in Patients with Mild Alzheimer's Disease? Evidence from a Randomized Controlled Trial. - Pongan, Elodie; Tillmann, Barbara; Leveque, Yohana; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Dauphinot, Virginie; El Haouari, Hanane; Navez, Malou; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Among non-pharmacological therapies, musical intervention is often used for patients with Alzheimer's disease (AD) and patients presenting chronic pain. However, their efficacy is still under debate. OBJECTIVE: Our aim was to determine the efficacy of choral singing versus painting sessions on chronic pain, mood, quality of life, and cognition in AD patients. METHODS: In this multicenter randomized controlled trial, 59 mild AD patients were randomized to a 12-week singing (SG; n = 31) or painting group (PG; n = 28). Chronic pain, anxiety, depression, and quality of life were assessed before, after, and 1 month after the sessions. Cognitive abilities were assessed before and after interventions. The evolution of these different measures was assessed with mixed linear models. The primary data analysis was by intention-to-treat, and completed by a 'per protocol' approach. RESULTS: Both singing and painting interventions led to significant pain reduction (Time effect: F = 4.71; p = 0.01), reduced anxiety (Time effect: F = 10.74; p < 0.0001), improved Quality of Life (Time effect: F = 6.79; p = 0.002), improved digit span (F = 12.93; p = 0.001), and inhibitory processes (Time effect: F = 4.93; p = 0.03). Depression was reduced over time in PG only (Time x Group effect: F = 4.53; p = 0.01). Verbal Memory performance remained stable over time in SG, but decreased in PG (Time x group effect: F = 9.29; p = 0.004). CONCLUSION: Findings suggest that singing and painting interventions may reduce pain and improve mood, quality of life, and cognition in patients with mild AD, with differential effects of painting for depression and singing for memory performance.

Care Plan Improvement in Nursing Homes: An Integrative Review. - Mariani, Elena; Chattat, Rabih; Vernooij-Dassen, Myrra; Koopmans, Raymond; Engels, Yvonne (J Alzheimers Dis, 2017)
BACKGROUND: Care planning nowadays is a key activity in the provision of services to nursing home residents. A care plan describes the residents' needs and the actions to address them, providing both individualized and standardized interventions and should be updated as changes in the residents' conditions occur. OBJECTIVE: The aim of this review was to identify the core elements of the implementation of changes in nursing homes' care plans, by providing an overview of the type of stakeholders involved, describing the implementation strategies used, and exploring how care plans changed. METHODS: An integrative literature review was used to evaluate intervention studies taking place in nursing homes. Data were collected from PubMed, CINHAL-EBSCO, and PsycINFO. English language articles published between 1995 and April 2015 were included. Data analysis followed the strategy of Knafl and Whittemore. RESULTS: Twenty-six articles were included. The stakeholders involved were professionals, family caregivers, and patients. Only a few studies directly involved residents and family caregivers in the quality improvement process. The implementation strategies used were technology implementation, audit, training, feedback, and supervision. The majority of interventions changed the residents' care plans in terms of developing a more standardized care documentation that primarily focuses on its quality. Only some interventions developed more tailored care plans that focus on individualized needs. CONCLUSION: Care plans generally failed in providing both standardized and personalized interventions. Efforts should be made to directly involve residents in care planning and provide professionals with efficient tools to report care goals and actions in care plans.

CD44 Splice Variants as Potential Players in Alzheimer's Disease Pathology. - Pinner, Elhanan; Gruper, Yaron; Ben Zimra, Micha; Kristt, Don; Laudon, Moshe; Naor, David; Zisapel, Nava (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive deficits, deposition of amyloid-β (Aβ) plaques, intracellular neurofibrillary tangles, and neuronal cell death. Neuroinflammation is commonly believed to participate in AD pathogenesis. CD44 is an inflammation-related gene encoding a widely-distributed family of alternatively spliced cell surface glycoproteins that have been implicated in inflammation, metastases, and inflammation-linked neuronal injuries. Here we investigated the expression patterns of CD44S (which does not contain any alternative exon) and CD44 splice variants in postmortem hippocampal samples from AD patients and matched non-AD controls. The expression of CD44S and CD44 splice variants CD44V3, CD44V6, and CD44V10 was significantly higher in AD patients compared to non-AD controls. Immunohistochemistry of human hippocampal sections revealed that CD44S differentially localized to neuritic plaques and astrocytes, whereas CD44V3, CD44V6, and CD44V10 expression was mostly neuronal. Consistent with these findings, we found that the expression of CD44V6 and CD44V10 was induced by Aβ peptide in neuroblastoma cells and primary neurons. Furthermore, in loss of function studies we found that both CD44V10-specific siRNA and CD44V10 antibody protected neuronal cells from Aβ-induced toxicity, suggesting a causal relationship between CD44V10 and neuronal cell death. These data indicate that certain CD44 splice variants contribute to AD pathology and that CD44V10 inhibition may serve as a new neuroprotective treatment strategy for this disease.

Central Olfactory Dysfunction in Alzheimer's Disease and Mild Cognitive Impairment: A Functional MRI Study. - Vasavada, Megha M; Martinez, Brittany; Wang, Jianli; Eslinger, Paul J; Gill, David J; Sun, Xiaoyu; Karunanayaka, Prasanna; Yang, Qing X (J Alzheimers Dis, 2017)
BACKGROUND: Olfactory deficits are present in early Alzheimer's disease (AD) and mild cognitively impaired (MCI) patients. However, whether these deficits are due to dysfunction of the central or peripheral olfactory nervous system remains uncertain. This question is fundamentally important for developing imaging biomarkers for AD using olfactory testing. OBJECTIVE: This study sought to use olfactory functional magnetic resonance imaging (fMRI) to further demonstrate the involvement of the central olfactory system in olfactory deficits in MCI and AD. METHODS: We investigated the central olfactory system in 27 cognitively normal controls (CN), 21 MCI, and 15 AD subjects using olfactory fMRI with an odor-visual association paradigm during which a visual cue was paired with lavender odorant (odor condition) or odorless air (no-odor condition). RESULTS: The CN subjects had significantly greater activated volume in the primary olfactory cortex during both the odor and no-odor conditions compared to either the MCI or AD groups (p < 0.05). No significant differences were observed between the odor and no-odor conditions within each group. No-odor condition activation in AD and MCI correlated with the cognitive and olfactory assessments. CONCLUSION: The no-odor condition, allowing investigation of activation patterns when the peripheral olfactory system was not directly involved, elicited the same functional response as the odor condition for each of the three groups. Thus, the olfactory activation deficits present in AD and MCI patients are most likely caused by degeneration of the central olfactory nervous system.

Central Review of Amyloid-Related Imaging Abnormalities in Two Phase III Clinical Trials of Bapineuzumab in Mild-To-Moderate Alzheimer's Disease Patients. - Ketter, Nzeera; Brashear, H Robert; Bogert, Jennifer; Di, Jianing; Miaux, Yves; Gass, Achim; Purcell, Derk D; Barkhof, Frederik; Arrighi, H Michael (J Alzheimers Dis, 2017)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) consist of ARIA-E (with effusion or edema) and ARIA-H (hemosiderin deposits [HDs]). OBJECTIVES: To address accurate ascertainment of ARIA identification, a final magnetic resonance imaging (MRI) reading was performed on patients with mild-to-moderate Alzheimer's disease randomized to bapineuzumab IV or placebo during two Phase III trials (APOE ɛ4 allele carriers or noncarriers). METHODS: Final MRI central review consisted of a systematic sequential locked, adjudicated read in 1,331 APOE ɛ4 noncarriers and 1,121 carriers by independent neuroradiologists. Assessment of ARIA-E, ARIA-H, intracerebral hemorrhages, and age-related white matter changes is described. RESULTS: In the Final Read, treatment-emergent ARIA-E were identified in 242 patients including 76 additional cases not noted previously in real time. Overall, incidence proportion of ARIA-E was higher in carriers (active 21.2%; placebo 1.1%) than in noncarriers (pooled active 11.3%; placebo 0.6%), and was more often identified in homozygote APOE ɛ4 carriers than heterozygotes (34.5% versus 16.9%). Incidence rate of ARIA-E increased with increased dose in noncarriers. Frequency of ARIA-E first episodes was highest after the first and second bapineuzumab infusion and declined after repeated infusions. Incidence of total HDs <10 mm (cerebral microhemorrhages) was higher in active groups versus placebo. CONCLUSION: ARIA was detected more often on MRI scans when every scan was reviewed by trained neuroradiologists and results adjudicated. There was increased incidence of ARIA-E in bapineuzumab-treated carriers who had a microhemorrhage at baseline. ARIA-E was a risk factor for incident ARIA-H and late onset ARIA-E was milder radiologically. Age-related white matter changes did not progress during the study.

Cerebral Amyloid Angiopathy-Related Microbleeds and Cerebrospinal Fluid Biomarkers in Alzheimer's Disease. - Noguchi-Shinohara, Moeko; Komatsu, Junji; Samuraki, Miharu; Matsunari, Ichiro; Ikeda, Tokuhei; Sakai, Kenji; Hamaguchi, Tsuyoshi; Ono, Kenjiro; Nakamura, Hiroyuki; Yamada, Masahito (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) commonly accompanies cerebral amyloid angiopathy (CAA). OBJECTIVE: We aimed to reveal associations between CAA-related brain microbleeds and cerebrospinal fluid (CSF) markers in AD patients. METHODS: Patients with probable AD (n = 88) from consecutive patients in our memory clinic were evaluated for patient demographics, vascular risk factors, neuropsychological tests, apolipoprotein E phenotype, MRI including T2*-weighted image and fluid attenuated inversion recovery sequence, and CSF amyloid and tau markers. RESULTS: The 88 patients with AD included 15 with microbleeds only in cortical/subcortical regions (cortical microbleeds) that could be CAA-related, 16 with microbleeds only in deep locations (deep microbleeds), 3 with microbleeds in both cortical and deep locations (mixed microbleeds), and 54 without microbleeds. The CSF levels of amyloid β-protein 1-40 (Aβ40) and amyloid β-protein 1-42 (Aβ42) were significantly lower in patients with cortical microbleeds than in those without microbleeds (p = 0.001 and p = 0.027, respectively). The result remained unchanged after adjustment for age, sex, apolipoprotein E E4 presence, and leukoaraiosis. CONCLUSIONS: CAA-related cortical microbleeds would be associated with lower CSF levels of Aβ40 and Aβ42 in AD, reflecting the deposition of both Aβ40 and Aβ42 in the cerebrovasculature.

Cerebral Oxidative Stress and Microvasculature Defects in TNF-α Expressing Transgenic and Porphyromonas gingivalis-Infected ApoE-/- Mice. - Rokad, Farheen; Moseley, Ryan; Hardy, Rowan S; Chukkapalli, Sasanka; Crean, StJohn; Kesavalu, Lakshmyya; Singhrao, Sim K (J Alzheimers Dis, 2017)
The polymicrobial dysbiotic subgingival biofilm microbes associated with periodontal disease appear to contribute to developing pathologies in distal body sites, including the brain. This study examined oxidative stress, in the form of increased protein carbonylation and oxidative protein damage, in the tumor necrosis factor-α (TNF-α) transgenic mouse that models inflammatory TNF-α excess during bacterial infection; and in the apolipoprotein knockout (ApoE-/-) mouse brains, following Porphyromonas gingivalis gingival monoinfection. Following 2,4-dinitrophenylhydrazine derivatization, carbonyl groups were detected in frontal lobe brain tissue lysates by immunoblotting and immunohistochemical analysis of fixed tissue sections from the frontotemporal lobe and the hippocampus. Immunoblot analysis confirmed the presence of variable carbonyl content and oxidative protein damage in all lysates, with TNF-α transgenic blots exhibiting increased protein carbonyl content, with consistently prominent bands at 25 kDa (p = 0.0001), 43 kDa, and 68 kDa, over wild-type mice. Compared to sham-infected ApoE-/- mouse blots, P. gingivalis-infected brain tissue blots demonstrated the greatest detectable protein carbonyl content overall, with numerous prominent bands at 25 kDa (p = 0.001) and 43 kDa (p = 0.0001) and an exclusive band to this group between 30-43 kDa* (p = 0.0001). In addition, marked immunostaining was detected exclusively in the microvasculature in P. gingivalis-infected hippocampal tissue sections, compared to sham-infected, wild-type, and TNF-α transgenic mice. This study revealed that the hippocampal microvascular structure of P. gingivalis-infected ApoE-/- mice possesses elevated oxidative stress levels, resulting in the associated tight junction proteins being susceptible to increased oxidative/proteolytic degradation, leading to a loss of functional integrity.

Cerebrospinal Fluid Aβ42/40 Corresponds Better than Aβ42 to Amyloid PET in Alzheimer's Disease. - Lewczuk, Piotr; Matzen, Anja; Blennow, Kaj; Parnetti, Lucilla; Molinuevo, José Luis; Eusebi, Paolo; Kornhuber, Johannes; Morris, John C; Fagan, Anne M (J Alzheimers Dis, 2017)
BACKGROUND: Decreased concentrations of amyloid-β 1-42 (Aβ42) in cerebrospinal fluid (CSF) and increased retention of Aβ tracers in the brain on positron emission tomography (PET) are considered the earliest biomarkers of Alzheimer's disease (AD). However, a proportion of cases show discrepancies between the results of the two biomarker modalities which may reflect inter-individual differences in Aβ metabolism. The CSF Aβ42/40 ratio seems to be a more accurate biomarker of clinical AD than CSF Aβ42 alone. OBJECTIVE: We tested whether CSF Aβ42 alone or the Aβ42/40 ratio corresponds better with amyloid PET status and analyzed the distribution of cases with discordant CSF-PET results. METHODS: CSF obtained from a mixed cohort (n = 200) of cognitively normal and abnormal research participants who had undergone amyloid PET within 12 months (n = 150 PET-negative, n = 50 PET-positive according to a previously published cut-off) was assayed for Aβ42 and Aβ40 using two recently developed immunoassays. Optimal CSF cut-offs for amyloid positivity were calculated, and concordance was tested by comparison of the areas under receiver operating characteristic (ROC) curves (AUC) and McNemar's test for paired proportions. RESULTS: CSF Aβ42/40 corresponded better than Aβ42 with PET results, with a larger proportion of concordant cases (89.4% versus 74.9%, respectively, p < 0.0001) and a larger AUC (0.936 versus 0.814, respectively, p < 0.0001) associated with the ratio. For both CSF biomarkers, the percentage of CSF-abnormal/PET-normal cases was larger than that of CSF-normal/PET-abnormal cases. CONCLUSION: The CSF Aβ42/40 ratio is superior to Aβ42 alone as a marker of amyloid-positivity by PET. We hypothesize that this increase in performance reflects the ratio compensating for general between-individual variations in CSF total Aβ.

Cerebrospinal Fluid Aβ42/Aβ40 as a Means to Limiting Tube- and Storage-Dependent Pre-Analytical Variability in Clinical Setting. - Gervaise-Henry, Christelle; Watfa, Gasshan; Albuisson, Eliane; Kolodziej, Allan; Dousset, Brigitte; Olivier, Jean-Luc; Jonveaux, Thérèse Rivasseau; Malaplate-Armand, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers have recently been included in the criteria for AD diagnosis. Unfortunately, their wider use in routine and interpretation require more standardization, particularly for the pre-analytical steps. In particular, amyloid-β (Aβ)42 peptide measurement is strongly influenced by the type of collection tube and by repeated freeze/thaw cycles. OBJECTIVE: The objectives of this study were to compare, in clinical setting, the impact of collection tubes and the repetition of freeze/thaw cycles on Aβ42 and Aβ40 concentrations and consequently determine if the Aβ42/Aβ40 ratio could resolve the diagnosis difficulties related to these pre-analytical parameters. METHODS: CSF from 35 patients was collected in different polypropylene (PP) and stored at - 80°C after sampling. For CSF collected in the reference tube, three successive freeze-thaw cycles were done. Aβ42 and Aβ40 concentrations were determined in each condition in order to calculate the Aβ42/Aβ40 ratio. RESULTS: Our results showed that CSF Aβ42 and Aβ40 values were significantly different according to the type of collection tube and the number of freeze/thaw cycles. Although the calculation of the Aβ42/Aβ40 ratio eliminated the effect of PP tube-dependent variation, this was not the case for freeze-thaw cycle-associated variation. CONCLUSION: The use of Aβ42/Aβ40 ratio rather than Aβ42 alone could contribute toward pre-analytical standardization, thus allowing the general use of CSF AD biomarkers in routine practice.

Cerebrospinal Fluid Biomarkers and Clinical Progression in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment. - Wolfsgruber, Steffen; Polcher, Alexandra; Koppara, Alexander; Kleineidam, Luca; Frölich, Lutz; Peters, Oliver; Hüll, Michael; Rüther, Eckart; Wiltfang, Jens; Maier, Wolfgang; Kornhuber, Johannes; Lewczuk, Piotr; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is very limited data on the prevalence of abnormal cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) and their predictive value for clinical progression in memory clinic patients with subjective cognitive decline (SCD). OBJECTIVE: To assess the frequency of abnormal CSF biomarkers of AD and their predictive value for clinical progression in memory clinic patients with SCD in comparison to patients with mild cognitive impairment (MCI) from the same cohort. METHODS: We analyzed prospective data from memory clinic patients of the German Competence Network Dementia cohort with a baseline diagnosis of SCD (n = 82) or MCI (n = 134), distinguished by actuarial neuropsychological MCI criteria ("Jak-Bondi criteria"). Risk of clinical progression during 3-year follow-up was evaluated with Cox-Proportional-Hazard models. RESULTS: Prevalence of abnormal values in CSF markers of tau-mediated neurodegeneration (67.8% versus 46.3%) but not of amyloid deposition (40.3% versus 35.4%) was significantly higher in MCI compared to SCD. The rate of incident AD dementia (26.1% versus 12.2%) was also significantly higher in MCI. In SCD, additional 22% progressed to MCI during follow-up. Combined amyloid/tau abnormality was the strongest predictor of clinical progression in both groups. CONCLUSION: High prevalence of biomarker abnormality and clinical progression, together with the predictive value of CSF biomarkers, in memory clinic patients with SCD support the validity and usefulness of this condition as a "pre-MCI" at risk stage of AD.

Cerebrospinal Fluid Biomarkers as a Diagnostic Tool of the Underlying Pathology of Primary Progressive Aphasia. - Paraskevas, George P; Kasselimis, Dimitrios; Kourtidou, Evie; Constantinides, Vasilios; Bougea, Anastasia; Potagas, Costas; Evdokimidis, Ioannis; Kapaki, Elisabeth (J Alzheimers Dis, 2017)
BACKGROUND: Primary progressive aphasia (PPA) may present with three main clinical variants, namely nonfluent agrammatic (nfaPPA), semantic (sPPA), and logopenic (lPPA) subtypes. Frontotemporal lobar degenerations (FTLD) or Alzheimer's disease (AD) are the most common etiologies. OBJECTIVE: To study the potential of cerebrospinal fluid (CSF) biomarkers for identifying the underlying pathology in patients with PPA. METHODS: CSF levels of total tau protein (τT), amyloid-β peptide (Aβ42), and tau phosphorylated at threonine-181 (τP - 181) were measured by double sandwich, enzyme-linked immunosorbent assay (ELISA) in 43 patients with PPA, 26 patients with AD, and 17 healthy controls. RESULTS: All patients could be classified as compatible with the AD or non-AD biomarker profile, either with the three biomarkers (90.7%) or their ratios, especially the τP - 181/Aβ42 ratio (9.3%). An AD-compatible biomarker profile was present in 39.5% of all PPA patients, specifically 22.2%, 35.7%, and 75% of nfaPPA, sPPA, and lPPA, respectively. In PPA patients with a non-AD profile (presumably FTLD), two different clusters could be identified according to the τP - 181/τT ratio, possibly corresponding to the two major FTLD pathologies (tau and TDP-43). CONCLUSION: CSF biomarkers may be a valuable tool for the discrimination between PPA patients with AD and non-AD pathophysiology and possibly between FTLD patients with tau and TDP-43 pathology.

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A View of the Regulatory Science Qualification Landscape from the Coalition Against Major Diseases CSF Biomarker Team. - Arnerić, Stephen P; Batrla-Utermann, Richard; Beckett, Laurel; Bittner, Tobias; Blennow, Kaj; Carter, Leslie; Dean, Robert; Engelborghs, Sebastiaan; Genius, Just; Gordon, Mark Forrest; Hitchcock, Janice; Kaplow, June; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) drug development is burdened with the current requirement to conduct large, lengthy, and costly trials to overcome uncertainty in patient progression and effect size on treatment outcome measures. There is an urgent need for the discovery, development, and implementation of novel, objectively measured biomarkers for AD that would aid selection of the appropriate subpopulation of patients in clinical trials, and presumably, improve the likelihood of successfully evaluating innovative treatment options. Amyloid deposition and tau in the brain, which are most commonly assessed either in cerebrospinal fluid (CSF) or by molecular imaging, are consistently and widely accepted. Nonetheless, a clear gap still exists in the accurate identification of subjects that truly have the hallmarks of AD. The Coalition Against Major Diseases (CAMD), one of 12 consortia of the Critical Path Institute (C-Path), aims to streamline drug development for AD and related dementias by advancing regulatory approved drug development tools for clinical trials through precompetitive data sharing and adoption of consensus clinical data standards. This report focuses on the regulatory process for biomarker qualification, briefly comments on how it contrasts with approval or clearance of companion diagnostics, details the qualifications currently available to the field of AD, and highlights the current challenges facing the landscape of CSF biomarkers qualified as hallmarks of AD. Finally, it recommends actions to accelerate regulatory qualification of CSF biomarkers that would, in turn, improve the efficiency of AD therapeutic development.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.

Changes of Cerebrospinal Fluid Peptides due to Tauopathy. - Majerova, Petra; Barath, Peter; Michalicova, Alena; Katina, Stanislav; Novak, Michal; Kovac, Andrej (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) and progressive supranuclear palsy are two common neurodegenerative tauopathies, and the most common cause of progressive brain dementia in elderly affecting more than 35 million people. The tauopathies are characterized by abnormal deposition of microtubule associated protein tau into intracellular neurofibrillary tangles composed mainly of the hyperphosphorylated form of the protein. The diagnosis of tauopathies is based on the presence of clinical features and pathological changes. Over the last decade, there has been an intensive search for novel biochemical markers for clinical diagnosis of AD and other tauopathies. In the present study, we used transgenic rat model for tauopathy expressing human truncated tau protein (aa 151-391/4R) to analyze the cerebrospinal fluid (CSF) peptidome using liquid chromatography - matrix assisted laser desorption/ionization mass spectrometry (LC-MALDI TOF/TOF). From 345 peptides, we identified a total of 175 proteins. Among them, 17 proteins were significantly altered in the CSF of transgenic rats. The following proteins were elevated in the CSF of transgenic rats when compared to the control animals: neurofilament light and medium chain, apolipoprotein E, gamma-synuclein, chromogranin A, reticulon-4, secretogranin-2, calsyntein-1 and -3, endothelin-3, neuroendocrine protein B72A, alpha-1-macroglobulin, and augurin. Interestingly most of the identified proteins were previously linked to AD and other tauopathies, indicating the significance of transgenic animals in biomarker validation.

Cholinesterase Inhibitor Therapy in Alzheimer's Disease: The Limits and Tolerability of Irreversible CNS-Selective Acetylcholinesterase Inhibition in Primates. - Moss, Donald E; Perez, Ruth G; Kobayashi, Haruo (J Alzheimers Dis, 2017)
Irreversible acetylcholinesterase (AChE) inhibition accumulates to high levels in the central nervous system (CNS) because AChE turnover in the brain is much slower than in peripheral tissues. As expected from this CNS selectivity, the irreversible AChE inhibitor methanesulfonyl fluoride (MSF) produces significant cognitive improvement in Alzheimer's disease patients without the gastrointestinal toxicity that plagues other AChE inhibitors. However, without dose-limiting gastrointestinal toxicity, one shortcoming of the prior human studies of MSF is that the upper limits of CNS AChE inhibition that might be tolerated could not be tested. Therefore, in this study, monkeys were treated with escalating intramuscular (IM) doses of MSF that culminated with several weeks of 1.5 mg/kg dosing, more than eight times the prior human clinical dose, still without signs of toxicity. Brain biopsies showed that ∼80% AChE inhibition had been produced and that the new synthesis of cortical AChE had a half-time (t1/2) of ∼12 days. A single IM dose of 1.5 mg/kg MSF produced ∼59% inhibition in cerebrospinal fluid (CSF) AChE as measured one day later. This corresponds to a peak of ∼80% inhibition in CSF AChE at the time of the injection, recovering with a t1/2 of 2.4 days. Computational analyses suggest that MSF at clinically relevant doses could theoretically produce a steady-state AChE inhibition between 65% and 85% in the CNS. These data suggest that the full therapeutic advantage of AChE inhibition therapy can be realized without interference from dose-limiting gastrointestinal toxicity if an irreversible inhibitor is employed.
Keywords: Acetylcholinesterase; Alzheimer Disease; Animals; Brain; Cholinesterase Inhibitors; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Erythrocytes; Injections, Intramuscular; Macaca fascicularis; Male; Nootropic Agents; Time Factors

Chronic Verubecestat Treatment Suppresses Amyloid Accumulation in Advanced Aged Tg2576-AβPPswe Mice Without Inducing Microhemorrhage. - Villarreal, Stephanie; Zhao, Fuqiang; Hyde, Lynn A; Holder, Daniel; Forest, Thomas; Sondey, Marie; Chen, Xia; Sur, Cyrille; Parker, Eric M; Kennedy, Matthew E (J Alzheimers Dis, 2017)
Verubecestat is a potent BACE1 enzyme inhibitor currently being investigated in Phase III trials for the treatment of mild-to-moderate and prodromal Alzheimer's disease. Multiple anti-amyloid immunotherapies have been dose-limited by adverse amyloid related imaging abnormalities such as vasogenic edema (ARIA-E) and microhemorrhage (ARIA-H) observed in human trials and mice. Verubecestat was tested in a 12-week nonclinical study for the potential to exacerbate microhemorrhage (ARIA-H) profiles in 18-22-month-old post-plaque Tg2576-AβPPswe mice. Animals were treated with verubecestat or controls including the anti-Aβ antibody analog of bapineuzumab (3D6) as a positive control for ARIA induction. ARIA-H was measured using in-life longitudinal T2*-MRI and Prussian blue histochemistry at study end. Verubecestat reduced plasma and cerebrospinal fluid Aβ40 and Aβ42 by >90% and 62% to 68%, respectively. The ARIA-H profile of verubecestat-treated mice was not significantly different than controls. Anti-Aβ treatment significantly increased ARIA-H detected by Prussian blue staining; however, anti-Aβ antibody treatment did not impact plaque status. Verubecestat treatment significantly suppressed the accumulation of total levels of brain Aβ40 and Aβ42 and Thioflavin S positive plaque load. Stereological analysis of cortex and hippocampus plaque load similarly revealed significantly reduced area of Aβ immunoreactivity and reduced plaque number in verubecestat-treated animals compared to controls. The absence of elevated ARIA events in verubecestat-treated mice was associated with a significant reduction in the level of accumulated CNS amyloid pathology and brain Aβ peptides; effects consistent with the desired therapeutic mechanism of verubecestat in AD patients. These data will be compared with longitudinal MRI profiles from ongoing clinical trials.

Chronotropic Response and Cognitive Function in a Cohort at Risk for Alzheimer's Disease. - Law, Lena L; Schultz, Stephanie A; Boots, Elizabeth A; Einerson, Jean A; Dougherty, Ryan J; Oh, Jennifer M; Korcarz, Claudia E; Edwards, Dorothy F; Koscik, Rebecca L; Dowling, N Maritza; Gallagher, Catherine L; Bendlin, Barbara B; et al. (J Alzheimers Dis, 2017)
The objective of this study was to examine the association of chronotropic response (CR) and heart rate (HR) recovery- two indices of cardiovascular function within the context of a graded exercise test- with cognitive performance in a cognitively healthy, late-middle-aged cohort at risk for Alzheimer's disease (AD). Ninety participants (age = 63.52±5.86 years; 65.6% female) from the Wisconsin Registry for Alzheimer's Prevention participated in this study. They underwent graded exercise testing and a comprehensive neuropsychological assessment that assessed the following four cognitive domains: Immediate Memory, Verbal & Learning Memory, Working Memory, and Speed & Flexibility. Regression analyses, adjusted for age, sex, and education, were used to examine the association between CR, HR recovery, and cognition. We found significant associations between CR and cognitive performance in the domains of Immediate Memory, Verbal Learning & Memory, and Speed & Flexibility. In contrast, HR recovery was not significantly associated with cognitive function. The association between CR and cognition persisted even after controlling for HR recovery. Together, these findings indicatethat, in a cognitively normal, late-middle-aged cohort, CR is a stronger correlate of cognitive performance than HR recovery. Overall, this study reinforces the idea that cardiovascular health plays an important role in cognitive function, specifically in a cohort at risk for AD; and that interventions that promote vascular health may be a viable pathway to preventing or slowing cognitive decline due to AD.

Classification of Depression, Cognitive Disorders, and Co-Morbid Depression and Cognitive Disorders with Perfusion SPECT Neuroimaging. - Amen, Daniel G; Krishnamani, Pavitra; Meysami, Somayeh; Newberg, Andrew; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Depression and cognitive disorders (CDs) are two common co-morbid afflictions that commonly present with overlapping symptoms. OBJECTIVE: To evaluate if perfusion neuroimaging with brain SPECT can distinguish persons with depression from those with CDs or both conditions. METHODS: Inclusion criteria were DSM-IV defined depression or CDs (Alzheimer's disease, vascular dementia, dementia not otherwise specified, and amnestic disorders not otherwise specified) including persons with both (total n = 4,541; 847 CDs, 3,269 depression, 425 with both). Perfusion differences between the groups were calculated using two-sampled t-tests corrected for multiple comparisons. Diagnostic separation was determined with discriminant analysis. Feature selection revealed predictive regions in delineating depression from CDs and comorbid cases. RESULTS: Persons with CDs had lower cerebral perfusion compared to depression. In co-morbid persons, cerebral hypoperfusion was additive, with regions showing lower regional cerebral blood flow compared to either diagnosis alone. Both baseline and concentration SPECT regions yielded correct classification of 86% and leave one out cross-validation of 83%. AUC analysis for SPECT regions showed 86% accuracy, 80% sensitivity and 75% specificity. Discriminant analysis separated depression and CDs from comorbid cases with correct classification of 90.8% and cross validated accuracy of 88.6%. Area under the curve was 83% with sensitivity of 80% and specificity of 70%. Feature selection identified the most predictive regions in left hippocampus, right insula, cerebellar, and frontal lobe regions. CONCLUSION: Quantitative perfusion SPECT neuroimaging distinguishes depression from dementia and those with both co-morbidities. Perfusion brain SPECT can be utilized clinically to delineate between these two disorders.

Clinical Effectiveness and Tolerability of Electroconvulsive Therapy in Patients with Neuropsychiatric Symptoms of Dementia. - Isserles, Moshe; Daskalakis, Zafiris J; Kumar, Sanjeev; Rajji, Tarek K; Blumberger, Daniel M (J Alzheimers Dis, 2017)
BACKGROUND: Dementia frequently presents with aggression, agitation, and disorganized behavior for which current treatment is partially effective and is associated with significant adverse effects. OBJECTIVE: The aim of this study was to retrospectively assess the clinical effectiveness and tolerability of electroconvulsive therapy (ECT) in a sample of patients with neuropsychiatric symptoms of dementia (NPS) and to explore factors associated with response and with cognitive adverse effects. METHODS: We examined the clinical records of 25 patients with dementia and a pre-existing psychiatric disorder treated with ECT at an academic mental health hospital between April 1, 2010 and January 28, 2016. Twenty-nine acute ECT courses and fifteen maintenance courses were reviewed. We assessed treatment effectiveness and cognitive adverse effects as well as factors associated with response to treatment, including pre-existing psychiatric disorders, concomitant pharmacological treatment and types of dementia. RESULTS: ECT resulted in a clinically meaningful response in 72% of acute treatment courses. Cognitive adverse effects affecting functioning were reported in 7% of the acute treatment courses. Maintenance treatment was effective in sustaining the response in 87% of treatment courses with two reports of significant cognitive adverse effects. One patient fell and experienced a hip fracture a day after treatment. Use of antipsychotic or antidepressant medications, pre-existing psychiatric disorder, or gender were not associated with response. CONCLUSION: This study shows meaningful clinical effectiveness and good tolerability of ECT in patients with severe NPS of dementia. Furthermore, maintenance ECT was effective in sustaining treatment response.

Cognitive and Neuroanatomical Correlates in Early Versus Late Onset Parkinson's Disease Dementia. - Kim, Younggwang; Lee, Dongkyun; Cho, Kyoo Ho; Lee, Jae Jung; Ham, Jee Hyun; Ye, Byoung Seok; Lee, Seung-Koo; Lee, Jong-Min; Sohn, Young H; Lee, Phil Hyu (J Alzheimers Dis, 2017)
BACKGROUND: Aging is the most important risk factor of development of dementia in Parkinson's disease (PD), but there are no data on clinical and radiological heterogeneity of PD dementia (PDD) depending on age at onset. OBJECTIVES: The goal of this study was to examine whether patients with PDD are clinically and radiologically heterogeneous depending on age at onset. METHODS: A total of 116 patients with PD dementia and 121 age- and sex-matched normal controls were enrolled. The subjects were divided into early-onset (EOPDD; n = 39) and late-onset (LOPDD; n = 77) PDD with the respective age-matched control group based on a cutoff value of 70 years. The effects of diagnosis, age, and their interaction on neuropsychological tests, cortical thickness, and substantia innominata volume were assessed using analysis of covariance. RESULTS: EOPDD patients had a poorer cognitive performance on digit backward, forward span test (p = 0.011 and 0.05), and visual recognition memory function (p = 0.012) compared with LOPDD patients. Additionally, EOPDD patients exhibited cortical thinning in the left anterior cingulate gyrus and the right inferior temporal gyrus, with significantly decreased normalized substantia innominata volume (p = 0.044). CONCLUSIONS: Our data demonstrated that EOPDD patients exhibit poorer cognitive performance and more severe atrophy in the cortex and substantia innominata, implying that EOPDD may be a distinct phenotype different from LOPDD.

Cognitive Change in Rehabilitation Patients with Dementia: Prevalence and Association with Rehabilitation Success. - Dutzi, Ilona; Schwenk, Michael; Kirchner, Marietta; Bauer, Jürgen M; Hauer, Klaus (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is a frequent diagnosis in geriatric rehabilitation. Studies in patients with dementia on the development of their cognitive status during rehabilitation and its relation to functional outcomes have been scarce. OBJECTIVES: To describe the changes in cognitive status in patients with dementia during inpatient rehabilitation and to determine its association with patient characteristics and rehabilitation outcome. METHODS: Cohort study in a geriatric rehabilitation center with data collection at admission and discharge. Outcome measures were change in global and domain-related cognitive functioning and its association with activities of daily living (ADL) and discharge home. RESULTS: 154 patients (mean age 83.7 years) diagnosed with mild to moderate dementia were included. Cognitive performance significantly improved from admission to discharge for all cognitive variables tested (p < 0.001 to 0.03). Change in global cognitive functioning, executive functions, and episodic memory were positively associated with ADL recovery. Change in global cognitive functioning predicted ADL improvements (β= 0.32; p = 0.006). Only 7.8% of patients, characterized by worse ADL and motor abilities as well as higher frailty scores at admission, deteriorated in global cognitive scores. In comparison to patients with stable or improved cognition, these patients showed least improvements in ADL-scores (4.1 versus 12.5) and a trend for higher institutionalization (50% versus 26.5%). CONCLUSIONS: The findings highlight the potential of patients with dementia to recover cognitive functioning during rehabilitation. Cognitive change represents an independent rehabilitation outcome and a prognostic factor for successful rehabilitation suggesting that specific interventions are indicated to maintain and enhance cognitive functioning in these highly vulnerable patients.

Cognitive Rehabilitation in Alzheimer's Disease: A Controlled Intervention Trial. - Brueggen, Katharina; Kasper, Elisabeth; Ochmann, Sina; Pfaff, Henrike; Webel, Steffi; Schneider, Wolfgang; Teipel, Stefan (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive Rehabilitation for Alzheimer's disease (AD) is an integrative multimodal intervention. It aims to maintain autonomy and quality of life by enhancing the patients' abilities to compensate for decreased cognitive functioning. OBJECTIVE: We evaluated the feasibility of a group-based Cognitive Rehabilitation approach in mild AD dementia and assessed its effect on activities of daily living (ADL). METHODS: We included 16 patients with AD dementia in a controlled partial-randomized design. We adapted the manual-guided Cognitive Rehabilitation program (CORDIAL) to a group setting. Over the course of three months, one group received the Cognitive Rehabilitation intervention (n = 8), while the other group received a standardized Cognitive Training as an active control condition (n = 8). ADL-competence was measured as primary outcome. The secondary outcome parameters included cognitive abilities related to daily living, functional cognitive state, and non-cognitive domains, e.g., quality of life. For each scale, we assessed the interaction effect 'intervention by time', i.e., from pre-to post-intervention. RESULTS: We found no significant interaction effect of intervention by time on the primary outcome ADL-competence. The interaction effect was significant for quality of life (Cohen's d: -1.43), showing an increase in the intervention group compared with the control group. CONCLUSIONS: Our study demonstrates the feasibility of a group-based Cognitive Rehabilitation program for patients with mild AD dementia. The Cognitive Rehabilitation showed no significant effect on ADL, possibly reflecting a lack of transfer between the therapy setting and real life. However, the group setting enhanced communication skills and coping mechanisms. Effects on ADL may not have reached statistical significance due to a limited sample size. Furthermore, future studies might use an extended duration of the intervention and integrate caregivers to a greater extent to increase transfer to activities of daily living.

Cognitive Status, Gray Matter Atrophy, and Lower Orthostatic Blood Pressure in Older Adults. - O'Hare, Celia; Kenny, Rose-Anne; Aizenstein, Howard; Boudreau, Robert; Newman, Anne; Launer, Lenore; Satterfield, Suzanne; Yaffe, Kristine; Rosano, Caterina (J Alzheimers Dis, 2017)
BACKGROUND: Associations between orthostatic blood pressure and cognitive status (CS) have been described with conflicting results. OBJECTIVE: We hypothesize that long-term exposure to lower orthostatic blood pressure is related to having worse CS later in life and that atrophy of regions involved in central regulation of autonomic function mediate these associations. METHODS: Three-to-four measures of orthostatic blood pressure were obtained from 1997-2003 in a longitudinal cohort of aging, and average systolic orthostatic blood pressure response (ASOBPR) was computed as % change in systolic blood pressure from sit-to-stand measured at one minute post stand. CS was determined in 2010-2012 by clinician-adjudication (n = 240; age = 87.1±2.6; 59% women; 37% black) with a subsample also undergoing concurrent structural neuroimaging (n = 129). Gray matter volume of regions related to autonomic function was measured. Multinomial regression was used to compare ASOBPR in those who were cognitively intact versus those with a diagnosis of mild cognitive impairment or dementia, controlling for demographics, trajectories of seated blood pressure, incident cardiovascular risk/events and medications measured from 1997 to 2012. Models were repeated in the subsample with neuroimaging, before and after adjustment for regional gray matter volume. RESULTS: There was an inverse association between ASOBPR and probability of dementia diagnosis (9% lower probability for each % point higher ASOBPR: OR 0.91, CI95%  = 0.85-0.98; p = 0.01). Associations were similar in the subgroup with neuroimaging before and after adjustment for regional gray matter volume. CONCLUSION: ASOBPR may be an early marker of risk of dementia in older adults living in the community.

Cognitive Training Interventions for Patients with Alzheimer's Disease: A Systematic Review. - Kallio, Eeva-Liisa; Öhman, Hanna; Kautiainen, Hannu; Hietanen, Marja; Pitkälä, Kaisu (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive training (CT) refers to guided cognitive exercises designed to improve specific cognitive functions, as well as enhance performance in untrained cognitive tasks. Positive effects of CT on cognitive functions in healthy elderly people and persons with mild cognitive impairment have been reported, but data regarding the effects of CT in patients with dementia is unclear. OBJECTIVE: We systematically reviewed the current evidence from randomized controlled trials (RCTs) to find out if CT improves or stabilizes cognition and/or everyday functioning in patients with mild and moderate Alzheimer's disease. RESULTS: Altogether, 31 RCTs with CT as either the primary intervention or part of a broader cognitive or multi-component intervention were found. A positive effect was reported in 24 trials, mainly on global cognition and training-specific tasks, particularly when more intensive or more specific CT programs were used. Little evidence of improved everyday functioning was found. CONCLUSIONS: Despite some positive findings, the inaccurate definitions of CT, inadequate sample sizes, unclear randomization methods, incomplete datasets at follow-up and multiple testing may have inflated the results in many trials. Future high quality RCTs with appropriate classification and specification of cognitive interventions are necessary to confirm CT as an effective treatment option in Alzheimer's disease.

Co-Localization of Glia Maturation Factor with NLRP3 Inflammasome and Autophagosome Markers in Human Alzheimer's Disease Brain. - Ahmed, Mohammad Ejaz; Iyer, Shankar; Thangavel, Ramasamy; Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P; Zaheer, Smita; Zaheer, Asgar (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the presence of intracellular neurofibrillary tangles (NFTs) containing hyperphosphorylated tau, and the extracellular deposition of amyloid plaques (APs) with misfolded amyloid-β (Aβ) peptide. Glia maturation factor (GMF), a highly conserved pro-inflammatory protein, isolated and cloned in our laboratory, has been shown to activate glial cells leading to neuroinflammation and neurodegeneration in AD. We hypothesized that inflammatory reactions promoted by NLRP3-Caspase-1inflammasome pathway trigger dysfunction in autophagy and accumulation of Aβ which is amplified and regulated by GMF in AD. In this study, using immunohistochemical techniques we analyzed components of the NLRP3 inflammasome and autophagy- lysosomal markers in relation to Aβ, p-tau and GMF in human postmortem AD and age-matched non-AD brains. Tissue sections were prepared from the temporal cortex of human postmortem brains. Here, we demonstrate an increased expression of the inflammasome components NLRP3 and Caspase-1 and the products of inflammasome activation IL-1β and IL-18 along with GMF in the temporal cortex of AD brains. These inflammasome components and the pro-inflammatory cytokines co-localized with GMF in the vicinity and periphery of the APs and NFTs. Moreover, using double immunofluorescence staining, AD brain displayed an increase in the autophagy SQSTM1/p62 and LC3 positive vesicles and the lysosomal marker LAMP1 that also co-localized with GMF, Aβ and hyperphosphorylated p-tau. Our results indicate that in AD, the neuroinflammation promoted by the NLRP3 inflammasome may be amplified and regulated by GMF, which further impairs clearance of protein aggregates mediated by the auto-phagosomal pathway.

Combination Therapy with Zonisamide and Antiparkinson Drugs for Parkinson's Disease: A Meta-Analysis. - Matsunaga, Shinji; Kishi, Taro; Iwata, Nakao (J Alzheimers Dis, 2017)
BACKGROUND: There is uncertainty about the efficacy and tolerability of zonisamide for Parkinson's disease (PD). OBJECTIVE: We performed a meta-analysis of zonisamide treatment in PD patients who received antiparkinson drugs such as levodopa. METHODS: The primary outcome measures were the Unified Parkinson's Disease Rating Scale (UPDRS) Part III scores, wearing-off time, and discontinuation rate due to all causes. Secondary outcome measures were UPDRS total and subscale scores; discontinuation rates due to adverse events, inefficacy, and death; and individual adverse events. RESULTS: Four randomized placebo-controlled trials including 1,068 PD patients were analyzed. All studies were conducted in Japan. UPDRS Part III scores were significantly lower with zonisamide than with placebo (weighted mean difference [WMD], -2.56; 95% confidence interval [CI]; -4.20 to -0.92; p = 0.002). Further, zonisamide significantly decreased the wearing-off time compared with placebo (standardized mean difference, -0.24; 95% CI, -0.39 to -0.09; p = 0.001). Discontinuation rates due to all causes were similar between the zonisamide and placebo groups (risk ratio, 1.29; 95% CI, 0.90 to 1.84; p = 0.16). While zonisamide also decreased both UPDRS Part II (off-time) and UPDRS total scores compared to placebo (UPDRS Part II [off-time] scores: WMD, -0.79; UPDRS total scores: WMD, -2.51), there were no significant differences in other secondary outcomes between the two groups. CONCLUSIONS: Our results suggested that zonisamide combination therapy was beneficial in treating motor symptoms in PD patients receiving antiparkinson drugs and was well tolerated in Japanese patients. Future studies in populations other than the Japanese are needed.

A Common Variant of IL-6R is Associated with Elevated IL-6 Pathway Activity in Alzheimer's Disease Brains. - Haddick, Patrick C G; Larson, Jessica L; Rathore, Nisha; Bhangale, Tushar R; Phung, Qui T; Srinivasan, Karpagam; Hansen, David V; Lill, Jennie R; Pericak-Vance, Margaret A; Haines, Jonathan; Farrer, Lindsay A; Kauwe, John S; et al. (J Alzheimers Dis, 2017)
The common p.D358A variant (rs2228145) in IL-6R is associated with risk for multiple diseases and with increased levels of soluble IL-6R in the periphery and central nervous system (CNS). Here, we show that the p.D358A allele leads to increased proteolysis of membrane bound IL-6R and demonstrate that IL-6R peptides with A358 are more susceptible to cleavage by ADAM10 and ADAM17. IL-6 responsive genes were identified in primary astrocytes and microglia and an IL-6 gene signature was increased in the CNS of late onset Alzheimer's disease subjects in an IL6R allele dependent manner. We conducted a screen to identify variants associated with the age of onset of Alzheimer's disease in APOE ɛ4 carriers. Across five datasets, p.D358A had a meta P = 3 ×10-4 and an odds ratio = 1.3, 95% confidence interval 1.12 -1.48. Our study suggests that a common coding region variant of the IL-6 receptor results in neuroinflammatory changes that may influence the age of onset of Alzheimer's disease in APOE ɛ4 carriers.

Comorbidity Analysis between Alzheimer's Disease and Type 2 Diabetes Mellitus (T2DM) Based on Shared Pathways and the Role of T2DM Drugs. - Karki, Reagon; Kodamullil, Alpha Tom; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
BACKGROUND: Various studies suggest a comorbid association between Alzheimer's disease (AD) and type 2 diabetes mellitus (T2DM) indicating that there could be shared underlying pathophysiological mechanisms. OBJECTIVE: This study aims to systematically model relevant knowledge at the molecular level to find a mechanistic rationale explaining the existing comorbid association between AD and T2DM. METHOD: We have used a knowledge-based modeling approach to build two network models for AD and T2DM using Biological Expression Language (BEL), which is capable of capturing and representing causal and correlative relationships at both molecular and clinical levels from various knowledge resources. RESULTS: Using comparative analysis, we have identified several putative "shared pathways". We demonstrate, at a mechanistic level, how the insulin signaling pathway is related to other significant AD pathways such as the neurotrophin signaling pathway, PI3K/AKT signaling, MTOR signaling, and MAPK signaling and how these pathways do cross-talk with each other both in AD and T2DM. In addition, we present a mechanistic hypothesis that explains both favorable and adverse effects of the anti-diabetic drug metformin in AD. CONCLUSION: The two computable models introduced here provide a powerful framework to identify plausible mechanistic links shared between AD and T2DM and thereby identify targeted pathways for new therapeutics. Our approach can also be used to provide mechanistic answers to the question of why some T2DM treatments seem to increase the risk of AD.

Comparison of Gait Parameters for Predicting Cognitive Decline: The Mayo Clinic Study of Aging. - Savica, Rodolfo; Wennberg, Alexandra M V; Hagen, Clinton; Edwards, Kelly; Roberts, Rosebud O; Hollman, John H; Knopman, David S; Boeve, Bradley F; Machulda, Mary M; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies reported that slower gait speed might predict cognitive impairment and dementing illnesses, supporting the role of gait speed as a possible subclinical marker of cognitive impairment. However, the predictive value of other gait parameters for cognitive decline is unclear. OBJECTIVE: To investigate and compare the association with, and prediction of, specific gait parameters for cognition in a population-based sample. METHODS: The analysis included 3,426 cognitively normal participants enrolled in the Mayo Clinic Study of Aging. At baseline and every 15 months (mean follow-up = 1.93 years), participants had a study coordinator evaluation, neurological examination, and a neuropsychological assessment using nine tests that covered four domains. Gait parameters were assessed with the GAITRite® instrument. General linear mixed effects models were used to compute the annualized rate of change in cognitive domain z-scores, controlling for age, sex, education, depression, comorbidities, body mass index, APOE ɛ4 allele, and visit number, and excluding individuals with a history of stroke, alcoholism, Parkinson's disease, subdural hematoma, and normal pressure hydrocephalus. RESULTS: Spatial (stride length), temporal (ambulatory time, gait speed, step count, cadence, double support time), and spatiotemporal (cadence) gait parameters, and greater intraindividual variability in stride length, swing time, and stance time were associated with a significant decline in global cognition and in specific domains including memory, executive function, visuospatial, and language. CONCLUSIONS: Spatial, temporal, and spatiotemporal measures of gait and greater variability of gait parameters were associated with and predictive of both global- and domain-specific cognitive decline.

Conscientiousness is Negatively Associated with Grey Matter Volume in Young APOE ɛ4-Carriers. - Kunz, Lukas; Reuter, Martin; Axmacher, Nikolai; Montag, Christian (J Alzheimers Dis, 2017)
The etiology of late onset Alzheimer's disease (LOAD) depends on multiple factors, among which the APOE ɛ4 allele is the most adverse genetic determinant and conscientiousness represents an influential personality trait. A potential association of both factors with brain structure in young adulthood may constitute a constellation that sets the course toward or against the subtle disease progression of LOAD that starts decades before clinical manifestation. Hence, in the present study, we examined the modulating effects of APOE ɛ4 on the relation between personality dimensions, including conscientiousness, and total grey matter volume (GMV) in young healthy adults using an a priori genotyping design. 105 participants completed an inventory assessing the Five Factor Model of Personality (NEO-FFI) and a structural MRI scan. Total GMV was estimated using both Freesurfer as well as VBM8. Across all participants, total GMV was positively associated with extraversion and negatively related to age. In APOE ɛ4-carriers- but not in APOE ɛ4-non-carriers- conscientiousness was negatively associated with total GMV. In line with the hypothesis of antagonistic pleiotropy of the APOE ɛ4 allele, this result suggests that young APOE ɛ4-carriers with increased total GMV may particularly benefit from cognitive advantages and thus have a lower need to engage in conscientious behavior. In this subset of young APOE ɛ4-carriers, the reduction in conscientiousness could then bring along adverse health behavior in the long run, potentiating the risk for LOAD. Hence, young APOE ɛ4-carriers with increased total GMV may be at a particularly high risk for LOAD.

Consecutive Analysis of BACE1 Function on Developing and Developed Neuronal Cells. - Kamikubo, Yuji; Takasugi, Nobumasa; Niisato, Kazue; Hashimoto, Yoshie; Sakurai, Takashi (J Alzheimers Dis, 2017)
The amyloid-β protein precursor (AβPP) is cleaved by a transmembrane protease termed β-site AβPP cleavage enzyme (BACE1), which is being explored as a target for therapy and prevention of Alzheimer's disease (AD). Although genetic deletion of BACE1 results in abolished amyloid pathology in AD model mice, it also results in neurodevelopmental phenotypes such as hypomyelination and synaptic loss, observed in schizophrenia and autism-like phenotype. These lines of evidence indicate that the inhibition of BACE1 causes adverse side effects during the neurodevelopmental stage. However, the effects of the inhibition of BACE1 activity on already developed neurons remain unclear. Here, we utilized hippocampal slice cultures as an ex vivo model that enabled continuous and long-term analysis for the effect of BACE1 inhibition on neuronal circuits and synapses. Temporal changes in synaptic proteins in hippocampal slices indicated acute synaptic loss, followed by synapse formation and maintenance phases. Long-term BACE1 inhibition in the neurodevelopmental stage caused the loss of synaptic proteins but failed to alter synaptic proteins in the already developed maintenance stage. These data indicate that BACE1 function on synapses is dependent on synaptic developmental stages, and our study provides a useful model to observe the long-term effect of BACE1 activity in the brain, and to evaluate adverse effects of BACE inhibitors.

Cortical Cerebral Microinfarcts on 3 Tesla MRI in Patients with Vascular Cognitive Impairment. - Ferro, Doeschka A; van Veluw, Susanne J; Koek, Huiberdina L; Exalto, Lieza G; Biessels, Geert Jan (J Alzheimers Dis, 2017)
BACKGROUND: Cerebral microinfarcts (CMIs) are small ischemic lesions that are a common neuropathological finding in patients with stroke or dementia. CMIs in the cortex can now be detected in vivo on 3 Tesla MRI. OBJECTIVE: To determine the occurrence of CMIs and associated clinical features in patients with possible vascular cognitive impairment (VCI). METHOD: 182 memory-clinic patients (mean age 71.4±10.6, 55% male) with vascular injury on brain MRI (i.e., possible VCI) underwent a standardized work-up including 3 Tesla MRI and cognitive assessment. A control group consisted of 70 cognitively normal subjects (mean age 70.6±4.7, 60% male). Cortical CMIs and other neuroimaging markers of vascular brain injury were rated according to established criteria. RESULT: Occurrence of CMIs was higher (20%) in patients compared to controls (10%). Among patients, the presence of CMIs was associated with male sex, history of stroke, infarcts, and white matter hyperintensities. CMI presence was also associated with a diagnosis of vascular dementia and reduced performance in multiple cognitive domains. CONCLUSION: CMIs on 3 Tesla MRI are common in patients with possible VCI and co-occur with imaging markers of small and large vessel disease, likely reflecting a heterogeneous etiology. CMIs are associated with worse cognitive performance, independent of other markers of vascular brain injury.

Cortical Thickness and Depressive Symptoms in Cognitively Normal Individuals: The Mayo Clinic Study of Aging. - Pink, Anna; Przybelski, Scott A; Krell-Roesch, Janina; Stokin, Gorazd B; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2017)
Altered cortical thickness has been observed in aging and various neurodegenerative disorders. Furthermore, reduced hippocampal volume has been reported in late-life depression. Even mild depressive symptoms are common in the elderly. However, little is known about the structural MRI measures of depressive symptoms in normal cognitive aging. Thus we sought to examine the association between depressive symptoms with cortical thickness and hippocampal volume as measured by brain MRI among community-dwelling participants. We conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging, involving cognitively normal participants (N = 1,507) aged≥70 years. We observed that depressive symptoms were associated with lower global cortical thickness and lower thickness in specific prefrontal and temporal cortical regions, labeled by FreeSurfer software, version 5.3. As expected, the strength of correlation was very small, given that participants were community-dwelling with only mild depressive symptoms. We did not observe associations between hippocampal volume and depressive symptoms. These findings may provide insight into the structural correlates of mild depressive symptoms in elderly participants.

Cost-Utility of Using Alzheimer's Disease Biomarkers in Cerebrospinal Fluid to Predict Progression from Mild Cognitive Impairment to Dementia. - Handels, Ron L H; Wimo, Anders; Dodel, Richard; Kramberger, Milica G; Visser, Pieter Jelle; Molinuevo, José Luis; Verhey, Frans R J; Winblad, Bengt (J Alzheimers Dis, 2017)
BACKGROUND: Diagnostic research criteria for Alzheimer's disease support the use of biomarkers in the cerebrospinal fluid (CSF) to improve the accuracy of the prognosis regarding progression to dementia for people with mild cognitive impairment (MCI). OBJECTIVE: The aim of this study was to estimate the potential incremental cost-effectiveness ratio of adding CSF biomarker testing to the standard diagnostic workup to determine the prognosis for patients with MCI. METHODS: In an early technology assessment, a mathematical simulation model was built, using available evidence on added prognostic value as well as expert opinion to estimate the incremental costs and quality-adjusted life years (QALYs) of 20,000 virtual MCI patients with (intervention strategy) and without (control strategy) relying on CSF, from a health-care sector perspective and with a 5-year time horizon. RESULTS: Adding the CSF test improved the accuracy of prognosis by 11%. This resulted in an average QALY gain of 0.046 and € 432 additional costs per patient, representing an incremental cost-effectiveness ratio of € 9,416. CONCLUSION: The results show the potential of CSF biomarkers in current practice from a health-economics perspective. This result was, however, marked by a high degree of uncertainty, and empirical research is required into the impact of a prognosis on worrying, false-positive/negative prognosis, and stigmatization.

Curcumin Ameliorates Neuroinflammation, Neurodegeneration, and Memory Deficits in p25 Transgenic Mouse Model that Bears Hallmarks of Alzheimer's Disease. - Sundaram, Jeyapriya Raja; Poore, Charlene Priscilla; Sulaimee, Noor Hazim Bin; Pareek, Tej; Cheong, Wei Fun; Wenk, Markus R; Pant, Harish C; Frautschy, Sally A; Low, Chian-Ming; Kesavapany, Sashi (J Alzheimers Dis, 2017)
Several studies have indicated that neuroinflammation is indeed associated with neurodegenerative disease pathology. However, failures of recent clinical trials of anti-inflammatory agents in neurodegenerative disorders have emphasized the need to better understand the complexity of the neuroinflammatory process in order to unravel its link with neurodegeneration. Deregulation of Cyclin-dependent kinase 5 (Cdk5) activity by production of its hyperactivator p25 is involved in the formation of tau and amyloid pathology reminiscent of Alzheimer's disease (AD). Recent studies show an association between p25/Cdk5 hyperactivation and robust neuroinflammation. In addition, we recently reported the novel link between the p25/Cdk5 hyperactivation-induced inflammatory responses and neurodegenerative changes using a transgenic mouse that overexpresses p25 (p25Tg). In this study, we aimed to understand the effects of early intervention with a potent natural anti-inflammatory agent, curcumin, on p25-mediated neuroinflammation and the progression of neurodegeneration in p25Tg mice. The results from this study showed that curcumin effectively counteracted the p25-mediated glial activation and pro-inflammatory chemokines/cytokines production in p25Tg mice. Moreover, this curcumin-mediated suppression of neuroinflammation reduced the progression of p25-induced tau/amyloid pathology and in turn ameliorated the p25-induced cognitive impairments. It is widely acknowledged that to treat AD, one must target the early-stage of pathological changes to protect neurons from irreversible damage. In line with this, our results demonstrated that early intervention of inflammation could reduce the progression of AD-like pathological outcomes. Moreover, our data provide a rationale for the potential use of curcuminoids in the treatment of inflammation associated neurodegenerative diseases.

Damage to the Frontal Aslant Tract Accounts for Visuo-Constructive Deficits in Alzheimer's Disease. - Serra, Laura; Gabrielli, Giulia Bechi; Tuzzi, Elisa; Spanò, Barbara; Giulietti, Giovanni; Failoni, Virginia; Marra, Camillo; Caltagirone, Carlo; Koch, Giacomo; Cercignani, Mara; Bozzali, Marco (J Alzheimers Dis, 2017)
The frontal aslant tract (FAT) has been described as a bundle connecting the Broca's area to the supplementary motor area (SMA) and the pre-SMA in both hemispheres. The functional properties of this tract and its role in degenerative dementia, such as Alzheimer's disease (AD), still need to be fully clarified. The aim of this study was to explore the microstructural integrity of the FAT in patients with AD and its potential relationship with cognitive functioning. Twenty-three patients with AD and 25 healthy subjects (HS) were enrolled. All subjects underwent cognitive and MRI examination. MRI, including diffusion sequences, was used for probabilistic tractography analysis. We reconstructed individual FATs bilaterally and assessed their microstructural integrity using fractional anisotropy (FA), computed as both mean tract value and voxel-wise using SPM-8. Mean FA values were then used to test for correlations with cognitive measures. Mean tract FA and voxel-wise analyses revealed that patients with AD, compared to HS, had decreased FA in the FAT bilaterally. In addition, positive associations were found between FA in the FATs and patients' performance at tests for constructional praxis and visuospatial logical reasoning. The present results reveal a bilateral damage of FAT in AD patients. The association between FATs' microscopic abnormalities and constructive abilities fits well with the knowledge of a functional involvement of SMA and pre-SMA in movement sequences when executing constructive praxis tasks. The FAT is an associative bundle critically involved in the network sub-serving constructional praxis in patients with AD.

Decrease of Amyloid-β Levels by Curcumin Derivative via Modulation of Amyloid-β Protein Precursor Trafficking. - Kotani, Rina; Urano, Yasuomi; Sugimoto, Hachiro; Noguchi, Noriko (J Alzheimers Dis, 2017)
The abnormal production and deposition of amyloid-β (Aβ) peptides is a pathologic hallmark of Alzheimer's disease. Aβ is generated from amyloid-β protein precursor (AβPP) by two sequential proteolytic cleavage steps involving β- and γ-secretases in the trans-Golgi network and endosomes. Since direct inhibition of secretase could induce undesirable side-effects due to inadvertent inhibition of unrelated secretase substrates, it is important to establish methods for inhibiting Aβ production that do not affect secretase activity. It has been suggested that curcumin may have potent anti-amyloidogenic effect. In the present study, we evaluate the effect of curcumin derivatives on Aβ production in human neuroblastoma SH-SY5Y cells and in CHO cells which stably express human AβPP (CHO-AβPP). We found that the curcumin derivative CU6 was more effective than curcumin itself in reducing Aβ secretion. We further found that in SH-SY5Y cells CU6 inhibited neither β- nor γ-secretase activity, and that increased amounts of immature forms of AβPP accumulated in the endoplasmic reticulum (ER). We also found that CU6 induced expression of the ER chaperone glucose-regulated protein 78 (GRP78), and enhanced formation of the AβPP/GRP78 complex. These results suggest that CU6 downregulates intracellular AβPP trafficking, resulting in suppression of Aβ production independently of secretase activity.

Decreased Expression of hsa-miR-4274 in Cerebrospinal Fluid of Normal Pressure Hydrocephalus Mimics with Parkinsonian Syndromes. - Jurjević, Ivana; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Nakajima, Madoka; Kondo, Akihide; Kikkawa, Mika; Kanai, Mitsuyasu; Hattori, Nobutaka; Arai, Hajime (J Alzheimers Dis, 2017)
BACKGROUND: Patients presenting with the classical idiopathic normal pressure hydrocephalus (iNPH) triad often show additional parkinsonian spectrum signs. Accurate differential diagnosis strongly influences the long-term outcome of cerebrospinal fluid (CSF) shunting. OBJECTIVE: The aim of this study was to find potential CSF microRNA (miRNA) biomarkers for NPH mimics with parkinsonian syndromes that can reliably distinguish them from iNPH patients. METHODS: Two cohorts of 81 patients (cohort 1, n = 55; cohort 2, n = 26) with possible iNPH who were treated in two centers between January 2011 and May 2014 were studied. In both cohorts, CSF samples were obtained from patients clinically diagnosed with iNPH (n = 21 and n = 10, respectively), possible iNPH with parkinsonian spectrum (PS) (n = 18, n = 10, respectively), possible iNPH with Alzheimer's disease (AD) (n = 16), and non-affected elderly individuals (NC) (n = 6). A three-step qRT-PCR analysis of the CSF samples was performed to detect miRNAs that were differentially expressed in the groups. RESULTS: The expression of hsa-miR-4274 in CSF was decreased in both cohorts of PS group patients (cohort 1: p < 0.0001, cohort 2: p < 0.0001), and was able to distinguish PS from iNPH with high accuracy (area under the curve = 0.908). The CSF concentration of hsa-miR-4274 also correlated with the specific binding ratio of ioflupane (123I) dopamine transporter scan (r = -0.494, p = 0.044). By contrast, the level of hsa-miR-4274 was significantly increased in the PS group after CSF diversion. CONCLUSION: Levels of CSF hsa-miR-4274 can differentiate PS from patients with iNPH, AD, and NC. This may be clinically useful for diagnostic purposes and predicting shunt treatment responses.

Decreased Glucose Metabolism in Medial Prefrontal Areas is Associated with Nutritional Status in Patients with Prodromal and Early Alzheimer's Disease. - Sugimoto, Taiki; Nakamura, Akinori; Kato, Takashi; Iwata, Kaori; Saji, Naoki; Arahata, Yutaka; Hattori, Hideyuki; Bundo, Masahiko; Ito, Kengo; Niida, Shumpei; Sakurai, Takashi (J Alzheimers Dis, 2017)
BACKGROUND: Weight loss is frequently observed in patients with Alzheimer's disease (AD); however, the underlying mechanisms are not well understood. OBJECTS: To clarify the associations between nutritional status and AD-related brain changes using Pittsburgh Compound-B (PiB)-PET, fluorodeoxyglucose (FDG)-PET, and structural MRI. METHODS: The subjects were 34 amyloid-β (Aβ)-positive individuals with mild cognitive impairment or early AD (prodromal/early AD), and 55 Aβ-negative cognitively normal (CN) subjects who attended the Multimodal Neuroimaging for AD Diagnosis (MULNIAD) study. Nutritional status of the subjects was assessed by body mass index and waist to height ratio (waist circumference/height). The associations between nutritional status and brain changes were examined by multiple regression analysis using statistical parametric mapping. RESULTS: In the prodromal/early AD group, nutritional status was significantly positively correlated with regional cerebral glucose metabolism (rCGM) in the medial prefrontal cortices, while different topographical associations were seen in the CN group, suggesting these changes were AD-specific. Aβ deposition and gray matter volume were not significantly associated with nutritional status. Sub-analysis in the prodromal/early AD group demonstrated that fat mass index, but not fat-free mass index, was positively correlated with rCGM in the medial prefrontal areas. CONCLUSION: This present study provides preliminary results suggesting that hypometabolism in the medial prefrontal areas is specifically associated with AD-related weight loss, and decrease in fat mass may have a key role.

Depressive Symptoms are Associated with Progression to Dementia in Patients with Amyloid-Positive Mild Cognitive Impairment. - Moon, Byungseung; Kim, Seongheon; Park, Young Ho; Lim, Jae-Sung; Youn, Young Chul; Kim, SangYun; Jang, Jae-Won (J Alzheimers Dis, 2017)
BACKGROUND: Depressive symptoms are prevalent in patients with mild cognitive impairment (MCI) and are considered to be a risk factor for progression to dementia. OBJECTIVE: The purpose of this study was to evaluate whether depressive symptoms in MCI promote disease progression in a manner related to amyloid status, and to determine the relationship between depressive symptoms and longitudinal cerebral structural changes. METHODS: Baseline data for 336 patients with MCI (75 with depression and 261 without) from the Alzheimer's Disease Neuroimaging Initiative study were analyzed. All participants underwent comprehensive cognitive testing, volumetric magnetic resonance imaging (MRI), and [18F]AV45 positron emission tomography amyloid imaging. Depressive symptoms were measured using the Neuropsychiatric Inventory Questionnaire. A voxel-based morphometric analysis using volumetric brain MRI data was used to compare longitudinal structural changes related to depressive symptoms. RESULTS: The conversion rate to dementia was different between patients with and without depression in amyloid-positive MCI (40.8% versus 19.7%, respectively; p = 0.006). Patients who were amyloid-positive at baseline also exhibited a greater degree of 2-year cognitive decline. Depression in amyloid-positive MCI was associated with longitudinal cortical atrophy in the left cingulate gyrus. CONCLUSION: Our study indicates that the presence of depressive symptoms in patients with amyloid-positive MCI is associated with higher progression to dementia and longitudinal cortical atrophy.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of a Late-Life Dementia Prediction Index with Supervised Machine Learning in the Population-Based CAIDE Study. - Pekkala, Timo; Hall, Anette; Lötjönen, Jyrki; Mattila, Jussi; Soininen, Hilkka; Ngandu, Tiia; Laatikainen, Tiina; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: This study aimed to develop a late-life dementia prediction model using a novel validated supervised machine learning method, the Disease State Index (DSI), in the Finnish population-based CAIDE study. METHODS: The CAIDE study was based on previous population-based midlife surveys. CAIDE participants were re-examined twice in late-life, and the first late-life re-examination was used as baseline for the present study. The main study population included 709 cognitively normal subjects at first re-examination who returned to the second re-examination up to 10 years later (incident dementia n = 39). An extended population (n = 1009, incident dementia 151) included non-participants/non-survivors (national registers data). DSI was used to develop a dementia index based on first re-examination assessments. Performance in predicting dementia was assessed as area under the ROC curve (AUC). RESULTS: AUCs for DSI were 0.79 and 0.75 for main and extended populations. Included predictors were cognition, vascular factors, age, subjective memory complaints, and APOE genotype. CONCLUSION: The supervised machine learning method performed well in identifying comprehensive profiles for predicting dementia development up to 10 years later. DSI could thus be useful for identifying individuals who are most at risk and may benefit from dementia prevention interventions.

Discovery and Confirmation of Diagnostic Serum Lipid Biomarkers for Alzheimer's Disease Using Direct Infusion Mass Spectrometry. - Anand, Swati; Barnes, Justin M; Young, Sydney A; Garcia, Diana M; Tolley, H Dennis; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder lacking early biochemical diagnosis and treatment. Lipids have been implicated in neurodegenerative disorders including AD. A shotgun lipidomic approach was undertaken to determine if lipid biomarkers exist that can discriminate AD cases from controls. The discovery study involved sera from 29 different stage AD cases and 32 controls. Lipid extraction was performed using organic solvent and the samples were directly infused into a time-of-flight mass spectrometer. Differences between AD cases and controls were detected with 87 statistically significant lipid candidate markers found. These potential lipid markers were reevaluated in a second confirmatory study involving 27 cases and 30 controls. Of the 87 candidates from the first study, 35 continued to be statistically significant in the second confirmatory set. Tandem MS studies were performed and almost all confirmed markers were characterized and classified. Using a Bayesian lasso probit regression model on the confirmed markers, a multi-marker set with AUC = 0.886 was developed comparing all stages of AD with controls. Additionally, using confirmed biomarkers, multi-marker sets with AUCs >0.90 were developed for each specific AD Clinical Dementia Rating versus controls, including the earliest stage of AD. More conservative and likely more realistic statistical analyses still found multi-marker sets that appeared useful in diagnosing AD. Finally, using ordinal modeling a set of markers was developed that staged AD accurately 70% of the time, p = 0.0079. These results suggest that these serum lipidomic biomarkers may help diagnose and perhaps even stage AD.

Dissociable Effects of Aging and Mild Cognitive Impairment on Bottom-Up Audiovisual Integration. - Festa, Elena K; Katz, Andrew P; Ott, Brian R; Tremont, Geoffrey; Heindel, William C (J Alzheimers Dis, 2017)
Effective audiovisual sensory integration involves dynamic changes in functional connectivity between superior temporal sulcus and primary sensory areas. This study examined whether disrupted connectivity in early Alzheimer's disease (AD) produces impaired audiovisual integration under conditions requiring greater corticocortical interactions. Audiovisual speech integration was examined in healthy young adult controls (YC), healthy elderly controls (EC), and patients with amnestic mild cognitive impairment (MCI) using McGurk-type stimuli (providing either congruent or incongruent audiovisual speech information) under conditions differing in the strength of bottom-up support and the degree of top-down lexical asymmetry. All groups accurately identified auditory speech under congruent audiovisual conditions, and displayed high levels of visual bias under strong bottom-up incongruent conditions. Under weak bottom-up incongruent conditions, however, EC and amnestic MCI groups displayed opposite patterns of performance, with enhanced visual bias in the EC group and reduced visual bias in the MCI group relative to the YC group. Moreover, there was no overlap between the EC and MCI groups in individual visual bias scores reflecting the change in audiovisual integration from the strong to the weak stimulus conditions. Top-down lexicality influences on visual biasing were observed only in the MCI patients under weaker bottom-up conditions. Results support a deficit in bottom-up audiovisual integration in early AD attributable to disruptions in corticocortical connectivity. Given that this deficit is not simply an exacerbation of changes associated with healthy aging, tests of audiovisual speech integration may serve as sensitive and specific markers of the earliest cognitive change associated with AD.

Does Functional Connectivity Provide a Marker for Cognitive Rehabilitation Effects in Alzheimer's Disease? An Interventional Study. - Ochmann, Sina; Dyrba, Martin; Grothe, Michel J; Kasper, Elisabeth; Webel, Steffi; Hauenstein, Karlheinz; Teipel, Stefan J (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive rehabilitation (CR) is a cognitive intervention for patients with Alzheimer's disease (AD) that aims to maintain everyday competences. The analysis of functional connectivity (FC) in resting-state functional MRI has been used to investigate the effects of cognitive interventions. OBJECTIVES: We evaluated the effect of CR on the default mode network FC in a group of patients with mild AD, compared to an active control group. METHODS: We performed a three-month interventional study including 16 patients with a diagnosis of AD. The intervention group (IG) consisted of eight patients, performing twelve sessions of CR. The active control group (CG) performed a standardized cognitive training. We used a seed region placed in the posterior cingulate cortex (PCC) for FC analysis, comparing scans acquired before and after the intervention. Effects were thresholded at a significance of p < 0.001 (uncorrected) and a minimal cluster size of 50 voxels. RESULTS: The interaction of group by time showed a higher increase of PCC connectivity in IG compared to CG in the bilateral cerebellar cortex. CG revealed widespread, smaller clusters of higher FC increase compared with IG. Across all participants, an increase in quality of life was associated with connectivity increase over time in the bilateral precuneus. CONCLUSIONS: CR showed an effect on the FC of the DMN in the IG. These effects need further study in larger samples to confirm if FC analysis may suit as a surrogate marker for the effect of cognitive interventions in AD.

Down Syndrome, Partial Trisomy 21, and Absence of Alzheimer's Disease: The Role of APP. - Doran, Eric; Keator, David; Head, Elizabeth; Phelan, Michael J; Kim, Ron; Totoiu, Minodora; Barrio, Jorge R; Small, Gary W; Potkin, Steven G; Lott, Ira T (J Alzheimers Dis, 2017)
Overexpression of the amyloid precursor protein (APP) gene on chromosome 21 in Down syndrome (DS) has been linked to increased brain amyloid levels and early-onset Alzheimer's disease (AD). An elderly man with phenotypic DS and partial trisomy of chromosome 21 (PT21) lacked triplication of APP affording an opportunity to study the role of this gene in the pathogenesis of dementia. Multidisciplinary studies between ages 66-72 years comprised neuropsychological testing, independent neurological exams, amyloid PET imaging with 11C-Pittsburgh compound-B (PiB), plasma amyloid-β (Aβ) measurements, and a brain autopsy examination. The clinical phenotype was typical for DS and his intellectual disability was mild in severity. His serial neuropsychological test scores showed less than a 3% decline as compared to high functioning individuals with DS who developed dementia wherein the scores declined 17-28% per year. No dementia was detected on neurological examinations. On both PiB-PET scans, the patient with PT21 had lower PiB standard uptake values than controls with typical DS or sporadic AD. Plasma Aβ42 was lower than values for demented or non-demented adults with DS. Neuropathological findings showed only a single neuritic plaque and neurofibrillary degeneration consistent with normal aging but not AD. Taken together the findings in this rare patient with PT21 confirm the obligatory role of APP in the clinical, biochemical, and neuropathological findings of AD in DS.

Effect of APOE ε4 Genotype on Metabolic Biomarkers in Aging and Alzheimer's Disease. - Morris K, Jill; Uy, Roxanne Adeline Z; Vidoni, Eric D; Wilkins, Heather M; Archer, Ashley E; Thyfault, John P; Miles, John M; Burns, Jeffrey M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) may have heterogeneous pathophysiological underpinnings, with risk factors including apolipoprotein rmvarep4 (APOE4) genotype and insulin resistance. We hypothesized that distinct phenotypes exist within AD. We examined APOE4 and metabolic biomarkers in 338 subjects (n = 213 nondemented (ND), n = 125 AD). We further characterized steady state free fatty acid (FFA) levels in a subset of 45 participants who had also participated in a hyperinsulinemic-euglycemic clamp. Insulin resistance (HOMA-IR) was elevated in AD versus ND (p = 0.04) and in APOE4 noncarriers versus carriers (p < 0.01). This was driven by increased fasting insulin in AD versus ND (p < 0.01) and in APOE4 non-carriers versus carriers (p = 0.01). Fasting glucose was not different. In subjects who underwent a clamp, there was a group x genotype interaction on FFA levels during hyperinsulinemia (p = 0.03). APOE4 non-carriers with AD had higher FFA levels, while APOE4 carriers with AD exhibited lower FFA levels. Metabolic dysfunction is overrepresented in individuals with AD dementia who do not carry the APOE4 allele. This suggests that important subsets of AD phenotypes may exist that diverge metabolically.

The Effect of Escitalopram on Mood and Cognition in Depressive Alzheimer's Disease Subjects. - An, Hoyoung; Choi, Booyeol; Park, Kun-Woo; Kim, Do-Hoon; Yang, Dong-Won; Hong, Chang Hyung; Kim, Seong Yoon; Han, Seol-Heui (J Alzheimers Dis, 2017)
BACKGROUND: Effective treatments to alleviate depression in Alzheimer's disease (AD) have been scarce. OBJECTIVE: To investigate the efficacy and tolerability of escitalopram in the treatment of depression in AD. METHODS: In this 12-week randomized, double-blind, placebo-controlled trial with open-label, 12-week extension, AD subjects over 50 years of age, with depression defined by Olin's provisional diagnostic criteria, were enrolled. The Cornell Scale for Depression in Dementia (CSDD), and other measures of depression and cognition were repeated. RESULTS: 91 subjects were screened, and 84 were randomized into either the study group or placebo group (n = 42 for both groups). Twenty-four subjects (29%) were unable to finish the study, yielding a per protocol population of 60 subjects (study group: n = 27; placebo group: n = 33). At week 12, differences in measures of depression and cognition between the two groups were not statistically significant. However, exploratory analysis suggested that further research on a subset of subjects with 'definite major depression' (baseline CSDD score ≥18) is needed. The number of treatment-related adverse-events (AE) did not differ between groups (p = 0.83) and no serious treatment-related AE were observed. CONCLUSION: The use of escitalopram was well tolerated in depressive dementia patients. Future studies focusing on subjects with more severe levels of depression, and with more statistical power, will be needed.

The Effect of Traumatic Brain Injury History with Loss of Consciousness on Rate of Cognitive Decline Among Older Adults with Normal Cognition and Alzheimer's Disease Dementia. - Tripodis, Yorghos; Alosco, Michael L; Zirogiannis, Nikolaos; Gavett, Brandon E; Chaisson, Christine; Martin, Brett; McClean, Michael D; Mez, Jesse; Kowall, Neil; Stern, Robert A (J Alzheimers Dis, 2017)
Traumatic brain injury (TBI) is thought to be a risk factor for dementia, including dementia due to Alzheimer's disease (AD). However, the influence of TBI history on the neuropsychological course of AD is unknown and, more broadly, the effect of TBI history on age-related cognitive change is poorly understood. We examined the relationship between history of TBI with loss of consciousness (LOC) history and cognitive change in participants with normal cognition and probable AD, stratified by APOEɛ4 allele status. The sample included 706 participants (432 with normal cognition; 274 probable AD) from the National Alzheimer's Coordinating Center (NACC) dataset that completed the Uniform Data Set evaluation between 2005 and 2014. Normal and probable AD participants with a history of TBI were matched to an equal number of demographically and clinically similar participants without a TBI history. In this dataset, TBI with LOC was defined as brain trauma with brief or extended unconsciousness. For the normal and probable AD cohorts, there was an average of 3.2±1.9 and 1.8±1.1 years of follow-up, respectively. 30.8% of the normal cohort were APOEɛ4 carriers, whereas 70.8% of probable AD participants were carriers. Mixed effects regressions showed TBI with LOC history did not affect rates of cognitive change in APOEɛ4 carriers and non-carriers. Findings from this study suggest that TBI with LOC may not alter the course of cognitive function in older adults with and without probable AD. Future studies that better characterize TBI (e.g., severity, number of TBIs, history of subconconcussive exposure) are needed to clarify the association between TBI and long-term neurocognitive outcomes.

Effects of a DJ-1-Binding Compound on Spatial Learning and Memory Impairment in a Mouse Model of Alzheimer's Disease. - Kitamura, Yoshihisa; Inden, Masatoshi; Kimoto, Yasuto; Takata, Kazuyuki; Yanagisawa, Daijiro; Hijioka, Masanori; Ashihara, Eishi; Tooyama, Ikuo; Shimohama, Shun; Ariga, Hiroyoshi (J Alzheimers Dis, 2017)
Previously, DJ-1 modulator UCP0054278/comp-B was identified by virtual screening, where comp-B interacts with DJ-1 to produce antioxidant and neuroprotective responses in Parkinson's disease models. However, the effect of comp-B in an in vivo Alzheimer's disease (AD) model is yet undetermined. Thus, we examined the effect of comp-B on spatial learning, memory, and amyloid-β (Aβ) clearance in a transgenic mouse model of AD. We found that comp-B resolved the cognitive deficits, reduced insoluble Aβ42 levels, and prevented the degeneration of synaptic functions, thereby suggesting that comp-B may become a major compound for AD treatment.

The Effects of Cortical Hypometabolism and Hippocampal Atrophy on Clinical Trajectories in Mild Cognitive Impairment with Suspected Non-Alzheimer's Pathology: A Brief Report. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Shinagawa, Shunichiro; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Patel, Raihaan; Chakravarty, M Mallar; Strafella, Antonio; et al. (J Alzheimers Dis, 2017)
The clinical and structural trajectories of suspected non-Alzheimer' pathology (SNAP) remain elusive due to its heterogeneous etiology. Baseline and longitudinal clinical (global cognition, daily functioning, symptoms of dementia, and learning memory) and hippocampal volume trajectories over two years were compared between patients with amnestic mild cognitive impairment (aMCI) with SNAP with reduced hippocampal volumes (SNAP+HIPPO) and aMCI patients with SNAP without reduced hippocampal volumes. SNAP+HIPPO showed overall worse baseline cognitive functions. Longitudinally, SNAP+HIPPO showed faster deterioration of clinical symptoms of dementia. Having both hippocampal atrophy and cortical hypometabolism without amyloid pathology may exacerbate symptoms of dementia in aMCI.

Effects of Tooth Loss and the Apolipoprotein E ɛ4 Allele on Mild Memory Impairment in the Fujiwara-kyo Study of Japan: A Nested Case-Control Study. - Okamoto, Nozomi; Morikawa, Masayuki; Amano, Nobuko; Yanagi, Motokazu; Takasawa, Shin; Kurumatani, Norio (J Alzheimers Dis, 2017)
BACKGROUND: Several studies have suggested that periodontal disease can exacerbate the pro-inflammatory status of the brain. Tooth loss is one of the alternative evaluation indices of periodontal disease. There are few data on the relationship between tooth loss and memory impairment, depending on the apolipoprotein E (APOE) ɛ4 genotype. OBJECTIVE: To determine if tooth loss is associated with mild memory impairment (MMI) and if this association is modified by the presence of the APOEɛ4 allele. METHODS: A nested case-control study was conducted from 2007 to 2012 in Japan. Five hundred and thirty-seven Japanese subjects aged 65 years and over who were cognitively intact at baseline were analyzed. MMI at follow-up was evaluated. RESULTS: The median number of teeth at baseline was significantly lower in MMI participants (n = 179) than in controls (n = 358) (MMI: median 21.0, interquartile range 10.0-25.0 versus controls: 24.0, 14.0-27.0). After adjustment for demographics, vascular risk factors, and APOEɛ4 allele, the multivariate adjusted odds ratio (OR) of ≤8 teeth was 1.97 (95% confidence interval [CI], 1.13-3.44) compared to 25-32 teeth. Participants with both the presence of at least 1 APOEɛ4 allele and ≤8 teeth had a higher risk of MMI compared with those with neither (OR, 2.82; 95% CI, 1.15-6.91). Those with either risk factor alone did not have a higher risk of MMI. CONCLUSIONS: A lower number of teeth is related to risk of MMI. This may be primarily true for those individuals with an APOEɛ4 allele.

Elevated Epstein-Barr Virus Antibody Level is Associated with Cognitive Decline in the Korean Elderly. - Shim, Sung-Mi; Cheon, Hyo-Soon; Jo, Chulman; Koh, Young Ho; Song, Jihyun; Jeon, Jae-Pil (J Alzheimers Dis, 2017)
Chronic viral infection is implicated in cognitive decline and Alzheimer's disease (AD). Our goal was to identify biomarkers for the development of amnestic mild cognitive impairment (aMCI) from cognitively normal state. To accomplish this, we analyzed plasma IgG levels against Epstein-Barr virus (EBV) and herpes simplex virus 1 (HSV-1) in study subjects with incident aMCI (Converter) and normal cognitive function (NC Control) who did or did not convert from cognitively normal state to aMCI during the 2-year follow-up period, respectively. The Converter group exhibited elevated levels of anti-EBV IgG antibodies in the post-follow-up phase (aMCI state) compared to the pre-follow-up phase (cognitively normal state), but not the NC Control group. In contrast, the total IgG level was not significantly changed over the follow-up period. Moreover, elevated anti-EBV IgG levels were significantly associated with CDR scales and total CERAD scores in the Converter group. These results suggest that EBV infection or its related host immune response is linked to cognitive decline. Thus, an EBV antibody level may be used as a potential biomarker for assessing the risk of aMCI development, implying a role for chronic EBV infection in AD pathogenesis.

Estradiol and Cognition in the Cardiovascular Risk Factors, Aging and Dementia (CAIDE) Cohort Study. - Imtiaz, Bushra; Tolppanen, Anna Maija; Solomon, Alina; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2017)
Cardiovascular Risk factors, Aging and Dementia (CAIDE) is a Finnish population-based study. 731 cognitively normal women had self-reported hormone therapy (HT) data in 1998 as: no use, use ≤5 years, and >5 years. Information on type of HT was only available from 1995-1998 (Prescription Register). Cognition was assessed in 1998 and 2005-2008. Long-term (>5 years) HT use, especially use of estradiol alone among women having hysterectomy with bilateral oophorectomy, was associated with better episodic memory in 1998, but not in 2005-2008. Although a strong evidence for protective effect of estradiol on cognition was not observed in our study, improved global cognition among long-term users suggests that long-term postmenopausal HT may be beneficial for some cognitive domains.

Ethnic Variations in Prognosis of Patients with Dementia: A Prospective Nationwide Registry Linkage Study in The Netherlands. - Agyemang, Charles; van de Vorst, Irene E; Koek, Huiberdina L; Bots, Michiel L; Seixas, Azizi; Norredam, Marie; Ikram, Umar; Stronks, Karien; Vaartjes, Ilonca (J Alzheimers Dis, 2017)
BACKGROUND: Data on dementia prognosis among ethnic minority groups are limited in Europe. OBJECTIVE: We assessed differences in short-term (1-year) and long-term (3-year) mortality and readmission risk after a first hospitalization or first ever referral to a day clinic for dementia between ethnic minority groups and the ethnic Dutch population in the NetherlandsMethods: Nationwide prospective cohorts of first hospitalized dementia patients (N = 55,827) from January 1, 2000 to December 31, 2010 were constructed. Differences in short-term and long-term mortality and readmission risk following hospitalization or referral to the day clinic between ethnic minority groups (Surinamese, Turkish, Antilleans, Indonesians) and the ethnic Dutch population were investigated using Cox proportional hazard regression models with adjustment for age, sex, and comorbidities. RESULTS: Age-sex-adjusted short-term and long-term risks of death following a first hospitalization with dementia were comparable between the ethnic minority groups and the ethnic Dutch. Age- and sex-adjusted risk of admission was higher only in Turkish compared with ethnic Dutch (HR 1.57, 95% CI,1.08-2.29). The difference between Turkish and the Dutch attenuated and was no longer statistically significant after further adjustment for comorbidities. There were no ethnic differences in short-term and long-term risk of death, and risk of readmission among day clinic patients. CONCLUSION: Compared with Dutch patients with a comparable comorbidity rate, ethnic minority patients with dementia did not have a worse prognosis. Given the poor prognosis of dementia, timely and targeted advance care planning is essential, particularly in ethnic minority groups who are mired by cultural barriers and where uptake of advance care planning is known to be low.

Evaluation of the Reliability, Validity, and Predictive Validity of the Subscales of the Perceived Stress Scale in Older Adults. - Jiang, Julie M; Seng, Elizabeth K; Zimmerman, Molly E; Sliwinski, Martin; Kim, Mimi; Lipton, Richard B (J Alzheimers Dis, 2017)
BACKGROUND: The Perceived Stress Scale (PSS) is made up of two subscales but is typically used as a single summary measure. However, research has shown that the two subscales may have differential properties in older adults. OBJECTIVE: To evaluate the internal consistency, test-retest reliability, and the concurrent and predictive validity for development of amnestic mild cognitive impairment (aMCI) of the positively-worded (PSS-PW) and negatively-worded (PSS-NW) subscale scores of the PSS in older adults. METHODS: We recruited community residing older adults free of dementia from the Einstein Aging Study. Reliability of the PSS-PW and PSS-NW was assessed using Cronbach's alpha for internal consistency and intraclass correlation for one year test-retest reliability. Concurrent validity was evaluated by examining the relationship between the PSS subscales and depression, anxiety, neuroticism, and positive and negative affect. Predictive validity was assessed using multivariate Cox regression analyses to examine the relationship between baseline PSS-PW and PSS-NW score and subsequent onset of aMCI. RESULTS: Both PSS-PW and PSS-NW showed adequate internal consistency and retest reliabilities. Both the PSS-PW and PSS-NW were associated with depression, neuroticism, and negative affect. The PSS-NW was uniquely associated with anxiety while the PSS-PW was uniquely associated with positive affect. Only the PSS-PW was associated with a statistically significant increased risk of incident aMCI (HR = 1.27; 95% CI: 1.06-1.51 for every 5-point increase in PSS-PW). CONCLUSIONS: Evaluating the separate effects of the two PSS subscales may reveal more information than simply using a single summation score. Future research should investigate the PSS-PW and PSS-NW as separate subscales.

Exploring Erythrocytes as Blood Biomarkers for Alzheimer's Disease. - Stevenson, Anna; Lopez, Dianne; Khoo, Paul; Kalaria, Rajesh N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2017)
Peripheral biomarkers for dementia are few and far between. Despite research into blood plasma/serum biomarkers for dementia diagnostics, there is a lack of information on erythrocytes and their vast proteomes as potential biomarkers. This review identifies a number of relevant and potentially promising erythrocyte biomarkers for various subtypes of dementia. These include erythrocyte morphology, oxidative stress, and erythrocyte membrane proteins such as the glucose transporter (GLUT-1), amyloid-β, IgG, Hsp90, calpain-1, and band 3 protein. Of those proteins identified Hsp90, amyloid-β, calpain-1 and band 3 show the most promise as pre-clinical biomarkers. However, the most intriguing aspect of erythrocytes is their changed morphology in dementia. The altered morphology not only could be used as a diagnostic biomarker but may be crucial in early pathogenesis of the disease. Further work must be done to establish the pathological connection between the periphery and central disease processes.

Face-Name Associative Recognition Deficits in Subjective Cognitive Decline and Mild Cognitive Impairment. - Polcher, Alexandra; Frommann, Ingo; Koppara, Alexander; Wolfsgruber, Steffen; Jessen, Frank; Wagner, Michael (J Alzheimers Dis, 2017)
BACKGROUND: There is a need for more sensitive neuropsychological tests to detect subtle cognitive deficits emerging in the preclinical stage of Alzheimer's disease (AD). Associative memory is a cognitive function supported by the hippocampus and affected early in the process of AD. OBJECTIVE: We developed a short computerized face-name associative recognition test (FNART) and tested whether it would detect memory impairment in memory clinic patients with mild cognitive impairment (MCI) and subjective cognitive decline (SCD). METHODS: We recruited 61 elderly patients with either SCD (n = 32) or MCI (n = 29) and 28 healthy controls (HC) and compared performance on FNART, self-reported cognitive deterioration in different domains (ECog-39), and, in a reduced sample (n = 46), performance on the visual Paired Associates Learning of the CANTAB battery. RESULTS: A significant effect of group on FNART test performance in the total sample was found (p < 0.001). Planned contrasts indicated a significantly lower associative memory performance in the SCD (p = 0.001, d = 0.82) and MCI group (p < 0.001, d = 1.54), as compared to HCs, respectively. The CANTAB-PAL discriminated only between HC and MCI, possibly because of reduced statistical power. Adjusted for depression, performance on FNART was significantly related to ECog-39 Memory in SCD patients (p = 0.024) but not in MCI patients. CONCLUSIONS: Associative memory is substantially impaired in memory clinic patients with SCD and correlates specifically with memory complaints at this putative preclinical stage of AD. Further studies will need to examine the predictive validity of the FNART in SCD patients with regard to longitudinal (i.e., conversion to MCI/AD) and biomarker outcomes.

Factors Underpinning Caregiver Burden in Frontotemporal Dementia Differ in Spouses and their Children. - Kaizik, Cassandra; Caga, Jashelle; Camino, Julieta; O'Connor, Claire M; McKinnon, Colleen; Oyebode, Jan R; Piguet, Olivier; Hodges, John R; Mioshi, Eneida (J Alzheimers Dis, 2017)
The objectives of this observational study were to (1) compare spousal and child caregiver burden; (2) compare co-resident and live-out child caregiver burden; and (3) investigate factors influencing spousal and child caregiver burden. Data was collected from 90 caregivers of people with frontotemporal degeneration (FTD) recruited from the Frontotemporal Dementia Research Group (Frontier) at Neuroscience Research, Australia. Of this caregiver group, 43 were spousal caregivers and 47 were child caregivers. Caregiver burden and emotional state were evaluated using the short Zarit Burden Interview and the short version of the Depression, Anxiety and Stress Scale-21. The Social Network Index was applied to ascertain the social network of the caregiver, while the Intimate Bond Measure was used to evaluate the current quality of the relationship between the caregiver and the person with dementia. The Frontotemporal Dementia Rating Scale was used to assess severity of dementia. Spousal and child caregivers experienced similar levels of burden, depression, anxiety, and stress, regardless of disease severity. Co-resident child caregivers had smaller social networks and greater burden than live-out caregivers. Dementia severity was key in spousal caregiver burden, whereas caregiver depression was most important in child caregiver burden. Child and spousal caregivers of individuals with FTD share similar levels of burden, influenced by different factors. Future interventions need to account for these differences.

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer's Disease. - Reiter, Katherine; Nielson, Kristy A; Durgerian, Sally; Woodard, John L; Smith, J Carson; Seidenberg, Michael; Kelly, Dana A; Rao, Stephen M (J Alzheimers Dis, 2017)
Neuropathological changes associated with Alzheimer's disease (AD) precede symptom onset by more than a decade. Possession of an apolipoprotein E (APOE) ɛ4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ɛ4 carriers (ɛ4+) compared to ɛ4 non-carriers (ɛ4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ɛ4+ and ɛ4- individuals. The current five-year study examined global and regional volumes of cortical and subcortical grey and white matter and ventricular size in 42 ɛ4+ and 30 ɛ4- individuals. Cognitively intact participants, ages 65-85 at study entry, underwent repeat anatomical MRI scans on three occasions: baseline, 1.5, and 4.75 years. Results indicated no between-group volumetric differences at baseline. Over the follow-up interval, the ɛ4+ group experienced a greater rate of volume loss in total grey matter, bilateral hippocampi, right hippocampal subfields, bilateral lingual gyri, bilateral parahippocampal gyri, and right lateral orbitofrontal cortex compared to the ɛ4- group. Greater loss in grey matter volumes in ɛ4+ participants were accompanied by greater increases in lateral, third, and fourth ventricular volumes. Rate of change in white matter volumes did not differentiate the groups. The current results indicate that longitudinal measurements of brain atrophy can serve as a sensitive biomarker for identifying neuropathological changes in persons at genetic risk for AD and potentially, for assessing the efficacy of treatments designed to slow or prevent disease progression during the preclinical stage of AD.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Gender-Based Cerebral Perfusion Differences in 46,034 Functional Neuroimaging Scans. - Amen, Daniel G; Trujillo, Manuel; Keator, David; Taylor, Derek V; Willeumier, Kristen; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Studies have reported that females have widespread increases in regional cerebral blood flow, but the studies were relatively small and inconsistent. OBJECTIVE: Here we analyzed a healthy and a very large clinical psychiatric population to determine the effect of gender, using single photon emission computed tomography (SPECT). METHODS: Whole brain and region of interest (ROI) gender differences were analyzed in a total of 46,034 SPECT scans at baseline and concentration. The sample included 119 healthy subjects and 26,683 patients (60.4% male, 39.6% female); a subset of 11,587 patients had complete diagnostic information. A total of 128 regions were analyzed according to the AAL Atlas, using ROI Extract and SPSS statistical software programs, controlling for age, diagnoses, and correcting for multiple comparisons. RESULTS: Compared to males, healthy females showed significant whole brain (p < 0.01) and ROI increases in 65 baseline and 48 concentration regions (p < 0.01 corrected). Healthy males showed non-significant increases in 9 and 22 regions, respectively. In the clinical group, there were widespread significant increases in females, especially in the prefrontal and limbic regions, and specific increases in males in the inferior occipital lobes, inferior temporal lobes, and lobule 7 and Crus 2 of the cerebellum. These findings were replicated in the subset of 11,587 patients with the effect of diagnoses removed. CONCLUSIONS: Our results demonstrated significant gender differences in a healthy and clinical population. Understanding these differences is crucial in evaluating functional neuroimaging and may be useful in understanding the epidemiological gender differences among psychiatric disorders.

Gender-Specific Degeneration of Dementia-Related Subcortical Structures Throughout the Lifespan. - Nemeth, Viola Luca; Must, Anita; Horvath, Szatmar; Király, Andras; Kincses, Zsigmond Tamas; Vecsei, Laszlo (J Alzheimers Dis, 2017)
Age-related changes in brain structure are a question of interest to a broad field of research. Structural decline has been consistently, but not unambiguously, linked to functional consequences, including cognitive impairment and dementia. One of the areas considered of crucial importance throughout this process is the medial temporal lobe, and primarily the hippocampal region. Gender also has a considerable effect on volume deterioration of subcortical grey matter (GM) structures, such as the hippocampus. The influence of age×gender interaction on disproportionate GM volume changes might be mediated by hormonal effects on the brain. Hippocampal volume loss appears to become accelerated in the postmenopausal period. This decline might have significant influences on neuroplasticity in the CA1 region of the hippocampus highly vulnerable to pathological influences. Additionally, menopause has been associated with critical pathobiochemical changes involved in neurodegeneration. The micro- and macrostructural alterations and consequent functional deterioration of critical hippocampal regions might result in clinical cognitive impairment-especially if there already is a decline in the cognitive reserve capacity. Several lines of potential vulnerability factors appear to interact in the menopausal period eventually leading to cognitive decline, mild cognitive impairment, or Alzheimer's disease. This focused review aims to delineate the influence of unmodifiable risk factors of neurodegenerative processes, i.e., age and gender, on critical subcortical GM structures in the light of brain derived estrogen effects. The menopausal period appears to be of key importance for the risk of cognitive decline representing a time of special vulnerability for molecular, structural, and functional influences and offering only a narrow window for potential protective effects.

Genetic Prion Disease Caused by PRNP Q160X Mutation Presenting with an Orbitofrontal Syndrome, Cyclic Diarrhea, and Peripheral Neuropathy. - Fong, Jamie C; Rojas, Julio C; Bang, Jee; Legati, Andrea; Rankin, Katherine P; Forner, Sven; Miller, Zachary A; Karydas, Anna M; Coppola, Giovanni; Grouse, Carrie K; Ralph, Jeffrey; Miller, Bruce L; et al. (J Alzheimers Dis, 2017)
Patients with pathogenic truncating mutations in the prion gene (PRNP) usually present with prolonged disease courses with severe neurofibrillary tangle and cerebral amyloidosis pathology, but more atypical phenotypes also occur, including those with dysautonomia and peripheral neuropathy. We describe the neurological, cognitive, neuroimaging, and electrophysiological features of a 31-year-old man presenting with an orbitofrontal syndrome, gastrointestinal symptoms, and peripheral neuropathy associated with PRNP Q160X nonsense mutation, with symptom onset at age 27. The mutation was also detected in his asymptomatic father and a symptomatic paternal cousin; several members of prior generations died from early onset dementia. This is the first report of a family affected with the nonsense PRNP mutation Q160X displaying clear autosomal dominant disease in multiple family members and reduced penetrance. This case strengthens the evidence suggesting an association between PRNP truncating mutations and prion systemic amyloidosis. PRNP gene testing should be considered in any patient with atypical dementia, especially with early onset and neuropathy, even in the absence of a family history.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Hippocampal and Clinical Trajectories of Mild Cognitive Impairment with Suspected Non-Alzheimer's Disease Pathology. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Shinagawa, Shunichiro; Patel, Raihaan; Chakravarty, M Mallar; Graff-Guerrero, Ariel (J Alzheimers Dis, 2017)
Suspected non-Alzheimer's disease pathology (SNAP) characterizes individuals showing neurodegeneration (e.g., hypometabolism) without amyloid-β (Aβ). Findings from previous studies regarding clinical and structural trajectories of SNAP are inconsistent. Using data from the Alzheimer's Disease Neuroimaging Initiative, patients with amnestic mild cognitive impairment (MCI) were categorized into four groups: amyloid positive with hypometabolism (Aβ+ND+), amyloid only (Aβ+ND-), neither amyloid nor hypometabolism (Aβ-ND-), and SNAP (Aβ-ND+). Aβ+ND+(n = 33), Aβ+ND-(n = 32), and Aβ-ND-(n = 36) were matched to SNAP for age, gender, apolipoprotein E4 (apoE4) genotype, and scores on the Montreal Cognitive Assessment. Elderly controls (n = 40) were also matched to SNAP for age, gender, and apoE4 genotype. Longitudinal changes were compared across groups in terms of hippocampal volume, clinical symptoms, daily functioning, and cognitive functioning over a 2-year period. At baseline, no difference in cognition and functioning was observed between SNAP and Aβ+groups. SNAP showed worse clinical symptoms and impaired functioning at baseline compared to Aβ-ND-and controls. Two years of follow-up showed no differences in hippocampal volume changes between SNAP and any of the comparison groups. SNAP showed worse functional deterioration in comparison to Aβ-ND-and controls. However, Aβ+ND+ showed more severe changes in clinical symptoms in comparison to SNAP. Thus, patients with MCI and SNAP showed 1) more severe functional deterioration compared to Aβ-ND-and controls, 2) no differences with Aβ+ND-, and 3) less cognitive deterioration than Aβ+ND+. Future studies should investigate what causes SNAP, which is different from typical AD pathology and biomarker cascades.

Hippocampus and Basal Forebrain Volumetry for Dementia and Mild Cognitive Impairment Diagnosis: Could It Be Useful in Primary Care? - Teipel, Stefan J; Keller, Felix; Thyrian, Jochen R; Strohmaier, Urs; Altiner, Attila; Hoffmann, Wolfgang; Kilimann, Ingo (J Alzheimers Dis, 2017)
BACKGROUND: Once a patient or a knowledgeable informant has noticed decline in memory or other cognitive functions, initiation of early dementia assessment is recommended. Hippocampus and cholinergic basal forebrain (BF) volumetry supports the detection of prodromal and early stages of Alzheimer's disease (AD) dementia in highly selected patient populations. OBJECTIVE: To compare effect size and diagnostic accuracy of hippocampus and BF volumetry between patients recruited in highly specialized versus primary care and to assess the effect of white matter lesions as a proxy for cerebrovascular comorbidity on diagnostic accuracy. METHODS: We determined hippocampus and BF volumes and white matter lesion load from MRI scans of 71 participants included in a primary care intervention trial (clinicaltrials.gov identifier: NCT01401582) and matched 71 participants stemming from a memory clinic. Samples included healthy controls and people with mild cognitive impairment (MCI), AD dementia, mixed dementia, and non-AD related dementias. RESULTS: Volumetric measures reached similar effect sizes and cross-validated levels of accuracy in the primary care and the memory clinic samples for the discrimination of AD and mixed dementia cases from healthy controls. In the primary care MCI cases, volumetric measures reached only random guessing levels of accuracy. White matter lesions had only a modest effect on effect size and diagnostic accuracy. CONCLUSIONS: Hippocampus and BF volumetry may usefully be employed for the identification of AD and mixed dementia, but the detection of MCI does not benefit from the use of these volumetric markers in a primary care setting.

How Different are Quality of Life Ratings for People with Dementia Reported by Their Family Caregivers from Those Reported by the Patients Themselves? - Jacob, Louis; Han, Ji Won; Kim, Tae Hui; Park, Joon Hyuk; Lee, Seok Bum; Lee, Jung Jae; Ryu, Seung-Ho; Kim, Shin-Kyeom; Yoon, Jong Chul; Jhoo, Jin Hyeong; Kim, Jeong Lan; Kwak, Kyung Phil; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of patient quality of life (QoL) play a major role in the management of dementia. OBJECTIVE: We investigated the self-proxy discrepancy of QoL ratings in the elderly and the impact of dementia severity on the discrepancy. METHODS: QoL of 718 patients with dementia and 651 non-demented elderly were rated by themselves and their caregivers (CG) using the Quality of Life-Alzheimer's Disease (QoL-AD). The impact of the rater on the total and item scores of QoL-AD was analyzed using repeated measures ANOVA and differential response patterns between self and proxy were analyzed using differential item functioning (DIF) analysis. RESULTS: Self-rated scores were higher than CG-rated scores in all diagnostic groups. The interaction between rater and diagnostic group was significant in total QoL-AD score and 5 item scores ('memory', 'marriage', 'chores around the house', 'do things for fun', and 'life as a whole'). The strength of the DIF increased with advancing dementia in these items. CONCLUSION: Self-proxy rating discrepancy of QoL was influenced by the presence and severity of dementia only in five items.

How Does Exercise Reduce the Rate of Age-Associated Cognitive Decline? A Review of Potential Mechanisms. - Kennedy, Greg; Hardman, Roy J; Macpherson, Helen; Scholey, Andrew B; Pipingas, Andrew (J Alzheimers Dis, 2017)
The rate of age-associated cognitive decline varies considerably between individuals. It is important, both on a societal and individual level, to investigate factors that underlie these differences in order to identify those which might realistically slow cognitive decline. Physical activity is one such factor with substantial support in the literature. Regular exercise can positively influence cognitive ability, reduce the rate of cognitive aging, and even reduce the risk of Alzheimer's disease (AD) and other dementias. However, while there is substantial evidence in the extant literature for the effect of exercise on cognition, the processes that mediate this relationship are less clear. This review examines cardiovascular health, production of brain derived neurotrophic factor (BDNF), insulin sensitivity, stress, and inflammation as potential pathways, via which exercise may maintain or improve cognitive functioning, and may be particularly pertinent in the context of the aging brain. A greater understanding of these mechanisms and their potential relationships with exercise and cognition will be invaluable in providing biomarkers for investigating the efficacy of differing exercise regimes on cognitive outcomes.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Incident Cerebral Microbleeds Detected by Susceptibility Weight-Imaging Help to Identify Patients with Mild Cognitive Impairment Progressing to Alzheimer's Disease. - Basselerie, Hubert; Bracoud, Luc; Zeestraten, Eva; Bouguen, Eva; Kiyasova, Vera; Pueyo, Maria; Cognard, Christophe; Dumas, Hervé; Gramada, Raluca; Ousset, Pierre Jean; Vellas, Bruno; Bonneville, Fabrice (J Alzheimers Dis, 2017)
BACKGROUND: The relationship between cerebral microbleeds (CMB) and Alzheimer's disease (AD) has not yet been clearly determined, particularly with susceptibility weight-imaging (SWI). OBJECTIVE: To evaluate the SWI sequence using 3T MRI for the detection of CMB, and its ability to differentiate elderly control subjects (CS), stable mild cognitive impairment patients (MCI-s), MCI patients progressing to AD (MCI-p), and AD patients. METHODS: It was a prospective, monocentric, observational study that took place in Toulouse, France. Participants were 65 years and older, enrolled in three groups: CS, MCI, and AD. Based on the longitudinal analysis of cognitive decline, MCI subjects were retrospectively classified as MCI-s or MCI-p. Each patient had a 4-year follow-up with MRI at baseline (MRI#1) and during the fourth year (MRI#3). CMB were counted on native SWI images juxtaposed to minIP reformatted images. RESULTS: 150 patients were enrolled: 48 CS, 25 MCI-s, 18 MCI-p, 59 AD. At MRI#1 and at MRI#3, there was no significant difference in the prevalence of CMB between groups (p = 0.75 and p = 0.87). In the MCI-p + AD group, significantly more subjects had≥4 incident CMB compared to the CS + MCI-s group (p = 0.016). In the MCI-p + AD group, the prevalence of patients with >4 CMB was significantly higher at MRI#3 than at MRI#1 (p = 0.008). CONCLUSION: Using SWI, AD and MCI-p patients had developed significantly more new CMB than CS and MCI-s patients during the follow-up. Incident CMB might be suggested as a potential imaging marker of AD progression.

Increased Release of Apolipoprotein E in Extracellular Vesicles Following Amyloid-β Protofibril Exposure of Neuroglial Co-Cultures. - Nikitidou, Elisabeth; Khoonsari, Payam Emami; Shevchenko, Ganna; Ingelsson, Martin; Kultima, Kim; Erlandsson, Anna (J Alzheimers Dis, 2017)
Extracellular vesicles (EVs), including exosomes and larger microvesicles, have been implicated to play a role in several conditions, including Alzheimer's disease (AD). Since the EV content mirrors the intracellular environment, it could contribute with important information about ongoing pathological processes and may be a useful source for biomarkers, reflecting the disease progression. The aim of the present study was to analyze the protein content of EVs specifically released from a mixed co-culture of primary astrocytes, neurons, and oligodendrocytes treated with synthetic amyloid-β (Aβ42) protofibrils. The EV isolation was performed by ultracentrifugation and validated by transmission electron microscopy. Mass spectrometry analysis of the EV content revealed a total of 807 unique proteins, of which five displayed altered levels in Aβ42 protofibril exposed cultures. The most prominent protein was apolipoprotein E (apoE), and by western blot analysis we could confirm a threefold increase of apoE in EVs from Aβ42 protofibril exposed cells, compared to unexposed cells. Moreover, immunoprecipitation studies demonstrated that apoE was primarily situated inside the EVs, whereas immunocytochemistry indicated that the EVs most likely derived from the astrocytes and the neurons in the culture. The identified Aβ-induced sorting of apoE into EVs from cultured neuroglial cells suggests a possible role for intercellular transfer of apoE in AD pathology and encourage future studies to fully elucidate the clinical relevance of this event.

Intelligent Assistive Technology for Alzheimer's Disease and Other Dementias: A Systematic Review. - Ienca, Marcello; Fabrice, Jotterand; Elger, Bernice; Caon, Maurizio; Pappagallo, Alessandro Scoccia; Kressig, Reto W; Wangmo, Tenzin (J Alzheimers Dis, 2017)
Intelligent assistive technologies (IATs) have the potential of offering innovative solutions to mitigate the global burden of dementia and provide new tools for dementia care. While technological opportunities multiply rapidly, clinical applications are rare as the technological potential of IATs remains inadequately translated into dementia care. In this article, the authors present the results of a systematic review and the resulting comprehensive technology index of IATs with application in dementia care. Computer science, engineering, and medical databases were extensively searched and the retrieved items were systematically reviewed. For each IAT, the authors examined their technological type, application, target population, model of development, and evidence of clinical validation. The findings reveal that the IAT spectrum is expanding rapidly in volume and variety over time, and encompasses intelligent systems supporting various assistive tasks and clinical uses. At the same time, the results confirm the persistence of structural limitations to successful adoption including partial lack of clinical validation and insufficient focus on patients' needs. This index is designed to orient clinicians and relevant stakeholders involved in the implementation and management of dementia care across the current capabilities, applications, and limitations of IATs and to facilitate the translation of medical engineering research into clinical practice. In addition, a discussion of the major methodological challenges and policy implications for the successful and ethically responsible implementation of IAT into dementia care is provided.

An International Comparative Study on Driving Regulations on People with Dementia. - Kim, You Joung; An, Hoyoung; Kim, Binna; Park, Young Shin; Kim, Ki Woong (J Alzheimers Dis, 2017)
Over 40% of people with dementia drive, with a two to five times greater accident risk than controls. This has fueled public concerns about the risk of traffic accidents by drivers with dementia (DWD). We compared driving regulations on seniors and DWD between ten European and Asia-Pacific countries to identify key implications for national strategies. Moderate to severe dementia was a reason for driver's license revocation in all countries. However, regulations on mild dementia varied considerably, with most basing their decisions on severity, rather than simply the presence of dementia. Most used validated assessments, but responsibility for triggering the administrative process fell on drivers in some countries and on physicians in others. Administrations should consider the following when developing driving policies: 1) ideal regulations on DWD should ensure that restrictions are implemented only when needed; 2) fitness to drive should be assessed using validated instruments; 3) the use of processes that automatically initiate driving competency examinations following a diagnosis of dementia should be explored; and 4) restrictions should be delicately tailored to a range of driving competence levels, and assistive incentives compensating for lost driving privileges should be provided.

Intracerebroventricular Streptozotocin Induces Obesity and Dementia in Lewis Rats. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Koroukhov, Nickolay; Taler, Michal; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2017)
BACKGROUND: Animal models of dementia associated with metabolic abnormalities play an important role in understanding the bidirectional relationships between these pathologies. Rodent strains develop cognitive dysfunctions without alteration of peripheral metabolism following intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to estimate the effect of icv-STZ on cognitive functions and peripheral metabolism in Lewis rats, which are rarely used for the induction of cognitive abnormalities. METHODS: Inbred adult Lewis rats were treated with single icv-STZ (3 mg/kg). Cognitive functions were assessed using Morris water maze (MWM) test and locomotion by the Open Field test. Metabolic alterations were studied using histological and biochemical analysis of brain and peripheral tissues. RESULTS: The icv-STZ induced rapid weight decline during the first two weeks. Thereafter, the rats showed an accelerated weight gain. Three months after the icv-STZ treatment, the rats were severely obese and revealed fatty liver, pancreatic islet hypertrophy, significantly elevated levels of blood insulin, leptin, and adiponectin, but intact peripheral glucose homeostasis. The icv-STZ rats expressed amyloid-β deposits in blood vessels of leptomeningeal area, microgliosis, astrogliosis, and spongiosis in fimbria-fornix area of hippocampus. Locomotor activities of icv-STZ treated and sham-operated rats were similar. In the MWM test, the icv-STZ treated rats demonstrated severely impaired spatial learning during both acquisition and reversal phases. CONCLUSIONS: Icv-STZ treated Lewis rats develop severe dementia associated with obesity and peripheral metabolic abnormalities. This animal model may be useful for exploring the pathophysiological relationship between obesity and dementia and provides a new tool for development of effective therapy.

Intrahippocampal Pathways Involved in Learning/Memory Mechanisms are Affected by Intracerebral Infusions of Amyloid-β25-35 Peptide and Hydrated Fullerene C60 in Rats. - Gordon, Rita; Podolski, Igor; Makarova, Ekaterina; Deev, Alexander; Mugantseva, Ekaterina; Khutsyan, Sergey; Sengpiel, Frank; Murashev, Arkady; Vorobyov, Vasily (J Alzheimers Dis, 2017)
Primary memory impairments associated with increased level of amyloid-β (Aβ) in the brain have been shown to be linked, partially, with early pathological changes in the entorhinal cortex (EC) which spread on the whole limbic system. While the hippocampus is known to play a key role in learning and memory mechanisms, it is as yet unclear how its structures are involved in the EC pathology. In this study, changes in memory and neuronal morphology in male Wistar rats intrahippocampally injected with Aβ25-35 were correlated on days 14 and 45 after the injection to reveal specific cognitive-structural associations. The main focus was on the dentate gyrus (DG) and hippocampal areas of CA1 and CA3 because of their involvement in afferent flows from EC to the hippocampus through tri-synaptic (EC → DG → CA3 → CA1) and/or mono-synaptic (EC → CA1) pathways. Evident memory impairments were observed at both time points after Aβ25-35 injection. However, on day 14, populations of morphological intact neurons were decreased in CA3 and, drastically, in CA1, and the DG supramedial bundle was significantly damaged. On day 45, this bundle largely and CA1 neurons partially recovered, whereas CA3 neurons remained damaged. We suggest that Aβ25-35 primarily affects the tri-synaptic pathway, destroying the granular cells in the DG supramedial area and neurons in CA3 and, through the Schaffer collaterals, in CA1. Intrahippocampal pretreatment with hydrated fullerene C60 allows the neurons and their connections to survive the amyloidosis, thus supporting the memory mechanisms.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

Left Frontal Hub Connectivity during Memory Performance Supports Reserve in Aging and Mild Cognitive Impairment. - Franzmeier, Nicolai; Hartmann, Julia C; Taylor, Alexander N W; Araque Caballero, Miguel Á; Simon-Vermot, Lee; Buerger, Katharina; Kambeitz-Ilankovic, Lana M; Ertl-Wagner, Birgit; Mueller, Claudia; Catak, Cihan; Janowitz, Daniel; Stahl, Robert; et al. (J Alzheimers Dis, 2017)
Reserve in aging and Alzheimer's disease (AD) is defined as maintaining cognition at a relatively high level in the presence of neurodegeneration, an ability often associated with higher education among other life factors. Recent evidence suggests that higher resting-state functional connectivity within the frontoparietal control network, specifically the left frontal cortex (LFC) hub, contributes to higher reserve. Following up these previous resting-state fMRI findings, we probed memory-task related functional connectivity of the LFC hub as a neural substrate of reserve. In elderly controls (CN, n = 37) and patients with mild cognitive impairment (MCI, n = 17), we assessed global connectivity of the LFC hub during successful face-name association learning, using generalized psychophysiological interaction analyses. Reserve was quantified as residualized memory performance, accounted for gender and proxies of neurodegeneration (age, hippocampus atrophy, and APOE genotype). We found that greater education was associated with higher LFC-connectivity in both CN and MCI during successful memory. Furthermore, higher LFC-connectivity predicted higher residualized memory (i.e., reserve). These results suggest that higher LFC-connectivity contributes to reserve in both healthy and pathological aging.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

Longer-Term Investigation of the Value of 18F-FDG-PET and Magnetic Resonance Imaging for Predicting the Conversion of Mild Cognitive Impairment to Alzheimer's Disease: A Multicenter Study. - Inui, Yoshitaka; Ito, Kengo; Kato, Takashi (J Alzheimers Dis, 2017)
BACKGROUND: The value of fluorine-18-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) and magnetic resonance imaging (MRI) for predicting conversion of mild cognitive impairment (MCI) to Alzheimer's disease (AD) in longer-term is unclear. OBJECTIVE: To evaluate longer-term prediction of MCI to AD conversion using 18F-FDG-PET and MRI in a multicenter study. METHODS: One-hundred and fourteen patients with MCI were followed for 5 years. They underwent clinical and neuropsychological examinations, 18F-FDG-PET, and MRI at baseline. PET images were visually classified into predefined dementia patterns. PET scores were calculated as a semi quantitative index. For structural MRI, z-scores in medial temporal area were calculated by automated volume-based morphometry (VBM). RESULTS: Overall, 72% patients with amnestic MCI progressed to AD during the 5-year follow-up. The diagnostic accuracy of PET scores over 5 years was 60% with 53% sensitivity and 84% specificity. Visual interpretation of PET images predicted conversion to AD with an overall 82% diagnostic accuracy, 94% sensitivity, and 53% specificity. The accuracy of VBM analysis presented little fluctuation through 5 years and it was highest (73%) at the 5-year follow-up, with 79% sensitivity and 63% specificity. The best performance (87.9% diagnostic accuracy, 89.8% sensitivity, and 82.4% specificity) was with a combination identified using multivariate logistic regression analysis that included PET visual interpretation, educational level, and neuropsychological tests as predictors. CONCLUSION: 18F-FDG-PET visual assessment showed high performance for predicting conversion to AD from MCI, particularly in combination with neuropsychological tests. PET scores showed high diagnostic specificity. Structural MRI focused on the medial temporal area showed stable predictive value throughout the 5-year course.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Meditation and Music Improve Memory and Cognitive Function in Adults with Subjective Cognitive Decline: A Pilot Randomized Controlled Trial. - Innes, Kim E; Selfe, Terry Kit; Khalsa, Dharma Singh; Kandati, Sahiti (J Alzheimers Dis, 2017)
BACKGROUND: While effective therapies for preventing or slowing cognitive decline in at-risk populations remain elusive, evidence suggests mind-body interventions may hold promise. OBJECTIVES: In this study, we assessed the effects of Kirtan Kriya meditation (KK) and music listening (ML) on cognitive outcomes in adults experiencing subjective cognitive decline (SCD), a strong predictor of Alzheimer's disease. METHODS: Sixty participants with SCD were randomized to a KK or ML program and asked to practice 12 minutes/day for 3 months, then at their discretion for the ensuing 3 months. At baseline, 3 months, and 6 months we measured memory and cognitive functioning [Memory Functioning Questionnaire (MFQ), Trail-making Test (TMT-A/B), and Digit-Symbol Substitution Test (DSST)]. RESULTS: The 6-month study was completed by 53 participants (88%). Participants performed an average of 93% (91% KK, 94% ML) of sessions in the first 3 months, and 71% (68% KK, 74% ML) during the 3-month, practice-optional, follow-up period. Both groups showed marked and significant improvements at 3 months in memory and cognitive performance (MFQ, DSST, TMT-A/B; p's≤0.04). At 6 months, overall gains were maintained or improved (p's≤0.006), with effect sizes ranging from medium (DSST, ML group) to large (DSST, KK group; TMT-A/B, MFQ). Changes were unrelated to treatment expectancies and did not differ by age, gender, baseline cognition scores, or other factors. CONCLUSIONS: Findings of this preliminary randomized controlled trial suggest practice of meditation or ML can significantly enhance both subjective memory function and objective cognitive performance in adults with SCD, and may offer promise for improving outcomes in this population.

Memantine for Alzheimer's Disease: An Updated Systematic Review and Meta-analysis. - Kishi, Taro; Matsunaga, Shinji; Oya, Kazuto; Nomura, Ikuo; Ikuta, Toshikazu; Iwata, Nakao (J Alzheimers Dis, 2017)
BACKGROUND: The clinical benefit of memantine for Alzheimer's disease (AD) remains inconclusive. OBJECTIVE: We performed an updated systematic review and meta-analysis of the efficacy/safety of memantine in AD. METHODS: We included randomized trials of memantine for AD patients. Cognitive function scores (CF), behavioral disturbances scores (BD), and all-cause discontinuation were used as primary measures. Effect size based on a random-effects model was evaluated in the meta-analyses. RESULTS: Thirty studies (n = 7,567; memantine versus placebo: N = 11, n = 3,298; memantine + cholinesterase inhibitors (M+ChEIs) versus ChEIs: N = 17, n = 4,175) were identified. Memantine showed a significant improvement in CF [standardized mean difference (SMD) = -0.24, 95% confidence intervals (95% CIs) = -0.34, -0.15, p < 0.00001, I2 = 35% ] and BD (SMD = -0.16, 95% CIs = -0.29, -0.04, p = 0.01, I2 = 52%) compared with placebo. In the sensitivity analysis including only patients with moderate-severe AD, memantine was superior to the placebo in reducing BD without considerable heterogeneity (SMD = -0.20, 95% CIs = -0.34, -0.07, p = 0.003, I2 = 36%). Compared with ChEIs, M+ChEIs showed a greater reduction in BD (SMD = -0.20, 95% CIs = -0.36, -0.03, p = 0.02, I2 = 77%) and a trend of CF improvement (SMD = -0.11, 95% CIs = -0.22, 0.01, p = 0.06, I2 = 56%). However, in the sensitivity analysis of double-blind, placebo-controlled studies only, M+ChEIs showed a significant reduction in BD compared with ChEIs without considerable heterogeneity (SMD = -0.11, 95% CIs = -0.21, -0.01, p = 0.04, I2 = 40%). When performing the sensitivity analysis of donepezil studies only, M+ChEIs was superior to ChEIs in improving CF without considerable heterogeneity (SMD = -0.18, 95% CIs = -0.31, -0.05, p = 0.006, I2 = 49%). No differences were detected in all-cause discontinuation between the groups. CONCLUSIONS: The meta-analyses suggest the credible efficacy and safety of memantine in treating AD when used alone or in combination with ChEIs.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

A Meta-Analysis of Memantine for Depression. - Kishi, Taro; Matsunaga, Shinji; Iwata, Nakao (J Alzheimers Dis, 2017)
We conducted a systematic review and meta-analysis on whether memantine was beneficial for the treatment of depressive symptoms in major depressive disorder (MDD) and bipolar disorder (BD). The analysis included double-blind, randomized, placebo-controlled trials of memantine in MDD and BD. The primary outcome measures for efficacy and safety were response rate and all-cause discontinuation, respectively. Risk ratio (RR) and standardized mean difference with 95% confidence intervals (95% CI) were calculated. We identified six trials including 451 patients: MDD, four trials (n = 189), three of which studied memantine augmentation for antidepressants; BD, two trials (n = 262), both on memantine augmentation for mood stabilizers. The mean study duration was 8.33 weeks, and the mean age of patients was 39.9 years. Memantine was not superior to placebo with regard to response rate (RR = 0.92, 95% CI = 0.70-1.20, I2 = 72%), remission rate, improvement of depressive symptoms scale score, all-cause discontinuation (RR = 0.84, 95% CI = 0.60-1.18, I2 = 0%), discontinuation due to inefficacy and adverse events, or incidence of individual adverse events including decreased appetite, dizziness, nausea, and sedation. Although we conducted sensitivity analyses of the response rate to determine the reasons for the heterogeneity (diagnosis, age of patients, memantine dose, memantine augmentation, geographical region, and statistical population), we did not seek confounding factors. Memantine did not improve the treatment efficacy for depressive symptoms in MDD and BD patients. Long-term study of memantine for depression is required.

A Metal-Free Method for Producing MRI Contrast at Amyloid-β. - Hilt, Silvia; Tang, Tang; Walton, Jeffrey H; Budamagunta, Madhu; Maezawa, Izumi; Kálai, Tamás; Hideg, Kálmán; Singh, Vikrant; Wulff, Heike; Gong, Qizhi; Jin, Lee-Way; Louie, Angelique; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by depositions of the amyloid-β (Aβ) peptide in the brain. The disease process develops over decades, with substantial neurological loss occurring before a clinical diagnosis of dementia can be rendered. It is therefore imperative to develop methods that permit early detection and monitoring of disease progression. In addition, the multifactorial pathogenesis of AD has identified several potential avenues for AD intervention. Thus, evaluation of therapeutic candidates over lengthy trial periods also demands a practical, noninvasive method for measuring Aβ in the brain. Magnetic resonance imaging (MRI) is the obvious choice for such measurements, but contrast enhancement for Aβ has only been achieved using Gd(III)-based agents. There is great interest in gadolinium-free methods to image the brain. In this study, we provide the first demonstration that a nitroxide-based small-molecule produces MRI contrast in brain specimens with elevated levels of Aβ. The molecule is comprised of a  fluorene (a molecule with high affinity for Aβ) and a nitroxide spin label (a paramagnetic MRI contrast species). Labeling of brain specimens with the spin-labeled fluorene produces negative contrast in samples from AD model mice whereas no negative contrast is seen in specimens harvested from wild-type mice. Injection of spin-labeled fluorene into live mice resulted in good brain penetration, with the compound able to generate contrast 24-h post injection. These results provide a proof of concept method that can be used for early, noninvasive, gadolinium-free detection of amyloid plaques by MRI.

A Method for Diagnosing Alzheimer's Disease Based on Salivary Amyloid-β Protein 42 Levels. - Lee, Moonhee; Guo, Jian-Ping; Kennedy, Krista; McGeer, Edith G; McGeer, Patrick L (J Alzheimers Dis, 2017)
We have developed a non-invasive method of diagnosing Alzheimer's disease (AD), which can also predict the risk of its future onset. It is based on measuring salivary levels of amyloid-β protein terminating at position 42 (Aβ42). Brain deposits of this peptide are characteristic of AD. Biomarker studies indicate that such brain deposits commence a decade or more prior to clinical onset of the disease. We report here that Aβ42 is produced in all peripheral organs tested, thus establishing the generality of its production. We used this information to develop simple and sensitive tests to determine salivary Aβ42 levels. The levels were first stabilized by adding thioflavin S as an anti-aggregation agent and sodium azide as an anti-bacterial agent. We then quantitated the Aβ42 in a series of samples with ELISA type tests. Control cases showed almost identical levels of salivary Aβ42 regardless of sex or age. All AD cases secreted levels of Aβ42 more than double those of controls. Individuals at elevated risk of developing AD secreted levels comparable to the AD cases. The results establish that salivary Aβ42 levels can be used to diagnose AD as well as to predict the risk of its future onset.

MicroRNA Profile in Patients with Alzheimer's Disease: Analysis of miR-9-5p and miR-598 in Raw and Exosome Enriched Cerebrospinal Fluid Samples. - Riancho, Javier; Vázquez-Higuera, José Luis; Pozueta, Ana; Lage, Carmen; Kazimierczak, Martha; Bravo, María; Calero, Miguel; Gonalezález, Andrea; Rodríguez, Eloy; Lleo, Alberto; Sánchez-Juan, Pascual (J Alzheimers Dis, 2017)
BACKGROUND: MicroRNAs have been postulated as potential biomarkers for Alzheimer's disease (AD). Exosomes are nanovesicles which transport microRNAs, proteins, and other cargos. It has been hypothesized that the exosome traffic might be increased in neurodegenerative disorders. OBJECTIVE: i) To assess the cerebrospinal fluid (CSF) microRNA profile in a group of AD patients and control subjects and to validate a group of microRNAs previously reported by other authors. ii) To compare microRNA levels in whole CSF and in the exosome-enriched fraction in AD patients. METHODS: A panel of 760 microRNAs was analyzed in the CSF of 10 AD patients and 10 healthy subjects. Among microRNAs differently expressed, we selected those that had been previously reported by other authors. Candidates were validated in a larger group by individual qPCR assays. MicroRNA expression was also evaluated in exosome-enriched CSF samples of patients with AD and controls. RESULTS: Fifteen microRNAs were differently expressed in AD. MiR-9-5p, miR-134, and miR-598 were selected as candidates for further analysis. MiR-9-5p and miR-598 were detected in 50 and 75% of control CSF samples, respectively, while they were not detected in any AD CSF samples. We observed an opposite pattern when we evaluated the microRNA expression in the exosome-enriched CSF AD samples. No pattern variations were noted among healthy subjects. CONCLUSION: These data propose miR-9-5p and miR-598 as potential biomarkers for AD. Further studies in plasma and other body fluids will confirm their potential role as easily accessible biomarkers. In addition, our data suggest that exosome trafficking is different between AD and control subjects raising the need to take this phenomenon into consideration in future studies of AD biomarkers.

The Mild Behavioral Impairment Checklist (MBI-C): A Rating Scale for Neuropsychiatric Symptoms in Pre-Dementia Populations. - Ismail, Zahinoor; Agüera-Ortiz, Luis; Brodaty, Henry; Cieslak, Alicja; Cummings, Jeffrey; Fischer, Corinne E; Gauthier, Serge; Geda, Yonas E; Herrmann, Nathan; Kanji, Jamila; Lanctôt, Krista L; Miller, David S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Mild behavioral impairment (MBI) is a construct that describes the emergence at ≥50 years of age of sustained and impactful neuropsychiatric symptoms (NPS), as a precursor to cognitive decline and dementia. MBI describes NPS of any severity, which are not captured by traditional psychiatric nosology, persist for at least 6 months, and occur in advance of or in concert with mild cognitive impairment. While the detection and description of MBI has been operationalized in the International Society to Advance Alzheimer's Research and Treatment - Alzheimer's Association (ISTAART-AA) research diagnostic criteria, there is no instrument that accurately reflects MBI as described. OBJECTIVE: To develop an instrument based on ISTAART-AA MBI criteria. METHODS: Eighteen subject matter experts participated in development using a modified Delphi process. An iterative process ensured items reflected the five MBI domains of 1) decreased motivation; 2) emotional dysregulation; 3) impulse dyscontrol; 4) social inappropriateness; and 5) abnormal perception or thought content. Instrument language was developed a priori to pertain to non-demented functionally independent older adults. RESULTS: We present the Mild Behavioral Impairment Checklist (MBI-C), a 34-item instrument, which can easily be completed by a patient, close informant, or clinician. CONCLUSION: The MBI-C provides the first measure specifically developed to assess the MBI construct as explicitly described in the criteria. Its utility lies in MBI case detection, and monitoring the emergence of MBI symptoms and domains over time. Studies are required to determine the prognostic value of MBI for dementia development, and for predicting different dementia subtypes.

A Mitochondrial Biomarker-Based Study of S-Equol in Alzheimer's Disease Subjects: Results of a Single-Arm, Pilot Trial. - Wilkins, Heather M; Mahnken, Jonathan D; Welch, Paul; Bothwell, Rebecca; Koppel, Scott; Jackson, Richard L; Burns, Jeffrey M; Swerdlow, Russell H (J Alzheimers Dis, 2017)
Reductions in bioenergetic fluxes, mitochondrial enzyme activities, and mitochondrial number are observed in Alzheimer's disease (AD). Preclinical work indicates estrogen pathway signaling by either estrogen or selective β estrogen receptor (ERβ) agonists benefits these parameters. To assess whether an ERβ agonist could improve mitochondrial function in actual AD subjects, we administered S-equol (10 mg twice daily) to 15 women with AD and determined the platelet mitochondria cytochrome oxidase (COX) activity before initiating S-equol (lead-in), after two weeks of S-equol (active treatment), and two weeks after stopping S-equol (wash-out). Because the intra-individual variation of this enzyme across samples taken at different times was unknown we used a nonparametric, single-arm, dichotomous endpoint that classified subjects whose active treatment COX activity exceeded the average of their lead-in and wash-out measures as positive responders. Eleven positive responses were observed (p < 0.06). The implications of this finding on our null hypothesis (that S-equol does not influence platelet mitochondria COX activity) are discussed. To our knowledge, this is the first time a direct mitochondrial target engagement biomarker has been utilized in an AD clinical study.

Modeling the Distress of Spousal Caregivers of People with Dementia. - Wawrziczny, Emilie; Berna, Guillaume; Ducharme, Francine; Kergoat, Marie-Jeanne; Pasquier, Florence; Antoine, Pascal (J Alzheimers Dis, 2017)
BACKGROUND: The progressive mobilization of spouse caregivers who take care of a person with dementia (PWD) can lead to situations of distress. OBJECTIVE: The current study sought to investigate the influence of the characteristics of the caregiving context on spousal caregiver distress. METHODS: 125 spousal caregivers participated in this study. The characteristics of the caregiving context were assessed using questionnaires. We examined a moderated-mediator model (Step 1) in which we hypothesized that PWD and caregiver characteristics and dyadic determinants contribute to spousal caregiver distress. This model was compared based on the age at onset of the disease and the gender of the caregiver (Step 2). RESULTS: The model revealed that poor self-rated health and a lack of family support accentuated spousal caregiver distress, whereas the feeling of being prepared and level of confidence decreased spousal caregiver distress. Moreover, the quality of couple adjustment affected spousal caregiver distress, and this effect was mediated by the severity of the PWD's symptoms. Regarding the age at onset of the disease, the path between Couple Adjustment and the Care recipient's impairments was more important for caregivers of person with early-onset dementia (PEOD). Female caregivers who reported poor self-rated health experienced greater distress. CONCLUSIONS: It would be interesting to create a support program that would incorporate these three areas of intervention regarding the progression of the disease: first, "preparedness modules"; second, "dyadic modules" (especially for caregivers of PEOD); and third, "family modules". Specific attention should be given to female caregivers who report poor self-rated health.

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

Moderate Physical Activity is Associated with Cerebral Glucose Metabolism in Adults at Risk for Alzheimer's Disease. - Dougherty, Ryan J; Schultz, Stephanie A; Kirby, Taylor K; Boots, Elizabeth A; Oh, Jennifer M; Edwards, Dorothy; Gallagher, Catherine L; Carlsson, Cynthia M; Bendlin, Barbara B; Asthana, Sanjay; Sager, Mark A; Hermann, Bruce P; et al. (J Alzheimers Dis, 2017)
The objective of this study was to investigate the relationship between accelerometer-measured physical activity (PA) and glucose metabolism in asymptomatic late-middle-aged adults. Ninety-three cognitively healthy late-middle-aged adults from the Wisconsin Registry for Alzheimer's Prevention participated in this cross-sectional study. They underwent 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging and wore an accelerometer (ActiGraph GT3X+) to measure free-living PA. Accelerometer data yielded measures of light (LPA), moderate (MPA), and vigorous (VPA) intensity PA. FDG-PET images were scaled to the cerebellum and pons, and cerebral glucose metabolic rate was extracted from specific regions of interest (ROIs) known to be hypometabolic in AD, i.e., hippocampus, posterior cingulate, inferior temporal cortex, and angular gyrus. Regression analyses were utilized to examine the association between PA and glucose metabolism, while adjusting for potential confounds. There were associations between MPA and glucose metabolism in all ROIs examined. In contrast, LPA was not associated with glucose uptake in any ROI and VPA was only associated with hippocampal FDG uptake. Secondary analyses did not reveal associations between sedentary time and glucose metabolism in any of the ROIs. Exploratory voxel-wise analysis identified additional regions where MPA was significantly associated with glucose metabolism including the precuneus, supramarginal gyrus, amygdala, and middle frontal gyrus. These findings suggest that the intensity of PA is an important contributor to neuronal function in a late-middle-aged cohort, with MPA being the most salient. Prospective studies are necessary for fully elucidating the link between midlife engagement in PA and later life development of AD.

Modifiable Risk Factors for Prevention of Dementia in Midlife, Late Life and the Oldest-Old: Validation of the LIBRA Index. - Vos, Stephanie J B; van Boxtel, Martin P J; Schiepers, Olga J G; Deckers, Kay; de Vugt, Marjolein; Carrière, Isabelle; Dartigues, Jean-François; Pérès, Karine; Artero, Sylvaine; Ritchie, Karen; Galluzzo, Lucia; Scafato, Emanuele; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recently, the LIfestyle for BRAin health (LIBRA) index was developed to assess an individual's prevention potential for dementia. OBJECTIVE: We investigated the predictive validity of the LIBRA index for incident dementia in midlife, late life, and the oldest-old. METHODS: 9,387 non-demented individuals were recruited from the European population-based DESCRIPA study. An individual's LIBRA index was calculated solely based on modifiable risk factors: depression, diabetes, physical activity, hypertension, obesity, smoking, hypercholesterolemia, coronary heart disease, and mild/moderate alcohol use. Cox regression was used to test the predictive validity of LIBRA for dementia at follow-up (mean 7.2 y, range 1-16). RESULTS: In midlife (55-69 y, n = 3,256) and late life (70-79 y, n = 4,320), the risk for dementia increased with higher LIBRA scores. Individuals in the intermediate- and high-risk groups had a higher risk of dementia than those in the low-risk group. In the oldest-old (80-97 y, n = 1,811), higher LIBRA scores did not increase the risk for dementia. CONCLUSION: LIBRA might be a useful tool to identify individuals for primary prevention interventions of dementia in midlife, and maybe in late life, but not in the oldest-old.

The Modified Frontal Behavioral Inventory (FBI-mod) for Patients with Frontotemporal Lobar Degeneration, Alzheimer's Disease, and Mild Cognitive Impairment. - Suhonen, Noora-Maria; Hallikainen, Ilona; Hänninen, Tuomo; Jokelainen, Jari; Krüger, Johanna; Hall, Anette; Pikkarainen, Maria; Soininen, Hilkka; Remes, Anne M (J Alzheimers Dis, 2017)
While behavioral symptoms are both early and prevalent features of behavioral variant frontotemporal dementia (bvFTD), they can be present in other types of dementia as well, including Alzheimer's disease (AD) and even mild cognitive impairment (MCI). The Frontal Behavioral Inventory (FBI) was specifically developed to capture the behavioral and personality changes in bvFTD; it has also been modified into a self-administered caregiver questionnaire (FBI-mod). We examined the utility of the FBI-mod in differentiating bvFTD (n = 26), primary progressive aphasia (PPA) (n = 7), AD (n = 53), and MCI (n = 50) patients, and investigated how the FBI-mod may be associated with neuropsychological measures. The bvFTD patients scored significantly higher as compared to all other patient groups on the FBI-mod Total (p < 0.005), Negative (p < 0.005), and Positive (p < 0.01) scores. The cut-off point for the FBI-mod Total score that best discriminated the bvFTD and AD patients in our sample was 16, thus substantially lower than reported for the original FBI. For the bvFTD group, only mild correlations emerged between the FBI-mod and the cognitive measures. However, significant correlations between the FBI-mod and depressive symptoms as measured by the BDI-II were found for bvFTD. This suggests that while behavioral symptoms appear independent from cognitive deficits in bvFTD, they may nevertheless be interrelated with depressive symptoms. We conclude that the FBI-mod is an easily administered behavioral scale that can aid in differential diagnosis of bvFTD and should be used in clinical practice. The FBI-mod may further be considered as an outcome measure in clinical trials.

Molecular Mechanisms Underlying Neuroprotective Effect of Intranasal Administration of Human Hsp70 in Mouse Model of Alzheimer's Disease. - Evgen'ev, Michail B; Krasnov, George S; Nesterova, Inna V; Garbuz, David G; Karpov, Vadim L; Morozov, Alexey V; Snezhkina, Anastasiya V; Samokhin, Alexander N; Sergeev, Alexander; Kulikov, Alexei M; Bobkova, Natalia V (J Alzheimers Dis, 2017)
Heat shock protein 70, encoded by the HSPA1A gene in humans, is a key component of the machinery that protects neuronal cells from various stress conditions and whose production significantly declines during the course of aging and as a result of several neurodegenerative diseases. Herein, we investigated whether sub-chronic intranasal administration of exogenous Hsp70 (eHsp70) exerts a neuroprotective effect on the temporal cortex and areas of the hippocampus in transgenic 5XFAD mice, a model of Alzheimer's disease. The quantitative analysis of neuronal pathologies in the compared groups, transgenic (Tg) versus non-transgenic (nTg), revealed high level of abnormalities in the brains of transgenic mice. Treatment with human recombinant Hsp70 had profound rejuvenation effect on both neuronal morphology and functional state in the temporal cortex and hippocampal regions in transgenic mice. Hsp70 administration had a smaller, but still significant, effect on the functional state of neurons in non-transgenic mice as well. Using deep sequencing, we identified multiple differentially expressed genes (DEGs) in the hippocampus of transgenic and non-transgenic mice. Furthermore, this analysis demonstrated that eHsp70 administration strongly modulates the spectrum of DEGs in transgenic animals, reverting to a pattern similar to that observed in non-transgenic age-matched mice, which included upregulation of genes responsible for amine transport, transmission of nerve impulses and other pathways that are impaired in 5XFAD mice. Overall, our data indicate that Hsp70 treatment may be an effective therapeutic against old age diseases of the Alzheimer's type.

Mortality Risk after Diagnosis of Early-Onset Alzheimer's Disease versus Late-Onset Alzheimer's Disease: A Propensity Score Matching Analysis. - Chang, Ki Jung; Hong, Chang Hyung; Lee, Kang Soo; Kang, Dae Ryong; Lee, Jeong Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Do-Kwan; Lee, Yunhwan; Chung, Young Ki; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: We aimed to compare the risk of mortality in patients with early-onset Alzheimer's disease (EOAD) versus those with late-onset AD (LOAD) using a large number of study subjects. We applied propensity score matching (PSM) to minimize confounding biases in the comparison between EOAD and LOAD. METHODS: We obtained data from elderly Korean subjects with AD (n = 3,611) at baseline from the CREDOS cohort study, which was conducted from November 2005 to July 2013. We conducted PSM to reduce the bias due to confounding variables related to survival in patients with AD. The risks of mortality associated with EOAD and LOAD were evaluated by Cox proportional hazard analyses, controlling for relevant covariates. RESULTS: After propensity score matching, 312 subjects with EOAD and 624 subjects with LOAD were selected for further analysis. The Cox proportional hazard analysis showed that patients with EOAD are at a greater risk for mortality compared to those with LOAD (Hazard Ratio: 2.01, 95% CI: 1.01-4.00, p-value: 0.04) when controlling for the direct effect of aging on mortality. The results did not change after adjusting for age at diagnosis, general cognitive function, nutritional factor related to body mass index, and physical disability using activities of daily living. The results support the assumption that EOAD takes a more malignant course than LOAD. CONCLUSIONS: Our results provide support for the idea that EOAD takes a clinical course that is distinct from that of LOAD, especially as pertains to the risk of mortality.

Motor Phenotype in Neurodegenerative Disorders: Gait and Balance Platform Study Design Protocol for the Ontario Neurodegenerative Research Initiative (ONDRI). - Montero-Odasso, Manuel; Pieruccini-Faria, Frederico; Bartha, Robert; Black, Sandra E; Finger, Elizabeth; Freedman, Morris; Greenberg, Barry; Grimes, David A; Hegele, Robert A; Hudson, Christopher; Kleinstiver, Peter W; Lang, Anthony E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The association of cognitive and motor impairments in Alzheimer's disease and other neurodegenerative diseases is thought to be related to damage in the common brain networks shared by cognitive and cortical motor control processes. These common brain networks play a pivotal role in selecting movements and postural synergies that meet an individual's needs. Pathology in this "highest level" of motor control produces abnormalities of gait and posture referred to as highest-level gait disorders. Impairments in cognition and mobility, including falls, are present in almost all neurodegenerative diseases, suggesting common mechanisms that still need to be unraveled. OBJECTIVE: To identify motor-cognitive profiles across neurodegenerative diseases in a large cohort of patients. METHODS: Cohort study that includes up to 500 participants, followed every year for three years, across five neurodegenerative disease groups: Alzheimer's disease/mild cognitive impairment, frontotemporal degeneration, vascular cognitive impairment, amyotrophic lateral sclerosis, and Parkinson's disease. Gait and balance will be assessed using accelerometers and electronic walkways, evaluated at different levels of cognitive and sensory complexity, using the dual-task paradigm. RESULTS: Comparison of cognitive and motor performances across neurodegenerative groups will allow the identification of motor-cognitive phenotypes through the standardized evaluation of gait and balance characteristics. CONCLUSIONS: As part of the Ontario Neurodegenerative Research Initiative (ONDRI), the gait and balance platform aims to identify motor-cognitive profiles across neurodegenerative diseases. Gait assessment, particularly while dual-tasking, will help dissect the cognitive and motor contribution in mobility and cognitive decline, progression to dementia syndromes, and future adverse outcomes including falls and mortality.

mTORC2 (Rictor) in Alzheimer's Disease and Reversal of Amyloid-β Expression-Induced Insulin Resistance and Toxicity in Rat Primary Cortical Neurons. - Lee, Han-Kyu; Kwon, Bumsup; Lemere, Cynthia A; de la Monte, Suzanne; Itamura, Kyohei; Ha, Austin Y; Querfurth, Henry W (J Alzheimers Dis, 2017)
Mammalian target of rapamycin complex 1 (mTORC1), a nutrient sensor and central controller of cell growth and proliferation, is altered in various models of Alzheimer's disease (AD). Even less studied or understood in AD is mammalian target of rapamycin complex 2 (mTORC2) that influences cellular metabolism, in part through the regulations of Akt/PKB and SGK. Dysregulation of insulin/PI3K/Akt signaling is another important feature of AD pathogenesis. We found that both total mTORC1 and C2 protein levels and individual C1 and C2 enzymatic activities were decreased in human AD brain samples. In two rodent AD models, mTORC1 and C2 activities were also decreased. In a neuronal culture model of AD characterized by accumulation of cellular amyloid-β (Aβ)42, mTORC1 activity was reduced. Autophagic vesicles and markers were correspondingly increased and new protein synthesis was inhibited, consistent with mTORC1 hypofunction. Interestingly, mTORC2 activity in neural culture seemed resistant to the effects of intracellular amyloid. In various cell lines, Aβ expression provoked insulin resistance, characterized by inhibition of stimulated Akt phosphorylation, and an increase in negative mTORC1 regular, p-AMPK, itself a nutrient sensor. Rapamycin decreased phospho-mTOR and to lesser degree p-Rictor. This further suppression of mTORC1 activity protected cells from Aβ-induced toxicity and insulin resistance. More striking, Rictor over-expression fully reversed the Aβ-effects on primary neuronal cultures. Finally, using in vitro assay, Rictor protein addition completely overcame oligomeric Aβ-induced inhibition of the PDK-Akt activation step. We conclude that striking a new balance by restoring mTORC2 abundance and/or inhibition of mTORC1 has therapeutic potential in AD.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

Multimodal Cognitive Enhancement Therapy for Patients with Mild Cognitive Impairment and Mild Dementia: A Multi- Center, Randomized, Controlled, Double-Blind, Crossover Trial. - Han, Ji Won; Lee, Hyeonggon; Hong, Jong Woo; Kim, Kayoung; Kim, Taehyun; Byun, Hye Jin; Ko, Ji Won; Youn, Jong Chul; Ryu, Seung-Ho; Lee, Nam-Jin; Pae, Chi-Un; Kim, Ki Woong (J Alzheimers Dis, 2017)
We developed and evaluated the effect of Multimodal Cognitive Enhancement Therapy (MCET) consisting of cognitive training, cognitive stimulations, reality orientation, physical therapy, reminiscence therapy, and music therapy in combination in older people with mild cognitive impairment (MCI) or mild dementia. This study was a multi-center, double-blind, randomized, placebo-controlled, two-period cross-over study (two 8-week treatment phases separated by a 4-week wash-out period). Sixty-four participants with MCI or dementia whose Clinical Dementia Rating was 0.5 or 1 were randomized to the MCET group or the mock-therapy (placebo) group. Outcomes were measured at baseline, week 9, and week 21. Fifty-five patients completed the study. Mini-Mental State Examination (effect size = 0.47, p = 0.013) and Alzheimer's Disease Assessment Scale-Cognitive Subscale (effect size = 0.35, p = 0.045) scores were significantly improved in the MCET compared with mock-therapy group. Revised Memory and Behavior Problems Checklist frequency (effect size = 0.38, p = 0.046) and self-rated Quality of Life - Alzheimer's Disease (effect size = 0.39, p = 0.047) scores were significantly improved in the MCET compared with mock-therapy. MCET improved cognition, behavior, and quality of life in people with MCI or mild dementia more effectively than conventional cognitive enhancing activities did.

Network-Based Substrate of Cognitive Reserve in Alzheimer's Disease. - Serra, Laura; Mancini, Matteo; Cercignani, Mara; Di Domenico, Carlotta; Spanò, Barbara; Giulietti, Giovanni; Koch, Giacomo; Marra, Camillo; Bozzali, Marco (J Alzheimers Dis, 2017)
Cognitive reserve (CR) is known to modulate the clinical features of Alzheimer's disease (AD). This concept may be critical for the development of non-pharmacological interventions able to slow down patients' cognitive decline in the absence of disease-modifying treatments. We aimed at identifying the neurobiological substrates of CR (i.e., neural reserve) over the transition between normal aging and AD, by assessing the underlying brain networks and their topological properties. A cohort of 154 participants (n = 68 with AD, n = 61 with amnestic mild cognitive impairment (aMCI), and 25 healthy subjects) underwent resting-state functional MRI and neuropsychological testing. Within each group, participants were classified as having high or low CR, and functional connectivity measures were compared, within group, between high and low CR individuals. Network-based statistics and topological network properties derived from graph theory were explored. Connectivity differences between high and low CR were evident only for aMCI patients, with participants with high CR showing a significant increase of connectivity in a network involving mainly fronto-parietal nodes. Conversely, they showed significantly decreased connectivity in a network involving fronto-temporo-cerebellar nodes. Consistently, changes to topological measures were observed in either direction, and were associated with measures of global cognitive function. These findings support the hypothesis that CR impacts on neurodegenerative process in the early phase of AD only. In addition, they fit with the existence of a "neural reserve", characterized by specific neural networks and their efficiency. It remains to be demonstrated whether interventions later in life can modulate this "neural reserve".

Neural Basis of Apathy in Patients with Amnestic Mild Cognitive Impairment. - Kazui, Hiroaki; Takahashi, Ryuichi; Yamamoto, Yuki; Yoshiyama, Kenji; Kanemoto, Hideki; Suzuki, Yukiko; Sato, Shunsuke; Azuma, Shingo; Suehiro, Takashi; Shimosegawa, Eku; Ishii, Kazunari; Tanaka, Toshihisa (J Alzheimers Dis, 2017)
BACKGROUND: Although apathy is associated with damage to the frontal and temporal lobes in Alzheimer's disease (AD), the crucial regions for apathy in patients with amnestic mild cognitive impairment (aMCI) are unknown. OBJECTIVE: To identify brain regions associated with apathy in aMCI patients. METHODS: The subjects of this study were 98 aMCI patients who were entered in our dementia registry between March 1, 2009 and April 30, 2015 and who satisfied our criteria for aMCI. The association between the apathy score of the Neuropsychiatric Inventory and regional gray matter volume was analyzed using voxel-based morphometry. The association between apathy score and regional cerebral blood flow (rCBF) measured with single photon emission computed tomography (SPECT) was analyzed using Statistical Parametric Mapping. RESULTS: The aMCI patients were classified into aMCI with and without "SPECT images suggestive of AD" (aMCI-AD+ and aMCI-AD-, respectively) based on the Z-score summation analysis method. In aMCI-AD+ (n = 31), apathy was significantly and negatively correlated with gray matter volume in the right caudate nucleus and with rCBF in five regions (left posterior-medial frontal lobe, right superior frontal lobe, bilateral culmen-fusiform gyri, and left occipital lobe). In aMCI-AD-(n = 67), apathy was significantly and negatively correlated with gray matter volumes in five regions but it was not correlated with rCBF in any regions. CONCLUSION: In patients with a high probability of being in the aMCI stage of AD, apathy was associated with atrophy of the right caudate nucleus and hypoperfusion in the frontal, temporal and occipital lobes.

Neuroimaging Feature Terminology: A Controlled Terminology for the Annotation of Brain Imaging Features. - Iyappan, Anandhi; Younesi, Erfan; Redolfi, Alberto; Vrooman, Henri; Khanna, Shashank; Frisoni, Giovanni B; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Ontologies and terminologies are used for interoperability of knowledge and data in a standard manner among interdisciplinary research groups. Existing imaging ontologies capture general aspects of the imaging domain as a whole such as methodological concepts or calibrations of imaging instruments. However, none of the existing ontologies covers the diagnostic features measured by imaging technologies in the context of neurodegenerative diseases. Therefore, the Neuro-Imaging Feature Terminology (NIFT) was developed to organize the knowledge domain of measured brain features in association with neurodegenerative diseases by imaging technologies. The purpose is to identify quantitative imaging biomarkers that can be extracted from multi-modal brain imaging data. This terminology attempts to cover measured features and parameters in brain scans relevant to disease progression. In this paper, we demonstrate the systematic retrieval of measured indices from literature and how the extracted knowledge can be further used for disease modeling that integrates neuroimaging features with molecular processes.

Neuronal Expression of Truncated Tau Efficiently Promotes Neurodegeneration in Animal Models: Pitfalls of Toxic Oligomer Analysis. - Skrabana, Rostislav; Kovacech, Branislav; Filipcik, Peter; Zilka, Norbert; Jadhav, Santosh; Smolek, Tomas; Kontsekova, Eva; Novak, Michal (J Alzheimers Dis, 2017)
Animal models of neurodegeneration induced by neuronal expression of truncated tau protein emerge as an important tool for understanding the pathogenesis of human tauopathies and for therapy development. Here we highlight common features of truncated tau models and make a critical assessment of possible pitfalls in their analysis. Particularly, the amount of soluble tau oligomers, which are suspected to be neurotoxic agents participating on the spreading of pathology inside the brain, may be overestimated due to a post-lysis oxidative tau oligomerization. Using a mouse brain lysate spiked with recombinant truncated and full length tau forms, we show that tau oligomers might inadvertently be produced during the isolation procedure. This finding is further corroborated by the analysis of brain lysates originated from a mouse model expressing truncated tau variant. Our results underline the necessity of thiol-protecting conditions during the analysis of tau oligomers involved in the etiopathogenesis of various tauopathies including Alzheimer's disease.

Neuropsychological Profile in the C9ORF72 Associated Behavioral Variant Frontotemporal Dementia. - Suhonen, Noora-Maria; Haanpää, Ramona M; Korhonen, Ville; Jokelainen, Jari; Pitkäniemi, Anni; Heikkinen, Anna-Leena; Krüger, Johanna; Hartikainen, Päivi; Helisalmi, Seppo; Hiltunen, Mikko; Hänninen, Tuomo; Remes, Anne M (J Alzheimers Dis, 2017)
While the C9ORF72 expansion is a major cause of behavioral variant frontotemporal dementia (bvFTD), little is known of the resultant cognitive profile. Our aim was to characterize the neuropsychological profile of the C9ORF72 associated bvFTD. We contrasted structured neuropsychological assessments of the C9ORF72 expansion carrier bvFTD patients (n = 26) with non-carrier bvFTD patients (n = 47) and those with Alzheimer's disease (AD) (n = 47). As compared to the non-carrier bvFTD patients, the C9ORF72 expansion carriers performed at a higher level in an immediate verbal memory test while showing poorer phonemic verbal fluency. Additionally, the expansion carriers committed more errors in the Stroop test and the Alternating S task relative to the non-carriers. Finally, while the AD patients outperformed both bvFTD patient groups in working memory, their performance was more impaired in episodic memory tasks relative to the bvFTD groups. We conclude that bvFTD patients carrying the C9ORF72 expansion may display more pronounced executive deficits together with less severe verbal memory impairment as compared to their non-carrier bvFTD counterparts. Knowledge of the specific neuropsychological features associated with the C9ORF72 related bvFTD may aid in the early diagnosis of the disease as well as in targeting genetic testing.

Neuropsychological Symptoms in Sporadic Creutzfeldt-Jakob Disease Patients in Germany. - Krasnianski, Anna; Bohling, Geeske T; Heinemann, Uta; Varges, Daniela; Meissner, Bettina; Schulz-Schaeffer, Walter J; Reif, Andreas; Zerr, Inga (J Alzheimers Dis, 2017)
BACKGROUND: The polymorphism at codon 129 of the prion protein gene (PRNP) and the PrPSc types 1 and 2 belong to a molecular classification of sporadic Creutzfeldt-Jakob disease (sCJD) that correlates well with the clinical and neuropathological phenotype of sCJD. OBJECTIVE: The aim of the study was to perform the first detailed evaluation of neuropsychological deficits in a large group of definite sCJD patients with known molecular subtype. METHODS: We analyzed neuropsychological symptoms in a cohort of 248 sCJD patients with known M129 V polymorphism of PRNP and prion protein type. RESULTS: Neuropsychological symptoms were very frequent in our patients (96%) and occurred as early as in the first third of the disease course. Besides amnesia and impaired attention (89% each), frontal lobe syndrome (75%), aphasia (63%), and apraxia (57%) were the most common neuropsychological deficits. There was no statistically significant difference with regard to frequency of neuropsychological symptoms between the subtypes. In MV2 and VV2 patients, the onset of neuropsychological symptoms was significantly later than in all other subtypes. CONCLUSION: We provide the first detailed analysis of neuropsychological symptoms in a large group of sCJD patients with known M129 V genotype and prion protein type. We suggest that the rate of progression of neuropsychological symptoms is subtype-specific. These data may improve the diagnosis in atypical sCJD subtypes.

NFATc2 Modulates Microglial Activation in the AβPP/PS1 Mouse Model of Alzheimer's Disease. - Manocha, Gunjan D; Ghatak, Atreyi; Puig, Kendra L; Kraner, Susan D; Norris, Christopher M; Combs, Colin K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) brains are characterized by fibrillar amyloid-β (Aβ) peptide containing plaques and associated reactive microglia. The proinflammatory phenotype of the microglia suggests that they may negatively affect disease course and contribute to behavioral decline. This hypothesis predicts that attenuating microglial activation may provide benefit against disease. Prior work from our laboratory and others has characterized a role for the transcription factor, nuclear factor of activated T cells (NFAT), in regulating microglial phenotype in response to different stimuli, including Aβ peptide. We observed that the NFATc2 isoform was the most highly expressed in murine microglia cultures, and inhibition or deletion of NFATc2 was sufficient to attenuate the ability of the microglia to secrete cytokines. In order to determine whether the NFATc2 isoform, in particular, was a valid immunomodulatory target in vivo, we crossed an NFATc2-/- line to a well-known AD mouse model, an AβPP/PS1 mouse line. As expected, the AβPP/PS1 x NFATc2-/- mice had attenuated cytokine levels compared to AβPP/PS1 mice as well as reduced microgliosis and astrogliosis with no effect on plaque load. Although some species differences in relative isoform expression may exist between murine and human microglia, it appears that microglial NFAT activity is a viable target for modulating the proinflammatory changes that occur during AD.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Non-Phosphorylated Tau as a Potential Biomarker of Alzheimer's Disease: Analytical and Diagnostic Characterization. - Lewczuk, Piotr; Lelental, Natalia; Lachmann, Ingolf; Holzer, Max; Flach, Katharina; Brandner, Sebastian; Engelborghs, Sebastiaan; Teunissen, Charlotte E; Zetterberg, Henrik; Molinuevo, José Luis; Mroczko, Barbara; Blennow, Kaj; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Virtually nothing is known about a potential diagnostic role of non-phospho-epitopes of Tau (Non-P-Tau) in cerebrospinal fluid (CSF). OBJECTIVE: To establish and analytically and clinically characterize the first assay capable to measure concentrations of Non-P-Tau in human CSF. METHODS: An antibody (1G2) was developed that selectively binds to the Tau molecule non-phosphorylated at the positions T175 and T181, and was used in establishing a sandwich ELISA capable to measure Non-P-Tau in human CSF, following analytical and clinical validation of the method. RESULTS: The 1G2 antibody shows decreasing reactivity to tau peptides containing phosphorylation mainly at positions T175 and T181. Detection limit of the assay is 25 pg/ml; the coefficients of variation (CVs) of the optical densities of the repeated standard curves were between 3.6-15.9%. Median intra-assay imprecision of double measurements was 4.8%; inter-assay imprecision was in the range of 11.2% - 15.3%. Non-P-Tau concentrations are stable in the CSF samples sent to distinct laboratories under ambient temperature; inter-laboratory variation was approximately 30%. The Non-P-Tau CSF concentrations were highly significantly increased in patients with Alzheimer's disease in stage of mild cognitive impairment or dementia (AD/MCI, n = 58, 109.2±32.0 pg/mL) compared to the non-demented Controls (n = 42, 62.1±9.3 pg/mL, p < 0.001). At the cut-off of 78.3 pg/mL, the sensitivity and the specificity were 94.8% and 97.6%, respectively. CONCLUSION: For the first time, an assay is reported to reliably measure concentrations of non-phosphorylated Tau in human CSF.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

A Novel Loss-of-Function GRN Mutation p.(Tyr229*): Clinical and Neuropathological Features. - Kuuluvainen, Liina; Pöyhönen, Minna; Pasanen, Petra; Siitonen, Maija; Rummukainen, Jaana; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2017)
Mutations in the progranulin (GRN) gene represent about 5-10% of frontotemporal lobar degeneration (FTLD). We describe a proband with a novel GRN mutation c.687T>A, p.(Tyr229*), presenting with dyspraxia, dysgraphia, and dysphasia at the age of 60 and a very severe FTLD neuropathological phenotype with TDP43 inclusions. The nephew of the proband had signs of dementia and personality changes at the age of 60 and showed similar but milder FTLD pathology. Three other family members had had early-onset dementia. Gene expression studies showed decreased GRN gene expression in mutation carriers' blood samples. In conclusion, we describe a novel GRN, p.(Tyr229*) mutation, resulting in haploinsufficiency of GRN and a severe neuropathologic FTLD phenotype.

N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.

Occupational Attainment as Risk Factor for Progression from Mild Cognitive Impairment to Alzheimer's Disease: A CREDOS Study. - Myung, Woojae; Lee, Chunsoo; Park, Jin Hong; Woo, Sook-Young; Kim, Seonwoo; Kim, Sangha; Chung, Jae Won; Kang, Hyo Shin; Lim, Shinn-Won; Choi, Junbae; Na, Duk L; Kim, Seong Yoon; et al. (J Alzheimers Dis, 2017)
High occupational attainment has been known as a marker of cognitive reserve. Previous studies in the general population have shown that high occupational attainment is associated with reduced risk of Alzheimer's disease (AD). However, few studies have assessed the effect of occupational attainment on the clinical course of mild cognitive impairment (MCI). In this study, we evaluated whether individuals with high occupational attainment show more frequent progression from MCI to AD. Participants (n = 961) with MCI were recruited from a nationwide, hospital-based multi-center cohort, and were followed for up to 60 months (median: 17.64, interquartile range [12.36, 29.28]). We used Cox regression for competing risks to analyze the effect of occupational attainment on development of AD, treating dementia other than AD as a competing risk. Among the 961 individuals with MCI, a total of 280 (29.1%) converted to dementia during the follow-up period. The risk of progression to AD was higher in the individuals with high occupational attainment after controlling for potential confounders (hazard ratio = 1.83, 95% confidence interval = 1.25-2.69, p = 0.002). High occupational attainment in individuals with MCI is an independent risk factor for higher progression rate of MCI to AD. This result suggests that the protective effect of high occupational attainment against cognitive decline disappears in the MCI stage, and that careful assessment of occupational history can yield important clinical information for prognosis in individuals with MCI.

Odor Identification Screening Improves Diagnostic Classification in Incipient Alzheimer's Disease. - Quarmley, Megan; Moberg, Paul J; Mechanic-Hamilton, Dawn; Kabadi, Sushila; Arnold, Steven E; Wolk, David A; Roalf, David R (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of olfaction may serve as useful biomarkers of incipient dementia. Here we examine the improvement in diagnostic accuracy of Alzheimer's disease (AD) and mild cognitive impairment (MCI) when assessing both cognitive functioning and odor identification. OBJECTIVE: To determine the utility of odor identification as a supplementary screening test in incipient AD. METHODS: Sniffin' Sticks Odor Identification Test (SS-OIT) and the Montreal Cognitive Assessment (MoCA) were administered in 262 AD, 174 MCI [150 amnestic (aMCI), and 24 non-amnestic (naMCI)], and 292 healthy older adults (HOA). RESULTS: Odor identification scores were higher in HOA relative to MCI or AD groups, and MCI outperformed AD. Odor identification scores were higher in aMCI single domain than aMCI multiple domain. Complementing MoCA scores with the SS-OIT significantly improved diagnostic accuracy of individuals with AD and MCI, including within MCI subgroups. DISCUSSION: Odor identification is a useful supplementary screening tool that provides additional information relevant for clinical categorization of AD and MCI, including those who are at highest risk to convert to AD.

Of Mice and Men: Comparative Analysis of Neuro-Inflammatory Mechanisms in Human and Mouse Using Cause-and-Effect Models. - Kodamullil, Alpha Tom; Iyappan, Anandhi; Karki, Reagon; Madan, Sumit; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Perturbance in inflammatory pathways have been identified as one of the major factors which leads to neurodegenerative diseases (NDD). Owing to the limited access of human brain tissues and the immense complexity of the brain, animal models, specifically mouse models, play a key role in advancing the NDD field. However, many of these mouse models fail to reproduce the clinical manifestations and end points of the disease. NDD drugs, which passed the efficacy test in mice, were repeatedly not successful in clinical trials. There are numerous studies which are supporting and opposing the applicability of mouse models in neuroinflammation and NDD. In this paper, we assessed to what extend a mouse can mimic the cellular and molecular interactions in humans at a mechanism level. Based on our mechanistic modeling approach, we investigate the failure of a neuroinflammation targeted drug in the late phases of clinical trials based on the comparative analyses between the two species.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Only White Matter Hyperintensities Predicts Post-Stroke Cognitive Performances Among Cerebral Small Vessel Disease Markers: Results from the TABASCO Study. - Molad, Jeremy; Kliper, Efrat; Korczyn, Amos D; Ben Assayag, Einor; Ben Bashat, Dafna; Shenhar-Tsarfaty, Shani; Aizenstein, Orna; Shopin, Ludmila; Bornstein, Natan M; Auriel, Eitan (J Alzheimers Dis, 2017)
BACKGROUND: White matter hyperintensities (WMH) were shown to predict cognitive decline following stroke or transient ischemic attack (TIA). However, WMH are only one among other radiological markers of cerebral small vessel disease (SVD). OBJECTIVE: The aim of this study was to determine whether adding other SVD markers to WMH improves prediction of post-stroke cognitive performances. METHODS: Consecutive first-ever stroke or TIA patients (n = 266) from the Tel Aviv Acute Brain Stroke Cohort (TABASCO) study were enrolled. MRI scans were performed within seven days of stroke onset. We evaluated the relationship between cognitive performances one year following stroke, and previously suggested total SVD burden score including WMH, lacunes, cerebral microbleeds (CMB), and perivascular spaces (PVS). RESULTS: Significant negative associations were found between WMH and cognition (p < 0.05). Adding other SVD markers (lacunes, CMB, PVS) to WMH did not improve predication of post-stroke cognitive performances. Negative correlations between SVD burden score and cognitive scores were observed for global cognitive, memory, and visual spatial scores (all p < 0.05). However, following an adjustment for confounders, no associations remained significant. CONCLUSION: WMH score was associated with poor post-stroke cognitive performance. Adding other SVD markers or SVD burden score, however, did not improve prediction.

Orexin Impairs the Phagocytosis and Degradation of Amyloid-β Fibrils by Microglial Cells. - An, Hoyoung; Cho, Mi-Hyang; Kim, Dong-Hou; Chung, Seockhoon; Yoon, Seung-Yong (J Alzheimers Dis, 2017)
BACKGROUND: Intracranial accumulation of amyloid-β (Aβ) is a characteristic finding of Alzheimer's disease (AD). It is thought to be the result of Aβ overproduction by neurons and impaired clearance by several systems, including degradation by microglia. Sleep disturbance is now considered a risk factor for AD, but studies focusing on how sleep modulates microglial handling of Aβ have been scarce. OBJECTIVE: To determine whether phagocytosis and degradation of extracellular Aβ fibrils by BV2 microglial cells were impaired by treatment with orexin-A/B, a major modulator of the sleep-wake cycle, which may mimic sleep deprivation conditions. METHODS: BV2 cells were treated with orexin and Aβ for various durations and phagocytic and autophagic processes for degradation of extracellular Aβ were examined. RESULTS: After treatment with orexin, the formation of actin filaments around Aβ fibrils, which is needed for phagocytosis, was impaired, and phagocytosis regulating molecules such as PI3K, Akt, and p38-MAPK were downregulated in BV2 cells. Orexin also suppressed autophagic flux, through disruption of the autophagosome-lysosome fusion process, resulting in impaired Aβ degradation in BV2 cells. CONCLUSIONS: Our results demonstrate that orexin can hinder clearance of Aβ through the suppression of phagocytosis and autophagic flux in microglia. This is a novel mechanism linking AD and sleep, and suggests that attenuated microglial function, due to sleep deprivation, may increase Aβ accumulation in the brain.

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation. - Marwarha, Gurdeep; Rostad, Stephen; Lilek, Jaclyn; Kleinjan, Mason; Schommer, Jared; Ghribi, Othman (J Alzheimers Dis, 2017)
Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer's disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in AD by increasing the aspartyl protease β-site AβPP cleaving enzyme 1 (BACE1) and amyloid-β (Aβ) genesis. In this study, we determined the extent to which palmitate increases BACE1 and Aβ levels in vitro and in vivo as well as the potential role of ER stress as cellular mechanism underlying palmitate effects. We demonstrate, in palmitate-treated SH-SY5Y neuroblastoma cells and in the hippocampi of palmitate-enriched diet-fed mice, that palmitate evokes the activation of the C/EBP Homologous Protein (CHOP), a transcription factor that is specifically responsive to ER stress. Induction of CHOP expression is associated with increased BACE1 mRNA, protein and activity levels, and subsequent enhanced amyloidogenic processing of amyloid-β protein precursor (AβPP) that culminates in a substantial increase in Aβ genesis. We further show that CHOP is an indispensable molecular mediator of palmitate-induced upregulation in BACE1 activity and Aβ genesis. Indeed, we show that Chop-/- mice and CHOP knocked-down SH-SY5Y neuroblastoma cells do not exhibit the same commensurate degree of palmitate-induced increase in BACE1 expression levels and Aβ genesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Cell Line, Tumor; Dose-Response Relationship, Drug; Endoplasmic Reticulum Stress; Gene Expression Regulation; Hippocampus; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Palmitates; RNA, Messenger; Signal Transduction; Transcription Factor CHOP; Transcription Factors; Transfection

Passive Assessment of Routine Driving with Unobtrusive Sensors: A New Approach for Identifying and Monitoring Functional Level in Normal Aging and Mild Cognitive Impairment. - Seelye, Adriana; Mattek, Nora; Sharma, Nicole; Witter, Phelps; Brenner, Ariella; Wild, Katherine; Dodge, Hiroko; Kaye, Jeffrey (J Alzheimers Dis, 2017)
BACKGROUND: Driving is a key functional activity for many older adults, and changes in routine driving may be associated with emerging cognitive decline due to early neurodegenerative disease. Current methods for assessing driving such as self-report are inadequate for identifying and monitoring subtle changes in driving patterns that may be the earliest signals of functional change in developing mild cognitive impairment (MCI). OBJECTIVE: This proof of concept study aimed to establish the feasibility of continuous driving monitoring in a sample of cognitively normal and MCI older adults for an average of 206 days using an unobtrusive driving sensor and demonstrate that derived sensor-based driving metrics could effectively discriminate between MCI and cognitively intact groups. METHODS: Novel objective driving measures derived from 6 months of routine driving monitoring were examined in older adults with intact cognition (n = 21) and MCI (n = 7) who were enrolled in the Oregon Center for Aging and Technology (ORCATECH) longitudinal assessment program. RESULTS: Unobtrusive continuous monitoring of older adults' routine driving using a driving sensor was feasible and well accepted. MCI participants drove fewer miles and spent less time on the highway per day than cognitively intact participants. MCI drivers showed less day-to-day fluctuations in their driving habits than cognitively intact drivers. CONCLUSION: Sensor-based driving measures are objective, unobtrusive, and can be assessed every time a person drives his or her vehicle to identify clinically meaningful changes in daily driving. This novel methodology has the potential to be useful for the early detection and monitoring of changes in daily functioning within individuals.

Pathway-Specific Polygenic Risk Scores as Predictors of Amyloid-β Deposition and Cognitive Function in a Sample at Increased Risk for Alzheimer's Disease. - Darst, Burcu F; Koscik, Rebecca L; Racine, Annie M; Oh, Jennifer M; Krause, Rachel A; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Christian, Bradley T; Bendlin, Barbara B; Okonkwo, Ozioma C; Hogan, Kirk J; et al. (J Alzheimers Dis, 2017)
Polygenic risk scores (PRSs) have been used to combine the effects of variants with small effects identified by genome-wide association studies. We explore the potential for using pathway-specific PRSs as predictors of early changes in Alzheimer's disease (AD)-related biomarkers and cognitive function. Participants were from the Wisconsin Registry for Alzheimer's Prevention, a longitudinal study of adults who were cognitively asymptomatic at enrollment and enriched for a parental history of AD. Using genes associated with AD in the International Genomics of Alzheimer's Project's meta-analysis, we identified clusters of genes that grouped into pathways involved in amyloid-β (Aβ) deposition and neurodegeneration: Aβ clearance, cholesterol metabolism, and immune response. Weighted pathway-specific and overall PRSs were developed and compared to APOE alone. Mixed models were used to assess whether each PRS was associated with cognition in 1,200 individuals, cerebral Aβ deposition measured using amyloid ligand (Pittsburgh compound B) positron emission imaging in 168 individuals, and cerebrospinal fluid Aβ deposition, neurodegeneration, and tau pathology in 111 individuals, with replication performed in an independent sample. We found that PRSs including APOE appeared to be driven by the inclusion of APOE, suggesting that the pathway-specific PRSs used here were not more predictive than an overall PRS or APOE alone. However, pathway-specific PRSs could prove to be useful as more knowledge is gained on the genetic variants involved in specific biological pathways of AD.

Pazopanib Reduces Phosphorylated Tau Levels and Alters Astrocytes in a Mouse Model of Tauopathy. - Javidnia, Monica; Hebron, Michaeline L; Xin, Yue; Kinney, Nikolas G; Moussa, Charbel E-H (J Alzheimers Dis, 2017)
Hyperphosphorylation and aggregation of tau protein is a critical factor in many neurodegenerative diseases. These diseases are increasing in prevalence, and there are currently no cures. Previous work from our group and others has shown that tyrosine kinase inhibitors (TKIs) can stimulate autophagy, decrease pathological proteins, and improve symptoms in models of neurodegeneration. Here we examined the role of pazopanib in mouse models that express either human mutant P301L tau (TauP301L) or triple mutant amyloid precursor protein (3x-AβPP). The TauP301L mouse expresses P301L tau under the control of a prion promoter in both neurons and astrocytes, reminiscent of some human tauopathies. Pazopanib crosses the blood-brain barrier with no detectable peripheral off-side effects, and decreases p-tau in TauP301L mice. Pazopanib reaches a brain concentration sufficient for inhibition of several tyrosine kinases, including vascular endothelial growth factor receptors (VEGFRs). Further, pazopanib does not affect microglia but reduces astrocyte levels toward nontransgenic controls in TauP301L mice. Pazopanib does not alter amyloid beta levels or astrocytes in 3x-AβPP mice but modulates a number of inflammatory markers (IP-10, MIP-1α, MIP-1β, and RANTES). These data suggest that pazopanib may be involved in p-tau clearance and modulation of astrocytic activity in models of tauopathies.

PE859, A Novel Curcumin Derivative, Inhibits Amyloid-β and Tau Aggregation, and Ameliorates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8. - Okuda, Michiaki; Fujita, Yuki; Hijikuro, Ichiro; Wada, Mei; Uemura, Takuya; Kobayashi, Yukako; Waku, Tomonori; Tanaka, Naoki; Nishimoto, Takaaki; Izumi, Yasuhiko; Kume, Toshiaki; Akaike, Akinori; et al. (J Alzheimers Dis, 2017)
Aggregation of amyloid-β (Aβ) and tau plays a crucial role in the onset and progression of Alzheimer's disease (AD). Therefore, the inhibition of Aβ and tau aggregation may represent a potential therapeutic target for AD. Herein, we designed and synthesized both Aβ and tau dual aggregation inhibitors based on the structure of curcumin and developed the novel curcumin derivative PE859. In this study, we investigated the inhibitory activity of PE859 on Aβ aggregationin vitro and the therapeutic effects of PE859 on cognitive dysfunction via dual inhibition of Aβ and tau aggregation in vivo. PE859 inhibited Aβ aggregation in vitro and protected cultured cells from Aβ-induced cytotoxicity. Furthermore, PE859 ameliorated cognitive dysfunction and reduced the amount of aggregated Aβ and tau in brains of senescence-accelerated mouse prone 8 (SAMP8). These results warrant consideration of PE859 as a candidate drug for AD.

People with Dementia Can Learn Compensatory Movement Maneuvers for the Sit-to-Stand Task: A Randomized Controlled Trial. - Werner, Christian; Wiloth, Stefanie; Lemke, Nele Christin; Kronbach, Florian; Jansen, Carl-Philipp; Oster, Peter; Bauer, Jürgen M; Hauer, Klaus (J Alzheimers Dis, 2017)
BACKGROUND: A complex motor skill highly relevant to mobility in everyday life (e.g., sit-to-stand [STS] transfer) has not yet been addressed in studies on motor learning in people with dementia (PwD). OBJECTIVE: To determine whether a dementia-specific motor learning exercise program enables PwD to learn compensatory STS maneuvers commonly taught in geriatric rehabilitation therapy to enhance patients' STS ability. METHODS: Ninety-seven patients with mild-to-moderate dementia (Mini-Mental State Examination: 21.9±2.9 points) participated in a double-blinded, randomized, placebo-controlled trial with 10-week intervention and 3-month follow-up period. The intervention group (IG, n = 51) underwent a motor learning exercise program on compensatory STS maneuvers specifically designed for PwD. The control group (CG, n = 46) performed a low-intensity motor placebo activity. Primary outcomes were scores of the Assessment of Compensatory Sit-to-stand Maneuvers in People with Dementia (ACSID), which covers the number of recalled and initiated, and of effectively performed compensatory STS maneuvers. Secondary outcomes included temporal and kinematic STS characteristics measured by a body-fixed motion sensor (BFS, DynaPort® Hybrid). RESULTS: The IG significantly improved in all ACSID scores compared to the CG (p < 0.001). Secondary analysis confirmed learning effects for all BFS-based outcomes (p < 0.001-0.006). Learning gains were sustained during follow-up for most outcomes. CONCLUSION: People with mild-to-moderate dementia can learn and retain compensatory STS maneuvers in response to a dementia-specific motor learning exercise program. This is the first study that demonstrated preserved motor learning abilities in PwD by using a motor skill highly relevant to everyday life.

Peripheral versus Central Index of Metabolic Dysfunction and Associations with Clinical and Pathological Outcomes in Alzheimer's Disease. - McLimans, Kelsey E; Webb, Joseph L; Anantharam, Vellareddy; Kanthasamy, Anumantha; Willette, Auriel A (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Insulin-like growth factor binding protein 2 (IGFBP-2) regulates blood glucose levels, facilitates hippocampal synaptic plasticity and may have a predictive value for Alzheimer's disease (AD) diagnosis. METHODS: IGFBP-2 levels were studied in plasma in 566 subjects and in cerebrospinal fluid (CSF) in 245 subjects across the AD spectrum from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Variants in the IGFBP-2 gene were examined. Linear mixed modeling in SPSS tested main effects of IGFBP-2 and interactions with APOE4 on neurocognitive indices and biomarkers. Voxel-wise regression was used to gauge IGFBP-2 and regional grey matter and glucose metabolism associations. RESULTS: Each point increase in IGFBP-2 corresponded to a three times greater likelihood of having mild cognitive impairment (MCI) or AD. IGFBP-2 showed beneficial associations with respect to cognitive scores in individuals with two APOE4 alleles. Higher IGFBP-2 predicted higher insulin resistance, but not CSF amyloid or tau. Voxel-wise analyses showed that plasma IGFBP-2 predicted lower grey matter volume and FDG metabolism in a large area spanning the frontal, temporal, and occipital lobes. CSF IGFBP-2 levels showed similar voxel-wise analysis results, but were uniquely associated with CSF amyloid and tau. Analysis of single nucleotide polymorphisms (SNPs) in IGFBP-2 showed that subjects carrying risk alleles versus common alleles had increased risk of AD and lower memory scores. Voxel-wise analyses of these SNPs also implicated the hippocampus and prefrontal cortex. CONCLUSIONS: IGFBP-2 is associated with AD risk and outcomes; plasma IGFBP-2 provides stronger predictive power for brain outcomes, while CSF IGFBP-2 provides improved predictive accuracy for AD CSF biomarkers.

Persistence with Antihypertensive Drugs in Patients with Hypertension and Dementia in Germany. - Jacob, Louis; Adam-Schnepf, Leonie; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension, a chronic disease resulting from aging and its related physiopathological dysregulations, is often associated with dementia. OBJECTIVE: The goal was to analyze the persistence with antihypertensive drugs in patients affected by both hypertension and dementia in Germany. METHODS: This study included hypertension patients who were initially treated with antihypertensive drugs in 1,262 general practices in Germany between January 2013 and December 2015 (index date). Patients with hypertension and comorbid dementia were matched (1 : 1) to patients without dementia by age, gender, type of residence (nursing home versus home-care setting), physician, and initial antihypertensive therapy, using a propensity score method. The primary outcome was the rate of patients without treatment discontinuation with antihypertensive drugs in cases and controls in the 12 months following the index date. Cox regressions were used to determine the impact of dementia on persistence with antihypertensive treatment. RESULTS: This study included 2,191 patients with hypertension and comorbid dementia and 2,191 patients with hypertension but without dementia. The mean age was 79.3 years (SD = 10.3 years) in both groups. Twelve months after initiation of antihypertensive therapy, 73.5% of cases and 69.5% of controls were persistent (p < 0.001). Dementia was associated with a significant decrease in the risk of non-persistence with antihypertensive drugs in the entire population (HR = 0.86, 95% CI: 0.79-0.93). This finding was corroborated in five different subgroups (age ≤60 years, age 61-70 years, men, women, and patients living in home-care settings). CONCLUSIONS: Dementia was found to be a protective factor for persistence with antihypertensive drugs in Germany.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Physical Exercise Moderates the Relationship of Apolipoprotein E (APOE) Genotype and Dementia Risk: A Population-Based Study. - Fenesi, Barbara; Fang, Hanna; Kovacevic, Ana; Oremus, Mark; Raina, Parminder; Heisz, Jennifer J (J Alzheimers Dis, 2017)
Genetics and lifestyle independently determine dementia risk, but the interaction is unclear. We assessed the interactive relationship of apolipoprotein E (APOE) genotype and physical exercise on dementia risk over a 5-year period in 1,646 older adults from the Canadian Study of Health and Aging who were dementia-free at baseline. Physical exercise moderated the relationship between genotype and dementia (p < 0.01). Specifically, for APOE ɛ4 non-carriers, the odds of developing dementia were higher in non-exercisers than exercisers (OR = 1.98, 95% CI = 1.44, 2.71, p < 0.001), whereas, for APOE ɛ4 carriers, the odds of developing dementia were not significantly different between non-exercisers and exercisers (OR = 0.71, 95% CI = 0.46, 1.31, p = 0.34). Given that most individuals are not at genetic risk, physical exercise may be an effective strategy for preventing dementia.

Physical Exercise with Music Maintains Activities of Daily Living in Patients with Dementia: Mihama-Kiho Project Part 21. - Satoh, Masayuki; Ogawa, Jun-Ichi; Tokita, Tomoko; Nakaguchi, Noriko; Nakao, Koji; Kida, Hirotaka; Tomimoto, Hidekazu (J Alzheimers Dis, 2017)
BACKGROUND: Recent studies suggest that combined non-pharmacological interventions are more beneficial than single interventions for primary and secondary prevention of dementia. We previously reported enhanced effects of physical exercise with music (ExM) on cognitive function in normal elderly people compared to exercise alone. OBJECTIVE: To identify if ExM improves cognitive function and activities of daily livings (ADLs) in dementia patients over cognitive stimulation (CS). METHODS: We enrolled 85 patients with mild to moderate dementia. Forty-three subjects performed ExM developed by the Yamaha Music Foundation, and 42 subjects performed cognitive stimulation using portable game consoles and drills involving easy calculations, mazes, and mistake-searching in pictures. Interventions were performed once a week for 40 minutes. Before and after the six-month intervention, patients were assessed using neuropsychological batteries, and ADLs were assessed by patients' caregivers using the functional independence measure (FIM). Voxel-based specific regional analysis system for Alzheimer's disease (VSRAD) was used to assess medial temporal lobe atrophy. RESULTS: Twenty-three subjects dropped out during the intervention. Thirty-one patients from each group were analyzed. Post-intervention, both groups showed significantly improved visuospatial function. Significant benefits were observed in psychomotor speed or memory in the ExM or CS groups, respectively. FIM scores, reflecting ADLs, and VSRAD scores were significantly preserved in the ExM group, but significantly worsened in the CS group. CONCLUSIONS: ExM produced greater positive effects on cognitive function and ADLs in patients with mild to moderate dementia than CS, excluding memory. Optimal interventions for dementia will likely be achieved by combining ExMand CS.

The Pitfall of Behavioral Variant Frontotemporal Dementia Mimics Despite Multidisciplinary Application of the FTDC Criteria. - Krudop, Welmoed A; Dols, Annemieke; Kerssens, Cora J; Eikelenboom, Piet; Prins, Niels D; Möller, Christiane; Schouws, Sigfried; Rhebergen, Didi; van Exel, Eric; van der Flier, Wiesje M; Sikkes, Sietske; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The behavioral variant of frontotemporal dementia (bvFTD) has a broad differential diagnosis including other neurological and psychiatric disorders. Psychiatric misdiagnoses occur in up to 50% of bvFTD patients. Numbers on misdiagnosis of bvFTD in psychiatric disorders are lacking. OBJECTIVE: The aim of our study was to investigate the frequency and characteristics of bvFTD misdiagnoses in psychiatric disorders and other neurologic disorders. METHODS: Thirty-five patients with a (possible or probable) bvFTD diagnosis made by specialized memory clinic neurologists were included. Change in diagnosis after consulting a psychiatrist at baseline was recorded as well as change in diagnosis after two years of multidisciplinary neuropsychiatric follow-up. Differences in cognitive and behavioral profiles were investigated per diagnostic group after follow-up (bvFTD, psychiatry, other neurologic disorders). Clinical profiles are described in detail. RESULTS: In 17 patients (48.5%), the bvFTD baseline diagnosis changed: Two at baseline after psychiatric consultation, and 15 after two years of multidisciplinary follow-up. Eleven (64.5%) of these 17 patients (31.5% of total) were reclassified with a psychiatric diagnosis. We found no differences for cognitive baseline profiles between patients with bvFTD versus psychiatric diagnoses. CONCLUSION: In almost half of cases, the initial bvFTD diagnosis was changed after follow-up, most often into a psychiatric disorder. A multidisciplinary neuropsychiatric approach in the diagnostic process of bvFTD results in the identification of treatable disorders. Our findings illustrate a limited specificity of the [18F]FDG-PET-scan and the bvFTD criteria in a neuropsychiatric cohort, especially combined with certain clinical symptoms, like disinhibition, apathy, or loss of empathy.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Pleiotropic Effect of Human ApoE4 on Cerebral Ceramide and Saturated Fatty Acid Levels. - den Hoedt, Sandra; Janssen, Carola I F; Astarita, Giuseppe; Piomelli, Daniele; Leijten, Frank P J; Crivelli, Simone M; Verhoeven, Adrie J M; De Vries, Helga E; Walter, Jochen; Martinez-Martinez, Pilar; Sijbrands, Eric J G; Kiliaan, Amanda J; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) is known for its role in lipid trafficking and the ɛ4 allele is a risk factor for late onset Alzheimer's disease (AD). Recently, aberrant ceramide and fatty acid (FA) levels have been implicated in AD. OBJECTIVE: To determine the specific effects of human ApoE4 (hE4) on cerebral ceramide and FA content during chow or a high fat/high cholesterol (HFHC) diet. METHODS: Cerebral ceramide and FA profiles were determined by LC-MSMS in 15-month-old female wild-type (WT), ApoE-knockout (E0), and hE4-knockin mice fed chow or a HFHC diet for 3 months. mRNA levels of genes involved in ceramide and FA metabolism were determined by qPCR. RESULTS: Similar to E0, hE4 mice displayed lower cerebral total ceramide, Cer16 : 0, and Cer24 : 1 levels than WT mice on both diets. Akin to WT mice, hE4 mice had lower total and saturated FA levels on chow than E0 mice. The HFHC diet significantly increased total and saturated FA levels in hE4 mice. Chow-fed hE4 mice showed lower mRNA levels of ceramide synthase (CerS) 6, acid sphingomyelinase, and of most ceramide and FA transporters than WT and E0 mice. The HFHC diet downregulated the expression of CerSs in hE4 and WT mice, and of ceramide and FA transporters in WT mice, but not in E0 mice. CONCLUSION: hE4 reduced cerebral ceramide levels to levels observed in E0 mice independent of diet. The HFHC diet increased cerebral FA levels in hE4 mice. This was associated with alterations in the expression of ceramide and FA transporters specifically in hE4 mice.

Positive and Negative Experiences of Social Support and Risk of Dementia in Later Life: An Investigation Using the English Longitudinal Study of Ageing. - Khondoker, Mizanur; Rafnsson, Snorri Bjorn; Morris, Stephen; Orrell, Martin; Steptoe, Andrew (J Alzheimers Dis, 2017)
BACKGROUND: Having a network of close relationships may reduce the risk of developing dementia. However, social exchange theory suggests that social interaction entails both rewards and costs. The effects of quality of close social relationships in later life on the risk of developing dementia are not well understood. OBJECTIVE: To investigate the effects of positive and negative experiences of social support within key relationships (spouse or partner, children, other immediate family, and friends) on the risk of developing dementia in later life. METHODS: We analyzed 10-year follow up data (2003/4 to 2012/13) in a cohort of 10,055 dementia free (at baseline) core participants aged 50 years and over from the English Longitudinal Study of Ageing (ELSA). Incidence of dementia was identified from participant or informant reported physician diagnosed dementia or overall score of informant-completed IQCODE questionnaire. Effects of positive and negative experiences of social support measured at baseline on risk of developing dementia were investigated using proportional hazards regression accommodating interval censoring of time-to-dementia. RESULTS: There were 340 (3.4%) incident dementia cases during the follow-up. Positive social support from children significantly reduced the risk of dementia (hazard ratio, HR = 0.83, p = 0.042, 95% CI: 0.69 to 0.99). Negative support from other immediate family (HR = 1.26, p = 0.011, CI: 1.05 to 1.50); combined negative scores from spouse and children (HR = 1.23, p = 0.046, CI: 1.004 to 1.51); spouse, children, and other family (HR = 1.27, p = 0.021, CI = 1.04 to 1.56); other family & friends (HR = 1.25, p = 0.033, CI: 1.02 to 1.55); and the overall negative scores (HR = 1.31, p = 0.019, CI: 1.05 to 1.64) all were significantly associated with increased risk of dementia. CONCLUSION: Positive social support from children is associated with reduced risk of developing dementia whereas experiences of negative social support from children and other immediate family increase the risk. Further research is needed to better understand the causal mechanisms that drive these associations.

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia. - Wucherer, Diana; Eichler, Tilly; Hertel, Johannes; Kilimann, Ingo; Richter, Steffen; Michalowsky, Bernhard; Thyrian, Jochen René; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2017)
BACKGROUND: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD). OBJECTIVE: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized, controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in Germany. The comprehensive baseline assessment includes a home medication review. The present analyses are based on the data from 448 study participants (age 70+, DemTect <9). PIMs were identified using the list of Potentially Inappropriate Medications in the Elderly (Priscus). RESULTS: (1) A total of 99 study participants (22%) received at least one PIM. The highest prevalence was found for antidepressants, benzodiazepines, and analgetics. The most frequently prescribed PIMs were amitriptyline, etoricoxib, and doxazosin. (2) Use of a PIM was significantly associated with a diagnosis of a mental or behavioral disorder. CONCLUSIONS: The prescription rate of PIMs for community-dwelling PWD was comparable with the rates found for the general population of older people in Germany (20-29%). Antidepressants with anticholinergic properties and long-acting benzodiazepines were the most prescribed PIMs, despite having an unfavorable benefit-risk ratio. This high prevalence of PIM prescriptions in a vulnerable population of PWD indicates that standard care for dementia should include careful medication review and management.

Predicting Development of Amyotrophic Lateral Sclerosis in Frontotemporal Dementia. - Van Langenhove, Tim; Piguet, Olivier; Burrell, James R; Leyton, Cristian; Foxe, David; Abela, Melissa; Bartley, Lauren; Kim, Woojin S; Jary, Eve; Huang, Yue; Dobson-Stone, Carol; Kwok, John B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: A proportion of patients with frontotemporal dementia (FTD) also develop amyotrophic lateral sclerosis (ALS). OBJECTIVE: We aimed to establish the risk of developing ALS in patients presenting with FTD and to identify the relevant clinical variables associated with progression from FTD to FTD-ALS. METHODS: Of 218 consecutive patients with FTD, 10.1% had a dual FTD-ALS diagnosis at presentation. The remaining 152 FTD patients with follow-up of at least 12 months were included in the present study. We calculated the rate of progression to FTD-ALS and compared the baseline characteristics of FTD patients who developed ALS to those who did not develop ALS. RESULTS: Five percent of FTD patients developed ALS. The incidence rate of ALS was 6.7/100 patient-years in patients with FTD symptoms since 1 year, which declined with duration of FTD symptoms. No FTD patients developed ALS after 5 years. Five out of 8 FTD patients who developed ALS had presented with a mixed behavioral variant FTD and progressive non-fluent aphasia (bvFTD+PNFA) phenotype, 2 with bvFTD, and 1 with PNFA. Progression to FTD-ALS was significantly more frequent in patients with bvFTD+PNFA compared to those without this phenotype (p < 0.0001, OR 38.3, 95% CI: 7.3 to 199.2), and in FTD patients who carried the C9orf72 repeat expansion compared to those without the repeat expansion (p = 0.02, OR 8.0, 95% CI: 1.7 to 38.6). CONCLUSIONS: FTD patients with a mixed bvFTD+PNFA phenotype and with a C9orf72 repeat expansion should be closely monitored for the possible development of ALS. The risk of developing ALS in FTD appears to decline with the duration of FTD symptoms.

Prediction Model of Conversion to Dementia Risk in Subjects with Amnestic Mild Cognitive Impairment: A Longitudinal, Multi-Center Clinic-Based Study. - Jang, Hyemin; Ye, Byoung Seok; Woo, Sookyoung; Kim, Sun Woo; Chin, Juhee; Choi, Seong Hye; Jeong, Jee Hyang; Yoon, Soo Jin; Yoon, Bora; Park, Kyung Won; Hong, Yun Jeong; Kim, Hee Jin; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) have an increased risk of dementia. However, conversion rate varies. Therefore, predicting the dementia conversion in these patients is important. OBJECTIVE: We aimed to develop a nomogram to predict dementia conversion in aMCI subjects using neuropsychological profiles. METHODS: A total of 338 aMCI patients from two hospital-based cohorts were used in analysis. All patients were classified into 1) verbal, visual, or both, 2) early or late, and 3) single or multiple-domain aMCI according to the modality, severity of memory dysfunction, and multiplicity of involved cognitive domains, respectively. Patients were followed up, and conversion to dementia within 3 years was defined as the primary outcome. Our patients were divided into a training data set and a validation data set. The associations of potential covariates with outcome were tested, and nomogram was constructed by logistic regression model. We also developed another model with APOE data, which included 242 patients. RESULTS: In logistic regression models, both modalities compared with visual only (OR 4.44, 95% CI 1.83-10.75, p = 0.001), late compared to early (OR 2.59, 95% CI 1.17-5.72, p = 0.019), and multiple compared to single domain (OR 3.51, 95% CI 1.62-7.60, p = 0.002) aMCI were significantly associated with dementia conversion within 3 years. A nomogram incorporating these clinical variables was constructed on the training data set and validated on the validation data set. Both nomograms with and without APOE data showed good prediction performance (c-statistics ≥ 0.75). CONCLUSIONS: This study showed that several neuropsychological profiles of aMCI are significantly associated with imminent dementia conversion, and a nomogram incorporating these clinical subtypes is simple and useful to help to predict disease progression.

Predictors of Discharge Destinations and Three-Month Evolution of Patients Initially Hospitalized in a Cognitive Behavioral Unit. - Pongan, Elodie; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Federico, Denis; Sellier, Claire; Auguste, Nicolas; Fabre, Florence; Laurent, Bernard; Trombert-Paviot, Béatrice; Rouch, Isabelle (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies showed that a third of patients living at home entered an institution after hospitalization in Cognitive and Behavioral Units (CBUs). OBJECTIVE: The main objective of this study was to identify predictors of discharge destination for these patients. The secondary objective was to estimate whether institutionalization can have an impact on a patient's long-term prognosis. METHODS: The study population was selected from the EVITAL study and included 140 participants living at home before hospitalization in CBUs. Factors favoring nursing-home admission were investigated and the impact of discharge destinations (i.e., home or nursing home) on patients' prognosis was examined. RESULTS: Institutionalized patients were more likely to be women (F = 4.7; p = 0.03), with a higher dementia severity (F = 9.82; p = 0.007), often living alone (F = 19.69; p = 0.001), with a caregiver other than spouse (F = 8.93; p = 0.003), and with a higher patient quality of life (QoL) according to the caregiver (F = 11.73; p = 0.001). When using multivariate logistic linear regressions, we showed a relationship between marital status (OR = 0.19, 95% CI: 0.08-0.43, p < 0.001), dementia severity (OR = 0.15, 95% CI: 0.03-0.79, p = 0.03), QoL (OR = 0.88, 95% CI: 0.79-0.98, p = 0.017), and institutionalization. At three months, a higher overall rate of rehospitalization (F = 12.21; p < 0.001) and rehospitalization for behavioral and psychological symptoms of dementia (F = 6.76; p = 0.006) were observed for patients staying at home after CBU discharge. CONCLUSION: Our study allows for a better understanding of the institutionalization risk factors of the patients hospitalized in CBUs. Identification of these factors could help clinicians to better support patients and to help the transition to be smoother. Moreover, our results suggest that prognosis of institutionalized patients is not unfavorable when compared with patients staying at home.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Prevalence of Use of Cardiovascular Drugs in Dementia Patients Treated in General Practices in Germany. - Jacob, Louis; Bohlken, Jens; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is a chronic disease associated with numerous cardiovascular disorders. OBJECTIVE: To analyze the prevalence of cardiovascular drug use in dementia patients treated in general practices in Germany. METHODS: The present study included patients who were diagnosed with dementia (Alzheimer's disease, vascular dementia, or unspecified dementia) in 2015. The main outcome measure was the proportion of patients using cardiovascular drugs. Demographical and clinical variables included age, sex, dementia type, and cardiovascular co-diagnoses. A multivariate logistic regression model was used to analyze the association between cardiovascular drug use and these variables. RESULTS: We identified 7,987 and 1,268 dementia patients with and without prescriptions for cardiovascular drugs, respectively. The share of individuals who received cardiovascular treatments was 86.3%. Diuretics (20.9%), beta blocking agents (20.0%), and ACE inhibitors (17.4%) were the three most commonly prescribed types of medications. Patients between the ages of 71-80 (OR = 1.59), 81-90 (OR = 1.61), and over 90 years (OR = 1.48) were more likely to receive cardiovascular drugs than patients under the age of 70 years. Moreover, compared to those with unspecified dementia, individuals with Alzheimer's disease had a lower chance while those with vascular dementia had a higher chance of being prescribed these drugs (ORs equal to 0.81 and 1.22, respectively). Finally, we found a positive association between the use of cardiovascular drugs and all co-diagnoses (ORs ranging from 1.23 to 7.12). CONCLUSION: The prevalence of cardiovascular drug use in dementia patients was around 86%. This use was significantly associated with such factors as age, type of dementia, and co-diagnoses.

Psychotic Symptoms Associated with Poor Renal Function in Mild Cognitive Impairment and Dementias. - Kunschmann, Ralf; Busse, Stefan; Frodl, Thomas; Busse, Mandy (J Alzheimers Dis, 2017)
Patients suffering from cognitive decline such as mild cognitive impairment or neurodegenerative disorders including Alzheimer's dementia, vascular dementia, frontotemporal dementia, and Lewy body dementia are often accompanied by symptoms like psychosis, depression, agitation, and apathy. Aging increases not only the prevalence of dementia but also the development of kidney disorders, which had emerged as possible risk factor of cognitive impairment and dementia. However, a contribution of renal dysfunction to psychosis associated with cognitive decline remains to be investigated. We addressed the question whether patients diagnosed with mild cognitive impairment or dementia and co-symptoms show alterations in serum parameters. Analyzing 309 patients in total, we detected a positive correlation between the occurrence of psychotic symptoms and increased retention parameters in serum, including creatinine and urea levels and the estimated glomerular filtration rates. This was in particular detected in female patients. In male patients, psychotic symptoms were associated with an increased number of leukocytes in blood. We propose that clinicians should be aware of psychotic symptoms in patients with reduced cognitive functions that could be associated with changes in the retention parameters.

Pupillary Responses as a Biomarker of Early Risk for Alzheimer's Disease. - Granholm, Eric L; Panizzon, Matthew S; Elman, Jeremy A; Jak, Amy J; Hauger, Richard L; Bondi, Mark W; Lyons, Michael J; Franz, Carol E; Kremen, William S (J Alzheimers Dis, 2017)
Task-evoked pupillary responses may be a psychophysiological biomarker of early risk for mild cognitive impairment (MCI) and Alzheimer's disease (AD). Pupil dilation during cognitive tasks reflects cognitive effort until compensatory capacity is surpassed and performance declines are manifest, and reflects activation in the locus coeruleus, where degenerative changes have been found in the earliest stages of AD. We recorded pupillary responses during digit span recall in 918 participants ages 56-66. Despite normal performance, amnestic single-domain MCI (S-MCI) participants showed greater pupil dilation than non-amnestic S-MCI and cognitively normal (CN) participants at lower cognitive loads. Multi-domain MCI (M-MCI) participants failed to modulate effort across cognitive loads and showed poorer performance. Pupillary responses differentiated MCI and CN groups. Amnestic S-MCI participants required compensatory effort to maintain performance, consistent with increased risk for decline. Greater effort in CN individuals might indicate risk for MCI. Results are consistent with dysfunction in locus coeruleus-linked brain systems. This brief task shows promise as a biomarker for early MCI and AD risk prediction.

Quantitative 3D Telomeric Imaging of Buccal Cells Reveals Alzheimer's Disease-Specific Signatures. - Garcia, Angeles; Mathur, Shubha; Kalaw, Maria Carmela; McAvoy, Elizabeth; Anderson, James; Luedke, Angela; Itorralba, Justine; Mai, Sabine (J Alzheimers Dis, 2017)
This study validates and expands on our previous work that assessed three-dimensional (3D) nuclear telomere profiling in buccal cells of Alzheimer's disease (AD) patients and non-AD controls (Mathur et al., J Alzheimers Dis 39, 35-48, 2014). While the previous study used age- and gender-matched caregiver controls, the current study consented a new cohort of 44 age- and gender-matched healthy non-caregiver controls and 44 AD study participants. 3D telomeric profiles of buccal cells of AD patients and their non-AD controls were examined with participant information blinded to the analysis. In agreement with our previous study, we demonstrate that 3D telomeric profiles allow for the distinction between AD and non-AD individuals. This validation cohort provides an indication that the total number of 3D telomeric signals and their telomere lengths may be a suitable biomarker to differentiate between AD and non-AD and between mild, moderate, and severe AD. Further studies with larger sample sizes are required to move this technology further toward the clinic.

Quantitative Comparison of Dense-Core Amyloid Plaque Accumulation in Amyloid-β Protein Precursor Transgenic Mice. - Liu, Peng; Reichl, John H; Rao, Eshaan R; McNellis, Brittany M; Huang, Eric S; Hemmy, Laura S; Forster, Colleen L; Kuskowski, Michael A; Borchelt, David R; Vassar, Robert; Ashe, Karen H; Zahs, Kathleen R (J Alzheimers Dis, 2017)
There exist several dozen lines of transgenic mice that express human amyloid-β protein precursor (AβPP) with Alzheimer's disease (AD)-linked mutations. AβPP transgenic mouse lines differ in the types and amounts of Aβ that they generate and in their spatiotemporal patterns of expression of Aβ assemblies, providing a toolkit to study Aβ amyloidosis and the influence of Aβ aggregation on brain function. More complete quantitative descriptions of the types of Aβ assemblies present in transgenic mice and in humans during disease progression should add to our understanding of how Aβ toxicity in mice relates to the pathogenesis of AD. Here, we provide a direct quantitative comparison of amyloid plaque burdens and plaque sizes in four lines of AβPP transgenic mice. We measured the fraction of cortex and hippocampus occupied by dense-core plaques, visualized by staining with Thioflavin S, in mice from young adulthood through advanced age. We found that the plaque burdens among the transgenic lines varied by an order of magnitude: at 15 months of age, the oldest age studied, the median cortical plaque burden in 5XFAD mice was already ∼4.5 times that of 21-month-old Tg2576 mice and ∼15 times that of 21-24-month-old rTg9191 mice. Plaque-size distributions changed across the lifespan in a line- and region-dependent manner. We also compared the dense-core plaque burdens in the mice to those measured in a set of pathologically-confirmed AD cases from the Nun Study. Cortical plaque burdens in Tg2576, APPSwePS1ΔE9, and 5XFAD mice eventually far exceeded those measured in the human cohort.

Quantitative Erythrocyte Omega-3 EPA Plus DHA Levels are Related to Higher Regional Cerebral Blood Flow on Brain SPECT. - Amen, Daniel G; Harris, William S; Kidd, Parris M; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: The interrelationships between omega-3 fatty acids status, brain perfusion, and cognition are not well understood. OBJECTIVE: To evaluate if SPECT brain imaging of cerebral perfusion and cognition varies as a function of omega-3 fatty acid levels. METHODS: A random sample of 166 study participants was drawn from a psychiatric referral clinical for which erythrocyte quantification of omega-3 eicosapentaenoic acid (EPA) plus docosahexaenoic acid (DHA) (the Omega-3 Index) was available. Quantitative brain SPECT was done on 128 regions based on a standard anatomical Atlas Persons with erythrocyte EPA+DHA concentrations were dichotomized based on membership in top 50th percentile versus bottom 50th percentile categories. Two-sample t-tests were done to identify statistically significant differences in perfusion between the percentile groups. Partial correlations were modeled between EPA+DHA concentration and SPECT regions. Neurocognitive status was assessed using computerized testing (WebNeuro) and was separately correlated to cerebral perfusion on brain SPECT imaging and omega-3 EPA+DHA levels. RESULTS: Partial correlation analyses showed statistically significant relationships between higher omega-3 levels and cerebral perfusion were in the right parahippocampal gyrus (r = 0.20, p = 0.03), right precuneus (r = 0.20, p = 0.03), and vermis subregion 6 (p = 0.21, p = 0.03). Omega-3 Index levels separately correlated to the feeling subsection of the WebNeuro (r = 0.25, p = 0.01). CONCLUSION: Quantitative omega-3 EPA+DHA erythrocyte concentrations are independently correlated with brain perfusion on SPECT imaging and neurocognitive tests. These results have implications for the role of omega-3 fatty acids toward contributing to cognitive reserve.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study of Oral ELND005 (scyllo-Inositol) in Young Adults with Down Syndrome without Dementia. - Rafii, Michael S; Skotko, Brian G; McDonough, Mary Ellen; Pulsifer, Margaret; Evans, Casey; Doran, Eric; Muranevici, Gabriela; Kesslak, Patrick; Abushakra, Susan; Lott, Ira T (J Alzheimers Dis, 2017)
BACKGROUND: ELND005 (scyllo-Inositol; cyclohexane-1,2,3,4,5,6-hexol) has been evaluated as a potential disease-modifying treatment for Alzheimer's disease (AD). Individuals with Down syndrome (DS) have an increased risk for developing AD dementia. OBJECTIVE: To evaluate the safety and tolerability of ELND005 and to determine its pharmacokinetics (PK) and relationship between PK parameters, safety outcome measures, and exploratory efficacy outcome measures in young adults with DS without dementia. METHODS: This was a prospective, randomized, double-blind, placebo-controlled, parallel-group, three-arm, multicenter Phase II study of the safety and pharmacokinetics of ELND005 administered orally for 4 weeks (ClinicalTrials.gov NCT01791725). Participants who met study eligibility criteria were randomly assigned in a 2 : 1:1 ratio to receive ELND005 at either 250 mg twice daily (BID) or 250 mg once daily (QD) or matching placebo for 4 weeks. RESULTS: There were no apparent treatment group-related trends on cognitive or behavioral measures and there were no SAEs and no deaths in the study. Overall, mean changes from baseline in clinical laboratory parameters, vital sign measurements, electrocardiogram results, and other physical findings were unremarkable. ELND005 accumulation averaged approximately 2-fold with QD dosing, and 3- to 4-fold with BID dosing. CONCLUSION: Overall, treatment of adults with DS with ELND005 at both doses was well tolerated, achieved measurable blood levels and demonstrated no safety findings. Further studies will be needed to test efficacy.

Rare Genetic Variant in SORL1 May Increase Penetrance of Alzheimer's Disease in a Family with Several Generations of APOE-ɛ4 Homozygosity. - Louwersheimer, Eva; Cohn-Hokke, Petra E; Pijnenburg, Yolande A L; Weiss, Marjan M; Sistermans, Erik A; Rozemuller, Annemieke J; Hulsman, Marc; van Swieten, John C; van Duijn, Cock M; Barkhof, Frederik; Koene, Teddy; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The major genetic risk factor for late onset Alzheimer's disease (AD) is the APOE-ɛ4 allele. However, APOE-ɛ4 homozygosity is not fully penetrant, suggesting co-occurrence of additional genetic variants. OBJECTIVE: To identify genetic factors that, next to APOE-ɛ4 homozygosity, contribute to the development of AD. METHODS: We identified a family with nine AD patients spanning four generations, with an inheritance pattern suggestive of autosomal dominant AD, with no variants in PSEN1, PSEN2, or APP. We collected DNA from four affected and seven unaffected family members and performed exome sequencing on DNA from three affected and one unaffected family members. RESULTS: All affected family members were homozygous for the APOE-ɛ4 allele. Statistical analysis revealed that AD onset in this family was significantly earlier than could be expected based on APOE genotype and gender. Next to APOE-ɛ4 homozygosity, we found that all four affected family members carried a rare variant in the VPS10 domain of the SORL1 gene, associated with AβPP processing and AD risk. Furthermore, three of four affected family members carried a rare variant in the TSHZ3 gene, also associated with AβPP processing. Affected family members presented between 61 and 74 years, with variable presence of microbleeds/cerebral amyloid angiopathy and electroencephalographic abnormalities. CONCLUSION: We hypothesize that next to APOE-ɛ4 homozygosity, impaired SORL1 protein function, and possibly impaired TSHZ3 function, further disturbed Aβ processing. The convergence of these genetic factors over several generations might clarify the increased AD penetrance and the autosomal dominant-like inheritance pattern of AD as observed in this family.

Recent Increases in Hippocampal Tau Pathology in the Aging Japanese Population: The Hisayama Study. - Hamasaki, Hideomi; Honda, Hiroyuki; Okamoto, Tsuyoshi; Koyama, Sachiko; Suzuki, Satoshi O; Ohara, Tomoyuki; Ninomiya, Toshiharu; Kiyohara, Yutaka; Iwaki, Toru (J Alzheimers Dis, 2017)
BACKGROUND: The Hisayama study is a prospective cohort study of lifestyle-related diseases that commenced in 1961. Through it, a significant increasing trend in the prevalence of Alzheimer's disease has been observed over the past 18 years. OBJECTIVES: We sought to investigate the increases in brain pathology related to Alzheimer's disease using automated MATLAB morphometric analyses for quantifying tau pathology. METHODS: We examined a series of autopsied cases from Hisayama residents obtained between 1998 and 2003 (group A: 203 cases), and between 2009 and 2014 (group B: 232 cases). We developed custom software in MATLAB to analyze abnormal tau deposits quantitatively. Specimens were immunostained with both anti-amyloid-β-protein and anti-phosphorylated tau antibodies. RESULTS: Both the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) criteria for senile plaques and Braak stage for NFT were higher in group B. Morphometric analyses of the hippocampi also revealed a trend toward increased tau pathology in both men and women over 80 years of age in group B. The increases were also significant when the subjects were examined independently according to high or low CERAD scores and in all levels of AD neuropathologic change according to the National Institute on Aging-Alzheimer's Association guidelines (2012). CONCLUSION: We revealed a recent trend of increased tauopathy in the older people, which is partly independent of amyloid-β pathology.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

The Relationship between Markers of Inflammation and Degeneration in the Central Nervous System and the Blood-Brain Barrier Impairment in Alzheimer's Disease. - Muszyński, Paweł; Kulczyńska-Przybik, Agnieszka; Borawska, Renata; Litman-Zawadzka, Ala; Słowik, Agnieszka; Klimkowicz-Mrowiec, Aleksandra; Pera, Joanna; Dziedzic, Tomasz; Mroczko, Barbara (J Alzheimers Dis, 2017)
BACKGROUND: It is known that YKL-40- a marker of glial inflammation, and VILIP-1- a marker of neuronal injury, reflect functional and structural changes in AD brains, although there is limited data concerning their potential influence on blood-brain barrier (BBB) homeostasis. OBJECTIVE: Therefore, the aim of our study was to investigate the relationship between markers of inflammation and degeneration in the central nervous system (CNS) of patients with AD and mild cognitive impairment (MCI) as well as immunological response in CNS and BBB function. METHODS: Cerebrospinal fluid (CSF) concentrations of proteins tested were determined in 45 AD patients, 18 MCI subjects, and 23 non-demented controls using ELISA method. RESULTS: CSF concentrations of YKL-40 were significantly higher in MCI and AD patients, whereas CSF levels of VILIP-1 were statistically higher in the AD group as compared to the subjects without cognitive deficits. Elevated concentrations of YKL-40 correlated significantly with increased albumin quotient and decreased Aβ42/40 ratio in AD patients and with IgG quotient in the total study group. We did not find a relationship between VILIP-1 and immunological parameters reflecting BBB dysfunction and humoral immune response. CONCLUSION: Our findings indicate that YKL-40 may contribute to decreased stability and increased permeability of BBB in AD patients. It is assumed that YKL-40 is implicated in the development of brain barriers, although its precise mechanism of action in the BBB disruption remains unrevealed. Further studies on larger groups of patients are required to confirm our hypothesis.

Relative Incidence of Seizures and Myoclonus in Alzheimer's Disease, Dementia with Lewy Bodies, and Frontotemporal Dementia. - Beagle, Alexander J; Darwish, Sonja M; Ranasinghe, Kamalini G; La, Alice L; Karageorgiou, Elissaios; Vossel, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: Patients with Alzheimer's disease (AD) are more prone to seizures and myoclonus, but relative risk of these symptoms among other dementia types is unknown. OBJECTIVE: To determine incidence of seizures and myoclonus in the three most common neurodegenerative dementias: AD, dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD). METHODS: Our institution's medical records were reviewed for new-onset unprovoked seizures and myoclonus in patients meeting criteria for AD (n = 1,320), DLB (n = 178), and FTD (n = 348). Cumulative probabilities of developing seizures and myoclonus were compared between diagnostic groups, whereas age-stratified incidence rates were determined relative to control populations. RESULTS: The cumulative probability of developing seizures after disease onset was 11.5% overall, highest in AD (13.4%) and DLB (14.7%) and lowest in FTD (3.0%). The cumulative probability of developing myoclonus was 42.1% overall, highest in DLB (58.1%). The seizure incidence rates, relative to control populations, were nearly 10-fold in AD and DLB, and 6-fold in FTD. Relative seizure rates increased with earlier age-at-onset in AD (age <50, 127-fold; 50-69, 21-fold; 70+, 2-fold) and FTD (age <50, 53-fold; 50-69, 9-fold), and relative myoclonus rates increased with earlier age-at-onset in all groups. Seizures began an average of 3.9 years after the onset of cognitive or motor decline, and myoclonus began 5.4 years after onset. CONCLUSIONS: Seizures and myoclonus occur with greater incidence in patients with AD, DLB, and FTD than in the general population, but rates vary with diagnosis, suggesting varied pathomechanisms of network hyperexcitability. Patients often experience these symptoms early in disease, suggesting hyperexcitability could be an important target for interventions.

Risk Factors for Mild Cognitive Impairment in German Primary Care Practices. - Jacob, Louis; Bohlken, Jens; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) is a common mental disorder affecting around 16% of elderly people without dementia. MCI is considered an intermediate state between normal cognition and dementia. OBJECTIVE: To analyze risk factors for the development of MCI in German primary care practices. METHODS: In total, 3,604 MCI patients and 3,604 controls without MCI were included between January 2010 and December 2015. Several disorders potentially associated with MCI were determined. Multivariate logistic regression models were fitted with MCI as a dependent variable and other disorders as potential predictors. RESULTS: The mean age was 75.2 years and 45.3% of patients were men. MCI development was found to be associated with 12 disorders: intracranial injury, anxiety disorder, depression, mental and behavioral disorders due to alcohol use, stroke, hyperlipidemia, obesity, hypertension, Parkinson's disease, sleep disorder, coronary heart disease, and diabetes with odds ratios ranging from 1.13 (diabetes) to 2.27 (intracranial injury). CONCLUSION: Intracranial injury, anxiety, and depression showed the strongest association with MCI. Further analyses are needed to gain a better understanding of the MCI risk factors.

Risk of Mortality Associated with Antipsychotic Monotherapy and Polypharmacy Among Community-Dwelling Persons with Alzheimer's Disease. - Koponen, Marjaana; Taipale, Heidi; Lavikainen, Piia; Tanskanen, Antti; Tiihonen, Jari; Tolppanen, Anna-Maija; Ahonen, Riitta; Hartikainen, Sirpa (J Alzheimers Dis, 2017)
We aimed to analyze the risk of non-cancer mortality according to duration of antipsychotic use and to compare the risk associated with polypharmacy and monotherapy among community-dwellers with Alzheimer's disease (AD). The risk of mortality between most frequently used antipsychotic drugs was compared. Data from a nationwide register-based MEDALZ study that included all 70,718 community-dwellers newly diagnosed with AD during 2005-2011 in Finland was utilized. Death, excluding cancer as direct cause of death, was extracted from Causes of Death Register. Incident antipsychotic use was compared with time without antipsychotics with Cox proportional hazard models. Antipsychotic use was associated with an increased risk of mortality (adjusted hazard ratio [aHR] 1.61; 95% Confidence Interval [CI] 1.53-1.70). The absolute difference in mortality rate was 4.58 (95% CI 4.53-4.63) deaths per 100 person-years. The risk of mortality was increased from the first days of use and attenuated gradually but remained increased even after two years of use (aHR 1.30; 95% CI 1.16-1.46). Compared with nonuse, antipsychotic polypharmacy (aHR 2.88; 95% CI 2.38-3.49) was associated with an increased risk of mortality than monotherapy (aHR 1.57; 95% CI 1.49-1.66). Haloperidol was associated with higher risk of mortality (aHR 1.52; 95% CI 1.14-2.02) and quetiapine with lower risk (aHR 0.84; 95% CI 0.75-0.94) compared with risperidone. In conclusion, the findings support current treatment guidelines on having a high threshold for antipsychotic initiation among persons with AD. Antipsychotic polypharmacy and long-term use should be avoided and drug choice should be weighed against risk/benefit evidence.

The Role of Cerebrovascular Disease on Cognitive and Functional Status and Psychosis in Severe Alzheimer's Disease. - Kim, Julia; Schweizer, Tom A; Fischer, Corinne E; Munoz, David G (J Alzheimers Dis, 2017)
BACKGROUND: The pathophysiology behind psychosis in patients with Alzheimer's disease (AD) remains unknown. Vascular risk factors have been recognized as an important modifier of the clinical presentation of AD. OBJECTIVE: The purpose of our study is to investigate the mechanism through which vascular risk factors mediate psychosis and whether or not it involves cerebrovascular lesions. METHODS: Data was provided by the National Alzheimer's Coordinating Centre. The Uniform Data Set was used to collect information on subject-reported history of vascular risk factors, clinician-reported state of cognitive performance, and presence of psychosis based on the Neuropsychiatric Inventory Questionnaire (NPI-Q). The Neuropathology Data Set was used to evaluate the presence of vascular lesions and the severity of AD pathology. Subjects with high probability of AD based on the NIA/AA Reagan criteria were included in the analysis. RESULTS: We identified 1,459 patients with high probability of AD and corresponding NPI-Q scores. We confirmed the association between hypertension and diabetes on psychosis, specifically in delusions and the co-occurrence of delusions and hallucinations. Furthermore, the presence of white matter rarefaction based on pathological evaluation was associated with hallucinations. A history of vascular risk factors was positively associated with vascular lesions. However, vascular lesions in the presence of vascular risk factors did not increase the likelihood of psychosis. Furthermore, vascular lesions were not associated with greater cognitive or functional impairments in this group with severe AD pathology. CONCLUSION: Vascular risk factors and vascular lesions are independently associated with psychosis in patients with severe AD. However, vascular lesions are not the mechanism through which vascular risk factors mediate psychosis.

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

Sample Size Estimation for Alzheimer's Disease Trials from Japanese ADNI Serial Magnetic Resonance Imaging. - Fujishima, Motonobu; Kawaguchi, Atsushi; Maikusa, Norihide; Kuwano, Ryozo; Iwatsubo, Takeshi; Matsuda, Hiroshi (J Alzheimers Dis, 2017)
BACKGROUND: Little is known about the sample sizes required for clinical trials of Alzheimer's disease (AD)-modifying treatments using atrophy measures from serial brain magnetic resonance imaging (MRI) in the Japanese population. OBJECTIVE: The primary objective of the present study was to estimate how large a sample size would be needed for future clinical trials for AD-modifying treatments in Japan using atrophy measures of the brain as a surrogate biomarker. METHODS: Sample sizes were estimated from the rates of change of the whole brain and hippocampus by the k-means normalized boundary shift integral (KN-BSI) and cognitive measures using the data of 537 Japanese Alzheimer's Neuroimaging Initiative (J-ADNI) participants with a linear mixed-effects model. We also examined the potential use of ApoE status as a trial enrichment strategy. RESULTS: The hippocampal atrophy rate required smaller sample sizes than cognitive measures of AD and mild cognitive impairment (MCI). Inclusion of ApoE status reduced sample sizes for AD and MCI patients in the atrophy measures. CONCLUSION: These results show the potential use of longitudinal hippocampal atrophy measurement using automated image analysis as a progression biomarker and ApoE status as a trial enrichment strategy in a clinical trial of AD-modifying treatment in Japanese people.

Screening for Alzheimer's Disease: Cognitive Impairment in Self-Referred and Memory Clinic-Referred Patients. - Kirsebom, Bjørn-Eivind; Espenes, Ragna; Waterloo, Knut; Hessen, Erik; Johnsen, Stein Harald; Bråthen, Geir; Aarsland, Dag; Fladby, Tormod (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive assessment is essential in tracking disease progression in AD. Presently, cohorts including preclinical at-risk participants are recruited by different means, which may bias cognitive and clinical features. We compared recruitment strategies to levels of cognitive functioning. OBJECTIVE: We investigate recruitment source biases in self-referred and memory clinic-referred patient cohorts to reveal potential differences in cognitive performance and demographics among at-risk participants. METHODS: We included 431 participants 40-80 years old. Participants were classified as controls (n = 132) or symptom group (n = 299). The symptom group comprised of subjective cognitive decline (SCD, n = 163) and mild cognitive impairment (MCI, n = 136). We compared cognitive performance and demographics in memory clinic-referrals (n = 86) to self-referred participants responding to advertisements and news bulletins (n = 179). Participants recruited by other means were excluded from analysis (n = 34). RESULTS: At symptom group level, we found significant reductions in cognitive performance in memory clinic-referrals compared to self-referrals. However, here reductions were only found within the MCI group. We found no differences in cognitive performance due to recruitment within the SCD group. The MCI group was significantly impaired compared to controls on all measures. Significant reductions in learning, and executive functions were also found for the SCD group. CONCLUSION: Regardless of recruitment method, both the SCD and MCI groups showed reductions in cognitive performance compared to controls. We found differences in cognitive impairment for memory clinic-referrals compared to self-referrals only within the MCI group, SCD-cases being equally affected irrespective of referral type.

Screening for Mild Cognitive Impairment and Dementia with Automated, Anonymous Online and Telephone Cognitive Self-Tests. - Van Mierlo, Lisa D; Wouters, Hans; Sikkes, Sietske A M; van der Flier, Wiesje M; Prins, Niels D; Bremer, Jonne A E; Koene, Teddy; Van Hout, Hein P J (J Alzheimers Dis, 2017)
BACKGROUND: Many older people worry about cognitive decline. Early cognitive screening in an anonymous and easily accessible manner may reassure older people who are unnecessarily worried about normal cognitive aging while it may also expedite help seeking in case of suspicious cognitive decline. OBJECTIVE: To develop and validate online and telephone-based automated self-tests of cognitive function. METHODS: We examined the feasibility and validity of the self-tests in a prospective study of 117 participants of whom 34 had subjective cognitive decline (SCD), 30 had mild cognitive impairment (MCI), and 53 had dementia. The ability of these self-tests to accurately distinguish MCI and dementia from SCD was examined with ROC curves. Convergent validity was examined by calculating rank correlations between the self-tests and neuropsychological tests. RESULTS: Both the online and telephone cognitive self-tests were feasible, because the majority of participants (86% and 80%, respectively) were able to complete them. The online self-test had adequate diagnostic accuracy in the screening for MCI and dementia versus SCD with an Area under the Curve (AUC) of 0.86 (95% CI: 0.78-0.93). The AUC of the MMSE was 0.82 (95% CI: 0.74-0.89). By contrast, the telephone self-test had lower diagnostic accuracy (AUC = 0.75, 95% CI: 0.64-0.86). Both self-tests had good convergent validity as demonstrated by moderate to strong rank correlations with neuropsychological tests. CONCLUSION: We demonstrated good diagnostic accuracy and convergent validity for the online self-test of cognitive function. It is therefore a promising tool in the screening for MCI and dementia.

Selenium Levels in Serum, Red Blood Cells, and Cerebrospinal Fluid of Alzheimer's Disease Patients: A Report from the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL). - Cardoso, Bárbara R; Hare, Dominic J; Bush, Ashley I; Li, Qiao-Xin; Fowler, Christopher J; Masters, Colin L; Martins, Ralph N; Ganio, Katherine; Lothian, Amber; Mukherjee, Soumya; Kapp, Eugene A; Roberts, Blaine R (J Alzheimers Dis, 2017)
Selenium (Se) protects cells against oxidative stress damage through a range of bioactive selenoproteins. Increased oxidative stress is a prominent feature of Alzheimer's disease (AD), and previous studies have shown that Se deficiency is associated with age-related cognitive decline. In this study, we assessed Se status in different biofluids from a subgroup of participants in the Australian Imaging, Biomarkers and Lifestyle Flagship Study of Ageing. As Se in humans can either be an active component of selenoproteins or inactive via non-specific incorporation into other proteins, we used both size exclusion chromatography-inductively coupled plasma-mass spectrometry (SEC-ICP-MS) and tandem mass spectrometry to characterize selenoproteins in serum. We observed no differences in total Se concentration in serum or cerebrospinal fluid of AD subjects compared to mildly cognitively impairment patients and healthy controls. However, Se levels in erythrocytes were decreased in AD compared to controls. SEC-ICP-MS analysis revealed a dominant Se-containing fraction. This fraction was subjected to standard protein purification and a bottom-up proteomics approach to confirm that the abundant Se in the fraction was due, in part, to selenoprotein P. The lack of change in the Se level is at odds with our previous observations in a Brazilian population deficient in Se, and we attribute this to the Australian cohort being Se-replete.

Selenoprotein S Reduces Endoplasmic Reticulum Stress-Induced Phosphorylation of Tau: Potential Role in Selenate Mitigation of Tau Pathology. - Rueli, Rachel H L H; Torres, Daniel J; Dewing, Andrea S T; Kiyohara, Arlene C; Barayuga, Stephanie M; Bellinger, Miyoko T; Uyehara-Lock, Jane H; White, Lon R; Moreira, Paula I; Berry, Marla J; Perry, George; Bellinger, Frederick P (J Alzheimers Dis, 2017)
Previous studies demonstrated that selenium in the form of sodium selenate reduces neurofibrillary tangle formation in Alzheimer's disease models. Hyperphosphorylation of tau, which leads to formation of neurofibrillary tangles in Alzheimer's disease, is increased by endoplasmic reticulum (ER) stress. Selenoprotein S (SelS) is part of an ER membrane complex that removes misfolded proteins from the ER as a means to reduce ER stress. Selenate, as with other forms of selenium, will increase selenoprotein expression. We therefore proposed that increased SelS expression by selenate would contribute to the beneficial actions of selenate in Alzheimer's disease. SelS expression increased with ER stress and decreased under conditions of elevated glucose concentrations in the SH-SY5Y neuronal cell line. Reducing expression of SelS with siRNA promoted cell death in response to ER stress. Selenate increased SelS expression, which significantly correlated with decreased tau phosphorylation. Restricting SelS expression during ER stress conditions increased tau phosphorylation, and also promoted aggregation of phosphorylated tau in neurites and soma. In human postmortem brain, SelS expression coincided with neurofibrillary tangles, but not with amyloid-β plaques. These results indicate that selenate can alter phosphorylation of tau by increasing expression of SelS in Alzheimer's disease and potentially other neurodegenerative disorders.

Severity of Depression Impacts Imminent Conversion from Mild Cognitive Impairment to Alzheimer's Disease. - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Fleischhacker, Walter Wolfgang; Blasko, Imrich; Deisenhammer, Eberhard A (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) has been suggested to represent a prodromal stage of dementia and to confer a high risk for conversion to dementia Alzheimer's type (DAT). OBJECTIVES: In this study, we examined the predictive value of depressive symptoms and neuropsychological variables on conversion of MCI to DAT. METHODS: Neuropsychological and clinical follow-up data of 260 MCI patients seen at the Psychiatric Memory Clinic of the Medical University of Innsbruck between 2005 and 2015 were analyzed retrospectively. Depression was assessed using the Geriatric Depression Scale (GDS). Potential predictors of conversion from MCI to DAT were analyzed by logistic regression analyses and additional survival-analytic methods. RESULTS: Of the 260 patients (mean age 71.5±7.7 years), 83 (32%) converted to DAT within a mean follow-up time of 3.2±2.2 years and estimated one-year conversion rate of 10.1%. The univariate analysis showed with few exceptions (gender, use of antidepressants, low GDS score) group differences at baseline in patients converted to DAT compared to stable MCI patients. Logistic regression analysis as well as survival analysis revealed moderate to severe depression together with higher age and specific cognitive deficits as predictors of conversion from MCI to DAT. CONCLUSION: Our results support the predictive value of different neuropsychological measures on the progression of DAT. In addition, we found a strong negative influence of depression on conversion to DAT in MCI patients. These results emphasize the importance of assessing depressive symptoms in the early stages of DAT when evaluating the conversion from MCI to DAT.

Sex-Dependent Associations of Serum Uric Acid with Brain Function During Aging. - Kueider, Alexandra M; An, Yang; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Studenski, Stephanie; Ferrucci, Luigi; Thambisetty, Madhav (J Alzheimers Dis, 2017)
Serum uric acid (SUA) is an abundant natural antioxidant capable of reducing cellular oxidation, a major cause of neurodegenerative disease. In line with this, SUA levels are lower in Alzheimer's disease; however, the association between SUA and cognition remains unclear. Results from studies examining the effects of SUA on cognition may be difficult to interpret in the context of normal versus pathological aging. This study examined sex-specific associations of baseline SUA with cognition during aging. Data from dementia-free participants initially aged 26-99 (N = 1,451) recruited for the Baltimore Longitudinal Study of Aging (BLSA), were used in the current analyses. SUA was assessed using blood samples collected during research visits. Cognition was measured using five composite scores (verbal memory, attention, executive function, language, and visuospatial ability). At the first study visit, compared with women, men were older, more likely to be White, had more years of education, higher baseline SUA levels, and higher cardiovascular risk scores. Higher baseline SUA was associated with attenuated declines in attention (β= 0.006; p = 0.03) and visuospatial abilities (β= 0.007; p = 0.01) in men. There was a trend to suggest higher baseline SUA in men was associated with attenuated declines in language, but this finding did not reach statistical significance (p = 0.09). There were no significant findings with SUA and cognition in women. In this sample of cognitively healthy, community-dwelling adults, we found that higher SUA levels at baseline were associated with attenuated declines in attention and visuospatial abilities in men. SUA was not associated with cognition or change in cognition over time in women.

Situation Model for Situation-Aware Assistance of Dementia Patients in Outdoor Mobility. - Yordanova, Kristina; Koldrack, Philipp; Heine, Christina; Henkel, Ron; Martin, Mike; Teipel, Stefan; Kirste, Thomas (J Alzheimers Dis, 2017)
BACKGROUND: Dementia impairs spatial orientation and route planning, thus often affecting the patient's ability to move outdoors and maintain social activities. Situation-aware deliberative assistive technology devices (ATD) can substitute impaired cognitive function in order to maintain one's level of social activity. To build such a system, one needs domain knowledge about the patient's situation and needs. We call this collection of knowledge situation model. OBJECTIVE: To construct a situation model for the outdoor mobility of people with dementia (PwD). The model serves two purposes: 1) as a knowledge base from which to build an ATD describing the mobility of PwD; and 2) as a codebook for the annotation of the recorded behavior. METHODS: We perform systematic knowledge elicitation to obtain the relevant knowledge. The OBO Edit tool is used for implementing and validating the situation model. The model is evaluated by using it as a codebook for annotating the behavior of PwD during a mobility study and interrater agreement is computed. In addition, clinical experts perform manual evaluation and curation of the model. RESULTS: The situation model consists of 101 concepts with 11 relation types between them. The results from the annotation showed substantial overlapping between two annotators (Cohen's kappa of 0.61). CONCLUSION: The situation model is a first attempt to systematically collect and organize information related to the outdoor mobility of PwD for the purposes of situation-aware assistance. The model is the base for building an ATD able to provide situation-aware assistance and to potentially improve the quality of life of PwD.

Skin Autofluorescence Examination as a Diagnostic Tool for Mild Cognitive Impairment in Healthy People. - Igase, Michiya; Ohara, Maya; Igase, Keiji; Kato, Takeaki; Okada, Yoko; Ochi, Masayuki; Tabara, Yasuharu; Kohara, Katsuhiko; Ohyagi, Yasumasa (J Alzheimers Dis, 2017)
BACKGROUND: Accumulation of advanced glycation endproducts (AGEs) is thought to be involved in the pathogenesis of dementia, especially Alzheimer's disease. Tissue AGE accumulation can be estimated using the relative simple noninvasive measurement of skin autofluorescence (SAF), a method based on the fluorescent properties of some AGEs. However, possible involvement of tissue AGE accumulation in mild cognitive impairment (MCI) has not been fully investigated. OBJECTIVE: We investigated whether tissue AGE accumulation estimated by SAF is associated with mild cognitive impairment. METHODS: We analyzed 226 community-dwelling subjects. In addition to several atherosclerosis-related clinical parameters, MCI screening test, assessment of brain atrophy, and SAF were performed on people aged > 40 years. MCI was assessed using the Japanese version of the MCI screening method. Atrophy of the brain was assessed by examining the temporal horn area (THA) by brain MRI. RESULTS: SAF was significantly higher in participants with MCI than in those with normal cognitive function (2.56±0.55 versus 2.10±0.41; p < 0.001). Logistic regression analyses with adjustment for confounding factors including age and THA showed that high SAF > 2.27 was significantly related to the presence of MCI (odds, 6.402; 95% CI, 1.590-25.773, p = 0.009). CONCLUSION: We found an association between SAF and MCI, which was independent of brain atrophy, in healthy subjects.

Sleep EEG Detects Epileptiform Activity in Alzheimer's Disease with High Sensitivity. - Horváth, András; Szűcs, Anna; Barcs, Gábor; Kamondi, Anita (J Alzheimers Dis, 2017)
BACKGROUND: The reported prevalence of epilepsy in Alzheimer's disease (AD) is variable, probably due to the different methodological approaches. OBJECTIVE: We aimed to define the optimal electroencephalogram (EEG) settings for reliable detection of epileptiform discharges in AD patients. METHODS: We analyzed 24-h EEGs of 5 patients living with AD and epilepsy. The sensitivity of various length EEGs in detecting epileptiform discharges in different periods of the day, the diurnal distribution of the discharges, and their relation to sleep-stages were calculated. RESULTS: Significant high correlation was identified between the sensitivity of EEG and the length of recordings (r = 0.972, p = 0.005). The sensitivity of a 30-min EEG-epoch recorded between 8:00 and 16:00 was 0.0375 compared to 0.7 between 0:00 and 8:00 (p = 0.005). The average sensitivity of an 8-h EEG-epoch was≥0.8. 82% of epileptiform discharges occurred during sleep, mainly related to non-REM sleep (p < 0.001). CONCLUSION: 8-h awake-, or 1-h sleep-EEG provide sufficient sensitivity in detecting epileptiform activity in AD. This needs to be considered in studies on AD-related epilepsy. Recognizing epilepsy in AD patients is essential because it might compromise cognitive functions and accelerate the progression of the disease.

Spatial Patterns of Longitudinal Gray Matter Change as Predictors of Concurrent Cognitive Decline in Amyloid Positive Healthy Subjects. - Araque Caballero, Miguel Ángel; Klöppel, Stefan; Dichgans, Martin; Ewers, Michael (J Alzheimers Dis, 2017)
A substantial proportion of cognitively healthy elders (HC) show abnormally high amyloid-β (Aβ) deposition, a major pathology of Alzheimer's disease (AD). These subjects are at increased risk of Alzheimer's disease (AD) dementia, and biomarkers are needed to predict their cognitive deterioration. Here we used relevance vector regression (RVR), a pattern-recognition method, to predict concurrent cognitive decline on the basis of longitudinal gray matter (GM) changes, within two a priori, meta-analytically defined functional networks subserving episodic memory and executive function. Ninety-six HC subjects were assessed annually for three years with structural MRI and cognitive tests within the Alzheimer's Disease Neuroimaging Initiative. Presence of abnormal biomarker values of Aβ (Aβ+) were determined with cerebrospinal fluid and amyloid-PET (HC-Aβ+, n=30; with n=66 for normal HC-Aβ-). Using leave-one-out cross-validation, we found that in HC-Aβ+ patterns of GM changes within both networks predicted decline in episodic memory (r=0.61, p<0.001; r=0.40, p=0.03), but not executive function. In HC-Aβ-, GM changes within the executive function network predicted decline in executive function (r=0.44, p<0.001). Previously established region-of-interest (ROI)-based predictors such as changes in hippocampal volume, within an AD-signature multi-ROI, or total GM volume were not predictive of cognitive decline in any group or cognitive domain. RVR analyses unrestricted to the a priori networks yielded compatible results with the restricted case. In conclusion, RVR-derived patterns of subtle cortical GM changes are biomarker candidates of concurrent cognitive decline in aging and subjects at risk for AD.

Stress-Induced Synaptic Dysfunction and Neurotransmitter Release in Alzheimer's Disease: Can Neurotransmitters and Neuromodulators be Potential Therapeutic Targets? - Jha, Saurabh Kumar; Jha, Niraj Kumar; Kumar, Dhiraj; Sharma, Renu; Shrivastava, Abhishek; Ambasta, Rashmi K; Kumar, Pravir (J Alzheimers Dis, 2017)
The communication between neurons at synaptic junctions is an intriguing process that monitors the transmission of various electro-chemical signals in the central nervous system. Albeit any aberration in the mechanisms associated with transmission of these signals leads to loss of synaptic contacts in both the neocortex and hippocampus thereby causing insidious cognitive decline and memory dysfunction. Compelling evidence suggests that soluble amyloid-β (Aβ) and hyperphosphorylated tau serve as toxins in the dysfunction of synaptic plasticity and aberrant neurotransmitter (NT) release at synapses consequently causing a cognitive decline in Alzheimer's disease (AD). Further, an imbalance between excitatory and inhibitory neurotransmission systems induced by impaired redox signaling and altered mitochondrial integrity is also amenable for such abnormalities. Defective NT release at the synaptic junction causes several detrimental effects associated with altered activity of synaptic proteins, transcription factors, Ca2+ homeostasis, and other molecules critical for neuronal plasticity. These detrimental effects further disrupt the normal homeostasis of neuronal cells and thereby causing synaptic loss. Moreover, the precise mechanistic role played by impaired NTs and neuromodulators (NMs) and altered redox signaling in synaptic dysfunction remains mysterious, and their possible interlink still needs to be investigated. Therefore, this review elucidates the intricate role played by both defective NTs/NMs and altered redox signaling in synaptopathy. Further, the involvement of numerous pharmacological approaches to compensate neurotransmission imbalance has also been discussed, which may be considered as a potential therapeutic approach in synaptopathy associated with AD.

Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms. - Marková, Hana; Andel, Ross; Stepankova, Hana; Kopecek, Miloslav; Nikolai, Tomas; Hort, Jakub; Thomas-Antérion, Catherine; Vyhnálek, Martin (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaints (SCCs) may be an early marker of prodromal Alzheimer's disease. OBJECTIVES: Using a 10-item yes/no SCCs questionnaire (Le Questionnaire de Plainte Cognitive [QPC]), we evaluated the prevalence and distribution of SCCs in cognitively healthy Czech older adults and examined total score and specific QPC items in relation to depressive symptomology and cognitive performance. METHODS: A sample of 340 cognitively healthy older community-dwelling volunteers aged 60 or older from the third wave of the longitudinal project National Normative Study of Cognitive Determinants of Healthy Aging, who underwent a comprehensive neuropsychological assessment and completed the QPC and the 15-item Geriatric Depression Scale (GDS-15). Regression analysis was controlled for age when GDS-15 was the outcome and for age and GDS-15 with cognitive domains as the outcome. RESULTS: 71% reported 1 + SCCs, with prevalence of individual complaints ranging from 4% to 40%. The number of SCCs was associated with GDS-15 (p < 0.001). Personality change (p < 0.001) and Limitation in daily activities (p = 0.002) were significantly associated with higher GDS-15 score and Spatial orientation difficulties (p = 0.019) and Impression of worse memory in comparison to peers (p = 0.012) were significantly associated with lower memory performance. CONCLUSIONS: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study. - Tao, Jing; Liu, Jiao; Liu, Weilin; Huang, Jia; Xue, Xiehua; Chen, Xiangli; Wu, Jinsong; Zheng, Guohua; Chen, Bai; Li, Ming; Sun, Sharon; Jorgenson, Kristen; et al. (J Alzheimers Dis, 2017)
The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic resonance imaging and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR) were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe, and putamen after 12-weeks of exercise. No significant differences were observed in GMV between the Tai Chi Chuan and Baduanjin groups. We also found that compared to healthy controls, Tai Chi Chuan and Baduanjin significantly improved visual reproduction subscores on the WMS-CR. Baduanjin also improved mental control, recognition, touch, and comprehension memory subscores of the WMS-CR compared to the control group. Memory quotient and visual reproduction subscores were both associated with GMV increases in the putamen and hippocampus. Our results demonstrate the potential of Tai Chi Chuan and Baduanjin exercise for the prevention of memory deficits in older adults.

Tau Oligomers Associate with Inflammation in the Brain and Retina of Tauopathy Mice and in Neurodegenerative Diseases. - Nilson, Ashley N; English, Kelsey C; Gerson, Julia E; Whittle, T Barton; Crain, C Nicolas; Xue, Judy; Sengupta, Urmi; Castillo-Carranza, Diana L; Zhang, Wenbo; Gupta, Praveena; Kayed, Rakez (J Alzheimers Dis, 2017)
It is well-established that inflammation plays an important role in Alzheimer's disease (AD) and frontotemporal lobar dementia (FTLD). Inflammation and synapse loss occur in disease prior to the formation of larger aggregates, but the contribution of tau to inflammation has not yet been thoroughly investigated. Tau pathologically aggregates to form large fibrillar structures known as tangles. However, evidence suggests that smaller soluble aggregates, called oligomers, are the most toxic species and form prior to tangles. Furthermore, tau oligomers can spread to neighboring cells and between anatomically connected brain regions. In addition, recent evidence suggests that inspecting the retina may be a window to brain pathology. We hypothesized that there is a relationship between tau oligomers and inflammation, which are hallmarks of early disease. We conducted immunofluorescence and biochemical analyses on tauopathy mice, FTLD, and AD subjects. We showed that oligomers co-localize with astrocytes, microglia, and HMGB1, a pro-inflammatory cytokine. Additionally, we show that tau oligomers are present in the retina and are associated with inflammatory cells suggesting that the retina may be a valid non-invasive biomarker for brain pathology. These results suggest that there may be a toxic relationship between tau oligomers and inflammation. Therefore, the ability of tau oligomers to spread may initiate a feed-forward cycle in which tau oligomers induce inflammation, leading to neuronal damage, and thus more inflammation. Further mechanistic studies are warranted in order to understand this relationship, which may have critical implications for improving the treatment of tauopathies.

Tau Oligomers in Sera of Patients with Alzheimer's Disease and Aged Controls. - Kolarova, Michala; Sengupta, Urmi; Bartos, Ales; Ricny, Jan; Kayed, Rakez (J Alzheimers Dis, 2017)
Although tau protein was long regarded as an intracellular protein with several functions inside the cell, new evidence has shown tau secretion into the extracellular space. The active secretion of tau could be a physiological response of neurons to increased intracellular amounts of tau during the progression of tau pathology. We looked for potential differences in the serum levels of toxic tau oligomers in regards to cognitive impairment of subjects. We detected tau oligomers in the serum of Alzheimer's disease (AD) patients, but they were also present to some extent in the serum of healthy older subjects where the levels positively correlated with aging (Spearman r = 0.26, p = 0.016). On the contrary, we found lower levels of tau oligomers in the serum of mild cognitive impairment (MCI) (p = 0.033) and MCI-AD (p = 0.006) patients. These results could suggest that clearance of extracellular tau proteins takes place, in part, in the periphery. In the case of MCI patients, the lower levels of tau oligomers could be the result of impaired clearance of tau protein from interstitium to blood and consequent accumulation of tau aggregates in the brain.

Tau Proteins Cross the Blood-Brain Barrier. - Banks, William A; Kovac, Andrej; Majerova, Petra; Bullock, Kristin M; Shi, Min; Zhang, Jing (J Alzheimers Dis, 2017)
Tauopathies are a hallmark of many neurodegenerative diseases, including Alzheimer's disease and traumatic brain injuries. It has been demonstrated that amyloid-beta peptides, alpha-synuclein, and prion proteins cross the blood-brain barrier (BBB), contributing to their abilities to induce disease. Very little is known about whether tau proteins can cross the BBB. Here we systematically characterized several key forms of tau proteins to cross the BBB, including Tau-441 (2N4R), Tau-410 (2N3R), truncated tau 151-391 (0N4R), and truncated tau 121-227. All of these tau proteins crossed the BBB readily and bidirectonally; however, only Tau-410 had a saturable component to its influx. The tau proteins also entered the blood after their injection into the brain, with Tau 121-227 having the slowest exit from brain. The tau proteins varied in regards to their enzymatic stability in brain and blood and in their peripheral pharmacokinetics. These results show that blood-borne tau proteins could contribute to brain tauopathies. The result also suggest that the CNS can contribute to blood levels of tau, raising the possibility that, as suggested for other misfolded proteins, blood levels of tau proteins could be used as a biomarker of CNS disease.

Tau Rather than TDP-43 Proteins are Potential Cerebrospinal Fluid Biomarkers for Frontotemporal Lobar Degeneration Subtypes: A Pilot Study. - Kuiperij, H Bea; Versleijen, Alexandra A M; Beenes, Marijke; Verwey, Nicolaas A; Benussi, Luisa; Paterlini, Anna; Binetti, Giuliano; Teunissen, Charlotte E; Raaphorst, Joost; Schelhaas, Helenius J; Küsters, Benno; Pijnenburg, Yolande A L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous disease both at the clinical, genetic, and pathobiological level. The underlying pathological spectrum (termed FTLD, frontotemporal lobar degeneration) is in most cases defined by accumulation of either tau (FTLD-tau) or TDP-43 proteins (FTLD-TDP). Biomarkers to differentiate these subtypes are not yet available, whereas these are essential requirements to study the natural course of disease and for homogeneous inclusion of patients in clinical studies. OBJECTIVE: To study if a combination of total (t-) and phosphorylated (p-)tau, and t-TDP-43 and p-TDP-43 proteins in cerebrospinal fluid (CSF) is suitable to discriminate FTLD-tau and FTLD-TDP subtypes. METHODS: We developed immunoassays for the quantification of t-TDP-43 and p-TDP-43 proteins and used commercially available assays for the quantification of t-tau and p-tau proteins. We quantified these proteins in ventricular CSF samples from neuropathologically defined FTLD-tau and FTLD-TDP cases to study the reflection of underlying brain pathology in CSF composition, and in lumbar CSF samples from FTLD-tau and FTLD-TDP patients to study the diagnostic potential of CSF biomarkers. RESULTS: In ventricular CSF, t-TDP-43 and t-tau levels, when combined into one model, were significantly different between neuropathologically-defined FTLD-tau and FTLD-TDP cases. In a pilot study using lumbar CSF, the p-tau/t-tau ratio, but not t-TDP-43 levels, were significantly different between FTLD-TDP and FTLD-tau patients. CONCLUSION: We conclude that with current available methods, CSF tau, rather than TDP-43 proteins, may have diagnostic value in the differentiation of FTLD patients with either tau or TDP-43 pathology.

Temporal Order of Alzheimer's Disease-Related Cognitive Marker Changes in BLSA and WRAP Longitudinal Studies. - Bilgel, Murat; Koscik, Rebecca L; An, Yang; Prince, Jerry L; Resnick, Susan M; Johnson, Sterling C; Jedynak, Bruno M (J Alzheimers Dis, 2017)
Investigation of the temporal trajectories of currently used neuropsychological tests is critical to identifying earliest changing measures on the path to dementia due to Alzheimer's disease (AD). We used the Progression Score (PS) method to characterize the temporal trajectories of measures of verbal memory, executive function, attention, processing speed, language, and mental status using data spanning normal cognition, mild cognitive impairment, and AD from 1,661 participants with a total of 7,839 visits (age at last visit 77.6 SD 9.2) in the Baltimore Longitudinal Study of Aging (BLSA) and 1510 participants with a total of 3,473 visits (age at last visit 59.5 SD 7.4) in the Wisconsin Registry for Alzheimer's Prevention (WRAP). This method aligns individuals in time based on the similarity of their longitudinal measurements to reveal temporal trajectories. As a validation of our methodology, we explored the associations between the individualized cognitive progression scores (Cog-PS) computed by our method and clinical diagnosis. Digit span tests were the first to show declines in both data sets, and were detected mainly among cognitively normal individuals. These were followed by tests of verbal memory, which were in turn followed by Trail Making Tests, Boston Naming Test, and Mini-Mental State Examination. Differences in Cog-PS across the clinical diagnosis and APOEɛ4 groups were statistically significant, highlighting the potential use of Cog-PS as individualized indicators of disease progression. Identifying cognitive measures that are changing in preclinical AD can lead to the development of novel cognitive tests that are finely tuned to detecting earliest changes.

Ten Challenges of the Amyloid Hypothesis of Alzheimer's Disease. - Kepp, Kasper Planeta (J Alzheimers Dis, 2017)
The inability to effectively halt or cure Alzheimer's disease (AD), exacerbated by the recent failures of high-profile clinical trials, emphasizes the urgent need to understand the complex biochemistry of this major neurodegenerative disease. In this paper, ten central, current challenges of the major paradigm in the field, the amyloid hypothesis, are sharply formulated. These challenges together show that new approaches are necessary that address data heterogeneity, increase focus on the proteome level, use available human patient data more actively, account for the aging phenotype as a background model of the disease, unify our understanding of the interplay between genetic and non-genetic risk factors, and combine into one framework both the familial and sporadic forms of the disease.

TFP5, a Peptide Inhibitor of Aberrant and Hyperactive Cdk5/p25, Attenuates Pathological Phenotypes and Restores Synaptic Function in CK-p25Tg Mice. - Shukla, Varsha; Seo, Jinsoo; Binukumar, B K; Amin, Niranjana D; Reddy, Preethi; Grant, Philip; Kuntz, Susan; Kesavapany, Sashi; Steiner, Joseph; Mishra, Santosh K; Tsai, Li-Huei; Pant, Harish C (J Alzheimers Dis, 2017)
It has been reported that cyclin-dependent kinase 5 (cdk5), a critical neuronal kinase, is hyperactivated in Alzheimer's disease (AD) and may be, in part, responsible for the hallmark pathology of amyloid plaques and neurofibrillary tangles (NFTs). It has been proposed by several laboratories that hyperactive cdk5 results from the overexpression of p25 (a truncated fragment of p35, the normal cdk5 regulator), which, when complexed to cdk5, induces hyperactivity, hyperphosphorylated tau/NFTs, amyloid-β plaques, and neuronal death. It has previously been shown that intraperitoneal (i.p.) injections of a modified truncated 24-aa peptide (TFP5), derived from the cdk5 activator p35, penetrated the blood-brain barrier and significantly rescued AD-like pathology in 5XFAD model mice. The principal pathology in the 5XFAD mutant, however, is extensive amyloid plaques; hence, as a proof of concept, we believe it is essential to demonstrate the peptide's efficacy in a mouse model expressing high levels of p25, such as the inducible CK-p25Tg model mouse that overexpresses p25 in CamKII positive neurons. Using a modified TFP5 treatment, here we show that peptide i.p. injections in these mice decrease cdk5 hyperactivity, tau, neurofilament-M/H hyperphosphorylation, and restore synaptic function and behavior (i.e., spatial working memory, motor deficit using Rota-rod). It is noteworthy that TFP5 does not inhibit endogenous cdk5/p35 activity, nor other cdks in vivo suggesting it might have no toxic side effects, and may serve as an excellent therapeutic candidate for neurodegenerative disorders expressing abnormally high brain levels of p25 and hyperactive cdk5.

Therapeutics of Neurotransmitters in Alzheimer's Disease. - Kandimalla, Ramesh; Reddy, P Hemachandra (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease, characterized by the loss of memory, multiple cognitive impairments and changes in the personality and behavior. Several decades of intense research have revealed that multiple cellular changes are involved in disease process, including synaptic damage, mitochondrial abnormalities and inflammatory responses, in addition to formation and accumulation of amyloid-β (Aβ) and phosphorylated tau. Although tremendous progress has been made in understanding the impact of neurotransmitters in the progression and pathogenesis of AD, we still do not have a drug molecule associated with neurotransmitter(s) that can delay disease process in elderly individuals and/or restore cognitive functions in AD patients. The purpose of our article is to assess the latest developments in neurotransmitters research using cell and mouse models of AD. We also updated the current status of clinical trials using neurotransmitters' agonists/antagonists in AD.

Three-Repeat Tau with Grain-Like Structures and Distribution in an 83-Year-Old Man. - Kasahata, Naoki; Sato, Tomohide; Onishi, Iichiroh; Kitagawa, Masanobu; Uchihara, Toshiki; Hirokawa, Katsuiku (J Alzheimers Dis, 2017)
We encountered an 83-year-old man with 3-repeat dominant grain-like tau deposition. Tau-positive lesions exhibited apparent similarity to argyrophilic grains in terms of their distribution in the ambient gyrus, amygdala, and dorsomedial temporal tip and the characteristic comma-like morphology. The abundant oligodendroglial tau immunoreactivities were 3-repeat dominant. Tuft-shaped astrocytes showed partial 3-repeat tau immnoreactivities. These grain-like structures, as well as tuft-shaped astrocytes and oligodendroglia, exhibited predominant 3-repeat tau immunoreactivity, suggesting that grain-like structures and their characteristic distribution are mutually linked and not unique to 4-repeat tau deposition. pTDP immunoreactivity, extensive macrophage infiltration, and spongiosis were associated with these 3-repeat tau deposits.

Tocotrienol-Rich Fraction Modulates Amyloid Pathology and Improves Cognitive Function in AβPP/PS1 Mice. - Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Durani, Lina Wati; Hamezah, Hamizah Shahirah; Damanhuri, Hanafi Ahmad; Wan Ngah, Wan Zurinah; Tsuji, Mayumi; Kiuchi, Yuji; Ono, Kenjiro; Tooyama, Ikuo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia. The cardinal neuropathological characteristic of AD is the accumulation of amyloid-β (Aβ) into extracellular plaques that ultimately disrupt neuronal function and lead to neurodegeneration. One possible therapeutic strategy therefore is to prevent Aβ aggregation. Previous studies have suggested that vitamin E analogs slow AD progression in humans. In the present study, we investigated the effects of the tocotrienol-rich fraction (TRF), a mixture of vitamin E analogs from palm oil, on amyloid pathology in vitro and in vivo. TRF treatment dose-dependently inhibited the formation of Aβ fibrils and Aβ oligomers in vitro. Moreover, daily TRF supplementation to AβPPswe/PS1dE9 double transgenic mice for 10 months attenuated Aβ immunoreactive depositions and thioflavin-S-positive fibrillar type plaques in the brain, and eventually improved cognitive function in the novel object recognition test compared with control AβPPswe/PS1dE9 mice. The present result indicates that TRF reduced amyloid pathology and improved cognitive functions, and suggests that TRF is a potential therapeutic agent for AD.

Transport of Non-Transferrin Bound Iron to the Brain: Implications for Alzheimer's Disease. - Tripathi, Ajai K; Karmakar, Shilpita; Asthana, Abhishek; Ashok, Ajay; Desai, Vilok; Baksi, Shounak; Singh, Neena (J Alzheimers Dis, 2017)
A direct correlation between brain iron and Alzheimer's disease (AD) raises questions regarding the transport of non-transferrin-bound iron (NTBI), a toxic but less researched pool of circulating iron that is likely to increase due to pathological and/or iatrogenic systemic iron overload. Here, we compared the distribution of radiolabeled-NTBI (59Fe-NTBI) and transferrin-bound iron (59Fe-Tf) in mouse models of iron overload in the absence or presence of inflammation. Following a short pulse, most of the 59Fe-NTBI was taken up by the liver, followed by the kidney, pancreas, and heart. Notably, a strong signal of 59Fe-NTBI was detected in the brain ventricular system after 2 h, and the brain parenchyma after 24 h. 59Fe-Tf accumulated mainly in the femur and spleen, and was transported to the brain at a much slower rate than 59Fe-NTBI. In the kidney, 59Fe-NTBI was detected in the cortex after 2 h, and outer medulla after 24 hours. Most of the 59Fe-NTBI and 59Fe-Tf from the kidney was reabsorbed; negligible amount was excreted in the urine. Acute inflammation increased the uptake of 59Fe-NTBI by the kidney and brain from 2-24 hours. Chronic inflammation, on the other hand, resulted in sequestration of iron in the liver and kidney, reducing its transport to the brain. These observations provide direct evidence for the transport of NTBI to the brain, and reveal a complex interplay between inflammation and brain iron homeostasis. Further studies are necessary to determine whether transient increase in NTBI due to systemic iron overload is a risk factor for AD.

Using Drugs as Molecular Probes: A Computational Chemical Biology Approach in Neurodegenerative Diseases. - Emon, Mohammad Asif Emran Khan; Kodamullil, Alpha Tom; Karki, Reagon; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Neurodegenerative diseases including Alzheimer's disease are complex to tackle because of the complexity of the brain, both in structure and function. Such complexity is reflected by the involvement of various brain regions and multiple pathways in the etiology of neurodegenerative diseases that render single drug target approaches ineffective. Particularly in the area of neurodegeneration, attention has been drawn to repurposing existing drugs with proven efficacy and safety profiles. However, there is a lack of systematic analysis of the brain chemical space to predict the feasibility of repurposing strategies. Using a mechanism-based, drug-target interaction modeling approach, we have identified promising drug candidates for repositioning. Mechanistic cause-and-effect models consolidate relevant prior knowledge on drugs, targets, and pathways from the scientific literature and integrate insights derived from experimental data. We demonstrate the power of this approach by predicting two repositioning candidates for Alzheimer's disease and one for amyotrophic lateral sclerosis.

Utility of Molecular and Structural Brain Imaging to Predict Progression from Mild Cognitive Impairment to Dementia. - Lan, Martin J; Ogden, R Todd; Kumar, Dileep; Stern, Yaakov; Parsey, Ramin V; Pelton, Gregory H; Rubin-Falcone, Harry; Pradhaban, Gnanavalli; Zanderigo, Francesca; Miller, Jeffrey M; Mann, J John; Devanand, D P (J Alzheimers Dis, 2017)
This project compares three neuroimaging biomarkers to predict progression to dementia in subjects with mild cognitive impairment (MCI). Eighty-eight subjects with MCI and 40 healthy controls (HCs) were recruited. Subjects had a 3T magnetic resonance imaging (MRI) scan, and two positron emission tomography (PET) scans, one with Pittsburgh compound B ([11C]PIB) and one with fluorodeoxyglucose ([18F]FDG). MCI subjects were followed for up to 4 y and progression to dementia was assessed on an annual basis. MCI subjects had higher [11C]PIB binding potential (BPND) than HCs in multiple brain regions, and lower hippocampus volumes. [11C]PIB BPND, [18F]FDG standard uptake value ratio (SUVR), and hippocampus volume were associated with time to progression to dementia using a Cox proportional hazards model. [18F]FDG SUVR demonstrated the most statistically significant association with progression, followed by [11C]PIB BPND and then hippocampus volume. [11C]PIB BPND and [18F]FDG SUVR were independently predictive, suggesting that combining these measures is useful to increase accuracy in the prediction of progression to dementia. Hippocampus volume also had independent predictive properties to [11C]PIB BPND, but did not add predictive power when combined with the [18F]FDG SUVR data. This work suggests that PET imaging with both [11C]PIB and [18F]FDG may help to determine which MCI subjects are likely to progress to AD, possibly directing future treatment options.

Validation of the Korean Version of the Lewy Body Composite Risk Score (K-LBCRS). - Ryu, Hui Jin; Kim, Minyoung; Moon, Yeonsil; Choi, Yeji; Han, Jee-Young; Galvin, James E; Han, Seol-Heui (J Alzheimers Dis, 2017)
The Lewy body composite risk score (LBCRS) is a useful clinical screening tool to help determine whether the dementia is related to Lewy body pathology. The purpose of this study is to verify reliability, validity, and diagnostic usefulness of Korean version of LBCRS (K-LBCRS). CDR-sum of boxes, Mini-Mental State Examination, and standardized scales related to cognition, mood, behavior, and motor function were administered to a total of 107 subjects, including 30 dementia with Lewy bodies (DLB), 54 Alzheimer's disease (AD), and 23 cognitively normal elderly people and their collateral informants. Internal consistency of the K-LBCRS was good with Cronbach's alpha of 0.85, and concurrent validity was also satisfactory, with K-LBCRS correlating highly with CDR-SB and other scales. The test-retest reliability was very high with a Pearson correlation coefficient of 0.97. The mean scores of K-LBCRS were significantly different among three groups, with DLB (6.2±2.4), AD (1.4±1.3), and controls (0.3±0.6). We identified a cut-off score of 3 as best to differentiate between DLB and AD, having AUC of 0.97 (95% CI 0.94-1.00), sensitivity 97%, specificity 83%, positive predictive value 76%, negative predictive value 98%, which is the same score suggested in the original study. This study shows K-LBCRS as a new useful screening tool for Korean DLB patients in clinical settings.

Varying Degrees of Temporoparietal Hypometabolism on FDG-PET Reveal Amyloid-Positive Logopenic Primary Progressive Aphasia is not a Homogeneous Clinical Entity. - Krishnan, Kamini; Machulda, Mary M; Whitwell, Jennifer L; Butts, Alissa M; Duffy, Joseph R; Strand, Edythe A; Senjem, Matthew L; Spychalla, Anthony J; Jack, Clifford R; Lowe, Val J; Josephs, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: The logopenic variant of primary progressive aphasia (lvPPA) manifests due to a breakdown of the language network with prominent hypometabolism of the left temporoparietal region. LvPPA is strongly associated with amyloid deposition, yet there is question as to whether it is a homogeneous clinical entity. OBJECTIVE: This study investigated whether differences in temporoparietal metabolic patterns on 18F fludeoxyglucose positron emission tomography (FDG-PET) could elucidate brain regions preferentially affected in lvPPA. METHOD: We used differences in FDG-PET metabolic z-scores relative to controls for means of left lateral temporal, left inferior parietal, and left superior parietal regions to classify 53 amyloid-positive lvPPA patients into temporal, parietal, or temporoparietal predominate groups. Clinical features and FDG-PET regions of hypometabolism outside of the temporoparietal region were then compared across the three groups; the latter using statistical parametric mapping. RESULTS: Of the 53 lvPPA patients, 15 were classified as temporal, 14 as temporoparietal, and 22 as parietal predominate. There were no significant differences between the groups on demographic measures, language evaluation, or apolipoprotein E genotype. Compared to the other two groups, individuals with the parietal predominate pattern had extensive hypometabolism in left frontal lobe and the precuneus. Furthermore, this group had greater behavioral dyscontrol and deficits in executive function, visuospatial skills, visual memory retention, working memory, and cognitive flexibility (Bonferronip < 0.05). CONCLUSIONS: This study demonstrates that there is clinical heterogeneity within amyloid-positive lvPPA. Patients with lvPPA with predominant parietal hypometabolism, unlike those with temporal or temporoparietal predominant hypometabolism, demonstrated widespread cognitive and behavioral changes.

Violation of Laws in Frontotemporal Dementia: A Multicenter Study in Japan. - Shinagawa, Shunichiro; Shigenobu, Kazue; Tagai, Kenji; Fukuhara, Ryuji; Kamimura, Naoto; Mori, Takaaki; Yoshiyama, Kenji; Kazui, Hiroaki; Nakayama, Kazuhiko; Ikeda, Manabu (J Alzheimers Dis, 2017)
Although violations of laws, such as shoplifting, are considered to be common in frontotemporal dementia (FTD) patients, there have been few studies on this subject and the frequencies and types of such violations have not been clarified. The objective of this study was to conduct a retrospective investigation of FTD patients in the psychiatry departments of multiple institutions to determine the types and frequencies of any law violations and compare them with those of AD patients. All patients were examined between January 2011 and December 2015 at the specialized dementia outpatient clinics of 10 facilities (5 psychiatry departments of university hospitals, 5 psychiatric hospitals). According to diagnostic criteria, 73 behavior variant FTD (bvFTD) patients, 84 semantic variant of primary progressive aphasia (svPPA) patients, and 255 age- and sex-matched AD subjects as the control group were selected. The findings revealed a higher rate of law violations in the bvFTD and svPPA patients before the initial consultation as compared to the AD group (bvFTD: 33%, svPPA: 21%, AD: 6%) and that many patients had been referred due to such violations. Laws had been broken 4 times or 5 or more times in several cases in the FTD group before the initial consultation. Regarding rates for different types of violation, in bvFTD subjects, the highest rate was for theft, followed by nuisance acts and hit and run. In svPPA, theft had the highest rate, followed by ignoring road signs. There was no gender difference in law violations but they were more frequent when the disease was severe at the initial consultation in the FTD group. As the rates of law violations after the initial consultation were lower than before it, interventions were considered to have been effective. These findings may be useful for future prevention as well as to the legal system.

Visit-to-Visit Blood Pressure Variability and Alzheimer's Disease: Links and Risks. - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Kagawa, Eisuke; Nakano, Yoshinori; Yamane, Aya; Higashihara, Tasuku; Miyauchi, Shunsuke; Tsuchiya, Akane (J Alzheimers Dis, 2017)
While hypertension has been shown to be a risk factor for vascular dementia, several studies have also demonstrated that hypertension also increases the risk of Alzheimer's disease (AD). Although the relationship between visit-to-visit blood pressure variability (VVV) and cognitive impairment, including AD, have been provided, the mechanisms remain poorly understood. This review paper focuses on the relationship of VVV with AD and summarizes the pathophysiology underlying that relationship, which appears to be mediated by arterial stiffness.

Visual Rating of Posterior Atrophy as a Marker of Progression to Dementia in Mild Cognitive Impairment Patients. - Kim, Hang-Rai; Park, Young Ho; Jang, Jae-Won; Park, So Young; Wang, Min Jeong; Baek, Min Jae; Kim, Beom Joon; Ahn, Soyeon; Kim, SangYun (J Alzheimers Dis, 2017)
BACKGROUND: Although medial temporal atrophy (MTA) is a useful imaging marker of the progression to dementia in mild cognitive impairment (MCI), substantial numbers of MCI patients without MTA still progress to dementia. OBJECTIVE: We investigated whether visual ratings of posterior atrophy (PA) on magnetic resonance imaging show independent predictive value for the progression to dementia in MCI patients. METHODS: This was a retrospective cohort study of elderly patients who visited Seoul National University Bundang Hospital between 2004 and 2012. A total of 148 patients who were initially diagnosed with MCI were followed for up to 3 years (median 22 months) to determine whether they progressed to dementia. We used 4-point and 5-point visual rating scales to assess PA and MTA, respectively. PA and MTA scores were dichotomized into normal (no atrophy) or abnormal (atrophy) in each patient. We performed a Cox regression analysis to examine the hazard ratios (HRs) of PA and MTA for the progression to dementia with adjustment for age, APOEɛ4 allele status, and baseline Mini-Mental State Examination score. RESULTS: Among the study population, 47 patients progressed to dementia. Visual assessment of the MRI scans revealed that 67 patients (45.3%) showed PA, whereas 85 patients (57.3%) showed MTA. The HRs with 95% confidence intervals for PA and MTA were 2.516 (1.244-5.091) and 4.238 (1.680-10.687), respectively. The predictive values of visually assessed PA and MTA remained significant, independent of the covariates. CONCLUSION: Visual assessment of PA has independent predictive value for progression to dementia in MCI patients.

Visual Selective Attention Toward Novel Stimuli Predicts Cognitive Decline in Alzheimer's Disease Patients. - Chau, Sarah A; Herrmann, Nathan; Sherman, Chelsea; Chung, Jonathan; Eizenman, Moshe; Kiss, Alex; Lanctôt, Krista L (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with selective attention impairments, which could contribute to cognitive and functional deficits. Using visual scanning parameters, selective attention toward novel stimuli, or novelty preference, can be measured by a non-verbal, non-invasive method that may be of value in predicting disease progression. OBJECTIVE: In this longitudinal study, we explored whether novelty preference can predict cognitive decline in AD patients. METHODS: Mild to moderate AD patients viewed slides containing both novel and repeat images. The number of fixations, the average fixation time, and the relative fixation time on the two types of images were measured by an eye-tracking system. Novelty preference was estimated by the differences between the visual scanning parameters on novel and repeat images. Cognition and attention were assessed using the Standardized Mini-Mental Status Examination (sMMSE) and the Conners' Continuous Performance Test (CPT), respectively. Cognition was re-assessed every 6 months for up to 2 years. RESULTS: Multivariate linear regressions of 32 AD patients (14 females, age = 77.9±7.8, baseline sMMSE = 22.2±4.4) indicated that reduced time spent on novel images (t = 2.78, p = 0.010) was also associated with greater decline in sMMSE scores (R2 = 0.41, Adjusted R2 = 0.35, F3,28 = 6.51, p = 0.002), adjusting for attention and baseline sMMSE. CONCLUSION: These results suggest that novelty preference, measured by visual attention scanning technology, may reflect pathophysiological processes that could predict disease progression in the cognitively-impaired.

Visuospatial Functioning in Cerebral Amyloid Angiopathy: A Pilot Study. - Valenti, Raffaella; Charidimou, Andreas; Xiong, Li; Boulouis, Gregoire; Fotiadis, Panagiotis; Ayres, Alison; Riley, Grace; Kuijf, Hugo J; Reijmer, Yael D; Pantoni, Leonardo; Gurol, M Edip; Davidsdottir, Sigurros; et al. (J Alzheimers Dis, 2017)
Cerebral amyloid angiopathy (CAA) is a contributor to cognitive impairment in the elderly. We hypothesized that the posterior cortical predilection of CAA would cause visual-processing impairment. We systematically evaluated visuospatial abilities in 22 non-demented CAA patients. Neurocognitive evaluation demonstrated visuoperceptual impairment (23% on Benton Facial Recognition Test [BFRT] and 13.6% on Benton Judgment of Line Orientation Test [BJLO]). BFRT was inversely correlated with white matter hyperintensities volume and BJLO with parietal cerebral microbleeds. This pilot study highlights the presence of visual-processing deficits in CAA. The impairment could be related to global disease severity in addition to local brain injury.

Vitamin D Insufficiency and Cognitive Function Trajectories in Older Adults: The Rancho Bernardo Study. - Laughlin, Gail A; Kritz-Silverstein, Donna; Bergstrom, Jaclyn; Reas, Emilie T; Jassal, Simerjot K; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
BACKGROUND: Evidence of a role for vitamin D (VitD) in cognitive aging is mixed and based primarily on extreme VitD deficiency. We evaluated the association of VitD insufficiency with cognitive function in older, community-dwelling adults living in a temperate climate with year-round sunshine. METHODS: A population-based longitudinal study of 1,058 adults (median age 75; 62% women) who had cognitive function assessed and serum levels of 25-hydroxyvitaminD (25OHD) measured in 1997-99 and were followed for up to three additional cognitive function assessments over a 12-year period. RESULTS: Overall, 14% (n = 145) of participants had VitD insufficiency defined as 25OHD <30 ng/ml. Adjusting for age, sex, education, and season, VitD insufficiency was associated with poorer baseline performance on the Mini-Mental Status Exam (MMSE) (p = 0.013), Trails Making Test B (Trails B) (p = 0.015), Category Fluency (p = 0.006), and Long Term Retrieval (p = 0.019); differences were equivalent to 5 years of age. For those with VitD insufficiency, the odds of mildly impaired performance at baseline were 38% higher for MMSE (p = 0.08), 78% higher for Trails B (p = 0.017), and 2-fold higher for Category Fluency and Long Term Retrieval (both p = 0.001). VitD insufficiency was not related to the rate of cognitive decline on any test or the risk of developing impaired performance during follow-up. CONCLUSION: In this population with little VitD deficiency, even moderately low VitD was associated with poorer performance on multiple domains of cognitive function. Low VitD did not predict 12-year cognitive decline. Clinical trials are essential to establish a causal link between VitD and cognitive well-being.

White Matter Degradation is Associated with Reduced Financial Capacity in Mild Cognitive Impairment and Alzheimer's Disease. - Gerstenecker, Adam; Hoagey, David A; Marson, Daniel C; Kennedy, Kristen M (J Alzheimers Dis, 2017)
Financial capacity (FC) is a cognitively complex activity of daily living that declines in mild cognitive impairment (MCI) and Alzheimer's disease (AD), limiting an individual's ability to manage one's finances and function independently. The neural underpinnings of this decline in function are poorly understood but likely involve age-related and disease-related degradation across structural networks. The purpose of the current study was to determine if altered white matter integrity is associated with declining FC in persons with MCI and AD compared to older controls. Individuals with MCI due to AD (n = 31), mild dementia (n = 39), and cognitively healthy older adults (n = 60) were administered a neuropsychological battery including the FC Instrument, a performance-based measure of FC. All 130 participants also underwent diffusion tensor imaging (DTI) upon which tract-based spatial statistics were performed. Both FC and white matter integrity decreased in accordance with disease severity with little to no effect in healthy elderly, significant effects in MCI, and greater effects in AD. Regional white matter degradation (increased diffusivities and decreased fractional anisotropy) was associated with reduced FC in both MCI and AD groups even after controlling for age, education, and gender. Specifically, in MCI, decreased fractional anisotropy, but not increased diffusivities, was associated with poorer FC in widespread cingulo-parietal-frontal and temporo-occipital areas. In AD, rather than anisotropy, increased mean and axial diffusivities in anterior cingulate, callosum, and frontal areas associated with poorer FC. These findings suggest a severity gradient of white matter degradation across DTI metrics and AD stages that predict declining financial skill and knowledge.

ABCA7 Mediates Phagocytic Clearance of Amyloid-β in the Brain. - Fu, YuHong; Hsiao, Jen-Hsiang T; Paxinos, George; Halliday, Glenda M; Kim, Woojin Scott (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by dementia and abnormal deposits of aggregated amyloid-β in the brain. Recent genome-wide association studies have revealed that ABCA7 is strongly associated with AD. In vitro evidence suggests that the role of ABCA7 is related to phagocytic activity. Deletion of ABCA7 in a mouse model of AD exacerbates cerebral amyloid-β plaque load. However, the biological role of ABCA7 in AD brain pathogenesis is unknown. We show that ABCA7 is highly expressed in microglia and when monocytes are differentiated into macrophages. We hypothesized that ABCA7 plays a protective role in the brain that is related to phagocytic clearance of amyloid-β. We isolated microglia and macrophages from Abca7-/- and wild type mice and tested them for their capacity to phagocytose amyloid-β oligomers. We found that the phagocytic clearance of amyloid-β was substantially reduced in both microglia and macrophages from Abca7-/- mice compared to wild type mice. Consistent with these results, in vivo phagocytic clearance of amyloid-β oligomers in the hippocampus was reduced in Abca7-/- mice. Furthermore, ABCA7 transcription was upregulated in AD brains and in amyloidogenic mouse brains specifically in the hippocampus as a response to the amyloid-β pathogenic state. Together these results indicate that ABCA7 mediates phagocytic clearance of amyloid-β in the brain, and reveal a mechanism by which loss of function of ABCA7 increases the susceptibility to AD.

Active Cigarette Smoking in Cognitively-Normal Elders and Probable Alzheimer's Disease is Associated with Elevated Cerebrospinal Fluid Oxidative Stress Biomarkers. - Durazzo, Timothy C; Korecka, Magdalena; Trojanowski, John Q; Weiner, Michael W; O' Hara, Ruth; Ashford, John W; Shaw, Leslie M (J Alzheimers Dis, 2016)
Neurodegenerative diseases and chronic cigarette smoking are associated with increased cerebral oxidative stress (OxS). Elevated F2-isoprostane levels in biological fluid is a recognized marker of OxS. This study assessed the association of active cigarette smoking with F2-isoprostane in concentrations in cognitively-normal elders (CN), and those with mild cognitive impairment (MCI) and probable Alzheimer's disease (AD). Smoking and non-smoking CN (n = 83), MCI (n = 164), and probable AD (n = 101) were compared on cerebrospinal fluid (CSF) iPF2α-III and 8,12, iso-iPF2α-VI F2-isoprostane concentrations. Associations between F2-isoprostane levels and hippocampal volumes were also evaluated. In CN and AD, smokers had higher iPF2α-III concentration; overall, smoking AD showed the highest iPF2α-III concentration across groups. Smoking and non-smoking MCI did not differ on iPF2α-III concentration. No group differences were apparent on 8,12, iso-iPF2α-VI concentration, but across AD, higher 8,12, iso-iPF2α-VI level was related to smaller left and total hippocampal volumes. Results indicate that active cigarette smoking in CN and probable AD is associated with increased central nervous system OxS. Further investigation of factors mediating/moderating the absence of smoking effects on CSF F2-isoprostane levels in MCI is warranted. In AD, increasing magnitude of OxS appeared to be related to smaller hippocampal volume. This study contributes additional novel information to the mounting body of evidence that cigarette smoking is associated with adverse effects on the human central nervous system across the lifespan.

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age-Related Effects of the Apolipoprotein E Gene on Brain Function. - Matura, Silke; Prvulovic, David; Hartmann, Daniel; Scheibe, Monika; Sepanski, Beate; Butz, Marius; Oertel-Knöchel, Viola; Knöchel, Christian; Karakaya, Tarik; Fußer, Fabian; Hattingen, Elke; Pantel, Johannes (J Alzheimers Dis, 2016)
The apolipoprotein E (ApoE) ɛ4 allele is a well-established genetic risk factor for sporadic Alzheimer's disease. Some evidence suggests a negative role of the ApoE ɛ4 allele for cognitive performance in late life, while beneficial effects on cognition have been shown in young age. We investigated age-related effects of the ApoE gene on brain function by assessing cognitive performance, as well as functional activation patterns during retrieval of Face-Name pairs in a group of young (n = 50; age 26.4±4.6 years, 25 ɛ4 carriers) and old (n = 40; age 66.1±7.0 years, 20 ɛ4 carriers) participants. A cross-sectional factorial design was used to examine the effects of age, ApoE genotype, and their interaction on both cognitive performance and the blood oxygenation level dependent (BOLD) brain response during retrieval of Face-Name pairs. While there were no genotype-related differences in cognitive performance, we found a significant interaction of age and ApoE genotype on task-related activation bilaterally in anterior cingulate gyrus and superior frontal gyrus, as well as left and right insula. Old age was associated with increased activity in ɛ4 carriers. The increased BOLD response in old ɛ4 carriers during retrieval could indicate a neurocognitive disadvantage associated with the ɛ4 allele with increasing age. Furthermore, recruitment of neuronal resources resulted in enhanced memory performance in young ɛ4 carriers, pointing to a better neurofunctional capacity associated with the ApoE4 genotype in young age.

Alcohol Consumption and Incident Dementia: Evidence from the Sydney Memory and Ageing Study. - Heffernan, Megan; Mather, Karen A; Xu, Jing; Assareh, Amelia A; Kochan, Nicole A; Reppermund, Simone; Draper, Brian; Trollor, Julian N; Sachdev, Perminder; Brodaty, Henry (J Alzheimers Dis, 2016)
Alcohol consumption is a potentially modifiable risk factor for dementia, but the literature is not completely consistent. This inconsistency may be partly due to an interaction with the apolipoprotein E (APOE) genotype, an established risk factor for Alzheimer's dementia. The aim of this study was to examine whether alcohol consumption is associated with incident dementia or decline in specific cognitive domains over 4 years, and if this effect is modified by APOEɛ4 status. Non-demented community dwelling older adults (70-90 years) from an ongoing longitudinal study were assessed for cognitive impairment in attention/processing speed, language, executive function, visuospatial ability, and memory. Incident dementia was diagnosed according to DSM-IV criteria. Compared to those who did not drink in the previous 12 months, neither low consumption (HR 0.64 95% CI 0.3-1.4) or risky consumption (HR 0.58 95% CI 0.2-1.5) was associated with incident dementia. Carriers of the APOEɛ4 allele were more likely to develop dementia, but there was no significant interaction with alcohol consumption.

Alterations in Phase-Related Prefrontal Activation During Cognitive Tasks and Nicotinic α4β2 Receptor Availability in Alzheimer's Disease. - Oboshi, Yumi; Kikuchi, Mitsuru; Terada, Tatsuhiro; Yoshikawa, Etsuji; Bunai, Tomoyasu; Ouchi, Yasuomi (J Alzheimers Dis, 2016)
BACKGROUND: Evidence shows that the cholinergic system plays an important role in regulating working memory and that working memory-related prefrontal activation decreases with age and neuronal degeneration, such as Alzheimer's disease (AD). However, the relation between attention-related α4β2 nicotinic cholinergic function and task-induced prefrontal activation especially time course-related activation remains to be explored. OBJECTIVE: We aimed to elucidate the relationship between changes in task-induced oxy-hemoglobin concentration (cerebral blood flow, CBF) in the prefrontal cortex and the availability of α4β2 nicotinic receptors in the brain of AD patients in light of their task performance. METHODS: Eleven mild-to-moderate AD patients and eleven normal elderly subjects underwent the near-infrared spectroscopy during easy and difficult working memory tasks for estimating prefrontal CBF changes and positron emission tomography with the α4β2 tracer [18F]2FA-85380 ([18F]2FA) for measuring the α4β2 nicotinic receptor binding. RESULTS: Significant correlations between mean oxy-hemoglobin concentration in the channels with significant [group] main effects and prefrontal [18F]2FA binding were observed during the early easy task period in the normal group and during the late difficult task in the AD group. In addition, those prefrontal CBF responses were significantly correlated with not correct performance but the execution time to spend. CONCLUSION: The α4β2 nicotinic acetylcholine receptors in the prefrontal cortex play an important role in increasing prefrontal activation when attending to novel stimuli, irrespective of the accuracy of the outcome. A delay in the cholinergic-induced increase in prefrontal activation in AD patients might explain their delayed responses in the cognitive task.

Alterations in the Levels of Amyloid-β, Phospholipid Hydroperoxide, and Plasmalogen in the Blood of Patients with Alzheimer's Disease: Possible Interactions between Amyloid-β and These Lipids. - Yamashita, Shinji; Kiko, Takehiro; Fujiwara, Hironori; Hashimoto, Michio; Nakagawa, Kiyotaka; Kinoshita, Mikio; Furukawa, Katsutoshi; Arai, Hiroyuki; Miyazawa, Teruo (J Alzheimers Dis, 2016)
Aside from accumulation of amyloid-β (Aβ) peptide in the brain, Alzheimer's disease (AD) has been reported as being associated with peroxidation of major phospholipids (e.g., phosphatidylcholine (PtdCho)) and degradation of antioxidative phospholipids (e.g., ethanolamine plasmalogen (PlsEtn)). In addition to its presence in the brain, Aβ is also found in blood; however, there is still little information about the levels of PtdCho hydroperoxide (PCOOH) and PlsEtn in the blood of patients with AD. In this study, by assuming a possible interaction among Aβ, PCOOH, and PlsEtn in blood circulation, we evaluated the levels of these molecules and correlations in blood samples that had been obtained from our former AD study for PCOOH measurement (Kiko et al., J Alzheimers Dis28, 593-600, 2012). We found that when compared to controls, plasma from patients with AD showed lower concentrations of PlsEtn species, especially PlsEtn bearing the docosahexaenoic acid (DHA) moiety. In addition, lower PlsEtn and higher PCOOH levels were observed in red blood cells (RBCs) of patients with AD. In both AD and control blood samples, RBC PCOOH levels tended to correlate with plasma levels of Aβ40, and each PlsEtn species showed different correlations with plasma Aβ. These results, together with in vitro data suggesting Aβ aggregation due to a decrease in levels of PlsEtn having DHA, led us to deduce that Aβ is involved in alterations in levels of PCOOH and PlsEtn species observed in the blood of patients with AD.
Keywords: Aged; Amyloid beta-Peptides; Female; Humans; Hydrogen Peroxide; Male; Phosphatidylcholines; Plasmalogens

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered Executive Function in Pre-Mild Cognitive Impairment. - Seo, Eun Hyun; Kim, Hoowon; Lee, Kun Ho; Choo, Il Han (J Alzheimers Dis, 2016)
BACKGROUND: For the early detection of Alzheimer's disease (AD), there is increasing interest in pre-mild cognitive impairment (pre-MCI). OBJECTIVE: We explored the neuropsychological characteristics in a group of pre-MCI and cognitively normal (CN) elderly individuals, with the aim of providing measures sensitive to cognitive change in pre-MCI. METHODS: We included 188 CN elderly and 77 individuals with pre-MCI. All participants underwent comprehensive clinical and neuropsychological assessment. We compared 17 cognitive tests between the CN and pre-MCI groups by using one-way ANOVAs with false discovery rate correction for multiple comparisons. Pearson's correlations were also obtained between episodic memory and executive function tests in the pre-MCI group. RESULTS: The pre-MCI group showed significantly lower scores for visual immediate recall, fluency tests, and Stroop color naming in the color-word incongruent condition than the CN group (p < 0.05). Most of these executive function measures were significantly correlated with episodic memory (p < 0.05). There were no significant group-differences in other tests assessing attention, verbal memory, visuospatial ability, and language. CONCLUSION: Our findings indicate that poor executive function especially demanding inhibition and goal-directed behaviors within time limit could be the characteristics of the very early cognitive sign in the course of AD.

Alzheimer's and Parkinson's Diseases: Expected Economic Impact on Europe-A Call for a Uniform European Strategy. - Maresova, Petra; Klimova, Blanka; Novotny, Michal; Kuca, Kamil (J Alzheimers Dis, 2016)
The purpose of this study is to analyze the economic burden of persons with Alzheimer's disease (AD) and Parkinson's disease (PD) in Europe. On the basis of available data about the number of persons with dementia, their prevalence, and treatment and care costs, a mean cost burden is estimated for the year of 2030 and for the year of 2050 in Europe. The method of retrospective analysis of available sources was used; furthermore, analysis of database data such as WHO and Eurostat, which provide information about the number of older people and people with dementia; and specification of direct and indirect medical and nonmedical costs of patients with AD and PD from current studies was also used. The findings of this study confirm that the number of patients affected with AD and PD, as well as annual costs of the treatment and care of these patients, in the selected European countries are rapidly growing. The cost burden of both AD and PD in the selected European countries rises year by year, and by 2050, the cost burden of both diseases in fact will be almost two times higher in comparison with the year of 2010. In 2050, the overall mean cost burden is estimated to reach 357 billion Euros. The European Union calls for a joint initiative in the development of a uniformed strategic plan in the fight against dementia.

Amyloid-β Increases Activity of Proteasomes Capped with 19S and 11S Regulators. - Morozov, Alexey V; Kulikova, Alexandra A; Astakhova, Tatiana M; Mitkevich, Vladimir A; Burnysheva, Ksenia M; Adzhubei, Alexei A; Erokhov, Pavel A; Evgen'ev, Michail B; Sharova, Natalia P; Karpov, Vadim L; Makarov, Alexander A (J Alzheimers Dis, 2016)
Accumulation of amyloid-β (Aβ) in neurons accompanies Alzheimer's disease progression. In the cytoplasm Aβ influences activity of proteasomes, the multisubunit protein complexes that hydrolyze the majority of intracellular proteins. However, the manner in which Aβ affects the proteolytic activity of proteasomes has not been established. In this study the effect of Aβ42 and Aβ42 with isomerized Asp7 on activity of different forms of proteasomes has been analyzed. It has been shown that Aβ peptides efficiently reduce activity of the 20S proteasomes, but increase activity of the 20S proteasomes capped with the 19S and/or 11S regulators. Modulation of proteasome activity is mainly determined by the C-terminal segment of Aβ (amino acids 17-42). This study demonstrated an important role of proteasome regulators in the interplay between Aβ and the proteasomes.

Analysis of Cerebrospinal Fluid and [11C]PIB PET Biomarkers for Alzheimer's Disease with Updated Protocols. - Wang, Min Jeong; Yi, SangHak; Han, Jee-Young; Park, So Young; Jang, Jae-Won; Chun, In Kook; Giau, Vo Van; Bagyinszky, Eva; Lim, Kun Taek; Kang, Sung Min; An, Seong Soo A; Park, Young Ho; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recently, a Korean research group suggested a consensus protocol, based on the Alzheimer's Disease Neuroimaging Initiative study protocol but with modifications for minimizing the confounding factors, for the evaluation of cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: Here, we analyzed fluid and imaging biomarkers of Alzheimer's disease (AD) in Korean population. We used the updated protocol to propose a more accurate CSF biomarker value for the diagnosis of AD. METHODS: Twenty-seven patients with AD and 30 cognitively normal controls (NC) were enrolled. CSF was collected from 55 subjects (patients with AD = 26, NC = 29) following the Korea consensus protocol. CSF biomarkers were measured using the INNO-BIA AlzBio3 immunoassay, and Pittsburgh compound B (PIB) positron emission tomography (PET) scans were also performed. RESULTS: The cutoff values of CSF amyloid beta 1-42 (Aβ42), total tau (t-Tau), and phosphorylated tau (p-Tau) proteins were 357.1 pg/ml, 83.35 pg/ml, and 38.00 pg/ml, respectively. The cutoff values of CSF t-Tau/Aβ42 and p-Tau/Aβ42 ratio- were 0.210 (sensitivity 100%, specificity 86.21%) and 0.1350 (sensitivity 88.46%, specificity of 92.86%). The concordance rate with PIB-PET was higher using the CSF t-Tau/Aβ42 ratio (κ= 0.849, CI 0.71-0.99) than CSF Aβ42 alone (κ= 0.703, CI 0.51-0.89). CONCLUSIONS: Here, we improved controversial factors associated with the previous CSF study protocol and suggested a new cutoff value for the diagnosis of AD. Our results showed good diagnostic performance for differentiation of AD. Thus, we expect our findings could be a cornerstone in the establishment and clinical application of biomarkers for AD diagnosis.

Apolipoprotein E Related Co-Morbidities and Alzheimer's Disease. - Singhrao, Sim K; Harding, Alice; Chukkapalli, Sasanka; Olsen, Ingar; Kesavalu, Lakshmyya; Crean, StJohn (J Alzheimers Dis, 2016)
The primary goal of advancement in clinical services is to provide a health care system that enhances an individual's quality of life. Incidence of diabetes mellitus, cardiovascular disease, and associated dementia coupled with the advancing age of the population, have led to an increase in the worldwide challenge to the healthcare system. In order to overcome these challenges, prior knowledge of common, reliable risk factors and their effectors is essential. Oral health constitutes one such relatively unexplored but indispensable risk factor for aforementioned co-morbidities, in the form of poor oral hygiene and tooth loss during aging. Behavioral traits such as low education, smoking, poor diet, neglect of oral health, lack of exercise, and hypertension are few of the risk factors that are shared commonly among these conditions. In addition, common genetic susceptibility traits such as the apolipoprotein E gene, together with an individual's lifestyle can also influence the development of co-morbidities such as periodontitis, atherosclerosis/stroke, diabetes, and Alzheimer's disease. This review specifically addresses the susceptibility of apolipoprotein E gene allele 4 as the plausible commonality for the etiology of co-morbidities that eventually result from periodontal diseases and ultimately progress to dementia.
Keywords: Aging; Alzheimer Disease; Animals; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus, Type 2; Humans; Mice; Periodontal Diseases

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association of Physical Function with Clinical and Subclinical Brain Disease: The Framingham Offspring Study. - Camargo, Erica C; Weinstein, Galit; Beiser, Alexa S; Tan, Zaldy S; DeCarli, Charles; Kelly-Hayes, Margaret; Kase, Carlos; Murabito, Joanne M; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Handgrip strength and gait speed are simple measures of physical capability and have been associated with current and future health outcomes. However, studies on their associations with brain structure and function in middle-aged adults are lacking. OBJECTIVE: To assess the relationship of fast-paced walking speed and handgrip strength with risk of dementia, Alzheimer's disease (AD), and stroke, as well as the cross-sectional associations with cognitive and brain magnetic resonance imaging (MRI) measures in a middle-aged community sample. METHODS: Framingham Offspring (n = 2,176; mean age 62, 54% female) had physical function, brain MRI, and cognitive evaluations between 1999 and 2005 and were followed-up for incident dementia AD and stroke until 11 years later. We related walking speed and handgrip strength to incident dementia, AD, and stroke using Cox models, and to brain and cognitive measures using multivariable linear and logistic regression. Models were adjusted for age, sex, education, and vascular risk factors. RESULTS: Slow walking and weak handgrip were associated with more than 2.5-fold increase in risk of AD. Weaker handgrip was associated with an increased risk of incident stroke (HR 1.74, 95% CI: 1.12-2.70/SDU, p = 0.01) in persons ≥65 years. Both measures were associated with lower total brain volume and poorer performance on tests of visual memory, language, executive function, and visuoperceptual function. Slower gait was also related to poorer verbal memory, and weaker handgrip to poorer abstraction. CONCLUSION: Tests of walking speed and handgrip strength may serve as clinical markers of brain structure and function and may improve dementia risk prediction.

Association of Platelet Serotonin Levels in Alzheimer's Disease with Clinical and Cerebrospinal Fluid Markers. - Tajeddinn, Walid; Fereshtehnejad, Seyed-Mohammad; Seed Ahmed, Mohammed; Yoshitake, Takashi; Kehr, Jan; Shahnaz, Tasmin; Milovanovic, Micha; Behbahani, Homira; Höglund, Kina; Winblad, Bengt; Cedazo-Minguez, Angel; Jelic, Vesna; et al. (J Alzheimers Dis, 2016)
INTRODUCTION: Serotonin (5-HT) is involved in the pathology of Alzheimer's disease (AD). OBJECTIVE: We aimed to measure 5-HT level in platelets in AD and explore its association with cerebrospinal fluid (CSF), AD biomarkers (amyloid-β 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau)), and clinical symptoms. METHODS: 15 patients with AD and 20 patients with subjective cognitive impairment (SCI) were included. 5-HT metabolites were measured, in a specific fraction, using high performance liquid chromatography with electrochemical detection (HPLC-ECD). RESULTS: Significantly lower 5-HT concentrations were observed in AD patients compared to SCI patients both after normalization against total protein (p = 0.008) or platelet count (p = 0.019). SCI patients with lower 5-HT level have higher AD CSF biomarkers, total tau (p = 0.026) and tau/Aβ42 ratio (p = 0.001), compared to those with high 5-HT levels. CONCLUSION: AD patients have reduced platelet 5-HT levels. In SCI, lower 5-HT content was associated with a higher AD-CSF biomarker burden.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Associations between Performance on an Abbreviated CogState Battery, Other Measures of Cognitive Function, and Biomarkers in People at Risk for Alzheimer's Disease. - Racine, Annie M; Clark, Lindsay R; Berman, Sara E; Koscik, Rebecca L; Mueller, Kimberly D; Norton, Derek; Nicholas, Christopher R; Blennow, Kaj; Zetterberg, Henrik; Jedynak, Bruno; Bilgel, Murat; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2016)
It is not known whether computerized cognitive assessments, like the CogState battery, are sensitive to preclinical cognitive changes or pathology in people at risk for Alzheimer's disease(AD). In 469 late middle-aged participants from the Wisconsin Registry for Alzheimer's Prevention(mean age 63.8±7 years at testing; 67% female; 39% APOE4+), we examined relationships between a CogState abbreviated battery(CAB) of seven tests and demographic characteristics, traditional paper-based neuropsychological tests as well as a composite cognitive impairment index, cognitive impairment status(determined by consensus review), and biomarkers for amyloid and tau(CSF phosphorylated-tau/Aβ42 and global PET-PiB burden) and neural injury(CSF neurofilament light protein). CSF and PET-PiB were collected in n = 71 and n = 91 participants, respectively, approximately four years prior to CAB testing. For comparison, we examined three traditional tests of delayed memory in parallel. Similar to studies in older samples, the CAB was less influenced by demographic factors than traditional tests. CAB tests were generally correlated with most paper-based cognitive tests examined and mapped onto the same cognitive domains. Greater composite cognitive impairment index was associated with worse performance on all CAB tests. Cognitively impaired participants performed significantly worse compared to normal controls on all but one CAB test. Poorer One Card Learning test performance was associated with higher levels of CSF phosphorylated-tau/Aβ42. These results support the use of the CogState battery as measures of early cognitive impairment in studies of people at risk for AD.

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

A Bacterial Component to Alzheimer's-Type Dementia Seen via a Systems Biology Approach that Links Iron Dysregulation and Inflammagen Shedding to Disease. - Pretorius, Etheresia; Bester, Janette; Kell, Douglas B (J Alzheimers Dis, 2016)
The progression of Alzheimer's disease (AD) is accompanied by a great many observable changes, both molecular and physiological. These include oxidative stress, neuroinflammation, and (more proximal to cognitive decline) the death of neuronal and other cells. A systems biology approach seeks to organize these observed variables into pathways that discriminate those that are highly involved (i.e., causative) from those that are more usefully recognized as bystander effects. We review the evidence that iron dysregulation is one of the central causative pathway elements here, as this can cause each of the above effects. In addition, we review the evidence that dormant, non-growing bacteria are a crucial feature of AD, that their growth in vivo is normally limited by a lack of free iron, and that it is this iron dysregulation that is an important factor in their resuscitation. Indeed, bacterial cells can be observed by ultrastructural microscopy in the blood of AD patients. A consequence of this is that the growing cells can shed highly inflammatory components such as lipopolysaccharides (LPS). These too are known to be able to induce (apoptotic and pyroptotic) neuronal cell death. There is also evidence that these systems interact with elements of vitamin D metabolism. This integrative systems approach has strong predictive power, indicating (as has indeed been shown) that both natural and pharmaceutical iron chelators might have useful protective roles in arresting cognitive decline, and that a further assessment of the role of microbes in AD development is more than highly warranted.

Better Objective Sleep Quality in Older Adults with High Subjective Memory Decline. - Cavuoto, Marina G; Ong, Ben; Pike, Kerryn E; Nicholas, Christian L; Bei, Bei; Kinsella, Glynda J (J Alzheimers Dis, 2016)
BACKGROUND: Sleep disturbance is implicated in memory function across normal aging and neurodegenerative disease. Furthermore, there is mounting evidence to suggest that high levels of subjective memory decline (SMD) may signal very early neurodegenerative changes associated with Alzheimer's disease (AD). This view prompts research examining the relationship between SMD and other risk factors for cognitive decline, including sleep disturbance. OBJECTIVE: To determine whether objective and subjective indices of sleep predict SMD in older adults. METHODS: 181 community-based older adults were divided into groups of high and low SMD based on their responses to the Memory Assessment Complaint Questionnaire (MAC-Q). They undertook two weeks of objective sleep monitoring (actigraphy), and completed a subjective sleep quality assessment using the Pittsburgh Sleep Quality Index. RESULTS: Hierarchical logistic regression indicated that after controlling for demographics and mood, objective sleep quality predicted high SMD group status (ΔNagelkerke R2 = 0.07, χ2 = 9.80 (3), p = 0.020), while subjective sleep quality did not. Contrary to expectation, however, less sleep disruption predicted high SMD. CONCLUSION: These unexpected results may suggest a non-linear trajectory between sleep and memory decline in aging. The findings are discussed in relation to previous research, which taken together, may indicate compensatory sleep patterns of reduced sleep disruption in people with high levels of SMD. These preliminary findings suggest the utility of including analysis of sleep behavior in further longitudinal research of this at-risk group of older people.

Biochemical and Radiological Markers of Alzheimer's Disease Progression. - Dziedzic, Tomasz; Pera, Joanna; Klimkowicz-Mrowiec, Aleksandra; Mroczko, Barbara; Slowik, Agnieszka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative, inevitably progressive disease with a rate of cognitive, functional, and behavioral decline that varies highly from patient to patient. Although several clinical predictors of AD progression have been identified, to our mind in clinical practice there is a lack of a reliable biomarker that enables one to stratify the risk of deterioration. Identification of biomarkers that allow the monitoring of AD progression could change the way physicians and caregivers make treatment decisions. This review summarizes the results of studies on potential biochemical and radiological markers related to AD progression.
Keywords: Alzheimer Disease; Biomarkers; Disease Progression; Humans; Neuroimaging; Radionuclide Imaging

Biofunctionalized Silica Nanoparticles: Standards in Amyloid-β Oligomer-Based Diagnosis of Alzheimer's Disease. - Hülsemann, Maren; Zafiu, Christian; Kühbach, Katja; Lühmann, Nicole; Herrmann, Yvonne; Peters, Luriano; Linnartz, Christina; Willbold, Johannes; Kravchenko, Kateryna; Kulawik, Andreas; Willbold, Sabine; Bannach, Oliver; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) oligomers represent a promising biomarker for the early diagnosis of Alzheimer's disease (AD). However, state-of-the-art methods for immunodetection of Aβ oligomers in body fluids show a large variability and lack a reliable and stable standard that enables the reproducible quantitation of Aβ oligomers. At present, the only available standard applied in these assays is based on a random aggregation process of synthetic Aβ and has neither a defined size nor a known number of epitopes. In this report, we generated a highly stable standard in the size range of native Aβ oligomers that exposes a defined number of epitopes. The standard consists of a silica nanoparticle (SiNaP), which is functionalized with Aβ peptides on its surface (Aβ-SiNaP). The different steps of Aβ-SiNaP synthesis were followed by microscopic, spectroscopic and biochemical analyses. To investigate the performance of Aβ-SiNaPs as an appropriate standard in Aβ oligomer immunodetection, Aβ-SiNaPs were diluted in cerebrospinal fluid and quantified down to a concentration of 10 fM in the sFIDA (surface-based fluorescence intensity distribution analysis) assay. This detection limit corresponds to an Aβ concentration of 1.9 ng l-1 and lies in the sensitivity range of currently applied diagnostic tools based on Aβ oligomer quantitation. Thus, we developed a highly stable and well-characterized standard for the application in Aβ oligomer immunodetection assays that finally allows the reproducible quantitation of Aβ oligomers down to single molecule level and provides a fundamental improvement for the worldwide standardization process of diagnostic methods in AD research.

Biomarkers Differentiating Dementia with Lewy Bodies from Other Dementias: A Meta-Analysis. - Mishima, Aki; Nihashi, Takashi; Ando, Yoshio; Kawai, Hisashi; Kato, Takashi; Ito, Kengo; Terasawa, Teruhiko (J Alzheimers Dis, 2016)
BACKGROUND: Several nuclear imaging and cerebrospinal fluid (CSF) biomarkers are under investigation, aimed at facilitating the differential diagnosis of dementias. OBJECTIVE: To quantitatively synthesize data on test performance in differentiating dementia with Lewy bodies (DLB) from other dementias. METHODS: We searched PubMed (January 2000- March 2015) for English-language publications that assessed a selected set of five imaging and three CSF biomarkers for this purpose. We meta-analyzed measures of agreement between biomarker results and clinical diagnosis. RESULTS: Forty-five publications were eligible. The majority of evidence was based on studies that enrolled representative disease populations. For differentiating between DLB and Alzheimer's disease (AD) or other dementias, metaiodobenzylguanidine scintigraphy and dopamine transporter (DAT) single photon emission computed tomography (SPECT) showed, respectively, excellent (summary kappa = 0.85; 95% confidence interval [95% CI], 0.74-0.96) and good (summary kappa = 0.71; 95% CI, 0.43-0.99) agreement. Metaiodobenzylguanidine scintigraphy appeared superior to fluorodeoxyglucose- positron emission tomography (summary kappa = 0.53; 95% CI, 0.36-0.69) and cerebral blood flow SPECT (summary kappa = 0.40; 95% CI, 0.33-0.47). For differentiating DLB from AD, CSF t-tau levels (summary kappa = 0.68; 95% CI, 0.55-0.82) performed comparably to metaiodobenzylguanidine scintigraphy and DAT SPECT. Sparse direct comparative evidence failed to corroborate these indirect comparisons. CONCLUSION: Metaiodobenzylguanidine scintigraphy and DAT SPECT are highly concordant with clinical diagnosis in differentiating DLB from other dementias. However, given the limitations in the study design, the applicability of these results to real-world differential diagnosis remains unclear. Prospective studies targeting patients with atypical presentations that adopt gold standard tests would reliably estimate the true test performance of these promising biomarkers.
Keywords: Biomarkers; Dementia; Diagnosis, Differential; Humans; Lewy Bodies; PubMed; Radionuclide Imaging; Retrospective Studies

Blood-Based Biomarker Candidates of Cerebral Amyloid Using PiB PET in Non-Demented Elderly. - Westwood, Sarah; Leoni, Emanuela; Hye, Abdul; Lynham, Steven; Khondoker, Mizanur R; Ashton, Nicholas J; Kiddle, Steven J; Baird, Alison L; Sainz-Fuertes, Ricardo; Leung, Rufina; Graf, John; Hehir, Cristina Tan; et al. (J Alzheimers Dis, 2016)
Increasingly, clinical trials for Alzheimer's disease (AD) are being conducted earlier in the disease phase and with biomarker confirmation using in vivo amyloid PET imaging or CSF tau and Aβ measures to quantify pathology. However, making such a pre-clinical AD diagnosis is relatively costly and the screening failure rate is likely to be high. Having a blood-based marker that would reduce such costs and accelerate clinical trials through identifying potential participants with likely pre-clinical AD would be a substantial advance. In order to seek such a candidate biomarker, discovery phase proteomic analyses using 2DGE and gel-free LC-MS/MS for high and low molecular weight analytes were conducted on longitudinal plasma samples collected over a 12-year period from non-demented older individuals who exhibited a range of 11C-PiB PET measures of amyloid load. We then sought to extend our discovery findings by investigating whether our candidate biomarkers were also associated with brain amyloid burden in disease, in an independent cohort. Seven plasma proteins, including A2M, Apo-A1, and multiple complement proteins, were identified as pre-clinical biomarkers of amyloid burden and were consistent across three time points (p <  0.05). Five of these proteins also correlated with brain amyloid measures at different stages of the disease (q <  0.1). Here we show that it is possible to detect a plasma based biomarker signature indicative of AD pathology at a stage long before the onset of clinical disease manifestation. As in previous studies, acute phase reactants and inflammatory markers dominate this signature.

Brain Atrophy of Secondary REM-Sleep Behavior Disorder in Neurodegenerative Disease. - Kim, Hee-Jin; Im, Hyung Kyun; Kim, Juhan; Han, Jee-Young; de Leon, Mony; Deshpande, Anup; Moon, Won-Jin (J Alzheimers Dis, 2016)
BACKGROUND: Rapid eye movement sleep behavior disorder (RBD) may present as an early manifestation of an evolving neurodegenerative disorder with alpha-synucleinopathy. OBJECTIVE: We investigated that dementia with RBD might show distinctive cortical atrophic patterns. METHODS: A total of 31 patients with idiopathic Parkinson's disease (IPD), 23 with clinically probable Alzheimer's disease (AD), and 36 healthy controls participated in this study. Patients with AD and IPD were divided into two groups according to results of polysomnography and rated with a validated Korean version of the RBD screening questionnaire (RBDSQ-K), which covers the clinical features of RBD. Voxel-based morphometry was adapted for detection of regional brain atrophy among groups of subjects. RESULTS: Scores on RBDSQ-K were higher in the IPD group (3.54 ± 2.8) than in any other group (AD, 2.94 ± 2.4; healthy controls, 2.31 ± 1.9). Atrophic changes according to RBDSQ-K scores were characteristically in the posterior part of the brain and brain stem, including the hypothalamus and posterior temporal region including the hippocampus and bilateral occipital lobe. AD patients with RBD showed more specialized atrophic patterns distributed in the posterior and inferior parts of the brain including the bilateral temporal and occipital cortices compared to groups without RBD. The IPD group with RBD showed right temporal cortical atrophic changes. CONCLUSION: The group of patients with neurodegenerative diseases and RBD showed distinctive brain atrophy patterns, especially in the posterior and inferior cortices. These results suggest that patients diagnosed with clinically probable AD or IPD might have mixed pathologies including α-synucleinopathy.

Brain-Specific Basal and Novelty-Induced Alternations in PI3K-Akt and MAPK/ERK Signaling in a Middle-Aged AβPP/PS1 Mouse Model of Alzheimer's Disease. - Guillot, Florence; Kemppainen, Susanna; Lavasseur, Gregoire; Miettinen, Pasi O; Laroche, Serge; Tanila, Heikki; Davis, Sabrina (J Alzheimers Dis, 2016)
Although it is well established that insulin/IGF and BDNF signaling are dysfunctionally regulated in Alzheimer's disease, there are very few studies documenting changes in major target proteins in different murine models of the disease. We investigated a panel of proteins in the PI3K-Akt and MAPK/ERK cascades in parietal cortex, dentate gyrus and CA1 in 13-month-old AβPP/PS1 transgenic mice to determine whether amyloid pathology is associated with basal dysregulation of these proteins or following exposure to novelty. The most striking effect we found was that there was little common regulation of proteins either by pathology alone or exposure to novelty across the three structures, suggesting dysfunctional mechanisms that occur simultaneously have important structure specificity. CA1 shared certain dysfunctional regulation of proteins in the MAPK/ERK cascade, but shared dysfunctional regulation of the PI3K/Akt cascade with the dentate gyrus. Changes in ERK/CREB in transgenic mice did not result in coordinated dysfunction of the downstream transcription factor, Egr1, as it was overexpressed in a normal manner following exposure to novelty. In the PI3K-Akt cascade, there was a flagrant increase in the levels of proteins associated with inflammation, such as NFκB, and structure specific regulation of proteins associated with autophagy, such as mTOR and FOXO1 and lack of regulation of Beclin-1. Finally, Beclin-1 was increased by novelty in wild-type mice but deficient in transgenic mice. Results are interpreted in terms of structure-specific dysfunctional regulation of signaling mechanisms associated with Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Gene Expression Regulation; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mitogen-Activated Protein Kinase Kinases; Mutation; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Presenilin-1; Signal Transduction

Cerebral Microbleeds and Cerebrovascular Reactivity in the General Population: The EDAN Study. - Akoudad, Saloua; Gurol, M Edip; Fotiadis, Panagiotis; Koudstaal, Peter J; Hofman, Albert; Ikram, M Arfan; Greenberg, Steven M; Vernooij, Meike W (J Alzheimers Dis, 2016)
BACKGROUND: In patients with symptomatic cerebral amyloid angiopathy (CAA), cerebrovascular reactivity to visual stimuli is reduced. Lobar microbleeds are a diagnostic hallmark of CAA, but are also highly prevalent in asymptomatic individuals. Recent data suggest that the latter group might have CAA. OBJECTIVE: We investigated whether cerebrovascular reactivity is impaired in asymptomatic individuals with lobar microbleeds. METHODS: From the population-based Rotterdam Study, we invited 35 participants with lobar microbleeds and 15 age-matched controls (all≥55 years) for functional MRI (fMRI) as part of the Early Detection of Angiopathy Network (EDAN) Study. Cerebrovascular reactivity parameters (i.e., amplitude and time to peak responses) were assessed in response to visual stimulation using fMRI. Student's t-test and linear regression were used to compare fMRI parameters in participants with and without microbleeds. RESULTS: Amplitude and time to peak responses did not differ between participants with and without microbleeds (respectively, p = 0.179 and p = 0.555). Participants with microbleeds had slightly higher amplitude responses compared to participants without microbleeds. After excluding individuals with mixed microbleeds (i.e., lobar and non-lobar microbleeds), we found no significant difference in cerebrovascular reactivity for persons with a single microbleed or multiple microbleeds compared to persons without microbleeds. CONCLUSIONS: In the general population, lobar microbleeds may not relate to impaired cerebrovascular reactivity. In asymptomatic individuals, lobar microbleeds may either reflect less advanced CAA pathology insufficient to cause functional vascular impairment, or reflect vascular pathology other than CAA.

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebral White Matter Changes on Therapeutic Response to Rivastigmine in Alzheimer's Disease. - Ho, Bo-Lin; Kao, Yi-Hui; Chou, Mei-Chuan; Yang, Yuan-Han (J Alzheimers Dis, 2016)
BACKGROUND: Rivastigmine has been approved in the treatment of Alzheimer's disease (AD) patients as it can inhibit acetyl- and butyryl-cholinesterase and provide neuroprotective effects involving the synapses. White matter changes (WMCs) are frequently observed in AD, and clinical-pathological correlations imply their possible impacts on cognitive function by interference with cortical and subcortical neuronal pathways. OBJECTIVE: To evaluate the therapeutic effects of rivastigmine in AD patients with cerebral WMCs. METHODS: Clinically diagnosed AD patients from Kaohsiung Municipal Ta-Tung hospital were recruited together with their cranial magnetic resonance imaging and a series of annual psychometric tests, including Mini-Mental State Examination (MMSE) and sum of boxes of clinical dementia rating scale (CDR-SB). WMCs were rated through the modified Fazekas scale for the periventricular and deep WMCs. RESULTS: In total, 87 AD patients treated with rivastigmine were enrolled. Patients at severe stage of WMCs, compared to mild stage ones, had significant improvement evaluated by MMSE (periventricular WMCs, p = 0.025; deep WMCs, p = 0.030), but not CDR-SB. Compared to the worsening group, the clinically improving group had a significant higher ratio of pre-existing hypertension in terms of cognitive performance [p = 0.016, odds ratio (OR) = 3.48, 95% CI = 1.25-10.34], while having younger age (p = 0.043, OR = 0.11, 95% CI = 0.01-1.12) in terms of global status. CONCLUSION: Rivastigmine may provide better benefits in cognitive function, but not global status, for AD patients with more advanced WMCs. The detailed mechanisms still have to be determined in future studies.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers Across the Spectrum of Lewy Body Diseases: Results from a Large Multicenter Cohort. - van Steenoven, Inger; Aarsland, Dag; Weintraub, Daniel; Londos, Elisabet; Blanc, Frédéric; van der Flier, Wiesje M; Teunissen, Charlotte E; Mollenhauer, Brit; Fladby, Tormod; Kramberger, Milica G; Bonanni, Laura; Lemstra, Afina W (J Alzheimers Dis, 2016)
BACKGROUND: Concomitant Alzheimer's disease (AD) pathology is observed in Lewy body diseases (LBD), but the clinical impact is unknown. Only a few biomarker studies in LBD exist and have included small cohorts from single centers. OBJECTIVE: We aimed to evaluate the prevalence of abnormal cerebrospinal fluid (CSF) AD biomarkers across the spectrum of LBD in a large multicenter cohort and to assess whether an AD biomarker profile was associated with demographic and clinical differences in dementia with Lewy bodies (DLB). METHODS: We included 375 DLB patients, 164 Parkinson's disease (PD) patients without dementia, and 55 PD patients with dementia (PDD) from 10 centers. CSF amyloid-beta42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) values were dichotomized as abnormal or normal according to locally available cut-off values. A CSF AD profile was defined as abnormal Aβ42 combined with abnormal t-tau and/or p-tau. RESULTS: A substantial proportion of DLB patients had abnormal values for CSF Aβ42, t-tau, and p-tau, while abnormal values were uncommon in PD without dementia. Patients with PDD had values in between. A CSF AD profile was observed in 25% of DLB patients, compared with only 9% of PDD and 3% of PD without dementia. Within DLB, patients with a CSF AD profile were older, more often female, performed worse on the Mini-Mental State Examination, and had shorter disease duration compared with patients with normal CSF. CONCLUSION: A CSF AD profile is more common in DLB compared with PDD and PD, and is associated with more severe cognitive impairment in DLB.

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Changes in Neural Connectivity and Memory Following a Yoga Intervention for Older Adults: A Pilot Study. - Eyre, Harris A; Acevedo, Bianca; Yang, Hongyu; Siddarth, Prabha; Van Dyk, Kathleen; Ercoli, Linda; Leaver, Amber M; Cyr, Natalie St; Narr, Katherine; Baune, Bernhard T; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2016)
BACKGROUND: No study has explored the effect of yoga on cognitive decline and resting-state functional connectivity. OBJECTIVES: This study explored the relationship between performance on memory tests and resting-state functional connectivity before and after a yoga intervention versus active control for subjects with mild cognitive impairment (MCI). METHODS: Participants ( ≥ 55 y) with MCI were randomized to receive a yoga intervention or active "gold-standard" control (i.e., memory enhancement training (MET)) for 12 weeks. Resting-state functional magnetic resonance imaging was used to map correlations between brain networks and memory performance changes over time. Default mode networks (DMN), language and superior parietal networks were chosen as networks of interest to analyze the association with changes in verbal and visuospatial memory performance. RESULTS: Fourteen yoga and 11 MET participants completed the study. The yoga group demonstrated a statistically significant improvement in depression and visuospatial memory. We observed improved verbal memory performance correlated with increased connectivity between the DMN and frontal medial cortex, pregenual anterior cingulate cortex, right middle frontal cortex, posterior cingulate cortex, and left lateral occipital cortex. Improved verbal memory performance positively correlated with increased connectivity between the language processing network and the left inferior frontal gyrus. Improved visuospatial memory performance correlated inversely with connectivity between the superior parietal network and the medial parietal cortex. CONCLUSION: Yoga may be as effective as MET in improving functional connectivity in relation to verbal memory performance. These findings should be confirmed in larger prospective studies.

Characterizing Aging, Mild Cognitive Impairment, and Dementia with Blood-Based Biomarkers and Neuropsychology. - Kleinschmidt, Martin; Schoenfeld, Robby; Göttlich, Claudia; Bittner, Daniel; Metzner, Jürgen Erich; Leplow, Bernd; Demuth, Hans-Ulrich (J Alzheimers Dis, 2016)
BACKGROUND: Current treatment in Alzheimer's disease (AD) is initiated at a stage where the brain already has irreversible structural deteriorations. Therefore, the concept of treatment prior to obvious cognitive deficits has become widely accepted, and simple biochemical tests to discriminate normal aging from prodromal or demented stages are now common practice. OBJECTIVE: The objective of the study was the differentiation of controls, mild cognitive impairment (MCI) and AD patients by novel blood-based assays in combination with neuropsychological tests. METHODS: In a cross-sectional study, 143 subjects aged 18 to 85 years were recruited. All participants were classified by a comprehensive neuropsychological assessment. Blood samples were analyzed for several amyloid-β (Aβ) species, pro-inflammatory markers, anti-Aβ autoantibodies, and ApoE allele status, respectively. RESULTS: Plasma Aβ1-42 was significantly decreased in MCI and AD compared to age-matched controls, whereas Aβ1-40 did not differ, but increases with age in healthy controls. The Aβ1-42 to Aβ1-40 ratio was stepwise decreased from age-matched controls via MCI to AD, and shows a clear correlation with memory scores. Reduced Aβ1-42 and Aβ1-42 to Aβ1-40 ratio have strongly correlated with carrying ApoE ɛ4 allele. Autoantibodies against pyroglutamate-modified Aβ, but only a certain subclass, were significantly decreased in AD compared to MCI and age-matched controls, whereas autoantibodies against the unmodified N-terminus of Aβ did not differ. CONCLUSION: Comprehensive sample preparation and assay standardization enable reliable usage of plasma Aβ for diagnosis of MCI and AD. Anti-pGlu-Aβ autoantibodies correlate with cognition, but not with ApoE, supporting the associated plasma Aβ analysis with additional and independent information.
Keywords: Activities of Daily Living; Adolescent; Adult; Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Analysis of Variance; Apolipoproteins E; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Cytokines; Dementia; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; Young Adult

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Cholesterol, 24-Hydroxycholesterol, and 27-Hydroxycholesterol as Surrogate Biomarkers in Cerebrospinal Fluid in Mild Cognitive Impairment and Alzheimer's Disease: A Meta-Analysis. - Wang, Hua-Long; Wang, Yan-Yong; Liu, Xin-Gang; Kuo, Sheng-Han; Liu, Na; Song, Qiao-Yun; Wang, Ming-Wei (J Alzheimers Dis, 2016)
Abnormal cholesterol metabolism is an established feature of Alzheimer's disease (AD). Cerebrospinal fluid (CSF) is the fluid surrounding the central nervous system, and the protein and lipid content alterations in the CSF could be biomarkers for degenerative changes in the brain. The laboratory diagnosis of AD is limited to the analysis of three biomarkers in CSF: Aβ42, total tau, and phospho-tau. The purpose of this analysis is to systematically analyze the available data describing the biomarkers of cholesterol and its metabolites in the CSF of subjects with AD. MEDLINE, EMBASE, and the Cochrane Central database were systematically queried to collect studies that have evaluated the markers of cholesterol and its metabolites in the CSF of subjects with mild cognitive impairment (MCI) or AD and age-matched controls. Analysis of the published data shows that the levels of cholesterol are increased in MCI subjects; 24-hydroxycholesterol and 27-hydroxycholesterol are elevated in AD and MCI subjects compared to controls. There is a significant dysfunction of cholesterol metabolism in the CSF of AD subjects. This analysis indicates that in addition to the available biomarkers in the CSF, such as Aβ42, total tau, and phospho-tau, 24-hydroxycholesterol, 27-hydroxycholesterol, and cholesterol appear to be sensitive biomarkers for the evaluation of MCI and AD.
Keywords: Alzheimer Disease; Cholesterol; Cognitive Dysfunction; Databases, Bibliographic; Humans; Hydroxycholesterols

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Application of Automatic Segmentation of Medial Temporal Lobe Subregions in Prodromal and Dementia-Level Alzheimer's Disease. - Gertje, Eske Christiane; Pluta, John; Das, Sandhitsu; Mancuso, Lauren; Kliot, Dasha; Yushkevich, Paul; Wolk, David (J Alzheimers Dis, 2016)
BACKGROUND: Volumetry of medial temporal lobe (MTL) structures to diagnose Alzheimer's disease (AD) in its earliest symptomatic stage could be of great importance for interventions or disease modifying pharmacotherapy. OBJECTIVE: This study aimed to demonstrate the first application of an automatic segmentation method of MTL subregions in a clinical population. Automatic segmentation of magnetic resonance images (MRIs) in a research population has previously been shown to detect evidence of neurodegeneration in MTL subregions and to help discriminate AD and mild cognitive impairment (MCI) from a healthy comparison group. METHODS: Clinical patients were selected and T2-weighted MRI scan quality was checked. An automatic segmentation method of hippocampal subfields (ASHS) was applied to scans of 67 AD patients, 38 amnestic MCI patients, and 57 healthy controls. Hippocampal subfields, entorhinal cortex (ERC), and perirhinal cortex were automatically labeled and subregion volumes were compared between groups. RESULTS: One fourth of all scans were excluded due to bad scan quality. There were significant volume reductions in all subregions, except BA36, in aMCIs (p < 0.001), most prominently in Cornu Ammonis 1 (CA1) and ERC, and in all subregions in AD. However, sensitivity of CA1 and ERC hardly differed from sensitivity of WH in aMCI and AD. CONCLUSION: Applying automatic segmentation of MTL subregions in a clinical setting as a potential biomarker for prodromal AD is feasible, but issues of image quality due to motion remain to be addressed. CA1 and ERC provided strongest group discrimination in differentiating aMCIs from controls, but discriminatory power of different subfields was low overall.

Clinical Conversion or Reversion of Mild Cognitive Impairment in Community versus Hospital Based Studies: GDEMCIS (Gwangju Dementia and Mild Cognitive Impairment Study) and CREDOS (Clinical Research Center for Dementia of South Korea). - Roh, Hyun Woong; Hong, Chang Hyung; Lee, Yunhwan; Lee, Kang Soo; Chang, Ki Jung; Kang, Dae Ryong; Lee, Jung-Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Doh Kwan; et al. (J Alzheimers Dis, 2016)
BACKGROUND: In keeping with increasing interest in dementia, few recent studies suggest that clinical course of mild cognitive impairment vary across different studies with hospital-based subjects showing higher rates of conversion than community-based subjects. OBJECTIVE: The main objective of the present study was to assess whether the clinical conversion or reversion rates differ according to recruitment source. METHODS: The baseline study subjects comprised of patients who were diagnosed with mild cognitive impairment in community-based GDEMCIS or hospital-based CREDOS. The two studies had nearly the same protocol and were performed over a similar period. We used propensity score matching for baseline comparability. After that, Cox proportional hazards regression analyses were conducted to estimate the hazard ratios and 95% confidence intervals of clinical conversion or reversion. RESULTS: Based on 89 GDEMCIS subjects, 1 : 4 propensity score matching was conducted and 356 CREDOS subjects were selected. After adjusting for covariates including baseline demographics, comorbidity, depression, disability, and neuropsychological result, Cox proportional hazard regression analysis for time to clinical conversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 2.13 (95% CI, 1.08-4.21), as compared to recruitment from community-based GDEMCIS. Similarly, Cox proportional hazard regression analysis for time to reversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 0.34 (95% CI, 0.20-0.59), as compared to recruitment from community-based GDEMCIS. CONCLUSION: The present study demonstrated that even after the matching process and adjustments for baseline covariates, recruitment source greatly affected the course of mild cognitive impairment.

Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter

Cognitive Reserve in Alzheimer's Dementia: Diagnostic Accuracy of a Testing-the-Limits Paradigm. - Küster, Olivia C; Kösel, Jonas; Spohn, Stephanie; Schurig, Niklas; Tumani, Hayrettin; von Arnim, Christine A F; Uttner, Ingo (J Alzheimers Dis, 2016)
Individuals with higher cognitive reserve are more able to cope with pathological brain alterations, potentially due to the application of more efficient cognitive strategies. The extent to which an individual's cognitive performance can be increased by advantageous conditions differs substantially between patients with Alzheimer's dementia (AD) and healthy older adults and can be assessed with the Testing-the-Limits (TtL) approach. Thus, TtL has been proposed as a tool for the early diagnosis of AD. Here, we report the diagnostic accuracy of a memory TtL paradigm to discriminate between AD patients and controls. The TtL paradigm was administered to 57 patients with clinically diagnosed AD and 94 controls. It consisted of a pre-test condition, representing baseline cognitive performance, the presentation of an encoding strategy, and two subsequent post-test conditions, representing learning potential. Receiver operating characteristic (ROC) curves were analyzed for each condition in order to receive optimal cutoff points along with their sensitivity and specificity and to compare the diagnostic accuracy of the conditions. Differentiation between AD patients and controls, indicated by the area under the ROC curve, increased significantly for the TtL post-test and total error scores compared to the pre-test score. The combined error score in the two post-tests could differentiate between AD patients and controls with a sensitivity of 0.93 and a specificity of 0.80. The presented approach can be carried out in 25 minutes and thus constitutes a time- and cost-effective way to diagnose AD with high accuracy.

Cognitive Stimulation for People with Dementia in Long-Term Care Facilities: Baseline Cognitive Level Predicts Cognitive Gains, Moderated by Depression. - Middelstädt, Jennifer; Folkerts, Ann-Kristin; Blawath, Sabrina; Kalbe, Elke (J Alzheimers Dis, 2016)
BACKGROUND: Increasing evidence demonstrates the efficacy of cognitive stimulation (CS) in individuals with dementia. However, conducting studies in nursing homes engenders specific challenges that have limited the data gathered on this topic so far. OBJECTIVE: The aim of this randomized controlled trial was to investigate the effects of CS on cognition, quality of life (QoL), behavioral symptoms, and activities of daily life in persons with dementia living in nursing homes. We further aimed to identify predictors of the intervention's benefits. METHODS: Seventy-one persons with mild to moderate dementia were randomly allocated to the experimental group (EG; n = 36) that visited a CS program twice weekly for eight weeks or to the control group (CG; n = 35) that was receiving usual care. Neuropsychological tests were conducted before and after the intervention period and at six-week follow-up. RESULTS: There were no significant interaction effects Time×Group for the outcome measures. However, regression analysis revealed that a low cognitive baseline level predicted cognitive improvements. Furthermore, a low baseline level of QoL predicted a QoL benefit. For both findings, depression was a significant moderator, meaning that persons with fewer depressive symptoms had a higher probability of showing improvements. CONCLUSION: This study provides data on profiles of patients who are most likely to profit from CS intervention in nursing-home settings and demonstrates that treatment of depression is of the utmost relevance for a positive outcome of CS. Living conditions will have to be considered more thoroughly in future research.

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Collapsin Response Mediator Protein-2 (CRMP2) is a Plausible Etiological Factor and Potential Therapeutic Target in Alzheimer's Disease: Comparison and Contrast with Microtubule-Associated Protein Tau. - Hensley, Kenneth; Kursula, Petri (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) has long been viewed as a pathology that must be caused either by aberrant amyloid-β protein precursor (AβPP) processing, dysfunctional tau protein processing, or a combination of these two factors. This is a reasonable assumption because amyloid-β peptide (Aβ) accumulation and tau hyperphosphorylation are the defining histological features in AD, and because AβPP and tau mutations can cause AD in humans or AD-like features in animal models. Nonetheless, other protein players are emerging that one can argue are significant etiological players in subsets of AD and potentially novel, druggable targets. In particular, the microtubule-associated protein CRMP2 (collapsin response mediator protein-2) bears striking analogies to tau and is similarly relevant to AD. Like tau, CRMP2 dynamically regulates microtubule stability; it is acted upon by the same kinases; collects similarly in neurofibrillary tangles (NFTs); and when sequestered in NFTs, complexes with critical synapse-stabilizing factors. Additionally, CRMP2 is becoming recognized as an important adaptor protein involved in vesicle trafficking, amyloidogenesis and autophagy, in ways that tau is not. This review systematically compares the biology of CRMP2 to that of tau in the context of AD and explores the hypothesis that CRMP2 is an etiologically significant protein in AD and participates in pathways that can be rationally engaged for therapeutic benefit.
Keywords: Alzheimer Disease; Animals; Humans; Intercellular Signaling Peptides and Proteins; Nerve Tissue Proteins; tau Proteins

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Connected Language in Late Middle-Aged Adults at Risk for Alzheimer's Disease. - Mueller, Kimberly Diggle; Koscik, Rebecca L; Turkstra, Lyn S; Riedeman, Sarah K; LaRue, Asenath; Clark, Lindsay R; Hermann, Bruce; Sager, Mark A; Johnson, Sterling C (J Alzheimers Dis, 2016)
Connected language is often impaired among people with Alzheimer's disease (AD), yet little is known about when language difficulties first emerge on the path to a clinical diagnosis. The objective of this study was to determine whether individuals with psychometric (preclinical) evidence of amnestic mild cognitive impairment (pMCI) showed deficits in connected language measures. Participants were 39 pMCI and 39 cognitively healthy (CH) adults drawn from the Wisconsin Registry for Alzheimer's Prevention, who were matched for age, literacy, and sex. Participants completed a connected language task in which they described the Cookie Theft picture from the Boston Diagnostic Aphasia Examination. Language samples were analyzed across three language domains: content, syntactic complexity, and speech fluency. Paired t-tests were used to compare CH and pMCI groups on all variables, and Cohen's d effect sizes were calculated for each comparison. The CH and pMCI groups differed significantly on measures of content (e.g., CH group produced more semantic units, more unique words and had larger idea density, on average, than the pMCI group). The picture description findings are consistent with previous retrospective studies showing semantic language differences in adults with autopsy-confirmed AD. Given that these comparisons are between cognitively healthy and pMCI individuals (before a clinical MCI diagnosis), these findings may represent subtle language difficulty in spontaneous speech, and may be predictive of larger language changes over time.

Contribution of the Cholinergic System to Verbal Memory Performance in Mild Cognitive Impairment. - Peter, Jessica; Lahr, Jacob; Minkova, Lora; Lauer, Eliza; Grothe, Michel J; Teipel, Stefan; Köstering, Lena; Kaller, Christoph P; Heimbach, Bernhard; Hüll, Michael; Normann, Claus; Nissen, Christoph; et al. (J Alzheimers Dis, 2016)
Acetylcholine is critically involved in modulating learning and memory function, which both decline in neurodegeneration. It remains unclear to what extent structural and functional changes in the cholinergic system contribute to episodic memory dysfunction in mild cognitive impairment (MCI), in addition to hippocampal degeneration. A better understanding is critical, given that the cholinergic system is the main target of current symptomatic treatment in mild to moderate Alzheimer's disease. We simultaneously assessed the structural and functional integrity of the cholinergic system in 20 patients with MCI and 20 matched healthy controls and examined their effect on verbal episodic memory via multivariate regression analyses. Mediating effects of either cholinergic function or hippocampal volume on the relationship between cholinergic structure and episodic memory were computed. In MCI, a less intact structure and function of the cholinergic system was found. A smaller cholinergic structure was significantly correlated with a functionally more active cholinergic system in patients, but not in controls. This association was not modulated by age or disease severity, arguing against compensational processes. Further analyses indicated that neither functional nor structural changes in the cholinergic system influence verbal episodic memory at the MCI stage. In fact, those associations were fully mediated by hippocampal volume. Although the cholinergic system is structurally and functionally altered in MCI, episodic memory dysfunction results primarily from hippocampal neurodegeneration, which may explain the inefficiency of cholinergic treatment at this disease stage.

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Diagnostic Accuracy of MRI and Additional [18F]FDG-PET for Behavioral Variant Frontotemporal Dementia in Patients with Late Onset Behavioral Changes. - Vijverberg, Everard G B; Wattjes, Mike P; Dols, Annemiek; Krudop, Welmoed A; Möller, Christiane; Peters, Anne; Kerssens, Cora J; Gossink, Flora; Prins, Niels D; Stek, Max L; Scheltens, Philip; van Berckel, Bart N M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Neuroimaging has a reasonable accuracy to differentiate behavioral variant frontotemporal dementia (bvFTD) from other neurodegenerative disorders, its value for the differentiation of bvFTD among subjects with acquired behavioral disturbances is unknown. OBJECTIVE: To determine the diagnostic accuracy of MRI, additional [18F]FDG-PET, and their combination for bvFTD among subjects with late onset behavioral changes. METHODS: Patients with late onset behavioral changes referred to a memory clinic or psychiatric services were included. At baseline, 111 patients had a brain MRI scan and 74 patients received an additional [18F]FDG-PET when the MRI was inconclusive. The consensus diagnosis after two-year-follow-up was used as the gold standard to calculate sensitivity and specificity for baseline neuroimaging. RESULTS: 27 patients had probable/definite bvFTD and 84 patients had a non-bvFTD diagnosis (primary psychiatric diagnosis or other neurological disorders). MRI had a sensitivity of 70% (95% CI 52-85%) with a specificity of 93% (95% CI 86-97%). Additional [18F]FDG-PET had a sensitivity of 90% (95% CI 66-100%) with a specificity of 68% (95% CI 56-79%). The sensitivity of combined neuroimaging was 96% (95% CI 85-100%) with a specificity of 73% (95% CI 63-81%). In 66% of the genetic FTD cases, MRI lacked typical frontotemporal atrophy. 40% of cases with a false positive [18F]FDG-PET scan had a primary psychiatric diagnosis. CONCLUSION: A good diagnostic accuracy was found for MRI and additional [18F]FDG-PET for bvFTD in patients with late onset behavioral changes. Caution with the interpretation of neuroimaging results should especially be taken in cases with a genetic background and in cases with a primary psychiatric differential diagnosis where [18F]FDG-PET is the only abnormal investigation.

Differences in Depressive Patterns According to Disease Severityin Early-Onset Alzheimer's Disease. - Yoon, Bora; Yang, Dong Won; Hong, Yun Jeong; Choi, Seong Hye; Park, Sun Ah; Park, Hee Kyung; Kim, Yong Duk; Shim, Yong S (J Alzheimers Dis, 2016)
BACKGROUND & OBJECTIVE: Depression frequently combines with dementia, including early-onset Alzheimer's disease (EOAD). We investigated differences in prevalence and characteristics of depressive symptoms according to dementia severity in EOAD patients. METHODS: The 15-item Korean version of the Geriatric Depression Scale (GDS-15) was administered to 412 EOAD patients. Factor analysis was used to assess GDS-15 factor structure. We subdivided participants into three groups by disease severity, then compared the frequencies and scores of individual GDS-15 items and performed logistic regression analysis to assess associations between depressive symptoms and EOAD stage. RESULTS: Factor analysis yielded three factor categories: 1) "hopelessness and ominousness" (symptoms no. 6, 8, 12, 14, 15); 2) "unhappiness and dissatisfaction" (no. 1, 3, 5, 7, 11); and 3) "monotony and lack of energy" (no. 2, 4, 9, 10, 13). Factor 2 depressive symptoms (no. 1, 5, 11) were less common in moderate EOAD. The risk of Factor 1 symptoms: no. 12 (OR, 2.04; 95% CI, 1.19-3.50; p = 0.010) and 14 (OR, 1.84; 95% CI, 1.07-3.16; p = 0.028) was higher in mild than very mild EOAD. The risk of Factor 2 symptoms: no. 9 (OR, 2.69; 95% CI, 1.08-6.71; p = 0.033) and 13 (OR, 2.12; 95% CI, 1.02-4.40; p = 0.043) was higher in moderate than mild EOAD. CONCLUSION: We confirmed that depressive symptoms differ according to EOAD severity. When assessing depressive symptoms related to dementia progression, we recommend focusing on "hopelessness and ominousness" in very mild EOAD and "unhappiness and dissatisfaction" in mild EOAD.

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Dihydropyridine Derivatives Modulate Heat Shock Responses and have a Neuroprotective Effect in a Transgenic Mouse Model of Alzheimer's Disease. - Kasza, Ágnes; Hunya, Ákos; Frank, Zsuzsa; Fülöp, Ferenc; Török, Zsolt; Balogh, Gábor; Sántha, Miklós; Bálind, Árpád; Bernáth, Sándor; Blundell, Katie L I M; Prodromou, Chrisostomos; Horváth, Ibolya; et al. (J Alzheimers Dis, 2016)
Heat shock proteins (Hsps) have chaperone activity and play a pivotal role in the homeostasis of proteins by preventing misfolding, by clearing aggregated and damaged proteins from cells, and by maintaining proteins in an active state. Alzheimer's disease (AD) is thought to be caused by amyloid-β peptide that triggers tau hyperphosphorylation, which is neurotoxic. Although proteostasis capacity declines with age and facilitates the manifestation of neurodegenerative diseases such as AD, the upregulation of chaperones improves prognosis. Our research goal is to identify potent Hsp co-inducers that enhance protein homeostasis for the treatment of AD, especially 1,4-dihydropyridine derivatives optimized for their ability to modulate cellular stress responses. Based on favorable toxicological data and Hsp co-inducing activity, LA1011 was selected for the in vivo analysis of its neuroprotective effect in the APPxPS1 mouse model of AD. Here, we report that 6 months of LA1011 administration effectively improved the spatial learning and memory functions in wild type mice and eliminated neurodegeneration in double mutant mice. Furthermore, Hsp co-inducer therapy preserves the number of neurons, increases dendritic spine density, and reduces tau pathology and amyloid plaque formation in transgenic AD mice. In conclusion, the Hsp co-inducer LA1011 is neuroprotective and therefore is a potential pharmaceutical candidate for the therapy of neurodegenerative diseases, particularly AD.

Discovering New Genes in the Pathways of Common Sporadic Neurodegenerative Diseases: A Bioinformatics Approach. - Kim, Yong Hwan; Beak, Seung Han; Charidimou, Andreas; Song, Min (J Alzheimers Dis, 2016)
Late onset Alzheimer's disease (AD) and Parkinson's disease (PD) are mostly "sporadic" age-related neurodegenerative disorders, but with a clear genetic component. However, their genetic architecture is complex and heterogeneous, largely remaining a conundrum, with only a handful of well-established genetic risk factors consistently associated with these diseases. It is possible that numerous, yet undiscovered, AD and PD related genes might exist. We focused on the 'gene' as a mediator to find new potential genes that might have a relationship with both disorders using bio-literature mining techniques. Based on Entrez Gene, we extracted the genes and directional gene-gene relation in the entire MEDLINE records and then constructed a directional gene-gene network. We identified common genes associated with two different but related diseases by performing shortest path analysis on the network. With our approach, we were able to identify and map already known genes that have a direct relationship with PD and AD. In addition, we identified 7 genes previously unknown to be a bridge between these two disorders. We confirmed 4 genes, ROS1, FMN1, ATP8A2, and SNORD12C, by biomedical literature and further checked 3 genes, ERVK-10, PRS, and C7orf49, that might have a high possibility to be related with both diseases. Additional experiments were performed to demonstrate the effectiveness of our proposed method. Comparing to the co-occurrence approach, our approach detected 25% more candidate genes and verified 10% more genes that have the relationship between both diseases than the co-occurrence approach did.
Keywords: Computational Biology; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Humans; Male; MEDLINE; Neurodegenerative Diseases

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Discrepancy in Expression of β-Secretase and Amyloid-β Protein Precursor in Alzheimer-Related Genes in the Rat Medial Temporal Lobe Cortex Following Transient Global Brain Ischemia. - Pluta, Ryszard; Kocki, Janusz; Ułamek-Kozioł, Marzena; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Brzozowska, Judyta; Furmaga-Jabłońska, Wanda; Bogucka-Kocka, Anna; Czuczwar, Stanisław J (J Alzheimers Dis, 2016)
Brain ischemia may be causally related with Alzheimer's disease. Presumably, β-secretase and amyloid-β protein precursor gene expression changes may be associated with Alzheimer's disease neuropathology. Consequently, we have examined quantitative changes in both β-secretase and amyloid-β protein precursor genes in the medial temporal lobe cortex with the use of quantitative rtPCR analysis following 10-min global brain ischemia in rats with survival of 2, 7, and 30 days. The greatest significant overexpression of β-secretase gene was noted on the 2nd day, while on days 7-30 the expression of this gene was only modestly downregulated. Amyloid-β protein precursor gene was downregulated on the 2nd day, but on days 7-30 postischemia, there was a significant reverse tendency. Thus, the demonstrated alterations indicate that the considerable changes of expression of β-secretase and amyloid-β protein precursor genes may be connected with a response of neurons in medial temporal lobe cortex to transient global brain ischemia. Finally, the ischemia-induced gene changes may play a key role in a late and slow onset of Alzheimer-type pathology.
Keywords: Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Brain Ischemia; Disease Models, Animal; Down-Regulation; Female; Rats; Rats, Wistar; Temporal Lobe; Time Factors

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Do Chinese Researchers Conduct Ethical Research and Use Ethics Committee Review in Clinical Trials of Anti-Dementia Drugs? An Analysis of Biomedical Publications Originating from China. - Zeng, Lingfeng; Liang, Weixiong; Pan, Jianke; Cao, Ye; Liu, Jun; Wang, Qi; Wang, Lu; Zou, Yuanping; Wang, Kezhu; Kong, Lingshuo; Xie, Hui; Xu, Weihua; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Medical research using human participants must conform to the basic ethical principles found in the Declaration of Helsinki (DoH) of the World Medical Association. OBJECTIVE: The purpose of this review was to assess whether journals in China have improved in regard to the fulfillment of ethical disclosure procedures for clinical trials of anti-dementia drugs. METHODS: Four medical databases were searched for articles reporting clinical trials of oral anti-dementia drugs published in China in 2003, 2009, and 2014. The frequencies of reporting of informed consent from participants (ICP), approval of a regional ethical committee (REC), reference to DoH, and study registration were estimated respectively. Statistical analyses were conducted with SPSS v21 software. RESULTS: Among those randomized controlled trials published in 2003, 2009, and 2014, disclosure of REC approval was present for 2.67%, 1.15%, and 6.84%; statements of ICP were included in 9.33%, 7.76%, and 17.34%; reference to DoH was found for 4.00%, 1.44%, and 7.45%; and study registration reporting was included in 2.67%, 2.59%, and 9.28%, respectively. Improvements to reporting rates between 2009 and 2014 were seen, with more than twice as many trials reporting REC approval, ICP, reference to DoH, and study registration compared with 2009. CONCLUSION: Compared with 2003 and 2009, reporting rates for REC approval, ICP, reference to DoH, and study registration for clinical trials of anti-dementia drugs were enhanced in 2014 in the major medical journals of China. However, biomedical publications without definite statements of ethical considerations remain common, and this continues to be seen in Chinese journals. It is imperative that measures are taken to reinforce the ethical protection in clinical trials in China.

Dysregulation of Autophagy, Mitophagy, and Apoptotic Genes in the Medial Temporal Lobe Cortex in an Ischemic Model of Alzheimer's Disease. - Ułamek-Kozioł, Marzena; Kocki, Janusz; Bogucka-Kocka, Anna; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Furmaga-Jabłońska, Wanda; Brzozowska, Judyta; Czuczwar, Stanisław J; Pluta, Ryszard (J Alzheimers Dis, 2016)
Ischemic brain damage is a pathological incident that is often linked with medial temporal lobe cortex injury and finally its atrophy. Post-ischemic brain injury associates with poor prognosis since neurons of selectively vulnerable ischemic brain areas are disappearing by apoptotic program of neuronal death. Autophagy has been considered, after brain ischemia, as a guardian against neurodegeneration. Consequently, we have examined changes in autophagy (BECN 1), mitophagy (BNIP 3), and apoptotic (caspase 3) genes in the medial temporal lobe cortex with the use of quantitative reverse-transcriptase PCR following transient 10-min global brain ischemia in rats with survival 2, 7, and 30 days. The intense significant overexpression of BECN 1 gene was noted on the 2nd day, while on days 7-30 the expression of this gene was still upregulated. BNIP 3 gene was downregulated on the 2nd day, but on days 7-30 post-ischemia, there was a significant reverse tendency. Caspase 3 gene, associated with apoptotic neuronal death, was induced in the same way as BNIP 3 gene after brain ischemia. Thus, the demonstrated changes indicate that the considerable dysregulation of expression of BECN 1, BNIP 3, and caspase 3 genes may be connected with a response of neuronal cells in medial temporal lobe cortex to transient complete brain ischemia.

Dysregulation of Elongation Factor 1A Expression is Correlated with Synaptic Plasticity Impairments in Alzheimer's Disease. - Beckelman, Brenna C; Day, Stephen; Zhou, Xueyan; Donohue, Maggie; Gouras, Gunnar K; Klann, Eric; Keene, C Dirk; Ma, Tao (J Alzheimers Dis, 2016)
Synaptic dysfunction may represent an early and crucial pathophysiology in Alzheimer's disease (AD). Recent studies implicate a connection between synaptic plasticity deficits and compromised capacity of de novo protein synthesis in AD. The mRNA translational factor eukaryotic elongation factor 1A (eEF1A) is critically involved in several forms of long-lasting synaptic plasticity. By examining postmortem human brain samples, a transgenic mouse model, and application of synthetic human Aβ42 on mouse hippocampal slices, we demonstrated that eEF1A protein levels were significantly decreased in AD, particularly in the hippocampus. In contrast, brain levels of eukaryotic elongation factor 2 were unaltered in AD. Further, upregulation of eEF1A expression by the adenylyl cyclase activator forskolin, which induces long-lasting synaptic plasticity, was blunted in hippocampal slices derived from Tg2576 AD model mice. Finally, Aβ-induced hippocampal long-term potentiation defects were alleviated by upregulation of eEF1A signaling via brain-specific knockdown of the gene encoding tuberous sclerosis 2. In summary, our findings suggest a strong correlation between the dysregulation of eEF1A synthesis and AD-associated synaptic failure. These findings provide insights into the understanding of molecular mechanisms underlying AD etiology and may aid in identification of novel biomarkers and therapeutic targets.

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

EEG Markers of Dementia with Lewy Bodies: A Multicenter Cohort Study. - Bonanni, Laura; Franciotti, Raffaella; Nobili, Flavio; Kramberger, Milica G; Taylor, John-Paul; Garcia-Ptacek, Sara; Falasca, N Walter; Famá, Francesco; Cromarty, Ruth; Onofrj, Marco; Aarsland, Dag (J Alzheimers Dis, 2016)
Quantitative EEG (QEEG) has demonstrated good discriminative capacity for dementia with Lewy bodies (DLB) diagnosis as compared to Alzheimer's disease (AD) with a predictive value of 100% in a single cohort study. EEG in DLB was characterized by a dominant frequency (DF) in pre-alpha (5.5-7.5 Hz), theta, or delta bands and DF variability (DFV) >1.2 Hz, frequency prevalence (FP) pre-alpha in >40% and FP alpha in <32% of the epochs. To validate the aforementioned QEEG findings in independent cohorts of clinically diagnosed DLB versus AD patients, we analyzed EEG traces of 79 DLB and 133 AD patients (MMSE >20) collected from four European Centers. EEG traces from 19 scalp derivations were acquired as at least 10 min continuous signals and epoched in off-setting as series of 2-second-long epochs, subsequently processed by Fast Fourier Transform (frequency resolution 0.5 Hz). DLB patients showed EEG specific abnormalities in posterior derivations characterized by DF <8 Hz FP pre-alpha >50%, FP alpha <25%. DFV was >0.5 Hz. AD patients displayed stable alpha DF, DFV <0.5 Hz, FP pre-alpha <30%, and FP alpha >55%. DLB and AD differed for DF (p < 10-6), DFV (p < 0.05), FP pre-alpha (p < 10-12) and FP alpha (p < 10-12). Discriminant analysis detected specific cut-offs for every EEG mathematical descriptor; DF = 8, DFV = 2.2 Hz, FP pre-alpha=33%, FP alpha = 41% for posterior derivations. If at least one of the cut-off values was met, the percentage of DLB and AD patients correctly classified was 90% and 64%, respectively. The findings in this multicenter study support the validity of QEEG analysis as a tool for diagnosis in DLB patients.

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People. - Hisatsune, Tatsuhiro; Kaneko, Jun; Kurashige, Hiroki; Cao, Yuan; Satsu, Hideo; Totsuka, Mamoru; Katakura, Yoshinori; Imabayashi, Etsuko; Matsuda, Hiroshi (J Alzheimers Dis, 2016)
Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60-78 years old) completed the follow-up tests. Among the tests, delayed recall verbal memory assessed by the Wechsler Memory Scale-Logical Memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0128). Blood analysis revealed a decreased secretion of inflammatory cytokines, including CCL-2 and IL-8, in the ACS group. MRI analysis using arterial spin labeling showed a suppression in the age-related decline in brain blood flow in the posterior cingulate cortex area in the ACS group, compared to the placebo group (p = 0.0248). In another randomized controlled trial, delayed recall verbal memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0202). These results collectively suggest that ACS may preserve verbal episodic memory and brain perfusion in elderly people, although further study is needed.
Keywords: Adult; Aged; Aging; Anserine; Brain; Carnosine; Cytokines; Dietary Supplements; Double-Blind Method; Female; Gene Expression Regulation; Humans; Image Processing, Computer-Assisted; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Verbal Learning

The Effects of Amnestic Mild Cognitive Impairment on Go/NoGo Semantic Categorization Task Performance and Event-Related Potentials. - Mudar, Raksha A; Chiang, Hsueh-Sheng; Eroh, Justin; Nguyen, Lydia T; Maguire, Mandy J; Spence, Jeffrey S; Kung, Fanting; Kraut, Michael A; Hart, John (J Alzheimers Dis, 2016)
We examined the effects of amnestic mild cognitive impairment (aMCI) on behavioral (response times and error rates) and scalp-recorded event-related potential (ERP) measures of response execution and inhibition, using Go/NoGo tasks involving basic and superordinate semantic categorization. Twenty-five aMCI (16 F; 68.5±8 years) and 25 age- and gender-matched normal control subjects (16 F; 65.4±7.1 years) completed two visual Go/NoGo tasks. In the single car task, responses were made based on single exemplars of a car (Go) and a dog (NoGo) (basic). In the object animal task, responses were based on multiple exemplars of objects (Go) and animals (NoGo) (superordinate). The aMCI subjects had higher commission errors on the NoGo trials compared to the control subjects, whereas both groups had comparable omission errors and reaction times during the Go trials. The aMCI subjects had significantly prolonged N2 ERP latency during Go and NoGo trials across tasks compared to the controls. Both groups showed similar categorization effects and response type effects in N2/P3 ERP latencies and P3 amplitude. Our findings indicate that altered early neural processing indexed by N2 latency distinguishes subjects with aMCI from controls during the Go/NoGo task. Prolonged Go-N2 latency in aMCI appears to precede behavioral changes in response execution, whereas prolonged NoGo-N2 latency underlies behavioral deterioration in response inhibition.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain; Brain Mapping; Cognitive Dysfunction; Electroencephalography; Evoked Potentials; Female; Humans; Inhibition (Psychology); Male; Middle Aged; Neuropsychological Tests; Reaction Time

Effects of Hypertension and Anti-Hypertensive Treatment on Amyloid-β (Aβ) Plaque Load and Aβ-Synthesizing and Aβ-Degrading Enzymes in Frontal Cortex. - Ashby, Emma L; Miners, James S; Kehoe, Patrick G; Love, Seth (J Alzheimers Dis, 2016)
Epidemiological data associate hypertension with a predisposition to Alzheimer's disease (AD), and a number of postmortem and in vivo studies also demonstrate that hypertension increases amyloid-β (Aβ) pathology. In contrast, anti-hypertensive medications reportedly improve cognition and decrease the risk of AD, while certain classes of anti-hypertensive drugs are associated with decreased AD-related pathology. We investigated the effects of hypertension and anti-hypertensive treatment on Aβ plaque load in postmortem frontal cortex in AD. Aβ load was significantly increased in hypertensive (n = 20) relative to normotensive cases (n = 62) and was also significantly higher in treated (n = 9) than untreated hypertensives (n = 11). We then looked into mechanisms by which hypertension and treatment might increase Aβ load, focusing on Aβ-synthesizing enzymes, β- and γ-secretase, and Aβ-degrading enzymes, angiotensin-converting enzyme (ACE), insulin-degrading enzyme (IDE) and neprilysin. ACE and IDE protein levels were significantly lower in hypertensive (n = 21) than normotensive cases (n = 64), perhaps translating to decreased Aβ catabolism in hypertensives. ACE level was significantly higher in treated (n = 9) than untreated hypertensives (n = 12), possibly reflecting feedback upregulation of the renin-angiotensin system. Prospective studies in larger cohorts stratified according to anti-hypertensive drug class are needed to confirm these initial findings and to elucidate the interactions between hypertension, anti-hypertensive treatments, and Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Amyloid Precursor Protein Secretases; Antihypertensive Agents; Female; Frontal Lobe; Humans; Hypertension; Immunohistochemistry; Insulysin; Male; Neprilysin; Peptidyl-Dipeptidase A; Plaque, Amyloid; Retrospective Studies

Effects of Meditation versus Music Listening on Perceived Stress, Mood, Sleep, and Quality of Life in Adults with Early Memory Loss: A Pilot Randomized Controlled Trial. - Innes, Kim E; Selfe, Terry Kit; Khalsa, Dharma Singh; Kandati, Sahiti (J Alzheimers Dis, 2016)
BACKGROUND: Older adults with subjective cognitive decline (SCD) are at increased risk not only for Alzheimer's disease, but for poor mental health, impaired sleep, and diminished quality of life (QOL), which in turn, contribute to further cognitive decline, highlighting the need for early intervention. OBJECTIVE: In this randomized controlled trial, we assessed the effects of two 12-week relaxation programs, Kirtan Kriya Meditation (KK) and music listening (ML), on perceived stress, sleep, mood, and health-related QOL in older adults with SCD. METHODS: Sixty community-dwelling older adults with SCD were randomized to a KK or ML program and asked to practice 12 minutes daily for 12 weeks, then at their discretion for the following 3 months. At baseline, 12 weeks, and 26 weeks, perceived stress, mood, psychological well-being, sleep quality, and health-related QOL were measured using well-validated instruments. RESULTS: Fifty-three participants (88%) completed the 6-month study. Participants in both groups showed significant improvement at 12 weeks in psychological well-being and in multiple domains of mood and sleep quality (p's≤0.05). Relative to ML, those assigned to KK showed greater gains in perceived stress, mood, psychological well-being, and QOL-Mental Health (p's≤0.09). Observed gains were sustained or improved at 6 months, with both groups showing marked and significant improvement in all outcomes. Changes were unrelated to treatment expectancies. CONCLUSIONS: Findings suggest that practice of a simple meditation or ML program may improve stress, mood, well-being, sleep, and QOL in adults with SCD, with benefits sustained at 6 months and gains that were particularly pronounced in the KK group.

Efficacy and Safety of Crocus sativus L. in Patients with Mild Cognitive Impairment: One Year Single-Blind Randomized, with Parallel Groups, Clinical Trial. - Tsolaki, Magda; Karathanasi, Elina; Lazarou, Ioulietta; Dovas, Kostas; Verykouki, Eleni; Karacostas, Anastasios; Georgiadis, Kostas; Tsolaki, Anthoula; Adam, Katerina; Kompatsiaris, Ioannis; Sinakos, Zacharias (J Alzheimers Dis, 2016)
There is evidence to suggest the efficacy of Crocus (saffron) in the management of cognitive decline. This study examined the efficacy of Crocus in patients with amnesic and multi domain MCI (aMCImd). The participants included 17 patients on Crocus and 18 on a waiting list, who were examined with a short neuropsychological battery, MRI 3T, while some patients were examined via 256-channel electroencephalogram (HD-EEG) at baseline and after 12 months. The results showed that patients on Crocus had improved Mini-Mental State Examination scores (p = 0.015), while the control group deteriorated. Also, MRI, EEG, and ERP showed improvement in specific domains. This led us to conclude that Crocus is a good choice for management of aMCImd.

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Evaluation of Underlying Causes of Death in Patients with Dementia to Support Targeted Advance Care Planning. - van de Vorst, Irene E; Koek, Huiberdina L; Bots, Michiel L; Vaartjes, Ilonca (J Alzheimers Dis, 2016)
BACKGROUND: Insight in causes of death in demented patients may help physicians in end-of-life care. OBJECTIVES: To investigate underlying causes of death (UCD) in demented patients stratified by age, sex, dementia subtype [Alzheimer's disease (AD), vascular dementia (VaD)] and to compare them with UCD in the general population (GP). METHODS: A nationwide cohort of 59,201 patients with dementia (admitted to a hospital or visiting a day clinic) was constructed [38.7% men, 81.4 years (SD 7.0)] from 2000 through 2010. UCDs were reported and compared to the GP by calculating relative risks (RRs). RESULTS: During follow up [median follow up time 1.3 years (IQR 0.3- 3.0)], 64.2% of women and 69.3% of men died. Leading UCDs were dementia (17.5% in men and 23.7% in women) and cardiovascular disease (CVD) (18.7% and 19.2%, respectively). When compared to the GP, dementia was a more common UCD (RR in men 4.65, 95% CI 4.43-4.88), while CVD (RR in men 0.67, 95% CI 0.65-0.68) and cancer (RR 0.40, 95% CI 0.39-0.41) were less common. These differences were more pronounced in patients aged between 60-69 as compared to those aged≥90 years. Patients with AD died less often of cerebrovascular diseases as compared to VaD (RR in men 0.53, 95% CI 0.47-0.59). CONCLUSION: UCDs in patients with dementia differs from that of the GP, as dementia is more often and cancer less often an UCD. Although less frequent compared to the GP, CVD also is one of the leading UCDs in patients with dementia. This information is valuable for targeted advance care planning.

The Evolution of Caregiver Burden in Frontotemporal Dementia with and without Amyotrophic Lateral Sclerosis. - Hsieh, Sharpley; Leyton, Cristian E; Caga, Jashelle; Flanagan, Emma; Kaizik, Cassandra; O'Connor, Claire M; Kiernan, Matthew C; Hodges, John R; Piguet, Olivier; Mioshi, Eneida (J Alzheimers Dis, 2016)
BACKGROUND AND AIMS: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) represent a disease spectrum. Caregiver burden in subtypes of FTD has not yet been directly compared with those patients who have co-existent FTD and ALS (ALSFTD). METHOD: Perceived caregiver burden was evaluated using the short Zarit Burden Interview (ZBI) in patients with behavioral-variant FTD (bvFTD, n = 21), semantic dementia (SD, n = 18), and ALSFTD (n = 15) at the initial clinical presentation and follow-up assessments. The Mini-Addenbrooke's Cognitive Examination (M-ACE) and the Motor Neuron Disease Behaviour Scale (MiND-B) were also used. Linear mixed effects models examined longitudinal changes on the ZBI, M-ACE, and MiND-B across groups. RESULTS: Burden at baseline was highest for the bvFTD group. Longitudinally, perceived burden increased for the SD and ALSFTD groups whereas in bvFTD, the level of burden which was high at baseline and remained high with disease progression. The severity of abnormal behaviors at baseline, as assessed by the MiND-B, correlated with baseline levels of caregiver burden and further accounted for 23% of the variance in caregiver burden at clinical follow-up. CONCLUSIONS: The trajectory of perceived burden differs across the FTD-ALS spectrum, with SD and ALSFTD caregivers demonstrating an increased burden that develops over time, compared to a persistently high level for bvFTD caregivers, evident throughout the disease course. The evolution of burden in these three syndromes likely reflects the initial presentation and clinical characterization that develops with time. Psycho-education programs for caregivers, which provide better coping strategies for challenging behaviors, may reduce levels of burden experienced with disease progression.
Keywords: Adaptation, Psychological; Aged; Amyotrophic Lateral Sclerosis; Analysis of Variance; Caregivers; Case-Control Studies; Cost of Illness; Disease Progression; Female; Frontotemporal Dementia; Humans; Interviews as Topic; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Examining the Relationship Between Autobiographical Memory Impairment and Carer Burden in Dementia Syndromes. - Kumfor, Fiona; Teo, Drusilla; Miller, Laurie; Lah, Suncica; Mioshi, Eneida; Hodges, John R; Piguet, Olivier; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Autobiographical memory (ABM) refers to the capacity to remember one's own past, and is known to be central for supporting one's identity and sense of self. This capacity is commonly affected in Alzheimer's disease (AD), as well as semantic dementia (SD) and behavioral-variant frontotemporal dementia (bvFTD). Importantly, ABM plays a critical social function, facilitating relationship intimacy and empathy, and thus loss of ABM may also negatively affect families and carers. OBJECTIVE: To explore the relationship between ABM disruption and carer burden in AD, SD, and bvFTD, and establish whether characteristic ABM profiles differentially relate to carer burden across dementia syndromes. METHODS: We recruited 12 AD, 10 SD, and 13 bvFTD patients and their primary carer. All participants completed the Autobiographical Interview to assess memory for recent and remote events. Carers completed: the Zarit Burden Interview; Depression, Anxiety and Stress Scale (DASS-21); and the Intimate Bond Measure (IBM). RESULTS: In AD, loss of recent ABM was associated with worse psychological wellbeing of carers on the DASS-21. In contrast in SD, remote ABM dysfunction was associated with SD patients showing greater controlling behavior within their intimate relationships. In bvFTD, surprisingly, despite pervasive ABM impairment, no relationship between extent of ABM loss and carer burden was observed. CONCLUSION: These preliminary results reveal that ABM impairment impacts on patients' families and carers and suggest that these influences vary according to the pattern of ABM dysfunction. Disease-specific interventions focusing on preserved aspects of ABM may improve quality of life for both patients and carers.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; Analysis of Variance; Behavioral Symptoms; Caregivers; Female; Frontotemporal Dementia; Humans; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Statistics as Topic

Excess Costs Associated with Possible Misdiagnosis of Alzheimer's Disease Among Patients with Vascular Dementia in a UK CPRD Population. - Happich, Michael; Kirson, Noam Y; Desai, Urvi; King, Sarah; Birnbaum, Howard G; Reed, Catherine; Belger, Mark; Lenox-Smith, Alan; Price, David (J Alzheimers Dis, 2016)
BACKGROUND: Prior diagnosis of Alzheimer's disease (AD) among patients later diagnosed with vascular dementia (VaD) has been associated with excess costs, suggesting potential benefits of earlier rule-out of AD diagnosis. OBJECTIVE: To investigate whether prior diagnosis with AD among patients with VaD is associated with excess costs in the UK. METHODS: Patients with a final VaD diagnosis, continuous data visibility for≥6 months prior to index date, and linkage to Hospital Episode Statistics data were retrospectively selected from de-identified Clinical Practice Research Datalink data. Patients with AD diagnosis before a final VaD diagnosis were matched to similar patients with no prior AD diagnosis using propensity score methods. Annual excess healthcare costs were calculated for 5 years post-index, stratified by time to final diagnosis. RESULTS: Of 9,311 patients with VaD, 508 (6%) had prior AD diagnosis with a median time to VaD diagnosis exceeding 2 years from index date. Over the entire follow-up period, patients with prior AD diagnosis had accumulated healthcare costs that were approximately GBP2,000 higher than those for matched counterparts (mostly due to higher hospitalization costs). Cost differentials peaked particularly in the period including the final VaD diagnosis, with excess costs quickly declining thereafter. CONCLUSION: Potential misdiagnosis of AD among UK patients with VaD resulted in substantial excess costs. The decline in excess costs following a final VaD diagnosis suggests potential benefits from earlier rule-out of AD.

Extracellular Tau Paired Helical Filaments Differentially Affect Tau Pathogenic Mechanisms in Mitotic and Post-Mitotic Cells: Implications for Mechanisms of Tau Propagation in the Brain. - Varghese, Merina; Santa-Maria, Ismael; Ho, Lap; Ward, Libby; Yemul, Shrishailam; Dubner, Lauren; Księżak-Reding, Hanna; Pasinetti, Giulio Maria (J Alzheimers Dis, 2016)
The release of paired helical filaments (PHFs) from neurons into the extracellular space may contribute to the propagation of tau pathology across brain regions in Alzheimer's disease (AD) and other tauopathies. The majority of available mechanistic studies exploring the pathologic role of extracellular PHFs are conducted in proliferating cell lines. Here, we compare how extracellular PHFs induce tauopathy in mitotic cells and in post-mitotic brain neurons. In a mitotic cell line (HEK 293T), extracellular exposure to AD PHFs leads to an intracellular "aggresomal" type deposition of tau, coincidental with redistribution of dynein, a retrograde motor protein. We also observed that PHFs impaired proteasome degradation, but not autophagy. Exposure of cells to proteasome inhibitors was sufficient to induce intracellular tau aggregate formation as well as reorganization of dynein and the intermediate filament protein, vimentin. Thus, in mitotic cells, extracellular PHFs promote cellular tau aggregation, in part, by interfering with cellular proteasome degradation processes. In contrast with our observations with proliferating cells, exposure of post-mitotic primary neuronal cultures to AD PHFs did not promote "aggresomal" tau deposition, but instead resulted in a widespread accumulation of phosphorylated tau-immunoreactive swellings in neuritic processes, characterized by disturbed cytoskeletal organization of dynein and vimentin. Collectively, our observations suggest that extracellular PHFs may contribute to the propagation of tau pathology by independent mechanisms in post-mitotic and mitotic brain cells. These outcomes indicate that in addition to post-mitotic brain neurons, mitotic brain cells should also be considered as targets for therapeutic interventions to attenuate propagation of tauopathy.

Familial Presenilin Mutations and Sporadic Alzheimer's Disease Pathology: Is the Assumption of Biochemical Equivalence Justified? - Roher, Alex E; Maarouf, Chera L; Kokjohn, Tyler A (J Alzheimers Dis, 2016)
Studies of presenilin (PSEN) gene mutations producing early onset Alzheimer's disease (AD) have helped elucidate the pathogenic mechanisms of dementia and guided clinical trials of potential therapeutic interventions. Although familial and sporadic forms of AD share features, it is unclear if the two are precisely equivalent. In addition, PSEN mutations do not all produce a single phenotype, but exhibit substantial variability in clinical manifestations, which are related to the position and chemical nature of their amino acid substitutions as well as ratios of critical molecules such as Aβ40 and Aβ42. These differences complicate the interpretation of critical clinical trial results and their desired extrapolation to sporadic AD treatment. In this perspective, we examine differences between familial AD and sporadic AD as well as attributes shared by these uniquely arising disturbances in brain biochemical homeostasis that culminate in dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Brain; Humans; Mutation; Presenilins

FDG-PET and Neuropsychiatric Symptoms among Cognitively Normal Elderly Persons: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Ruider, Hanna; Lowe, Val J; Stokin, Gorazd B; Pink, Anna; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Christianson, Teresa J; Machulda, Mary M; Jack, Clifford R; Petersen, Ronald C; et al. (J Alzheimers Dis, 2016)
One of the key research agenda of the field of aging is investigation of presymptomatic Alzheimer's disease (AD). Furthermore, abnormalities in brain glucose metabolism (as measured by FDG-PET) have been reported among cognitively normal elderly persons. However, little is known about the association of FDG-PET abnormalities with neuropsychiatric symptoms (NPS) in a population-based setting. Thus, we conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging in order to examine the association between brain glucose metabolism and NPS among cognitively normal (CN) persons aged > 70 years. Participants underwent FDG-PET and completed the Neuropsychiatric Inventory Questionnaire (NPI-Q), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI). Cognitive classification was made by an expert consensus panel. We conducted multivariable logistic regression analyses to compute odds ratios (OR) and 95% confidence intervals after adjusting for age, sex, and education. For continuous variables, we used linear regression and Spearman rank-order correlations. Of 668 CN participants (median 78.1 years, 55.4% males), 205 had an abnormal FDG-PET (i.e., standardized uptake value ratio < 1.32 in AD-related regions). Abnormal FDG-PET was associated with depression as measured by NPI-Q (OR = 2.12; 1.23-3.64); the point estimate was further elevated for APOE ɛ4 carriers (OR = 2.59; 1.00-6.69), though marginally significant. Additionally, we observed a significant association between abnormal FDG-PET and depressive and anxiety symptoms when treated as continuous measures. These findings indicate that NPS, even in community-based samples, can be an important additional tool to the biomarker-based investigation of presymptomatic AD.

Fine Particulate Matter, Residential Proximity to Major Roads, and Markers of Small Vessel Disease in a Memory Study Population. - Wilker, Elissa H; Martinez-Ramirez, Sergi; Kloog, Itai; Schwartz, Joel; Mostofsky, Elizabeth; Koutrakis, Petros; Mittleman, Murray A; Viswanathan, Anand (J Alzheimers Dis, 2016)
BACKGROUND: Long-term exposure to ambient air pollution has been associated with impaired cognitive function and vascular disease in older adults, but little is known about these associations among people with concerns about memory loss. OBJECTIVE: To examine associations between exposures to fine particulate matter and residential proximity to major roads and markers of small vessel disease. METHODS: From 2004-2010, 236 participants in the Massachusetts Alzheimer's Disease Research Center Longitudinal Cohort participated in neuroimaging studies. Residential proximity to major roads and estimated 2003 residential annual average of fine particulate air pollution (PM2.5) were linked to measures of brain parenchymal fraction (BPF), white matter hyperintensities (WMH), and cerebral microbleeds. Associations were modeled using linear and logistic regression and adjusted for clinical and lifestyle factors. RESULTS: In this population (median age [interquartile range] = 74 [12], 57% female) living in a region with median 2003 PM2.5 annual average below the current Environmental Protection Agency (EPA) standard, there were no associations between living closer to a major roadway or for a 2μg/m3 increment in PM2.5 and smaller BPF, greater WMH volume, or a higher odds of microbleeds. However, a 2μg/m3 increment in PM2.5 was associated with -0.19 (95% Confidence Interval (CI): -0.37, -0.005) lower natural log-transformed WMH volume. Other associations had wide confidence intervals. CONCLUSIONS: In this population, where median 2003 estimated PM2.5 levels were below the current EPA standard, we observed no pattern of association between residential proximity to major roads or 2003 average PM2.5 and greater burden of small vessel disease or neurodegeneration.

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

Functional Connectivity of Ventral and Dorsal Visual Streams in Posterior Cortical Atrophy. - Migliaccio, Raffaella; Gallea, Cécile; Kas, Aurélie; Perlbarg, Vincent; Samri, Dalila; Trotta, Laura; Michon, Agnès; Lacomblez, Lucette; Dubois, Bruno; Lehéricy, Stéphane; Bartolomeo, Paolo (J Alzheimers Dis, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) induces progressive dysfunction of ventral and dorsal visual networks. Little is known, however, about corresponding changes in functional connectivity (FC). OBJECTIVES: To investigate FC changes in the visual networks, their relationship with cortical atrophy, and the association with Alzheimer's disease (AD) pathology. METHODS: Ten PCA patients and 28 age-matched controls participated in the study. Using resting state fMRI, we measured FC in ventral and dorsal cortical visual networks, defined on the basis of a priori knowledge of long-range white matter connections. To assess the relationships with AD, we determined AD biomarkers in cerebrospinal fluid and FC in the default mode network (DMN), which is vulnerable to AD pathology. Voxel-based morphometry analysis assessed the pattern of grey matter (GM) atrophy. RESULTS: PCA patients showed GM atrophy in bilateral occipital and inferior parietal regions. PCA patients had lower FC levels in a ventral network than controls, but higher FC in inferior components of the dorsal network. In particular, the increased connectivity correlated with greater GM atrophy in occipital regions. All PCA patients had positive cerebrospinal fluid biomarkers for AD; however, FC in global DMN did not differ from controls. CONCLUSIONS: FC in PCA reflects brain structure in a non-univocal way. Hyperconnectivity of dorsal networks may indicate aberrant communication in response to posterior brain atrophy or processes of neural resilience during the initial stage of brain dysfunction. The lack of difference from controls in global DMN FC highlights the atypical nature of PCA with respect to typical AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Case-Control Studies; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Oxygen; Visual Pathways

Gene Expression of Quaking in Sporadic Alzheimer's Disease Patients is Both Upregulated and Related to Expression Levels of Genes Involved in Amyloid Plaque and Neurofibrillary Tangle Formation. - Farnsworth, Bryn; Peuckert, Christiane; Zimmermann, Bettina; Jazin, Elena; Kettunen, Petronella; Emilsson, Lina Sors (J Alzheimers Dis, 2016)
Quaking (QKI) is a gene exclusively expressed within glial cells. QKI has previously been implicated in various neurological disorders and diseases, including Alzheimer's disease (AD), a condition for which increasing evidence suggests a central role of glia cells. The objective of the present study was to investigate the expression levels of QKI and three QKI isoforms (QKI5, QKI6, and QKI7) in AD. Genes that have previously been related to the ontogeny and progression of AD, specifically APP, PSEN1, PSEN2, and MAPT, were also investigated. A real-time PCR assay of 123 samples from human postmortem sporadic AD patients and control brains was performed. The expression values were analyzed with an analysis of covariance model and subsequent multiple regressions to explore the possibility of related expression values between QKI, QKI isoforms, and AD-related genes. Further, the sequences of AD-related genes were analyzed for the presence of QKI binding domains. QKI and all measured QKI isoforms were found to be significantly upregulated in AD samples, relative to control samples. However, APP, PSEN1, PSEN2, and MAPT were not found to be significantly different. QKI and QKI isoforms were found to be predictive for the variance of APP, PSEN1, PSEN2, and MAPT, and putative QKI binding sites suggests an interaction with QKI. Overall, these results implicate a possible role of QKI in AD, although the exact mechanism by which this occurs remains to be uncovered.

Gene Expression Profiling in the APP/PS1KI Mouse Model of Familial Alzheimer's Disease. - Weissmann, Robert; Hüttenrauch, Melanie; Kacprowski, Tim; Bouter, Yvonne; Pradier, Laurent; Bayer, Thomas A; Kuss, Andreas W; Wirths, Oliver (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by early intraneuronal amyloid-β (Aβ) accumulation, extracellular deposition of Aβ peptides, and intracellular hyperphosphorylated tau aggregates. These lesions cause dendritic and synaptic alterations and induce an inflammatory response in the diseased brain. Although the neuropathological characteristics of AD have been known for decades, the molecular mechanisms causing the disease are still under investigation. Studying gene expression changes in postmortem AD brain tissue can yield new insights into the molecular disease mechanisms. To that end, one can employ transgenic AD mouse models and the next-generation sequencing technology. In this study, a whole-brain transcriptome analysis was carried out using the well-characterized APP/PS1KI mouse model for AD. These mice display a robust phenotype reflected by working memory deficits at 6 months of age, a significant neuron loss in a variety of brain areas including the CA1 region of the hippocampus and a severe amyloid pathology. Based on deep sequencing, differentially expressed genes (DEGs) between 6-month-old WT or PS1KI and APP/PS1KI were identified and verified by qRT-PCR. Compared to WT mice, 250 DEGs were found in APP/PS1KI mice, while 186 DEGs could be found compared to PS1KI control mice. Most of the DEGs were upregulated in APP/PS1KI mice and belong to either inflammation-associated pathways or lysosomal activation, which is likely due to the robust intraneuronal accumulation of Aβ in this mouse model. Our comprehensive brain transcriptome study further highlights APP/PS1KI mice as a valuable model for AD, covering molecular inflammatory and immune responses.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Disease Models, Animal; Gene Expression Profiling; Male; Mice; Mice, Transgenic; Nerve Degeneration; Presenilin-1; Transcriptome

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

A Genetic Variant of the Sortilin 1 Gene is Associated with Reduced Risk of Alzheimer's Disease. - Andersson, Carl-Henrik; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Wallin, Anders; Nilsson, Staffan; Kettunen, Petronella (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder represented by the accumulation of intracellular tau protein and extracellular deposits of amyloid-β (Aβ) in the brain. The gene sortilin 1 (SORT1) has previously been associated with cardiovascular disease in gene association studies. It has also been proposed to be involved in AD pathogenesis through facilitating Aβ clearance by binding apoE/Aβ complexes prior to cellular uptake. However, the neuropathological role of SORT1 in AD is not fully understood. To evaluate the associations between gene variants of SORT1 and risk of AD, we performed genetic analyses in a Swedish case-control cohort. Ten single nucleotide polymorphisms (SNPs), covering the whole SORT1 gene, were selected and genotyped in 620 AD patients and 1107 controls. The SNP rs17646665, located in a non-coding region of the SORT1 gene, remained significantly associated with decreased risk of AD after multiple testing (pc = 0.0061). In addition, other SNPs were found to be nominally associated with risk of AD, as well as altered cognitive function and the CSF biomarker Aβ42, but these associations did not survive correction for multiple testing. The fact that SORT1 has been strongly associated with risk of cardiovascular disease is intriguing as cardiovascular disease is also regarded as a risk factor for AD. Finally, increased knowledge about SORT1 function has a potential to increase our understanding of APOE, the strongest risk factor for AD.

Glutamine and Glutamate Complex, as Measured by Functional Magnetic Resonance Spectroscopy, Alters During Face-Name Association Task in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Jahng, Geon-Ho; Oh, Janghoon; Lee, Do-Wan; Kim, Hyug-Gi; Rhee, Hak Young; Shin, Wonchul; Paik, Jong-Woo; Lee, Kyung Mi; Park, Soonchan; Choe, Bo-Young; Ryu, Chang-Woo (J Alzheimers Dis, 2016)
BACKGROUND: The metabolite response during a memory task in Alzheimer's disease (AD) patients is unknown. OBJECTIVE: To investigate the metabolite changes in subjects with AD, amnestic mild cognitive impairment (aMCI), and cognitively normal (CN) elderly during a memory task using functional magnetic resonance spectroscopy (fMRS). METHODS: This study involved 23 young normal controls (YC), 24 CN elderly, 24 aMCI, and 24 mild and probable AD individuals. fMRS data were acquired at the precuneus and posterior cingulate brain regions during a face-name association task. Statistical analyses of quantified metabolites were performed to evaluate differences of the metabolite values between the stimulation conditions and among the four subject groups. Receiver operating curve analysis was performed to evaluate whether the metabolic changes after functional activations can differentiate the subject groups. RESULT: Glutamine and glutamate complex (Glx) was statistically significantly different between the fixation and repeat conditions in aMCI (p = 0.0492) as well as between the fixation and the novel conditions in the AD (p = 0.0412) group. The total N-acetylaspartate (tNAA) was statistically significantly different among the four subject groups in the fixation condition (DF = 3, F = 7.673, p <  0.001), the novel condition (DF = 3, F = 6.945, p <  0.001), and the repeat condition (DF = 3, F = 7.127, p <  0.001). tNAA, tCr, and mIns could be used to differentiate CN from aMCI. Furthermore, tNAA, tCr, Glx, and Glu could also differentiate CN from AD, and aMCI from AD. CONCLUSION: Glx was altered during a stimulation that may be used to evaluate neuronal dysfunction in a demented patient. tNAA and tCr were reduced in patients with AD.

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

Halting of Caspase Activity Protects Tau from MC1-Conformational Change and Aggregation. - Mead, Emma; Kestoras, Dimitra; Gibson, Yolanda; Hamilton, Lucy; Goodson, Ross; Jones, Sophie; Eversden, Sarah; Davies, Peter; O'Neill, Michael; Hutton, Michael; Szekeres, Philip; Wolak, Joanna (J Alzheimers Dis, 2016)
Intracellular neurofibrillary tangles (NFTs) are the hallmark of Alzheimer's disease and other tauopathies in which tau, a microtubule-associated protein, loses its ability to stabilize microtubules. Several post-translational modifications including phosphorylation and truncation increase tau's propensity to aggregate thus forming NFTs; however, the mechanisms underlying tau conformational change and aggregation still remain to be defined. Caspase activation and subsequent proteolytic cleavage of tau is thought to be a potential trigger of this disease-related pathological conformation. The aim of this work was to investigate the link between caspase activation and a disease-related conformational change of tau in a neuroblastoma cell-based model of spontaneous tau aggregation. We demonstrated that caspase induction initiates proteolytic cleavage of tau and generation of conformationally altered and aggregated tau recognized by the MC1 conformational antibody. Most importantly, these events were shown to be attenuated with caspase inhibitors. This implies that therapeutics aimed at inhibiting caspase-mediated tau cleavage may prove beneficial in slowing cleavage and aggregation, thus potentially halting tau pathology and disease progression.

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

Hierarchical Distribution of the Tau Cytoskeletal Pathology in the Thalamus of Alzheimer's Disease Patients. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Del Turco, Domenico; Ghebremedhin, Estifanos; Seidel, Kay; den Dunnen, Wilfred; Korf, Horst-Werner (J Alzheimers Dis, 2016)
In spite of considerable progress in neuropathological research on Alzheimer's disease (AD), knowledge regarding the exact pathoanatomical distribution of the tau cytoskeletal pathology in the thalamus of AD patients in the advanced Braak and Braak AD stages V or VI of the cortical cytoskeletal pathology is still fragmentary. Investigation of serial 100 μm-thick brain tissue sections through the thalamus of clinically diagnosed AD patients with Braak and Braak AD stage V or VI cytoskeletal pathologies immunostained with the anti-tau AT8 antibody, along with the affection of the extraterritorial reticular nucleus of the thalamus, reveals a consistent and severe tau immunoreactive cytoskeletal pathology in the limbic nuclei of the thalamus (e.g., paraventricular, anterodorsal and laterodorsal nuclei, limitans-suprageniculate complex). The thalamic nuclei integrated into the associative networks of the human brain (e.g., ventral anterior and mediodorsal nuclei) are only mildly affected, while its motor precerebellar (ventral lateral nucleus) and sensory nuclei (e.g., lateral and medial geniculate bodies, ventral posterior medial and lateral nuclei, parvocellular part of the ventral posterior medial nucleus) are more or less spared. The highly stereotypical and characteristic thalamic distribution pattern of the AD-related tau cytoskeletal pathology represents an anatomical mirror of the hierarchical topographic distribution of the cytoskeletal pathology in the interconnected regions of the cerebral cortex of AD patients. These pathoanatomical parallels support the pathophysiological concept of a transneuronal spread of the disease process of AD along anatomical pathways. The AD-related tau cytoskeletal pathology in the thalamus most likely contributes substantially to the neuropsychiatric disease symptoms (e.g., dementia), attention deficits, oculomotor dysfunctions, altered non-discriminative aspects of pain experience of AD patients, and the disruption of their waking and sleeping patterns.
Keywords: Alzheimer Disease; Cytoskeleton; Humans; tau Proteins; Thalamus

High Risk of Dementia in Ventricular Enlargement with Normal Pressure Hydrocephalus Related Symptoms1. - Koivisto, Anne M; Kurki, Mitja I; Alafuzoff, Irina; Sutela, Anna; Rummukainen, Jaana; Savolainen, Sakari; Vanninen, Ritva; Jääskeläinen, Juha E; Soininen, Hilkka; Leinonen, Ville (J Alzheimers Dis, 2016)
BACKGROUND: Differential diagnosis of ventricular enlargement with normal pressure hydrocephalus (NPH) related symptoms is challenging. Patients with enlarged ventricles often manifest cognitive deterioration but their long-term outcome is not well known. OBJECTIVES: We aim to evaluate long-term cognitive outcome in patients with enlarged ventricles and clinically suspected NPH. METHODS: A neurologist and a neurosurgeon clinically evaluated 468 patients with enlarged ventricles and suspected NPH using radiological methods, intraventricular pressure monitoring, and frontal cortical brain biopsy. The neurologist confirmed final diagnoses after a median follow-up interval of 4.8 years. RESULTS: Altogether, 232 patients (50%) with enlarged ventricles did not fulfill the criteria for shunt surgery. The incidence of dementia among patients with enlarged ventricles, and at least one NPH-related symptom with adequate follow-up data (n = 446) was high, varying from 77 (iNPH, shunt responders) to 141/1000 person-years (non-shunted patients with enlarged ventricles). At the end of the follow-up, 59% of all these patients were demented. The demented population comprised 73% of non-shunted patients with enlarged ventricles, 63% of shunted iNPH patients that did not respond to treatment, and 46% of iNPH patients that were initially responsive to shunting. The most common cause of dementia was Alzheimer's disease (n = 94, 36%), followed by vascular dementia (n = 68, 26%). CONCLUSIONS: One-half of patients with enlarged ventricles and clinically suspected NPH were not shunted after intraventricular pressure monitoring. Dementia caused by various neurodegenerative diseases was frequently seen in patients with ventricular enlargement. Thus, careful diagnostic evaluation in collaboration with neurologists and neurosurgeons is emphasized.

High-Sodium Diet Has Opposing Effects on Mean Arterial Blood Pressure and Cerebral Perfusion in a Transgenic Mouse Model of Alzheimer's Disease. - Taheri, Saeid; Yu, Jin; Zhu, Hong; Kindy, Mark S (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral ionic homeostasis impairment, especially Ca2+, has been observed in Alzheimer's disease (AD) and also with hypertension. Hypertension and AD both have been implicated in impaired cerebral autoregulation. However, the relationship between the ionic homeostasis impairment in AD and hypertension and cerebral blood flow (CBF) autoregulation is not clear. OBJECTIVE: To test the hypothesis that a high-salt diet regimen influences the accumulation of amyloid-β (Aβand CBF) and CBF, exacerbates cognitive decline, and increases the propensity to AD. METHODS: Double transgenic mice harboring the amyloid-β protein precursor (APPswe), and presenilin-1 (PSEN1) along with control littermates, 2 months of age at initiation of special diet, were divided into 4 groups: Group A, APP/PS1 and Group B, controls fed a high-sodium (4.00%) chow diet for 3 months; Group C, APP/PS1 and Group D, controls fed a low-sodium (0.08%) regular chow diet for 3 months. Mean arterial blood pressure (MAP) and CBF were measured noninvasively using the tail MAP measurement device and magnetic resonance imaging, respectively. Aβ plaques numbers in the cortex and hippocampus of APP/PS1 were quantified. RESULTS: In contrary to controls, APP/PS1 mice fed a high-salt diet did not show markedly elevated mean systolic and diastolic blood pressure (134±4.8 compared with 162±2.8 mmHg, and 114±5.0 compared with 137±20 mmHg, p< 0.0001). However, a high-salt diet increased CBF in both APP/PS1 and controls and did not alter the cerebral tissue integrity. Aβ plaques were significantly reduced in the cortex and hippocampus of mice fed a high-salt diet. CONCLUSION: These data suggest that a high-salt diet differently affects MAP and CBF in APP/PS1 mice and controls.

High-Throughput Screening for Identification of Blood-Brain Barrier Integrity Enhancers: A Drug Repurposing Opportunity to Rectify Vascular Amyloid Toxicity. - Qosa, Hisham; Mohamed, Loqman A; Al Rihani, Sweilem B; Batarseh, Yazan S; Duong, Quoc-Viet; Keller, Jeffrey N; Kaddoumi, Amal (J Alzheimers Dis, 2016)
The blood-brain barrier (BBB) is a dynamic interface that maintains brain homeostasis and protects it from free entry of chemicals, toxins, and drugs. The barrier function of the BBB is maintained mainly by capillary endothelial cells that physically separate brain from blood. Several neurological diseases, such as Alzheimer's disease (AD), are known to disrupt BBB integrity. In this study, a high-throughput screening (HTS) was developed to identify drugs that rectify/protect BBB integrity from vascular amyloid toxicity associated with AD progression. Assessing Lucifer Yellow permeation across in-vitro BBB model composed from mouse brain endothelial cells (bEnd3) grown on 96-well plate inserts was used to screen 1280 compounds of Sigma LOPAC®1280 library for modulators of bEnd3 monolayer integrity. HTS identified 62 compounds as disruptors, and 50 compounds as enhancers of the endothelial barrier integrity. From these 50 enhancers, 7 FDA approved drugs were identified with EC50 values ranging from 0.76-4.56 μM. Of these 7 drugs, 5 were able to protect bEnd3-based BBB model integrity against amyloid toxicity. Furthermore, to test the translational potential to humans, the 7 drugs were tested for their ability to rectify the disruptive effect of Aβ in the human endothelial cell line hCMEC/D3. Only 3 (etodolac, granisetron, and beclomethasone) out of the 5 effective drugs in the bEnd3-based BBB model demonstrated a promising effect to protect the hCMEC/D3-based BBB model integrity. These drugs are compelling candidates for repurposing as therapeutic agents that could rectify dysfunctional BBB associated with AD.

The Identification of Aluminum in Human Brain Tissue Using Lumogallion and Fluorescence Microscopy. - Mirza, Ambreen; King, Andrew; Troakes, Claire; Exley, Christopher (J Alzheimers Dis, 2016)
Aluminum in human brain tissue is implicated in the etiologies of neurodegenerative diseases including Alzheimer's disease. While methods for the accurate and precise measurement of aluminum in human brain tissue are widely acknowledged, the same cannot be said for the visualization of aluminum. Herein we have used transversely-heated graphite furnace atomic absorption spectrometry to measure aluminum in the brain of a donor with Alzheimer's disease, and we have developed and validated fluorescence microscopy and the fluor lumogallion to show the presence of aluminum in the same tissue. Aluminum is observed as characteristic orange fluorescence that is neither reproduced by other metals nor explained by autofluorescence. This new and relatively simple method to visualize aluminum in human brain tissue should enable more rigorous testing of the aluminum hypothesis of Alzheimer's disease (and other neurological conditions) in the future.

Immunization Against Specific Fragments of Neurotrophin p75 Receptor Protects Forebrain Cholinergic Neurons in the Olfactory Bulbectomized Mice. - Bobkova, Natalia; Vorobyov, Vasily; Medvinskaya, Natalia; Nesterova, Inna; Tatarnikova, Olga; Nekrasov, Pavel; Samokhin, Alexander; Deev, Alexander; Sengpiel, Frank; Koroev, Dmitry; Volpina, Olga (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by progressive cognitive impairment associated with marked cholinergic neuron loss and amyloid-β (Aβ) peptide accumulation in the brain. The cytotoxicity in AD is mediated, at least in part, by Aβ binding with the extracellular domain of the p75 neurotrophin receptor (p75NTR), localized predominantly in the membranes of acetylcholine-producing neurons in the basal forebrain. Hypothesizing that an open unstructured loop of p75NTR might be the effective site for Aβ binding, we have immunized both olfactory bulbectomized (OBX) and sham-operated (SO) mice (n = 82 and 49, respectively) with synthetic peptides, structurally similar to different parts of the loops, aiming to block them by specific antibodies. OBX-mice have been shown in previous studies, and confirmed in the present one, to be characterized by typical behavioral, morphological, and biochemical AD hallmarks, including cholinergic deficits in forebrain neurons. Immunization of OBX- or SO-mice with KLH conjugated fragments of p75NTR induced high titers of specific serum antibodies for each of nine chosen fragments. However, maximal protective effects on spatial memory, evaluated in a Morris water maze, and on activity of choline acetyltransferase in forebrain neurons, detected by immunoreactivity to specific antibodies, were revealed only for peptides with amino acid residue sequences of 155-164 and 167-176. We conclude that the approach based on immunological blockade of specific p75NTR sites, linked with the cytotoxicity, is a useful and effective tool for study of AD-associated mechanisms and for development of highly selective therapy of cholinergic malfunctioning in AD patients.

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impacts of Illiteracy on the Risk of Dementia: A Global Health Perspective. - Suh, Seung Wan; Han, Ji Won; Park, Jae Young; Hong, Jong Woo; Kim, Kayoung; Kim, Taehyun; Lee, Kyoung Hwan; Han, Guehee; Jeong, Hyeon; Seo, Jiyeong; Kim, Tae Hui; Lee, Dong Young; et al. (J Alzheimers Dis, 2016)
Despite its significance as a contributing factor for late-life dementia risk, illiteracy is frequently underappreciated in the management of dementia. In this study, we estimated the proportion of dementia cases attributable to illiteracy using the population attributable fraction (PAF), and calculated to what extent the monetary cost of dementia could be saved in the future by reducing illiteracy from the South Korean, Latin American, South Asian/Middle Eastern, and African populations. We collected necessary data from the 2011 United Nations Human Development Report and prevalence studies conducted in these regions. Additional variables not included in the above sources were estimated using a logit model under a "trend scenario"-based assumption. Around 16% of the total number of dementia cases in South Korea in 2015 can be attributed to illiteracy, with this figure predicted to decline to around 2% by 2050. This translates to a saving in dementia care costs of approximately 52 billion USD, providing we are successful in theoretically eradicating illiteracy as of 2015, in the population aged 65 years or under. Likewise, reducing illiteracy to 50% in Latin America, South Asia/The Middle East, and Africa by 2050 could generate further cost savings of between 71 and 244 billion, 13 and 94 billion, and 17 and 78 billion USD, respectively. Even public policies aimed solely at reducing illiteracy in the childhood, adolescent, or middle-aged population could potentially have a role in the primary prevention of dementia. Moving forward, governments will need to address this issue in a purposeful and systematic manner.

The Incidence of Benzodiazepine and Related Drug Use in Persons with and without Alzheimer's Disease. - Saarelainen, Laura; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tolppanen, Anna-Maija; Tiihonen, Jari; Hartikainen, Sirpa (J Alzheimers Dis, 2016)
BACKGROUND: Benzodiazepines and related drugs (BZDR) are occasionally used to treat certain symptoms of Alzheimer's disease (AD). However, the risks related to BZDR use are high in older persons. Although frequent BZDR use has been reported in persons with AD, no previous study has focused specifically on the incidence of BZDR use in this population. OBJECTIVE: We investigated the incidence of BZDR use in persons with and without AD during a five-year follow-up. METHODS: The Finnish nationwide, register-based MEDALZ cohort includes all AD cases who received a clinically verified AD diagnosis in 2005-2011 (n = 70,718) and their matched comparison persons. Incidence of BZDR, including benzodiazepines (lorazepam, oxazepam, temazepam, alprazolam, chlordiazepoxide, diazepam, and nitrazepam) and Z-drugs (zolpidem and zopiclone), use was investigated in the cohort from two years before to three years after the diagnosis of AD. Further, initial BZDRs were investigated. RESULTS: The incidence of BZDR use was higher in persons with AD starting from 12 months before the diagnosis and peaked at six months after the diagnosis of AD (incidence rate ratio [IRR] = 2.6, 95% confidence interval [CI] = 2.5-2.8). Benzodiazepines were more frequently initiated by persons with AD, with the incidence peaking at six months after the diagnosis (IRR = 4.5, 95% CI = 4.1-4.9) and remaining over three times higher than in comparison persons until three years after the diagnosis. CONCLUSION: Early symptomatic treatment with BZDRs is contrary to AD treatment guidelines. As BZDRs impair cognition, the observed early treatment with BZDRs may complicate the monitoring of AD treatment effectiveness.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Benzodiazepines; Cohort Studies; Female; Finland; Humans; Incidence; Male; Middle Aged; Substance-Related Disorders

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Levels of Extracellular Microvesicle Markers and Decreased Levels of Endocytic/Exocytic Proteins in the Alzheimer's Disease Brain. - Musunuri, Sravani; Khoonsari, Payam Emami; Mikus, Maria; Wetterhall, Magnus; Häggmark-Mänberg, Anna; Lannfelt, Lars; Erlandsson, Anna; Bergquist, Jonas; Ingelsson, Martin; Shevchenko, Ganna; Nilsson, Peter; Kultima, Kim (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder accounting for more than 50% of all dementia cases. AD neuropathology is characterized by the formation of extracellular plaques and intracellular neurofibrillary tangles consisting of aggregated amyloid-β and tau, respectively. The disease mechanism has only been partially elucidated and is believed to also involve many other proteins. OBJECTIVE: This study intended to perform a proteomic profiling of post mortem AD brains and compare it with control brains as well as brains from other neurological diseases to gain insight into the disease pathology. METHODS: Here we used label-free shotgun mass spectrometry to analyze temporal neocortex samples from AD, other neurological disorders, and non-demented controls, in order to identify additional proteins that are altered in AD. The mass spectrometry results were verified by antibody suspension bead arrays. RESULTS: We found 50 proteins with altered levels between AD and control brains. The majority of these proteins were found at lower levels in AD. Pathway analyses revealed that several of the decreased proteins play a role in exocytic and endocytic pathways, whereas several of the increased proteins are related to extracellular vesicles. Using antibody-based analysis, we verified the mass spectrometry results for five representative proteins from this group of proteins (CD9, HSP72, PI42A, TALDO, and VAMP2) and GFAP, a marker for neuroinflammation. CONCLUSIONS: Several proteins involved in exo-endocytic pathways and extracellular vesicle functions display altered levels in the AD brain. We hypothesize that such changes may result in disturbed cellular clearance and a perturbed cell-to-cell communication that may contribute to neuronal dysfunction and cell death in AD.

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Inhibition of Cholesterol Biosynthesis Reduces γ-Secretase Activity and Amyloid-β Generation. - Kim, Yoonhee; Kim, Chaeyoung; Jang, Hye Young; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) is one of major molecules contributing to the pathogenesis of Alzheimer's disease (AD). Aβ is derived from amyloid-β protein precursor (AβPP) through sequential cleavages by β- and γ-secretases. Regulation of these components is thought to be an important factor in Aβ generation during the pathogenesis of AD. AβPP, β-secretase, and γ-secretase reside in lipid rafts, where cholesterol regulates the integrity and flexibility of membrane proteins and Aβ is generated. However, the relationship between cholesterol and Aβ generation is controversial. In this study, we aimed to elucidate the direct effects of cholesterol depletion on AβPP processing using AY9944, which blocks the last step of cholesterol biosynthesis and thus minimizes the unknown side effects of upstream inhibitors, such as HMG-CoA reductase inhibitors. Treatment with AY9944 decreased γ-secretase activity and Aβ generation. These results suggested that changes in membrane composition by lowering cholesterol with AY9944 affected γ-secretase activity and Aβ generation, which is associated with AD pathogenesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Animals; Anticholesteremic Agents; Cell Line; Cholesterol; Cricetinae; Down-Regulation; Humans; In Situ Nick-End Labeling; Luminescent Proteins; Membrane Glycoproteins; Membrane Microdomains; Mutation; Presenilin-1; Protein Transport; trans-1,4-Bis(2-chlorobenzaminomethyl)cyclohexane Dihydrochloride; Transfection

Inhibition of Histone Deacetylase 3 Restores Amyloid-β Oligomer-Induced Plasticity Deficit in Hippocampal CA1 Pyramidal Neurons. - Krishna, Kumar; Behnisch, Thomas; Sajikumar, Sreedharan (J Alzheimers Dis, 2016)
Neurodegenerative diseases such as Alzheimer's disease (AD) are associated with alterations in epigenetic factors leading to cognitive decline. Histone deacetylase 3 (HDAC3) is a known critical epigenetic negative regulator of learning and memory. In this study, attenuation of long-term potentiation by amyloid-β oligomer, and its reversal by specific HDAC3 inhibitor RGFP966, was performed in rat CA1 pyramidal neurons using whole cell voltage-clamp and field recording techniques. Our findings provide the first evidence that amyloid-β oligomer-induced synaptic plasticity impairment can be prevented by inhibition of HDAC3 enzyme both at the single neuron as well as in a population of neurons, thus identifying HDAC3 as a potential target for ameliorating AD related plasticity impairments.
Keywords: Acrylamides; Alzheimer Disease; Amyloid beta-Peptides; Animals; Excitatory Postsynaptic Potentials; Hippocampus; Histone Deacetylase Inhibitors; Histone Deacetylases; Long-Term Potentiation; Male; Patch-Clamp Techniques; Peptide Fragments; Phenylenediamines; Pyramidal Cells; Rats, Wistar; Tissue Culture Techniques

Insight into the Dissociation of Behavior from Histology in Synucleinopathies and in Related Neurodegenerative Diseases. - Sekiyama, Kazunari; Takamatsu, Yoshiki; Koike, Wakako; Waragai, Masaaki; Takenouchi, Takato; Sugama, Shuei; Hashimoto, Makoto (J Alzheimers Dis, 2016)
Recent clinical trials using immunization approaches against Alzheimer's disease (AD) have failed to demonstrate improved cognitive functions in patients, despite potent suppression in the formation of both senile plaques and other amyloid-β deposits in postmortem brains. Similarly, we observed that treatment with ibuprofen, a non-steroidal anti-inflammatory drug, was effective in improving the histopathology, such as reducing both protein aggregation and glial activation, in the brains of transgenic mice expressing dementia with Lewy bodies-linked P123H β-synuclein. In contrast, only a small improvement in cognitive functions was observed in these mice. Collectively, it is predicted that histology does not correlate with behavior that is resilient and resistant to therapeutic stimuli. Notably, such a 'discrepancy between histology and behavior' is reminiscent of AD-like pathologies and incidental Lewy bodies, which are frequently encountered in postmortem brains of the elderly who had been asymptomatic for memory loss and Parkinsonism during their lives. We suggest that 'the discrepancy between histology and behavior' may be a universal feature that is associated with various aspects of neurodegenerative diseases. Furthermore, given that the cognitive reserve is specifically observed in human brains, human behavior may be evolutionally distinct from that in other animals, thus, contributing to the differential efficiency of therapy between human and lower animals, an important issue in the therapy of neurodegenerative diseases. Overall, it is important to better understand 'the discrepancy between histology and behavior' in the mechanism of neurodegeneration for the development of effective therapies against neurodegenerative diseases.

Insulin Resistance is Associated with Increased Levels of Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Reduced Memory Function in At-Risk Healthy Middle-Aged Adults. - Hoscheidt, Siobhan M; Starks, Erika J; Oh, Jennifer M; Zetterberg, Henrik; Blennow, Kaj; Krause, Rachel A; Gleason, Carey E; Puglielli, Luigi; Atwood, Craig S; Carlsson, Cynthia M; Asthana, Sanjay; Johnson, Sterling C; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Type 2 diabetes is associated with an increased risk for Alzheimer's disease (AD). Regulation of normal insulin function may be important in reducing the prevalence of dementia due to AD, particularly in individuals who harbor genetic risk for or have a parental family history of AD. The relationship between insulin resistance (IR) and AD pathology remains poorly understood, particularly in midlife prior to the onset of clinical metabolic disease or cognitive decline. OBJECTIVE: We examined associations between IR as indexed by HOMA-IR, cerebrospinal fluid (CSF) biomarkers of AD pathology, and memory in middle-aged adults enriched for AD. We postulated that higher HOMA-IR and APOEɛ4 carriage would be associated with greater CSF AD pathology and poor memory performance. METHODS: Cognitively asymptomatic middle-aged adults (N = 70, mean age = 57.7 years) from the Wisconsin Alzheimer's Disease Research Center with a parental family history of dementia due to AD underwent lumbar puncture, blood draw, and neuropsychological testing. CSF AD biomarkers including soluble amyloid-β protein precursor β (sAβPPβ), amyloid-β42 (Aβ42), and phosphorylated tau (P-tau181) were examined with respect to HOMA-IR and APOEɛ4 status. Delayed memory performance was examined with respect to HOMA-IR, CSF AD biomarkers, and APOEɛ4 status. RESULTS: Higher HOMA-IR was associated with higher sAβPPβ and Aβ42 . APOEɛ4 carriers had significantly higher levels of sAβPPα, sAβPPβ, and P-tau181/Aβ42 compared to noncarriers. The concurrent presence of higher HOMA-IR and CSF AD pathology predicted worse delayed memory performance. CONCLUSION: Overall, the findings suggest that IR and APOEɛ4 are contributing factors to the development of AD pathology in midlife, and provide support for targeting insulin function as a potentially modifiable risk factor for AD.

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intracerebroventricular Infusion of Angiotensin-(1-7) Ameliorates Cognitive Impairment and Memory Dysfunction in a Mouse Model of Alzheimer's Disease. - Uekawa, Ken; Hasegawa, Yu; Senju, Satoru; Nakagata, Naomi; Ma, Mingjie; Nakagawa, Takashi; Koibuchi, Nobutaka; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2016)
This work was performed to test our hypothesis that angiotensin-(1-7) can ameliorate cognitive impairment and cerebrovascular reactivity in 5XFAD mice, a useful model of Alzheimer's disease. 5XFAD mice received intracerebroventricular infusion of (1) vehicle, (2) angiotensin-(1-7), or (3) angiotensin-(1-7)+A779, a specific Mas receptor antagonist, for 4 weeks. Angiotensin-(1-7), through Mas receptor, significantly ameliorated cognitive impairment in 5XFAD mice. As estimated by acetazolamide-induced increase in cerebral blood flow, angiotensin-(1-7), through Mas receptor, enhanced cerebrovascular reactivity in 5XFAD mice. In conclusion, angiotensin-(1-7)/Mas receptor axis improves cognitive function and cerebrovascular function in a mouse model of Alzheimer's disease.

The Korean Size/Weight Attribute Test: A Semantic Knowledge Test for Korean Older Adults and Brain-Imaging Evidence. - Yoo, Yongjoon; Shin, Seong A; Park, Soowon; Lee, Ji-Hye; Youn, Jung-Hae; Kim, Yu Kyeong; Lee, Jun-Young (J Alzheimers Dis, 2016)
BACKGROUND: A standardized tool for evaluating semantic knowledge of the Korean population is needed. OBJECTIVE: The purpose of this study was to develop a neuropsychological test for the evaluation of semantic knowledge in the Korean elderly population. METHODS: The Korean version of the Size/Weight Attribute Test (SWAT-K) was developed in reference to the original version. The diagnostic validity of SWAT-K was evaluated with 95 elderly outpatients [67 normal controls; 18 with Alzheimer's disease (AD); 10 with semantic-variant progressive aphasia (SV-PPA)]. Voxel-based morphometry (VBM) was employed to examine associations between SWAT-K scores and morphological changes of the brain. RESULTS: SWAT-K could discriminate the three subject groups (normal >AD, p <  0.001; AD >SV-PPA, p = 0.040), whereas Boston Naming Test could not distinguish SV-PPA from AD. ROC curve analysis confirmed high levels of sensitivity (0.90) and specificity (0.93) for SWAT-K. The test's inter-rater reliability (ICC = 0.827) and test-retest reliability (ICC = 0.666) were assessed as well. VBM found a significant positive correlation (uncorrected p <  0.005, k >  100) between SWAT-K scores and gray matter volume in right inferior frontal cortex (T = 4.08, k = 191) and bilateral temporal cortices (left, T = 4.42, k = 135; right, T = 3.55, k = 253), the areas the most affected in SV-PPA. CONCLUSIONS: SWAT-K is a sensitive and reliable test for evaluating semantic knowledge in the Korean elderly population. Strong positive correlations between SWAT-K scores and the brain areas responsible for semantic processing further corroborate the validity of SWAT-K.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Analysis of Variance; Brain; Dementia; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Republic of Korea; ROC Curve; Semantics

Late-Life Depressive Symptoms and Lifetime History of Major Depression: Cognitive Deficits are Largely Due to Incipient Dementia rather than Depression. - Heser, Kathrin; Bleckwenn, Markus; Wiese, Birgitt; Mamone, Silke; Riedel-Heller, Steffi G; Stein, Janine; Lühmann, Dagmar; Posselt, Tina; Fuchs, Angela; Pentzek, Michael; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Late-life depression is frequently accompanied by cognitive impairments. OBJECTIVE: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. METHODS: In a cohort of very old initially non-demented primary care patients (n = 2,709, mean age = 81.1 y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. RESULTS: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. CONCLUSION: Marked cognitive impairments in old age depression should not be dismissed as "depressive pseudodementia", but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Less Daily Computer Use is Related to Smaller Hippocampal Volumes in Cognitively Intact Elderly. - Silbert, Lisa C; Dodge, Hiroko H; Lahna, David; Promjunyakul, Nutta-On; Austin, Daniel; Mattek, Nora; Erten-Lyons, Deniz; Kaye, Jeffrey A (J Alzheimers Dis, 2016)
BACKGROUND: Computer use is becoming a common activity in the daily life of older individuals and declines over time in those with mild cognitive impairment (MCI). The relationship between daily computer use (DCU) and imaging markers of neurodegeneration is unknown. OBJECTIVE: The objective of this study was to examine the relationship between average DCU and volumetric markers of neurodegeneration on brain MRI. METHODS: Cognitively intact volunteers enrolled in the Intelligent Systems for Assessing Aging Change study underwent MRI. Total in-home computer use per day was calculated using mouse movement detection and averaged over a one-month period surrounding the MRI. Spearman's rank order correlation (univariate analysis) and linear regression models (multivariate analysis) examined hippocampal, gray matter (GM), white matter hyperintensity (WMH), and ventricular cerebral spinal fluid (vCSF) volumes in relation to DCU. A voxel-based morphometry analysis identified relationships between regional GM density and DCU. RESULTS: Twenty-seven cognitively intact participants used their computer for 51.3 minutes per day on average. Less DCU was associated with smaller hippocampal volumes (r = 0.48, p = 0.01), but not total GM, WMH, or vCSF volumes. After adjusting for age, education, and gender, less DCU remained associated with smaller hippocampal volume (p = 0.01). Voxel-wise analysis demonstrated that less daily computer use was associated with decreased GM density in the bilateral hippocampi and temporal lobes. CONCLUSIONS: Less daily computer use is associated with smaller brain volume in regions that are integral to memory function and known to be involved early with Alzheimer's pathology and conversion to dementia. Continuous monitoring of daily computer use may detect signs of preclinical neurodegeneration in older individuals at risk for dementia.

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Longitudinal Relationships between Caloric Expenditure and Gray Matter in the Cardiovascular Health Study. - Raji, Cyrus A; Merrill, David A; Eyre, Harris; Mallam, Sravya; Torosyan, Nare; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Carmichael, Owen T; Gach, H Michael; Thompson, Paul M; Longstreth, W T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity (PA) can be neuroprotective and reduce the risk for Alzheimer's disease (AD). In assessing physical activity, caloric expenditure is a proxy marker reflecting the sum total of multiple physical activity types conducted by an individual. OBJECTIVE: To assess caloric expenditure, as a proxy marker of PA, as a predictive measure of gray matter (GM) volumes in the normal and cognitively impaired elderly persons. METHODS: All subjects in this study were recruited from the Institutional Review Board approved Cardiovascular Health Study (CHS), a multisite population-based longitudinal study in persons aged 65 and older. We analyzed a sub-sample of CHS participants 876 subjects (mean age 78.3, 57.5% F, 42.5% M) who had i) energy output assessed as kilocalories (kcal) per week using the standardized Minnesota Leisure-Time Activities questionnaire, ii) cognitive assessments for clinical classification of normal cognition, mild cognitive impairment (MCI), and AD, and iii) volumetric MR imaging of the brain. Voxel-based morphometry modeled the relationship between kcal/week and GM volumes while accounting for standard covariates including head size, age, sex, white matter hyperintensity lesions, MCI or AD status, and site. Multiple comparisons were controlled using a False Discovery Rate of 5 percent. RESULTS: Higher energy output, from a variety of physical activity types, was associated with larger GM volumes in frontal, temporal, and parietal lobes, as well as hippocampus, thalamus, and basal ganglia. High levels of caloric expenditure moderated neurodegeneration-associated volume loss in the precuneus, posterior cingulate, and cerebellar vermis. CONCLUSION: Increasing energy output from a variety of physical activities is related to larger gray matter volumes in the elderly, regardless of cognitive status.

Low Plasma Cholinesterase Activities are Associated with Deficits in Spatial Orientation, Reduced Ability to Perform Basic Activities of Daily Living, and Low Body Mass Index in Patients with Progressed Alzheimer's Disease. - Dingova, Dominika; Fazekas, Tomas; Okuliarova, Petra; Strbova, Jaroslava; Kucera, Matej; Hrabovska, Anna (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder characterized by a central cholinergic deficit. Non-neuronal cholinergic changes are, however, described as well. Here we focused on possible changes in the activity of the plasma cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), in hospitalized AD patients. We analyzed plasma AChE and BChE activities with regards to age, gender, body mass index (BMI), cognitive functions, and ability to perform activities of daily living in AD patients in comparison to healthy subjects. We observed lower AChE activity and trend toward lower BChE activity in AD patients, which both correlated with low BMI. AD patients unable to perform basic activities of daily living (feeding, bathing, dressing, and grooming) showed reduced plasma AChE activities, while worse spatial orientation was linked to lower BChE activities. Three out of four AD patients with the lowest BChE activities died within one year. In conclusion, progressed AD was accompanied by lower plasma AChE activity and trend toward lower BChE activity, which correlated with BMI and deficits in different components of the AD.
Keywords: Acetylcholinesterase; Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Blood Chemical Analysis; Body Mass Index; Butyrylcholinesterase; Female; Hospitalization; Humans; Male; Middle Aged; Orientation, Spatial

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measurement Error, Reliability, and Minimum Detectable Change in the Mini-Mental State Examination, Montreal Cognitive Assessment, and Color Trails Test among Community Living Middle-Aged and Older Adults. - Feeney, Joanne; Savva, George M; O'Regan, Claire; King-Kallimanis, Bellinda; Cronin, Hilary; Kenny, Rose Anne (J Alzheimers Dis, 2016)
BACKGROUND: Knowing the reliability of cognitive tests, particularly those commonly used in clinical practice, is important in order to interpret the clinical significance of a change in performance or a low score on a single test. OBJECTIVE: To report the intra-class correlation (ICC), standard error of measurement (SEM) and minimum detectable change (MDC) for the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Color Trails Test (CTT) among community dwelling older adults. METHODS: 130 participants aged 55 and older without severe cognitive impairment underwent two cognitive assessments between two and four months apart. Half the group changed rater between assessments and half changed time of day. RESULTS: Mean (standard deviation) MMSE was 28.1 (2.1) at baseline and 28.4 (2.1) at repeat. Mean (SD) MoCA increased from 24.8 (3.6) to 25.2 (3.6). There was a rater effect on CTT, but not on the MMSE or MoCA. The SEM of the MMSE was 1.0, leading to an MDC (based on a 95% confidence interval) of 3 points. The SEM of the MoCA was 1.5, implying an MDC95 of 4 points. MoCA (ICC = 0.81) was more reliable than MMSE (ICC = 0.75), but all tests examined showed substantial within-patient variation. CONCLUSION: An individual's score would have to change by greater than or equal to 3 points on the MMSE and 4 points on the MoCA for the rater to be confident that the change was not due to measurement error. This has important implications for epidemiologists and clinicians in dementia screening and diagnosis.

Memory Binding Test Predicts Incident Amnestic Mild Cognitive Impairment. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2016)
BACKGROUND: The Memory Binding Test (MBT), previously known as Memory Capacity Test, has demonstrated discriminative validity for distinguishing persons with amnestic mild cognitive impairment (aMCI) and dementia from cognitively normal elderly. OBJECTIVE: We aimed to assess the predictive validity of the MBT for incident aMCI. METHODS: In a longitudinal, community-based study of adults aged 70+, we administered the MBT to 246 cognitively normal elderly adults at baseline and followed them annually. Based on previous work, a subtle reduction in memory binding at baseline was defined by a Total Items in the Paired (TIP) condition score of ≤22 on the MBT. Cox proportional hazards models were used to assess the predictive validity of the MBT for incident aMCI accounting for the effects of covariates. The hazard ratio of incident aMCI was also assessed for different prediction time windows ranging from 4 to 7 years of follow-up, separately. RESULTS: Among 246 controls who were cognitively normal at baseline, 48 developed incident aMCI during follow-up. A baseline MBT reduction was associated with an increased risk for developing incident aMCI (hazard ratio (HR) = 2.44, 95% confidence interval: 1.30-4.56, p = 0.005). When varying the prediction window from 4-7 years, the MBT reduction remained significant for predicting incident aMCI (HR range: 2.33-3.12, p: 0.0007-0.04). CONCLUSION: Persons with poor performance on the MBT are at significantly greater risk for developing incident aMCI. High hazard ratios up to seven years of follow-up suggest that the MBT is sensitive to early disease.

Memory Impairment at Initial Clinical Presentation in Posterior Cortical Atrophy. - Ahmed, Samrah; Baker, Ian; Husain, Masud; Thompson, Sian; Kipps, Christopher; Hornberger, Michael; Hodges, John R; Butler, Christopher R (J Alzheimers Dis, 2016)
Posterior cortical atrophy (PCA) is characterized by core visuospatial and visuoperceptual deficits, and predominant atrophy in the parieto-occipital cortex. The most common underlying pathology is Alzheimer's disease (AD). Existing diagnostic criteria suggest that episodic memory is relatively preserved. The aim of this study was to examine memory performance at initial clinical presentation in PCA, compared to early-onset AD patients (EOAD). 15 PCA patients and 32 EOAD patients, and 34 healthy controls were entered into the study. Patients were tested on the Addenbrooke's Cognitive Examination (ACE-R), consisting of subscales in memory and visuospatial skills. PCA and EOAD patients were significantly impaired compared to controls on the ACE total score (p < 0.001), visuospatial skills (p < 0.001), and memory (p < 0.001). Consistent with the salient diagnostic deficits, PCA patients were significantly more impaired on visuospatial skills compared to EOAD patients (p < 0.001). However, there was no significant difference between patient groups in memory. Further analysis of learning, recall, and recognition components of the memory subscale showed that EOAD and PCA patients were significantly impaired compared to controls on all three components (p < 0.001), however, there was no significant difference between EOAD and PCA patients. The results of this study show that memory is impaired in the majority of PCA patients at clinical presentation. The findings suggest that memory impairment must be considered in assessment and management of PCA. Further study into memory in PCA is warranted, since the ACE-R is a brief screening tool and is likely to underestimate the presence of memory impairment.

A Mercaptoacetamide-Based Class II Histone Deacetylase Inhibitor Increases Dendritic Spine Density via RasGRF1/ERK Pathway. - Song, Jung Min; Sung, You Me; Nam, Jin Han; Yoon, Hyejin; Chung, Andrew; Moffat, Emily; Jung, Mira; Pak, Daniel T S; Kim, Jungsu; Hoe, Hyang-Sook (J Alzheimers Dis, 2016)
BACKGROUND: The accumulation of amyloid-β (Aβ) leads to the loss of dendritic spines and synapses, which is hypothesized to cause cognitive impairments in Alzheimer's disease (AD) patients. In our previous study, we demonstrated that a novel mercaptoacetamide-based class II histone deacetylase inhibitor (HDACI), known as W2, decreased Aβ levels and improved learning and memory in mice. However, the underlying mechanism of this effect is unknown. OBJECTIVE: Because dendritic spine formation is associated with cognitive performance, here we investigated whether HDACI W2 regulates dendritic spine density and its molecular mechanism of action. METHODS: To examine the effect of HDACI W2 on dendritic spine density, we conducted morphological analysis of dendritic spines using GFP transfection and Golgi staining. In addition, to determine the molecular mechanism of W2 effects on spines, we measured the levels of mRNAs and proteins involved in the Ras signaling pathway using quantitative real-time PCR, immunocytochemistry, and western analysis. RESULTS: We found that HDACI W2 altered dendritic spine density and morphology in vitro and in vivo. Additionally, W2 increased the mRNA or protein levels of Ras GRF1 and phospho-ERK. Moreover, knockdown of RasGRF1 and inhibition of ERK activity prevented the W2-mediated spinogenesis in primary hippocampal neurons. CONCLUSION: Our Class II-selective HDACI W2 promotes the formation and growth of dendritic spines in a RasGRF1 and ERK dependent manner in primary hippocampal neurons.
Keywords: Acetamides; Animals; Blotting, Western; Cells, Cultured; Cerebral Cortex; Dendritic Spines; Gene Knockdown Techniques; Green Fluorescent Proteins; Hippocampus; Histone Deacetylase Inhibitors; Immunohistochemistry; MAP Kinase Signaling System; Mice, Inbred C57BL; ras-GRF1; Rats, Sprague-Dawley; Real-Time Polymerase Chain Reaction; Receptors, AMPA; Receptors, N-Methyl-D-Aspartate; RNA, Messenger; Thioglycolates; Transfection

Metallothioneins in Prion- and Amyloid-Related Diseases. - Adam, Pavlína; Křížková, Soňa; Heger, Zbyněk; Babula, Petr; Pekařík, Vladimír; Vaculovičoá, Markéta; Gomes, Cláudio M; Kizek, René; Adam, Vojtěch (J Alzheimers Dis, 2016)
Prion and other amyloid-forming diseases represent a group of neurodegenerative disorders that affect both animals and humans. The role of metal ions, especially copper and zinc is studied intensively in connection with these diseases. Their involvement in protein misfolding and aggregation and their role in creation of reactive oxygen species have been shown. Recent data also show that metal ions not only bind the proteins with high affinity, but also modify their biochemical properties, making them important players in prion-related diseases. In particular, the level of zinc ions is tightly regulated by several mechanisms, including transporter proteins and the low molecular mass thiol-rich metallothioneins. From four metallothionein isoforms, metallothionein-3, a unique brain-specific metalloprotein, plays a crucial role only in this regulation. This review critically evaluates the involvement of metallothioneins in prion- and amyloid-related diseases in connection with the relationship between metallothionein isoforms and metal ion regulation of their homeostasis.
Keywords: Amyloidosis; Animals; Brain Diseases; Humans; Metallothionein; Prion Diseases

Metformin Facilitates Amyloid-β Generation by β- and γ-Secretases via Autophagy Activation. - Son, Sung Min; Shin, Hong-Joon; Byun, Jayoung; Kook, Sun Young; Moon, Minho; Chang, Yu Jin; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
The evidence of strong pathological associations between type 2 diabetes and Alzheimer's disease (AD) has increased in recent years. Contrary to suggestions that anti-diabetes drugs may have potential for treating AD, we demonstrate here that the insulin sensitizing anti-diabetes drug metformin (Glucophage®) increased the generation of amyloid-β (Aβ), one of the major pathological hallmarks of AD, by promoting β- and γ-secretase-mediated cleavage of amyloid-β protein precursor (AβPP) in SH-SY5Y cells. In addition, we show that metformin caused autophagosome accumulation in Tg6799 AD model mice. Extremely high γ-secretase activity was also detected in autophagic vacuoles, apparently a novel site of Aβ peptide generation. Together, these data suggest that metformin-induced accumulation of autophagosomes resulted in increased γ-secretase activity and Aβ generation. Additional experiments indicated that metformin increased phosphorylation of AMP-activated protein kinase, which activates autophagy by suppressing mammalian target of rapamycin (mTOR). The suppression of mTOR then induces the abnormal accumulation of autophagosomes. We conclude that metformin, an anti-diabetes drug, may exacerbate AD pathogenesis by promoting amyloidogenic AβPP processing in autophagosomes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Autophagy; Cell Line, Tumor; Disease Models, Animal; Female; Humans; Hypoglycemic Agents; Lysosomes; Metformin; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microscopy, Electron; Mutation; Neuroblastoma; Signal Transduction

Midlife Physical Activity and Cognition Later in Life: A Prospective Twin Study. - Iso-Markku, Paula; Waller, Katja; Vuoksimaa, Eero; Heikkilä, Kauko; Rinne, Juha; Kaprio, Jaakko; Kujala, Urho M (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity has been associated with a reduced risk of cognitive decline but the nature of this association remains obscure. OBJECTIVE: To study associations between midlife physical activity and cognition in old age for a prospective cohort of Finnish twins. METHODS: Physical activity in the Finnish Twin Cohort was assessed using questionnaire responses collected in 1975 and 1981. After a mean follow-up of 25.1 years, the subjects' (n = 3050; mean age 74.2; range 66-97) cognition was evaluated with a validated telephone interview. Both participation in vigorous physical activity, and the volume of physical activity, divided into quintiles, were used as predictors of cognitive impairment. Metrics collected by TELE were used to categorize participants as: cognitively impaired, suffering mild cognitive impairment, or cognitively healthy. RESULTS: Participation in vigorous physical activity compared to non-participation for both 1975 and 1981 was associated with a lower risk of cognitive impairment in individual-based analyses (fully adjusted OR 0.50, 95% CI 0.35-0.73). Pairwise analyses yielded similar but statistically non-significant associations. In terms of the volume of physical activity, the most active quintile of individuals (OR 0.69, 95% CI 0.46-1.04) had a reduced risk of cognitive decline compared with the most sedentary quintile in the fully adjusted model although no clear dose-response was found. CONCLUSION: Vigorous midlife physical activity was associated with less cognitive impairment but without a clear dose-response association between the volume of physical activity and cognition.

Mindfulness Training for Older Adults with Subjective Cognitive Decline: Results from a Pilot Randomized Controlled Trial. - Smart, Colette M; Segalowitz, Sidney J; Mulligan, Bryce P; Koudys, Jacob; Gawryluk, Jodie R (J Alzheimers Dis, 2016)
INTRODUCTION: Subjective cognitive decline (SCD) in older adults is a condition with a complex phenomenology and diverse etiologies including (but not limited to) mood, personality, and health concerns, as well as biomarkers of preclinical Alzheimer's disease such as amyloid-β deposition and gray matter volume loss. Approximately 60% of affected persons are estimated to decline to Alzheimer's dementia. Regardless of etiology, persons with SCD may be optimal targets for early intervention. OBJECTIVE: To ascertain the feasibility and impact of mindfulness training (MT) as an early intervention in persons with SCD. METHODS: Using a single-blind, randomized controlled trial design, older adults with (n = 14) and without (n = 22) SCD were randomized to either MT or a control condition of psychoeducation (PE) on cognitive aging. EEG/ERP (specifically, the P3 component), structural MRI, and self-report measures of psychological functioning were obtained within 4 weeks prior to and within 2 weeks following intervention. RESULTS: MT resulted in decreased reaction time intra-individual variability for all participants, with a selective increase in the P3 event-related component for those with SCD. Compared with PE, MT also resulted in an increase in percent volume brain change in structural MRI. Finally, all SCD participants reported a decrease in cognitive complaints and increase in memory self-efficacy following intervention. DISCUSSION: Results suggest that MT is a feasible early intervention in persons with SCD. Longer-term follow-up with larger sample sizes will determine whether MT can slow the rate of decline in persons who may be at risk for Alzheimer's dementia.

A Mitochondrial Role of SV2a Protein in Aging and Alzheimer's Disease: Studies with Levetiracetam. - Stockburger, Carola; Miano, Davide; Baeumlisberger, Marion; Pallas, Thea; Arrey, Tabiwang N; Karas, Michael; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2016)
Aberrant neuronal network activity associated with neuronal hyperexcitability seems to be an important cause of cognitive decline in aging and Alzheimer's disease (AD). Out of many antiepileptics, only levetiracetam improved cognitive dysfunction in AD patients and AD animal models by reducing hyperexcitability. As impaired inhibitory interneuronal function, rather than overactive neurons, seems to be the underlying cause, improving impaired neuronal function rather than quieting overactive neurons might be relevant in explaining the lack of activity of the other antiepileptics. Interestingly, improvement of cognitive deficits by levetiracetam caused by small levels of soluble Aβ was accompanied by improvement of synaptic function and plasticity. As the negative effects of Aβ on synaptic plasticity strongly correlate with mitochondrial dysfunction, wehypothesized that the effect of levetiracetam on synaptic activity might be raised by an improved mitochondrial function. Accordingly, we investigated possible effects of levetiracetam on neuronal deficits associated with mitochondrial dysfunction linked to aging and AD. Levetiracetam improved several aspects of mitochondrial dysfunction including alterations of fission and fusion balance in a cell model for aging and early late-onset AD. We demonstrate for the first time, using immunohistochemistry and proteomics, that the synaptic vesicle protein 2A (SV2a), the molecular target of levetiracetam, is expressed in mitochondria. In addition, levetiracetam shows significant effect on the opening of the mitochondrial permeability transition pore. Importantly, the effects of levetiracetam were significantly abolished when SV2a was knockdown using siRNA. In conclusion, interfering with the SV2a protein at the mitochondrial level and thereby improving mitochondrial function might represent an additional therapeutic effect of levetiracetam to improve symptoms of late-onset AD.
Keywords: Adenosine Triphosphate; Aging; Alzheimer Disease; Animals; Brain; Cell Line; Cognition Disorders; Female; GAP-43 Protein; Gene Expression Regulation; Humans; Male; Membrane Glycoproteins; Mitochondria; Mitochondrial Membrane Transport Proteins; Nerve Tissue Proteins; Nitroprusside; Nootropic Agents; Piracetam; Proteomics; Rats; RNA, Small Interfering

Morroniside-Induced PP2A Activation Antagonizes Tau Hyperphosphorylation in a Cellular Model of Neurodegeneration. - Yang, Cui-cui; Kuai, Xue-xian; Gao, Wen-bin; Yu, Jian-chun; Wang, Qi; Li, Lin; Zhang, Lan (J Alzheimers Dis, 2016)
BACKGROUND: An accumulation of hyperphosphorylated tau in the brain is a hallmark of Alzheimer's disease (AD). Deficits in protein phosphatase 2A (PP2A) are associated with tau hyperphosphorylation in AD. OBJECTIVE: To investigate the effects of morroniside (MOR), isolated from Cornus officinalis, on tau hyperphosphorylation and its underlying mechanisms related to PP2A. METHODS: SK-N-SH cells were pretreated with 50-200 μM MOR for 24 h followed by 20 nM okadaic acid (OA) for 6 h. PP2Ac siRNA was transfected into HEK293 cells to determine the direct interaction of MOR with PP2A. Western blotting was used to measure the expression of proteins and enzymes. PP2A activity was measured by molybdenum blue spectrophotometry. RESULTS: Pretreatment with MOR improved the cellular morphological damage and inhibited tau hyperphosphorylation in SK-N-SH cells induced by OA, a PP2A inhibitor. Moreover, MOR increased PP2A activity, concurrent with a decrease in the expression of demethylated PP2A at Leu309 and phosphorylated PP2A at Tyr307. MOR decreased protein phosphatase methylesterase 1 (PME-1) expression and the ratio of PME-1/leucine carboxyl methyltransferase 1 (LCMT-1). Furthermore, MOR treatment decreased the phosphorylation of Src at Tyr416, which regulates the phosphorylation of PP2A. MOR had no effect on PP2Ac expression and tau hyperphosphorylation in PP2Ac siRNA-transfected cells. CONCLUSION: MOR attenuated OA-induced tau hyperphosphorylation via PP2A activation, and its mechanism might be related to the regulation of PP2Ac post-translational modification and upstream enzymes such as Src and PME-1.
Keywords: Analysis of Variance; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Glycosides; HEK293 Cells; Humans; Neuroblastoma; Okadaic Acid; Phosphorylation; Protein Phosphatase 2; RNA, Small Interfering; tau Proteins; Transfection; Tyrosine

Mortality in Mild Cognitive Impairment: A Longitudinal Study in Memory Clinics. - Connors, Michael H; Ames, David; Boundy, Karyn; Clarnette, Roger; Kurrle, Sue; Mander, Alastair; Ward, John; Woodward, Michael; Brodaty, Henry (J Alzheimers Dis, 2016)
BACKGROUND: Patients with mild cognitive impairment (MCI) are at greater risk of mortality than the general population. Comparatively little research has examined predictors of mortality in MCI and no research has examined whether time-varying variables, such as change in cognition and function, predict survival. OBJECTIVE: To identify predictors of mortality in patients with MCI. METHODS: 185 patients with MCI were recruited from nine memory clinics around Australia. Patients completed measures of cognition, function, and neuropsychiatric symptoms over three years. Mortality data were obtained from state registries eight years after baseline. RESULTS: 55 (30%) patients died within this period. Older age, lower cognitive and functional ability at baseline, and greater decline in functional ability over six months predicted mortality. CONCLUSION: Easily measurable clinical data predict mortality in patients with MCI. Longitudinal assessment over time can provide additional information about patients' risk.

Neuropsychological Features of Microbleeds and Cortical Microinfarct Detected by High Resolution Magnetic Resonance Imaging. - Ueda, Yukito; Satoh, Masayuki; Tabei, Ken-Ichi; Kida, Hirotaka; Ii, Yuichiro; Asahi, Masaru; Maeda, Masayuki; Sakuma, Hajime; Tomimoto, Hidekazu (J Alzheimers Dis, 2016)
BACKGROUND: Lobar microbleeds (MBs) and cortical microinfarct (CMI) are caused by cerebral amyloid angiopathy in the elderly and increase in number in Alzheimer's disease. OBJECTIVE: The aim of this study is to elucidate the effects of lobar MBs and CMIs on cognitive function. METHODS: The subjects were outpatients who visited the memory clinic of Mie University Hospital. Among 120 subjects, 109 patients fulfilled the inclusion criteria. We quantitatively estimated MBs and CMIs using double inversion recovery and 3D FLAIR images of 3T MRI. Neuropsychological assessments included intellectual, memory, constructional, and frontal lobe function. RESULTS: Of the 109 patients, MBs and CMIs were observed in 68 (62%) and 17 (16%) subjects, respectively. Of the 68 patients with MBs, lobar MBs were found in 28, deep MBs in 8 and mixed MBs in 31. In each age group, the number of MBs increased in patients with CMI (CMI+ group) than those without CMI (CMI- group), and MBs and CMIs additively decreased MMSE scores. In psychological screens, the MBs+ group with more than 10 MBs showed significantly lower scores of category- and letter-WF than MB- group. The CMI+ group showed significantly worse scores than CMI- group in Japanese Raven's coloured progressive matrices, Trail Making Test-A, category- and letter-word fluency and copy and drawing of figures. CONCLUSION: Lobar MBs and CMIs in the elderly frequently coexisted with each other and additively contributed to cognitive impairment, which is mainly predisposed to frontal lobe function.

Neuropsychological Markers of Medial Perirhinal and Entorhinal Cortex Functioning are Impaired Twelve Years Preceding Diagnosis of Alzheimer's Dementia. - Hirni, Daniela I; Kivisaari, Sasa L; Krumm, Sabine; Monsch, Andreas U; Berres, Manfred; Oeksuez, Fatma; Reinhardt, Julia; Ulmer, Stephan; Kressig, Reto W; Stippich, Christoph; Taylor, Kirsten I (J Alzheimers Dis, 2016)
Neurofibrillary pathology in Alzheimer's dementia (AD) is associated with cognitive impairments and cortical thinning, and begins in medial perirhinal cortex (mPRC) before entering entorhinal cortex (ERC). Thus, mPRC dysfunction (e.g., semantic object memory impairments) may predate or accompany ERC (i.e., episodic memory) dysfunction in the preclinical course of typical AD. We developed formulae estimating mPRC and ERC integrity (i.e., cortical thickness) using common neuropsychological tests in 31 healthy individuals and 58 early AD patients. These formulae estimated the longitudinal courses of mPRC and ERC functioning in independent groups of 28 optimally healthy individuals who developed AD (NC-AD) over 2.8-13.4 years and 28 pairwise-matched, stable, healthy individuals (NC-NC). Mixed models demonstrated significantly worse NC-AD than NC-NC estimated mPRC and ERC functioning at the earliest observation, 12 years preceding diagnosis, and a significant decline 4 years preceding the AD diagnosis. These findings demonstrate that specific neuropsychological impairments occur early in the course of preclinical AD and that tasks measuring mPRC functioning may serve as additional, powerful markers of preclinical AD.

Non-Fibrillar Oligomeric Amyloid-β within Synapses. - Pickett, Eleanor K; Koffie, Robert M; Wegmann, Susanne; Henstridge, Christopher M; Herrmann, Abigail G; Colom-Cadena, Marti; Lleo, Alberto; Kay, Kevin R; Vaught, Melissa; Soberman, Roy; Walsh, Dominic M; Hyman, Bradley T; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by memory loss, insidious cognitive decline, profound neurodegeneration, and the extracellular accumulation of amyloid-β (Aβ) peptide in senile plaques and intracellular accumulation of tau in neurofibrillary tangles. Loss and dysfunction of synapses are believed to underlie the devastating cognitive decline in AD. A large amount of evidence suggests that oligomeric forms of Aβ associated with senile plaques are toxic to synapses, but the precise sub-synaptic localization of Aβ and which forms are synaptotoxic remain unknown. Here, we characterize the sub-synaptic localization of Aβ oligomers using three high-resolution imaging techniques, stochastic optical reconstruction microscopy, immunogold electron microscopy, and Förster resonance energy transfer in a plaque-bearing mouse model of AD. With all three techniques, we observe oligomeric Aβ inside synaptic terminals. Further, we tested a panel of Aβ antibodies using the relatively high-throughput array tomography technique to determine which forms are present in synapses. Our results show that different oligomeric Aβ species are present in synapses and highlight the potential of array tomography for rapid testing of aggregation state specific Aβ antibodies in brain tissue.

A Novel and Intelligent Home Monitoring System for Care Support of Elders with Cognitive Impairment. - Lazarou, Ioulietta; Karakostas, Anastasios; Stavropoulos, Thanos G; Tsompanidis, Theodoros; Meditskos, Georgios; Kompatsiaris, Ioannis; Tsolaki, Magda (J Alzheimers Dis, 2016)
BACKGROUND: Assistive technology, in the form of a smart home environment, is employed to support people with dementia. OBJECTIVES: To propose a system for continuous and objective remote monitoring of problematic daily living activity areas and design personalized interventions based on system feedback and clinical observations for improving cognitive function and health-related quality of life. METHODS: The assistive technology of the proposed system, including wearable, sleep, object motion, presence, and utility usage sensors, was methodically deployed at four different home installations of people with cognitive impairment. Detection of sleep patterns, physical activity, and activities of daily living, based on the collected sensor data and analytics, was available at all times through comprehensive data visualization solutions. Combined with clinical observation, targeted psychosocial interventions were introduced to enhance the participants' quality of life and improve their cognitive functions and daily functionality. Meanwhile, participants and their caregivers were able to visualize a reduced set of information tailored to their needs. RESULTS: Overall, paired-sample t-test analysis of monitored qualities revealed improvement for all participants in neuropsychological assessment. Moreover, improvement was detected from the beginning to the end of the trial, in physical condition and in the domains of sleep. Detecting abnormalities via the system, for example in sleep quality, such as REM sleep, has proved to be critical to assess current status, drive interventions, and evaluate improvements in a reliable manner. CONCLUSION: It has been proved that the proposed system is suitable to support clinicians to reliably drive and evaluate clinical interventions toward quality of life improvement of people with cognitive impairment.

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

An Optimized Combination of Ginger and Peony Root Effectively Inhibits Amyloid-β Accumulation and Amyloid-β-Mediated Pathology in AβPP/PS1 Double-Transgenic Mice. - Lim, Soonmin; Choi, Jin Gyu; Moon, Minho; Kim, Hyo Geun; Lee, Wonil; Bak, Hyoung-Rok; Sung, Hachang; Park, Chi Hye; Kim, Sun Yeou; Oh, Myung Sook (J Alzheimers Dis, 2016)
The progressive aggregation of amyloid-β protein (Aβ) into senile plaques is a major pathological factor of Alzheimer's disease (AD) and is believed to result in memory impairment. We aimed to investigate the effect of an optimized combination of ginger and peony root (OCGP), a standardized herbal mixture of ginger and peony root, on Aβ accumulation and memory impairment in amyloid-β protein precursor (AβPP)/presenilin 1 (PS1) double-transgenic mice. In an in vitro thioflavin T fluorescence assay, 100 μg/ml OCGP inhibited Aβ accumulation to the same extent as did 10 μM curcumin. Furthermore, AβPP/PS1 double-transgenic mice treated with OCGP (50 or 100 mg/kg/day given orally for 14 weeks) exhibited reduced Aβ plaque accumulation in the hippocampus and lower levels of glial fibrillary acid protein and cyclooxygease-2 expression compared with vehicle-treated controls. These results suggest that OCGP may prevent memory impairment in AD by inhibiting Aβ accumulation and inflammation in the brain.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Cyclooxygenase 2; Disease Models, Animal; Dose-Response Relationship, Drug; Ginger; Glial Fibrillary Acidic Protein; Humans; Male; Mice; Mice, Transgenic; Mutation; Paeonia; Phytotherapy; Plant Preparations; Plaque, Amyloid; Presenilin-1

Oral Infections and Cytokine Levels in Patients with Alzheimer's Disease and Mild Cognitive Impairment Compared with Controls. - Cestari, José Augusto Ferrari; Fabri, Gisele Maria Campos; Kalil, Jorge; Nitrini, Ricardo; Jacob-Filho, Wilson; de Siqueira, José Tadeu Tesseroli; Siqueira, Silvia Regina D T (J Alzheimers Dis, 2016)
BACKGROUND: Oral infections are prevalent in the adult population. Their impact includes the implication as a risk factor for Alzheimer's disease (AD), altering its progression. One of the potential mechanisms involves immune mediators such as circulating cytokines. OBJECTIVE: The goal of the present study was to investigate the prevalence of oral infections and blood levels of IL-1β, TNF-α, and IL-6 in patients with AD, mild cognitive impairment (MCI), and controls. METHODS: Sixty-five elderly were evaluated (25 AD, 19 MCI, and 21 controls) by the following methods: Mini Mental State Exam, Questionnaire of Functional Activities, periodontal and oral evaluation, and blood concentrations of IL-1β, TNF-α and IL-6. RESULTS: Patients with AD had high serum IL-6 levels (p = 0.029), and patients with periodontitis had high serum TNF-α levels (p = 0.005). There was an association between IL-6 and TNF-α in patients with AD/MCI and periodontitis (p = 0.023). CONCLUSION: The increased levels of TNF-α and IL-6 in this study suggests their implication in the overlapping mechanisms between oral infections and AD. Longitudinal studies are necessary for further investigation.

Paired Studies Comparing Clinical Profiles of Lewy Body Dementia with Alzheimer's and Parkinson's Diseases. - Scharre, Douglas W; Chang, Shu-Ing; Nagaraja, Haikady N; Park, Ariane; Adeli, Anahita; Agrawal, Punit; Kloos, Anne; Kegelmeyer, Deb; Linder, Shannon; Fritz, Nora; Kostyk, Sandra K; Kataki, Maria (J Alzheimers Dis, 2016)
Limited data compares clinical profiles of Lewy Body Dementia (LBD) with Alzheimer's disease (AD) and Parkinson's disease (PD). Twenty-one mildly demented ambulatory LBD subjects were individually matched by MMSE score with 21 AD subjects and by UPDRS motor score with 21 PD subjects. Matched by age, gender, education, and race, pairs were compared using cognitive, functional, behavioral, and motor measures. LBD group performed worse than PD on axial motor, gait, and balance measures. AD had more amnesia and orientation impairments, but less executive and visuospatial deficits than LBD subjects. LBD group had more sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea than AD or PD. Axial motor, gait, and balance disturbances correlated with executive, visuospatial, and global cognition deficits. LBD is differentiated from AD and PD by retrieval memory, visuospatial, and executive deficits; axial motor, gait and balance impairments; sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea.

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patients that have Undergone Hemodialysis Exhibit Lower Amyloid Deposition in the Brain: Evidence Supporting a Therapeutic Strategy for Alzheimer's Disease by Removal of Blood Amyloid. - Sakai, Kazuyoshi; Senda, Takao; Hata, Ryuji; Kuroda, Makoto; Hasegawa, Midori; Kato, Masao; Abe, Masato; Kawaguchi, Kazunori; Nakai, Shigeru; Hiki, Yoshiyuki; Yuzawa, Yukio; Kitaguchi, Nobuya (J Alzheimers Dis, 2016)
As a proof of concept that removal of blood amyloid-β (Aβ) can reduce Aβ deposition in the brains of patients with Alzheimer's disease, cortices of patients who had undergone hemodialysis (HD), which removes Aβ from the blood, were histochemically analyzed; postmortem brain sections were stained with anti-Aβ antibodies. Brains from patients who had undergone HD had significantly fewer senile plaques than those of patient who had not undergone HD. This significant difference was also confirmed by silver staining. Our findings suggest that removal of blood Aβ by hemodialysis results in lower accumulation of Aβ in the brain.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Autopsy; Brain; Case-Control Studies; Humans; Kidney Diseases; Plaque, Amyloid; Renal Dialysis; Silver Staining; Statistics, Nonparametric

Pauses During Autobiographical Discourse Reflect Episodic Memory Processes in Early Alzheimer's Disease. - Pistono, Aurélie; Jucla, Mélanie; Barbeau, Emmanuel J; Saint-Aubert, Laure; Lemesle, Béatrice; Calvet, Benjamin; Köpke, Barbara; Puel, Michèle; Pariente, Jérémie (J Alzheimers Dis, 2016)
There is a large body of research on discourse production in Alzheimer's disease (AD). Some studies have focused on pause production, revealing that patients make extensive use of pauses during speech. This has been attributed to lexical retrieval difficulties, but pausing may also reflect other forms of cognitive impairment as it increases with cognitive load. The aim of the present study was to analyze autobiographical discourse impairment in AD from a broad perspective, looking at pausing behavior (frequency, duration, and location). Our first objective was to characterize discourse changes in mild cognitive impairment (MCI) due to AD. Our second objective was to determine the cognitive and neuroanatomical correlates of these changes. Fifteen patients with MCI due to AD and 15 matched cognitively normal controls underwent an ecological episodic memory task, a full neuropsychological assessment, and a 3D T1-weighted MRI scans. Autobiographical discourse collected from the ecological episodic memory task was recorded, transcribed, and analyzed, focusing on pausing. Intergroup comparisons showed that although patients did not produce more pauses than controls overall, they did make more between-utterance pauses. The number of these specific pauses was positively correlated with patients' episodic memory performance. Furthermore, neuroimaging analysis showed that, in the patient group, their use was negatively correlated with frontopolar area (BA 10) grey matter density. This region may therefore play an important role in the planning of autobiographical discourse production. These findings demonstrate that pauses in early AD may reflect a compensatory mechanism for improving mental time travel and memory retrieval.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Female; Humans; Male; Memory Disorders; Memory, Episodic; Mental Status Schedule; Neuropsychological Tests; Positron-Emission Tomography; Statistics as Topic

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Peripheral Administration of GSK-3β Antisense Oligonucleotide Improves Learning and Memory in SAMP8 and Tg2576 Mouse Models of Alzheimer's Disease. - Farr, Susan A; Sandoval, Karin E; Niehoff, Michael L; Witt, Ken A; Kumar, Vijaya B; Morley, John E (J Alzheimers Dis, 2016)
Glycogen synthase kinase (GSK)-3β is a multifunctional protein that has been implicated in the pathological characteristics of Alzheimer's disease (AD), including the heightened levels of neurofibrillary tangles, amyloid-beta (Aβ), and neurodegeneration. We have previously shown that an antisense oligonucleotide directed at the Tyr 216 site on GSK-3β (GAO) when injected centrally can decrease GSK-3β levels, improve learning and memory, and decrease oxidative stress. In addition, we showed that GAO can cross the blood-brain barrier. Herein the impact of peripherally administered GAO in both the non-transgenic SAMP8 and transgenic Tg2576 (APPswe) models of AD were examined respective to learning and memory. Brain tissues were then evaluated for expression changes in the phosphorylated-Tyr 216 residue, which leads to GSK-3β activation, and the phosphorylated-Ser9 residue, which reduces GSK-3β activity. SAMP8 GAO-treated mice showed improved acquisition and retention using aversive T-maze, and improved declarative memory as measured by the novel object recognition (NOR) test. Expression of the phosphorylated-Tyr 216 was decreased and the phosphorylated-Ser9 was increased in GAO-treated SAMP8 mice. Tg2576 GAO-treated mice improved acquisition and retention in both the T-maze and NOR tests, with an increased phosphorylated-Ser9 GSK-3β expression. Results demonstrate that peripheral administration of GAO improves learning and memory, corresponding with alterations in GSK-3β phosphorylation state. This study supports peripherally administered GAO as a viable means to mediate GSK-3β activity within the brain and a possible treatment for AD.

Pharmacological Modulations of the Serotonergic System in a Cell-Model of Familial Alzheimer's Disease. - Tajeddinn, Walid; Persson, Torbjörn; Calvo-Garrido, Javier; Seed Ahmed, Mohammed; Maioli, Silvia; Vijayaraghavan, Swetha; Kazokoglu, Mehmet Selim; Parrado-Fernández, Cristina; Yoshitake, Takashi; Kehr, Jan; Francis, Paul; Winblad, Bengt; et al. (J Alzheimers Dis, 2016)
Serotonin (5-HT) plays a central role in the integrity of different brain functions. The 5-HT homeostasis is regulated by many factors, including serotonin transporter (SERT), monoamine oxidase enzyme (MAO), and several 5-HT receptors, including the 5-HT1B. There is little knowledge how the dynamics of this system is affected by the amyloid-β (Aβ) burden of Alzheimer's disease (AD) pathology. SH-SY5Y neuroblastoma cells transfected with the amyloid precursor protein (APP) gene containing the Swedish mutations causing familial AD (APPswe), were used as a model to explore the effect of Aβ pathology on 5-HT1B and related molecules including the receptor adaptor protein (p11), SERT and MAOA gene expression, and MAOA activity after treatment with selective serotonin reuptake inhibitor (SSRI) (sertraline), and a 5-HT1B receptor antagonist. Sertraline led more than 70 fold increase of 5-HT1B gene expression (p < 0.001), an increased serotonin turnover in both APPswe and control cells and reduced intracellular serotonin levels by 75% in APPswe cells but not in controls (p > 0.05). Treatment with the 5-HT1B receptor antagonist increased SERT gene-expression in control cells but not in the APPswe cells. 5-HT and 5-HT1B antagonist treatment resulted in different p11 expression patterns in APPswe cells compared to controls. Although MAOA gene expression was not changed by APPswe overexpression, adding 5-HT lead to a significant increase in MAOA gene expression in APPswe but not control cells. These findings suggest that the sensitivity of the 5-HT1B receptor and related systems is affected by APPswe overexpression, with potential relevance for pharmacologic intervention in AD. This may at least partly explain the lack of effect of SSRIs in patients with AD and depression.

Phenomenological Reliving and Visual Imagery During Autobiographical Recall in Alzheimer's Disease. - El Haj, Mohamad; Kapogiannis, Dimitrios; Antoine, Pascal (J Alzheimers Dis, 2016)

Physical and Cognitive Stimulation Using an Exergame in Subjects with Normal Aging, Mild and Moderate Cognitive Impairment. - Ben-Sadoun, Grégory; Sacco, Guillaume; Manera, Valeria; Bourgeois, Jérémy; König, Alexandra; Foulon, Pierre; Fosty, Baptiste; Bremond, François; d'Arripe-Longueville, Fabienne; Robert, Philippe (J Alzheimers Dis, 2016)
BACKGROUND: The use of Serious exerGames (SeG) as enriched environments (EE), which promotes cognitive simulation with physical activity in a positive emotional context, has been proposed to represent a powerful method to slow down the decline due to neurodegenerative diseases (ND), such as Alzheimer's disease (AD). However, so far, no SeG targeting EE has been tested in ND subjects. OBJECTIVE: This study aimed at evaluating the usability and short-term training effects of X-Torp, an action SeG designed for elderly ND subjects with mild cognitive impairment (MCI) and AD. METHODS: X-Torp is a SeG played using the Microsoft® Kinect™. 10 ND subjects and 8 healthy elderly controls (HEC) were enrolled in a 1-month program with three training sessions per week. Usability was evaluated through game time, game performance, the aerobic intensity level reached, perceived emotions, and perceived usability. RESULTS: All participants successfully completed the training program. ND subjects played less and had a lower game performance compared to HEC. During the sessions, ND subjects maintained a light intensity of aerobic activity, while HEC maintained a moderate intensity. Both groups experienced only positive emotions, and reported a 'moderate' to 'high' perceived competence, a 'moderate' game difficulty, and a 'high' interest in the game. CONCLUSION: Usability results suggest that X-Torp represents a usable EE for healthy subjects and persons with MCI and AD. However, in order to reach moderate or high intensity of aerobic activity, X-Torp control modes should be adapted to become more physically stimulating.

PiB-PET Imaging-Based Serum Proteome Profiles Predict Mild Cognitive Impairment and Alzheimer's Disease. - Kang, Seokjo; Jeong, Hyobin; Baek, Je-Hyun; Lee, Seung-Jin; Han, Sun-Ho; Cho, Hyun Jin; Kim, Hee; Hong, Hyun Seok; Kim, Young Ho; Yi, Eugene C; Seo, Sang Won; Na, Duk L; et al. (J Alzheimers Dis, 2016)
Development of a simple, non-invasive early diagnosis platform of Alzheimer's disease (AD) using blood is urgently required. Recently, PiB-PET imaging has been shown to be powerful to quantify amyloid-β plaque loads leading to pathophysiological alterations in AD brains. Thus, there has been a need for serum biomarkers reflecting PiB-PET imaging data as an early diagnosis platform of AD. Here, using LC-MS/MS analysis coupled with isobaric tagging, we performed comprehensive proteome profiling of serum samples from cognitively normal controls, mild cognitive impairment (MCI), and AD patients, who were selected using PiB-PET imaging. Comparative analysis of the proteomes revealed 79 and 72 differentially expressed proteins in MCI and AD, respectively, compared to controls. Integrated analysis of these proteins with genomic and proteomic data of AD brain tissues, together with network analysis, identified three biomarker candidates representing the altered proteolysis-related process in MCI or AD: proprotein convertase subtilisin/kexin type 9 (PCSK9), coagulation factor XIII, A1 polypeptide (F13A1), and dermcidin (DCD). In independent serum samples of MCI and AD, we confirmed the elevation of the candidates using western blotting and ELISA. Our results suggest that these biomarker candidates can serve as a potential non-invasive early diagnosis platform reflecting PiB-PET imaging for MCI and AD.

Post Hoc Analyses of ApoE Genotype-Defined Subgroups in Clinical Trials. - Kennedy, Richard E; Cutter, Gary R; Wang, Guoqiao; Schneider, Lon S (J Alzheimers Dis, 2016)
BACKGROUND: Many post hoc analyses of clinical trials in Alzheimer's disease (AD) and mild cognitive impairment (MCI) are in small Phase 2 trials. Subject heterogeneity may lead to statistically significant post hoc results that cannot be replicated in larger follow-up studies. OBJECTIVE: We investigated the extent of this problem using simulation studies mimicking current trial methods with post hoc analyses based on ApoE4 carrier status. METHODS: We used a meta-database of 24 studies, including 3,574 subjects with mild AD and 1,171 subjects with MCI/prodromal AD, to simulate clinical trial scenarios. Post hoc analyses examined if rates of progression on the Alzheimer's Disease Assessment Scale-cognitive (ADAS-cog) differed between ApoE4 carriers and non-carriers. RESULTS: Across studies, ApoE4 carriers were younger and had lower baseline scores, greater rates of progression, and greater variability on the ADAS-cog. Up to 18% of post hoc analyses for 18-month trials in AD showed greater rates of progression for ApoE4 non-carriers that were statistically significant but unlikely to be confirmed in follow-up studies. The frequency of erroneous conclusions dropped below 3% with trials of 100 subjects per arm. In MCI, rates of statistically significant differences with greater progression in ApoE4 non-carriers remained below 3% unless sample sizes were below 25 subjects per arm. CONCLUSIONS: Statistically significant differences for ApoE4 in post hoc analyses often reflect heterogeneity among small samples rather than true differential effect among ApoE4 subtypes. Such analyses must be viewed cautiously. ApoE genotype should be incorporated into the design stage to minimize erroneous conclusions.
Keywords: Alzheimer Disease; Apolipoprotein E4; Clinical Trials as Topic; Cognitive Dysfunction; Data Interpretation, Statistical; Humans; Research Design

Posterior Ventricular Enlargement to Differentiate Dementia with Lewy Bodies from Alzheimer's Disease. - Ye, Byoung Seok; Lee, Yoonju; Kwak, Kichang; Park, Yeong-Hun; Ham, Jee Hyun; Lee, Jae Jung; Shin, Na-Young; Lee, Jong-Min; Sohn, Young H; Lee, Phil Hyu (J Alzheimers Dis, 2016)
BACKGROUND: Enlargement of the lateral ventricle is observed in dementia associated with Alzheimer's disease (AD) and dementia with Lewy bodies (DLB). OBJECTIVE: The degree of anteroposterior ventricular enlargement and its correlation with clinical and neuropsychological features were investigated in DLB patients. METHODS: Forty-eight patients with DLB, 76 with AD, and 45 subjects with normal cognition (NC) underwent structural brain MRI and detailed neuropsychological tests. Ventricular shape was compared among the groups by visual inspection. Posterior ventricle enlargement (PVE) was defined as the ratio of the distance between the temporal and occipital horns of the lateral ventricle to the distance between the temporal horn of the lateral ventricle and occipital pole of the brain. RESULTS: After controlling for age, sex, and education, higher PVE was observed in the DLB group than in the AD group (68.5 ± 7.9% versus 62.8 ± 9.0%, respectively; p = 0.001) or the NC group (61.9 ± 9.9%, p = 0.002). However, higher PVE was not associated with poorer neuropsychological performance, nor was it associated with any clinical features in the DLB group after controlling for age, sex, and education. CONCLUSION: PVE occurs more often in DLB than in AD and NC. However, it is unclear how PVE is related to the clinical and neuropsychological features of DLB.

Postmortem Adult Human Microglia Proliferate in Culture to High Passage and Maintain Their Response to Amyloid-β. - Guo, Ling; Rezvanian, Aras; Kukreja, Lokesh; Hoveydai, Ramez; Bigio, Eileen H; Mesulam, M-Marsel; El Khoury, Joseph; Geula, Changiz (J Alzheimers Dis, 2016)
Microglia are immune cells of the brain that display a range of functions. Most of our knowledge about microglia biology and function is based on cells from the rodent brain. Species variation in the complexity of the brain and differences in microglia response in the primate when compared with the rodent, require use of adult human microglia in studies of microglia biology. While methods exist for isolation of microglia from postmortem human brains, none allow culturing cells to high passage. Thus cells from the same case could not be used in parallel studies and multiple conditions. Here we report a method, which includes use of growth factors such as granulocyte macrophage colony stimulating factor, for successful culturing of adult human microglia from postmortem human brains up to 28 passages without significant loss of proliferation. Such cultures maintained their phenotype, including uptake of the scavenger receptor ligand acetylated low density lipoprotein and response to the amyloid-β peptide, and were used to extend in vivo studies in the primate brain demonstrating that inhibition of microglia activation protects neurons from amyloid-β toxicity. Significantly, microglia cultured from brains with pathologically confirmed Alzheimer's disease displayed the same characteristics as microglia cultured from normal aged brains. The method described here provides the scientific community with a new and reliable tool for mechanistic studies of human microglia function in health from childhood to old age, and in disease, enhancing the relevance of the findings to the human brain and neurodegenerative conditions.

A Potential VEP Biomarker for Mild Cognitive Impairment: Evidence from Selective Visual Deficit of Higher-Level Dorsal Pathway. - Yamasaki, Takao; Horie, Shizuka; Ohyagi, Yasumasa; Tanaka, Eri; Nakamura, Norimichi; Goto, Yoshinobu; Kanba, Shigenobu; Kira, Jun-Ichi; Tobimatsu, Shozo (J Alzheimers Dis, 2016)
Visual dysfunctions are common in Alzheimer's disease (AD). Our aim was to establish a neurophysiological biomarker for amnestic mild cognitive impairment (aMCI). Visual evoked potentials (VEPs) were recorded in aMCI patients who later developed AD (n = 15) and in healthy older (n = 15) and younger controls (n = 15). Visual stimuli were optimized to separately activate lower and higher levels of the ventral and dorsal streams. We compared VEP parameters across the three groups of participants and conducted a linear correlation analysis between VEPs and data from neuropsychological tests. We then used a receiver operating characteristic (ROC) analysis to discriminate those with aMCI from those who were healthy older adults. The latency and phase of VEPs to lower-level stimuli (chromatic and achromatic gratings) were significantly affected by age but not by cognitive decline. Conversely, VEP latencies for higher-ventral (faces and kanji-words) and dorsal (kana-words and optic flow motion) stimuli were not affected by age, but they were significantly prolonged in aMCI patients. Interestingly, VEPs for higher-dorsal stimuli were related to outcomes of neuropsychological tests. Furthermore, the ROC analysis showed that the highest areas under the curve were obtained for VEP latencies in response to higher-dorsal stimuli. These results suggest aMCI-related functional impairment specific to higher-level visual processing. Further, dysfunction in the higher-level of the dorsal stream could be an early indicator of cognitive decline. Therefore, we conclude that VEPs associated with higher-level dorsal stream activity can be a sensitive biomarker for early detection of aMCI.

Predictors of Mortality in Dementia: The PRIME Study. - Connors, Michael H; Ames, David; Boundy, Karyn; Clarnette, Roger; Kurrle, Sue; Mander, Alastair; Ward, John; Woodward, Michael; Brodaty, Henry (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is a terminal illness. While various baseline characteristics of patients, such as age, sex, and dementia severity, are known to predict mortality, little research has examined how changes in patients' symptoms over time predict survival. There are also limited data on patients seen in memory clinics, as opposed to other health care settings, and whether antipsychotic medications are associated with mortality in dementia once patients' demographic and clinical features are controlled for. OBJECTIVE: To identify predictors of mortality in patients with dementia. METHOD: Of 970 patients recruited from nine memory clinics around Australia, 779 patients had dementia at baseline. Patients completed measures of dementia severity, cognition, functional ability, neuropsychiatric symptoms, caregiver burden, and medication use at baseline and at regular intervals over a three-year period. Mortality data were obtained from state registries eight years after baseline. RESULTS: Overall, 447 (57.4%) of the patients with dementia died within the eight years. Older age, male sex, more severe dementia and functional impairment at baseline, greater decline in dementia severity and functional impairment over six months, taking a larger number of medications, and use of atypical antipsychotic medication predicted earlier mortality. CONCLUSIONS: The findings confirm that demographic and diagnostic features predict the survival of patients with dementia. Importantly, the findings indicate that changes in dementia severity and functional impairment over time predict mortality independently of baseline levels, and provide further evidence for the higher mortality risk of patients taking antipsychotic medications.

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer's Disease and Mild Cognitive Impairment Patients. - Rai, Nitish; Kumar, Rahul; Desai, Gaurav Rajesh; Venugopalan, G; Shekhar, Shashank; Chatterjee, Prasun; Tripathi, Manjari; Upadhyay, Ashish Datt; Dwivedi, Sadanand; Dey, Aparajit B; Dey, Sharmistha (J Alzheimers Dis, 2016)
Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups was determined by real time polymerase chain reaction. The results showed significant overexpression of serum sesn2 protein and mRNA levels in the AD group compared to MCI and elderly control groups. A difference in serum sesn2 concentration between MCI and the control group was also evident. ROC analysis showed highly sensitive, selective cutoff values for sens2 in the differentiation of AD, MCI, and controls. No significant difference in sesn1 level was observed among the study groups. This study highlights the important role of sesn2 in the progression of the AD, indicating its potential utility as a protein marker in this devastating disease.

Reliability and Validity of a Novel Internet-Based Battery to Assess Mood and Cognitive Function in the Elderly. - Myers, Candice A; Keller, Jeffrey N; Allen, H Raymond; Brouillette, Robert M; Foil, Heather; Davis, Allison B; Greenway, Frank L; Johnson, William D; Martin, Corby K (J Alzheimers Dis, 2016)
Dementia is a chronic condition in the elderly and depression is often a concurrent symptom. As populations continue to age, accessible and useful tools to screen for cognitive function and its associated symptoms in elderly populations are needed. The aim of this study was to test the reliability and validity of a new internet-based assessment battery for screening mood and cognitive function in an elderly population. Specifically, the Helping Hand Technology (HHT) assessments for depression (HHT-D) and global cognitive function (HHT-G) were evaluated in a sample of 57 elderly participants (22 male, 35 female) aged 59-85 years. The study sample was categorized into three groups: 1) dementia (n = 8; Mini-Mental State Exam (MMSE) score 10-24), 2) mild cognitive impairment (n = 24; MMSE score 25-28), and 3) control (n = 25; MMSE score 29-30). Test-retest reliability (Pearson correlation coefficient, r) and internal consistency reliability (Cronbach's alpha, α) of the HHT-D and HHT-G were assessed. Validity of the HHT-D and HHT-G was tested via comparison (Pearson r) to commonly used pencil-and-paper based assessments: HHT-D versus the Geriatric Depression Scale (GDS) and HHT-G versus the MMSE. Good test-retest (r = 0.80; p < 0.0001) and acceptable internal consistency reliability (α= 0.73) of the HHT-D were established. Moderate support for the validity of the HHT-D was obtained (r = 0.60 between the HHT-D and GDS; p < 0.0001). Results indicated good test-retest (r = 0.87; p < 0.0001) and acceptable internal consistency reliability (α= 0.70) of the HHT-G. Validity of the HHT-G was supported (r = 0.71 between the HHT-G and MMSE; p < 0.0001). In summary, the HHT-D and HHT-G were found to be reliable and valid computerized assessments to screen for depression and cognitive status, respectively, in an elderly sample.

Retinal oximetry imaging in Alzheimer's disease. - Einarsdottir, Anna Bryndis; Hardarson, Sveinn Hakon; Kristjansdottir, Jona Valgerdur; Bragason, David Thor; Snaedal, Jon; Stefánsson, Einar (J Alzheimers Dis, 2016)
BACKGROUND: Structural and physiological abnormalities have been reported in the retina in Alzheimer's disease (AD). Retinal oximetry detects changes in retinal oxygen metabolism in many eye diseases, where structural changes are seen. OBJECTIVE: To compare oxygen saturation in retinal blood vessels in patients with AD and a healthy cohort. METHODS: Oxygen saturation of hemoglobin was measured in retinal blood vessels, using imaging with spectrophotometric noninvasive retinal oximeter. 18 individuals with mild to moderate dementia of the Alzheimer-type (stage 3-5 according to the Global Deterioration Scale) and 18 healthy subjects underwent retinal oximetry in a case control study. RESULTS: Retinal oxygen saturation in arterioles and venules in patients with moderate AD was significantly elevated compared to healthy individuals. Retinal arterioles have 94.2 ± 5.4% oxygen saturation in moderate AD compared with 90.5 ± 3.1% in healthy subjects (mean ± SD, n = 10, p = 0.028). Retinal venules were 51.9 ± 6.0% saturated in moderate AD compared with 49.7 ± 7.0% in healthy subjects (mean ± SD, n = 10, p = 0.02). CONCLUSION: This is the first study of retinal oxygen metabolism in any central nervous system disease. It discovers abnormalities in retinal oxygen metabolism in AD. The findings are similar to those seen in age-related macular degeneration and diabetic retinopathy. Noninvasive retinal oximetry may offer new insights into pathophysiology of AD. Further studies are needed to confirm and expand these findings.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Hemoglobins; Humans; Male; Middle Aged; Oximetry; Oxygen; Oxygen Consumption; Regional Blood Flow; Retina; Retinal Vessels

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

The Role of Cerebrospinal Fluid Biomarkers in the Evolution of Diagnostic Criteria in Alzheimer's Disease: Shortcomings in Prodromal Diagnosis. - Szalárdy, Levente; Zádori, Dénes; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2016)
The available evidence indicates a high performance of core cerebrospinal fluid (CSF) biomarkers in differentiating between Alzheimer's disease (AD) and other dementias, and suggests that their characteristic alterations can be detected even at the prodromal stage of AD. On this basis, the ability of core CSF biomarkers to identify prodromal AD patients from pre-dementia of all causes can be postulated, a concept that is reflected in recent revisions of AD research criteria and a consensus statement. Following an overview on the role of biomarkers in the evolution of diagnostic criteria of AD in recent decades, this paper provides a critical review of the widely applied CSF biomarker study designs and evaluating approaches that address the ability of core CSF biomarkers to diagnose prodromal AD, with special focus on their potential limitations in terms of clinical interpretation and utility. The findings together raise the question of whether we are indeed able to establish a CSF biomarker-based diagnosis of AD at the prodromal stage.

The Role of Cerebrovascular Disease in Amyloid Deposition. - Noh, Young; Seo, Sang Won; Jeon, Seun; Lee, Jong Min; Kim, Jae Seung; Lee, Jae-Hong; Kim, Jung-Hyun; Kim, Geon Ha; Ye, Byoung Seok; Cho, Hanna; Kim, Hee Jin; Yoon, Cindy W; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Some patients clinically diagnosed with subcortical vascular cognitive impairment (SVCI) have co-morbidity with AD pathology. OBJECTIVE: We investigated topographical differences in amyloid burden between SVCI and Alzheimer's disease type cognitive impairment (ADCI) using [11C] Pittsburgh compound B (PiB) positron emission tomography (PET). The purpose of this study was to investigate the role of cerebrovascular disease (CVD) in amyloid deposition. METHODS: We recruited 44 patients with SVCI and 44 patients with ADCI (amnestic mild cognitive impairment or Alzheimer's disease) with absent or minimal white matter hyperintensities, all with PiB-positive PET scans [PiB+]. As controls, we included 13 participants with normal cognition and PiB-negative scans. We divided the SVCI and ADCI patients into three groups according to global PiB retention ratio of SVCI, and then compared the tertiles in terms of the distribution of PiB retention using statistical parametric mapping analyses. Lobar to global PiB retention ratio and asymmetry indices were also compared between SVCI and ADCI groupsResults: Compared to PiB+ ADCI patients, PiB+ SVCI patients exhibited: 1) increased left-right asymmetry, and increased anterior-posterior difference; and 2) increased PiB retention in the parietal cortex, the occipital cortex and the precuneus-posterior cingulate cortex. In contrast, ADCI patients showed increased PiB retention in the striatum. When stratified by level of PiB retention, each group showed different characteristics. CONCLUSION: Our results showed that the distribution of amyloid deposition differed between patients with PiB+ SVCI and ADCI. These suggest that CVD contribute to and alter the known progression pattern in amyloid deposition in Alzheimer's disease.

Self-Reported Change in Quality of Life with Retirement and Later Cognitive Decline: Prospective Data from the Nurses' Health Study. - Vercambre, Marie-Noël; Okereke, Olivia I; Kawachi, Ichiro; Grodstein, Francine; Kang, Jae H (J Alzheimers Dis, 2016)
To investigate whether a positive transition into retirement may be associated with later cognitive aging, we included a subset of 4,926 Nurses' Health Study participants who retired from work at ages 60-69, then provided a subjective assessment of the change in overall quality of life (QOL) with retirement. Subsequently (range: 1 month to 4.7 years later), when all were aged 70+ years, they completed a baseline telephone cognitive battery evaluating global cognition, episodic memory, and executive function. They had up to three follow-up cognitive assessments. Controlling for various occupational factors before retirement and socioeconomic, lifestyle, and health-related factors as of the baseline cognitive assessment, we used generalized linear models for repeated measures to estimate mean differences in rates of cognitive decline across categories of QOL transition at retirement: "worse", "same", or "better". Over a median 6 years of follow-up, the global cognitive score change was -0.123 on average. Compared with women who reported no change in QOL at retirement (31%), women who reported improvement (61%) showed a significantly slower rate of cognitive decline (difference = +0.011 95% CI = 0.004, 0.019). This mean difference was equivalent to that observed between women who were 2 years apart in age. No significant differences in cognitive decline rates were observed for the women who reported worsened QOL (8%). Secondary analyses to address possible reverse causation showed robust associations. A positive transition into retirement was associated with better maintenance of cognitive function over time in aging women. These findings need to be replicated in other populations.

Serotonin 2A Receptor Inverse Agonist as a Treatment for Parkinson's Disease Psychosis: A Systematic Review and Meta-analysis of Serotonin 2A Receptor Negative Modulators. - Yasue, Ichiro; Matsunaga, Shinji; Kishi, Taro; Fujita, Kiyoshi; Iwata, Nakao (J Alzheimers Dis, 2016)
BACKGROUND: There is uncertainty about the efficacy and tolerability of serotonin 2A (5-HT2A) receptor negative modulators for Parkinson's disease psychosis (PDP). OBJECTIVE: This is the first meta-analysis of randomized placebo-controlled trials (RCTs) testing negative modulators of the 5-HT2A receptor as a treatment for PDP. METHODS: The primary outcome was the Scale for Assessment of Positive Symptoms (SAPS)-hallucinations (H) and -delusions (D) scores (SAPS-H+D). Other outcome measures were SAPS-H, SAPS-D, the Unified Parkinson's Disease Rating Scale Part II and III (UPDRS-II+III), discontinuation rates, and individual adverse events. RESULTS: Four RCTs were identified that met inclusion criteria, all assessing the 5-HT2A inverse agonist pimavanserin (including 417 drug-treated and 263 placebo-treated PDP patients). Pimavanserin significantly decreased SAPS-H+D scores compared to placebo [weighted mean differences (WMD) = -2.26, 95% confidence interval (95% CI) = -3.86 to -0.67, p = 0.005, I2 = 30% , N = 4 studies, n = 502 patients]. Moreover, pimavanserin was superior to placebo for reducing SAPS-H (WMD = -2.15, 95% CI = -3.45 to -0.86, p = 0.001, I2 = 0% , N = 2, n = 237) and SAPS-D scores (WMD = -1.32, 95% CI = -2.32 to -0.32, p = 0.010, I2 = 0% , N = 2, n = 237). Pimavanserin was associated with less orthostatic hypotension than placebo (risk ratio = 0.33, 95% CI = 0.15-0.75, p = 0.008, I2 = 0% , number needed to harm = 17, p = 0.01, N = 3, n = 476). There were no significant differences in rates of all-cause discontinuation, adverse events, and death, UPDRS-II+III scores, and incidences of individual adverse events (other than orthostatic hypotension) between pimavanserin and placebo groups. CONCLUSIONS: Pooled RCT results suggest that pimavanserin is beneficial for the treatment of PDP and is well tolerated. We did not identify other negative modulators of the 5-HT2A receptor for the treatment of PDP.
Keywords: Antiparkinson Agents; Humans; Parkinson Disease; Randomized Controlled Trials as Topic; Receptor, Serotonin, 5-HT2A; Serotonin 5-HT2 Receptor Agonists

Serum Adiponectin Levels, Neuroimaging, and Cognition in the Mayo Clinic Study of Aging. - Wennberg, Alexandra M V; Gustafson, Deborah; Hagen, Clinton E; Roberts, Rosebud O; Knopman, David; Jack, Clifford; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2016)
BACKGROUND: Adiponectin, a protein involved in inflammatory pathways, may impact the development and progression of Alzheimer's disease (AD). Adiponectin levels have been associated with mild cognitive impairment (MCI) and AD; however, its association with Alzheimer-associated neuroimaging and cognitive outcomes is unknown. OBJECTIVE: Determine the cross-sectional association between plasma adiponectin and neuroimaging and cognitive outcomes in an older population-based sample. METHODS: Multivariable adjusted regression models were used to investigate the association between plasma adiponectin and hippocampal volume (HVa), PiB-PET, FDG PET, cortical thickness, MCI diagnosis, and neuropsychological test performance. Analyses included 535 non-demented participants aged 70 and older enrolled in the Mayo Clinic Study of Aging. RESULTS: Women had higher adiponectin than men (12,631 ng/mL versus 8,908 ng/mL, p < 0.001). Among women, higher adiponectin was associated with smaller HVa (B = -0.595; 95% CI -1.19, -0.005), poorer performance in language (B = -0.676; 95% CI -1.23, -0.121), and global cognition (B = -0.459; 95% CI -0.915, -0.002), and greater odds of a MCI diagnosis (OR = 6.23; 95% CI 1.20, 32.43). In analyses stratified by sex and elevated amyloid (PiB-PET SUVR >1.4), among women with elevated amyloid, higher adiponectin was associated with smaller HVa (B = -0.723; 95% CI -1.43, -0.014), poorer performance in memory (B = -1.02; 95% CI -1.73, -0.312), language (B = -0.896; 95% CI -1.58, -0.212), global cognition (B = -0.650; 95% CI -1.18, -0.116), and greater odds of MCI (OR = 19.34; 95% CI 2.72, 137.34). CONCLUSION: Higher plasma adiponectin was associated with neuroimaging and cognitive outcomes among women. Longitudinal analyses are necessary to determine whether higher adiponectin predicts neurodegeneration and cognitive decline.

Sideritis spp. Extracts Enhance Memory and Learning in Alzheimer's β-Amyloidosis Mouse Models and Aged C57Bl/6 Mice. - Hofrichter, Jacqueline; Krohn, Markus; Schumacher, Toni; Lange, Cathleen; Feistel, Bjöorn; Walbroel, Bernd; Pahnke, Jens (J Alzheimers Dis, 2016)
Nowadays, Alzheimer's disease is the most prevalent epiphenomenon of the aging population. Although soluble amyloid-β (Aβ) species (monomers, oligomers) are recognized triggers of the disease, no therapeutic approach is able to stop it. Herbal medicines are used to treat different diseases in many regions of the world. On the Balkan Peninsula, at the eastern Mediterranean Sea, and adjacent regions, Sideritis species are used as traditional medicine to prevent age-related problems in elderly. To evaluate this traditional knowledge in controlled experiments, we tested extracts of two commonly used Sideritis species, Sideritis euboea and Sideritis scardica, with regard to their effects on cognition in APP-transgenic and aged, non-transgenic C57Bl/6 mice. Additionally, histomorphological and biochemical changes associated with Aβ deposition and treatment were assessed. We found that daily oral treatment with Sideritis spp. extracts highly enhanced cognition in aged, non-transgenic as well as in APP-transgenic mice, an effect that was even more pronounced when extracts of both species were applied in combination. The treatment strongly reduced Aβ42 load in APP-transgenic mice, accompanied by increased phagocytic activity of microglia, and increased expression of the α-secretase ADAM10. Moreover, the treatment was able to fully rescue neuronal loss of APP-transgenic mice to normal levels as seen in non-transgenic controls. Having the traditional knowledge in mind, our results imply that treatment with Sideritis spp. extracts might be a potent, well-tolerated option for treating symptoms of cognitive impairment in elderly and with regard to Alzheimer's disease by affecting its most prominent hallmarks: Aβ pathology and cognitive decline.

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species. - Tiiman, Ann; Luo, Jinghui; Wallin, Cecilia; Olsson, Lisa; Lindgren, Joel; Jarvet, Jϋri; Per, Roos; Sholts, Sabrina B; Rahimipour, Shai; Abrahams, Jan Pieter; Karlström, Amelie Eriksson; Gräslund, Astrid; et al. (J Alzheimers Dis, 2016)
Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environment. Here, we study Cu(II) and Zn(II) interactions with Aβ bound to SDS micelles or to engineered aggregation-inhibiting molecules (the cyclic peptide CP-2 and the ZAβ3(12-58)Y18L Affibody molecule). In all studied systems the Aβ N-terminal segment was found to be unbound, unstructured, and free to bind metal ions. In SDS micelles, Aβ was found to bind Cu(II) and Zn(II) with the same ligands and the same KD as in aqueous solution. ROS was generated in all Cu(II)/Aβ complexes. These results indicate that binding of Aβ to membranes, drugs, and other entities that do not interact with the Aβ N-terminal part, appears not to compromise the N-terminal segment's ability to bind metal ions, nor impede the capacity of N-terminally bound Cu(II) to generate ROS.

Specific Triazine Herbicides Induce Amyloid-β42 Production. - Portelius, Erik; Durieu, Emilie; Bodin, Marion; Cam, Morgane; Pannee, Josef; Leuxe, Charlotte; Mabondzo, Aloϊse; Oumata, Nassima; Galons, Hervé; Lee, Jung Yeol; Chang, Young-Tae; Stϋber, Kathrin; et al. (J Alzheimers Dis, 2016)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by secretases leads to extracellular release of amyloid-β (Aβ) peptides. Increased production of Aβ42 over Aβ40 and aggregation into oligomers and plaques constitute an Alzheimer's disease (AD) hallmark. Identifying products of the 'human chemical exposome' (HCE) able to induce Aβ42 production may be a key to understanding some of the initiating causes of AD and to generate non-genetic, chemically-induced AD animal models. A cell model was used to screen HCE libraries for Aβ42 inducers. Out of 3500+ compounds, six triazine herbicides were found that induced a β- and γ-secretases-dependent, 2-10 fold increase in the production of extracellular Aβ42 in various cell lines, primary neuronal cells, and neurons differentiated from human-induced pluripotent stem cells (iPSCs). Immunoprecipitation/mass spectrometry analyses show enhanced production of Aβ peptides cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and lower, a characteristic of AD. Neurons derived from iPSCs obtained from a familial AD (FAD) patient (AβPP K724N) produced more Aβ42 versus Aβ40 than neurons derived from healthy controls iPSCs (AβPP WT). Triazines enhanced Aβ42 production in both control and AD iPSCs-derived neurons. Triazines also shifted the cleavage pattern of alcadeinα, another γ-secretase substrate, suggesting a direct effect of triazines on γ-secretase activity. In conclusion, several widely used triazines enhance the production of toxic, aggregation prone Aβ42/Aβ43 amyloids, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in late-onset AD.

Stem Cell Therapy for Alzheimer's Disease: A Review of Recent Clinical Trials. - Kang, Jae Myeong; Yeon, Byeong Kil; Cho, Seong-Jin; Suh, Yoo-Hun (J Alzheimers Dis, 2016)
Stem cell therapy has been noted to be a disease-modifying treatment for Alzheimer's disease (AD). After the failure to develop new drugs for AD, the number of studies on stem cells, such as mesenchymal stem cells (MSCs) and neural stem cells (NSCs), has increased from the early 2000 s. Issues pertaining to stem cells have been investigated in many animal studies in terms of stem cell origin, differentiation potency, method of culture, tumor formation, injection route, and mobility. Since 2010, mainly in East Asia, researchers began clinical trials investigating the use of stem cells for AD. Two phase I trials on moderate AD have been completed; though they revealed no severe acute or long-term side effects, no significant clinical efficacy was observed. Several studies, which involve more sophisticated study designs using different injection routes, well-established scales, and biomarkers such as amyloid positron emission tomography, are planned for mild to moderate AD patients. Here, we review the concept of stem cell therapy for AD and the progress of recent clinical trials.

Stimulating the Activity of Amyloid-Beta Degrading Enzymes: A Novel Approach for the Therapeutic Manipulation of Amyloid-Beta Levels. - Kuruppu, Sanjaya; Rajapakse, Niwanthi W; Spicer, Alexander J; Parkington, Helena C; Smith, A Ian (J Alzheimers Dis, 2016)
Alzheimer's disease is a debilitating neurological disease placing significant burden on health care budgets around the world. It is widely believed that accumulation of amyloid-beta (Aβ) in the brain is a key event that initiates neurodegeneration, thus the clearance of Aβ from brain could be a key therapeutic strategy. Aβ exists in an equilibrium in healthy individuals, and recent research would suggest that dysfunction in the clearance pathways is the driving force behind its accumulation. One mechanism of clearance is proteolytic degradation by enzymes, and increasing the expression of these enzymes in animal models of Alzheimer's disease has indeed shown promising results. This approach could be challenging to translate into the clinic given the likely need for genetic manipulation. We hypothesize that stimulating the activity of these enzymes (as opposed to increasing expression) through pharmacological agents will enhance degradation or at least prevent amyloid deposition, and is therefore another potentially novel avenue to manipulate Aβ levels for therapeutic purposes. We discuss the recent research supporting this hypothesis as well as possible drawbacks to this approach.

Strategies for improving memory: a randomized trial of memory groups for older people, including those with mild cognitive impairment. - Kinsella, Glynda J; Ames, David; Storey, Elsdon; Ong, Ben; Pike, Kerryn E; Saling, Michael M; Clare, Linda; Mullaly, Elizabeth; Rand, Elizabeth (J Alzheimers Dis, 2016)
BACKGROUND: Governments are promoting the importance of maintaining cognitive health into older age to minimize risk of cognitive decline and dementia. Older people with amnestic mild cognitive impairment (aMCI) are particularly vulnerable to memory challenges in daily activities and are seeking ways to maintain independent living. OBJECTIVE: To evaluate the effectiveness of memory groups for improving memory strategies and memory ability of older people, especially those with aMCI. METHODS: 113 healthy older adults (HOA) and 106 adults with aMCI were randomized to a six-week memory group or a waitlist control condition. Outcome was evaluated through knowledge and use of memory strategies, memory ability (self-report and neuropsychological tests), and wellbeing. Assessments included a six-month follow-up. RESULTS: Using intention to treat analyses, there were intervention effects for HOA and aMCI groups in strategy knowledge (HOA: η2= 0.20; aMCI: η2= 0.06), strategy use (HOA: η2= 0.18; aMCI: η2= 0.08), and wellbeing (HOA: η2= 0.11; aMCI: η2= 0.05). There were also intervention effects in the HOA group, but not the aMCI group, in self-reported memory ability (η2= 0.06) and prospective memory tests (η2= 0.02). By six-month follow-up, gains were found on most HOA outcomes. In the aMCI group gains were found in strategy use, and by this stage, gains in prospective memory were also found. CONCLUSION: Memory groups can engage older people in techniques for maintaining cognitive health and improve memory performance, but more modest benefits are seen for older adults with aMCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cross-Over Studies; Female; Humans; Male; Memory, Episodic; Neuropsychological Tests; Self Report

Stratification by Genetic and Demographic Characteristics Improves Diagnostic Accuracy of Cerebrospinal Fluid Biomarkers in Rapidly Progressive Dementia. - Karch, André; Llorens, Franc; Schmitz, Matthias; Arora, Amandeep Singh; Zafar, Saima; Lange, Peter; Schmidt, Christian; Zerr, Inga (J Alzheimers Dis, 2016)
BACKGROUND: Cerebrospinal fluid (CSF) biomarkers are routinely used for the differential diagnosis of rapidly progressive dementia, but are also affected by patients' characteristics. OBJECTIVE: To assess if stratification by age, sex, and genetic risk factors improves the accuracy of cerebrospinal fluid (CSF) biomarkers in patients with rapidly progressive dementia. METHODS: 1,538 individuals with sporadic Creutzfeldt-Jakob disease (CJD), 173 with classic Alzheimer's disease (cAD), 37 with rapidly progressive Alzheimer's disease (rpAD), and 589 without signs of dementia were included in this retrospective diagnostic study. The effect of age, sex, PRNP codon 129, and APOE genotype on CSF levels of tau, p-tau, Aβ1-42, and Aβ1-40 values measured at time of diagnostic work-up was assessed. RESULTS: Tau was a better marker for the differentiation of CJD and rpAD in older (AUC:0.97; 95% CI:0.96-1.00) than in younger (AUC:0.91; 95% CI:0.87-0.94) patients as tau levels increased with age in CJD patients, but not in rpAD patients. PRNP codon 129 and APOE genotype had complex effects on biomarkers in all diseases, making stratification by genotype a powerful tool. In females (AUC:0.78; 95% CI:0.65-0.91) and patients older than 70 (AUC:0.78; 95% CI:0.62-0.93), tau was able to differentiate with moderate accuracy between cAD and rpAD patients. CONCLUSION: Implementation of stratum-specific reference ranges improves the diagnostic accuracy of CSF biomarkers for the differential diagnosis of rapidly progressive dementia. Diagnostic criteria developed for this setting have to take this into account.

STX, a Novel Membrane Estrogen Receptor Ligand, Protects Against Amyloid-β Toxicity. - Gray, Nora E; Zweig, Jonathan A; Kawamoto, Colleen; Quinn, Joseph F; Copenhaver, Philip F (J Alzheimers Dis, 2016)
Because STX is a selective ligand for membrane estrogen receptors, it may be able to confer the beneficial effects of estrogen without eliciting the deleterious side effects associated with activation of the nuclear estrogen receptors. This study evaluates the neuroprotective properties of STX in the context of amyloid-β (Aβ) exposure. MC65 and SH-SY5Y neuroblastoma cell lines, as well as primary hippocampal neurons from wild type (WT) and Tg2576 mice, were used to investigate the ability of STX to attenuate cell death, mitochondrial dysfunction, dendritic simplification, and synaptic loss induced by Aβ. STX prevented Aβ-induced cell death in both neuroblastoma cell lines; it also normalized the decrease in ATP and mitochondrial gene expression caused by Aβ in these cells. Notably, STX also increased ATP content and mitochondrial gene expression in control neuroblastoma cells (in the absence of Aβ). Likewise in primary neurons, STX increased ATP levels and mitochondrial gene expression in both genotypes. In addition, STX treatment enhanced dendritic arborization and spine densities in WT neurons and prevented the diminished outgrowth of dendrites caused by Aβ exposure in Tg2576 neurons. These data suggest that STX can act as an effective neuroprotective agent in the context of Aβ toxicity, improving mitochondrial function as well as dendritic growth and synaptic differentiation. In addition, since STX also improved these endpoints in the absence of Aβ, this compound may have broader therapeutic value beyond Alzheimer's disease.
Keywords: Acrylamides; Adenosine Triphosphate; Amyloid beta-Peptides; Animals; Cell Death; Cell Line, Tumor; Drug Evaluation, Preclinical; Estrogen Receptor Modulators; Genes, Mitochondrial; Hippocampus; Humans; Mice, Transgenic; Mitochondria; Neurons; Neuroprotective Agents

Tau Accumulation in Primary Motor Cortex of Variant Alzheimer's Disease with Spastic Paraparesis. - Lyoo, Chul Hyoung; Cho, Hanna; Choi, Jae Yong; Hwang, Mi Song; Hong, Sang Kyoon; Kim, Yun Joong; Ryu, Young Hoon; Lee, Myung Sik (J Alzheimers Dis, 2016)
We studied topographic distribution of tau and amyloid-β in a patient with variant Alzheimer's disease with spastic paraparesis (VarAD) by comparing AD patients. The proband developed progressive memory impairment, dysarthria, and spastic paraparesis at age 23. Heterozygous missense mutation (L166P) was found in exon 6 of presenilin-1 gene. The proband showed prominently increased amyloid binding in striatum and cerebellum and asymmetrical tau binding in the primary sensorimotor cortex contralateral to the side more affected by spasticity. We suspect that upper motor neuron dysfunctions may be attributed to excessive abnormal tau accumulation rather than amyloid-β in the primary motor cortex.
Keywords: Adult; Aged; Alzheimer Disease; Aniline Compounds; Brain Mapping; Carbolines; Female; Humans; Male; Motor Cortex; Mutation, Missense; Paraparesis, Spastic; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; Stilbenes; tau Proteins

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration. - Yu, Rosa; Deochand, Chetram; Krotow, Alexander; Leão, Raiane; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis studies showed that smokers have increased risk for developing Alzheimer's disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. OBJECTIVE: The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. METHODS: Adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). The frontal lobes were used for histology and qRT-PCR analysis. RESULTS: Luxol fast blue, Hematoxylin and Eosin stained histological sections revealed CS-associated reductions in myelin staining intensity and narrowing of the corpus callosum. CS exposures broadly decreased mRNA levels of immature and mature oligodendrocyte myelin-associated, neuroglial, and oligodendrocyte-related transcription factors. These effects were more prominent in the CS8 compared with CS4 group, suggesting that molecular abnormalities linked to white matter atrophy and myelin loss worsen with duration of CS exposure. Recovery normalized or upregulated less than 25% of the suppressed genes; in most cases, inhibition of gene expression was either sustained or exacerbated. CONCLUSION: CS exposures broadly inhibit expression of genes needed for myelin synthesis and maintenance. These adverse effects often were not reversed by short-term CS withdrawal. The results support the hypothesis that smoking contributes to white matter degeneration, and therefore could be a key risk factor for a number of neurodegenerative diseases, including AD.
Keywords: 2',3'-Cyclic-Nucleotide Phosphodiesterases; AC133 Antigen; Animals; Antigens, CD; Brain; Disease Models, Animal; Galactosylceramides; Gene Expression Regulation; Glycoproteins; Leukoencephalopathies; Male; Mice; Nerve Degeneration; Nerve Tissue Proteins; Neuroglia; Neurons; Oligodendroglia; Papain; Peptides; Smoking; Tobacco; Transcription Factors

Topographical APOE ɛ4 Genotype Influence on Cerebral Metabolism in the Continuum of Alzheimer's Disease: Amyloid Burden Adjusted Analysis. - Seo, Eun Hyun; Kim, Sang Hoon; Park, Sang Hag; Kang, Seong-Ho; Choo, Il Han (J Alzheimers Dis, 2016)
BACKGROUND: APOE ɛ4 contributes to Alzheimer's disease (AD) pathogenesis by amyloid-beta (Aβ)-dependent and Aβ-independent processes. OBJECTIVE: We investigated the APOE ɛ4 influence on regional cerebral glucose metabolism (rCMglc) in the continuum of AD after Aβ adjustment. METHODS: We included 318 cognitively normal (CN) elderly, 498 mild cognitive impairment (MCI), and 178 AD from the Alzheimer's Disease Neuroimaging Initiative database. They had [18F] florbetapir positron emission tomography (PET) and [18F] fluorodeoxyglucose (FDG)-PET conducted within 3 months of a clinical and cognitive assessment visit and APOE genotype. At first, the rCMglc differences between APOE ɛ4 carriers (ɛ4+) and non-carriers (ɛ4-) were estimated on a voxel-based analysis using a 'two-sample t-test' design. In the second analysis, Aβ was added as covariate. RESULTS: In CN, ɛ4+ showed reduced rCMglc compared to ɛ4-in the bilateral frontal, temporal, and the left parietal regions. In MCI, ɛ4+ showed reduced rCMglc compared to ɛ4- in the bilateral posterior parietal, temporal, and left frontal regions. In AD, ɛ4+ showed reduced rCMglc in the left hippocampus, right insular, and right temporal gyrus. However, after Aβ adjustment, the significant differences in the temporal regions were absent in CN and MCI, and none of the areas detected as significant in the first analysis were statistically significant in AD. CONCLUSIONS: Our study demonstrated that Aβ-independent APOE ɛ4 influence on rCMglc is limited to the parietal and frontal, but not temporal lobes. These results suggest that APOE ɛ4 may predispose for regional vulnerability according to Aβ-independent and Aβ-dependent processes.

Topographical Information-Based High-Order Functional Connectivity and Its Application in Abnormality Detection for Mild Cognitive Impairment. - Zhang, Han; Chen, Xiaobo; Shi, Feng; Li, Gang; Kim, Minjeong; Giannakopoulos, Panteleimon; Haller, Sven; Shen, Dinggang (J Alzheimers Dis, 2016)
Temporal synchronization-based functional connectivity (FC) has long been used by the neuroscience community. However, topographical FC information may provide additional information to characterize the advanced relationship between two brain regions. Accordingly, we proposed a novel method, namely high-order functional connectivity (HOFC), to capture this second-level relationship using inter-regional resemblance of the FC topographical profiles. Specifically, HOFC first calculates an FC profile for each brain region, notably between the given brain region and other brain regions. Based on these FC profiles, a second layer of correlations is computed between all pairs of brain regions (i.e., correlation's correlation). On this basis, we generated an HOFC network, where "high-order" network properties were computed. We found that HOFC was discordant with the traditional FC in several links, indicating additional information being revealed by the new metrics. We applied HOFC to identify biomarkers for early detection of Alzheimer's disease by comparing 77 mild cognitive impairment patients with 89 healthy individuals (control group). Sensitivity in detection of group difference was consistently improved by ∼25% using HOFC compared to using FC. An HOFC network analysis also provided complementary information to an FC network analysis. For example, HOFC between olfactory and orbitofrontal cortices was found significantly reduced in patients, besides extensive alterations in HOFC network properties. In conclusion, our results showed promise in using HOFC to comprehensively map the human brain connectome.

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Transcriptional Analysis of Blood Lymphocytes and Skin Fibroblasts, Keratinocytes, and Endothelial Cells as a Potential Biomarker for Alzheimer's Disease. - Mukhamedyarov, Marat A; Rizvanov, Albert A; Yakupov, Eduard Z; Zefirov, Andrey L; Kiyasov, Andrey P; Reis, Helton J; Teixeira, Antônio L; Vieira, Luciene B; Lima, Luciana M; Salafutdinov, Ilnur I; Petukhova, Elena O; Khaiboullina, Svetlana F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating and progressive form of dementia that is typically associated with a build-up of amyloid-β plaques and hyperphosphorylated and misfolded tau protein in the brain. Presently, there is no single test that confirms AD; therefore, a definitive diagnosis is only made after a comprehensive medical evaluation, which includes medical history, cognitive tests, and a neurological examination and/or brain imaging. Additionally, the protracted prodromal phase of the disease makes selection of control subjects for clinical trials challenging. In this study we have utilized a gene-expression array to screen blood and skin punch biopsy (fibroblasts, keratinocytes, and endothelial cells) for transcriptional differences that may lead to a greater understanding of AD as well as identify potential biomarkers. Our analysis identified 129 differentially expressed genes from blood of dementia cases when compared to healthy individuals, and four differentially expressed punch biopsy genes between AD subjects and controls. Additionally, we identified a set of genes in both tissue compartments that showed transcriptional variation in AD but were largely stable in controls. The translational products of these variable genes are involved in the maintenance of the Golgi structure, regulation of lipid metabolism, DNA repair, and chromatin remodeling. Our analysis potentially identifies specific genes in both tissue compartments that may ultimately lead to useful biomarkers and may provide new insight into the pathophysiology of AD.

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease. - Lee, Geon-Hwi; Jang, Byungki; Choi, Hong-Seok; Kim, Hee-Jun; Park, Jeong-Ho; Jeon, Yong-Chul; Carp, Richard I; Kim, Yong-Sun; Choi, Eun-Kyoung (J Alzheimers Dis, 2016)
Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we investigate the role of Cx43 in the pathogenesis of prion diseases. Upregulated Cx43 expression, which was dependent on c-Jun N-Terminal Kinase (JNK)/c-Jun signaling cascades, was found in prion-affected brain tissues and hippocampal neuronal cells. Scrapie infection-induced Cx43 formed aggregated plaques within the cytoplasmic compartments at the cell-cell interfaces. The ethidium bromide (EtBr) uptake assay and scrape-loading dye transfer assay demonstrated that increased Cx43 has functional consequences for the activity of Cx43 hemichannels. Interestingly, blockade of PrPSc accumulation reduced Cx43 expression through the inhibition of JNK signaling, indicating that PrPSc accumulation may be directly involved in JNK activation-mediated Cx43 upregulation. Overall, our findings describe a scrapie infection-mediated novel regulatory signaling pathway of Cx43 expression and may suggest a role for Cx43 in the pathogenesis of prion diseases.
Keywords: Animals; Brain; Cell Membrane; Cells, Cultured; Connexin 43; Disease Models, Animal; JNK Mitogen-Activated Protein Kinases; MAP Kinase Signaling System; Mesocricetus; Mice, Inbred C57BL; Mice, Knockout; PrPSc Proteins; RNA, Messenger; Scrapie; Up-Regulation

Validation of a Commercial Chemiluminescence Immunoassay for the Simultaneous Measurement of Three Different Amyloid-β Peptides in Human Cerebrospinal Fluid and Application to a Clinical Cohort. - Klafki, Hans-W; Hafermann, Henning; Bauer, Chris; Haussmann, Ute; Kraus, Inga; Schuchhardt, Johannes; Muck, Stephan; Scherbaum, Norbert; Wiltfang, Jens (J Alzheimers Dis, 2016)
A comprehensive assay validation campaign of a commercially available chemiluminescence multiplex immunoassay for the simultaneous measurement of the amyloid-β peptides Aβ38, Aβ40, and Aβ42 in human cerebrospinal fluid (CSF) is presented. The assay quality parameters we addressed included impact of sample dilution, parallelism, lower limits of detection, lower limits of quantification, intra- and inter-assay repeatability, analytical spike recoveries, and between laboratory reproducibility of the measurements. The assay performed well in our hands and fulfilled a number of predefined acceptance criteria. The CSF levels of Aβ40 and Aβ42 determined in a clinical cohort (n = 203) were statistically significantly correlated with available ELISA data of Aβ1-40 (n = 158) and Aβ1-42 (n = 179) from a different laboratory. However, Bland-Altman method comparison indicated systematic differences between the assays. The data presented here furthermore indicate that the CSF concentration of Aβ40 can surrogate total CSF Aβ and support the hypothesis that the Aβ42/Aβ40 ratio outperforms CSF Aβ42 alone as a biomarker for Alzheimer's disease due to a normalization to total Aβ levels.

Validation of microRNAs in Cerebrospinal Fluid as Biomarkers for Different Forms of Dementia in a Multicenter Study. - Müller, Mareike; Kuiperij, H Bea; Versleijen, Alexandra A M; Chiasserini, Davide; Farotti, Lucia; Baschieri, Francesca; Parnetti, Lucilla; Struyfs, Hanne; De Roeck, Naomi; Luyckx, Jill; Engelborghs, Sebastiaan; Claassen, Jurgen A; et al. (J Alzheimers Dis, 2016)
MicroRNAs (miRNAs) regulate translational inhibition of proteins, but are also detected in body fluids, including cerebrospinal fluid (CSF), where they may serve as disease-specific biomarkers. Previously, we showed differential expression of miR-146a, miR-29a, and miR-125b in the CSF of Alzheimer's disease (AD) patients versus controls. In this study, we aim to confirm these findings by using larger, independent sample cohorts of AD patients and controls from three different centers. Furthermore, we aim to identify confounding factors that possibly arise using such a multicenter approach. The study was extended by including patients diagnosed with mild cognitive impairment due to AD, frontotemporal dementia and dementia with Lewy bodies. Previous results of decreased miR-146a levels in AD patients compared to controls were confirmed in one center. When samples from all three centers were combined, several confounding factors were identified. After controlling for these factors, we did not identify differences in miRNA levels between the different groups. However, we provide suggestions to circumvent various pitfalls when measuring miRNAs in CSF to improve future studies.

A Validation Study of Vascular Cognitive Impairment Genetics Meta-Analysis Findings in an Independent Collaborative Cohort. - Skrobot, Olivia Anna; McKnight, Amy Jayne; Passmore, Peter Anthony; Seripa, Davide; Mecocci, Patrizia; Panza, Francesco; Kalaria, Rajesh; Wilcock, Gordon; Munafò, Marcus; Erkinjuntti, Timo; Karhunen, Pekka; Pessi, Tanja; et al. (J Alzheimers Dis, 2016)
Vascular cognitive impairment (VCI), including its severe form, vascular dementia (VaD), is the second most common form of dementia. The genetic etiology of sporadic VCI remains largely unknown. We previously conducted a systematic review and meta-analysis of all published genetic association studies of sporadic VCI prior to 6 July 2012, which demonstrated that APOE (ɛ4, ɛ2) and MTHFR (rs1801133) variants were associated with susceptibility for VCI. De novo genotyping was conducted in a new independent relatively large collaborative European cohort of VaD (nmax = 549) and elderly non-demented samples (nmax = 552). Where available, genotype data derived from Illumina's 610-quad array for 1210 GERAD1 control samples were also included in analyses of genes examined. Associations were tested using the Cochran-Armitage trend test: MTHFR rs1801133 (OR = 1.36, 95% CI 1.16-1.58, p = <0.0001), APOE rs7412 (OR = 0.62, 95% CI 0.42-0.90, p = 0.01), and APOE rs429358 (OR = 1.59, 95% CI 1.17-2.16, p = 0.003). Association was also observed with APOE epsilon alleles; ɛ4 (OR = 1.85, 95% CI 1.35-2.52, p = <0.0001) and ɛ2 (OR = 0.67, 95% CI 0.46-0.98, p = 0.03). Logistic regression and Bonferroni correction in a subgroup of the cohort adjusted for gender, age, and population maintained the association of APOE rs429358 and ɛ4 allele.

Vascular Contributions in Alzheimer's Disease-Related Neuropathological Changes: First Autopsy Evidence from a South Asian Aging Population. - Wijesinghe, Printha; Shankar, S K; Yasha, T C; Gorrie, Catherine; Amaratunga, Dhammika; Hulathduwa, Sanjayah; Kumara, K Sunil; Samarasinghe, Kamani; Suh, Yoo-Hun; Steinbusch, Harry W M; De Silva, K Ranil D (J Alzheimers Dis, 2016)
BACKGROUND: Evidence from various consortia on vascular contributions has been inconsistent in determining the etiology of sporadic Alzheimer's disease (AD). OBJECTIVE: To investigate vascular risk factors and cerebrovascular pathologies associated in manifestation of AD-related neuropathological changes of an elderly population. METHODS: Postmortem brain samples from 76 elderly subjects (≥50 years) were used to study genetic polymorphisms, intracranial atherosclerosis of the circle of Willis (IASCW), and microscopic infarcts in deep white matters. From this cohort, 50 brains (≥60 years) were subjected to neuropathological diagnosis using immunohistopathological techniques. RESULTS: Besides the association with age, the apolipoprotein E ɛ4 allele was significantly and strongly associated with Thal amyloid-β phases ≥1 [odds ratio (OR) = 6.76, 95% confidence interval (CI) 1.37-33.45] and inversely with Braak neurofibrillary tangle (NFT) stages ≥III (0.02, 0.0-0.47). Illiterates showed a significant positive association for Braak NFT stages ≥IV (14.62, 1.21-176.73) and a significant negative association for microscopic infarcts (0.15, 0.03-0.71) in deep white matters. With respect to cerebrovascular pathologies, cerebral small vessel lesions (white matter hyperintensities and cerebral amyloid angiopathy) showed a higher degree of associations among them and with AD-related neuropathological changes (p < 0.05) compared to large vessel pathology (IASCW), which showed a significant association only with Braak NFT stages ≥I (p = 0.050). CONCLUSION: These findings suggest that besides age, education, and genetic factors, other vascular risk factors were not associated with AD-related neuropathological changes and urge prompt actions be taken against cerebral small vessel diseases since evidence for effective prevention is still lacking.

Ventilatory Response to Hypercapnia Predicts Dementia with Lewy Bodies in Late-Onset Major Depressive Disorder. - Takahashi, Sho; Mizukami, Katsuyoshi; Arai, Tetsuaki; Ogawa, Ryoko; Kikuchi, Norihiro; Hattori, Satoshi; Darby, David; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: Studies have shown that developing major depressive disorder (MDD) at 50 years of age or older can predict dementia. Depression is particularly common in dementia with Lewy bodies (DLB), and occasionally occurs before the onset of extrapyramidal symptoms. Moreover, systemic autonomic dysfunction, including an abnormal ventilatory response to hypercapnia (VRH), is common in patients with DLB. OBJECTIVE: Here, we aimed to determine whether the VRH is useful for distinguishing depression that is predictive of DLB from other types of MDD. METHODS: Participants were 35 consecutive patients with first onset MDD at 50 years or older with bradykinesia. After diagnosing the clinical subtype of MDD according to DSM-IV criteria, each subject underwent a battery of psychological tests, autonomic examinations including VRH, brain magnetic resonance imaging, and 123I-meta-iodobenzylguanidine scintigraphy. RESULTS: Longitudinal follow-up showed that all 18 patients with abnormal VRH results developed DLB, whereas none of the 17 patients with normal VRH results converted to DLB within the study period (sensitivity: 100% , specificity: 100%). Additionally, over half of the DLB converters showed abnormalities on other autonomic examinations. For converters, the most common MDD subtype had psychotic and melancholic features simultaneously. The frequency of hypersensitivity to psychotropics was higher in converters than it was in non-converters. CONCLUSION: In the present study, patients with abnormal VRH results were very likely to develop DLB. Thus, for patients with late-onset MDD accompanied by bradykinesia, the VRH in combination with the clinical subtype of MDD or hypersensitivity to psychotropics may be useful for diagnosing prodromal DLB.
Keywords: 3-Iodobenzylguanidine; Aged; Aged, 80 and over; Depressive Disorder, Major; Follow-Up Studies; Heart Rate; Humans; Hypercapnia; Hypotension, Orthostatic; Kaplan-Meier Estimate; Lewy Body Disease; Middle Aged; Partial Pressure; Psychiatric Status Rating Scales; Retrospective Studies; Ventilators, Mechanical

Vitamin D and Memory Decline: Two Population-Based Prospective Studies. - Kuźma, Elżbieta; Soni, Maya; Littlejohns, Thomas J; Ranson, Janice M; van Schoor, Natasja M; Deeg, Dorly J H; Comijs, Hannie; Chaves, Paulo H M; Kestenbaum, Bryan R; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vitamin D deficiency has been linked with dementia risk, cognitive decline, and executive dysfunction. However, the association with memory remains largely unknown. OBJECTIVE: To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. METHODS: We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid vitamin D measurements, and follow-up memory assessments. The Benton Visual Retention Test (in the CHS) and Rey's Auditory Verbal Learning Test (in the LASA) were used to assess visual and verbal memory, respectively. RESULTS: In the CHS, those moderately and severely deficient in serum 25(OH)D changed -0.03 SD (95% CI: -0.06 to 0.01) and -0.10 SD (95% CI: -0.19 to -0.02) per year respectively in visual memory compared to those sufficient (p = 0.02). In the LASA, moderate and severe deficiency in serum 25(OH)D was associated with a mean change of 0.01 SD (95% CI: -0.01 to 0.02) and -0.01 SD (95% CI: -0.04 to 0.02) per year respectively in verbal memory compared to sufficiency (p = 0.34). CONCLUSIONS: Our findings suggest an association between severe vitamin D deficiency and visual memory decline but no association with verbal memory decline. They warrant further investigation in prospective studies assessing different memory subtypes.
Keywords: Humans; Memory Disorders; Netherlands; Prospective Studies; United States; Vitamin D; Vitamin D Deficiency

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

Yokukansan in the Treatment of Behavioral and Psychological Symptoms of Dementia: An Updated Meta-Analysis of Randomized Controlled Trials. - Matsunaga, Shinji; Kishi, Taro; Iwata, Nakao (J Alzheimers Dis, 2016)
BACKGROUND: Previous clinical studies found that yokukansan has a therapeutic effect on behavioral and psychological symptoms of dementia (BPSD) in dementia patients. OBJECTIVE: To perform an updated meta-analysis of randomized controlled trials (RCTs) testing yokukansan for patients with BPSD. METHODS: Primary efficacy and safety endpoints were BPSD total scores and all-cause discontinuation, respectively. Secondary outcomes were BPSD subscales, cognitive function scores [Mini-mental state examination (MMSE)], activities of daily living (ADL) scores, discontinuation due to adverse events (AEs), and incidences of AEs. RESULTS: Five RCTs with 381 patients with BPSD were included. Compared with controls [placebo+usual care (UC)], yokukansan significantly decreased BPSD total scores [standardized mean difference (SMD) = -0.32, 95% confidence interval (CI) = -0.53 to -0.11, p = 0.003, I2 = 0%, N = 5 studies, n = 361]. Yokukansan was more efficacious in reducing BPSD subscale scores (delusions: SMD = -0.51, 95% CI = -0.98 to -0.04, hallucinations: SMD = -0.54, 95% CI = -0.96 to -0.12, agitation/aggression: SMD = -0.37, 95% CI = -0.60 to -0.15) than placebo+UC. However, yokukansan was not superior to placebo+UC for BPSD total as well as any subscales scores only in Alzheimer's disease patients. Compared with UC, yokukansan treatment improved ADL scores (SMD = -0.32, 95% CI = -0.62 to -0.01). MMSE scores did not differ between the yokukansan and placebo+UC treatment groups. No significant differences were found in all-cause discontinuation, discontinuation due to AEs, and incidences of AEs between yokukansan and placebo+UC treatments. CONCLUSIONS: Our results suggest that yokukansan is beneficial for the treatment of patients with BPSD and is well-tolerated; it was not beneficial for BPSD total and any subscale scores only in Alzheimer's disease patients.

Zinc-Mediated Binding of Nucleic Acids to Amyloid-β Aggregates: Role of Histidine Residues. - Khmeleva, Svetlana A; Radko, Sergey P; Kozin, Sergey A; Kiseleva, Yana Y; Mezentsev, Yuri V; Mitkevich, Vladimir A; Kurbatov, Leonid K; Ivanov, Alexis S; Makarov, Alexander A (J Alzheimers Dis, 2016)
Amyloid-β peptide (Aβ) plays a central role in Alzheimer's disease (AD) pathogenesis. Besides extracellular Aβ, intraneuronal Aβ (iAβ) has been suggested to contribute to AD onset and development. Based on reported in vitro Aβ-DNA interactions and nuclear localization of iAβ, the interference of iAβ with the normal DNA expression has recently been proposed as a plausible pathway by which Aβ can exert neurotoxicity. Employing the sedimentation assay, thioflavin T fluorescence, and dynamic light scattering we have studied effects of zinc ions on binding of RNA and single- and double-stranded DNA molecules to Aβ42 aggregates. It has been found that zinc ions significantly enhance the binding of RNA and DNA molecules to pre-formed β-sheet rich Aβ42 aggregates. Another type of Aβ42 aggregates, the zinc-induced amorphous aggregates, was demonstrated to also bind all types of nucleic acids tested. To evaluate the role of the Aβ metal-binding domain's histidine residues in Aβ-nucleic acid interactions mediated by zinc, Aβ16 mutants with substitutions H6R and H6A-H13A and rat Aβ16 lacking histidine residue 13 were used. The zinc-induced interaction of Aβ16 with DNA was shown to critically depend on histidine residues 6 and 13. However, the inclusion of H6R mutation in Aβ42 peptide did not affect DNA binding to Aβ42 aggregates. Since oxidative and/or nitrosative stresses implicated in AD pathogenesis are known to release zinc ions from metallothioneins in cytoplasm and cell nuclei, our findings suggest that intracellular zinc can be an important player in iAβ-nucleic acid interactions.

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Acute Exposure of the Mediobasal Hypothalamus to Amyloid-β25-35 Perturbs Hepatic Glucose Metabolism. - Arrieta-Cruz, Isabel; Knight, Colette M; Gutiérrez-Juérez, Roger (J Alzheimers Dis, 2015)
Patients with Alzheimer's disease (AD) have a higher risk for developing insulin resistance and diabetes. Amyloid plaques, a hallmark of AD, are composed of amyloid-β (Aβ). Because the mediobasal hypothalamus controls hepatic glucose production, we examined the hypothesis that its exposure to Aβ perturbs the regulation of glucose metabolism. The infusion of Aβ25-35, but not its scrambled counterpart, into the mediobasal hypothalamus of young rats, increased circulating glucose as a consequence of enhanced hepatic glucose production during pancreatic clamp studies. These findings suggest a link between AD and alterations of glucose metabolism.

Adipose Tissue Distribution in Patients with Alzheimer's Disease: A Whole Body MRI Case-Control Study. - Diehl-Wiesenecker, Eva; von Armin, Christine A F; Dupuis, Luc; Müller, Hans-Peter; Ludolph, Albert C; Kassubek, Jan (J Alzheimers Dis, 2015)
BACKGROUND: Total and central adiposity have been associated with increased risk of Alzheimer's disease (AD). Visceral and subcutaneous adipose tissues have different metabolic characteristics and could therefore be differentially associated with AD. OBJECTIVE: To compare regional fat distribution determined by magnetic resonance imaging (MRI) in AD patients and healthy controls and investigate associations with stage of the disease and chemical markers. The investigation was performed in a prospective case-control study. METHODS: We examined thirty patients with mild to moderate AD by whole-body MRI (1.5 T) and clinical questionnaires in comparison to thirty cognitively healthy age- and gender-matched study participants. Volumes of total, subcutaneous, and visceral body fat tissue were determined by an unbiased automatic analysis algorithm. Levels of leptin, ghrelin, and adiponectin were determined in serum, amyloid-β (Aβ)1-42 and tau protein levels in cerebrospinal fluid (CSF). RESULTS: Male AD patients displayed significantly more total fat tissue than male controls. This difference was not observed in women. We observed a trend toward higher volume of visceral fat tissue in all patients (p = 0.13). Severity of disease was not associated with fat distribution in our study. Increased leptin levels correlated with lower CSF Aβ 1-42 in female, but not in male, AD patients. CONCLUSIONS: Fat volume is increased in male, but not in female AD patients. Negative correlation of leptin levels and CSF Aβ 1-42 in females might be one co-factor for the increased AD risk of females. Further studies are required to confirm this gender difference in fat volume during AD and evaluate its pathophysiological importance.

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

Ankle-Brachial Index but Neither Intima Media Thickness Nor Coronary Artery Calcification is Associated With Mild Cognitive Impairment. - Weimar, Christian; Winkler, Angela; Dlugaj, Martha; Lehmann, Nils; Hennig, Frauke; Bauer, Marcus; Kröger, Knut; Kälsch, Hagen; Mahabadi, Amir-Abass; Dragano, Nico; Moebus, Susanne; Hoffmann, Barbara; et al. (J Alzheimers Dis, 2015)
BACKGROUND: Several studies have reported an association of atherosclerosis with mild cognitive impairment (MCI) and dementia independent of cardiovascular risk factors. OBJECTIVE: To compare the cross-sectional association of the ankle-brachial index (ABI), intima media thickness (IMT), and coronary artery calcification (CAC) with MCI and its subtypes, amnestic MCI (aMCI) and non-amnestic MCI (naMCI) in the population-based Heinz Nixdorf Recall cohort study. METHODS: 4,086 participants performed a validated brief cognitive assessment at the first follow-up examination (2006-2008). MCI was diagnosed according to previously published criteria. Prevalence ratio (PR) regression models adjusted for age, gender, education, cardiovascular risk factors, and APOE genotype were used to compare the association of the ABI, the CAC-Agatston score and the IMT with MCI and its subtypes. RESULTS: We identified 490 participants with MCI (mean age 66.1 ± 7.8, 46.9 % male, aMCI n = 249, naMCI n = 241) and 1,242 cognitively normal participants. A decreasing ABI (per 0.1) was significantly associated with a higher MCI prevalence in fully adjusted models (PR 1.06; 95% confidence interval (CI) 1.01-1.11), whereas an increasing CAC (log(CAC+1)) or IMT (per 0.1 mm) were not associated after adjustment. A decreasing ABI was also significantly associated with naMCI in fully adjusted models (PR 1.12; CI 1.03-1.21) but not with aMCI. CONCLUSIONS: Our data show that the degree of generalized atherosclerosis as measured by the ABI is associated with MCI and with naMCI in a population-based cohort.

The APOE Gene is Differentially Methylated in Alzheimer's Disease. - Foraker, Jessica; Millard, Steven P; Leong, Lesley; Thomson, Zachary; Chen, Sunny; Keene, C Dirk; Bekris, Lynn M; Yu, Chang-En (J Alzheimers Dis, 2015)
The ɛ4 allele of the human apolipoprotein E gene (APOE) is a well-proven genetic risk factor for the late onset form of Alzheimer's disease (AD). However, the biological mechanisms through which the ɛ4 allele contributes to disease pathophysiology are incompletely understood. The three common alleles of APOE, ɛ2, ɛ3 and ɛ4, are defined by two single nucleotide polymorphisms (SNPs) that reside in the coding region of exon 4, which overlaps with a well-defined CpG island (CGI). Both SNPs change not only the protein codon but also the quantity of CpG dinucleotides, primary sites for DNA methylation. Thus, we hypothesize that the presence of an ɛ4 allele changes the DNA methylation landscape of the APOE CGI and that such epigenetic alteration contributes to AD susceptibility. To explore the relationship between APOE genotype, AD risk, and DNA methylation of the APOE CGI, we applied bisulfite pyrosequencing and evaluated methylation profiles of postmortem brain from 15 AD and 10 control subjects. We observed a tissue-specific decrease in DNA methylation with AD and identified two AD-specific differentially methylated regions (DMRs), which were also associated with APOE genotype. We further demonstrated that one DMR was completely un-methylated in a sub-population of genomes, possibly due to a subset of brain cells carrying deviated APOE methylation profiles. These data suggest that the APOE CGI is differentially methylated in AD brain in a tissue- and APOE-genotype-specific manner. Such epigenetic alteration might contribute to neural cell dysfunction in AD brain.

Blood Protein Markers of Neocortical Amyloid-β Burden: A Candidate Study Using SOMAscan Technology. - Voyle, Nicola; Baker, David; Burnham, Samantha C; Covin, Antonia; Zhang, Zhanpan; Sangurdekar, Dipen P; Tan Hehir, Cristina A; Bazenet, Chantal; Lovestone, Simon; Kiddle, Steven; Dobson, Richard J B (J Alzheimers Dis, 2015)
BACKGROUND: Four previously reported studies have tested for association of blood proteins with neocortical amyloid-β burden (NAB). If shown to be robust, these proteins could have utility as a blood test for enrichment in clinical trials of Alzheimer's disease (AD) therapeutics. OBJECTIVE: This study aimed to investigate whether previously identified blood proteins also show evidence for association with NAB in serum samples from the Australian Imaging, Biomarker and Lifestyle Flagship Study of Ageing (AIBL). The study considers candidate proteins seen in cohorts other than AIBL and candidates previously discovered in the AIBL cohort. METHODS: Our study used the SOMAscan platform for protein quantification in blood serum. Linear and logistic regressions were used to model continuous NAB and dichotomized NAB respectively using single proteins as a predictor. Multiple protein models were built using stepwise regression techniques and support vectors machines. Age and APOE ε4 carriage were used as covariates for all analysis. RESULTS: Of the 41 proteins previously reported, 15 AIBL candidates and 20 non-AIBL candidates were available for testing. Of these candidates, pancreatic polypeptide (PPY) and IgM showed a significant association with NAB. Notably, IgM was found to associate with continuous NAB across cognitively normal control subjects. CONCLUSIONS: We have further demonstrated the association of PPY and IgM with NAB, despite technical differences between studies. There are several reasons for a lack of significance for the other candidates including platform differences and the use of serum rather than plasma samples. To investigate the possibility of technical differences causing lack of further replication, further studies are required.

Body Mass Index and Mortality Rate in Korean Patients with Alzheimer's Disease. - Jang, Hyemin; Kim, Jong Hun; Choi, Seong Hye; Lee, Yunhwan; Hong, Chang Hyung; Jeong, Jee Hyang; Han, Hyun Jeong; Moon, So Young; Park, Kyung Won; Han, Seol-Hee; Park, Kee Hyung; Kim, Hee Jin; et al. (J Alzheimers Dis, 2015)
Background: A relationship between body weight, cognitive impairment, and the onset of Alzheimer's disease (AD) was recently reported. However, to our knowledge, no studies have investigated the relationship between body weight and mortality in Asian AD patients. Objective: We evaluated the relationship between body mass index (BMI) and mortality rate in Korean AD cohorts. Methods: Participants were consecutively included from two Korean representative registries: 579 AD patients from Samsung Medical Center and 1911 AD patients from the Clinical Research Center for Dementia of South Korea study. We combined these two AD cohorts to evaluate the association between BMI and mortality. BMI was used to categorize the participants into underweight, normal-weight, overweight, and obesity subgroups. All deaths were confirmed through the nationwide mortality database of Statistics Korea. Results: 53 of 181 (29.3%), 208 of 1,127 (18.5%), 88 of 626 (14.1%), and 115 of 556 (20.7%) patients died in the underweight, normal-weight, overweight, and obese subgroups during 43.7 months of follow-up. The time-dependent cox proportional hazards model showed that, relative to the normal-weight subgroup, the underweight group had higher mortality (HR 1.82 (95% CI, 1.07-3.09)) while overweight group had lower mortality rate (HR 0.60 (95% CI, 0.38-0.95)) The effects of underweight and overweight were prominent in younger and older elderly group, respectively. However, there were no interactive effects of dementia severity or gender and BMI on survival rate. Conclusion: Relative to AD patients of normal weight, those who were underweight had an increased mortality rate, and overweight predicted decreased mortality in AD patients. Furthermore, our findings may help facilitate mortality stratification in AD patients by using baseline BMI.

Clinical Benefits for Older Alzheimer's Disease Patients: Okayama Late Dementia Study (OLDS). - Matsuzono, Kosuke; Yamashita, Toru; Ohta, Yasuyuki; Hishikawa, Nozomi; Sato, Kota; Kono, Syoichiro; Deguchi, Kentaro; Nakano, Yumiko; Abe, Koji (J Alzheimers Dis, 2015)
BACKGROUND/OBJECTIVE: There are few reports on the effects of anti-Alzheimer's disease (AD) drugs on older AD patients, and possible differences based on gender in a real world setting. METHODS: "Okayama Late Dementia Study (OLDS)" is a retrospective clinical cohort study focusing on older AD patients (n = 373; age≥75 years) treated with monotherapy donepezil (n = 55), galantamine (n = 222), rivastigmine (n = 63), or memantine (n = 33). The patients were evaluated as an entire group and separated by gender, using seven batteries for dementia assessment at baseline and at 3, 6, and 12 months of drug therapy. RESULTS: All four drugs preserved cognitive and affective functions until 12 months, except for Frontal Assessment Battery (FAB) with memantine ( *p <  0.05 versus baseline). Donepezil monotherapy significantly improved Hasegawa Dementia Rating Scale-Revised (HDS-R) at 3 months ( *p <  0.05), and memantine (3 and 6 months,  *p <  0.05) and rivastigmine (3 months,  **p <  0.01) improved Abe's Behavior and Psychological Symptom of Dementia Score (ABS), respectively. Activities of daily living (ADL) became significantly worse with galantamine at 12 months ( *p <  0.05). Male Mini-Mental State Examination scores became worse at 12 months with donepezil ( *p <  0.05), as did female Geriatric Depression Scale scores at 6 months ( *p <  0.05). Male HDS-R and ABS scores were preserved in the galantamine group until 12 months. Female ABS scores with memantine improved at 6 months ( *p <  0.05), while male ADL scores became worse with rivastigmine at 12 months ( *p <  0.05). CONCLUSION: OLDS revealed that anti-AD drugs were effective even for older AD patients, and the clinical benefits of each drug showed a small difference with regard to gender.

Cognitive Function and Its Relationship with Macular Pigment Optical Density and Serum Concentrations of its Constituent Carotenoids. - Kelly, David; Coen, Robert F; Akuffo, Kwadwo Owusu; Beatty, Stephen; Dennison, Jessica; Moran, Rachel; Stack, Jim; Howard, Alan N; Mulcahy, Riona; Nolan, John M (J Alzheimers Dis, 2015)
BACKGROUND: Macular pigment (MP) levels correlate with brain concentrations of lutein (L) and zeaxanthin (Z), and have also been shown to correlate with cognitive performance in the young and elderly. OBJECTIVE: To investigate the relationship between MP, serum concentrations of L and Z, and cognitive function in subjects free of retinal disease with low MP (Group 1, n = 105) and in subjects with AMD (Group 2, n = 121). METHODS: MP was measured using customized heterochromatic flicker photometry and dual-wavelength autofluorescence; cognitive function was assessed using a battery of validated cognition tests; serum L and Z concentrations were determined by HPLC. RESULTS: Significant correlations were evident between MP and various measures of cognitive function in both groups (r = -0.273 to 0.261, p≤0.05, for all). Both serum L and Z concentrations correlated significantly (r = 0.187, p≤0.05 and r = 0.197, p≤0.05, respectively) with semantic (animal) fluency cognitive scores in Group 2 (the AMD study group), while serum L concentrations also correlated significantly with Verbal Recognition Memory learning slope scores in the AMD study group (r = 0.200, p = 0.031). Most of the correlations with MP, but not serum L or Z, remained significant after controlling for age, gender, diet, and education level. CONCLUSION: MP offers potential as a non-invasive clinical biomarker of cognitive health, and appears more successful in this role than serum concentrations of L or Z.

Comprehensive Gene- and Pathway-Based Analysis of Depressive Symptoms in Older Adults. - Nho, Kwangsik; Ramanan, Vijay K; Horgusluoglu, Emrin; Kim, Sungeun; Inlow, Mark H; Risacher, Shannon L; McDonald, Brenna C; Farlow, Martin R; Foroud, Tatiana M; Gao, Sujuan; Callahan, Christopher M; Hendrie, Hugh C; et al. (J Alzheimers Dis, 2015)
Depressive symptoms are common in older adults and are particularly prevalent in those with or at elevated risk for dementia. Although the heritability of depression is estimated to be substantial, single nucleotide polymorphism-based genome-wide association studies of depressive symptoms have had limited success. In this study, we PERFORMED genome-wide gene- and pathway-based analyses of depressive symptom burden. Study participants included non-Hispanic Caucasian subjects (n = 6,884) from three independent cohorts, the Alzheimer's Disease Neuroimaging Initiative (ADNI), the Health and Retirement Study (HRS), and the Indiana Memory and Aging Study (IMAS). Gene-based meta-analysis identified genome-wide significant associations (ANGPT4 and FAM110A, q-value = 0.026; GRM7-AS3 and LRFN5, q-value = 0.042). Pathway analysis revealed enrichment of association in 105 pathways, including multiple pathways related to ERK/MAPK signaling, GSK3 signaling in bipolar disorder, cell development, and immune activation and inflammation. GRM7, ANGPT4, and LRFN5 have been previously implicated in psychiatric disorders, including the GRM7 region displaying association with major depressive disorder. The ERK/MAPK signaling pathway is a known target of antidepressant drugs and has important roles in neuronal plasticity, and GSK3 signaling has been previously implicated in Alzheimer's disease and as a promising therapeutic target for depression. Our results warrant further investigation in independent and larger cohorts and add to the growing understanding of the genetics and pathobiology of depressive symptoms in aging and neurodegenerative disorders. In particular, the genes and pathways demonstrating association with depressive symptoms may be potential therapeutic targets for these symptoms in older adults.

Cortical Transcriptional Profiles in APOE4 Carriers with Alzheimer's Disease: Patterns of Protection and Degeneration. - Conejero-Goldberg, Concepcion; Hyde, Thomas M; Chen, Shufen; Herman, Mary M; Kleinman, Joel E; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2015)
Transcriptional profiling of postmortem Alzheimer's disease (AD) brain tissue has yielded important insights into disease. We recently described a novel approach to understand transcriptional changes in AD designed to identify both neurosusceptibility and intrinsic neuroprotective factors in young non-AD E4 carriers. Here we extend our work to APOE4-related AD itself. In temporal cortex (BA 21), a region known to be vulnerable to AD pathology, we identified over 1,400 transcripts that differed between APOE4 controls and APOE4 carriers diagnosed with AD. Results from somatosensory cortex (BA 1/2/3), a region relatively preserved in AD differed strikingly from temporal cortex in that differences were far fewer (37 versus 1,492). We also conducted another set of contrasts involving APOE3 AD cases and APOE4 AD cases to better understand what transcriptional differences were dependent on genotype, but independent of disease status. When analyzing interregional differences, ten pathways differed between both brain areas in the APOE4 AD cases to APOE4 controls contrast and two pathways differed between both brain areas in the APOE4 cases to APOE3 controls contrast. Base excision repair pathway was found in common for both contrasts. In summary, our results indicate that many of the molecular changes identified in the brains of patients with AD reflect the non-specific consequences of neurodegeneration, rather than causative processes. Additionally, the molecular signatures specific to somatosensory cortex may make it uniquely resistant to AD pathology and thereby could provide important leads for treatment.

Depression and Suicidal Ideation During Two Psychosocial Treatments in Older Adults with Major Depression and Dementia. - Kiosses, Dimitris N; Rosenberg, Paul B; McGovern, Amanda; Fonzetti, Pasquale; Zaydens, Hana; Alexopoulos, George S (J Alzheimers Dis, 2015)
BACKGROUND: Depression is prevalent in dementia and contributes to poor outcomes for patients and their families. Antidepressants have limited efficacy in older adults with major depression and dementia, and psychosocial interventions are under-investigated. OBJECTIVE: To examine the course, predictors and moderators of depression and suicidal ideation during 12 weeks of home-delivered Problem Adaptation Therapy (PATH) versus Supportive Therapy for Cognitively Impaired Older Adults (ST-CI) in 39 older adults with major depression and dementia. METHODS: Thirty-nine older adults with major depression, mild or moderate dementia, and disability participated in a randomized controlled trial that compared the efficacy of PATH versus ST-CI. Depression and suicidal ideation were assessed with Cornell Scale for Depression in Dementia Total Score and Suicide Item. RESULTS: PATH participants had significantly greater reduction in depression than ST-CI participants over 12 weeks of treatment. PATH participants with high social support had the greatest reduction in depression. Both treatments had comparable reduction in suicidal ideation. CONCLUSION: PATH is more effective in reducing depression in older adults with major depression and dementia compared to ST-CI. These results are clinically significant as antidepressants have limited efficacy in this population. Home-delivered psychosocial treatments may reduce suicidal ideation in this population.

Diabetes is Associated with Worse Executive Function in Both Eastern and Western Populations: Shanghai Aging Study and Mayo Clinic Study of Aging. - Zhao, Qianhua; Roberts, Rosebud O; Ding, Ding; Cha, Ruth; Guo, Qihao; Meng, Haijiao; Luo, Jianfeng; Machulda, Mary M; Shane Pankratz, V; Wang, Bei; Christianson, Teresa J H; Aakre, Jeremiah A; et al. (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVES: It remains unknown whether the association between diabetes mellitus (DM) and cognitive function differs in Eastern and Western populations. This study aimed to elucidate whether DM is associated with worse cognitive performance in both populations. METHODS: The Shanghai Aging Study (SAS) and the Mayo Clinic Study of Aging (MCSA) are two population-based studies with similar design and methodology in Shanghai, China and Rochester, MN, USA. Non-demented participants underwent cognitive testing, and DM was assessed from the medical record. Separate analyses were performed in SAS and MCSA regarding the association between DM and cognitive performance. RESULTS: A total of 3,348 Chinese participants in the SAS and 3,734 American subjects in the MCSA were included. Compared with MCSA subjects, SAS participants were younger, less educated, and had lower frequency of vascular disease, APOE ɛ4 carriers and obesity. Participants with DM (compared to non-DM participants) performed significantly worse on all the cognitive domains in both the SAS and MCSA. After adjustment for age, gender, education, and vascular covariates, DM was associated with worse performance in executive function (β=-0.15, p = 0.001 for SAS, and β=-0.10, p = 0.008 for MCSA) in the total sample and in the cognitively normal sub-sample. Furthermore, DM was associated with poor performance in visuospatial skills, language, and memory in the SAS, but not in the MCSA. CONCLUSIONS: Diabetes is associated with cognitive dysfunction and, in particular, exerts a negative impact on executive function regardless of race, age, and prevalence of vascular risk factors.

The GLP-1 Receptor Agonist Liraglutide Improves Memory Function and Increases Hippocampal CA1 Neuronal Numbers in a Senescence-Accelerated Mouse Model of Alzheimer's Disease. - Hansen, Henrik H; Fabricius, Katrine; Barkholt, Pernille; Niehoff, Michael L; Morley, John E; Jelsing, Jacob; Pyke, Charles; Bjerre Knudsen, Lotte; Farr, Susan A; Vrang, Niels (J Alzheimers Dis, 2015)
Recent studies indicate that glucagon-like peptide 1 (GLP-1) receptor agonists, currently used in the management of type 2 diabetes, exhibit neurotrophic and neuroprotective effects in amyloid-β (Aβ) toxicity models of Alzheimer's disease (AD). We investigated the potential pro-cognitive and neuroprotective effects of the once-daily GLP-1 receptor agonist liraglutide in senescence-accelerated mouse prone 8 (SAMP8) mice, a model of age-related sporadic AD not dominated by Aβ plaques. Six-month-old SAMP8 mice received liraglutide (100 or 500 μg/kg/day, s.c.) or vehicle once daily for 4 months. Vehicle-dosed age-matched 50% back-crossed as well as untreated young (4-month-old) SAMP8 mice were used as control groups for normal memory function. Vehicle-dosed 10-month-old SAMP8 mice showed significant learning and memory retention deficits in an active-avoidance T-maze, as compared to both control groups. Also, 10-month-old SAMP8 mice displayed no immunohistological signatures of Aβ plaques or hyperphosphorylated tau, indicating the onset of cognitive deficits prior to deposition of amyloid plaques and neurofibrillary tangles in this AD model. Liraglutide significantly increased memory retention and total hippocampal CA1 pyramidal neuron numbers in SAMP8 mice, as compared to age-matched vehicle-dosed SAMP8 mice. In conclusion, liraglutide delayed or partially halted the progressive decline in memory function associated with hippocampal neuronal loss in a mouse model of pathological aging with characteristics of neurobehavioral and neuropathological impairments observed in early-stage sporadic AD.

Human ApoE Isoforms Differentially Modulate Glucose and Amyloid Metabolic Pathways in Female Brain: Evidence of the Mechanism of Neuroprotection by ApoE2 and Implications for Alzheimer's Disease Prevention and Early Intervention. - Keeney, Jeriel Thomas-Richard; Ibrahimi, Shaher; Zhao, Liqin (J Alzheimers Dis, 2015)
Three major genetic isoforms of apolipoprotein E (ApoE), ApoE2, ApoE3, and ApoE4, exist in humans and lead to differences in susceptibility to Alzheimer's disease (AD). This study investigated the impact of human ApoE isoforms on brain metabolic pathways involved in glucose utilization and amyloid-β (Aβ) degradation, two major areas that are significantly perturbed in preclinical AD. Hippocampal RNA samples from middle-aged female mice with targeted human ApoE2, ApoE3, and ApoE4 gene replacement were comparatively analyzed with a qRT-PCR custom array for the expression of 85 genes involved in insulin/insulin-like growth factor (Igf) signaling. Consistent with its protective role against AD, ApoE2 brain exhibited the most metabolically robust profile among the three ApoE genotypes. When compared to ApoE2 brain, both ApoE3 and ApoE4 brains exhibited markedly reduced levels of Igf1, insulin receptor substrates (Irs), and facilitated glucose transporter 4 (Glut4), indicating reduced glucose uptake. Additionally, ApoE4 brain exhibited significantly decreased Pparg and insulin-degrading enzyme (Ide), indicating further compromised glucose metabolism and Aβ dysregulation associated with ApoE4. Protein analysis showed significantly decreased Igf1, Irs, and Glut4 in ApoE3 brain, and Igf1, Irs, Glut4, Pparg, and Ide in ApoE4 brain compared to ApoE2 brain. These data provide the first documented evidence that human ApoE isoforms differentially affect brain insulin/Igf signaling and downstream glucose and amyloid metabolic pathways, illustrating a potential mechanism for their differential risk in AD. A therapeutic strategy that enhances brain insulin/Igf1 signaling activity to a more robust ApoE2-like phenotype favoring both energy production and amyloid homeostasis holds promise for AD prevention and early intervention.

Long-Term Interrelationship between Brain Metabolism and Amyloid Deposition in Mild Cognitive Impairment. - Kemppainen, Nina; Joutsa, Juho; Johansson, Jarkko; Scheinin, Noora M; Någren, Kjell; Rokka, Johanna; Parkkola, Riitta; Rinne, Juha O (J Alzheimers Dis, 2015)
The aim of this longitudinal positron emission tomography (PET) study was to evaluate the interrelationship between brain metabolism and amyloid accumulation during the disease process from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Nine MCI patients, who converted to AD between two and five years, and nine healthy subjects underwent [11C]PIB and [18F]FDG PET scans at baseline and at 5 years. [11C]PIB uptake was clearly higher in MCI patients at baseline compared to controls and spread extensively to the cerebral cortex during the conversion to AD. [18F]FDG uptake was reduced especially in the temporal-parietal regions in MCI compared to controls at baseline, and widely over the cortex at the 5-year follow-up. The reduction in metabolism during the follow-up was significant in the posterior brain regions. In addition, brain amyloid load was positively associated with metabolism in posterior brain regions in MCI, but not after conversion to AD. The results suggest that there are interactions between brain amyloid accumulation and metabolism during the AD process, including a possible compensatory upregulation of posterior brain metabolism in the early phase.

Reduced Benefit of Memory Elaboration in Older Adults with Subjective Memory Decline. - Pike, Kerryn E; Zeneli, Amina; Ong, Ben; Price, Sarah; Kinsella, Glynda J (J Alzheimers Dis, 2015)
BACKGROUND: Cognitive interventions for neurodegenerative diseases, such as Alzheimer's disease (AD), are best targeted at the preclinical stages, and subjective memory decline (SMD) without objective memory impairment on standard tests in older adults may represent a very early preclinical stage. Elaborated encoding effectively enhances memory performance for healthy older adults (HOAs), but has not been examined in people with SMD. OBJECTIVE: To examine elaborated encoding in people with SMD, compared with HOAs. METHODS: Participants were 32 HOAs and 22 people with SMD, defined using the Memory Complaint Questionnaire. Participants completed a verbal paired associate learning (PAL) task with delayed recall under elaborated and non-elaborated encoding conditions, as well as the California Verbal Learning Test-II. RESULTS: On the PAL learning trials, with age controlled, a significant interaction of group X encoding condition emerged, F(1, 51) =  6.47, MSE = 6.54, p = 0.014, ηp2 = 0.11. Simple main effects revealed no differences between groups in the non-elaborated condition, but in the elaborated condition HOAs recalled more pairs than SMD, although both groups benefited from elaboration. At delayed recall, HOA recalled more pairs than SMD, F(1, 51) =  4.59, p = 0.037, ηp2 = 0.08, and both groups benefited from elaboration, F(1, 52) =  19.25, p <  0.001, ηp2 = 0.27. CONCLUSION: People with SMD benefit from elaborated encoding, although not to the same extent as HOAs. This objective difference in complex learning and memory suggests neural changes in SMD that may represent preclinical AD. Elaborated encoding is a promising technique to help maintain memory and decrease anxiety in this at-risk population.

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

TREM2 variants in Alzheimer's disease. - Guerreiro, Rita; Wojtas, Aleksandra; Bras, Jose; Carrasquillo, Minerva; Rogaeva, Ekaterina; Majounie, Elisa; Cruchaga, Carlos; Sassi, Celeste; Kauwe, John S K; Younkin, Steven; Hazrati, Lilinaz; Collinge, John; et al. (N Engl J Med, 2013)
BACKGROUND: Homozygous loss-of-function mutations in TREM2, encoding the triggering receptor expressed on myeloid cells 2 protein, have previously been associated with an autosomal recessive form of early-onset dementia. METHODS: We used genome, exome, and Sanger sequencing to analyze the genetic variability in TREM2 in a series of 1092 patients with Alzheimer's disease and 1107 controls (the discovery set). We then performed a meta-analysis on imputed data for the TREM2 variant rs75932628 (predicted to cause a R47H substitution) from three genomewide association studies of Alzheimer's disease and tested for the association of the variant with disease. We genotyped the R47H variant in an additional 1887 cases and 4061 controls. We then assayed the expression of TREM2 across different regions of the human brain and identified genes that are differentially expressed in a mouse model of Alzheimer's disease and in control mice. RESULTS: We found significantly more variants in exon 2 of TREM2 in patients with Alzheimer's disease than in controls in the discovery set (P=0.02). There were 22 variant alleles in 1092 patients with Alzheimer's disease and 5 variant alleles in 1107 controls (P<0.001). The most commonly associated variant, rs75932628 (encoding R47H), showed highly significant association with Alzheimer's disease (P<0.001). Meta-analysis of rs75932628 genotypes imputed from genomewide association studies confirmed this association (P=0.002), as did direct genotyping of an additional series of 1887 patients with Alzheimer's disease and 4061 controls (P<0.001). Trem2 expression differed between control mice and a mouse model of Alzheimer's disease. CONCLUSIONS: Heterozygous rare variants in TREM2 are associated with a significant increase in the risk of Alzheimer's disease. (Funded by Alzheimer's Research UK and others.).
Keywords: Aged; Alzheimer Disease; Animals; Brain; Exome; Genetic Variation; Genome-Wide Association Study; Genotype; Genotyping Techniques; Heterozygote; Humans; Membrane Glycoproteins; Mice; Mice, Inbred A; Mutation; Receptors, Immunologic; Risk Factors; RNA, Messenger; Sequence Analysis, DNA

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

Predicting regional neurodegeneration from the healthy brain functional connectome. - Zhou, Juan; Gennatas, Efstathios D; Kramer, Joel H; Miller, Bruce L; Seeley, William W (Neuron, 2012)
Neurodegenerative diseases target large-scale neural networks. Four competing mechanistic hypotheses have been proposed to explain network-based disease patterning: nodal stress, transneuronal spread, trophic failure, and shared vulnerability. Here, we used task-free fMRI to derive the healthy intrinsic connectivity patterns seeded by brain regions vulnerable to any of five distinct neurodegenerative diseases. These data enabled us to investigate how intrinsic connectivity in health predicts region-by-region vulnerability to disease. For each illness, specific regions emerged as critical network "epicenters" whose normal connectivity profiles most resembled the disease-associated atrophy pattern. Graph theoretical analyses in healthy subjects revealed that regions with higher total connectional flow and, more consistently, shorter functional paths to the epicenters, showed greater disease-related vulnerability. These findings best fit a transneuronal spread model of network-based vulnerability. Molecular pathological approaches may help clarify what makes each epicenter vulnerable to its targeting disease and how toxic protein species travel between networked brain structures.
Keywords: Aged; Atrophy; Brain; Brain Mapping; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neural Pathways; Neurodegenerative Diseases; Oxygen; Reference Values

Propagation of tau pathology in a model of early Alzheimer's disease. - de Calignon, Alix; Polydoro, Manuela; Suárez-Calvet, Marc; William, Christopher; Adamowicz, David H; Kopeikina, Kathy J; Pitstick, Rose; Sahara, Naruhiko; Ashe, Karen H; Carlson, George A; Spires-Jones, Tara L; Hyman, Bradley T (Neuron, 2012)
Neurofibrillary tangles advance from layer II of the entorhinal cortex (EC-II) toward limbic and association cortices as Alzheimer's disease evolves. However, the mechanism involved in this hierarchical pattern of disease progression is unknown. We describe a transgenic mouse model in which overexpression of human tau P301L is restricted to EC-II. Tau pathology progresses from EC transgene-expressing neurons to neurons without detectable transgene expression, first to EC neighboring cells, followed by propagation to neurons downstream in the synaptic circuit such as the dentate gyrus, CA fields of the hippocampus, and cingulate cortex. Human tau protein spreads to these regions and coaggregates with endogenous mouse tau. With age, synaptic degeneration occurs in the entorhinal target zone and EC neurons are lost. These data suggest that a sequence of progressive misfolding of tau proteins, circuit-based transfer to new cell populations, and deafferentation induced degeneration are part of a process of tau-induced neurodegeneration.
Keywords: Age Factors; Alzheimer Disease; Animals; Disease Models, Animal; Disease Progression; Entorhinal Cortex; Epitopes; Gene Expression Regulation; Glial Fibrillary Acidic Protein; Gliosis; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Degeneration; Neurofibrillary Tangles; Neurons; RNA, Messenger; Serine; tau Proteins; Tauopathies

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

18F-THK523: a novel in vivo tau imaging ligand for Alzheimer's disease. - Fodero-Tavoletti, Michelle T; Okamura, Nobuyuki; Furumoto, Shozo; Mulligan, Rachel S; Connor, Andrea R; McLean, Catriona A; Cao, Diana; Rigopoulos, Angela; Cartwright, Glenn A; O'Keefe, Graeme; Gong, Sylvia; Adlard, Paul A; et al. (Brain, 2011)
While considerable effort has focused on developing positron emission tomography β-amyloid imaging radiotracers for the early diagnosis of Alzheimer's disease, no radiotracer is available for the non-invasive quantification of tau. In this study, we detail the characterization of (18)F-THK523 as a novel tau imaging radiotracer. In vitro binding studies demonstrated that (18)F-THK523 binds with higher affinity to a greater number of binding sites on recombinant tau (K18Δ280K) compared with β-amyloid(1-42) fibrils. Autoradiographic and histofluorescence analysis of human hippocampal serial sections with Alzheimer's disease exhibited positive THK523 binding that co-localized with immunoreactive tau pathology, but failed to highlight β-amyloid plaques. Micro-positron emission tomography analysis demonstrated significantly higher retention of (18)F-THK523 (48%; P < 0.007) in tau transgenic mice brains compared with their wild-type littermates or APP/PS1 mice. The preclinical examination of THK523 has demonstrated its high affinity and selectivity for tau pathology both in vitro and in vivo, indicating that (18)F-THK523 fulfils ligand criteria for human imaging trials.
Keywords: Alzheimer Disease; Analysis of Variance; Aniline Compounds; Animals; Autoradiography; Binding Sites; Brain; Female; Fluorodeoxyglucose F18; Humans; Immunohistochemistry; Male; Mice; Quinolines; Radiopharmaceuticals; tau Proteins

Anti-aβ therapeutics in Alzheimer's disease: the need for a paradigm shift. - Golde, Todd E; Schneider, Lon S; Koo, Edward H (Neuron, 2011)
Most current Alzheimer's disease (AD) therapies in advanced phases of development target amyloid β-peptide (Aβ) production, aggregation, or accumulation. Translational models suggest that anti-Aβ therapies may be highly effective if tested as agents to prevent or delay development of the disease or as therapies for asymptomatic patients with very early signs of AD pathology. However, anti-Aβ therapeutics are currently being tested in symptomatic patients where they are likely to be much less effective or ineffective. The lack of alignment between human clinical studies and preclinical studies, together with predictions about optimal trial design based on our understanding of the initiating role of Aβ aggregates in AD, has created a treatment versus prevention dilemma. In this perspective, we discuss why it is imperative to resolve this dilemma and suggest ways for moving forward in the hopes of enhancing the development of truly effective AD therapeutics.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Clinical Trials as Topic; Disease Progression; Health Services Needs and Demand; Humans; Translational Medical Research

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Disrupted energy metabolism and neuronal circuit dysfunction in cognitive impairment and Alzheimer's disease. - Kapogiannis, Dimitrios; Mattson, Mark P (Lancet Neurol, 2011)
Epidemiological, neuropathological, and functional neuroimaging evidence implicates global and regional disruptions in brain metabolism and energetics in the pathogenesis of cognitive impairment. Nerve cell microcircuits are modified by excitatory and inhibitory synaptic activity and neurotrophic factors. Ageing and Alzheimer's disease cause perturbations in cellular energy metabolism, level of excitation or inhibition, and neurotrophic factor release, which overwhelm compensatory mechanisms and result in dysfunction of neuronal microcircuits and brain networks. A prolonged positive energy balance impairs the ability of neurons to adapt to oxidative and metabolic stress. Results from experimental studies in animals show how disruptions caused by chronic positive energy balance, such as diabetes, lead to accelerated cognitive ageing and Alzheimer's disease. Therapeutic interventions to allay cognitive dysfunction that target energy metabolism and adaptive stress responses (such as neurotrophin signalling) have been effective in animal models and in preliminary studies in humans.
Keywords: Alzheimer Disease; Animals; Brain; Cognition Disorders; Energy Metabolism; Humans; Nerve Net

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Exercise training increases size of hippocampus and improves memory. - Erickson, Kirk I; Voss, Michelle W; Prakash, Ruchika Shaurya; Basak, Chandramallika; Szabo, Amanda; Chaddock, Laura; Kim, Jennifer S; Heo, Susie; Alves, Heloisa; White, Siobhan M; Wojcicki, Thomas R; Mailey, Emily; et al. (Proc Natl Acad Sci U S A, 2011)
The hippocampus shrinks in late adulthood, leading to impaired memory and increased risk for dementia. Hippocampal and medial temporal lobe volumes are larger in higher-fit adults, and physical activity training increases hippocampal perfusion, but the extent to which aerobic exercise training can modify hippocampal volume in late adulthood remains unknown. Here we show, in a randomized controlled trial with 120 older adults, that aerobic exercise training increases the size of the anterior hippocampus, leading to improvements in spatial memory. Exercise training increased hippocampal volume by 2%, effectively reversing age-related loss in volume by 1 to 2 y. We also demonstrate that increased hippocampal volume is associated with greater serum levels of BDNF, a mediator of neurogenesis in the dentate gyrus. Hippocampal volume declined in the control group, but higher preintervention fitness partially attenuated the decline, suggesting that fitness protects against volume loss. Caudate nucleus and thalamus volumes were unaffected by the intervention. These theoretically important findings indicate that aerobic exercise training is effective at reversing hippocampal volume loss in late adulthood, which is accompanied by improved memory function.
Keywords: Aged; Aging; Brain-Derived Neurotrophic Factor; Enzyme-Linked Immunosorbent Assay; Exercise; Hippocampus; Humans; Magnetic Resonance Imaging; Memory; Middle Aged; Organ Size; Space Perception

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide